Implementing genomic screening in diverse populations - Abul-Husn, N.S.; Soper, E.R.; Braganza, G.T.; Rodriguez, J.E.; Zeid, N.; Cullina, S.; Bobo, D.; Moscati, A.; Merkelson, A.; Loos, R.J.F.; Cho, J.H.; Belbin, G.M.; et al. (Genome Medicine, 2021)
Background: Population-based genomic screening has the predicted ability to reduce morbidity and mortality associated with medically actionable conditions. However, much research is needed to develop standards for genomic screening and to understand the perspectives of people offered this new testing modality. This is particularly true for non-European ancestry populations who are vastly underrepresented in genomic medicine research. Therefore, we implemented a pilot genomic screening program in the BioMe Biobank in New York City, where the majority of participants are of non-European ancestry. Methods: We initiated genomic screening for well-established genes associated with hereditary breast and ovarian cancer syndrome (HBOC), Lynch syndrome (LS), and familial hypercholesterolemia (FH). We evaluated and included an additional gene (TTR) associated with hereditary transthyretin amyloidosis (hATTR), which has a common founder variant in African ancestry populations. We evaluated the characteristics of 74 participants who received results associated with these conditions. We also assessed the preferences of 7461 newly enrolled BioMe participants to receive genomic results. Results: In the pilot genomic screening program, 74 consented participants received results related to HBOC (N = 26), LS (N = 6), FH (N = 8), and hATTR (N = 34). Thirty-three of 34 (97.1%) participants who received a result related to hATTR were self-reported African American/African (AA) or Hispanic/Latinx (HL), compared to 14 of 40 (35.0%) participants who received a result related to HBOC, LS, or FH. Among the 7461 participants enrolled after the BioMe protocol modification to allow the return of genomic results, 93.4% indicated that they would want to receive results. Younger participants, women, and HL participants were more likely to opt to receive results. Conclusions: The addition of TTR to a pilot genomic screening program meant that we returned results to a higher proportion of AA and HL participants, in comparison with genes traditionally included in genomic screening programs in the USA. We found that the majority of participants in a multi-ethnic biobank are interested in receiving genomic results for medically actionable conditions. These findings increase knowledge about the perspectives of diverse research participants on receiving genomic results and inform the broader implementation of genomic medicine in underrepresented patient populations.
Keywords: adult; African; African American; age; aged; ancestry group; article; ATTR amyloidosis; biobank; familial hypercholesterolemia; female; gene; genetic association; genetic screening; genetic variability; hereditary breast and ovarian cancer syndrome; hereditary nonpolyposis colorectal cancer; Hispanic; human; major clinical study; male; patient preference; pilot study; priority journal; self report; TTR gene

Randomized trial of community health worker-led decision coaching to promote shared decision-making for prostate cancer screening among Black male patients and their providers - Makarov, D.V.; Feuer, Z.; Ciprut, S.; Lopez, N.M.; Fagerlin, A.; Shedlin, M.; Gold, H.T.; Li, H.; Lynch, G.; Warren, R.; Ubel, P.; Ravenell, J.E. (Trials, 2021)
Background: Black men are disproportionately affected by prostate cancer, the most common non-cutaneous malignancy among men in the USA. The United States Preventive Services Task Force (USPSTF) encourages prostate-specific antigen (PSA) testing decisions to be based on shared decision-making (SDM) clinician professional judgment, and patient preferences. However, evidence suggests that SDM is underutilized in clinical practice, especially among the most vulnerable patients. The purpose of this study is to evaluate the efficacy of a community health worker (CHW)-led decision-coaching program to facilitate SDM for prostate cancer screening among Black men in the primary care setting, with the ultimate aim of improving/optimizing decision quality. Methods: We proposed a CHW-led decision-coaching program to facilitate SDM for prostate cancer screening discussions in Black men at a primary care FQHC. This study enrolled Black men who were patients at the participating clinical site and up to 15 providers who cared for them. We estimated to recruit 228 participants, ages 40–69 to be randomized to either (1) a decision aid along with decision coaching on PSA screening from a CHW or (2) receiving a decision aid along with CHW-led interaction on modifying dietary and lifestyle to serve as an attention control. The independent randomization process was implemented within each provider and we controlled for age by dividing patients into two strata: 40–54 years and 55–69 years. This sample size sufficiently powered the detection differences in the primary study outcomes: knowledge, indicative of decision quality, and differences in PSA screening rates. Primary outcome measures for patients will be decision quality and decision regarding whether to undergo PSA screening. Primary outcome measures for providers will be acceptability and feasibility of the intervention. We will examine how decision coaching about prostate cancer screening impact patient-provider communication. These outcomes will be analyzed quantitatively through objective, validated scales and qualitatively through semi-structured, in-depth interviews, and thematic analysis of clinical encounters. Through a conceptual model combining elements of the Preventative Health Care Model (PHM) and Informed Decision-Making Model, we hypothesize that the prostate cancer screening decision coaching intervention will result in a preference-congruent decision and decisional satisfaction. We also hypothesize that this intervention will improve physician satisfaction with counseling patients about prostate cancer screening. Discussion: Decision coaching is an evidence-based approach to improve decision quality in many clinical contexts, but its efficacy is incompletely explored for PSA screening among Black men in primary care. Our proposal to evaluate a CHW-led decision-coaching program for PSA screening has high potential for scalability and public health impact. Our results will determine the efficacy, cost-effectiveness, and sustainability of a CHW intervention in a community clinic setting in order to inform subsequent widespread dissemination, a critical research area highlighted by USPSTF. Trial registration: The trial was registered prospectively with the National Institute of Health registry (www.clinicaltrials.gov), registration number NCT03726320, on October 31, 2018.
Keywords: adult; aged; article; attention; cancer screening; comparative effectiveness; conceptual model; controlled study; cost effectiveness analysis; counseling; diet; feasibility study; health auxiliary; human; interview; lifestyle; major clinical study; male; national health organization; preventive health service; primary medical care; prostate cancer; quantitative analysis; randomization; randomized controlled trial; sample size; satisfaction; shared decision making; thematic analysis; prostate specific antigen

An open-label, pilot study of veliparib and lapatinib in patients with metastatic, triple-negative breast cancer - Stringer-Reasor, E.M.; May, J.E.; Olariu, E.; Caterinicchia, V.; Li, Y.; Chen, D.; Della Manna, D.L.; Rocque, G.B.; Vaklavas, C.; Falkson, C.I.; Nabell, L.M.; Acosta, E.P.; et al. (Breast Cancer Research, 2021)
Background: Poly (ADP-ribose)-polymerase inhibitors (PARPi) have been approved for cancer patients with germline BRCA1/2 (gBRCA1/2) mutations, and efforts to expand the utility of PARPi beyond BRCA1/2 are ongoing. In preclinical models of triple-negative breast cancer (TNBC) with intact DNA repair, we have previously shown an induced synthetic lethality with combined EGFR inhibition and PARPi. Here, we report the safety and clinical activity of lapatinib and veliparib in patients with metastatic TNBC. Methods: A first-in-human, pilot study of lapatinib and veliparib was conducted in metastatic TNBC (NCT02158507). The primary endpoint was safety and tolerability. Secondary endpoints were objective response rates and pharmacokinetic evaluation. Gene expression analysis of pre-treatment tumor biopsies was performed. Key eligibility included TNBC patients with measurable disease and prior anthracycline-based and taxane chemotherapy. Patients with gBRCA1/2 mutations were excluded. Results: Twenty patients were enrolled, of which 17 were evaluable for response. The median number of prior therapies in the metastatic setting was 1 (range 0–2). Fifty percent of patients were Caucasian, 45% African–American, and 5% Hispanic. Of evaluable patients, 4 demonstrated a partial response and 2 had stable disease. There were no dose-limiting toxicities. Most AEs were limited to grade 1 or 2 and no drug–drug interactions noted. Exploratory gene expression analysis suggested baseline DNA repair pathway score was lower and baseline immunogenicity was higher in the responders compared to non-responders. Conclusions: Lapatinib plus veliparib therapy has a manageable safety profile and promising antitumor activity in advanced TNBC. Further investigation of dual therapy with EGFR inhibition and PARP inhibition is needed. Trial registration: ClinicalTrials.gov, NCT02158507. Registered on 12 September 2014
Keywords: adult; advanced cancer; African American; antineoplastic activity; article; cancer patient; Caucasian; chemotherapy; clinical article; clinical trial; controlled study; DNA repair; drug combination; drug safety; drug therapy; eligibility; exploratory research; female; gene mutation; germ line; Hispanic; human; immunogenicity; lethality; molecularly targeted therapy; pharmacokinetics; pilot study; signal transduction; triple negative breast cancer; tumor biopsy; anthracycline; BRCA1 protein; endogenous compound; epidermal growth factor receptor; lapatinib; nicotinamide adenine dinucleotide adenosine diphosphate ribosyltransferase; unclassified drug; veliparib

Improving Lifestyle Behaviors After Breast Cancer Treatment Among African American Women With and Without Diabetes: Role of Health Care Professionals - Jarvandi, S.; Pérez, M.; Margenthaler, J.; Colditz, G.A.; Kreuter, M.W.; Jeffe, D.B. (Annals of behavioral medicine : a publication of the Society of Behavioral Medicine, 2021)
BACKGROUND: Little is known about the effect of health professionals' advice on promoting healthy lifestyle behaviors (diet and exercise) among breast cancer patients. PURPOSE: To identify predictors of receiving lifestyle advice from health professionals and its impact on healthy lifestyle behaviors. METHODS: We used data from a randomized controlled trial of an interactive, cancer-communication video program using African American breast cancer survivor stories for newly diagnosed African American breast cancer patients (Stages 0-III). Participants completed five interviews over 2 years. This intervention did not significantly affect changes in quality-of-life outcomes. In secondary analysis, we examined differences in baseline variables between women with and without diabetes. Logistic regression models identified independent predictors of receiving advice from "a doctor or other health professional" to improve diet and exercise and of self-reported change in diet and exercise habits at 2 year follow-up. RESULTS: Of 193 patients included (85% of 228 enrolled), 53 (28%) had diabetes. At 2 year follow-up, a greater proportion of women with (vs. without) diabetes reported receiving advice by a doctor/health professional to improve their diet (73% vs. 57%, p = .04,). Predictors of receiving dietary advice were obesity, diabetes, and breast-conserving surgery (each p < .05). Women receiving dietary advice were 2.75 times more likely to report improving their diet (95% confidence interval: 1.17, 6.46) at follow-up, but receiving physical activity advice was not significantly associated with patients reporting an increase in exercise. CONCLUSIONS: Although receiving dietary advice predicted dietary improvements, receiving exercise advice did not lead to an increase in physical activity. CLINICAL TRIAL REGISTRATION: Trial Number NCT00929084.
Keywords: NCT00929084; adult; African American; article; breast cancer; cancer patient; cancer staging; cancer survival; cancer survivor; cancer therapy; controlled study; diabetic obesity; diet; exercise; female; follow up; habit; health practitioner; human; interview; lifestyle; major clinical study; partial mastectomy; physical activity; quality of life; randomized controlled trial; secondary analysis; videorecording

Does Scalp Cooling Have the Same Efficacy in Black Patients Receiving Chemotherapy for Breast Cancer? - Dilawari, A.; Gallagher, C.; Alintah, P.; Chitalia, A.; Tiwari, S.; Paxman, R.; Adams-Campbell, L.; Dash, C. (The oncologist, 2021)
LESSONS LEARNED: Despite FDA approval to reduce alopecia, data on efficacy of scalp cooling in Black cancer patients is limited due to lack of minority representation in prior clinical trials. Scalp cooling devices may have less efficacy in Black patients; additional studies are required to explore the possible causes for this, including hair texture and cap design. BACKGROUND: The Paxman scalp cooling (SC) device is FDA-approved for prevention of chemotherapy-induced alopecia (CIA). Studies report 50%-80% success rates and high patient satisfaction, yet there have been no studies of SC in Black patients. We conducted a phase II feasibility study of Paxman SC with a planned enrollment of 30 Black patients receiving chemotherapy for stage I-III breast cancer. METHODS: Black patients who planned to receive ≥4 cycles of chemotherapy with non-anthracycline (NAC) or anthracycline (AC) regimens were eligible. Alopecia was assessed by trained oncology providers using the modified Dean scale (MDS) prior to each chemotherapy session. Distress related to alopecia was measured by the Chemotherapy Alopecia Distress Scale (CADS). CONCLUSION: SC may not be efficacious in preventing alopecia in Black women. Differences in hair thickness, hair volume, and limitations of cooling cap design are possible contributing factors. RESULTS: 15 patients enrolled in the intervention before the study was closed early due to lack of efficacy. Median MDS and CADS increased after SC suggesting increased hair loss (p < .001) and alopecia distress (p = .04). Only one participant was successful in preventing significant hair loss; the majority stopped SC before chemotherapy completion due to grade 3 alopecia (>50% hair loss).
Keywords: adult; adverse drug reaction; alopecia; article; breast cancer; cancer chemotherapy; cancer patient; cancer staging; clinical article; clinical trial; controlled study; cooling system; distress syndrome; drug efficacy; feasibility study; female; hair loss; human; patient satisfaction; phase 2 clinical trial; prevention; scalp; thickness; anthracycline

Racial Disparities in Intravenous Bisphosphonate Use Among Older Patients With Multiple Myeloma Enrolled in Medicare - Zhou, J.; Sweiss, K.; Nutescu, E.A.; Han, J.; Patel, P.R.; Ko, N.Y.; Lee, T.A.; Chiu, B.C.-H.; Calip, G.S. (JCO oncology practice, 2021)
PURPOSE: Intravenous (IV) bisphosphonates reduce the risk of skeletal-related events in patients with multiple myeloma (MM). However, data describing racial differences in IV bisphosphonate utilization outside of clinical trial settings are limited. We evaluated population-level IV bisphosphonate initiation and discontinuation among patients of age ≥ 65 years with MM. METHODS: We conducted a retrospective cohort study of patients of age ≥ 65 years diagnosed with first primary MM between 2001 and 2011. Patients were identified using the SEER-Medicare linked database and followed through December 2013. Cumulative incidences of IV bisphosphonate initiation and time to discontinuation among users were compared between racial and ethnic groups. In Fine and Gray competing risk models, we estimated subdistribution hazard ratios (SHRs) and 95% CIs for initiation and discontinuation. RESULTS: We included 14,231 eligible patients with MM (median age, 76 years; 52% male). Over a median follow-up of 23.1 months, 54% of patients received at least one IV bisphosphonate dose. Our final analytical sample included 10,456 non-Hispanic (NH) Whites, 2,267 NH Blacks, 548 Asian and Pacific islanders, and 815 Hispanic and Latino patients. A higher proportion of White patients (56.1%) newly received IV bisphosphonates after MM diagnosis compared with NH Blacks (45.4%). Compared with White patients, NH Black patients were less likely to initiate IV bisphosphonates (SHR, 0.74; 95% CI, 0.70 to 0.79) and slightly more likely to discontinue treatment (SHR, 1.10; 95% CI, 1.01 to 1.19). CONCLUSION: Approximately half of the patients with MM of age ≥ 65 years did not receive IV bisphosphonates, with significant delay among racial minority groups. These findings highlight the need for improvement of IV bisphosphonate uptake in patients with MM of age ≥ 65 years.
Keywords: aged; article; Black person; cancer patient; Caucasian; clinical trial; cohort analysis; controlled study; cumulative incidence; drug therapy; drug withdrawal; ethnic group; female; follow up; Hispanic; human; major clinical study; male; medicare; minority group; multiple myeloma; Pacific Islander; retrospective study; risk assessment; bisphosphonic acid derivative

Opportunities to Improve Women's Health: Engaging Racial/Ethnic Diverse Women to Provide Biospecimens for Research - Edmonds, M.C.; Sutton, A.L.; Cummings, Y.; Sheppard, V.B. (Journal of women's health (2002), 2021)
Purpose: Inclusion of women in biomedical cancer research have the potential to close gaps in cancer health disparities and improve adjuvant therapies for women; yet samples needed to advance this area of science are lacking. We developed low-cost educational recruitment strategies to increase our collection of biospecimens from women. Materials and Methods: Women diagnosed with hormone receptor positive (HR+) breast cancer that initiated hormonal therapy were recruited from three integrated health systems. The analytical sample (n = 144) consisted of women who consented but did not return a saliva sample within 1 year of the initial assessment (baseline). Brief informational recruitment materials were developed via published literature and preliminary data. Women received recruitment materials, which included a personalized information letter, a colorful low-literacy instruction sheet, a postage-paid envelope, and collection kits. We evaluated intervention materials and performed descriptive and bivariate statistics to describe factors associated with biospecimen donation. Results: Of the total sample, 61% were white and 34% were black. Overall, 29 surveys (20%) and 25 (17%) saliva kits were returned. Women found the materials helpful and easy to read and understand. Women with higher levels of functional well-being and lower ratings of religiosity were more likely to return biospecimens (p < 0.005) after receiving enhanced materials. Conclusion: This article provides recruitment strategies to enhance biospecimen samples among women. Receipt of brief informational print materials inclusive of personalized messages enhanced our outreach strategies and increased our overall biospecimen provision rate by 17%. The inclusion of messages with a focus on spirituality and other cultural messages may further increase biospecimen provision in racial/ethnic diverse groups of women; however, further study is needed to support this claim. Clinical Trail Registration Number: NCT02992730.
Keywords: NCT02992730; adult; article; bivariate analysis; breast cancer; cancer survivor; female; hormonal therapy; human; human tissue; literacy; major clinical study; preliminary data; religion; saliva; transcription initiation; wellbeing; women's health; endogenous compound; hormone receptor

Immunogenomic gene signature of cell-death associated genes with prognostic implications in lung cancer - Ahluwalia, P.; Ahluwalia, M.; Mondal, A.K.; Sahajpal, N.; Kota, V.; Rojiani, M.V.; Rojiani, A.M.; Kolhe, R. (Cancers, 2021)
Lung cancer is one of the leading causes of death worldwide. Cell death pathways such as autophagy, apoptosis, and necrosis can provide useful clinical and immunological insights that can assist in the design of personalized therapeutics. In this study, variations in the expression of genes involved in cell death pathways and resulting infiltration of immune cells were explored in lung adenocarcinoma (The Cancer Genome Atlas: TCGA, lung adenocarcinoma (LUAD), 510 patients). Firstly, genes involved in autophagy (n = 34 genes), apoptosis (n = 66 genes), and necrosis (n = 32 genes) were analyzed to assess the prognostic significance in lung cancer. The significant genes were used to develop the cell death index (CDI) of 21 genes which clustered patients based on high risk (high CDI) and low risk (low CDI). The survival analysis using the Kaplan–Meier curve differentiated patients based on overall survival (40.4 months vs. 76.2 months), progression-free survival (26.2 months vs. 48.6 months), and disease-free survival (62.2 months vs. 158.2 months) (Log-rank test, p < 0.01). Cox proportional hazard model significantly associated patients in high CDI group with a higher risk of mortality (Hazard Ratio: H.R 1.75, 95% CI: 1.28–2.45, p < 0.001). Differential gene expression analysis using principal component analysis (PCA) identified genes with the highest fold change forming distinct clusters. To analyze the immune parameters in two risk groups, cytokines expression (n = 265 genes) analysis revealed the highest association of IL-15RA and IL 15 (> 1.5-fold, p < 0.01) with the high-risk group. The microenvironment cell-population (MCP)-counter algorithm identified the higher infiltration of CD8+ T cells, macrophages, and lower infiltration of neutrophils with the high-risk group. Interestingly, this group also showed a higher expression of immune checkpoint molecules CD-274 (PD-L1), CTLA-4, and T cell exhaustion genes (HAVCR2, TIGIT, LAG3, PDCD1, CXCL13, and LYN) (p < 0.01). Furthermore, functional enrichment analysis identified significant perturbations in immune pathways in the higher risk group. This study highlights the presence of an immunocompromised microenvironment indicated by the higher infiltration of cytotoxic T cells along with the presence of checkpoint molecules and T cell exhaustion genes. These patients at higher risk might be more suitable to benefit from PD-L1 blockade or other checkpoint blockade immunotherapies.
Keywords: CD8 antigen; CXCL13 chemokine; cytotoxic T lymphocyte antigen 4; hepatitis A virus cellular receptor 2; interleukin 15; interleukin 15 receptor alpha; programmed death 1 ligand 1; protein kinase Lyn; T lymphocyte receptor; adult; African American; aged; aneuploidy; apoptosis; article; autophagy (cellular); cancer immunotherapy; cancer prognosis; cancer radiotherapy; cancer staging; Caucasian; CD8+ T lymphocyte; cell death; cell fate; cell infiltration; cell population; CXCL13 gene; disease free survival; disease specific survival; distant metastasis; female; gene; gene expression; genetic association; genetic variability; HAVCR2 gene; high risk patient; high risk population; human; immune response; immunocompetent cell; immunocompromised patient; immunogenomics; Kaplan Meier method; LAG3 gene; low risk patient; lung adenocarcinoma; lung cancer; lymph node metastasis; lymphocytic infiltration; LYN gene; macrophage; major clinical study; male; middle aged; mortality risk; neutrophil chemotaxis; overall survival; patient selection; PDCD1 gene; principal component analysis; progression free survival; proportional hazards model; survival analysis; TIGIT gene; tumor microenvironment

The Effectiveness of Shared Compared to Informed Decision Making for Prostate Cancer Screening in a High-Risk African American Population: A Randomized Control Trial - Carlson, D.S.; Grivas, P.; Wei, W.; Dhillon, P.K.; Abraksia, S. (Cancer Investigation, 2021)
Background: Prostate cancer incidence and mortality in the United States in African Americans (AA) are higher than in Caucasians. Eastern Cuyahoga County in Ohio is majority AA and is considered an underserved population particularly vulnerable to healthcare disparities. There is a paucity of data about shared decision making among high-risk AA men with regard to prostate cancer screening. This study aims to examine shared versus informed decision making (SDM versus IDM) in a randomized, control trial among a large, high-risk AA population. Methods: Patients were included in annual one-day outreach events, each held over 3 years (2017–2019), and were randomized at each event into IDM (control) and SDM (investigational) groups and then were offered screening via prostate specific antigen (PSA) and digital rectal exam (DRE). The primary endpoints were proportion of participants over 40 who did not demonstrate decisional conflict about prostate cancer screening measured by the SURE score, as well as change of knowledge score about prostate cancer screening. Results: Overall, 175 patients were enrolled in the trial; 79 in the SDM arm and 96 in the IDM arm. The investigational (SDM) arm had 3/79 (3.9%) conflict versus 6/96 (6.4%) in the control (IDM) arm (p = 0.74). With regard to knowledge improvement, the SDM cohort demonstrated improvement following educational tools for 66/79 (81%) of participants versus 76/96 (79%) in the IDM cohort (p = 0.85). There was no difference in the proportion (63%) of participants in either group who found the information very helpful (using a Likert scale). Conclusions: Our education-based study showed no significant difference between SDM and IDM with regard to decisional conflict about prostate cancer screening. The study also demonstrated significant improvement in knowledge about prostate cancer screening in a high-risk AA population in both groups. Our results should be interpreted with caution due to several limitations; however, the study can serve as a benchmark for future studies in this very important topic.
Keywords: adult; African American; article; cancer screening; cohort analysis; comparative effectiveness; controlled study; digital rectal examination; education; high risk population; human; Likert scale; major clinical study; male; prostate cancer; randomized controlled trial; shared decision making; endogenous compound; prostate specific antigen

IMPROVE, a community-based exercise intervention versus support group to improve functional and health outcomes among older African American and Non-Hispanic White breast cancer survivors from diverse socioeconomic backgrounds: Recruitment strategies and baseline characteristics - Owusu, C.; Nock, N.L.; Feuntes, V.; Margevicius, S.; Hergenroeder, P.; Austin, K.; Bennet, E.; Cerne, S.; Moore, H.C.F.; Petkac, J.; Schluchter, M.; Schmitz, K.H.; et al. (Cancer, 2021)
Background: Behavioral intervention studies in older breast cancer survivors, particularly older African American (AA) and socioeconomic status–disadvantaged breast cancer survivors, are lacking. To inform future studies, the authors examined recruitment strategies in older breast cancer survivors who participated in an exercise intervention study. Methods: IMPROVE is a randomized trial designed to evaluate a group-based exercise intervention versus a support group (ClinicalTrials.gov identifier, NCT02763228). Participants were aged ≥65 years who had survived stage I through III breast cancer and were within 5 years of treatment completion. Participants were recruited through multiple approaches, including peripheral, linguistic, and constituent-involving strategies that incorporated the identification of potentially eligible patients from 3 local hospitals and from State of Ohio registries and through direct clinician and community organization referrals. Results: Between October 2016 and November 2019, 7487 patients were screened, 4790 were potentially eligible, and 213 were randomized into the study. The eligible:randomization rates were 4.4% overall and 84%, 8%, and 2% for recruitment using direct referrals, hospital registries, and state registries, respectively. The median age of the randomized cohort was 70 years (range, 65-88 years) and included 44% AA and 44% socioeconomic status–disadvantaged breast cancer survivors. Compared with all registry-eligible patients, directly referred-eligible patients were more likely to be AA versus Non-Hispanic White (41% vs 19%; P =.006), to be contacted successfully (100% vs 33%; P <.0001), and to accept study participation (88% vs 16%; P <.0001). Conclusions: Direct referrals appeared to be the most efficient strategy for recruiting AA survivors. Behavioral intervention studies seeking to target older AA and socioeconomic status–disadvantaged breast cancer survivors should include strategies that foster direct referrals to study participation.
Keywords: African American; aged; article; breast cancer; cancer staging; cancer survival; cancer survivor; community; controlled study; exercise; female; human; intervention study; multicenter study (topic); Ohio; randomization; randomized controlled trial (topic); social status; support group; systematic review

Knowledge and perceptions of BRCA1/2 genetic testing and needs of diverse women with a personal or family history of breast cancer in South Florida - Jones, T.; Howard, H.; Freeman-Costin, K.; Creighton, A.; Wisdom-Chambers, K.; Underhill-Blazey, M. (Journal of Community Genetics, 2021)
The vast majority of (BRCA1/2) genetic testing has been conducted in White women, in particular Ashkenazi Jewish women, with limited information available for Black and Hispanic women. Understanding perspectives of those who are underserved is critical to developing interventions to support inclusive approaches to genetic testing. This qualitative study explored knowledge and perceptions of BRCA1/2 genetic testing among diverse women in South Florida. We also explored participants’ information needs. Convenience sampling was used to recruit a diverse group of 15 women with a personal or family history of breast cancer. We conducted semi-structured interviews and used grounded theory method to analyze the data. Five themes were identified: (1) lacking awareness and knowledge of BRCA1/2 genetic testing and results among Black women, (2) perceiving BRCA1/2 genetic testing as beneficial to themselves and a way to be proactive about cancer risk, (3) perceiving BRCA1/2 genetic testing as beneficial to family members, (4) interactions with healthcare providers and the healthcare system that shape genetic testing experiences, and (5) information needs for reducing cancer risk and promoting health. Our findings suggest that diverse underserved women perceived genetic testing as beneficial to themselves and family members. Women needed more information about the BRCA genes and genetic testing, prevention strategies, and the latest breast cancer research. Healthcare providers, particularly nurse practitioners, need to engage diverse high-risk women in discussions about their cancer risk, address unmet information needs, and, in particular, educate Black women about the benefits of pursuing genetic testing.
Keywords: adult; article; awareness; breast cancer; cancer research; cancer risk; clinical article; controlled study; convenience sample; family history; female; Florida; genetic screening; grounded theory; health care system; human; human tissue; nurse practitioner; perception; qualitative research; semi structured interview; BRCA1 protein; BRCA2 protein; endogenous compound

Does Scalp Cooling Have the Same Efficacy in Black Patients Receiving Chemotherapy for Breast Cancer? - Dilawari, A.; Gallagher, C.; Alintah, P.; Chitalia, A.; Tiwari, S.; Paxman, R.; Adams-Campbell, L.; Dash, C. (Oncologist, 2021)
Lessons Learned: Despite U.S. Food and Drug Administration approval to reduce alopecia, data on efficacy of scalp cooling in Black patients with cancer are limited by lack of minority representation in prior clinical trials. Scalp cooling devices may have less efficacy in Black patients; additional studies are required to explore the possible causes for this, including hair texture and cap design. Background: The Paxman scalp cooling (SC) device is U.S. Food and Drug Administration (FDA)-approved for prevention of chemotherapy-induced alopecia. Studies report 50%–80% success rates and high patient satisfaction, yet there have been no studies of SC in Black patients. We conducted a phase II feasibility study of Paxman SC with a planned enrollment of 30 Black patients receiving chemotherapy for stage I–III breast cancer. Methods: Black patients who planned to receive at least four cycles of chemotherapy with non-anthracycline (NAC) or anthracycline (AC) regimens were eligible. Alopecia was assessed by trained oncology providers using the modified Dean scale (MDS) prior to each chemotherapy session. Distress related to alopecia was measured by the Chemotherapy Alopecia Distress Scale (CADS). Results: Fifteen patients enrolled in the intervention before the study was closed early because of lack of efficacy. Median MDS and CADS increased after SC, suggesting increased hair loss (p <.001) and alopecia distress (p =.04). Only one participant was successful in preventing significant hair loss; the majority stopped SC before chemotherapy completion because of grade 3 alopecia (>50% hair loss). Conclusion: SC may not be efficacious in preventing alopecia in Black women. Differences in hair thickness, hair volume, and limitations of cooling cap design are possible contributing factors.
Keywords: adult; adverse drug reaction; alopecia; article; breast cancer; cancer chemotherapy; cancer patient; cancer staging; clinical article; clinical trial; controlled study; cooling system; distress syndrome; drug efficacy; feasibility study; female; Food and Drug Administration; hair loss; human; patient satisfaction; phase 2 clinical trial; prevention; scalp; side effect; thickness; anthracycline

Racial disparity in prostate cancer in the African American population with actionable ideas and novel immunotherapies - Dovey, Z.S.; Nair, S.S.; Chakravarty, D.; Tewari, A.K. (Cancer Reports, 2021)
Background: African Americans (AAs) in the United States are known to have a higher incidence and mortality for Prostate Cancer (PCa). The drivers of this epidemiological disparity are multifactorial, including socioeconomic factors leading to lifestyle and dietary issues, healthcare access problems, and potentially tumor biology. Recent findings: Although recent evidence suggests once access is equal, AA men have equal outcomes to Caucasian American (CA) men, differences in PCa incidence remain, and there is much to do to reverse disparities in mortality across the USA. A deeper understanding of these issues, both at the clinical and molecular level, can facilitate improved outcomes in the AA population. This review first discusses PCa oncogenesis in the context of its diverse hallmarks before benchmarking key molecular and genomic differences for PCa in AA men that have emerged in the recent literature. Studies have emphasized the importance of tumor microenvironment that contributes to both the unequal cancer burden and differences in clinical outcome between the races. Management of comorbidities like obesity, hypertension, and diabetes will provide an essential means of reducing prostate cancer incidence in AA men. Although requiring further AA specific research, several new treatment strategies such as immune checkpoint inhibitors used in combination PARP inhibitors and other emerging vaccines, including Sipuleucel-T, have demonstrated some proven efficacy. Conclusion: Genomic profiling to integrate clinical and genomic data for diagnosis, prognosis, and treatment will allow physicians to plan a “Precision Medicine” approach to AA men. There is a pressing need for further research for risk stratification, which may allow early identification of AA men with higher risk disease based on their unique clinical, genomic, and immunological profiles, which can then be mapped to appropriate clinical trials. Treatment options are outlined, with a concise description of recent work in AA specific populations, detailing several targeted therapies, including immunotherapy. Also, a summary of current clinical trials involving AA men is presented, and it is important that policies are adopted to ensure that AA men are actively recruited. Although it is encouraging that many of these explore the lifestyle and educational initiatives and therapeutic interventions, there is much still work to be done to reduce incidence and mortality in AA men and equalize current racial disparities.
Keywords: adult; African American; benchmarking; cancer incidence; cancer prognosis; carcinogenesis; clinical outcome; comorbidity; diabetes mellitus; diet; drug combination; European American; genetic susceptibility; health care access; human; hypertension; immunotherapy; lifestyle; male; molecularly targeted therapy; mortality; obesity; personalized medicine; physician; prognosis; prostate cancer; protein fingerprinting; race; review; socioeconomics; tumor microenvironment; biological marker; immune checkpoint inhibitor; nicotinamide adenine dinucleotide adenosine diphosphate ribosyltransferase inhibitor; sipuleucel T

Integration of electronic pathology reporting with clinical trial matching for advanced prostate cancer - Borno, H.T.; Duffy, C.; Zhang, S.; Canchola, A.J.; Loya, Z.; Golden, T.; Oh, D.L.; Odisho, A.Y.; Gomez, S. (Urologic Oncology: Seminars and Original Investigations, 2021)
Introduction: Racial/ethnic diversity in prostate cancer (CaP) clinical trials (CTs) is essential to address CaP disparities. California Cancer Registry mandated electronic reporting (e-path) of structured data elements from pathologists diagnosing cancer thereby creating an opportunity to identify and approach patients rapidly. This study tested the utility of an online CT matching tool (called Trial Library) used in combination with e-path to improve matching of underrepresented CaP patients into CTs at time of diagnosis. Methods: This was a nonrandomized, single-arm feasibility study among patients with a new pathologic diagnosis of high-risk CaP (Gleason Score ≥8). Eligible patients were sent recruitment materials and enrolled patients were introduced to Trial Library. Results: A total of 419 case listings were assessed. Patients were excluded due to physician contraindication, not meeting baseline eligibility, or unable to be reached. Final participants (N = 52) completed a baseline survey. Among study participants, 77% were White, 10% were Black/Hispanic/Missing, and 14% were Asian. The majority of the study participants were over 65 years of age (81%) and Medicare insured (62%). Additionally, 81% of participants reported using the Internet to learn about CaP. The majority (62%) of participants reported that Trial Library increased their interest in CT participation. Conclusions: The current study demonstrated that leveraging structured e-path data reporting to a population-based cancer registry to recruit men with high risk CaP to clinical research is feasible and acceptable. We observed that e-path may be linked with an online CT matching tool, Trial Library. Future studies will prioritize recruitment from reporting facilities that serve more racially/ethnically diverse patient populations.
Keywords: adult; advanced cancer; article; cancer registry; clinical research; contraindication; controlled study; feasibility study; Gleason score; Hispanic; human; Internet; major clinical study; male; medicare; physician; prostate cancer

Representativeness of black patients in cancer clinical trials sponsored by the national cancer institute compared with pharmaceutical companies - Unger, J.M.; Hershman, D.L.; Osarogiagbon, R.U.; Gothwal, A.; Anand, S.; Dasari, A.; Overman, M.; Loree, J.M.; Raghav, K. (JNCI Cancer Spectrum, 2021)
Background: Many clinical trials supporting new drug applications underrepresent minority patients. Trials conducted by the National Cancer Institute's National Clinical Trial's Network (NCTN) have greater outreach to community sites, potentially allowing better representation. We compared the representation of Black patients in pharmaceutical company-sponsored cancer clinical trials with NCTN trials and with the US cancer population. Methods: We established a large cohort of study publications representing the results of trials that supported new US Food and Drug Administration drug approvals from 2008 to 2018. NCTN trial data were from the SWOG Cancer Research Network. US cancer population rates were estimated using Surveillance, Epidemiology, and End Results survey data. We compared the proportion of Black patients by enrollment year for each cancer type and overall. Tests of proportions were used. All statistical tests were 2-sided. Results: A total 358 trials (pharmaceutical company-sponsored trials, 85; SWOG trials, 273) comprised of 93 825 patients (pharmaceutical company-sponsored trials, 46 313; SWOG trials, 47 512) for 15 cancer types were analyzed. Overall, the proportion of Black patients was 2.9% for pharmaceutical company-sponsored trials, 9.0% for SWOG trials, and 12.1% for the US cancer population (P<.001 for each pairwise comparison). These findings were generally consistent across individual cancer types. Conclusions: The poor representation of Black patients in pharmaceutical company-sponsored trials supporting new drug applications could result in the use of new drugs with little data about efficacy or side effects in this key population. Moreover, because pharmaceutical company-sponsored trials test the newest available therapies, limited access to these trials represents a disparity in access to potential breakthrough therapies.
Keywords: new drug; adult; article; Black person; bladder cancer; breast cancer; cancer patient; cancer research; clinical trial (topic); cohort analysis; colorectal cancer; controlled study; drug approval; drug industry; esophagus cancer; female; female genital tract cancer; Food and Drug Administration; glioblastoma; head and neck cancer; human; kidney cancer; leukemia; lung cancer; lymphoma; major clinical study; male; malignant neoplasm; melanoma; national health organization; pancreas cancer; phase 1 clinical trial (topic); phase 2 clinical trial (topic); phase 3 clinical trial (topic); priority journal; prostate cancer; publication; sarcoma; stomach cancer; United States

A case-control study examining disparities in clinical trial participation among breast surgical oncology patients - Fayanju, O.M.; Ren, Y.; Thomas, S.M.; Greenup, R.A.; Hyslop, T.; Shelley Hwang, E.; Stewart, J.H. (JNCI Cancer Spectrum, 2021)
Background: Clinical trial participation among racial and ethnic minorities remains low despite national efforts. We sought to determine how participation in clinical trials by breast surgical oncology patients has changed over time and what characteristics are associated with participation. Methods:Women with breast cancer enrolled in National Cancer Institute-sponsored, cooperative-group trials from 2000 to 2012 and who underwent oncologic surgery (n 17 125) were compared with trial-eligible women in the National Cancer Database diagnosed in 2000-2012 (n 792 719). Race-specific trial participation was plotted over time by income and reported as a proportion of the combined cohorts. Factors associated with trial participation were estimated using logistic regression; we report odds ratios (ORs) with 95% confidence intervals (CIs). A P value less than .05 was considered statistically significant for all analyses. All tests were two-sided. Results: Participation declined across all groups over time because of a decrease in the scale and number of trials. In 2000- 2003, Asian-Pacific Islander (7.17%), Hispanic (3.48%), and white (7.13%) patients from the highest income group had higher participation than their lower-income counterparts (Asian-Pacific Islander: 3.95%; Hispanic: 2.67%; white: 5.96%), but by 2008- 2012, only high-income white patients participated more than lower-income whites (0.32% vs 0.25%, all P<.01). Black (OR 0.80, 95% CI 0.75 to 0.85) and Hispanic (OR 0.84, 95% CI 0.77 to 0.92) patients were less likely to participate than whites, but there were statistically significant interactions between income and race and ethnicity, with high-income black patients being approximately 50% less likely to participate than lower-income blacks (all P<.001). Conclusions: Multifaceted interventions addressing the intersectionality of race, ethnicity, and other patient characteristics are needed to address persistent disparities in trial participation among breast surgical oncology patients.
Keywords: adult; article; Black person; breast cancer; cancer surgery; case control study; Caucasian; controlled clinical trial; controlled study; ethnicity; female; highest income group; Hispanic; human; national health organization; Pacific Islander; surgical oncology

Phase II study of neratinib in older adults with HER2 amplified or HER2/3 mutated metastatic breast cancer - Yuan, Y.; Lee, J.S.; Yost, S.E.; Stiller, T.; Blanchard, M.S.; Padam, S.; Katheria, V.; Kim, H.; Sun, C.; Tang, A.; Martinez, N.; Patel, N.D.; et al. (Journal of Geriatric Oncology, 2021)
Objective: The tolerability and efficacy of targeted therapy in older adults with cancer has not been adequately studied. Neratinib is a novel HER1, HER2, HER4 tyrosine kinase inhibitor that has recently been granted FDA approval for treatment of breast cancer. The major toxicity of neratinib is diarrhea, which affects up to 90% of patients. This phase II trial evaluates the safety and tolerability of neratinib in adults ≥60. Methods: Patients aged 60 or older with histologically proven metastatic breast cancer and HER2 amplification (defined by ASCO/CAP guideline) or HER2/HER3 activating mutation were enrolled to receive neratinib at 240 mg daily in 28-day cycles. The association between tolerability, defined as dose reduction and number of completed courses, and log2 Cancer and Aging Research Group (CARG) toxicity risk score was assessed using a Student's t-test and linear regression, respectively. Response rate, progression free survival, and overall survival were also evaluated. Results: 25 patients were enrolled with median age of 66 (range 60–79). Seventy-six percent of patients were white, 16% Asian, and 8% African-American. Seventy-six percent were patients with hormone receptor (HR) positive metastatic breast cancer (MBC) and 24% were patients with HR negative MBC. Median number of prior lines of metastatic therapy were 3 (range 0–11). 20/25 (80%) had worst grade toxicities ≥2. A total of 9/25 (36%) had grade 3 toxicities including 5/20 (20%) diarrhea, 2/20 (8%) vomiting, and 2/20 (8%) abdominal pain. There were no grade 4 or 5 toxicities. A total of 9/25 (36%) had dose reduction, and 2/25 (8%) discontinued therapy due to toxicity. The association between dose reductions and CARG toxicity score reached borderline statistical significance suggesting a trend with participants with higher CARG toxicity risk scores being more likely to require a dose modification (p = 0.054). 1/25 (4%) had a partial response, 11/25 (44%) had stable disease, 12/25 (48%) had progression of disease, and 1/25 (4%) was not assessed. Median progression free survival (PFS) was 2.6 months (95% CI [2.56–5.26]), and median overall survival (OS) was 17.4 months (95% CI [10.3, NA]). Conclusions: Neratinib was safe in this population of older adults with HER2 amplified or HER2/3 mutated metastatic breast cancer (BC). Higher CARG toxicity risk score may be associated with greater need for dose adjustments. Future studies are needed to confirm this finding.
Keywords: abdominal pain; adult; adverse drug reaction; African American; aged; aging; article; cancer patient; cancer survival; clinical article; clinical trial; controlled study; diarrhea; drug safety; drug therapy; enzyme activity; female; gene amplification; gene mutation; histopathology; human; linear regression analysis; metastatic breast cancer; overall survival; pharmacokinetics; phase 2 clinical trial; practice guideline; progression free survival; risk assessment; statistical significance; vomiting; endogenous compound; epidermal growth factor receptor 2; hormone receptor; neratinib

Effect of Text Messaging on Bowel Preparation and Appointment Attendance for Outpatient Colonoscopy: A Randomized Clinical Trial - Mahmud, N.; Asch, D.A.; Sung, J.; Reitz, C.; Coniglio, M.S.; McDonald, C.; Bernard, D.; Mehta, S.J. (JAMA Network Open, 2021)
Importance: Outpatient colonoscopy is important for colorectal cancer screening. However, nonadherence and poor bowel preparation are common. Objective: To determine if an automated text messaging intervention with a focus on informational and reminder functions could improve attendance rates and bowel preparation quality for outpatient colonoscopy. Design, Setting, and Participants: This randomized clinical trial was conducted in an endoscopy center at an urban academic medical center. Adult patients scheduled for outpatient colonoscopy between January and September 2019 were enrolled by telephone call (early phase) or by automated text message (late phase). Data were analyzed from October 2019 to January 2020. Interventions: After enrollment, patients were randomized in a 1:1 ratio to usual care (ie, written instructions and nurse telephone call) or to the intervention (ie, usual care plus an automated series of 9 educational or reminder text messages in the week prior to scheduled colonoscopy). Main Outcomes and Measures: The primary outcome was appointment attendance rate with good or excellent bowel preparation. Secondary outcomes included appointment attendance rate, bowel preparation quality (poor or inadequate, fair or adequate, and good or excellent), and cancellation lead time (in days). Results: Among 753 patients included and randomized in the trial (median [interquartile range] age, 56 [49-64] years; 364 [48.3%] men; 429 [57.2%] Black), 367 patients were randomized to the intervention group and 386 patients were randomized to the control group. There was no significant difference in the primary outcome between groups (patients attending appointments with good or excellent bowel preparation: intervention, 195 patients [53.1%]; control, 210 patients [54.4%]; P =.73), including when stratified by early or late phase enrollment groups. Similarly, there were no significant differences in secondary outcomes. Conclusions and Relevance: This randomized clinical trial found no significant difference in appointment attendance or bowel preparation quality with an automated text messaging intervention compared with the usual care control. Future work could optimize the content and delivery of text message interventions or identify patient subgroups that may benefit from this approach. Trial Registration: ClinicalTrials.gov Identifier: NCT03710213.
Keywords: adult; article; colonoscopy; controlled study; female; human; intestine preparation; major clinical study; male; nurse; outcome assessment; outpatient; randomized controlled trial; telephone; text messaging; university hospital

Successful Recruitment of Black Men to Prostate Cancer Clinical Trials - A Lesson in Achievement - Hahn, A.W.; Bilen, M.A.; Agarwal, N. (JAMA Network Open, 2021)
Keywords: achievement; adult; controlled study; human; male; note; prostate cancer

Clinical Efficacy of Enzalutamide vs Bicalutamide Combined with Androgen Deprivation Therapy in Men with Metastatic Hormone-Sensitive Prostate Cancer: A Randomized Clinical Trial - Vaishampayan, U.N.; Heilbrun, L.K.; Monk, P.; Tejwani, S.; Sonpavde, G.; Hwang, C.; Smith, D.; Jasti, P.; Dobson, K.; Dickow, B.; Heath, E.I.; Semaan, L.; et al. (JAMA Network Open, 2021)
Importance: Black patients have been underrepresented in prospective clinical trials of advanced prostate cancer. This study evaluated the efficacy of enzalutamide compared with bicalutamide, with planned subset analysis of Black patients with metastatic hormone-sensitive prostate cancer (mHSPC), which is a disease state responsive to androgen deprivation therapy (ADT). Objective: To compare the efficacy of enzalutamide vs bicalutamide in combination with ADT in men with mHSPC, with a subset analysis of Black patients. Design, Setting, and Participants: In this randomized clinical trial, a phase 2 screening design enabled a nondefinitive comparison of the primary outcome by treatment. Patients were stratified by race (Black or other) and bone pain (present or absent). Accrual of at least 30% Black patients was required. This multicenter trial was conducted at 4 centers in the US. Men with mHSPC with no history of seizures and adequate marrow, renal, and liver function were eligible. Data analysis was performed from February 2019 to March 2020. Interventions: Participants were randomized 1:1 to receive oral enzalutamide (160 mg daily) or bicalutamide (50 mg daily) in addition to ADT. Main Outcomes and Measures: The primary end point was the 7-month prostate-specific antigen (PSA) response (SMPR) rate, a previously accepted surrogate for overall survival (OS) outcome. Secondary end points included adverse reactions, time to PSA progression, and OS. Results: A total of 71 men (median [range] age, 65 [51-86] years) were enrolled; 29 (41%) were Black, 41 (58%) were White, and 1 (1%) was Asian. Thirty-six patients were randomized to receive enzalutamide, and 35 were randomized to receive bicalutamide. Twenty-six patients (37%) had bone pain and 37 patients (52%) had extensive disease. SMPR was achieved in 30 of 32 patients (94%; 95% CI, 80%-98%) taking enzalutamide and 17 of 26 patients (65%; 95% CI, 46%-81%) taking bicalutamide (P =.008) (difference, 29%; 95% CI, 5%-50%). Among Black patients, the SMPR was 93% (95% CI, 69%-99%) among those taking enzalutamide and 42% (95% CI, 19%-68%) among those taking bicalutamide (P =.009); among non-Black patients, the SMPR was 94% (95% CI, 74%-99%) among those taking enzalutamide and 86% (95% CI, 60%-96%) among those taking bicalutamide. The 12-month PSA response rates were 84% with enzalutamide and 34% with bicalutamide. Conclusions and Relevance: The findings of this randomized clinical trial comparing enzalutamide with bicalutamide suggest that enzalutamide is associated with improved outcomes compared with bicalutamide, in terms of the rate and duration of PSA response, in Black patients with mHSPC. Trial Registration: ClinicalTrials.gov Identifier: NCT02058706.
Keywords: adult; androgen deprivation therapy; article; bone marrow; bone pain; cancer patient; cancer survival; clinical trial; comparative effectiveness; controlled study; data analysis; drug combination; drug therapy; human; kidney; liver function; major clinical study; male; multicenter study; overall survival; phase 2 clinical trial; prospective study; prostate cancer; race; randomized controlled trial; reaction time; seizure; bicalutamide; endogenous compound; enzalutamide; hormone; prostate specific antigen

Pre-diagnostic allostatic load and health-related quality of life in a cohort of Black breast cancer survivors - Xing, C.Y.; Doose, M.; Qin, B.; Lin, Y.; Carson, T.L.; Plascak, J.J.; Demissie, K.; Hong, C.-C.; Bandera, E.V.; Llanos, A.A.M. (Breast Cancer Research and Treatment, 2020)
Purpose: To determine the association of pre-diagnostic allostatic load (AL) with health-related quality of life (HRQOL) among Black women with breast cancer. Methods: In a sample of 409 Black women with non-metastatic breast cancer enrolled in the Women’s Circle of Health Follow-Up Study (WCHFS), two pre-diagnostic AL measures were estimated using medical records data from up to 12 months prior to breast cancer diagnosis: AL-lipid/metabolic profile-based measure and AL-inflammatory profile-based measure. HRQOL was assessed approximately 24 months post diagnosis, using the Functional Assessment of Cancer Therapy-Breast Cancer (FACT-B) instrument, including 5 subscale scores [presented by physical well-being (PWB), social & family well-being (SFWB), emotional well-being (EWB), functional well-being (FWB), and breast cancer-specific scale (BCS)] and 3 derived total scores [presented by trial outcome index (TOI), Functional Assessment of Cancer Therapy-General (FACT-G) and FACT-B]. We used multivariable logistic regression models, using dichotomized AL scores (lower AL: 0–3 points, higher AL: 4–8 points), to assess the associations between the two pre-diagnostic AL measures and HRQOL. Results: Higher pre-diagnostic AL was associated with poorer FWB and lower FACT-G, but these associations were statistically significant for the AL-inflammatory profile-based measure (FWB: OR 1.63, 95% CI 1.04, 2.56; FACT-G: OR 1.62, 95% CI 1.04, 2.54), but not the AL-lipid/metabolic profile-based measure (FWB: OR 1.45, 95% CI 0.81, 2.59; FACT-G: OR 1.33, 95% CI 0.75, 2.37). Conclusion: These findings suggest that higher AL, particularly when measured using the inflammatory profile-based measure, was associated with poorer HRQOL, namely FWB and FACT-G, among Black breast cancer survivors.
Keywords: cholesterol; high density lipoprotein cholesterol; triacylglycerol; adult; age distribution; article; Black person; breast cancer; cancer diagnosis; cancer grading; cancer staging; cancer survivor; cholesterol blood level; cohort analysis; comorbidity; controlled study; diastolic blood pressure; educational status; female; Functional Assessment of Cancer Therapy Breast Cancer Instrument; high density lipoprotein cholesterol level; human; longitudinal study; low density lipoprotein cholesterol level; major clinical study; marriage; pre diagnostic allostatic load; priority journal; quality of life; quality of life assessment; systolic blood pressure; triacylglycerol blood level; waist circumference

Tailoring virtual human-delivered interventions: A digital intervention promoting colorectal cancer screening for Black women - Vilaro, M.J.; Wilson-Howard, D.S.; Griffin, L.N.; Tavassoli, F.; Zalake, M.S.; Lok, B.C.; Modave, F.P.; George, T.J.; Carek, P.J.; Krieger, J.L. (Psycho-Oncology, 2020)
Objective: Despite efforts to reduce cancer disparities, Black women remain underrepresented in cancer research. Virtual health assistants (VHAs) are one promising digital technology for communicating health messages and promoting health behaviors to diverse populations. This study describes participant responses to a VHA-delivered intervention promoting colorectal cancer (CRC) screening with a home-stool test. Methods: We recruited 53 non-Hispanic Black women 50 to 73 years old to participate in focus groups and think-aloud interviews and test a web-based intervention delivered by a race- and gender-concordant VHA. A user-centered design approach prioritized modifications to three successive versions of the intervention based on participants' comments. Results: Participants identified 26 cues relating to components of the VHA's credibility, including trustworthiness, expertise, and authority. Comments on early versions revealed preferences for communicating with a human doctor and negative critiques of the VHA's appearance and movements. Modifications to specific cues improved the user experience, and participants expressed increased willingness to engage with later versions of the VHA and the screening messages it delivered. Informed by the Modality, Agency, Interactivity, Navigability Model, we present a framework for developing credible VHA-delivered cancer screening messages. Conclusions: VHAs provide a systematic way to deliver health information. A culturally sensitive intervention designed for credibility promoted user interest in engaging with guideline-concordant CRC screening messages. We present strategies for effectively using cues to engage audiences with health messages, which can be applied to future research in varying contexts.
Keywords: adult; aged; article; cancer screening; colorectal cancer; colorectal tumor; controlled study; early cancer diagnosis; feces analysis; female; gender; human; human experiment; interview; major clinical study; male; medical information; practice guideline; psycho-oncology; qualitative research; race; transcription initiation; web-based intervention

Racial differences in veterans’ response to a standard vs. patient-centered decision aid for prostate cancer: Implications for decision making in African American and White men - Langford, A.T.; Scherer, L.D.; Ubel, P.A.; Holmes-Rovner, M.; Scherr, K.A.; Fagerlin, A. (Patient Education and Counseling, 2020)
Objective: To determine whether racial differences exist in patient preferences for prostate cancer treatment after being informed about options using a patient-centered vs. a standard decision aid (DA). Methods: This article reports secondary analyses of a large study of men diagnosed with early stage prostate cancer. Men were recruited from 4 VA Health Systems and randomized to receive a patient-centered or standard DA about prostate cancer treatment options. Data were collected at 1) baseline, 2) after reading the DA but prior to diagnosis, and 3) after receiving a cancer diagnosis and meeting with a urologist. Results: White patients who received the patient-centered DA written at a 7th grade reading level were more likely to prefer active surveillance and less likely to prefer radiation compared to those who received the standard DA written at >9th grade reading level. African American patients’ treatment preferences did not differ as a function of DA. Conclusions: When informed about prostate cancer treatment options through a patient-centered DA, White patients changed their treatment preferences but African American patients did not. Practice Implications: As DAs are increasingly being used in clinical practice, more research is needed regarding the efficacy, relevance, and receptivity of DAs for African Americans.
Keywords: prostate specific antigen; adult; African American; anxiety; article; cancer diagnosis; cancer radiotherapy; cancer therapy; clinical practice; comparative study; controlled study; decision support system; disease surveillance; early cancer; education; European American; exploratory mediation analysis; gender; Gleason score; health literacy; human; major clinical study; male; middle aged; patient care; patient decision making; patient preference; priority journal; prostate cancer; prostatectomy; race difference; randomized controlled trial; reading; secondary analysis; statistical analysis; urologist; veteran

Erratum regarding missing Declaration of Competing Interest statements in previously published articles (Contemporary Clinical Trials Communications (2019) 16, (S2451865419302236), (10.1016/j.conctc.2019.100461)) (Contemporary Clinical Trials Communications, 2020)
Declaration of Competing Interest statements were not included in the published version of the following articles that appeared in previous issues of Contemporary Clinical Trials Communications. The appropriate Declaration/Competing Interest statements, provided by the Authors, are included below. 1. “Intestinal-level anti-inflammatory bioactivities of catechin-rich green tea: Rationale, design, and methods of a double-blind, randomized, placebo-controlled crossover trial in metabolic syndrome and healthy adults” [Contemporary Clinical Trials Communications, 2019; 17: 100495] https://doi.org/10.1016/j.conctc.2019.100495 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.2. “Trauma Management Therapy and Prolonged Exposure Therapy for PTSD in an active duty sample: Design and methodology of a randomized clinical trial” [Contemporary Clinical Trials Communications, 2019; 17: 100491] https://doi.org/10.1016/j.conctc.2019.100491 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.3. “Virtual reality for pain management in patients with heart failure: Study rationale and design” [Contemporary Clinical Trials Communications, 2019; 16: 100470] https://doi.org/10.1016/j.conctc.2019.100470 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.4. “Recruitment and retention of families interested in a parent-based pediatric obesity intervention” [Contemporary Clinical Trials Communications, 2019; 16: 100467] https://doi.org/10.1016/j.conctc.2019.100467 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.5. “2D (2 Dimensional) TEQR design for Determining the optimal Dose for safety and efficacy” [Contemporary Clinical Trials Communications, 2019; 16: 100461] https://doi.org/10.1016/j.conctc.2019.100461 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.6. “Design of a novel digital intervention to promote healthy weight management among postpartum African American women” [Contemporary Clinical Trials Communications, 2019; 16: 100460] https://doi.org/10.1016/j.conctc.2019.100460 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.7. “Integrating smartphone technology, social support and the outdoor built environment to promote community-based aerobic and resistance-based physical activity: Rationale and study protocol for the ‘ecofit’ randomized controlled trial” [Contemporary Clinical Trials Communications, 2019; 16: 100457] https://doi.org/10.1016/j.conctc.2019.100457 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.8. “Qualitative analysis of COACH: A community-based behavioral intervention to reduce obesity health disparities within a marginalized community” [Contemporary Clinical Trials Communications, 2019; 16: 100452] https://doi.org/10.1016/j.conctc.2019.100452 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.9. “Statistical considerations for testing an AI algorithm used for prescreening lung CT images” [Contemporary Clinical Trials Communications, 2019; 16: 100434] https://doi.org/10.1016/j.conctc.2019.100434 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.10. “Study protocol: Randomized controlled trial of web-based decision support tools for high-risk women and healthcare providers to increase breast cancer chemoprevention” [Contemporary Clinical Trials Communications, 2019; 16: 100433] https://doi.org/10.1016/j.conctc.2019.100433 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.11. “Bayesian adaptive randomization trial of intravenous ketamine for veterans with late-life, treatment-resistant depression” [Contemporary Clinical Trials Communications, 2019; 16: 100432] https://doi.org/10.1016/j.conctc.2019.100432 Declaration of competing interest: The authors declare the following financial interests/personal relationships which may be considered as potential competing interests: Dr. Sanjay Mathew has served as a consultant to Allergan, Alkermes, Bracket, Clexio Biosciences, Janssen, Perception Neurosciences, and Sage Therapeutics. He has served as a co-investigator for clinical trials funded by NeuroRx and Janssen and has received research support from Biohaven Pharmaceuticals and VistaGen Therapeutics. Dr. Marijn Lijffijt has served as principal investigator for trials funded by NeuroRx and Vistagen Therapeutics.12. “A descriptive research: Exclusion from submitted clinical data package in the review process of new drug approval due to GCP violation in Japan” [Contemporary Clinical Trials Communications, 2019; 15: 100416] https://doi.org/10.1016/j.conctc.2019.100416 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.13. “Ultrafiltration-profiled hemodialysis to reduce dialysis-related cardiovascular stress: Study protocol for a randomized controlled trial” [Contemporary Clinical Trials Communications, 2019; 15: 100415] https://doi.org/10.1016/j.conctc.2019.100415 Declaration of competing interest: In the last 3 years, JEF has received speaking honoraria from American Renal Associates, the American Society of Nephrology, Dialysis Clinic, Inc., the National Kidney Foundation, and multiple universities. JEF is on the medical advisory board of NxStage Medical, Inc. and has received consulting fees from Fresenius Medical Care, North America and AstraZeneca. In the last 3 years, MMA has received investigator-initiated research funding from the Renal Research Institute, a subsidiary of Fresenius Medical Care, North America and honoraria from the International Society of Nephrology. The remaining authors have no competing interests.14. “Efficacy of smoking cessation with varenicline plus counselling for e-cigarettes users (VAREVAPE): A protocol for a randomized controlled trial” [Contemporary Clinical Trials Communications, 2019; 15: 100412] https://doi.org/10.1016/j.conctc.2019.100412 Declaration of competing interest: “The authors declare the following financial interests/personal relationships which may be considered as potential competing interests: PC is fixed-term researcher at University of Catania, Italy and won the 2015 unrestricted grant from Pfizer,GRAND, Global Research Award for Nicotine Dependence, that as declared in the text support this study. MM is fixed-term researcher at Centro per la Prevenzione e Cura del Tabagismo, University of Catania. In relation to his work in the area of tobacco control and respiratory diseases, P has received lecture fees and research funding from Pfizer, Inc., GlaxoSmithKline plc, CV Therapeutics, NeuroSearch A/S, Sandoz, MSD, Boehringer Ingelheim, Novartis, Duska Therapeutics, and Forest Laboratories. He has also served as a consultant for Pfizer, Inc., Global Health Alliance for treatment of tobacco dependence, CV Therapeutics, NeuroSearch A/S, Boehringer Ingelheim, Duska Therapeutics, Forest Laboratories, ECITA (Electronic Cigarette Industry Trade Association, in the UK), and Health Diplomat (consulting company that delivers solutions to global health problems with special emphasis on harm minimization). Lecture fees from a number of European EC industry and trade associations (including Fédération Interprofessionnelle de la VAPE in France and Federazione Italiana Esercenti Svapo Elettronico in Italy) were directly donated to vaper advocacy no-profit organizations. He is currently Head of the European Technical Committee for standardization on “Requirements and test methods for emissions of electronic cigarettes” (CEN/TC 437; WG4). He is also founder of the Center of Excellence for the acceleration of Harm Reduction at the University of Catania (CoEHAR), which has received a grant from the Foundation for a Smoke Free World to support 8 independent investigator-initiated research projects on tobacco harm reduction, and scientific advisor for LIAF, Lega Italiana Anti Fumo (Italian acronym for Italian Anti- Smoking League). The other authors have no conflict of interests to declare.15. “Recruitment challenges in stroke neurorecovery clinical trials” [Contemporary Clinical Trials Communications, 2019; 15: 100404] https://doi.org/10.1016/j.conctc.2019.100404 Declaration of competing interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.
Keywords: erratum

Screening strategies for the detection of anal high-grade squamous intraepithelial lesions in women living with HIV - Chiao, E.Y.; Lensing, S.Y.; Wiley, D.J.; Deshmukh, A.A.; Lee, J.; Darragh, T.M.; Einstein, M.H.; Jay, N.; Berry-Lawhorn, J.M.; Palefsky, J.M.; Wilkin, T.; Barroso, L.F.; et al. (AIDS (London, England), 2020)
OBJECTIVE: HIV-infected women (WLHIV) have more than 10-fold higher risk for squamous cell cancer of the anus. Experts suggest cytology-based strategies developed for cervical cancer screening may prevent anal cancer by detecting anal cytologic or histological high-grade squamous intraepithelial lesion (hHSIL) for treatment. Currently, there is no consensus on anal-hHSIL screening strategies for WLHIV. DESIGN: Between 2014 and 2016, 276 WLHIV were recruited at 12 US AIDS Malignancy Consortium clinical trials sites to evaluate hHSIL prevalence and (test) screening strategies. METHODS: Participants completed detailed questionnaire, underwent anal assessments including high-risk human papillomavirus (hrHPV) testing using hrHPV-Hybrid Capture 2 (HC2) and hrHPV-APTIMA, anal cytology, and concurrent high-resolution anoscopy. Screening test characteristics for predicting hHSIL validated by central review of histologic diagnosis were estimated sensitivity, specificity, positive predictive value, and false-omission rate. Paired analyses compared sensitivity and specificity for hrHPV single tests to anal cytology alone. RESULTS: 83% (229/276) of enrolled WLHIV had complete anal assessment data and were included in this analysis. Mean age was 50, 62% black and 60 (26%) had hHSIL. Anal cyotology (>atypical squamous cells of undetermined significance), hrHPV-HC2, and hrHPV-APTIMA sensitivity estimates were similarly high (83, 77, and 75%, respectively, P values > 0.2). Specificity was higher for both hrHPV-APTIMA and hrHPV-HC2 compared with anal cytology (67 vs. 50%, P < 0.001) and (61 vs. 50%, P = 0.020), respectively. CONCLUSION: Anal hrHPV testing demonstrated similar sensitivity for anal cytology (>atypical squamous cells of undetermined significance) to predict anal hHSIL. Among tests with similar sensitivity, the specificity was significantly higher for hrHPV-APTIMA and hrHPV-HC2. Thus, anal hrHPV testing may be an important alternative strategy to anal cytology for anal hHSIL screening among WLHIV.
Keywords: anus tumor; early cancer diagnosis; female; human; Human immunodeficiency virus infection; middle aged; papillomavirus infection; pathology; virology

Characteristics Associated with Participation in ENGAGED 2 - A Web-based Breast Cancer Risk Communication and Decision Support Trial - Wernli, K.J.; Bowles, E.A.; Knerr, S.; Leppig, K.A.; Ehrlich, K.; Gao, H.; Schwartz, M.D.; O'Neill, S.C. (The Permanente journal, 2020)
PURPOSE: We evaluated demographic and clinical characteristics associated with participation in a clinical trial testing the efficacy of an online tool to support breast cancer risk communication and decision support for risk mitigation to determine the generalizability of trial results. METHODS: Eligible women were members of Kaiser Permanente Washington aged 40-69 years with a recent normal screening mammogram, heterogeneously or extremely dense breasts and a calculated risk of > 1.67% based on the Breast Cancer Surveillance Consortium 5-year breast cancer risk model. Trial outcomes were chemoprevention and breast magnetic resonance imaging by 12-months post-baseline. Women were recruited via mail with phone follow-up using plain language materials notifying them of their density status and higher than average breast cancer risk. Multivariable logistic regression calculated independent odds ratios (ORs) for associations between demographic and clinical characteristics with trial participation. RESULTS: Of 2,569 eligible women contacted, 995 (38.7%) participated. Women with some college (OR = 1.99, 95% confidence interval [CI] 1.34-2.96) or college degree (OR = 3.35, 95% CI 2.29-4.90) were more likely to participate than high school-educated women. Race/ethnicity also was associated with participation (African-American OR = 0.50, 95% CI 0.29-0.87; Asian OR = 0.22, 95% CI 0.12-0.41). Multivariate adjusted ORs for family history of breast/ovarian cancer were not associated with trial participation. DISCUSSION: Use of plain language and potential access to a website providing personal breast cancer risk information and education were insufficient in achieving representative participation in a breast cancer prevention trial. Additional methods of targeting and tailoring, potentially facilitated by clinical and community outreach, are needed to facilitate equitable engagement for all women.
Keywords: adult; African American; article; breast cancer; cancer prevention; cancer risk; chemoprophylaxis; clinical evaluation; clinical feature; controlled study; decision support system; demography; ethnicity; family history; female; follow up; high school; human; language; major clinical study; mammography; nuclear magnetic resonance imaging; ovary cancer; race; risk assessment; Washington

Race-dependent differences in risk, genomics, and Epstein-barr virus exposure in monoclonal gammopathies: Results of SWOG S0120 - Dhodapkar, M.V.; Sexton, R.; Hoering, A.; van Rhee, F.; Barlogie, B.; Orlowski, R. (Clinical Cancer Research, 2020)
Purpose: Risk of multiple myeloma is increased in African American (AA) populations compared with European American (EA) cohorts. Current estimates of risk of progression of monoclonal gammopathy of undetermined significance (MGUS) are based largely on studies in EA cohorts. Prospective analyses of this risk in AA cohorts are lacking. Patients and Methods: Between 2003 and 2011, 331 eligible patients with IgG/A monoclonal gammopathy were enrolled in a prospective observational trial (SWOG S0120). Results: Of 331 eligible patients, 57 (17%) were of AA descent. The risk of transformation to clinical malignancy in AA patients was significantly lower than in non-AA cohort (2-year risk 5% vs. 15%; 5-year risk 13% vs. 24%; log-rank P ¼ 0.047). Differences in risk were evident for both MGUS and asymptomatic multiple myeloma. Gene expression profile (GEP) of CD138-purified plasma cells revealed that all molecular multiple myeloma subsets can be identified in both cohorts. However, the proportion of patients with high-risk GEP risk score (GEP-70 gene risk > -0.26) was lower in the AA cohort (0% vs. 33%, P ¼ 0.01). AA cohorts also have higher levels of antibodies against Epstein-Barr nuclear antigen-1 (EBNA-1; P < 0.001). Conclusions: These data provide the first prospective evidence that multiple myeloma precursor states in AA patients may have lower risk of disease compared with non-AA counterparts with lower incidence of high-risk GEP and increased EBV seropositivity. Race-dependent differences in biology and clinical risk of gammopathy may impact optimal management of these patients.
Keywords: adult; American; article; cancer patient; cohort analysis; controlled study; Epstein Barr virus; female; gene expression profiling; genomics; human; human cell; incidence; major clinical study; male; monoclonal immunoglobulinemia; multiple myeloma; nonhuman; prospective study; protein expression; race; risk assessment; endogenous compound; Epstein Barr virus antigen 1; immunoglobulin G; syndecan 1

A population-based study of invitation to and participation in clinical trials among women with early-stage breast cancer - Patel, M.A.; Shah, J.L.; Abrahamse, P.H.; Jagsi, R.; Katz, S.J.; Hawley, S.T.; Veenstra, C.M. (Breast Cancer Research and Treatment, 2020)
Purpose: Although many studies clearly demonstrate disparities in cancer clinical trial enrollment, there is a lack of consensus on potential causes. Furthermore, virtually nothing is known about associations between patients’ decision-making style and their participation in clinical trials. Methods: Women with newly diagnosed, stage 0–II breast cancer reported to the Georgia and Los Angeles County Surveillance, Epidemiology, and End Results (SEER) registries in 2013–2014 were surveyed approximately seven months after diagnosis. We investigated two primary outcome variables: (1) invitation to participate in a clinical trial, (2) participation in a clinical trial. We evaluated bivariate associations using Chi-squared tests and used multivariable logistic regression models to investigate associations between patient variables, including decision-making style, and the primary outcomes. Results: 2578 patients responded (71% response rate); 30% were > age 65, 18% were black, 18% were Latina, 29% had ≤ high school education. 10% of patients reported invitation to participate in a clinical trial; 5% reported participation in a clinical trial. After adjustment younger age, receipt of chemotherapy or radiation, disease stage, and a more rational (versus more intuitive) decision-making style were associated with a higher odds of invitation to participate. Being married was associated with a higher odds of participation; having an annual family income ≥ $40,000 was associated with a lower odds of participation. Conclusions: 10% of patients reported invitation to participate in a clinical trial, and half of these reported participation. Invitation to participate varied by age and decision-making style, and participation varied by marital status and income.
Keywords: adult; age; aged; article; breast cancer; cancer chemotherapy; cancer radiotherapy; cancer registry; cancer staging; clinical decision making; clinical outcome; clinical trial; clinical trial (topic); cohort analysis; educational status; family income; female; health disparity; health survey; human; major clinical study; marriage; mastectomy; outcome variable; patient participation; population research; priority journal; questionnaire; tumor volume

Increasing accrual of minority patients in breast cancer clinical trials - Trant, A.A.; Walz, L.; Allen, W.; DeJesus, J.; Hatzis, C.; Silber, A. (Breast Cancer Research and Treatment, 2020)
Background: Black and Hispanic patients participate in clinical trials at lower rates than white patients nationally; lack of diversity in clinical trials prevents appropriate safety and efficacy testing of new treatments in these populations. Methods: The Oncology Welcomes New Haven into Trials (OWN IT) initiative at the Yale Cancer Center used a multi-tiered approach to improve breast cancer minority clinical trial accrual through community focus groups, ongoing community outreach, institutional executive council representation, grand rounds presentation, and didactic lectures with healthcare providers. Eligibility criteria of breast cancer trials at Smilow Cancer Center were reviewed using clinicaltrials.gov. Also, an anonymous, 5-min survey was conducted at regular visits with Smilow Breast Center patients to gauge awareness of and access to clinical trials. Survey data were compared to the Yale Cancer Center Clinical Trials Office, Connecticut Tumor Registry, and U.S. Census records. Two-tailed Fisher’s tests were used for all analyses. Results: There was a significant increase in the number of minority patients who participated in clinical trials at Smilow Cancer Center from 2016 (95/750) to 2018 (155/944) (p = 0.0325). Two hundred patients participated in the survey; response rate 92%. There was no significant difference in the rate at which patients were invited to participate in clinical trials or the rate at which they declined to participate based on race or ethnicity. Black and Hispanic patients were significantly less likely to be aware of clinical trials than white patients (p <.001). The review of eligibility criteria showed that over half of the studies reviewed had restrictions regarding increased liver function tests, and many restricted the participation of patients with other chronic conditions. Conclusions: Low participation in clinical trials among black and Hispanic patients is likely multifaceted. This study indicated that there are likely structural factors at work which can be modified with institutional effort. The role of patient education regarding clinical trials and accrual should be studied further as should eligibility criteria as a potential barrier to participation.
Keywords: adult; aged; article; Black person; breast cancer; chronic disease; clinical trial (topic); health care disparity; health survey; Hispanic; human; liver function test; minority group; patient participation; priority journal; race

A novel CNN algorithm for pathological complete response prediction using an I-SPY TRIAL breast MRI database - Liu, M.Z.; Mutasa, S.; Chang, P.; Siddique, M.; Jambawalikar, S.; Ha, R. (Magnetic Resonance Imaging, 2020)
Purpose: To apply our convolutional neural network (CNN) algorithm to predict neoadjuvant chemotherapy (NAC) response using the I-SPY TRIAL breast MRI dataset. Methods: From the I-SPY TRIAL breast MRI database, 131 patients from 9 institutions were successfully downloaded for analysis. First post-contrast MRI images were used for 3D segmentation using 3D slicer. Our CNN was implemented entirely of 3 × 3 convolutional kernels and linear layers. The convolutional kernels consisted of 6 residual layers, totaling 12 convolutional layers. Dropout with a 0.5 keep probability and L2 normalization was utilized. Training was implemented by using the Adam optimizer. A 5-fold cross validation was used for performance evaluation. Software code was written in Python using the TensorFlow module on a Linux workstation with one NVidia Titan X GPU. Results: Of 131 patients, 40 patients achieved pCR following NAC (group 1) and 91 patients did not achieve pCR following NAC (group 2). Diagnostic accuracy of our CNN two classification model distinguishing patients with pCR vs non-pCR was 72.5 (SD ± 8.4), with sensitivity 65.5% (SD ± 28.1) and specificity of 78.9% (SD ± 15.2). The area under a ROC Curve (AUC) was 0.72 (SD ± 0.08). Conclusion: It is feasible to use our CNN algorithm to predict NAC response in patients using a multi-institution dataset.
Keywords: laboratory software; NVidia Titan X GPU; Pythonidae; radiology workstation; TensorFlow module; adult; African American; Alaska Native; American Indian; area under the curve; article; Asian; brain size; breast cancer; Caucasian; controlled study; convolutional neural network; diagnostic accuracy; diagnostic test accuracy study; dynamic contrast-enhanced magnetic resonance imaging; histogram; human; institutional review; learning algorithm; major clinical study; middle aged; nuclear magnetic resonance imaging; Pacific Islander; prediction; priority journal; probability; NVidia Titan X GPU; Python; TensorFlow module

Physiologic vasomotor symptoms are associated with verbal memory dysfunction in breast cancer survivors - Fogel, J.; Rubin, L.H.; Kilic, E.; Walega, D.R.; Maki, P.M. (Menopause (New York, N.Y.), 2020)
OBJECTIVE: Vasomotor symptoms (VMS), sleep disturbance, and cognitive complaints are common among women with a history of breast cancer and contribute to decreased quality of life. Studies in healthy women showed an association between verbal memory performance and physiologic VMS measured with ambulatory skin conductance monitors but not with VMS by self-report. We hypothesized that we would find a similar association in women with breast cancer. METHODS: Participants included 30 female breast cancer survivors (mean age 52.7 y; 26.7% African-American) with moderate-to-severe VMS enrolled in a larger clinical trial of a nonhormonal intervention for VMS. At baseline, participants completed assessments of physiologic VMS, actigraphy-based assessments of sleep, questionnaires about mood, and two tests of verbal memory - Logical Memory (LM) and the California Verbal Learning Test (CVLT). Using baseline data, we conducted multivariate regression analyses to examine the association between VMS and memory, controlling for sleep and other factors. RESULTS: On average, women reported 46% of total physiologic VMS. A higher frequency of physiologic VMS - but not reported VMS - was significantly associated with lower scores on the California Verbal Learning Test short-delay free recall (r[28] = -0.41, P = 0.03), long-delay free recall (r[28] = -0.42, P = 0.03), and total clustering, (r[28] = -0.39, P = 0.04). These associations were independent of sleep, mood, and other factors. CONCLUSIONS: Independent of their effect on sleep, VMS may be a modifiable contributor to memory difficulties in women with breast cancer. These findings underscore the importance of objective measurement of VMS in cognitive studies. : Video Summary:http://links.lww.com/MENO/A623.
Keywords: actimetry; adult; African American; amnesia; article; breast cancer; California verbal learning test; cancer survival; cancer survivor; controlled study; female; human; middle aged; mood; questionnaire; sleep; verbal memory; videorecording

A Multi-faceted Intervention Aimed at Black-White Disparities in the Treatment of Early Stage Cancers: The ACCURE Pragmatic Quality Improvement trial - Cykert, S.; Eng, E.; Manning, M.A.; Robertson, L.B.; Heron, D.E.; Jones, N.S.; Schaal, J.C.; Lightfoot, A.; Zhou, H.; Yongue, C.; Gizlice, Z. (Journal of the National Medical Association, 2020)
Background: Reports continue to show that Blacks with curable lung or breast cancer complete treatment less often than similar Whites contributing to worse survival. ACCURE is an intervention trial designed to address this problem. Patients and methods: A pragmatic, quality improvement trial comparing an intervention group to retrospective and concurrent controls. Patients with early stage breast or lung cancer aged 18 to 85 were enrolled (N = 302) at 2 cancer centers between April 2013 and March 2015 for the intervention component. Data from patients seen between January 2007 and December 2012 with these diagnoses were obtained to establish control completion rates. Concurrent data for non-study patients were used to identify secular trends. The intervention included: a real time registry derived from electronic health records of participants to signal missed appointments or unmet care milestones, a navigator, and clinical feedback. The primary outcome was “Treatment Complete”, a composite variable representing completion of surgery, recommended radiation and chemotherapy for each patient. Results: The mean age in the intervention group was 63.1 years; 37.1% of patients were Black. Treatment completion in retrospective and concurrent controls showed significant Black-White differences (Blacks (B) 79.8% vs. Whites (W) 87.3%, p < 0.001; 83.1% B vs. 90.1% W, p < 0.001, respectively). The disparity lessened within the intervention (B 88.4% and W 89.5%, p = 0.77). Multivariate analyses confirmed disparities reduction. OR for Black-White disparity within the intervention was 0.98 (95% CI 0.46–2.1); Black completion in the intervention compared favorably to Whites in retrospective (OR 1.6; 95% CI 0.90–2.9) and concurrent (OR 1.1; 95% CI 0.59–2.0) controls. Conclusion: A real time registry combined with feedback and navigation improved completion of treatment for all breast and lung cancer patients and narrowed disparities. Similar multi-faceted interventions could mitigate disparities in the treatment of other cancers and chronic conditions.
Keywords: adult; aged; article; Black person; breast cancer; cancer center; cancer patient; cancer staging; Caucasian; chemoradiotherapy; chronic disease; controlled study; drug therapy; electronic health record; female; human; intervention study; lung cancer; major clinical study; middle aged; multicenter study; outcome assessment; racism; radiation; total quality management; isotretinoin

Subtype-specific risk factors for postmenopausal breast cancer: findings from the PLCO trial - Abdel-Rahman, O.; Tang, P.A.; Cheung, W.Y. (Clinical and Translational Oncology, 2020)
Objective: The aim of this analysis is to evaluate the relative weight of different epidemiological risk factors on the development of different breast cancer subtypes (i.e. luminal, Her2+ overexpressed or triple negative). Methods: De-identified datasets of female participants recruited within the Prostate, Lung, Colorectal, and Ovarian (PLCO) trial were accessed. Multivariate Cox regression analysis was utilized to assess factors affecting the development of breast cancer (regardless of subtype). Additional multivariate analyses were conducted to assess factors affecting the development of the three principal subtypes of breast cancer (ER+/Her2− breast cancer; Her2 overexpressed breast cancer and ER−/Her2− breast cancer). Results: A total of 73,570 eligible participants were evaluated in the current analysis of which 2370 participants subsequently developed breast cancer. The following factors were associated with a higher risk of ER+/Her2− breast cancer: white race (P < 0.001), nulliparity (P < 0.001), higher body mass index (P = 0.003), prior exposure to hormone treatment (P = 0.004) and breast cancer in first-degree female relatives (P < 0.001). The following factors were associated with a higher risk of Her2 overexpressed breast cancer: prior exposure to hormone treatment (P = 0.002) and breast cancer in first-degree female relatives (P = 0.001). The following factors were associated with a higher risk of ER−/Her2− breast cancer: black race (P = 0.013), younger age (P = 0.017) and breast cancer in first-degree female relatives (P 0.023). Conclusions: There is considerable heterogeneity in risk factors among patients with different subtypes of breast cancer. In particular, factors associated with high estrogen levels seem to be associated with luminal breast cancer rather than other breast cancer subtypes.
Keywords: epidermal growth factor receptor 2; estrogen; estrogen receptor; progesterone receptor; adult; article; body mass; breast cancer; cancer growth; cancer mortality; cancer prognosis; cancer risk; cancer screening; cancer staging; cohort analysis; colorectal cancer; female; histology; hormonal therapy; human; lung cancer; major clinical study; nullipara; obesity; ovary cancer; overall survival; postmenopause; prostate cancer; risk factor

Racial/ethnic disparities and survival characteristics in non-pancreatic gastrointestinal tract neuroendocrine tumors - Goksu, S.Y.; Ozer, M.; Beg, M.S.; Sanford, N.N.; Ahn, C.; Fangman, B.D.; Goksu, B.B.; Verma, U.; Sanjeevaiah, A.; Hsiehchen, D.; Jones, A.L.; Kainthla, R.; et al. (Cancers, 2020)
Background: We studied the effect of race and ethnicity on disease characteristics and survival in gastrointestinal neuroendocrine tumors. Methods: The Surveillance, Epidemiology, and End Results database was used to select patients with non-pancreatic gastrointestinal neuroendocrine tumors diagnosed between 2004 and 2015. Trends in survival were evaluated among three groups: Hispanic, non-Hispanic White, and non-Hispanic Black. Kaplan–Meier and Cox regression methods were performed to calculate overall survival and cause-specific survival after adjusting for patient and tumor characteristics. Results: A total of 26,399 patients were included in the study: 65.1% were non-Hispanic White, 19.9% were non-Hispanic Black, and 15% were Hispanic. Non-Hispanic White patients were more likely to be male (50.0%, p < 0.001), older than 60 years (48.0%, p < 0.001), and present with metastatic disease (17.7%, p < 0.001). Non-Hispanic White patients had small intestine neuroendocrine tumors, while Hispanic and non-Hispanic Black patients had rectum neuroendocrine tumors as the most common primary site. Hispanic patients had better overall survival, while non-Hispanic Black patients had better cause-specific survival versus non-Hispanic White patients. This finding was confirmed on multivariable analysis where Hispanic patients had improved overall survival compared to non-Hispanic White patients (Hazard ratio (HR): 0.89 (0.81–0.97)), whereas non-Hispanic Black patients had better cause-specific survival compared to non-Hispanic White patients (HR: 0.89 (0.80–0.98)). Conclusions: Race/ethnicity is an independent prognostic factor in patients with gastrointestinal neuroendocrine tumors.
Keywords: adult; age; appendix tumor; article; Black person; cancer diagnosis; cancer epidemiology; cancer prognosis; cancer staging; cancer survival; Caucasian; cause specific survival; clinical feature; cohort analysis; colon tumor; controlled study; data base; esophagus tumor; ethnic difference; female; gastrointestinal tumor; gender; health disparity; Hispanic; human; major clinical study; male; middle aged; neuroendocrine tumor; outcome assessment; overall survival; pancreas islet cell tumor; patient selection; race difference; rectum tumor; retrospective study; small intestine tumor; stomach tumor; survival analysis; trend study; tumor localization; tumor volume

A phase I/II study of docetaxel in combination with pegylated liposomal doxorubicin in metastatic castration-resistant prostate cancer - Laber, D.A.; Eatrides, J.; Jaglal, M.V.; Haider, M.; Visweshwar, N.; Patel, A. (Medical Oncology, 2020)
Taxanes and anthracyclines have been among the best-studied chemotherapy classes in castration-resistant prostate cancer (CRPC). Docetaxel (D) 75 mg/m2 every 3 weeks has been the standard first line chemotherapy for CRPC. Encapsulation of doxorubicin in polyethylene glycol-coated liposomes (PLD) was developed to enhance the safety and efficacy of conventional doxorubicin. We hypothesize that the combination of weekly low dose-D and PLD would result in a high response rate and low toxicity. Eligibility criteria included metastatic progressive CRPC, no prior D or PLD and good organ function. After a short phase I with no dose-limiting toxicity, D 30 mg/m2 was administered on days 1, 8 and 15; and PLD 30 mg/m2 on day 1 only, every 28 days. Thirty-seven patients were enrolled. The PSA response rate was 53%. Twenty-two subjects had measurable disease; one (5%) achieved complete response, five (23%) partial response, and twelve (54%) stable disease. Twenty-seven patients (73%) manifested pain relief. The median time to progression was 3.7 months for all patients and 7.9 months for responders. Median overall survival was 16.3 months. Grade 4 neutropenia without infection and anemia occurred in 1 patient each. Grade 3 treatment-related toxicities included: 15% fatigue; 9% neutropenia, anemia and nausea; 6% dehydration and hand-foot syndrome; and 3% infection, febrile neutropenia, thrombosis, stomatitis, headache, vomiting, weight loss and weakness. In this non-comparative study D-PLD demonstrated a higher activity than previously reported with single agent D with favorable side effect profile. A phase 3 study would be needed to evaluate the true benefit of this combination. ClinicalTrials.gov Identifier: NCT00456989.
Keywords: NCT00456989; docetaxel; doxorubicin; prostate specific antigen; adult; African American; aged; alopecia; analgesia; anemia; anorexia; article; bleeding; body weight disorder; body weight loss; cancer radiotherapy; cancer surgery; castration resistant prostate cancer; Caucasian; clinical article; confusion; dehydration; disease exacerbation; drug efficacy; drug safety; edema; fatigue; febrile neutropenia; fever; follow up; hand foot syndrome; headache; human; infection; low drug dose; male; metastasis; nail disease; nausea; neutropenia; orchiectomy; overall survival; peripheral neuropathy; phase 1 clinical trial; phase 2 clinical trial; priority journal; prostate adenocarcinoma; prostatectomy; stomatitis; thrombocytopenia; thrombosis; vomiting; weakness

The Problem of Underrepresentation: Black Participants in Lifestyle Trials Among Patients with Prostate Cancer - Zuniga, K.B.; Borno, H.; Chan, J.M.; Van Blarigan, E.L.; Friedlander, T.W.; Wang, S.; Zhang, L.; Kenfield, S.A. (Journal of racial and ethnic health disparities, 2020)
INTRODUCTION: Healthy lifestyle behaviors are an essential component of prostate cancer survivorship; however, it is unknown whether Black participants are adequately represented in randomized controlled trials (RCTs) on lifestyle interventions. The goal of this study was to identify types of lifestyle RCTs that may require improved recruitment resources to enhance generalizability of lifestyle recommendations to Black patients. MATERIALS AND METHODS: ClinicalTrials.gov was used to identify lifestyle RCTs among patients with prostate cancer. Using racial distribution data from the Surveillance, Epidemiology, and End Results (SEER) program as a reference, one-sample proportion tests were performed to assess adequate recruitment of Black participants. RESULTS: Of 31 lifestyle trials, one trial reported race-specific results. Proportion of Black participants was acquired from 26 trials. Compared to the US population, Black participants were overrepresented in the overall study population (17% versus 15%, p = 0.019). Black participants were underrepresented in trials exploring exercise interventions (9% versus 15%, p = 0.041), trials among patients with advanced disease (9% versus 16%, p < 0.001), and in university-funded trials (12% versus 15%, p = 0.026). CONCLUSIONS: The reporting of race data, and race-specific results when feasible, is essential for clinicians to accurately generalize findings from lifestyle trials. Additional resources may be necessary to aid in strategic recruitment of Black participants for trials on exercise interventions, trials among patients with advanced disease, and in university-funded trials.
Keywords: adult; advanced cancer; African American; article; cancer patient; controlled study; diet; exercise; human; human tissue; lifestyle; male; prostate cancer; race; randomized controlled trial (topic); systematic review

Accelerated Epigenetic Aging and Methylation Disruptions Occur in Human Immunodeficiency Virus Infection Prior to Antiretroviral Therapy - Yang, C.X.; Schon, E.; Obeidat, M.; Kobor, M.S.; McEwen, L.; MacIsaac, J.; Lin, D.; Novak, R.M.; Hudson, F.; Klinker, H.; Dharan, N.; Horvath, S.; et al. (The Journal of infectious diseases, 2020)
BACKGROUND: Whether accelerated aging develops over the course of chronic HIV infection or can be observed prior to significant immunosuppression on is unknown. We studied DNA methylation in blood to estimate cellular aging in persons living with HIV (PLWH) prior to the initiation of antiretroviral therapy. METHODS: 378 antiretroviral therapy-naïve PLWH with CD4 T cell counts >500 cells/mm 3 enrolled in the Strategic Timing of Antiretroviral Therapy trial (Pulmonary Substudy) were compared to 34 HIV-negative controls. DNA methylation was performed using the Illumina MethylationEPIC BeadChip. Differentially methylated positions (DMPs) and regions (DMRs) in PLWH compared to controls were identified using a robust linear model. Methylation age was calculated using a previously described epigenetic clock. RESULTS: There were a total of 56,639 DMPs and 6,103 DMRs at a false discovery rate<0.1. The top 5 DMPs corresponded to genes NLRC5, VRK2, B2M, and GPR6 and were highly enriched for cancer-related pathways. PLWH had significantly higher methylation age compared to HIV-negative controls (p=0.001), with black race, low CD4, high CD8 T cell counts, and duration of HIV being risk factors for age acceleration. CONCLUSIONS: PLWH prior to the initiation of antiretroviral therapy and with preserved immune status show evidence of advanced methylation aging.
Keywords: acceleration; adult; antiretroviral therapy; article; Black person; CD4 lymphocyte count; CD8 lymphocyte count; cell aging; controlled study; DNA methylation; epigenetics; female; human; Human immunodeficiency virus infected patient; Human immunodeficiency virus infection; immune status; major clinical study; male; risk factor; tumor-related gene; CD4 antigen; endogenous compound

Genetic testing and surveillance of young breast cancer survivors and blood relatives: A cluster randomized trial - Katapodi, M.C.; Ming, C.; Northouse, L.L.; Duffy, S.A.; Duquette, D.; Mendelsohn-Victor, K.E.; Milliron, K.J.; Merajver, S.D.; Dinov, I.D.; Janz, N.K. (Cancers, 2020)
We compared a tailored and a targeted intervention designed to increase genetic testing, clinical breast exam (CBE), and mammography in young breast cancer survivors (YBCS) (diagnosed <45 years old) and their blood relatives. A two-arm cluster randomized trial recruited a random sample of YBCS from the Michigan cancer registry and up to two of their blood relatives. Participants were stratified according to race and randomly assigned as family units to the tailored (n = 637) or the targeted (n = 595) intervention. Approximately 40% of participants were Black. Based on intention-to-treat analyses, YBCS in the tailored arm reported higher self-efficacy for genetic services (p = 0.0205) at 8-months follow-up. Genetic testing increased approximately 5% for YBCS in the tailored and the targeted arm (p ≤ 0.001; p < 0.001) and for Black and White/Other YBCS (p < 0.001; p < 0.001). CBEs and mammograms increased significantly in both arms, 5% for YBCS and 10% for relatives and were similar for Blacks and White/Others. YBCS and relatives needing less support from providers reported significantly higher self-efficacy and intention for genetic testing and surveillance. Black participants reported significantly higher satisfaction and acceptability. Effects of these two low-resource interventions were comparable to previous studies. Materials are suitable for Black women at risk for hereditary breast/ovarian cancer (HBOC).
Keywords: adult; age distribution; article; Black person; blood relative; breast cancer; breast examination; cancer epidemiology; cancer registry; cancer risk; cancer survivor; Caucasian; controlled study; female; follow up; genetic screening; human; intention to treat analysis; major clinical study; mammography; Michigan; patient satisfaction; race difference; randomized controlled trial; sampling; self concept

The Impact of Primary Tumor Surgery on Survival in HER2 Positive Stage IV Breast Cancer Patients in the Current Era of Targeted Therapy - Mudgway, R.; Chavez de Paz Villanueva, C.; Lin, A.C.; Senthil, M.; Garberoglio, C.A.; Lum, S.S. (Annals of Surgical Oncology, 2020)
Objective: We sought to examine the impact of primary tumor resection on survival in HER2+ stage IV breast cancer patients in the era of HER2 targeted therapy. Methods: We conducted a retrospective cohort study of women with HER2+ stage IV breast cancer in the National Cancer Database from 2010 to 2012 comparing those who did and did not undergo definitive breast surgery. Results: Of 3231 patients, treatment included primary site surgery in 35.0%; chemo/targeted therapy in 89.4%; endocrine therapy in 37.7%; and radiation in 31.8%. Surgery was associated with Medicare/other government (OR 1.36, 95% CI 1.03–1.81) or private insurance (OR 1.93, 95% CI 1.53–2.42) versus none/Medicaid, radiation (OR 2.10, 95% CI 1.76–2.51), chemo/targeted therapy (OR 1.99, 95% CI 1.47–2.70), and endocrine therapy (OR 1.73, 95% CI 1.40–2.14). Non-Hispanic Black versus White patients (OR 0.68, 95% CI 0.53–0.87) were less likely to have surgery. Overall mortality was associated with insurance (Medicare/other government versus none/Medicaid, HR 0.36, p < 0.0001), receipt of chemo/targeted therapy (HR 0.76, p = 0.008), endocrine therapy (HR 0.70, p = 0.0006), and radiation therapy (HR 1.33, p = 0.0009), NH Black versus White race/ethnicity (HR 1.39, p = 0.002), visceral versus bone-only metastases (HR 1.44, p = 0.0003), and lowest versus highest income quartile (HR 1.36, p = 0.01). Propensity score analysis showed surgery was associated with improved survival versus no surgery (HR 0.56, 95% CI 0.40–0.77). Conclusions: Surgery of the primary site for metastatic HER2+ breast cancer is associated with improved overall survival in selected patients.
Keywords: NCT00941759; pertuzumab; trastuzumab; adult; article; bone metastasis; breast surgery; cancer hormone therapy; cancer mortality; cancer radiotherapy; cancer staging; cancer surgery; cancer survival; cancer therapy; cohort analysis; controlled study; female; health care quality; health insurance; human; human epidermal growth factor receptor 2 positive breast cancer; major clinical study; mastectomy; medicaid; medicare; modified radical mastectomy; patient selection; primary tumor; propensity score; prospective study; race difference; radical mastectomy; randomized controlled trial; retrospective study; simple mastectomy; systemic therapy

#BlackBreastsMatter: Process evaluation of recruitment and engagement of pregnant African American women for a social media intervention study to increase breastfeeding - Dauphin, C.; Clark, N.; Cadzow, R.; Saad-Harfouche, F.; Rodriguez, E.; Glaser, K.; Kiviniemi, M.; Keller, M.; Erwin, D. (Journal of Medical Internet Research, 2020)
Background: In the United States, there are lower rates of breastfeeding among African American mothers, particularly those who are younger women. Recent epidemiological studies have shown a strong association of more aggressive types of breast cancer (estrogen receptor negative) among African American women, with a higher risk in African American women who did not breastfeed their children. Objective: This study aims to describe the process evaluation of recruitment and educational strategies to engage pregnant African American participants for a pilot study designed to determine whether social media messaging about breast cancer risk reduction through breastfeeding may positively influence breastfeeding rates. Methods: This pilot study is conducted in collaboration with a local Women, Infants, and Children (WIC) organization and hospital and prenatal clinics of a local health care network. To engage African American women to enroll in the study, several methods and monitoring processes were explored, including WIC electronic text-based messages sent out to all phones of current WIC recipients (referred to as e-blasts); keyword responses to texts from flyers and posters in local community-based organizations, hospitals, and prenatal clinics; keyword responses using electronic links posted in established Facebook groups; and snowball recruitment of other pregnant women by current participants through Facebook. Once enrolled, participants were randomized to 2 study conditions: (1) an intervention group receiving messages about breast cancer risk reduction and breastfeeding or (2) a control group receiving breastfeeding-only messages. Data were obtained through electronic monitoring, SurveyMonkey, qualitative responses on Facebook, focus groups, and interviews. Results: More than 3000 text messages were sent and received through WIC e-blasts and keyword responses from flyers. A total of 472 women were recruited through WIC e-blast, and 161 responded to flyers and contacts through the local health care network, community-based organizations, Facebook, and friend referrals. A total of 633 women were assessed for eligibility to participate in the study. A total of 288 pregnant African American women were enrolled, consented, and completed presurvey assessments (102.8% of the goal), and 22 participants attended focus groups or interviews reporting on their experiences with Facebook and the educational messages. Conclusions: This process evaluation suggests that using electronic, smartphone apps with social media holds promise for both recruitment and conduct of health education intervention studies for pregnant African American women. Providing messaging and resources through social media to reinforce and educate women about breastfeeding and potentially provide lactation support is intriguing. Convenience (for researchers and participants) is an attribute of social media for this demographic of women and worthy of further research as an educational tool.
Keywords: NCT03680235; smartphone; adolescent; adult; African American; article; breast cancer; breast feeding; controlled study; female; health education; human; information processing; interview; major clinical study; patient referral; pilot study; pregnant woman; randomized controlled trial; recipient; risk reduction; social media; young adult

Feasibility and potential efficacy of commercial mHealth/eHealth tools for weight loss in African American breast cancer survivors: Pilot randomized controlled trial - Ferrante, J.M.; Devine, K.A.; Bator, A.; Rodgers, A.; Ohman-Strickland, P.A.; Bandera, E.V.; Hwang, K.O. (Translational Behavioral Medicine, 2020)
Weight management after breast cancer (BC) treatment in African American (AA) women is crucial to reduce comorbid conditions and health disparities. We examined feasibility and potential efficacy of commercial eHealth/mHealth tools for weight management in AA BC survivors in New Jersey. Participants (N = 35) were randomized to an intervention (SparkPeople) plus activity tracker, Fitbit Charge (n = 18), or wait-list active control group (Fitbit only, n = 17). Anthropometric, behavioral, and quality of life (QOL) outcomes were collected at baseline, 3, 6, and 12 months. Differences in outcomes were assessed using intent-to-treat analysis. Retention was 97.1%. Both groups lost weight, with no significant differences between groups. At month 6, mean weight change was: intervention: -1.71 kg (SD 2.33; p =. 006), 33.3% lost ≥3% of baseline weight; control: -2.54 kg (SD 4.00, p =. 002), 23.5% lost ≥3% weight. Intervention participants achieved significant improvements in waist circumference (-3.56 cm, SD 4.70, p =. 005), QOL (p =. 030), and use of strategies for healthy eating (p =. 025) and decreasing calories (p <. 001). Number of days logged food per week was associated with decreases in waist circumference at 6 months (β -0.79, 95% CI, -1.49, -0.09, p =. 030) and 12 months (β -2.16, 95% CI, -4.17, -0.15, p =. 038). Weight loss was maintained at 12 months. This is the first study to demonstrate potential efficacy of commercial eHealth/mHealth tools for weight loss in AA BC survivors, without additional counseling from the research team. If effective, they may be convenient weight loss tools that can be easily and widely disseminated. Clinical Trials registration: ClinicalTrials.gov NCT02699983.
Keywords: NCT02699983; activity tracker; Fitbig Alta; Fitbit Charge; adult; African American; article; body weight change; body weight loss; breast cancer; calorie; cancer survival; cancer survivor; clinical article; clinical effectiveness; controlled study; feasibility study; female; health disparity; human; New Jersey; outcome assessment; patient compliance; patient counseling; physical activity; pilot study; priority journal; quality of life; randomized controlled trial; telehealth; treatment outcome; waist circumference; weight loss program; Fitbig Alta; Fitbit Charge

Effect of a digital health intervention on decreasing barriers and increasing facilitators for colorectal cancer screening in vulnerable patients - Denizard-Thompson, N.M.; Miller, D.P.; Snavely, A.C.; Spangler, J.G.; Doug Case, L.; Weaver, K.E. (Cancer Epidemiology Biomarkers and Prevention, 2020)
Background: Colorectal cancer is the second leading cause of cancer-related death in the United States, in part, because one third of Americans fail to get screened. In a prior randomized controlled trial, we found that an iPad patient decision aid called Mobile Patient Technology for Health-CRC (mPATH-CRC) doubled the proportion of patients who completed colorectal cancer screening. Methods: All data for the current analysis were collected as part of a randomized controlled trial to determine the impact of mPATH-CRC on receipt of colorectal cancer screening within 24 weeks. Participants were enrolled from six community-based primary care practices between June 2014 and May 2016 and randomized to either usual care or mPATH-CRC. Six potential mediators of the intervention effect on screening were considered. The Iacobucci method was used to assess the significance of the mediation. Results: A total of 408 patients had complete data for all potential mediators. Overall, the potential mediators accounted for approximately three fourths (76.3%) of the effect of the program on screening completion. Perceived benefits, self-efficacy, ability to state a screening decision, and patient–provider discussion were statistically significant mediators. Patient–provider discussion accounted for the largest proportion of the effect of mPATH-CRC (70.7%). Conclusions: mPATH-CRC increased completion of colorectal cancer screening by affecting patient-level and system-level mediators. However, the most powerful mediator was the occurrence of a patient–provider discussion about screening. Digital interventions like mPATH-CRC are an important adjunct to the patient–provider encounter. Impact: Understanding the factors that mediated mPATH-CRC's success is paramount to developing other effective interventions.
Keywords: adult; African American; aged; article; cancer screening; colonoscopy; colorectal cancer; controlled study; female; health care delivery; health disparity; health literacy; health program; human; income; major clinical study; male; occult blood test; patient care; practice guideline; primary medical care; priority journal; randomized controlled trial; self concept; telephone interview; unemployment; vulnerable population

The impact of a randomized dietary and physical activity intervention on chronic inflammation among obese African-American women - Babatunde, O.A.; Arp Adams, S.; Truman, S.; Sercy, E.; Murphy, A.E.; Khan, S.; Hurley, T.G.; Wirth, M.D.; Choi, S.K.; Johnson, H.; Hebert, J.R. (Women & health, 2020)
Lifestyle interventions may reduce inflammation and lower breast cancer (BrCa) risk. This randomized trial assessed the impact of the Sistas Inspiring Sistas Through Activity and Support (SISTAS) study on plasma C-reactive protein (CRP), interleukin-6 (IL-6) and Dietary Inflammatory Index (DII). This unblinded, dietary and physical activity trial was implemented in 337 obese (body mass index [BMI] ≥30 kg/m2) African American (AA) women recruited between 2011 and 2015 in South Carolina through a community-based participatory approach with measurements at baseline, 3 months, and 12 months. Participants were randomized into either intervention (n = 176) or wait-list control group (n = 161). Linear mixed-effect models were used for analyses of CRP and IL-6. Baseline CRP was significantly higher in those with greater obesity, body fat percentage, and waist circumference (all p <.01). No difference was observed between groups for CRP or IL-6 at 3 or 12 months; however, improvements in diet were observed in the intervention group compared to the control group (p = .02) at 3 months but were not sustained at 12 months. Although the intervention was not successful at reducing levels of CRP or IL-6, a significant decrease was observed in DII score for the intervention group, indicating short-term positive dietary change.
Keywords: adult; African American; article; body fat; body mass; breast cancer; cancer risk; chronic inflammation; controlled study; diet; female; gene expression; human; human tissue; lifestyle; major clinical study; obesity; physical activity; protein expression; randomized controlled trial; South Carolina; waist circumference; C reactive protein; endogenous compound; interleukin 6

Physiologic vasomotor symptoms are associated with verbal memory dysfunction in breast cancer survivors - Fogel, J.; Rubin, L.H.; Kilic, E.; Walega, D.R.; Maki, P.M. (Menopause (New York, N.Y.), 2020)
OBJECTIVE: Vasomotor symptoms (VMS), sleep disturbance, and cognitive complaints are common among women with a history of breast cancer and contribute to decreased quality of life. Studies in healthy women showed an association between verbal memory performance and physiologic VMS measured with ambulatory skin conductance monitors but not with VMS by self-report. We hypothesized that we would find a similar association in women with breast cancer. METHODS: Participants included 30 female breast cancer survivors (mean age 52.7 y; 26.7% African-American) with moderate-to-severe VMS enrolled in a larger clinical trial of a nonhormonal intervention for VMS. At baseline, participants completed assessments of physiologic VMS, actigraphy-based assessments of sleep, questionnaires about mood, and two tests of verbal memory - Logical Memory (LM) and the California Verbal Learning Test (CVLT). Using baseline data, we conducted multivariate regression analyses to examine the association between VMS and memory, controlling for sleep and other factors. RESULTS: On average, women reported 46% of total physiologic VMS. A higher frequency of physiologic VMS - but not reported VMS - was significantly associated with lower scores on the California Verbal Learning Test short-delay free recall (r[28] = -0.41, P = 0.03), long-delay free recall (r[28] = -0.42, P = 0.03), and total clustering, (r[28] = -0.39, P = 0.04). These associations were independent of sleep, mood, and other factors. CONCLUSIONS: Independent of their effect on sleep, VMS may be a modifiable contributor to memory difficulties in women with breast cancer. These findings underscore the importance of objective measurement of VMS in cognitive studies. : Video Summary:http://links.lww.com/MENO/A623.
Keywords: actimetry; adult; African American; amnesia; article; breast cancer; California verbal learning test; cancer survival; cancer survivor; controlled study; female; human; middle aged; mood; questionnaire; sleep; verbal memory; videorecording

Pilot Feasibility Study of a Video Intervention to Educate Patients with Breast Cancer About Clinical Trials - Yeager, K.A.; Bai, J.; Gogineni, K.; Meisel, J.L.; Kweon, J.; Bruner, D.W.; Waldrop-Valverde, D. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2020)
The purpose of this project was to develop and test the feasibility and preliminary efficacy of a video about cancer clinical trials (CCTs) developed for breast cancer patients. We developed 2 brief 7-min videos that focused on breast cancer patients describing their experiences participating in CCTs, supplemented with doctors and research staff explaining key research concepts. One video was culturally tailored to Black patients and the other to White patients. To assess feasibility study, participants and their care providers completed a survey to evaluate their satisfaction with the video. Eligibility criteria for the study included ≥ 21 years of age, English-speaking, no prior experience participating in a CCT, and being potentially eligible for breast CCT enrollment. Preliminary efficacy was evaluated with a pretest-posttest design using a single item asking about intent to enroll in a clinical trial. The mean age of the patient sample (n = 50) was 53.0 years, and 50.0% were Black. Participants reported that the video was in the right length, useful, and easy to understand. Providers' evaluation (n = 5) revealed that viewing the video helped prepare patients for further CCT discussion. Preliminary efficacy showed no statistically significant difference in participant interest in CCT enrollment pre- and post-video. Changes in patients' intent in enrollment were associated with age and education. Culturally adapted video interventions can be helpful in supporting both patients and providers throughout the CCT education process but additional work is needed to improve enrollment into clinical trials.
Keywords: adult; age; article; breast cancer; cancer patient; clinical article; controlled study; drug efficacy; education; feasibility study; female; human; pretest posttest design; satisfaction; speech; videorecording

Tracking the Nonenrolled: Lung Cancer Screening Patterns Among Individuals not Accrued to a Clinical Trial - Gerber, D.E.; Hamann, H.A.; Chavez, C.; Dorsey, O.; Santini, N.O.; Browning, T.; Ochoa, C.D.; Adesina, J.; Natchimuthu, V.S.; Steen, E.; Zhu, H.; Lee, S.J.C. (Clinical Lung Cancer, 2020)
Introduction: For lung cancer screening, the available data are often derived from patients enrolled prospectively in clinical trials. We, therefore, investigated lung cancer screening patterns among individuals eligible for, but not enrolled in, a screening trial. Patients and Methods: From February 2017 through February 2019, we enrolled subjects in a trial examining telephone-based navigation during low-dose computed tomography (LDCT) for lung cancer screening. We identified patients for whom LDCT was ordered and who were approached, but not enrolled, in the trial. We categorized nonenrollment as the patient had declined or could not be reached. We compared the characteristics and LDCT completion rates among these groups and the enrolled population using the 2-sample t test and χ2 test. Results: Of 900 individuals approached for participation (mean age, 62 years; 45% women, 53% black), 447 were enrolled in the screening clinical trial. No significant demographic differences were found between the enrolled and nonenrolled cohorts. Of the 453 individuals not enrolled, 251 (55%) had declined participation and 202 (45%) could not be reached, despite up to 6 attempts. LDCT completion was significantly associated with enrollment status: 81% of enrolled individuals, 73% of individuals who declined participation, and 49% of those who could not be reached (P < .001). Conclusions: In the present single-center study, demographic factors did not predict for participation in a lung cancer screening trial. Lung cancer screening adherence rates were substantially lower for those not enrolled in a screening trial, especially for those who could not be contacted. These findings may inform the broader implementation of screening programs.
Keywords: NCT02758054; adult; article; cancer screening; chi square test; cohort analysis; comparative study; computer assisted tomography; controlled study; demography; female; health behavior; human; lung cancer; major clinical study; male; middle aged; patient compliance; patient participation; prospective study; randomized controlled trial; Student t test; Texas

Pharmacist intervention in colorectal cancer screening initiative - Holle, L.M.; Levine, J.; Buckley, T.; White, C.M.; White, C.; Hadfield, M.J. (Journal of the American Pharmacists Association, 2020)
Objectives: To assess the novel approach of using the community pharmacist as the primary health care team member to facilitate colorectal cancer (CRC) risk counseling and screening in socioeconomically disadvantaged populations. Setting: A collaborative effort between the UConn Health Colon Cancer Prevention Program and UConn School of Pharmacy in conjunction with large independent chain pharmacies (medium to medium-high volume) located in metropolitan areas of Connecticut, including Hartford, Bridgeport, New Haven, and Stamford. Pharmacies located in hospitals, across the street from a large physician practice, or within the community. Practice description: The study involved 2 phases. The first phase involved education and training for community pharmacists regarding counseling approaches for patients on the topic of CRC. The second phase of the study involved patient recruitment and counseling with subsequent fecal immunohistochemical testing (FIT). Practice innovation: A community pharmacist provided face-to-face counseling on CRC risk factor reduction and provided CRC screening to patients who were without insurance or underinsured. No CRC screening or education program existed beforehand. Evaluation: A target sample size of 60 participants was needed with a type 1 error rate of 5% and a power of 80%. Exploration of variables using multivariate logistic regression model included any variable with a univariate P < 0.2. Multivariate P values < 0.05 were considered independent predictors. Results: After approaching 312 consumers, 16 of them consented to the study. The majority of participants (88%) were African American or Latino, and 69% were currently unemployed. Eight participants agreed to complete FIT, and 88% of participants completed FIT correctly. Only 1 positive FIT result was observed, but a subsequent colonoscopy was negative. Of the 12 questions that assessed baseline CRC knowledge in the initial survey, 16 participants answered an average of 2.6 (range, 0–6, SD, 1.6) questions incorrectly. Only 4 participants completed the follow-up survey of CRC knowledge and program satisfaction; thus, exploration of variables was not conducted. Patients indicated high satisfaction with the program of education and FIT dispensing. Conclusion: This study faced difficulty in recruiting pharmacists to participate, with the main reason being lack of compensation and disruption to workflow. Patient participation in the trial was also low because of a lack of time or interest in participation. Of the patients who did participate, the level of satisfaction in having the pharmacist speak to them about CRC screening was high. This service is an excellent example of how the pharmacist can provide a more accessible, convenient, and responsive approach to patients’ needs while improving health equity. Future studies that employ a revenue model to build the infrastructure and capacity necessary to offer this service efficiently and consistently are needed.
Keywords: adult; African American; article; cancer screening; colonoscopy; colorectal cancer; community pharmacist; consumer; education program; face to face support group; female; follow up; health insurance; health survey; Hispanic; human; major clinical study; male; middle aged; occult blood; patient counseling; patient participation; patient satisfaction; practice guideline; primary health care; professional knowledge; sample size

Diversity of enrollment in prostate cancer clinical trials: current status and future directions - Rencsok, E.M.; Bazzi, L.A.; McKay, R.R.; Huang, F.W.; Friedant, A.; Vinson, J.; Peisch, S.; Zarif, J.C.; Simmons, S.; Hawthorne, K.; Villanti, P.; Kantoff, P.W.; et al. (Cancer Epidemiology Biomarkers and Prevention, 2020)
Background: Although there are considerable racial and ethnic disparities in prostate cancer incidence and mortality in the United States and globally, clinical trials often do not reflect disease incidence across racial and ethnic subgroups. This study aims to comprehensively review the reporting of race and ethnicity data and the representation of race and ethnicity across prostate cancer treatment-, prevention-, and screening-based clinical trials. Methods: Seventy-two global phase III and IV prevention, screening, and treatment prostate cancer clinical trials with enrollment start dates between 1987 and 2016 were analyzed in this study, representing a total of 893,378 individual trial participants. Availability and representation of race and ethnicity data by trial funding type, temporal changes in the racial/ethnic diversity of participants, and geographic representation of countries were assessed. Results: Of the 72 trials analyzed, 59 (81.9%) had available race data, and 11 (15.3%) of these trials additionally reported ethnicity. Of the trials reporting data, participants were overwhelmingly white men (with the highest proportion in U.S. nonpublicly funded trials), comprising over 96% of the study population. The proportion of white participants in prostate cancer clinical trials has remained at over 80% since 1990. Geographically, Africa and the Caribbean were particularly underrepresented with only 3% of countries included. Conclusions: Trial participants continue to be majority white despite the known racial disparities in prostate cancer clinical outcomes. Impact: Current and future trials must use novel recruitment strategies to ensure enrollment of underrepresented men. Targeting the inclusion of African and Caribbean medical centers is crucial to achieve equity in representation.
Keywords: Africa; African American; Alaska Native; American Indian; article; Asian; Black person; cancer prevention; cancer screening; cancer therapy; Caribbean; Caucasian; clinical outcome; ethnic difference; funding; Hispanic; human; major clinical study; male; multiracial person; patient information; patient selection; phase 3 clinical trial (topic); phase 4 clinical trial (topic); prevention study; priority journal; prostate cancer; race difference; systematic review

African Immigrant Health: Prostate Cancer Attitudes, Perceptions, and Barriers - Malika, N.; Ogundimu, O.; Roberts, L.; Alemi, Q.; Casiano, C.; Montgomery, S. (American journal of men's health, 2020)
Prostate cancer (PCa) is the second leading cause of cancer-related death among Black men who present with higher incidence, mortality, and survival compared to other racial groups. African immigrant men, however, are underrepresented in PCa research and thus this research sought to address that gap. This study applied a social determinants of health framework to understand the knowledge, perceptions, and behavioral tendencies regarding PCa in African immigrants. African immigrant men and women residing in different parts of the country (California, Texas, Colorado, Oklahoma, and Florida) from various faith-based organizations, African community groups, and social groups were recruited to participate in key informant interviews (n = 10) and two focus groups (n = 23). Four themes were identified in this study: (a) PCa knowledge and attitudes-while knowledge is very limited, perceptions about prostate health are very strong; (b) culture and gender identity strongly influence African health beliefs; (c) preservation of manhood; and (d) psychosocial stressors (e.g., financial, racial, immigration, lack of community, and negative perceptions of invasiveness of screening) are factors that play a major role in the overall health of African immigrant men. The results of this qualitative study unveiled perceptions, attitudes, beliefs, and knowledge of PCa among African immigrants that should inform the planning, development, and implementation of preventive programs to promote men's health and PCa awareness.
Keywords: adult; article; attitude; awareness; California; cancer research; clinical article; Colorado; controlled study; faith-based organization; female; Florida; gender identity; health belief; human; immigrant; immigration; interview; male; men's health; Oklahoma; perception; prostate cancer; qualitative research; social determinants of health; Texas

Healthcare utilization and cost of care in elderly breast cancer patients enrolled in SWOG clinical trials - Hershman, D.L.; Till, C.; Wright, J.D.; Accordino, M.; Vaidya, R.; Barlow, W.E.; Ramsey, S.; Unger, J.M. (Breast Cancer Research and Treatment, 2020)
Importance: Patients with cancer are at risk for unplanned hospitalizations during treatment which can increase the cost of care. Objectives: To determine demographic and clinical factors associated with healthcare utilization and costs among clinical trial participants. Design, setting, and patients: We conducted a retrospective analysis among breast cancer patients over the age of 65 treated on SWOG clinical trials from 1999 to 2011 with trial data linked to Medicare claims. Main outcomes and measures: The outcomes were healthcare utilization (emergency room visits (ER), hospitalizations) and costs from Medicare Claims. Demographic, clinical, and prognostic factors were captured from clinical trial records. We identified cardiovascular comorbidities/risk factors (CVD-RFs) of diabetes, hypertension, hypercholesterolemia, and coronary artery disease (CAD) from Medicare claims. Multivariable logistic and linear regression were used to assess the association between CVD-RFs and outcomes. Results: Among the 708 patients included in the analysis, 160 (22.6%) experienced 234 separate hospitalizations, and 193 (27.3%) experienced 311 separate ER visits. Black race was associated with an increase in hospitalizations (OR [95% CI], 2.52 [1.10–5.79], p = 0.03), but not emergency room visits compared to white race. Diabetes, hypertension, hypercholesterolemia, and CAD were all independently associated with increased risk of both hospitalizations and ER visit. Hypertension had the strongest association, with more than a threefold risk of hospitalization for those with hypertension compared to those without (OR [95% CI], 3.16 [1.85–5.40], p < 0.001). For those with ≥ 3 RFs, the risk of hospitalization was nearly 3 times greater compared to 0 or 1 CVD-RFs (OR [95% CI], 2.74 [1.71–4.38], p < 0.001). Similar results were seen for ER visits. In the first 12 months after trial registration, patients with diabetes ($38,324 vs $30,923, 23.9% increase, p = 0.05), hypercholesterolemia ($34,168 vs $30,661, 11.4% increase, p = 0.02), and CAD ($37,781 vs $31,698, 19.2% increase, p = 0.04) had statistically significantly higher total healthcare costs. Additionally, those with ≥ 2 significant CVD-RFs ($35,353 vs. $28,899, 22.3% increase, p = 0.005) had statistically significantly higher total healthcare costs. Conclusions: Among participants treated on clinical trials, black race and presence of multiple cardiovascular comorbidities was associated with a substantial increase in ER visits, hospitalizations and healthcare costs. Efforts to reduce unplanned hospitalizations should focus on this high-risk group.
Keywords: aged; article; Black person; breast cancer; cancer patient; cancer prognosis; cardiovascular risk; clinical outcome; clinical study; comorbidity; confidence interval; controlled study; coronary artery disease; demography; diabetes mellitus; emergency ward; female; geriatric patient; health care cost; health care utilization; high risk population; hospitalization; human; hypercholesterolemia; hypertension; linear regression analysis; logistic regression analysis; medical record; medicare; odds ratio; priority journal; race difference; retrospective study; risk factor; very elderly

Outcomes Among Minority Patients With Metastatic Colorectal Cancer in a Safety-net Health Care System - Lau-Min, K.; Prakash, P.; Jo, E.; Thrift, A.P.; Hilsenbeck, S.; Musher, B.L. (Clinical Colorectal Cancer, 2020)
Metastatic colorectal cancer outcomes continue to improve, but they vary significantly by race and ethnicity. Hypothesizing that these disparities arise from unequal access to care rather than intrinsic biology, we showed that survival of 103 consecutive patients with metastatic colorectal cancer treated at an academic safety-net hospital that treats the underserved, predominantly minority population of Harris County, Texas, was superior to that of subjects enrolled in the CRYSTAL (Cetuximab Combined with Irinotecan in First-Line Therapy for Metastatic Colorectal Cancer) trial. Our findings suggest that administering high-quality comprehensive cancer care to vulnerable populations can overcome disparities reported in the medical literature.
Keywords: bevacizumab; capecitabine; cetuximab; fluoropyrimidine; fluorouracil; folinic acid; irinotecan; oxaliplatin; panitumumab; regorafenib; adult; article; Asian; Black person; cancer chemotherapy; cancer patient; cancer radiotherapy; cancer surgery; cancer survival; clinical pathway; evidence based practice; female; financial management; health care delivery; Hispanic; human; integration; major clinical study; male; medically uninsured; metastatic colorectal cancer; middle aged; Middle East; minority group; outcome assessment; overall survival; retrospective study; safety net health care; survival rate; treatment response; vulnerable population

A Phase I Study of Safety, Pharmacokinetics, and Pharmacodynamics of Concurrent Everolimus and Buparlisib Treatment in Advanced Solid Tumors - Owonikoko, T.K.; Harvey, R.D.; Carthon, B.; Chen, Z.; Lewis, C.; Collins, H.; Zhang, C.; Lawson, D.H.; Alese, O.B.; Bilen, M.A.; Sica, G.L.; Steuer, C.E.; et al. (Clinical Cancer Research, 2020)
Purpose: Concurrent inhibition of mTOR and PI3K led to improved efficacy in preclinical models and provided the rationale for this phase I study of everolimus and buparlisib (BKM120) in patients with advanced solid tumor. Patients and Methods: We used the Bayesian Escalation with Overdose Control design to test escalating doses of everolimus (5 or 10 mg) and buparlisib (20, 40, 60, 80, and 100 mg) in eligible patients. Pharmacokinetic assessment was conducted using blood samples collected on cycle 1, days 8 and 15. Pharmacodynamic impact on mTOR/PI3K pathway modulation evaluated in paired skin biopsies collected at baseline and end of cycle 1. Results: We enrolled 43 patients, median age of 63 (range, 39–78) years; 25 (58.1%) females, 35 (81.4%) Caucasians, and 8 (18.6%) Blacks. The most frequent toxicities were hyperglycemia, diarrhea, nausea, fatigue, and aspartate aminotransferase elevation. Dose-limiting toxicities observed in 7 patients were fatigue (3), hyperglycemia (2), mucositis (1), acute kidney injury (1), and urinary tract infection (1). The recommended phase II dose (RP2D) for the combination was established as everolimus (5 mg) and buparlisib (60 mg). The best response in 27 evaluable patients was progressive disease and stable disease in 3 (11%) and 24 (89%), respectively. The median progression-free survival and overall survival were 2.7 (1.8–4.2) and 9 (6.4–13.2) months. Steady-state pharmacokinetic analysis showed dose-normalized maximum concentrations and AUC values for everolimus and buparlisib in combination to be comparable with single-agent pharmacokinetic. Conclusions: The combination of everolimus and buparlisib is safe and well-tolerated at the RP2D of 5 and 60 mg on a continuous daily schedule.
Keywords: NCT01470209; buparlisib; everolimus; mammalian target of rapamycin; phosphatidylinositol 3 kinase; acute kidney failure; adult; aged; Akt signaling; anemia; anorexia; anxiety disorder; area under the curve; article; Black person; bladder cancer; blood analysis; body weight loss; breast cancer; cancer chemotherapy; cancer growth; cancer patient; cancer survival; Caucasian; cellulitis; clinical article; cohort analysis; colorectal cancer; concentration at steady-state; constipation; coughing; dehydration; diarrhea; dizziness; drug safety; dry eye; dyspepsia; dyspnea; dysuria; ear infection; edema; erectile dysfunction; fatigue; female; fever; gastroenteropancreatic neuroendocrine tumor; headache; human; human tissue; hyperbilirubinemia; hypercholesterolemia; hyperglycemia; hypertension; hypertransaminasemia; hypertriglyceridemia; hyperuricemia; hypoalbuminemia; hypocalcemia; hypokalemia; hypomagnesemia; hyponatremia; hypophosphatemia; hypotension; insomnia; leukopenia; lung cancer; lung embolism; male; maximum concentration; memory disorder; mucosa inflammation; multiple cycle treatment; musculoskeletal pain; nausea; neuropathy; neutropenia; nocturia; nose obstruction; oral mucositis; ovary cancer; overall survival; Parainfluenza virus infection; pharmacokinetic parameters; phase 1 clinical trial; phase 2 clinical trial; pneumonia; priority journal; progression free survival; pruritus; rash; rectum hemorrhage; respiratory failure; salivary gland cancer; sepsis; side effect; skin biopsy; soft tissue sarcoma; solid malignant neoplasm; survival rate; thrombocytopenia

Preparing African American Men to Make Informed Prostate Cancer Screening Decisions: Development and Pilot Testing of an Interactive Online Decision Aid - Allen, J.D.; Reich, A.; Cuevas, A.G.; Ladin, K. (JMIR mHealth and uHealth, 2020)
BACKGROUND: African American men are at a higher risk of developing and dying from prostate cancer compared to white men. The serum prostate-specific antigen (PSA) screening test has a high risk of false-positive results and overdiagnosis; therefore, it is not routinely recommended. Rather, men are encouraged to make individualized decisions with their medical providers, after being fully informed about its potential benefits, limitations, and risks. OBJECTIVE: This study aimed to describe the development and pilot testing of an interactive Web-based decision aid (DA; Prostate Cancer Screening Preparation [PCSPrep]) for African American men, designed to promote informed decision making for prostate cancer screening. METHODS: Four focus groups (n=33) were conducted to assess men's reactions to DAs developed in prior studies and gather information to modify the content and format. The pilot test employed a pre-posttest evaluation design. A convenience sample of 41 men aged 45-70 years with no history of prostate cancer was recruited from community settings. Participants completed online surveys before and after using PCSPrep that assessed prostate cancer screening knowledge, decision self-efficacy, decisional conflict, and preparation for decision making. RESULTS: Use of PCSPrep was associated with a significant increase in prostate cancer knowledge (49% vs 62% correct responses; P<.001), and men also experienced less decisional conflict (24 vs 15 on a scale of 0-100; P=.008). No changes in self-efficacy about decision making or screening preferences were observed. Most men (81%) reported that using PCSPrep prepared them to make informed decisions in partnership with their provider. CONCLUSIONS: PCSPrep was an acceptable DA that improved men's knowledge, reduced decisional conflict, and promoted the perception of being prepared for shared decision making. Further research is needed to test the DA in a larger randomized trial.
Keywords: adult; African American; aged; article; cancer screening; clinical article; controlled study; convenience sample; decision support system; early cancer diagnosis; human; human tissue; male; men's health; middle aged; minority health; pretest posttest design; prostate cancer; randomized controlled trial; self concept; shared decision making

Efficacy of Upfront Docetaxel With Androgen Deprivation Therapy for Castration-Sensitive Metastatic Prostate Cancer Among Minority Patients - Pathak, S.; Thekkekara, R.; Yadav, U.; Ahmed, A.T.; Yim, B.; Lad, T.E.; Mullane, M.; Batra, K.K.; Aronow, W.S.; Psutka, S.P. (American journal of therapeutics, 2020)
BACKGROUND: Upfront docetaxel (UD) with androgen deprivation therapy (ADT) has been demonstrated to improve survival outcomes in metastatic castration-sensitive prostate cancer (mCSPC). However, existing studies have included predominantly Caucasian patients. STUDY QUESTION: To compare the efficacy of addition of UD to ADT in mCSPC to ADT alone among minority patients. STUDY DESIGN: Retrospective study of mCSPC patients. MEASURES AND OUTCOMES: Patients treated with UD and ADT between January 2014 and December 2017 (UD + ADT, n = 44) were compared with those treated with ADT alone between January 2008 and January 2017 (ADT, n = 38); patients of Caucasian ethnicity were excluded. The outcome of interest was progression-free survival (PFS), which was estimated using Kaplan-Meier analysis and Cox proportional hazard analysis. RESULTS: Overall, 63 (76.8%) patients were African American and 16 (19.5%) were Hispanic. Fifty-five (67%) patients had high-volume mCSPC. The median follow-up was 14 months [95% confidence interval (CI): 10.4-16.5] for UD + ADT and 42 months (95% CI: 17-66.9) for ADT. Median PFS did not differ between groups: UD + ADT: 16 versus ADT: 18 months [hazard ratio (HR) for UD + ADT = 0.88, 95% CI: 0.48-1.62; P = 0.70]. In patients with high-volume disease, median PFS remained similar (UD + ADT: 16 vs. ADT: 14 months (HR for UD + ADT = 0.64, 95% CI: 0.33-1.25; P = 0.19). On multivariable analysis, prolonged time to nadir PSA, HR = 0.83 (95% CI: 0.76-0.90), was independently associated with PFS. The most common toxicities in UD + ADT were anemia and fatigue. Major limitations include small sample size and potential for selection bias due to the retrospective study design. CONCLUSIONS: In this retrospective review of a minority mCSPC cohort, UD + ADT was not associated with improved PFS compared with ADT alone. Although further study with larger sample size is needed, these results underscore the importance of ensuring accrual of minorities in clinical trials, reflective of the real-world setting.
Keywords: adult; African American; androgen deprivation therapy; anemia; article; cancer patient; cancer size; cancer survival; castration; Caucasian; clinical article; clinical trial; cohort analysis; controlled study; drug therapy; ethnicity; fatigue; follow up; Hispanic; human; Kaplan Meier method; male; progression free survival; prostate cancer; retrospective study; sample size; selection bias; docetaxel; endogenous compound; prostate specific antigen

IMPROVE, a community-based exercise intervention versus support group to improve functional and health outcomes among older African American and non-Hispanic White breast cancer survivors from diverse socioeconomic backgrounds: Rationale, design and methods - Owusu, C.; Nock, N.L.; Hergenroeder, P.; Austin, K.; Bennet, E.; Cerne, S.; Moore, H.; Petkac, J.; Schluchter, M.; Schmitz, K.H.; Webb-Hooper, M.; Atkins, L.; et al. (Contemporary Clinical Trials, 2020)
Background: African Americans (AA) and socioeconomic status (SES) disadvantaged older breast cancer survivors (BCS) are more likely to experience poor functional and health outcomes. However, few studies have evaluated the putative beneficial effects of exercise on these outcomes in older racial minority and SES-disadvantaged BCS. Methods: This is a mixed-methods study that includes a randomized-controlled trial, “IMPROVE”, to evaluate a group-based exercise intervention compared to a support group program in older BCS, followed by post-intervention semi-structured interviews to evaluate the intervention. The trial aims to recruit 220 BCS with 55 in each of four strata defined by race (AA versus Non-Hispanic Whites) and SES (disadvantaged vs. non-disadvantaged). Participants are ≥65 years old and within five years of treatment completion for stage I-III breast cancer. Participants are randomized to a 52-week, three sessions/week, one-hour/session, moderate intensity aerobic and resistance group exercise intervention, (n = 110) or a 52-week, one hour/week, support group intervention [attention-control arm], (n = 110). The first 20 weeks of both programs are supervised and the last 32 weeks, unsupervised. The primary outcome is the change in Short Physical Performance Battery (SPPB) Scores at 20 weeks from baseline, between the two arms. Secondary outcomes include change in SPPB scores at 52 weeks, change in body composition and biomarkers, at 20 and 52 weeks from baseline, between arms. Discussion: Results of the trial may contribute to a better understanding of factors associated with recruitment, and acceptability, and will inform future exercise programs to optimally improve health outcomes for older BCS.
Keywords: biological marker; aerobic exercise; African American; aged; article; body composition; breast cancer; cancer survivor; comparative effectiveness; controlled study; exercise; female; functional status; health; human; intervention study; major clinical study; multimethod study; physical performance; prospective study; race; randomized controlled trial; resistance training; scoring system; semi structured interview; social status; support group

Dose-Dependent Increases in Ellagitannin Metabolites as Biomarkers of Intake in Humans Consuming Standardized Black Raspberry Food Products Designed for Clinical Trials - Roberts, K.M.; Grainger, E.M.; Thomas-Ahner, J.M.; Hinton, A.; Gu, J.; Riedl, K.; Vodovotz, Y.; Abaza, R.; Schwartz, S.J.; Clinton, S.K. (Molecular nutrition & food research, 2020)
SCOPE: Black raspberry (BRB) phytochemicals demonstrate anti-carcinogenic properties in experimental models, including prostate cancer. Two BRB foods, a confection and nectar, providing a consistent and reproducible product for human clinical studies are designed and characterized. METHODS AND RESULTS: Men with clinically localized prostate cancer are sequentially enrolled to a control group or one of four intervention groups (confection or nectar, 10 or 20 g dose; n = 8 per group) for 4 weeks prior to prostatectomy. Primary outcomes include: safety, adherence, and ellagitannin metabolism. Adherence to the intervention is >96%. No significant (≥grade II) toxicities are detected. Urinary urolithins (A, B, C, and D) and dimethyl ellagic acid (DMEA) quantified by Ultra high performance liquid chromatography tandem mass spectroscopy (UPLC/MS/MS) indicate a dose-dependent excretion yet heterogeneous patterns among men. Men in the BRB confection groups have greater urinary excretion of the microbial urinary metabolites urolithin A and DMEA, suggesting that this food matrix provides greater colonic microflora exposure. CONCLUSION: Fully characterized BRB confections and nectar are ideal for food-based large phase III human clinical studies. BRB products provide a bioavailable source of BRB phytochemicals, however large inter individual variation in polyphenol metabolism suggests that host genetics, microflora, and other factors are critical to understanding bioactivity and metabolism.
Keywords: adult; article; biological activity; cancer surgery; clinical article; clinical trial; colon flora; controlled study; drug safety; human; male; nectar; nonhuman; outcome assessment; pharmacokinetics; phase 3 clinical trial (topic); prostate cancer; prostatectomy; raspberry; surgery; tandem mass spectrometry; urinary excretion; biological marker; ellagitannin; phytochemical; polyphenol; unclassified drug

Increasing uptake of evidence-based screening services though a community health worker-delivered multimodality program: Study protocol for a randomized pragmatic trial - Carrasquillo, O.; Seay, J.; Jhaveri, V.; Long, T.; Kenya, S.; Thomas, E.; Sussman, D.; Trevil, D.; Koru-Sengul, T.; Kobetz, E. (Trials, 2020)
Background: Underserved ethnic minority populations experience significant disparities in HIV, hepatitis C virus (HCV), colorectal cancer (CRC), and cervical cancer incidence and mortality. Much of the excess burden of these diseases among underserved communities is due to lack of preventive care, including screening. Barriers to disease screening include low awareness, lack of access to care and health insurance, and cultural beliefs regarding disease prevention. Our current trial aims to examine community health worker (CHW)-delivered, home-based multi-modality screening for HIV, HCV, CRC, and cervical cancer simultaneously. Design: We are conducting a randomized pragmatic trial among 900 Haitian, Hispanic, and African-American participants from diverse underserved communities in South Florida. People between the ages of 50 and 65 who have not had appropriate HIV, HCV, CRC, and cervical cancer screening per United States Preventive Services Task Force (USPSTF) recommendations are eligible for the study. Participants are recruited by CHWs and complete a structured interview to assess multilevel determinants of disease risk. Participants are then randomized to receive HIV, HCV, CRC, and cervical cancer screening via navigation to care by a CHW (Group 1) or via CHW-delivered home-based screening (Group 2). The primary outcome is completion of screening for each of these diseases within 6 months post-enrollment. Discussion: Our trial is among the first to examine the effectiveness of a CHW-delivered, multimodality, home-based disease-screening approach. If found to be effective, this approach may represent a cost-effective strategy for disease screening within underserved and underscreened minority groups. Trial registration: Clinical Trials.gov # NCT02970136, registered November 21, 2016.
Keywords: NCT02970136; adult; African American; age distribution; article; clinical protocol; colorectal cancer; community care; controlled study; convenience sample; evidence based medicine; female; Florida; Haitian; health auxiliary; health care delivery; health program; hepatitis C; Hispanic; home care; human; Human immunodeficiency virus infection; major clinical study; male; mass screening; outcome assessment; pragmatic trial; program cost effectiveness; randomized controlled trial; risk assessment; uterine cervix cancer

Healthcare utilization and cost of care in elderly breast cancer patients enrolled in SWOG clinical trials - Hershman, D.L.; Till, C.; Wright, J.D.; Accordino, M.; Vaidya, R.; Barlow, W.E.; Ramsey, S.; Unger, J.M. (Breast cancer research and treatment, 2020)
IMPORTANCE: Patients with cancer are at risk for unplanned hospitalizations during treatment which can increase the cost of care. OBJECTIVES: To determine demographic and clinical factors associated with healthcare utilization and costs among clinical trial participants. DESIGN, SETTING, AND PATIENTS: We conducted a retrospective analysis among breast cancer patients over the age of 65 treated on SWOG clinical trials from 1999 to 2011 with trial data linked to Medicare claims. MAIN OUTCOMES AND MEASURES: The outcomes were healthcare utilization (emergency room visits (ER), hospitalizations) and costs from Medicare Claims. Demographic, clinical, and prognostic factors were captured from clinical trial records. We identified cardiovascular comorbidities/risk factors (CVD-RFs) of diabetes, hypertension, hypercholesterolemia, and coronary artery disease (CAD) from Medicare claims. Multivariable logistic and linear regression were used to assess the association between CVD-RFs and outcomes. RESULTS: Among the 708 patients included in the analysis, 160 (22.6%) experienced 234 separate hospitalizations, and 193 (27.3%) experienced 311 separate ER visits. Black race was associated with an increase in hospitalizations (OR [95% CI], 2.52 [1.10-5.79], p = 0.03), but not emergency room visits compared to white race. Diabetes, hypertension, hypercholesterolemia, and CAD were all independently associated with increased risk of both hospitalizations and ER visit. Hypertension had the strongest association, with more than a threefold risk of hospitalization for those with hypertension compared to those without (OR [95% CI], 3.16 [1.85-5.40], p < 0.001). For those with ≥ 3 RFs, the risk of hospitalization was nearly 3 times greater compared to 0 or 1 CVD-RFs (OR [95% CI], 2.74 [1.71-4.38], p < 0.001). Similar results were seen for ER visits. In the first 12 months after trial registration, patients with diabetes ($38,324 vs $30,923, 23.9% increase, p = 0.05), hypercholesterolemia ($34,168 vs $30,661, 11.4% increase, p = 0.02), and CAD ($37,781 vs $31,698, 19.2% increase, p = 0.04) had statistically significantly higher total healthcare costs. Additionally, those with ≥ 2 significant CVD-RFs ($35,353 vs. $28,899, 22.3% increase, p = 0.005) had statistically significantly higher total healthcare costs. CONCLUSIONS: Among participants treated on clinical trials, black race and presence of multiple cardiovascular comorbidities was associated with a substantial increase in ER visits, hospitalizations and healthcare costs. Efforts to reduce unplanned hospitalizations should focus on this high-risk group.
Keywords: aged; article; Black person; breast cancer; cancer patient; cancer prognosis; Caucasian; comorbidity; controlled study; coronary artery disease; demography; diabetic patient; emergency ward; female; health care utilization; high risk population; hospitalization; human; hypercholesterolemia; hypertension; linear regression analysis; major clinical study; medicare; outcome assessment; retrospective study; risk factor

Survival of African American and non-Hispanic white men with prostate cancer in an equal-access health care system - Riviere, P.; Luterstein, E.; Kumar, A.; Vitzthum, L.K.; Deka, R.; Sarkar, R.R.; Bryant, A.K.; Bruggeman, A.; Einck, J.P.; Murphy, J.D.; Martínez, M.E.; Rose, B.S. (Cancer, 2020)
Background: African American (AA) men in the general US population are more than twice as likely to die of prostate cancer (PC) compared with non-Hispanic white (NHW) men. The authors hypothesized that receiving care through the Veterans Affairs (VA) health system, an equal-access medical system, would attenuate this disparity. Methods: A longitudinal, centralized database of >20 million veterans was used to assemble a cohort of 60,035 men (18,201 AA men [30.3%] and 41,834 NHW men [69.7%]) who were diagnosed with PC between 2000 and 2015. Results: AA men were more likely to live in regions with a lower median income ($40,871 for AA men vs $48,125 for NHW men; P <.001) and lower high school graduation rates (83% for AA men vs 88% for NHW men; P <.001). At the time of diagnosis, AA men were younger (median age, 63.0 years vs 66.0 years; P <.001) and had a higher prostate-specific antigen level (median, 6.7 ng/mL vs 6.2 ng/mL; P <.001), but were less likely to have Gleason score 8 to 10 disease (18.8% among AA men vs 19.7% among NHW men; P <.001), a clinical T classification ≥3 (2.2% vs 2.9%; P <.001), or distant metastatic disease (2.7% vs 3.1%; P = 0.01). The 10-year PC-specific mortality rate was slightly lower for AA men (4.4% vs 5.1%; P =.005), which was confirmed in multivariable competing-risk analysis (subdistribution hazard ratio, 0.85; 95% CI, 0.78-0.93; P <.001). Conclusions: AA men diagnosed with PC in the VA health system do not appear to present with more advanced disease or experience worse outcomes compared with NHW men, in contrast to national trends, suggesting that access to care is an important determinant of racial equity.
Keywords: prostate specific antigen; adult; African American; age distribution; article; cancer classification; cancer survival; Caucasian; cohort analysis; controlled study; distant metastasis; Gleason score; health care access; health care delivery; health care system; health care utilization; highest income group; human; longitudinal study; lowest income group; major clinical study; male; mortality rate; patient selection; priority journal; prostate cancer; risk assessment

Association of Sociodemographic and Health-Related Factors with Receipt of Nondefinitive Therapy among Younger Men with High-Risk Prostate Cancer - Bagley, A.F.; Anscher, M.S.; Choi, S.; Frank, S.J.; Hoffman, K.E.; Kuban, D.A.; Mcguire, S.E.; Nguyen, Q.-N.; Chapin, B.; Aparicio, A.; Pezzi, T.A.; Smith, G.L.; et al. (JAMA Network Open, 2020)
Importance: Multiple randomized clinical trials have shown that definitive therapy improves overall survival among patients with high-risk prostate cancer. However, many patients do not receive definitive therapy because of sociodemographic and health-related factors. Objective: To identify factors associated with receipt of nondefinitive therapy (NDT) among patients aged 70 years and younger with high-risk prostate cancer. Design, Setting, and Participants: This cohort study identified 72036 patients aged 70 years and younger with high-risk prostate cancer and Charlson Comorbidity Index scores of 2 or less who were entered in the National Cancer Database between January 2004 and December 2014. Data analysis was conducted from November 2018 to December 2019. Exposure: Receipt of NDT as an initial treatment approach. Main Outcomes and Measures: Survival rates were compared based on receipt of definitive therapy or NDT, and sociodemographic and health-related factors were associated with the type of therapy received. Residual life expectancy was estimated from the National Center for Health Statistics to calculate person-years of life lost. Results: A total of 72036 men with a median (range) age of 63 (30-70) years, Charlson Comorbidity Index scores of 2 or less, and high-risk prostate cancer without regional lymph node or distant metastatic disease were analyzed. Among eligible patients, 5252 (7.3%) received NDT as an initial therapeutic strategy. On univariate and multivariate analyses, NDT was associated with worse overall survival (univariate analysis hazard ratio, 2.54; 95% CI, 2.40-2.69; P <.001; multivariate analysis hazard ratio, 2.40; 95% CI, 2.26-2.56; P <.001). Compared with patients with private insurance or managed care, those with no insurance, Medicaid, or Medicare were more likely to receive systemic therapy only (no insurance: Odds ratio [OR], 3.34; 95% CI, 2.81-3.98; P <.001; Medicaid: OR, 2.92; 95% CI, 2.48-3.43; P <.001; Medicare: OR, 1.36; 95% CI, 1.20-1.53; P <.001) or no treatment (no insurance: OR, 2.63; 95% CI, 2.24-3.08; P <.001; Medicaid: OR, 1.71; 95% CI, 1.45-2.01; P <.001; Medicare: OR, 1.14; 95% CI, 1.04-1.24; P =.004). Compared with white patients, black patients were more likely to receive systemic therapy only (OR, 1.93; 95% CI, 1.74-2.14; P <.001) or no treatment (OR, 1.46; 95% CI, 1.32-1.61; P <.001), and Hispanic patients were more likely to receive systemic therapy only (OR, 1.36; 95% CI, 1.13-1.64; P =.001) or no treatment (OR, 1.36; 95% CI, 1.14-1.60; P <.001). Between 2004 and 2014, patients without insurance or enrolled in Medicaid had 1.83-fold greater person-years of life lost compared with patients with private insurance (area under the curve, 77600 vs 42300 person-years of life lost). Conclusions and Relevance: In this study, receipt of NDT was associated with insurance status and race/ethnicity. While treatment decisions should be individualized for every patient, younger men with high-risk prostate cancer and minimal comorbidities should be encouraged to receive definitive local therapy regardless of other factors. These data suggest that significant barriers to life-extending treatment options for patients with prostate cancer remain.
Keywords: prostate specific antigen; adult; age; aged; article; cancer survival; cancer therapy; Charlson Comorbidity Index; cohort analysis; comorbidity; cryoablation; demography; health insurance; Hispanic; human; life expectancy; lymph node metastasis; major clinical study; male; managed care; medicaid; medicare; overall survival; priority journal; prostate cancer; social status; systemic therapy

The Association of Urologic Oncology Fellowship Training and Diagnostic Yield of Prostate Biopsy - DeWitt-Foy, M.E.; Klein, E.A.; ElShafei, A.; Coronado, W.M.; Campbell, S.; Gong, M.; Berglund, R.; Ulchaker, J.; Fareed, K.; Abouassaly, R. (Urology, 2020)
Objective: To determine the relationship between urologic oncology fellowship training (UOFT) and diagnostic yield of prostate biopsy. Methods: Retrospective review was conducted of patients who underwent prostate biopsy across the Cleveland Clinic between 2000 and 2018. Biopsies done by urologists with and without UOFT were detailed via descriptive statistics and appropriate (chi-square, Student t, Wilcoxon rank-sum) tests. Multivariate logistic regression was used to examine the association between UOFT and positive prostate biopsy, adjusting for relevant covariates. Results: A total of 11,241 biopsies by 129 urologists had complete information available for review. Sixteen urologists (12.4%) had UOFT; 113 either completed a different fellowship or no fellowship. Those with UOFT were more likely to use MRI-guided biopsy (7.80% vs 3.05%, P <.0001), more likely to get a positive biopsy (41.25% vs 32.72%, P <.0001), and more likely to obtain an adequate number (by ≥12) of cores (90.25% vs 74.53%, P <.0001). UOFT remained a significant predictor of positivity when adjusting for patient age and race, PSA, 5-alpha-reductase-inhibitor use, year of biopsy, years in practice, and type of biopsy (MRI or transrectal ultrasound guided). UOFT also predicted higher-risk biopsy (Gleason sum ≥7), adjusting for the same variables, though this association lost significance when adjusting for adequacy of biopsy. The learning curve to achieve a higher percentage of positive biopsies was steeper for nonurologic oncology fellowship trained than for UOFT urologists. Conclusion: UOFT is associated with higher diagnostic yield on prostate biopsy, higher uptake of MRI-guided biopsy, and less steep learning curve. This may be due to patient selection, technique, or, as we demonstrate here, adherence to guidelines.
Keywords: dutasteride; finasteride; prostate specific antigen; adult; African American; American Indian; article; Asian; Caucasian; cohort analysis; controlled study; diagnostic accuracy; diagnostic value; drug use; Gleason score; human; human tissue; image guided biopsy; infectious complication; learning curve; male; medical education; medical practice; multiracial person; nuclear magnetic resonance imaging; oncology; patient selection; prediction; priority journal; prostate biopsy; prostate volume; protocol compliance; retrospective study; risk factor; transrectal ultrasonography; urologist; urology

Physical Activity Maintenance Following Home-Based, Individually Tailored Print Interventions for African American Women - Pekmezi, D.; Ainsworth, C.; Desmond, R.; Pisu, M.; Williams, V.; Wang, K.; Holly, T.; Meneses, K.; Marcus, B.; Demark-Wahnefried, W. (Health promotion practice, 2020)
African American women report low participation in physical activity and are disproportionately burdened by related conditions (obesity, breast, and colon cancer). Physical activity interventions have shown promising results among African American women, but most studies in this area have focused on short-term increases. More enduring changes in health behavior will be needed to eliminate existing health disparities. Thus, the current study examined 12-month physical activity and psychosocial outcomes from a pilot randomized controlled trial (N = 84) of a Home-based Individually tailored Physical activity Print (HIPP) intervention for African American women in the Deep South. Retention was 77.4% at 12 months. HIPP participants increased self-reported moderate-to-vigorous physical activity from 35.1 minutes/week (standard deviation [SD] = 47.8) at baseline to 124 minutes/week (SD = 95.5) at 12 months, compared with the wellness contact control participants who reported increases from 48.2 minutes/week (SD = 51.3) to 102.5 minutes/week (SD = 94.5) over 12 months (between-group p > .05). Results indicate that modest improvements in moderate-to-vigorous physical activity and related psychosocial variables occurred during the active intervention phase (months 0-6) and were sustained during the tapered maintenance period (months 6-12). Low-cost, high-reach, home-based strategies have great potential for supporting sustained participation in physical activity and achieving long-term health benefits among African American women in the Deep South.
Keywords: adult; African American; article; behavior change; cancer prevention; controlled study; exercise; female; health disparity; health promotion; human; human experiment; major clinical study; minority health; physical activity; randomized controlled trial; women's health

Development and validation of a preoperative nomogram for predicting survival of patients with locally advanced prostate cancer after radical prostatectomy - Zhou, X.; Ning, Q.; Jin, K.; Zhang, T.; Ma, X. (BMC Cancer, 2020)
Background: For selected locally advanced prostate cancer (PCa) patients, radical prostatectomy (RP) is one of the first-line treatments. We aimed to develop a preoperative nomogram to identify what kinds of patients can get the most survival benefits after RP. Methods: We conducted analyses with data from the Surveillance, Epidemiology, and End Results (SEER) database. Covariates used for analyses included age at diagnosis, marital status, race, American Joint Committee on Cancer (AJCC) 7th TNM stage, Prostate specific antigen, Gleason biopsy score (GS), percent of positive cores. We estimated the cumulative incidence function for cause-specific death. The Fine and Gray's proportional subdistribution hazard approach was used to perform multivariable competing risk analyses and reveal prognostic factors. A nomogram was built by these factors (including GS, percent of positive cores and N stage) and validated by concordance index and calibration curves. Risk stratification was established based on the nomogram. Results: We studied 14,185 patients. N stage, GS, and percent of positive cores were the independent prognostic factors used to construct the nomogram. For validating, in the training cohort, the C-index was 0.779 (95% CI 0.736-0.822), and in the validation cohort, the C-index was 0.773 (95% CI 0.710-0.836). Calibration curves showed that the predicted survival and actual survival were very close. The nomogram performed better over the AJCC staging system (C-index 0.779 versus 0.764 for training cohort, and 0.773 versus 0.744 for validation cohort). The new stratification of risk groups based on the nomogram also showed better discrimination than the AJCC staging system. Conclusions: The preoperative nomogram can provide favorable prognosis stratification ability to help clinicians identify patients who are suitable for surgery.
Keywords: adult; age; aged; article; Black person; cancer prognosis; cancer staging; cancer survival; Caucasian; cause of death; Gleason score; human; incidence; intermethod comparison; major clinical study; male; marriage; middle aged; nomogram; patient selection; prediction; preoperative evaluation; proportional hazards model; prostate biopsy; prostate cancer; prostatectomy; race difference; risk assessment

Unpacking trial offers and low accrual rates: A qualitative analysis of clinic visits with physicians and patients potentially eligible for a prostate cancer clinical trial - Hamel, L.M.; Dougherty, D.W.; Albrecht, T.L.; Wojda, M.; Jordan, A.; Moore, T.F.; Senft, N.; Carducci, M.; Heath, E.I.; Manning, M.A.; Penner, L.A.; Kim, S.; et al. (JCO Oncology Practice, 2020)
PURPOSE Cancer clinical trial accrual rates are low, and information about contributing factors is needed. We examined video-recorded clinical interactions to identify circumstances under which patients potentially eligible for a trial at a major cancer center were offered a trial. METHODS We conducted a qualitative directed content analysis of 62 recorded interactions with physicians (n = 13) and patients with intermediate- or high-risk prostate cancer (n = 43). Patients were screened and potentially eligible for a trial. We observed and coded the interactions in 3 steps: (1) classification of all interactions as explicit offer, offer pending, trial discussed/not offered, or trial not discussed; (2) in interactions with no explicit offer, classification of whether the cancer had progressed; (3) in interactions classified as progression but no trial offered, identification of factors discussed that may explain the lack of an offer. RESULTS Of the 62 interactions, 29% were classified as explicit offer, 12% as offer pending, 18% as trial discussed/not offered, and 39% as trial not discussed. Of those with no offer, 57% included information that the cancer had not progressed. In 68% of the remaining interactions with patients whose cancer had progressed but did not receive an offer, reasons for the lack of offer were identified, but in 32%, no explanation was provided. CONCLUSION Even in optimal circumstances, few patients were offered a trial, often because their cancer had not progressed. Findings support professional recommendations to broaden trial inclusion criteria. Findings suggest accrual rates should reflect the proportion of eligible patients who enroll.
Keywords: adult; African American; aged; article; cancer center; cancer patient; Caucasian; classification; clinical article; clinical study; clinical trial (topic); content analysis; convenience sample; doctor patient relationship; high risk patient; human; male; oncologist; patient selection; prostate cancer; qualitative analysis; secondary analysis; videorecording

Internalized HIV-Related Stigma and Breast Health Beliefs Among African-American Women Receiving Care for HIV in the USA - Fabian, K.; Molina, Y.; Kemp, C.G.; Nevin, P.E.; McCoy, K.; Simoni, J.M.; Andrasik, M.; Cohn, S.E.; Micci, S.; Rao, D. (Journal of racial and ethnic health disparities, 2020)
OBJECTIVES: African-American women suffer disproportionately from HIV, breast cancer, and other illnesses. Little is known about the relationship between internalized HIV-related stigma and health beliefs related to other illnesses, including breast cancer. Our study examined (1) the relationship between internalized HIV-related stigma and breast health beliefs over time and (2) the moderating effects of participating in a stigma reduction intervention and/or social support. METHODS: Data from 239 African-American women receiving care for HIV in Chicago, IL, or Birmingham, AL, enrolled in the Unity randomized controlled trial, were used in this secondary analysis. Threat of breast cancer was measured in terms of perceived susceptibility, fear, and adverse consequences as well as an overall perceived threat of breast cancer. We used multivariate models with generalized estimating equations to examine the relationship between internalized HIV-related stigma and breast health beliefs across three time points (baseline, immediately post-workshop, and at 12-month follow-up) and to examine if the study arm (HIV stigma reduction vs. breast cancer education) or social support moderated the relationship. RESULTS: Internalized HIV-related stigma was associated with greater overall perceived threat (p < 0.001), susceptibility (p = 0.03), fear (p < 0.001), and perceived adverse consequences (p < 0.001) of breast cancer. These associations remained consistent across study arms and across all levels of social support. CONCLUSIONS: Future studies that examine co-morbid health conditions among African-American women living with HIV should consider the impact of HIV-related stigma on attitudes and beliefs related to co-morbid conditions.
Keywords: adult; African American; article; breast cancer; controlled study; education; fear; female; follow up; health belief; human; Human immunodeficiency virus infected patient; Illinois; major clinical study; randomized controlled trial; secondary analysis; social support; stigma

Effect of a Patient Decision Aid on Lung Cancer Screening Decision-Making by Persons Who Smoke: A Randomized Clinical Trial - Volk, R.J.; Lowenstein, L.M.; Leal, V.B.; Escoto, K.H.; Cantor, S.B.; Munden, R.F.; Rabius, V.A.; Bailey, L.; Cinciripini, P.M.; Lin, H.; Housten, A.J.; Luckett, P.G.; et al. (JAMA Network Open, 2020)
Importance: Lung cancer screening with low-dose computed tomography lowers lung cancer mortality but has potential harms. Current guidelines support patients receiving information about the benefits and harms of lung cancer screening during decision-making. Objective: To examine the effect of a patient decision aid (PDA) about lung cancer screening compared with a standard educational material (EDU) on decision-making outcomes among smokers. Design, Setting, and Participants: This randomized clinical trial was conducted using 13 state tobacco quitlines. Current and recent tobacco quitline clients who met age and smoking history eligibility for lung cancer screening were enrolled from March 30, 2015, to September 12, 2016, and followed up for 6 months until May 5, 2017. Data analysis was conducted between May 5, 2017, and September 30, 2018. Interventions: Participants were randomized to the PDA video Lung Cancer Screening: Is It Right for Me? (n = 259) or to EDU (n = 257). Main Outcomes and Measures: The primary outcomes were preparation for decision-making and decisional conflict measured at 1 week. Secondary outcomes included knowledge, intentions, and completion of screening within 6 months of receiving the intervention measured by patient report. Results: Of 516 quit line clients enrolled, 370 (71.7%) were younger than 65 years, 320 (62.0%) were female, 138 (26.7%) identified as black, 47 (9.1%) did not have health insurance, and 226 (43.8%) had a high school or lower educational level. Of participants using the PDA, 153 of 227 (67.4%) were well prepared to make a screening decision compared with 108 of 224 participants (48.2%) using EDU (odds ratio [OR], 2.31; 95% CI, 1.56-3.44; P <.001). Feeling informed about their screening choice was reported by 117 of 234 participants (50.0%) using a PDA compared with 66 of 233 participants (28.3%) using EDU (OR, 2.56; 95% CI, 1.72-3.79; P <.001); 159 of 234 participants (68.0%) using a PDA compared with 110 of 232 (47.4%) participants using EDU reported being clear about their values related to the harms and benefits of screening (OR, 2.37; 95% CI, 1.60-3.51; P <.001). Participants using a PDA were more knowledgeable about lung cancer screening than participants using EDU at each follow-up assessment. Intentions to be screened and screening behaviors did not differ between groups. Conclusions and Relevance: In this study, a PDA delivered to clients of tobacco quit lines improved informed decision-making about lung cancer screening. Many smokers eligible for lung cancer screening can be reached through tobacco quit lines.
Keywords: NCT02286713; adult; aged; article; cancer screening; controlled study; female; follow up; human; lung cancer; major clinical study; male; medical information; outcome assessment; patient decision aid; patient decision making; priority journal; randomized controlled trial; risk benefit analysis; smoking; smoking cessation; tobacco use; videorecording

NCI–clinical trial accrual in a community network affiliated with a designated cancer center - Kim, D.J.; Otap, D.; Ruel, N.; Gupta, N.; Khan, N.; Dorff, T. (Journal of Clinical Medicine, 2020)
Most cancer care is delivered in the community, while most clinical trials exist in academic centers. We analyzed clinical trial accrual of a tertiary care cancer center and its affiliated community sites to better understand what types of trials accrued at the community sites and whether community accrual increased ethnic diversity. The institutional clinical trial database was searched for solid tumor accruals during 2018–2019. Patient’s race was abstracted, and trial’s funding source, phase, and disease type/stage were tabulated. Of 3689 accruals, 133 were at community sites, representing 26 unique trials while the main campus accrued to 93 unique trials. Community site accruals were highest for breast and colorectal cancer, but patients with less common cancers such as renal, nasopharyngeal, and gastric cancer were also accrued at community sites. Accruals occurred to randomized trials, as well as phase Ib and translational biomarker studies. Minority patients constituted 20.0% and 32.5% of community site accruals for therapeutic and non-therapeutic trials respectively, compared to 20.6% and 29.8% of main campus accruals for therapeutic and non-therapeutic trials, respectively. We conclude that community sites affiliated with an academic cancer center can accrue to a broad spectrum of clinical trials while enhancing racial diversity in participation of clinical trials. Further expansion of access to clinical trials in community sites is necessary to broaden patient access to state-of-the-art and next-generation treatment options.
Keywords: adjuvant; tumor marker; adult; African American; aged; American Indian; article; Asian; bioaccumulation; breast cancer; cancer center; Caucasian; chimeric antigen receptor T-cell immunotherapy; clinical trial; colorectal cancer; community care; controlled study; estimated glomerular filtration rate; ethnicity; female genital tract cancer; gastroesophageal junction; head and neck cancer; health auxiliary; hematologic malignancy; human; investigator sponsored trial; kidney cancer; liver cell carcinoma; major clinical study; melanoma; metastasis; nasopharynx cancer; national health organization; Native Hawaiian; neoadjuvant chemotherapy; non small cell lung cancer; pancreas cancer; phase 1 clinical trial; race; randomized controlled trial; sarcoma; solid malignant neoplasm; stereotactic body radiation therapy; stomach cancer; tertiary care center; toxicity; urogenital tract cancer

A large-cohort retrospective study of metastatic patterns and prognostic outcomes between inflammatory and non-inflammatory breast cancer - Wang, Z.; Wang, H.; Ding, X.; Chen, X.; Shen, K. (Therapeutic Advances in Medical Oncology, 2020)
Background and aims: Breast cancer-related death is attributable mainly to metastasis. Inflammatory breast cancer (IBC) is an infrequent subtype of breast cancer that shows a relatively high rate of metastasis. In this study, we aimed to compare the metastatic patterns and prognostic outcomes of IBC and non-inflammatory breast cancer (non-IBC). Methods: We extracted data between 2010 and 2014 from the Surveillance, Epidemiology and End Results (SEER) database. The Chi-square test and Fisher’s exact test were used to compare the categorical parameters among different groups. Logistic regression was applied for multivariate analysis. The Kaplan–Meier method and multivariate Cox regression models were performed to analyze prognosis. Results: We enrolled 233,686 breast cancer patients between 2010 and 2014 in our research, including 2806 IBC and 230,880 non-IBC patients. Compared with the non-IBC group, the IBC group tended to have a higher incidence of the human epidermal growth factor receptor 2 positive (HER2+) and triple-negative breast cancer (TNBC) subtypes, older age, a higher rate of unmarried status, a lower incidence of black race, poorer tumor differentiation, larger tumor sizes, and a higher frequency of regional lymph node invasion. IBC and non-IBC shared similar trends in molecular subtypes among different metastatic organs. The percentage of the hormone receptor positive (HR+)/human epidermal growth factor receptor 2 negative (HER2–) subtype decreased gradually in patients with lung (IBC 42.5%, non-IBC 55.7%), distant lymph node (IBC 41.5%, non-IBC 54.6%), liver (IBC 31.1%, non-IBC 46.7%), and brain (IBC 30.6%, non-IBC 47.9%) metastases compared with that in patients with bone (IBC 50.8%, non-IBC 69.0%) metastasis in both cohorts. In both the IBC and non-IBC cases, the proportion of visceral metastases increased in the TNBC subtype, especially brain metastasis (IBC 26.4%, non-IBC 21.2%), which had the largest increase. The frequencies of all sites (bone, lung, liver, brain, and distant lymph node) in IBC were much higher than those in non-IBC (bone: IBC 21.1%, non-IBC 3.0%; lung: IBC 11.4%, non-IBC 1.4%; liver: IBC 9.6%, non-IBC 1.2%; brain: IBC 2.6%, non-IBC 0.3%; distant lymph node: IBC 12.9%, non-IBC 1.0%). The most frequent bi-site metastasis was the bone and liver (IBC 2.5%, non-IBC 0.3%), and the most frequent tri-site combination was the bone, lung, and liver (IBC 1.1%, non-IBC 0.2%). Kaplan–Meier curves and multivariate Cox regression models suggested that the IBC cohort had poorer overall survival [hazard ratio (HR) 1.602, 95% confidence interval (CI) 1.496–1.716, p < 0.001] and breast cancer-specific survival (HR 1.511, 95% CI 1.402–1.628, p < 0.001) than the non-IBC cohort. Furthermore, univariate and multivariate analyses indicated that IBC was an independent prognostic factor in patients with different metastatic sites. Conclusion: IBC and non-IBC patients presented with different metastatic frequencies, clinical features and prognostic outcomes. Our findings provide more information for therapeutic decision making and clinical study designs.
Keywords: epidermal growth factor receptor 2; adult; aged; article; Black person; bone metastasis; brain metastasis; cancer patient; cancer prognosis; cancer registry; cancer research; cancer specific survival; cohort analysis; female; human; human epidermal growth factor receptor 2 negative breast cancer; human epidermal growth factor receptor 2 positive breast cancer; inflammatory breast cancer; liver metastasis; lung metastasis; lymph node; lymph node metastasis; major clinical study; male; outcome assessment; overall survival; retrospective study; trend study; triple negative breast cancer; tumor differentiation; tumor volume

Association of diet quality and physical activity on obesity-related cancer risk and mortality in black women: Results from the Women's Health Initiative - Chebet, J.J.; Thomson, C.A.; Kohler, L.N.; Ehiri, J.E.; Luo, J.; Cheng, T.-Y.D.; Pan, K.; Chlebowski, R.T.; Nassir, R.; Sealy-Jefferson, S.; Manson, J.E.; Saquib, N.; et al. (Cancer Epidemiology Biomarkers and Prevention, 2020)
Background: Obesity-related cancers disproportionately affect the Black community. We assessed the relationship between diet quality, physical activity, and their combined effect on obesity-related cancer risk and mortality in Black women enrolled in the Women's Health Initiative (WHI). Methods: Data from postmenopausal (50-79 years of age) Black women enrolled in WHI clinical trials or observational studies were analyzed. Exposure variables included baseline physical activity [metabolic equivalent of tasks (MET)-hours/ week of moderate-to-vigorous physical activity (MVPA)] and diet quality [Healthy Eating Index (HEI)-2015]. Outcomes included adjudicated obesity-related cancer incidence and mortality. Cox proportional hazard models were used to evaluate the association between MVPA and HEI-2015 and obesity-related cancer risk and mortality. Results: The analytical sample included 9,886 Black women, with a baseline mean body mass index (BMI) of 31.1 kg/m2 (SD ¼ 6.8); mean HEI-2015 score of 63.2 (SD ¼ 11.0, possible range 0 to 100); and mean MVPA of 5.0 (SD ¼ 9.4) MET-hours/week. Over an average of 13 years of follow-up, 950 (9.6%) obesity-related cancer cases were observed, with 313 (32.9%) resulting in death. Physical activity [HR, 1.05; 95% confidence interval (CI), 0.86-1.30], diet quality (HR, 0.99; 95% CI, 0.92-1.08), and their combination (HR, 1.05; 95% CI, 0.85-1.29) were not associated with risk for any or site-specific obesity-related cancers. Similarly, these health behaviors had no association with mortality. Conclusions: Diet quality, physical activity and their combined effect, as measured, were not associated with obesity-related cancer risk and mortality in Black women enrolled in WHI. Impact: Other social, behavioral, and biological factors may contribute to racial disparities observed in obesity-related cancer rates.
Keywords: adult; aged; alcohol consumption; article; Black person; body mass; breast cancer; cancer mortality; cancer risk; cohort analysis; colorectal cancer; controlled study; female; follow up; health behavior; health care disparity; human; intervention study; major clinical study; metabolic equivalent; middle aged; nutritional parameters; obesity; observational study; physical activity; postmenopause; priority journal; prospective study; questionnaire; randomized controlled trial; sedentary time; smoking; treatment outcome; waist circumference

Health-related quality of life outcomes for the LEAP study—CALGB 70305 (Alliance): A lymphedema prevention intervention trial for newly diagnosed breast cancer patients - Naughton, M.J.; Liu, H.; Seisler, D.K.; Le-Rademacher, J.; Armer, J.M.; Oliveri, J.M.; Sloan, J.A.; Hock, K.; Schwartz, M.; Unzeitig, G.; Melnik, M.; Yee, L.D.; et al. (Cancer, 2020)
Background: Lymphedema is an adverse effect of breast cancer treatment that causes swelling and pain in the arm and hand. We tested 2 lymphedema prevention interventions and their impact on health-related quality of life (HRQOL) in a group-randomized trial at 38 cooperative group sites within the United States. Methods: Patients were recruited before breast surgery. Sites were randomly assigned to education-only (EO) lymphedema prevention or education plus exercise and physical therapy (LEAP). Lymphedema was defined as a ≥10% difference in arm volume at any time from baseline to 18 months postsurgery. HRQOL was assessed using the Functional Assessment of Cancer Therapy–Breast plus 4 lymphedema items (FACT-B+4). Longitudinal mixed model regression analysis, adjusting for key demographic and clinical variables, examined participants' HRQOL by intervention group and lymphedema status. Results: A total of 547 patients (56% LEAP) were enrolled and completed HRQOL assessments. The results revealed no differences between the interventions in preventing lymphedema (P =.37) or HRQOL (FACT-B+4 total score; P =.8777). At 18 months, the presence of lymphedema was associated with HRQOL at borderline significance (P =.0825). However, African American patients reported greater lymphedema symptoms (P =.0002) and better emotional functioning (P =.0335) than patients of other races or ethnicities. Lower HRQOL during the intervention was associated with younger age (P ≤.0001), Eastern Cooperative Oncology Group performance status >0 (P =.0002), ≥1 positive lymph nodes (P =.0009), having no education beyond high school (P <.0001), having undergone chemotherapy (P =.0242), and having had only axillary node dissection or sentinel node biopsy versus both (P =.0007). Conclusion: The tested interventions did not differ in preventing lymphedema or in HRQOL outcomes. African American women reported greater HRQOL impacts due to lymphedema symptoms than women of other races or ethnicities.
Keywords: adult; African American; age; article; axillary lymph node; breast cancer; breast surgery; cancer chemotherapy; cancer patient; cancer surgery; controlled study; demography; dissection; ethnicity; exercise; female; Functional Assessment of Cancer Therapy Breast; high school; human; intervention study; lymphedema; major clinical study; physiotherapy; prevention; quality of life; race; randomized controlled trial; sentinel lymph node; surgery; United States

A Prospective Pilot Study Evaluating Feasibility and Preliminary Effects of Breathe Easier: A Mindfulness-based Intervention for Survivors of Lung Cancer and Their Family Members (Dyads) - McDonnell, K.K.; Gallerani, D.G.; Newsome, B.R.; Owens, O.L.; Beer, J.; Myren-Bennett, A.R.; Regan, E.; Hardin, J.W.; Webb, L.A. (Integrative Cancer Therapies, 2020)
Objective: Symptom burden remains a distressing problem for survivors with non-small-cell lung cancer (stages I-IIIa). This pilot study evaluated feasibility and preliminary effects of a tailored mindfulness-based intervention, Breathe Easier, which encompasses meditation, 2 levels of mindful hatha yoga, breathing exercises, and participant interaction. Methods: Participants were recruited from 2 cancer programs in the US Southeast. A family member was required for participation. Sixty-two participants enrolled (20% recruitment) and 49 completed the intervention (79% retention). Participants chose level 1 yoga (basic) or level 2 (more advanced). Of the completers, survivors were 39% male and 65% Black. A community-based participatory research framework helped identify the specific needs and interests of potential participants and foreseeable barriers to implementation. A 2-month prospective, 1-group, pre-post design evaluated feasibility. Intervention dosage was measured using written protocols. Attendance and completion of daily home assignments measured adherence. Acceptability was assessed using a 10-item questionnaire, completed at three time points. Preliminary outcome data collected pre- and post-intervention tested the hypothesis that participants who received the 8-week intervention Breathe Easier would, post-intervention, demonstrate (a) less dyspnea, (b) less fatigue, (c) less stress, (d) improved sleep, (e) improved anxiety and depression, and (f) improved functional exercise capacity. Exit interviews were conducted, transcribed verbatim, and analyzed for content using descriptive statistics. Results: Quantitative and qualitative measures indicated strong feasibility. Over time, level 1 participants had statistically less dyspnea, fatigue and improved exercise capacity, as well as improved sleep, and stress scores. Level 2 participants experienced slightly increased dyspnea and fatigue but improved sleep, stress, and exercise capacity. All participants experienced anxiety and depression within normal limits pre- and post-intervention. Five major themes emerged out of exit interviews: Learning to Breathe Easier; Interacting with Others as a Personal Benefit; Stretching, Releasing Tension, and Feeling Energized; Enhancing Closeness with Committed Partners; Refocusing on Living; and Sustaining New Skills as a Decision. Conclusions: The study offers insight into the feasibility of an 8-week in-person mindfulness-based intervention with a unique subset of understudied survivors of lung cancer and family members. Outcome data interpretation is limited by the 1-group design and sample size.
Keywords: adult; aged; anxiety; article; Black person; breathing exercise; cancer family; cancer survivor; clinical outcome; depression; dyspnea; evidence based practice; exercise; family therapy; fatigue; female; Functional Assessment of Chronic Illness Therapy; Functional Assessment of Chronic Illness Therapy Dyspnea Scale; Functional Assessment of Chronic Illness Therapy Fatigue Scale; hatha yoga; health care need; home mental health care; Hospital Anxiety and Depression Scale; human; intervention study; interview; intimacy; major clinical study; male; meditation; middle aged; mindfulness; non small cell lung cancer; outcome assessment; participatory research; patient attendance; patient compliance; patient participation; Perceived Stress Scale; pilot study; Pittsburgh Sleep Quality Index; preliminary data; pretest posttest design; priority journal; program evaluation; program feasibility; prospective study; qualitative research; quantitative study; six minute walk test; skill; sleep disorder; sleep quality; social interaction; physiological stress; stress management; stretching; thematic analysis

Age and race distribution in patients in phase III oncology clinical trials - Gopishetty, S.; Kota, V.; Guddati, A.K. (American Journal of Translational Research, 2020)
Background: Geriatric patients and minority patients are often under-represented in cancer clinical trials. The presence of multiple comorbidities makes geriatric patients ineligible for most clinical trials. Racial diversity may vary by geographical location and socio-economically backward areas may have a very different racial mix. The increase in cancer incidence in geriatric patients' raises the question of applicability of the results is such clinical trials. This study also explores the representation of different races in phase 3 clinical trials conducted in the past 10 years. Methods: Data about Phase III trials was extracted from the clinical trials.gov for 3 common solid organs and 3 hematological malignancies [breast, colon, lung, diffuse large B-cell lymphoma (DLBCL), acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL)]. The time period studied was for the past 10 years and included only adult patients (≥18 years). The age and race distribution of the patient population in these trials were extracted and analyzed. Results: Geriatric patients and minorities are under-represented in all phase III cancer clinical trials. The range of the proportion of geriatric patients varied from 10% to 40%. African American and Asian patients are under-represented in all phase III cancer clinical trials. Conclusions: The results of phase III clinical trials that are currently conducted on non-geriatric and Caucasian patient population may not meaningfully be applicable to geriatric patients and minorities. This study highlights the disparity of age and race for patients enrolled in clinical trials as against the patients seen in the real world.
Keywords: acute lymphoblastic leukemia; acute myeloid leukemia; adult; African American; article; Asian; breast; cancer incidence; case report; Caucasian; clinical article; colon; diffuse large B cell lymphoma; female; geriatric patient; human; lung; male; phase 3 clinical trial

Effect of Supplementation with Marine ω-3 Fatty Acid on Risk of Colorectal Adenomas and Serrated Polyps in the US General Population: A Prespecified Ancillary Study of a Randomized Clinical Trial - Song, M.; Lee, I.-M.; Manson, J.E.; Buring, J.E.; Dushkes, R.; Gordon, D.; Walter, J.; Wu, K.; Chan, A.T.; Ogino, S.; Fuchs, C.S.; Meyerhardt, J.A.; et al. (JAMA Oncology, 2020)
Importance: Marine ω-3 fatty acid has been suggested to protect against colorectal cancer. Objective: To assess the effect of daily marine ω-3 fatty acid supplementation on the risk of colorectal cancer precursors, including conventional adenomas and serrated polyps. Design, Setting, and Participants: This study was a prespecified ancillary study of the placebo-controlled randomized clinical trial VITAL (Vitamin D and Omega-3 Trial). An intention-to-treat analysis was used to examine the effect of daily marine ω-3 supplements among 25871 adults in the US general population (including 5106 African American persons) free of cancer and cardiovascular disease at enrollment. Randomization was from November 2011 to March 2014, and intervention ended as planned on December 31, 2017. Interventions: Marine ω-3 fatty acid, 1 g daily (which included eicosapentaenoic acid, 460 mg, and docosahexaenoic acid, 380 mg) and vitamin D3 (2000 IU daily) supplements. Main Outcomes and Measures: Risk of conventional adenomas (including tubular adenoma, tubulovillous adenoma, villous adenoma, and adenoma with high-grade dysplasia) or serrated polyps (including hyperplastic polyp, traditional serrated adenoma, and sessile serrated polyp). In a subset of participants who reported receiving a diagnosis of polyp on follow-up questionnaires, endoscopic and pathologic records were obtained to confirm the diagnosis. Odds ratios (ORs) and 95% CIs were calculated using logistic regression, after adjusting for age, sex, vitamin D treatment assignment, and use of endoscopy. Secondary analyses were performed according to polyp features and participants' characteristics. Results: The demographic characteristics of participants at randomization were well balanced between the treatment and placebo groups; for example, 50.6% vs 50.5% were women, and 19.7% vs 19.8% were African American persons were included in each group. The mean (SD) age was 67.1 (7.1) years in the placebo group and 67.2 (7.1) in the ω-3 treatment group. During a median follow-up of 5.3 years (range, 3.8-6.1 years), 294 cases of conventional adenomas were documented in the ω-3 group and 301 in the control group (multivariable OR, 0.98; 95% CI, 0.83-1.15) (1:1 ratio between number of cases and number of participants). In addition, 174 cases of serrated polyps were documented in the ω-3 group and 167 in the control group (OR, 1.05; 95% CI, 0.84-1.29). Null associations were found for polyp subgroups according to size, location, multiplicity, or histology. In secondary analyses, marine ω-3 treatment appeared to be associated with lower risk of conventional adenomas among individuals with low plasma levels of ω-3 index at baseline (OR, 0.76; 95% CI, 0.57-1.02; P =.03 for interaction by ω-3 index). A beneficial association of supplementation was also noted in the African American population (OR, 0.59; 95% CI, 0.35-1.00) but not in other racial/ethnic groups (P =.11 for interaction). Conclusions and Relevance: Supplementation with marine ω-3 fatty acids, 1 g per day, was not associated with reduced risk of colorectal cancer precursors. A potential benefit of this supplementation for individuals with low baseline ω-3 levels or for African American persons requires further confirmation.
Keywords: NCT01169259; colecalciferol; docosahexaenoic acid; icosapentaenoic acid; marine omega 3 fatty acid; omega 3 fatty acid; placebo; unclassified drug; African American; aged; article; cancer risk; colorectal adenoma; colorectal cancer; colorectal polyp; fatty acid blood level; female; follow up; histopathology; human; major clinical study; male; race difference; risk reduction; tumor localization; tumor volume; United States

Effect of a Patient Decision Aid on Lung Cancer Screening Decision-Making by Persons Who Smoke: A Randomized Clinical Trial - Volk, R.J.; Lowenstein, L.M.; Leal, V.B.; Escoto, K.H.; Cantor, S.B.; Munden, R.F.; Rabius, V.A.; Bailey, L.; Cinciripini, P.M.; Lin, H.; Housten, A.J.; Luckett, P.G.; et al. (JAMA Network Open, 2020)
Importance: Lung cancer screening with low-dose computed tomography lowers lung cancer mortality but has potential harms. Current guidelines support patients receiving information about the benefits and harms of lung cancer screening during decision-making. Objective: To examine the effect of a patient decision aid (PDA) about lung cancer screening compared with a standard educational material (EDU) on decision-making outcomes among smokers. Design, Setting, and Participants: This randomized clinical trial was conducted using 13 state tobacco quitlines. Current and recent tobacco quitline clients who met age and smoking history eligibility for lung cancer screening were enrolled from March 30, 2015, to September 12, 2016, and followed up for 6 months until May 5, 2017. Data analysis was conducted between May 5, 2017, and September 30, 2018. Interventions: Participants were randomized to the PDA video Lung Cancer Screening: Is It Right for Me? (n = 259) or to EDU (n = 257). Main Outcomes and Measures: The primary outcomes were preparation for decision-making and decisional conflict measured at 1 week. Secondary outcomes included knowledge, intentions, and completion of screening within 6 months of receiving the intervention measured by patient report. Results: Of 516 quit line clients enrolled, 370 (71.7%) were younger than 65 years, 320 (62.0%) were female, 138 (26.7%) identified as black, 47 (9.1%) did not have health insurance, and 226 (43.8%) had a high school or lower educational level. Of participants using the PDA, 153 of 227 (67.4%) were well prepared to make a screening decision compared with 108 of 224 participants (48.2%) using EDU (odds ratio [OR], 2.31; 95% CI, 1.56-3.44; P <.001). Feeling informed about their screening choice was reported by 117 of 234 participants (50.0%) using a PDA compared with 66 of 233 participants (28.3%) using EDU (OR, 2.56; 95% CI, 1.72-3.79; P <.001); 159 of 234 participants (68.0%) using a PDA compared with 110 of 232 (47.4%) participants using EDU reported being clear about their values related to the harms and benefits of screening (OR, 2.37; 95% CI, 1.60-3.51; P <.001). Participants using a PDA were more knowledgeable about lung cancer screening than participants using EDU at each follow-up assessment. Intentions to be screened and screening behaviors did not differ between groups. Conclusions and Relevance: In this study, a PDA delivered to clients of tobacco quit lines improved informed decision-making about lung cancer screening. Many smokers eligible for lung cancer screening can be reached through tobacco quit lines.
Keywords: adult; article; cancer screening; data analysis; decision making; female; follow up; health insurance; high school; human; lung cancer; major clinical study; male; outcome assessment; randomized controlled trial; smoking; tobacco; videorecording

Incidence and prognosis of liver metastasis at diagnosis: A pan-cancer population-based study - Wang, S.; Feng, Y.; Swinnen, J.; Oyen, R.; Li, Y.; Ni, Y. (American Journal of Cancer Research, 2020)
Metastasis is a major cause of cancer-related death and liver metastasis (LM) is a distinct type for its relatively good prognosis after timely treatment for selected patients. However, a generalizable estimation of incidence and prognosis of LM is lacking. Cancer patients with known LM status in the Surveillance, Epidemiology and End Results database were enrolled in the present study. The incidence and prognosis of LM were calculated by primary cancer type and clinicopathological factors. Among 1,630,725 cases, 105,329 (6.46%) cases present LM at diagnosis, with a median survival of 4 months. LM presents at diagnosis in 39.96% of pancreatic cancer, 16.00% of colorectal cancer (CRC) and 12.68% of lung cancer. Of all LM cases, 25.58% originated from lung cancer, with 24.76% from CRC and 17.55% from pancreatic cancer. LM originated from small intestine cancer shows the best prognosis (median survival: 30 months), followed by testis cancer (25 months) and breast cancer (15 months). Subgroup analyses demonstrated disparities in incidence and prognosis of LM, with higher incidence and poorer prognosis in the older population, African American, male, and patients with inferior socioeconomic status. The current study provides a generalizable data resource for the epidemiology of LM, which may help tailor screening protocol, design clinical trials and estimate disease burden.
Keywords: adult; African American; aged; article; breast cancer; cancer incidence; cancer patient; cancer prognosis; cancer staging; cancer survival; colorectal cancer; educational status; female; health insurance; household income; human; liver metastasis; lung cancer; major clinical study; male; marriage; median survival time; pancreas cancer; population research; primary tumor; sex difference; small intestine cancer; social status; testis cancer; unemployment; very elderly

Multicentre, prospective, randomised study comparing the diagnostic yield of colon capsule endoscopy versus CT colonography in a screening population (the TOPAZ study) - Cash, B.D.; Fleisher, M.R.; Fern, S.; Rajan, E.; Haithcock, R.; Kastenberg, D.M.; Pound, D.; Papageorgiou, N.P.; Fernández-Urién, I.; Schmelkin, I.J.; Rex, D.K. (Gut, 2020)
Objective: Colon capsule endoscopy (CCE) has shown promise for colorectal neoplasia detection compared with optical colonoscopy (OC), but has not been compared with other screening tests in average risk screening patients. Design: Patients 50 to 75 years of age (African Americans, 45-75 years) were randomised to CCE or CT colonography (CTC) and subsequent blinded OC. The primary endpoint was diagnostic yield of polyps ≥6 mm with CCE or CTC. Secondary endpoints included accuracy for size and histology, examination completeness, number/proportion of subjects with polyps and adenomas ≥6 mm and ≥10 mm, subject satisfaction and safety. Results: From 320 enrolled subjects, data from 286 (89.4%) were evaluable. The proportion of subjects with any polyp ≥6 mm confirmed by OC was 31.6% for CCE versus 8.6% for CTC (pPr non-inferiority and superiority=0.999). The diagnostic yield of polyps ≥10 mm was 13.5% with CCE versus 6.3% with CTC (pPr non-inferiority=0.9954). The sensitivity and specificity of CCE for polyps ≥6 mm was 79.2% and 96.3% while that of CTC was 26.8% and 98.9%. The sensitivity and specificity of CCE for polyps ≥10 mm was 85.7% and 98.2% compared with 50% and 99.1% for CTC. Both tests were well tolerated/safe. Conclusion: CCE was superior to CTC for detection of polyps ≥6 mm and non-inferior for identification of polyps ≥10 mm. CCE should be considered comparable or superior to CTC as a colorectal neoplasia screening test, although neither test is as effective as OC.
Keywords: adult; African American; aged; article; cancer screening; cancer size; capsule endoscopy; colon adenoma; colon polyp; colorectal cancer; colorectal tumor; computed tomographic colonography; controlled study; diagnostic test accuracy study; diagnostic value; drug safety; female; histology; histopathology; human; human tissue; major clinical study; male; middle aged; multicenter study; prospective study; randomized controlled trial; satisfaction; screening test; sensitivity and specificity; unclassified drug

THRIVE study protocol: a randomized controlled trial evaluating a web-based app and tailored messages to improve adherence to adjuvant endocrine therapy among women with breast cancer - Paladino, A.J.; Anderson, J.N.; Krukowski, R.A.; Waters, T.; Kocak, M.; Graff, C.; Blue, R.; Jones, T.N.; Buzaglo, J.; Vidal, G.; Schwartzberg, L.; Graetz, I. (BMC health services research, 2019)
BACKGROUND: Long-term use of adjuvant endocrine therapy (AET) among women with early-stage, hormone receptor-positive breast cancer significantly reduces the risk of hospitalizations, cancer recurrence, and mortality. AET is associated with adverse symptoms that often result in poor adherence. A web-enabled app offers a novel way to communicate and manage symptoms for women on AET. In a region with significant racial disparities in breast cancer outcomes, our study tests the impact of a web-enabled app that collects and transmits patient-reported symptoms to healthcare teams to facilitate timely and responsive symptom management on medication adherence. METHODS: In this randomized controlled trial, we randomize 300 patients initiating AET to one of three arms: 1) an "App" group (n = 100) that receives weekly reminders to use the THRIVE study app; 2) an "App+Feedback" group (n = 100) that receives weekly reminders and tailored feedback based on their use of the app; or 3) a "Usual Care" group (n = 100) that receives usual care only. Participants are stratified by race: 50% White and 50% Black. The duration of the intervention is six months following enrollment, and outcomes are assessed at 12-months. The primary outcome is adherence, which is captured using an electronic monitoring pillbox. Secondary outcomes include symptom burden, quality of life, self-efficacy for managing symptoms, and healthcare costs. We also evaluate the impact of the intervention on racial disparities in adherence. Data are derived from three sources: electronic health record data to capture treatment changes, healthcare utilization, and health outcomes; self-report survey data related to adherence, symptom burden, and quality of life; and an electronic medication monitoring device that captures adherence. DISCUSSION: A successful web-enabled intervention could be disseminated across systems, conditions, and populations. By evaluating the impact of this intervention on a comprehensive set of measures, including AET adherence, patient outcomes, and costs, our study will provide valuable and actionable results for providers, policy makers, and insurers who strive to achieve the "Triple Aim" - reduce costs while improving health outcomes and the patient care experience. TRIAL REGISTRATION: NCT03592771. Prospectively registered on July 19, 2018.
Keywords: NCT03592771; African American; breast tumor; Caucasian; female; human; Internet; medication compliance; mobile application; multimodality cancer therapy; patient compliance; psychology; quality of life; questionnaire; randomized controlled trial (topic); reminder system; self report; tumor recurrence

Real-world outcomes of sipuleucel-T treatment in PROCEED, a prospective registry of men with metastatic castration-resistant prostate cancer - Higano, C.S.; Armstrong, A.J.; Sartor, A.O.; Vogelzang, N.J.; Kantoff, P.W.; McLeod, D.G.; Pieczonka, C.M.; Penson, D.F.; Shore, N.D.; Vacirca, J.; Concepcion, R.S.; Tutrone, R.F.; et al. (Cancer, 2019)
Background: The large registry, PROVENGE Registry for the Observation, Collection, and Evaluation of Experience Data (PROCEED)(NCT01306890), evaluated sipuleucel-T immunotherapy for asymptomatic/minimally symptomatic metastatic castration-resistant prostate cancer (mCRPC). Methods: PROCEED enrolled patients with mCRPC receiving 3 biweekly sipuleucel-T infusions. Assessments included overall survival (OS), serious adverse events (SAEs), cerebrovascular events (CVEs), and anticancer interventions (ACIs). Follow-up was for ≥3 years or until death or study withdrawal. Results: In 2011-2017, 1976 patients were followed for 46.6 months (median). The median age was 72 years, and the baseline median prostate-specific antigen level was 15.0 ng/mL; 86.7% were white, and 11.6% were African American. Among the patients, 1902 had 1 or more sipuleucel-T infusions. The median OS was 30.7 months (95% confidence interval [CI], 28.6-32.2 months). Known prognostic factors were independently associated with OS in a multivariable analysis. Among the 1255 patients who died, 964 (76.8%) died of prostate cancer (PC) progression. The median time from the first infusion to PC death was 42.7 months (95% CI, 39.4-46.2 months). The incidence of sipuleucel-T–related SAEs was 3.9%. The incidence of CVEs was 2.8%, and the rate per 100 person-years was 1.2 (95% CI, 0.9-1.6). The CVE incidence among 11,972 patients with mCRPC from the Surveillance, Epidemiology, and End Results–Medicare database was 2.8%; the rate per 100 person-years was 1.5 (95% CI, 1.4-1.7). One or more ACIs (abiraterone, enzalutamide, docetaxel, cabazitaxel, or radium 223) were received by 77.1% of the patients after sipuleucel-T; 32.5% and 17.4% of the patients experienced 1- and 2-year treatment-free intervals, respectively. Conclusions: PROCEED provides contemporary survival data for sipuleucel-T–treated men in a real-world setting of new life-prolonging agents, which will be useful in discussing treatment options with patients and in powering future trials with sipuleucel-T. The safety and tolerability of sipuleucel-T in PROCEED were consistent with previous findings.
Keywords: adverse drug reaction; African American; aged; article; cancer growth; cancer patient; cancer prognosis; cancer survival; castration resistant prostate cancer; cerebrovascular disease; controlled study; drug safety; drug therapy; drug withdrawal; follow up; gene expression; human; immunotherapy; incidence; major clinical study; male; medicare; overall survival; pharmacokinetics; prospective study; protein expression; side effect; abiraterone; cabazitaxel; docetaxel; endogenous compound; enzalutamide; prostate specific antigen; radium; sipuleucel T

Recurrent PTPRT/JAK2 mutations in lung adenocarcinoma among African Americans - Mitchell, K.A.; Nichols, N.; Tang, W.; Walling, J.; Stevenson, H.; Pineda, M.; Stefanescu, R.; Edelman, D.C.; Girvin, A.T.; Zingone, A.; Sinha, S.; Bowman, E.; et al. (Nature Communications, 2019)
Reducing or eliminating persistent disparities in lung cancer incidence and survival has been challenging because our current understanding of lung cancer biology is derived primarily from populations of European descent. Here we show results from a targeted sequencing panel using NCI-MD Case Control Study patient samples and reveal a significantly higher prevalence of PTPRT and JAK2 mutations in lung adenocarcinomas among African Americans compared with European Americans. This increase in mutation frequency was validated with independent WES data from the NCI-MD Case Control Study and TCGA. We find that patients carrying these mutations have a concomitant increase in IL-6/STAT3 signaling and miR-21 expression. Together, these findings suggest the identification of these potentially actionable mutations could have clinical significance for targeted therapy and the enrollment of minority populations in clinical trials.
Keywords: NCT00339859; spectrophotometer; interleukin 6; Janus kinase 2; microRNA 21; receptor like protein tyrosine phosphatase; STAT3 protein; adolescent; adult; African American; aged; article; cancer incidence; carcinogenesis; case control study; child; clinical article; clinical trial; controlled study; DNA extraction; epigenetics; female; gene expression; gene frequency; gene mutation; gene sequence; human; human tissue; infant; lung adenocarcinoma; lung cancer; male; molecularly targeted therapy; mutation rate; mutational analysis; newborn; polymerase chain reaction; prevalence; signal transduction; single nucleotide polymorphism; smoking; spectrophotometry; squamous cell lung carcinoma; whole exome sequencing; NanoDrop

A comparative effectiveness analysis of the PBCG vs. PCPT risks calculators in a multi-ethnic cohort - Carbunaru, S.; Nettey, O.S.; Gogana, P.; Helenowski, I.B.; Jovanovic, B.; Ruden, M.; Hollowell, C.M.P.; Sharifi, R.; Kittles, R.A.; Schaeffer, E.; Gann, P.; Murphy, A.B. (BMC Urology, 2019)
Background: Predictive models that take race into account like the Prostate Cancer Prevention Trial Risk Calculator 2.0 (PCPT RC) and the new Prostate Biopsy Collaborative Group (PBCG) RC have been developed to equitably mitigate the overdiagnosis of prostate specific antigen (PSA) screening. Few studies have compared the performance of both calculators across racial groups. Methods: From 1485 prospectively recruited participants, 954 men were identified undergoing initial prostate biopsy for abnormal PSA or digital rectal examination in five Chicago hospitals between 2009 and 2014. Discrimination, calibration, and frequency of avoided biopsies were calculated to assess the performance of both risk calculators. Results: Of 954 participants, 463 (48.5%) were Black, 355 (37.2%) were White, and 136 (14.2%) identified as Other. Biopsy results were as follows: 310 (32.5%) exhibited no cancer, 323 (33.9%) indolent prostate cancer, and 321 (33.6%) clinically significant prostate cancer (csPCa). Differences in area under the curve (AUC)s for the detection of csPCa between PCPT and PBCG were not statistically different across all racial groups. PBCG did not improve calibration plots in Blacks and Others, as it showed higher levels of overprediction at most risk thresholds. PCPT led to an increased number of avoidable biopsies in minorities compared to PBCG at the 30% threshold (68% vs. 28% of all patients) with roughly similar rates of missed csPCa (23% vs. 20%). Conclusion: Significant improvements were noticed in PBCG's calibrations and net benefits in Whites compared to PCPT. Since PBCG's improvements in Blacks are disputable and potentially biases a greater number of low risk Black and Other men towards unnecessary biopsies, PCPT may lead to better biopsy decisions in racial minority groups. Further comparisons of commonly used risk calculators across racial groups is warranted to minimize excessive biopsies and overdiagnosis in ethnic minorities.
Keywords: prostate specific antigen; adult; aged; area under the curve; article; Black person; calibration; Caucasian; cohort analysis; comparative effectiveness; ethnic group; human; Illinois; major clinical study; male; prediction; prospective study; prostate biopsy; Prostate Biopsy Collaborative Group Risk Calculator; prostate cancer; Prostate Cancer Prevention Trial Risk Calculator; renal system parameters; trend study

Challenges and opportunities using online portals to recruit diverse patients to behavioral trials - Tabriz, A.A.; Fleming, P.J.; Shin, Y.; Resnicow, K.; Jones, R.M.; Flocke, S.A.; Shires, D.A.; Hawley, S.T.; Willens, D.; Lafata, J.E. (Journal of the American Medical Informatics Association, 2019)
We describe the use of an online patient portal to recruit and enroll primary care patients in a randomized trial testing the effectiveness of a colorectal cancer (CRC) screening decision support program. We use multiple logistic regression to identify patient characteristics associated with trial recruitment, enrollment, and engagement. We found that compared to Whites, Blacks had lower odds of viewing the portal message (OR = 0.46, 95% CI = 0.37-0.57), opening the attached link containing the study material (OR = 0.75, 95% CI = 0.62-0.92), and consenting to participate in the trial (OR = 0.85, 95% CI = 0.67-0.93). We also found that compared to Whites, Asians had lower odds of viewing the portal message (OR = 0.53, 95% CI = 0.33-0.64), opening the attached link containing the study material (OR = 0.76, 95% CI = 0.54-0.97), consenting to participate in the trial (OR = 0.68, 95% CI = 0.53-0.95), and completing the trial's baseline questionnaire (OR = 0.59, 95% CI = 0.36-0.90). While portals offer an opportunity to mitigate human bias in trial invitations, because of racial disparities - not only in who has a portal account, but in how they interact with trial recruitment and enrollment material within the portal - using portals alone for trial recruitment may generate study samples that are not racially diverse.
Keywords: adult; article; Black person; cancer screening; Caucasian; colorectal cancer; decision support system; female; human; major clinical study; male; medical record; middle aged; online system; patient information; primary medical care; questionnaire

Use of multiparametric magnetic resonance imaging and fusion-guided biopsies to properly select and follow African-American men on active surveillance - Bloom, J.B.; Lebastchi, A.H.; Gold, S.A.; Hale, G.R.; Sanford, T.; Mehralivand, S.; Ahdoot, M.; Rayn, K.N.; Czarniecki, M.; Smith, C.; Valera, V.; Wood, B.J.; et al. (BJU International, 2019)
Objectives: To determine the rate of Gleason Grade Group (GGG) upgrading in African-American (AA) men with a prior diagnosis of low-grade prostate cancer (GGG 1 or GGG 2) on 12-core systematic biopsy (SB) after multiparametric magnetic resonance imaging (mpMRI) and fusion biopsy (FB); and whether AA men who continued active surveillance (AS) after mpMRI and FB fared differently than a predominantly Caucasian (non-AA) population. Patients and methods: A database of men who had undergone mpMRI and FB was queried to determine rates of upgrading by FB amongst men deemed to be AS candidates based on SB prior to referral. After FB, Kaplan–Meier curves were generated for AA men and non-AA men who then elected AS. The time to GGG upgrading and time continuing AS were compared using the log-rank test. Results: AA men referred with GGG 1 disease on previous SB were upgraded to GGG ≥3 by FB more often than non-AA men, 22.2% vs 12.7% (P = 0.01). A total of 32 AA men and 258 non-AA men then continued AS, with a median (interquartile range) follow-up of 39.19 (24.24–56.41) months. The median time to progression was 59.7 and 60.5 months, respectively (P = 0.26). The median time continuing AS was 61.9 months and not reached, respectively (P = 0.80). Conclusions: AA men were more likely to be upgraded from GGG 1 on SB to GGG ≥3 on initial FB; however, AA and non-AA men on AS subsequently progressed at similar rates following mpMRI and FB. A greater tendency for SB to underestimate tumour grade in AA men may explain prior studies that have shown AA men to be at higher risk of progression during AS.
Keywords: nuclear magnetic resonance scanner; active surveillance; adult; African American; article; cancer epidemiology; cancer growth; Caucasian; cohort analysis; controlled study; follow up; fusion biopsy; Gleason score; human; human tissue; major clinical study; male; multiparametric magnetic resonance imaging; patient referral; patient selection; priority journal; prospective study; prostate biopsy; prostate cancer; retrospective study; Achieva

Old vs new: Risk factors predicting early onset colorectal cancer - Syed, A.R.; Thakkar, P.; Horne, Z.D.; Abdul-Baki, H.; Kochhar, G.; Farah, K.; Thakkar, S. (World Journal of Gastrointestinal Oncology, 2019)
BACKGROUND Colorectal cancer (CRC) is the second leading cause of all cancer related deaths in the United States and Europe. Although the incidence has been decreasing for individuals' = 50, it has been on the rise for individuals < 50. AIM To identify potential risk factors for early-onset CRC. METHODS A population-based cohort analysis using a national database, Explorys, screened all patients with an active electronic medical record from January 2012 to December 2016 with a diagnosis of CRC. Subgroups were stratified based on age (25 - 49 years vs = 50 years). Demographics, comorbidities, and symptom profiles were recorded and compared between both age groups. Furthermore, the younger group was also compared with a control group consisting of individuals aged 25-49 years within the same timeframe without a diagnosis of CRC. Twentydata points for CRC related factors were analyzed to identify potential risk factors specific to early-onset CRC. RESULTS A total of 68860 patients were identified with CRC, of which 5710 (8.3%) were younger than 50 years old, with 4140 (73%) between 40-49 years of age. Multivariable analysis was reported using odds ratio (OR) with 95%CI and demonstrated that several factors were associated with an increased risk of CRC in the early-onset group versus the later-onset group. These factors included: African-American race (OR 1.18, 95%CI: 1.09-1.27, P < 0.001), presenting symptoms of abdominal pain (OR 1.82, 95%CI: 1.72-1.92, P <0.001), rectal pain (OR 1.50, 95%CI: 1.28-1.77, P < 0.001), altered bowel function (OR 1.12, 95%CI: 1.05-1.19, P = 0.0005), having a family history of any cancer (OR 1.78, 95%CI: 1.67- 1.90, P < 0.001), gastrointestinal (GI) malignancy (OR 2.36, 95%CI: 2.18-2.55, P < 0.001), polyps (OR 1.41, 95%CI: 1.08-1.20, P < 0.001), and obesity (OR 1.14, 95%CI: 1.08-1.20, P < 0.001). Comparing the early-onset cohort versus the control group, factors that were associated with an increased risk of CRC were: male gender (OR 1.34, 95%CI: 1.27-1.41), P < 0.001), Caucasian (OR 1.48, 95%CI: 1.40-1.57, P < 0.001) and African-American race (OR 1.25, 95%CI: 1.17-1.35, P < 0.001), presenting symptoms of abdominal pain (OR 4.73, 95%CI: 4.49-4.98, P < 0.001), rectal pain (OR 7.48, 95%CI: 6.42-8.72, P < 0.001), altered bowel function (OR 5.51, 95%CI: 5.19-5.85, P < 0.001), rectal bleeding (OR 9.83, 95%CI: 9.12-10.6, P < 0.001), weight loss (OR 7.43, 95%CI: 6.77-8.15, P < 0.001), having a family history of cancer (OR 11.66, 95%CI: 10.97-12.39, P < 0.001), GI malignancy (OR 28.67, 95%CI: 26.64-30.86, P < 0.001), polyps (OR 8.15, 95%CI: 6.31-10.52, P < 0.001), tobacco use (OR 2.46, 95%CI: 2.33-2.59, P < 0.001), alcohol use (OR 1.71, 95%CI: 1.62-1.80, P < 0.001), presence of colitis (OR 4.10, 95%CI: 3.79-4.43, P < 0.001), and obesity (OR 2.88, 95%CI: 2.74-3.04, P < 0.001). CONCLUSION Pending further investigation, these potential risk factors should lower the threshold of suspicion for early CRC and potentially be used to optimize guidelines for early screening.
Keywords: abdominal pain; adult; African American; aged; alcohol consumption; article; cancer diagnosis; cancer risk; cancer screening; Caucasian; cohort analysis; colitis; colorectal cancer; comparative study; controlled study; early cancer; electronic medical record; female; gastrointestinal tumor; groups by age; human; hyperlipidemia; hypertension; intestine function disorder; major clinical study; male; middle aged; obesity; patient selection; rectum hemorrhage; risk factor; stomach polyp; very elderly

Follow-up approaches to a health literacy intervention to increase colorectal cancer screening in rural community clinics: A randomized controlled trial - Arnold, C.L.; Rademaker, A.W.; Morris, J.D.; Ferguson, L.A.; Wiltz, G.; Davis, T.C. (Cancer, 2019)
Background: Significant disparities exist in colorectal cancer (CRC) screening rates among those of low socioeconomic status, with fewer years of education, lacking health insurance, or living in rural areas. Methods: A randomized controlled trial was conducted to compare the effectiveness of 2 follow-up approaches to a health literacy intervention to improve CRC screening: automated telephone call or personal call. Patients aged 50 to 75 years residing in 4 rural community clinics in Louisiana were given a structured interview that assessed demographic, health literacy and CRC screening barriers, knowledge, and attitudes. All were given health literacy–informed CRC education, a patient-friendly CRC screening pamphlet, simplified fecal immunochemical test (FIT) instructions, and a FIT kit, and a “teach-back” method was used to confirm understanding. Patients were randomized to 1 of 2 telephone follow-up arms. If they did not mail their FIT kit within 4 weeks, they received a reminder call and were called again at 8 weeks if the test still was not received. Results: A total of 620 patients were enrolled. Approximately 55% were female, 66% were African American, and 40% had limited literacy. The overall FIT completion rate was 68%: 69.2% in the automated telephone call arm and 67% in the personal call arm. Greater than one-half of the patients (range, 58%-60%) returned the FIT kit without receiving a telephone call. There was no difference noted with regard to the effectiveness of the follow-up calls; each increased the return rate by 9%. Conclusions: Providing FIT kits and literacy-appropriate education at regularly scheduled clinic visits with a follow-up telephone call when needed was found to increase CRC screening among low-income, rural patients. The lower cost automated call was just as effective as the personal call.
Keywords: NCT02360605; adult; African American; aged; article; attitude to health; cancer screening; colorectal cancer; comparative effectiveness; controlled study; cost; female; follow up; health literacy; human; intervention study; lowest income group; major clinical study; male; occult blood test; priority journal; randomized controlled trial; risk factor; rural population

Black Light Smokers: How Nicotine Intake and Carcinogen Exposure Differ Across Various Biobehavioral Factors - St.Helen, G.; Benowitz, N.L.; Ahluwalia, J.S.; Tyndale, R.F.; Addo, N.; Gregorich, S.E.; Pérez-Stable, E.J.; Cox, L.S. (Journal of the National Medical Association, 2019)
Objective: The study objective was to identify biobehavioral variables associated with greater intake of nicotine and a tobacco carcinogen among Black light smokers who smoke 1 to 10 cigarettes per day (CPD). Methods: We analyzed baseline data collected from 426 Black light smokers enrolled in Kick It at Swope III (KIS III), a smoking cessation trial for Black smokers. We examined differences in concentrations of tobacco biomarkers, including urinary total nicotine equivalents (TNE) and total 4-(methylnitrosamino)-1-(3)pyridyl-1-butanonol (NNAL; a human carcinogen), across gender, age, plasma nicotine metabolite ratio (NMR), CPD, and measures of tobacco dependence, including time to first cigarette (TFC), using ANOVA. Results: Tobacco biomarker levels were significantly higher among those who smoked more CPD (6–10 vs 1–5 CPD) and those with greater reported physical dependence on tobacco. Concurrently, those who smoked 1–5 CPD smoked each cigarette more intensely than those who smoked 6–10 CPD. While we found no gender differences overall, among those who smoked 1–5 CPD, women had higher NNAL levels compared to men. The rate of nicotine metabolism, measured by the nicotine metabolite ratio, was not significantly related to TNE or NNAL levels. Conclusion: Among Black Light smokers, higher cigarette consumption and greater physical dependence—but not rate of nicotine metabolism, menthol use, or socioeconomic status—were associated with greater toxicant exposure and thus a likely increased risk of tobacco-related diseases. The lack of data on light smokers, and specifically on Blacks, make this observation important given the disproportionate burden of lung cancer in this population.
Keywords: cigarette; 4 (methylnitrosamino) 1 (3)pyridyl 1 butanonol; carcinogen; nicotine; unclassified drug; adult; article; Black person; controlled study; female; human; major clinical study; male; middle aged; priority journal; sex difference; smoking; smoking cessation; tobacco dependence

A 25-year Period Analysis of Other-cause Mortality in Localized Prostate Cancer - Knipper, S.; Pecoraro, A.; Palumbo, C.; Rosiello, G.; Luzzago, S.; Tian, Z.; Briganti, A.; Saad, F.; Tilki, D.; Graefen, M.; Karakiewicz, P.I. (Clinical Genitourinary Cancer, 2019)
Other-cause mortality should have decreased over time in patients with prostate cancer as patient selection for diagnosis and treatment may have improved. We tested this hypothesis in 367,884 patients with prostate cancer treated with radical prostatectomy or radiotherapy within the Surveillance, Epidemiology, and End Results database and observed important other-cause mortality reduction over the last 25 years.
Keywords: adult; African American; aged; article; cancer radiotherapy; cancer survival; Caucasian; cause of death; external beam radiotherapy; follow up; Hispanic; human; major clinical study; male; mortality; patient selection; prostate cancer; prostatectomy; trend study

Factors associated with willingness to provide biospecimens for genetics research among African American cancer survivors - Ewing, A.T.; Kalu, N.; Cain, G.; Erby, L.H.; Ricks-Santi, L.J.; Tetteyfio-Kidd Telemaque, E.; Scott, D.M. (Journal of Community Genetics, 2019)
This study evaluated factors associated with willingness to provide biospecimens for cancer genetic research among African American cancer survivors. A total of 200 African American adults diagnosed with breast, colon, and/or prostate cancers completed a self-administered survey. Family history information, beliefs about cancer research, cancer genetics and disparities knowledge, willingness to provide a biospecimen, and demographics were obtained. Chi-square, independent samples t tests, and logistic regression analyses were performed. Overall, 79% of this sample was willing to provide a biospecimen for cancer genetics research. Independent associations of willingness to provide a biospecimen existed among demographics (males (p = 0.041)), those who believed in the importance of genetic causes of cancer (p < 0.001), individuals who believe it is important to participate in genetics research (p < 0.001), and those who indicated they would participate in genetics research to help future generations (p = 0.026). Overall, 12.5–56% of participants demonstrated some level of genetics and cancer disparities. This study identified factors that may be incorporated into future research interventions to engage the African American cancer population in cancer genetics biobanking research.
Keywords: adult; African American; anatomical concepts; article; biospecimen; breast cancer; cancer genetics; cancer survivor; chi square test; cohort analysis; colon cancer; controlled study; demography; disease association; family history; female; health behavior; health disparity; health survey; human; knowledge; logistic regression analysis; major clinical study; male; patient participation; population research; priority journal; prostate cancer; risk factor; Student t test

Effect of Erlotinib Plus Bevacizumab vs Erlotinib Alone on Progression-Free Survival in Patients with Advanced EGFR-Mutant Non-Small Cell Lung Cancer: A Phase 2 Randomized Clinical Trial - Stinchcombe, T.E.; Jänne, P.A.; Wang, X.; Bertino, E.M.; Weiss, J.; Bazhenova, L.; Gu, L.; Lau, C.; Paweletz, C.; Jaslowski, A.; Gerstner, G.J.; Baggstrom, M.Q.; et al. (JAMA Oncology, 2019)
Importance: Erlotinib is a standard first-line therapy for patients with epidermal growth factor receptor (EGFR)-mutant non-small cell lung cancer (NSCLC). Median progression-free survival (PFS) with erlotinib is approximately 10 months. Objective: To determine whether adding bevacizumab to erlotinib treatment results in superior progression-free survival compared with erlotinib alone. Design, Setting, and Participants: This phase 2 randomized clinical trial compared erlotinib plus bevacizumab with erlotinib alone in EGFR-mutant NSCLC. The trial was conducted in 17 US academic and community medical centers among 88 patients with EGFR exon 19 deletion or exon 21 L858R mutation based on local testing and stage 4 NSCLC who were eligible for bevacizumab. Patients were enrolled between November 2, 2012, and August 22, 2016, and followed up for a median (range) of 33 (0.7-62.5) months. Data were analyzed on August 28, 2018, and included data from November 2, 2012, to August 20, 2018. Interventions: Patients were randomized with equal allocation to 150 mg of oral erlotinib daily alone or with 15 mg/kg of intravenous bevacizumab every 3 weeks. Study therapy continued until disease progression, unacceptable adverse event, or withdrawal of consent. Main Outcomes and Measures: The primary outcome was PFS as assessed by the investigator; secondary outcomes were objective response rate (ORR), adverse events, and overall survival (OS). Analysis was designed to detect a hazard ratio (HR) of 0.667 for PFS (an improvement from a median PFS of 10 to 15 months). Results: Among 88 patients enrolled, the median (range) age was 63 (31-84) years; 62 patients (70%) were female; 75 (85%) were white, 8 (9%) were African American, 3 (3%) were Asian, and for 2 (2%), data on race were not available. Forty-eight patients (55%) were never smokers, 45 patients (51%) were of Eastern Cooperative Oncology Group performance status 1, and 59 patients (67%) had EGFR exon 19 deletion. Compared with erlotinib, the combination did not result in a significant difference in PFS (HR, 0.81; 95% CI, 0.50-1.31; P =.39; median PFS 17.9 [combination] and 13.5 months [erlotinib]), ORR (81% vs 83%; P =.81), and OS (HR, 1.41; 95% CI, 0.71-2.81; P =.33; median OS, 32.4 months [combination] and 50.6 months [erlotinib]). Adverse events of grade 3 or higher observed in 5 or more patients in the combination and erlotinib arms were skin eruption in 11 (26%) vs 7 (16%) patients, diarrhea in 4 (9%) vs 6 (13%) patients, hypertension in 17 (40%) vs 9 (20%) patients, and proteinuria in 5 (12%) vs 0 (0%) patients. Conclusions and Relevance: Erlotinib plus bevacizumab compared with erlotinib did not result in a significant improvement in PFS in EGFR-mutant NSCLC.
Keywords: NCT01532089; bevacizumab; epidermal growth factor receptor; erlotinib; abdominal pain; adult; advanced cancer; African American; aged; article; Asian; cancer growth; cancer staging; Caucasian; controlled study; diarrhea; drug effect; dyspnea; EGFR gene; exon; fatigue; female; follow up; gene; gene deletion; gene mutation; groups by age; human; hypertension; major clinical study; male; non small cell lung cancer; overall survival; phase 2 clinical trial; progression free survival; proteinuria; randomized controlled trial; rash; retrospective study; smoking; treatment outcome; treatment response

Bridging the Gap: Racial concordance as a strategy to increase African American participation in breast cancer research - Frierson, G.M.; Pinto, B.M.; Denman, D.C.; Leon, P.A.; Jaffe, A.D. (Journal of health psychology, 2019)
Lack of African American females in breast cancer research has been receiving substantial attention. This study seeks to identify research perceptions and motivating factors needed to increase racial/ethnic minority participation in breast cancer research. A total of 57 African American women (Σ = 47.8 years), from Rhode Island and Texas, completed a questionnaire and focus group. While many participants were not breast cancer survivors, they reported knowledge of their racial group's risk for breast cancer. One major finding that could be seen as both a facilitator and barrier is racial concordance between participant and researcher. Cultural sensitivity and trust building is recommended to increase minority participation.
Keywords: adult; African American; attitude to health; breast tumor; ethnology; female; human; medical research; middle aged; patient participation; patient selection

Variation in Accrual and Race/Ethnicity Reporting in Urological and Nonurological Related Cancer Trials - Paul, K.; Sathianathen, N.; Dahm, P.; Le, C.; Konety, B.R. (Journal of Urology, 2019)
We performed a multiregistry analysis to assess relative differences in accrual sufficiency and race/ethnicity reporting in trials of common urological cancers and other nonurological solid organ tumors.Materials and Methods:We queried ClinicalTrials.gov and the ISRCTN (International Standard Randomised Controlled Trial Number) Registry for closed phase III and IV trials focused on prostate, colorectal, kidney, bladder, testicular, breast and lung cancer. Identified trials were cross-verified with appropriate published data sources. Comparative accrual sufficiency and rates of race/ethnicity reporting were calculated. Multivariable logistic regression analysis was performed to determine factors associated with accrual status and race/ethnicity reporting.Results:A total of 326 trials were identified based on our prespecified criteria, of which 63% reported sufficient accrual by time of closure and 58% reported data by race/ethnicity. Nonurological trials were significantly more likely to mention race data than urological trials (OR 3.25, 95% CI 1.24-8.55, p = 0.02). Industry sponsored trials were more likely to meet accrual targets than government funded projects (OR 5.44, 95% CI 1.64-18.20, p = 0.001). Although funding source did not influence race reporting, the reported recruitment of participants of African ethnicity was lower in industry sponsored trials (11.49% vs 3.18%, p <0.01). Two-thirds of the studies did not report baseline characteristics by African American race/ethnicity.Conclusions:Insufficient accrual and inadequate race/ethnicity reporting are prevalent issues, limiting interpretation of the results of clinical trials of major solid organ malignancies. Addressing these shortcomings would enhance result validity by raising statistical power and improving the transparency of reporting to better evaluate the generalizability of results. reproduction of this article is prohibited.
Keywords: African; African American; article; bladder cancer; breast cancer; clinical trial protocol; colorectal cancer; ethnicity; government; human; kidney cancer; lung cancer; priority journal; prostate cancer; race; secondary analysis; testis cancer; urinary tract cancer; urinary tract disease

Web-based versus in-person methods for training lay community health advisors to implement health promotion workshops: Participant outcomes from a cluster-randomized trial - Holt, C.L.; Tagai, E.K.; Santos, S.L.Z.; Scheirer, M.A.; Bowie, J.; Haider, M.; Slade, J. (Translational Behavioral Medicine, 2019)
Project HEAL (Health through Early Awareness and Learning) is an implementation trial that compared two methods of training lay peer community health advisors (CHAs) - in-person ("Traditional") versus web-based ("Technology") - to conduct a series of three evidence-based cancer educational workshops in African American churches. This analysis reports on participant outcomes from Project HEAL. Fifteen churches were randomized to the two CHA training methods and the intervention impact was examined over 24 months. This study was conducted in Prince George's County, MD, and enrolled 375 church members age 40-75. Participants reported on knowledge and screening behaviors for breast, prostate, and colorectal cancer. Overall, cancer knowledge in all areas increased during the study period (p <. 001). There were significant increases in digital rectal exam (p <. 05), fecal occult blood test (p <. 001), and colonoscopy (p <. 01) at 24 months; however, this did not differ by study group. Mammography maintenance (56% overall) was evidenced by women reporting multiple mammograms within the study period. Participants attending all three workshops were more likely to report a fecal occult blood test or colonoscopy at 24 months (p <. 05) than those who attended only one. These findings suggest that lay individuals can receive web-based training to successfully implement an evidence-based health promotion intervention that results in participant-level outcomes comparable with (a) people trained using the traditional classroom method and (b) previous efficacy trials. Findings have implications for resources and use of technology to increase widespread dissemination of evidence-based health promotion interventions through training lay persons in community settings.
Keywords: adult; African American; aged; article; behavior change; breast cancer; cancer screening; colonoscopy; colorectal cancer; digital rectal examination; e-learning; evidence based practice; female; follow up; health disparity; health education; health promotion; human; knowledge; lay health worker; major clinical study; male; mammography; occult blood test; priority journal; prostate cancer; public health; sigmoidoscopy; telehealth; workshop

Brief report of a tablet-delivered psychosocial intervention for men with advanced prostate cancer: Acceptability and efficacy by race - Bouchard, L.C.; Yanez, B.; Dahn, J.R.; Flury, S.C.; Perry, K.T.; Mohr, D.C.; Penedo, F.J. (Translational Behavioral Medicine, 2019)
Relative to non-Hispanic whites (NHW), black men are disproportionately affected by prostate cancer (PC) incidence, have poorer PC outcomes, and report greater compromises in health-related quality of life. Despite these challenges, black men are underrepresented in psychosocial cancer research, possibly due to limited access to supportive oncology programs. The purpose of this article is to examine the acceptability and efficacy for reducing disease-specific distress of a tablet-delivered psychosocial intervention for older men with advanced PC (APC) and explore differences by race. Men with APC (N = 192, 37.5% black, age M = 68.84 years) were randomized to 10-week Cognitive Behavioral Stress Management (CBSM) or attention-control Health Promotion (HP), both delivered via tablets. Assessments occurred at baseline in person, weekly during the 10-week program via tablets, and at 6 and 12 months in person. Weekly session evaluations and postprogram exit surveys assessed acceptability. Efficacy was assessed with a measure of PC-anxiety validated with racially diverse PC patients using linear mixed effects modeling. Study retention and group attendance did not differ by race. CBSM and HP were both acceptable among older APC patients. Black men rated both conditions more favorably than NHW men. Men in CBSM (vs. HP) reported greater reductions in PC-anxiety at 6 months (not sustained at 12 months). Black men in CBSM reported greater decreases in PC-anxiety over time compared with all other groups. Tablet-delivered CBSM and HP were acceptable for black and NHW APC patients, although black men rated both conditions more favorably. Black men reported a unique intervention benefit related to reduced disease-specific distress.
Keywords: advanced cancer; aged; anxiety; article; Black person; cancer incidence; cancer research; Caucasian; clinical assessment; clinical effectiveness; cognitive behavioral stress management; controlled study; distress syndrome; evaluation study; health promotion; human; major clinical study; male; patient attitude; priority journal; prostate cancer; psychosocial care; quality of life; race; randomized controlled trial

Study protocol for developing #CuttingCRC: A barbershop-based trial on masculinity barriers to care and colorectal cancer screening uptake among African-American men using an exploratory sequential mixed-methods design - Rogers, C.R.; Okuyemi, K.; Paskett, E.D.; Thorpe, R.J.; Rogers, T.N.; Hung, M.; Zickmund, S.; Riley, C.; Fetters, M.D. (BMJ Open, 2019)
Introduction Colorectal cancer (CRC) is preventable, as screening leads to the identification and removal of precancerous polyps. African-American men consistently have the highest CRC mortality rates, and their CRC-screening uptake remains low for complex reasons. Culture-specific masculinity barriers to care may contribute to the low uptake among African-American men. Examining these barriers to care is vital as CRC screening may challenge cultural role expectations of African-American men, whose tendency is to delay help-seeking medical care. Barbershops provide a pathway for reaching African-American men with masculinity barriers to care who are not regularly receiving healthcare services and CRC screening. This study aims to develop and pilot test a theory-driven, culture-specific, barbershop-based intervention targeting masculinity barriers to care and CRC-screening uptake among African-American men ages 45-75. Methods and analysis Guided by the theory of planned behaviour and the behaviour change wheel, we will use a multistage mixed-methods study design, beginning with an exploratory sequential approach to validate items for subsequent use in a pilot mixed-methods intervention. First, we will collect and analyse qualitative data from focus groups, cognitive interviews and expert item review to validate and test a culture-specific Masculinity Barriers to Care Scale (MBCS) among African-American men. Next, we will administer the MBCS to our target population as an online quantitative survey and evaluate the association between scores and CRC-screening uptake. Then, we will consider existing evidence-based approaches, our integrated results (qualitative +quantitative), and community input to design a culture-specific, behavioural intervention aimed at increasing CRC-screening uptake among African-American men and feasible for barbershop delivery. We will test the peer intervention in a pilot study with a two-Arm cluster randomised design (six barbershops, randomised by site) to reduce contamination and account for barbershop culture differences. Our primary outcomes for the pilot are recruitment, sample size estimation, preliminary efficacy and acceptability. Ethics and dissemination Ethics approval was obtained from the University of Utah Institutional Review Board (00113679), who will also be responsible for receiving communication updates regarding important protocol modifications. To ensure confidentiality, data dispersed to project team members will be blinded of any identifying participant information. Study results will be disseminated through publications in peer-reviewed journals, community dialogue sessions, and presentations at conferences. Trial registration number ClinicalTrials.gov identifier: NCT03733197 (Pre-results);https://clinicaltrials.gov/ct2/show/NCT03733197
Keywords: NCT03733197; adult; African American; aged; article; behavior change; behavioral risk factor surveillance system; cancer screening; cancer survival; colorectal cancer; human; male; masculinity; masculinity barriers to care scale; patient care; pilot study; qualitative analysis; quantitative analysis; scoring system; Theory of Planned Behavior

Promover una alianza entre la atención primaria y las organizaciones comunitarias para aumentar las pruebas de detección de cáncer colorrectal: el proyecto HAPPI - Bravo, R.L.; Kietzman, K.G.; Toy, P.; Duru, O.K.; Wallace, S.P. (Salud publica de Mexico, 2019)
Keywords: African American; aged; California; capacity building; colorectal tumor; community care; community participation; financial management; healthy aging; Hispanic; human; in service training; middle aged; organization and management; patient care; preventive health service; primary health care; public relations

Increasing the Representation of Minority Students in the Biomedical Workforce: the ReTOOL Program - Odedina, F.T.; Reams, R.R.; Kaninjing, E.; Nguyen, J.; Mochona, B.; Lyon, D.E.; Askins, N.; Behar-Horenstein, L.S. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2019)
With the growing burden of cancer in minority populations and limited progress in eliminating cancer disparities, it has become important to develop a diverse oncology workforce in basic, clinical, and behavioral research who will address cancer disparities and increase the participation of minority populations in clinical trials. To address the lack of well-trained underrepresented minority cancer scientists in Florida, the University of Florida collaborated with Florida A&M University in 2012 to establish the Florida Prostate Cancer Research Training Opportunities for Outstanding Leaders (ReTOOL) Program. Since 2012, the ReTOOL program has expanded to (1) cover all areas of cancer disparities; (2) offer training opportunities to minority students from all historically Black colleges and universities (HBCUs) in Florida; and (3) successfully secure both intramural and extramural federal funding to continuously provide research training opportunities for minority students in Florida. Focusing primarily on training Black students, the ReTOOL model includes culturally sensitive recruitment, mentorship, didactic curriculum, networking, and hands on experience in cancer research. This paper discusses the lessons learned from administering the ReTOOL program for 5 years, which includes having the right inputs (such as majority-minority institutions partnership, funding, faculty advisors, committed mentors, culturally competent staff, and standardized program requirements) and processes (such as pipeline approach, structured applications system, didactic curriculum, research experience, and continuous mentoring) for an effective research training program. The program impact is an increase in the pool of underrepresented minority candidates with scientific and academic career progression paths focused on reducing cancer health disparities.
Keywords: curriculum; decision making; education; female; Florida; human; male; medical research; mentoring; minority group; oncology; personnel; program evaluation; student

Reliability and between-group stability of a health-related quality of life symptom index for persons with anal high-grade squamous intraepithelial lesions: an AIDS Malignancy Consortium Study (AMC-A03) - Atkinson, T.M.; Palefsky, J.; Li, Y.; Webb, A.; Berry, J.M.; Goldstone, S.; Levine, R.; Wilkin, T.J.; Bucher, G.; Cella, D.; Burkhalter, J.E.; Holland, S.M.; et al. (Quality of Life Research, 2019)
Purpose: The Anal Cancer HSIL Outcomes Research (ANCHOR) trial aims to determine whether treating precancerous anal high-grade squamous intraepithelial lesions (HSIL), versus active surveillance, is effective in reducing anal cancer incidence in HIV-infected individuals. We evaluated the reliability (i.e., internal consistency, test–retest) and between-group stability of a 25-item ANCHOR Health-Related Symptom Index (A-HRSI). Methods: ANCHOR participants at least 1-month post-randomization to treatment or active surveillance completed the A-HRSI via telephone. Participants were contacted 7–10 days later to complete the A-HRSI and a participant global impression of change (PGIC) item. Results: Participants (n = 100) were enrolled (mean age = 51.4, 79% cisgender-male, 73% African American, 9% Hispanic) from five ANCHOR sites. Cronbach’s α was good for the physical symptoms (0.82) domain and fair for the physical impacts (0.79) and psychological symptoms (0.73) domains. Intraclass correlation coefficients were good for each of respective domains (i.e., 0.80, 0.85, and 0.82). There were no significant differences in PGIC between the treatment (n = 56) and active surveillance (n = 44) groups (F(1,98) = 2.03, p = 0.16). Conclusions: The A-HRSI is able to reliably assess participant-reported symptoms and impacts of anal HSIL across a 7–10 days of timeframe. Future work will involve the establishment of construct and discriminant validity prior to inclusion in the full ANCHOR trial.
Keywords: adult; African American; aged; anal high grade squamous intraepithelial lesion; anus carcinoma; article; burning sensation; cancer diagnosis; constipation; correlation coefficient; depression; disease surveillance; female; human; Human immunodeficiency virus infected patient; incidence; intestinal bleeding; major clinical study; male; outcomes research; patient-reported outcome; priority journal; quality of life; sexual behavior; test retest reliability

Enrollment and biospecimen collection in a multiethnic family cohort: the Northern California site of the Breast Cancer Family Registry - John, E.M.; Sangaramoorthy, M.; Koo, J.; Whittemore, A.S.; West, D.W. (Cancer Causes and Control, 2019)
Purpose: Racial/ethnic minorities are often assumed to be less willing to participate in and provide biospecimens for biomedical research. We examined racial/ethnic differences in enrollment of women with breast cancer (probands) and their first-degree relatives in the Northern California site of the Breast Cancer Family Registry from 1996 to 2011. Methods: We evaluated participation in several study components, including biospecimen collection, for probands and relatives by race/ethnicity, cancer history, and other factors. Results: Of 4,780 eligible probands, 76% enrolled in the family registry by completing the family history and risk factor questionnaires and 68% also provided a blood or mouthwash sample. Enrollment was highest (81%) for non-Hispanic whites (NHWs) and intermediate (73–76%) for Hispanics, African Americans, and all Asian American subgroups, except Filipina women (66%). Of 4,279 eligible relatives, 77% enrolled in the family registry, and 65% also provided a biospecimen sample. Enrollment was highest for NHWs (87%) and lowest for Chinese (68%) and Filipinas (67%). Among those enrolled, biospecimen collection rates were similar for NHW, Hispanic, and African American women, both for probands (92–95%) and relatives (82–87%), but lower for some Asian–American subgroups (probands: 72–88%; relatives: 71–88%), foreign-born Asian Americans, and probands those who were more recent immigrants or had low English language proficiency. Conclusions: These results show that racial/ethnic minority populations are willing to provide biospecimen samples for research, although some Asian American subgroups in particular may need more directed recruitment methods. To address long-standing and well-documented cancer health disparities, minority populations need equal opportunities to contribute to biomedical research.
Keywords: adult; African American; article; Asian American; biobank; birthplace; blood sampling; breast cancer; California; cancer registry; cancer risk; Caucasian; Chinese; cohort analysis; controlled study; English (language); ethnic difference; family history; family study; female; Filipino (people); first-degree relative; Hispanic; human; human tissue; immigrant; language ability; major clinical study; oncological parameters; priority journal; questionnaire; race difference; risk factor; risk factor questionnaire

Breast ultrasound utilization in a safety net emergency department - Porembka, J.H.; Compton, L.; Omar, L.; Sharma, P.; Clark, H.; Ahn, R.; Ganti, R.; Xi, Y.; Metzger, J.; Leyendecker, J.R. (Emergency Radiology, 2019)
Purpose: The purpose of this study is to (1) assess the diagnostic yield of ultrasounds performed in the emergency department for suspected breast abscess and determine the rates of reimaging, discordance, and emergent intervention in a large, busy safety net hospital and (2) determine clinical factors significantly associated with abscess as a way to improve patient selection for emergent breast ultrasounds. Methods: A total of 581 consecutive breast ultrasounds performed in the emergency department for suspected abscess over 15 months were retrospectively reviewed for imaging, demographics, laboratory data, and physical exam findings. Breast abscess was confirmed by combining imaging, clinical, and laboratory data. Linear logistic regression analysis estimated the likelihood of abscess, and the cross-validated area under the receiver operating characteristic curve (AUC) evaluated diagnostic performance. Results: Final diagnoses included abscess (153/581, 26%), cancer (29/581, 5%), granulomatous mastitis (41/581, 7%), normal (120/581, 21%), and other/indeterminate (238/581, 41%). Factors associated with abscess included induration, fluctuance, erythema, drainage, smoking, diabetes, and Black race. Based on these factors, the AUC of the characteristics predictive of abscess was 0.77 (CI, 0.72–0.81). Six breast cancers were not diagnosed on ultrasound. 40% of ultrasounds (231/581) were considered incomplete/inadequate. Conclusion: 74% (428/581) of emergent breast ultrasounds in our population were negative for abscess, while 21% (6/29) of cancers were not diagnosed, and 40% (231/581) of exams were incomplete/inadequate. Patient selection for emergent ultrasounds can be improved, allowing patients with a low likelihood of abscess to be imaged in a more optimal setting.
Keywords: EPIQ7; iU22; real time ultrasound scanner; ultrasound transducer; antibiotic agent; abscess drainage; adult; American Indian; antibiotic therapy; article; Asian; Black person; breast abscess; breast biopsy; breast carcinoma; breast cyst; Caucasian; diabetes mellitus; diagnostic value; echomammography; emergency ward; erythema; female; follow up; granulomatous mastitis; hematoma; Hispanic; human; laboratory test; major clinical study; medical record review; Pacific Islander; patient safety; patient selection; physical examination; predictive value; priority journal; race difference; receiver operating characteristic; retrospective study; safety net hospital; smoking; EPIQ7; iU22

The Detroit research on cancer survivors (ROCS) pilot study: A focus on outcomes after cancer in a racially diverse patient population - Beebe-Dimmer, J.L.; Albrecht, T.L.; Baird, T.E.; Ruterbusch, J.J.; Hastert, T.; Harper, F.W.K.; Simon, M.S.; Abrams, J.; Schwartz, K.L.; Schwartz, A.G. (Cancer Epidemiology Biomarkers and Prevention, 2019)
Background: African Americans are often diagnosed with advanced stage cancer and experience higher mortality compared with whites in the United States. Contributing factors, like differences in access to medical care and the prevalence of comorbidities, do not entirely explain racial differences in outcomes. Methods: The Detroit Research on Cancer Survivors (ROCS) pilot study was conducted to investigate factors related to short- and long-term outcomes among patients with cancer. Participants completed web-based surveys, and mailed saliva specimens were collected for future genetic studies. Results: We recruited 1,000 participants with an overall response rate of 68%. Thirty-one percent completed the survey without any interviewer support and the remaining participated in an interviewer-administered survey. Seventy-four percent provided a saliva specimen and 64% consented for tumor tissue retrieval. African American survivors required more interviewer support (P < 0.001); however, their response rate (69.6%) was higher than non-Hispanic whites (65.4%). African Americans reported poorer overall cancer-related quality of life compared with non-Hispanic whites, measured by FACT-G score (P < 0.001), however, this relationship was reversed after controlling for socioeconomic factors, marital status, and the presence of comorbidities. Conclusions: In this pilot study, we demonstrated that a web-based survey supplemented with telephone interviews and mailed saliva kits are cost-effective methods to collect patient-reported data and DNA for large studies of cancer survivors with a high proportion of minority patients. The preliminary data collected reinforces differences by race in factors affecting cancer outcomes. Our efforts continue as we expand this unique cohort to include more than 5,000 African American cancer survivors. Impact: Formal investigation of factors influencing adverse outcomes among African American cancer survivors will be critical in closing the racial gap in morbidity and mortality.
Keywords: adult; African American; aged; ancestry group; arthritis; article; body mass; breast cancer; cancer diagnosis; cancer localization; cancer patient; cancer registry; cancer screening; cancer staging; cancer survivor; cancer therapy; cerebrovascular accident; chronic obstructive lung disease; clinical outcome; clinical protocol; cohort analysis; colorectal cancer; comorbidity; congestive heart failure; cost effectiveness analysis; depression; diabetes mellitus; disease severity; family history; female; Functional Assessment of Cancer Therapy; Functional Assessment of Cancer Therapy General; health behavior; human; human cell; human tissue; hypercholesterolemia; hypertension; long term care; lung cancer; major clinical study; male; marriage; medical history; obesity; osteoporosis; patient-reported outcome; physical activity; pilot study; priority journal; prostate cancer; quality of life; race difference; refusal to participate; risk factor; saliva; socioeconomics; thyroid disease; underweight

Prevalence of Hepatitis B Virus, Hepatitis C Virus, and HIV Infection among Patients with Newly Diagnosed Cancer from Academic and Community Oncology Practices - Ramsey, S.D.; Unger, J.M.; Baker, L.H.; Little, R.F.; Loomba, R.; Hwang, J.P.; Chugh, R.; Konerman, M.A.; Arnold, K.; Menter, A.R.; Thomas, E.; Michels, R.M.; et al. (JAMA Oncology, 2019)
Importance: Universal screening of patients with newly diagnosed cancer for hepatitis B virus (HBV), hepatitis C virus (HCV), and HIV is not routine in oncology practice, and experts disagree about whether universal screening should be performed. Objective: To estimate the prevalence of HBV, HCV, and HIV infection among persons with newly diagnosed cancer. Design, Setting, and Participants: Multicenter prospective cohort study of patients with newly diagnosed cancer (ie, identified within 120 days of cancer diagnosis) at 9 academic and 9 community oncology institutions affiliated with SWOG (formerly the Southwest Oncology Group) Cancer Research Network, a member of the National Clinical Trials Network, with enrollment from August 29, 2013, through February 15, 2017. The data analysis was conducted using data available through August 17, 2017. Main Outcomes and Measures: The accrual goal was 3000 patients and the primary end point was the presence of HBV infection (previous or chronic), HCV infection, or HIV infection at enrollment. Patients with previous knowledge of infection as well as patients with unknown viral viral status were evaluated. Results: Of 3092 registered patients, 3051 were eligible and evaluable. Median (range) age was 60.6 (18.2-93.7) years, 1842 (60.4%) were female, 553 (18.1%) were black, and 558 (18.3%) were Hispanic ethnicity. Screened patients had similar clinical and demographic characteristics compared with those registered. The observed infection rate for previous HBV infection was 6.5% (95% CI, 5.6%-7.4%; n = 197 of 3050 patients); chronic HBV, 0.6% (95% CI, 0.4%-1.0%; n = 19 of 3050 patients); HCV, 2.4% (95% CI, 1.9%-3.0%; n = 71 of 2990 patients); and HIV, 1.1% (95% CI, 0.8%-1.6%; n = 34 of 3045). Among those with viral infections, 8 patients with chronic HBV (42.1%; 95% CI, 20.3%-66.5%), 22 patients with HCV (31.0%; 95% CI, 20.5%-43.1%), and 2 patients with HIV (5.9%; 95% CI, 0.7%-19.7%) were newly diagnosed through the study. Among patients with infections, 4 patients with chronic HBV (21.1%; 95% CI, 6.1%-45.6%), 23 patients with HCV (32.4%; 95% CI, 21.8%-44.5%), and 7 patients with HIV (20.6%; 95% CI, 8.7%-37.9%) had no identifiable risk factors. Conclusions and Relevance: Results of this study found that a substantial proportion of patients with newly diagnosed cancer and concurrent HBV or HCV are unaware of their viral infection at the time of cancer diagnosis, and many had no identifiable risk factors for infection. Screening patients with cancer to identify HBV and HCV infection before starting treatment may be warranted to prevent viral reactivation and adverse clinical outcomes. The low rate of undiagnosed HIV infection may not support universal screening of newly diagnosed cancer patients.
Keywords: hepatitis B vaccine; adult; age; aged; article; Black person; blood analysis; blood transfusion; breast cancer; cancer center; cohort analysis; colorectal cancer; contact examination; demography; digestive system cancer; female; gender; head and neck cancer; hematologic malignancy; hepatitis B; Hepatitis B virus; hepatitis C; Hepatitis C virus; Hispanic; human; Human immunodeficiency virus; Human immunodeficiency virus infection; intravenous drug abuse; liver cancer; lung cancer; major clinical study; male; malignant neoplasm; medical history; middle aged; needlestick injury; occupational exposure; prevalence; prospective study; prostate cancer; risk factor; sexual behavior; teaching hospital; unprotected sex; very elderly; virus load; young adult

Adherence to American Cancer Society and American Institute of Cancer Research dietary guidelines in overweight African American breast cancer survivors - Springfield, S.; Odoms-Young, A.; Tussing-Humphreys, L.; Freels, S.; Stolley, M. (Journal of cancer survivorship : research and practice, 2019)
PURPOSE: The American Cancer Society (ACS) and the American Institute for Cancer Research (AICR) each created dietary and physical activity guidelines to improve cancer survivorship. Despite African American breast cancer survivors (AABCS) having the lowest survival rates of any racial or ethnic group, limited information exists on their adherence to cancer-specific lifestyle recommendations. The study's purpose was to measure adherence to ACS/AICR dietary recommendations in AABCS. METHODS: Two hundred ten AABCS enrolled in the Moving Forward intervention trial, a randomized, community-based, 6-month weight loss study, were assessed for socio-demographics, dietary intake (via food frequency questionnaire), and related health factors at baseline. We operationalized the dietary recommendations put forth by ACS/AICR and created component and total adherence index scores. Descriptive statistics were used to calculate the proportion of women who met recommendations. Student's t test and χ2 tests were used to compare participant characteristics by median adherence scores. RESULTS: The mean total ACS/AICR score was 12.7 ± 2.5 out of 21 points (median, 13; range, 5 to 21). Over 90% were moderately or completely adherent to limiting alcohol and red & processed meat consumption, but the majority failed to meet the other recommendations to eat whole grains, legumes, fruits, vegetables, and avoid added sugars. Women with total scores below the median were younger, with higher BMI, had fewer years of education, and lower income levels. IMPLICATIONS FOR CANCER SURVIVORS: The present study extends the literature on AABCS adherence to cancer survivor-specific dietary guidelines. Findings will inform future dietary lifestyle interventions in this population.
Keywords: adult; African American; article; body mass; body weight loss; breast cancer; cancer survival; cancer survivor; chi square test; controlled study; dietary compliance; dietary intake; education; female; food frequency questionnaire; fruit; human; intervention study; legume; lifestyle; non profit organization; obesity; processed meat; randomized controlled trial; statistics; student; whole grain; alcohol; carbohydrate

Nonalcoholic Steatohepatitis Is the Fastest Growing Cause of Hepatocellular Carcinoma in Liver Transplant Candidates - Younossi, Z.; Stepanova, M.; Ong, J.P.; Jacobson, I.M.; Bugianesi, E.; Duseja, A.; Eguchi, Y.; Wong, V.W.; Negro, F.; Yilmaz, Y.; Romero-Gomez, M.; George, J.; et al. (Clinical Gastroenterology and Hepatology, 2019)
Background & Aims: Although hepatitis B and C have been the main drivers of hepatocellular carcinoma (HCC), nonalcoholic steatohepatitis (NASH) has recently become an important cause of HCC. The aim of this study was to assess the causes of HCC among liver transplant (LT) candidates in the United States. Methods: The Scientific Registry of Transplant Recipients (2002–2016) was used to estimate the trends in prevalence of HCC in LT candidates with the most common types of chronic liver disease: alcoholic liver disease (ALD), chronic hepatitis B (CHB), chronic hepatitis C, and NASH. Results: 158,347 adult LT candidates were included. Of these, 26,121 (16.5%) had HCC; this proportion increased from 6.4% (2002) to 23.0% (2016) (trend P <.0001). Over the study period, CHC remained the most common etiology for HCC (65%). The proportions of HCC accounted for by CHC and ALD remained stable (both trend P >.10), the proportion of CHB decreased 3.1-fold (P <.0001), while the proportion of NASH in HCC increased 7.7-fold (from 2.1% to 16.2%; P <.0001). Furthermore, since 2002, the prevalence of HCC in LT candidates with NASH increased 11.8-fold, while this rate increased 6.0-fold in CHB, 3.4-fold in ALD, and 2.3-fold in CHC (all P <.0001); the increasing trend in NASH was steeper than that for any other etiology (P <.0001 in a trend regression model). The proportion of LT candidates with HCC who ultimately received a transplant or died while waiting did not differ between etiologies (P >.05). Conclusions: Nonalcoholic steatohepatitis is the most rapidly growing cause of HCC among US patients listed for liver transplantation.
Keywords: adult; age distribution; alcohol liver disease; article; ascites; bacterial peritonitis; Black person; bleeding; cancer mortality; cancer prognosis; cancer recurrence; cancer staging; cancer surgery; cardiovascular disease; cause of death; cerebrovascular accident; chronic hepatitis B; chronic hepatitis C; chronic obstructive lung disease; comorbidity; coronary artery disease; deterioration; female; follow up; graft failure; graft recipient; hepatic encephalopathy; hospital admission; hospital discharge; human; hypertension; infection; kidney failure; liver cell carcinoma; liver cirrhosis; liver graft; liver transplantation; longitudinal study; major clinical study; male; malignant neoplasm; Model For End Stage Liver Disease Score; mortality risk; multiple organ failure; non insulin dependent diabetes mellitus; nonalcoholic fatty liver; obesity; patient dropout; postoperative complication; prevalence; respiratory failure; risk assessment; risk factor; sex ratio; surgical mortality; surgical risk; trend study; United States; variceal bleeding

Aspirin and non-aspirin NSAID use and prostate cancer incidence, mortality, and case fatality in the Atherosclerosis Risk in Communities study - Hurwitz, L.M.; Joshu, C.E.; Barber, J.R.; Prizment, A.E.; Vitolins, M.Z.; Jones, M.R.; Folsom, A.R.; Han, M.; Platz, E.A. (Cancer Epidemiology Biomarkers and Prevention, 2019)
Background: NSAIDs appear to moderately reduce prostate cancer risk. However, evidence is limited on whether NSAIDs protect against prostate cancer mortality (death from prostate cancer among men without a cancer history) and case fatality (death from prostate cancer among men with prostate cancer), and whether benefits are consistent in white and black men. This study investigated associations of aspirin and non-aspirin (NA) NSAID use with prostate cancer incidence, mortality, and case fatality in a population-based cohort of white and black men. Methods: We included 6,594 men (5,060 white and 1,534 black) from the Atherosclerosis Risk in Communities study without a cancer history at enrollment from 1987 to 1989. NSAID use was assessed at four study visits (1987–1998). Cancer outcomes were ascertained through 2012. Cox proportional hazards regression was used to estimate adjusted HRs, overall and by race. Results: Aspirin use was not associated with prostate cancer incidence. However, aspirin use was inversely associated with prostate cancer mortality [HR, 0.59; 95% confidence interval (CI), 0.36–0.96]. This association was consistent among white and black men and appeared restricted to men using aspirin daily and/or for cardiovascular disease prevention. Aspirin use was inversely associated with case fatality (HR, 0.45; 95% CI, 0.22–0.94). NA-NSAID use was not associated with these endpoints. Conclusions: Aspirin use was inversely associated with prostate cancer mortality and case fatality among white and black men. Impact: If confirmed by additional studies, benefits of aspirin for preventing prostate cancer mortality may need to be factored into risk–benefit calculations of men considering an aspirin regimen.
Keywords: acetylsalicylic acid; hydroxymethylglutaryl coenzyme A reductase inhibitor; nonsteroid antiinflammatory agent; adult; article; atherosclerosis; cancer incidence; cancer mortality; cancer research; cardiovascular disease; case fatality rate; clinical outcome; cohort analysis; disease association; human; major clinical study; male; priority journal; proportional hazards model; prospective study; prostate cancer; race

"Hard to reach, but not out of reach": Barriers and facilitators to recruiting Black African and Black Caribbean men with prostate cancer and their partners into qualitative research - Bamidele, O.O.; E McGarvey, H.; Lagan, B.M.; Chinegwundoh, F.; Ali, N.; McCaughan, E. (European journal of cancer care, 2019)
Access and recruitment barriers may have contributed to the underrepresentation of Black African/Caribbean men and their partners in current psychosocial research related to prostate cancer survivors. Whilst some studies have explored recruitment barriers and facilitators from participants' perspectives, little is known from researchers' point of view. This paper aimed to address this gap in the literature. Recruitment strategies included the following: cancer support groups, researchers' networks, media advertisement, religious organisations, National Health Service hospitals and snowball sampling. Thirty-six eligible participants (men = 25, partners = 11) were recruited into the study. Recruitment barriers comprised of gate-keeping and advertisement issues and the stigma associated with prostate cancer disclosure. Facilitators which aided recruitment included collaborating with National Health Service hospitals, snowball sampling, flexible data collection, building rapport with participants to gain their trust and researcher's attributes. Findings highlight that "hard to reach" Black African/Caribbean populations may be more accessible if researchers adopt flexible but strategic and culturally sensitive recruitment approaches. Such approaches should consider perceptions of stigma associated with prostate cancer within these communities and the influence gatekeepers can have in controlling access to potential participants. Increased engagement with healthcare professionals and gatekeepers could facilitate better access to Black African/Caribbean populations so that their voices can be heard and their specific needs addressed within the healthcare agenda.
Keywords: adolescent; adult; advertising; African American; aged; Black person; Caribbean Islands; ethnology; female; health care delivery; human; interpersonal communication; male; middle aged; patient attitude; patient referral; patient selection; prostate tumor; psychology; public relations; qualitative research; sexuality; stereotyping; young adult

Survivorship care visits in a high-risk population of breast cancer survivors - Skuli, S.J.; Sheng, J.Y.; Bantug, E.T.; Zafman, N.; Riley, C.; Ruck, J.M.; Smith, K.C.; Snyder, C.F.; Smith, K.L.; Stearns, V.; Wolff, A.C. (Breast Cancer Research and Treatment, 2019)
Purpose: Breast cancer survivors face numerous challenges after diagnosis and treatment. Several models have been developed to attempt to improve quality of care. Here, we describe characteristics and outcomes of patients who participated in survivorship visits (SV) at Johns Hopkins (JH). Methods: We retrospectively reviewed charts of breast cancer patients who participated in an optional SV 1–3 months after completing locoregional therapy and initial systemic therapy. We report patient demographics, comorbidities, tumor characteristics, treatments, and responses to symptom questionnaires. We compared the characteristics of SV participants to stage I–III analytical cases in the 2010–2015 JH Cancer Registry (JHCR). Results: We identified 87 women with stage I–III breast cancer who participated in SVs from 2010 to 2016. Compared to patients in the JHCR (n = 2942), SV participants were younger, more likely to be African American and more likely to have a higher TNM stage, hormone receptor-negative disease, and HER2-positive disease. They were more likely to have received chemotherapy and radiation therapy. They also have similar recurrence rates despite the SV cohort’s shorter median follow-up time. Among SV participants, the prevalence of comorbidities including peripheral neuropathy, anemia, lymphedema, anxiety, deep vein thrombosis, and depression increased significantly from time of diagnosis to most recent follow-up. Conclusions: Compared to the JHCR cohort, SV participants had higher risk cancers and a high frequency of comorbidities potentially associated with breast cancer and therapy. These high-risk patients may benefit most from specific interventions targeting survivorship care, and their experiences may help improve care delivery models.
Keywords: antineoplastic agent; adult; African American; aged; anemia; article; breast cancer; cancer chemotherapy; cancer radiotherapy; cancer recurrence; cancer registry; cancer staging; cancer survivor; comorbidity; deep vein thrombosis; demography; depression; female; follow up; high risk population; human; human epidermal growth factor receptor 2 positive breast cancer; lymphedema; major clinical study; medical record review; middle aged; patient participation; peripheral neuropathy; prevalence; priority journal; questionnaire; retrospective study; survivorship; systemic therapy

Overall survival of black and white men with metastatic castration-resistant prostate cancer treated with docetaxel - Halabi, S.; Dutta, S.; Tangen, C.M.; Rosenthal, M.; Petrylak, D.P.; Thompson, I.M.; Chi, K.N.; Araujo, J.C.; Logothetis, C.; Quinn, D.I.; Fizazi, K.; Morris, M.J.; et al. (Journal of Clinical Oncology, 2019)
PURPOSE Several studies have reported that among patients with localized prostate cancer, black men have a shorter overall survival (OS) time than white men, but few data exist for men with advanced prostate cancer. The primary goal of this analysis was to compare the OS in black and white men with metastatic castration-resistant prostate cancer (mCRPC) who were treated in phase III clinical trials with docetaxel plus prednisone (DP) or a DP-containing regimen. METHODS Individual participant data from 8,820 men with mCRPC randomly assigned in nine phase III trials to DP or a DP-containing regimen were combined. Race was based on self-report. The primary end point was OS. The Cox proportional hazards regression model was used to assess the prognostic importance of race (black v white) adjusted for established risk factors common across the trials (age, prostate-specific antigen, performance status, alkaline phosphatase, hemoglobin, and sites of metastases). RESULTS Of 8,820 men, 7,528 (85%) were white, 500 (6%) were black, 424 (5%) were Asian, and 368 (4%) were of unknown race. Black men were younger and had worse performance status, higher testosterone and prostate-specific antigen, and lower hemoglobin than white men. Despite these differences, the median OS was 21.0 months (95% CI, 19.4 to 22.5 months) versus 21.2 months (95% CI, 20.8 to 21.7 months) in black and white men, respectively. The pooled multivariable hazard ratio of 0.81 (95% CI, 0.72 to 0.91) demonstrates that overall, black men have a statistically significant decreased risk of death compared with white men (P, .001). CONCLUSION When adjusted for known prognostic factors, we observed a statistically significant increased OS in black versus white men with mCRPC who were enrolled in these clinical trials. The mechanism for these differences is not known.
Keywords: NCT00004001; alkaline phosphatase; docetaxel; hemoglobin; prednisone; prostate specific antigen; testosterone; article; Asian; Black person; cancer combination chemotherapy; cancer prognosis; castration resistant prostate cancer; Caucasian; clinical outcome; controlled study; follow up; hemoglobin blood level; human; major clinical study; male; metastatic castration resistant prostate cancer; overall survival; phase 3 clinical trial; priority journal; risk factor

Evaluation of a Computer-Based Decision Aid for Promoting Informed Prostate Cancer Screening Decisions Among African American Men: iDecide - Owens, O.L.; Felder, T.; Tavakoli, A.S.; Revels, A.A.; Friedman, D.B.; Hughes-Halbert, C.; Hébert, J.R. (American journal of health promotion : AJHP, 2019)
PURPOSE: To evaluate the effects of iDecide on prostate cancer knowledge, informed decision-making self-efficacy, technology use self-efficacy, and intention to engage in informed decision-making among African American men. DESIGN: One-group, pretest/posttest. SETTING: Community settings in South Carolina. PARTICIPANTS: African American men, ages 40 years +, without a prior prostate cancer diagnosis (n = 354). INTERVENTION: iDecide, an embodied conversational agent-led, computer-based prostate cancer screening decision aid. MEASURES: Prostate cancer knowledge, informed decision-making self-efficacy, technology use self-efficacy, and intention to engage in informed decision-making. ANALYSIS: Descriptive statistics, paired t tests, general linear modeling, Spearman correlations. RESULTS: On average, participants experienced significant improvements in their prostate cancer knowledge ( P ≤ .001), informed decision-making self-efficacy ( P ≤ .001), and technology use self-efficacy ( P ≤ .001), postintervention. Additionally, 67% of participants reported an intention to engage in informed decision-making. CONCLUSION: Given the significant improvements across all measures, this research demonstrates that embodied conversational agent-led decision aids can be used to enhance the capacity for making informed prostate cancer screening decisions among African American men and increase their technology use self-efficacy. One critical limitation of this study is that most men had received prostate cancer screening prior to engaging in our intervention, so the implications of this intervention may be different for men who do not have a history of screening. Additionally, actual engagement in informed decision-making postintervention was not assessed.
Keywords: prostate specific antigen; adult; African American; age; aged; attitude to computers; attitude to health; decision support system; early cancer diagnosis; ethnology; health promotion; human; male; middle aged; patient participation; procedures; prostate tumor; self concept; socioeconomics; South Carolina

Minority Recruitment Trends in Phase III Prostate Cancer Clinical Trials (2003 to 2014): Progress and Critical Areas for Improvement - Balakrishnan, A.S.; Palmer, N.R.; Fergus, K.B.; Gaither, T.W.; Baradaran, N.; Ndoye, M.; Breyer, B.N. (Journal of Urology, 2019)
Purpose:American minority groups have been historically underrepresented in phase III prostate cancer clinical trials despite often having higher risk disease. We analyzed enrollment trends of major racial/ethnic groups in the United States in phase III prostate cancer trials between 2003 and 2014 compared to SEER (Surveillance, Epidemiology and End Results) incidence data.Materials and Methods:Phase III prostate cancer trials primarily enrolling patients from the United States were identified in the ClinicalTrials.gov database. Enrollment trends were analyzed for major racial/ethnic groups. Prostate cancer incidence data from the SEER registry were used to identify enrollment targets. The enrollment difference was determined by calculating the absolute difference between the percent of a racial/ethnic subgroup in the SEER registry population and the percent of that subgroup in the phase III prostate cancer trial population.Results:Among 39 studies identified African American enrollment in therapeutic trials increased across the study period (p <0.001). The enrollment difference for African Americans was-9.0% (95% CI-7.6-10.5, p <0.001) in 2003 to 2005 and 1.4% (95% CI 0.2-2.6, p = 0.020) in 2012 to 2014. However, African American men were under enrolled in metastatic disease trials (enrollment difference-5.8%, 95% CI-4.8-6.8, p <0.001). Latino and Asian American men were consistently under enrolled in all trial types.Conclusions:Minority groups in the United States were largely under enrolled in phase III prostate cancer trials between 2003 and 2014. While recruitment efforts may have had an impact, as demonstrated by increased enrollment of African American men, there remains a need to expand recruitment efforts to achieve diversity in trials.
Keywords: African American; article; Asian American; Caucasian; ethnicity; Hispanic; human; major clinical study; male; metastasis; minority group; phase 3 clinical trial (topic); priority journal; prostate cancer; race difference

Mobile Mammography Screening as an Opportunity to Increase Access of Rural Women to Breast Cancer Research Studies - McElfish, P.A.; Su, L.J.; Lee, J.Y.; Runnells, G.; Henry-Tillman, R.; Kadlubar, S.A. (Breast Cancer: Basic and Clinical Research, 2019)
Objectives: Rural women are underrepresented in cancer research. We hypothesized that providing access to a research study to rural, medically underserved women who were receiving their breast cancer screening using a mobile mammography unit would increase the representation of rural women in a cancer cohort study. Design: This study is a cross-sectional study using a cohort of women who have been recruited to a breast cancer study in Arkansas. Setting: Recruiters accompanied a mobile mammography unit, the MammoVan, to implement a novel method for reaching and recruiting underrepresented rural Arkansas women into the study. Participants include 5850 women recruited from 2010 through 2012 as part of the Arkansas Rural Community Health (ARCH) study. Results: Participants recruited during their mammography screening on the MammoVan tended to be more rural, less educated, and more likely to be non-Hispanic than those recruited in other venues. A significant difference was not noted for race or age. Conclusion: Collaboration with the MammoVan greatly aided the recruitment of rural participants. These strategies can facilitate the representation of this historically underserved and understudied rural population in future research studies.
Keywords: MammoVan; mobile mammography unit; adult; African American; Arkansas; article; breast cancer; cancer research; cancer screening; Caucasian; clinical effectiveness; cohort analysis; education; female; health care access; Hispanic; human; major clinical study; mammography; medically underserved; rural area; MammoVan

Enrollment of racial minorities in clinical trials: Old problem assumes new urgency in the age of immunotherapy - Nazha, B.; Mishra, M.; Pentz, R.; Owonikoko, T.K. (American Society of Clinical Oncology Educational Book, 2019)
Minority U.S. populations are underrepresented in cancer clinical trials. This review appraises the impact of the disparity in clinical trial participation by minority patients in the current era of cancer immunotherapy. Enrollment on pivotal trials leading to U.S. regulatory approval of immune checkpoint inhibitors showed poor representation of minority ethnic groups. Specifically, we found that black patients constitute less than 4% of all patients enrolled across multiple trials that supported the approval of immune checkpoint inhibitors for the treatment of lung cancer. Similar underrepresentation was observed for trials conducted in renal cell carcinoma and other tumor types. Since efficacy of immunotherapy is only observed in a subset of patients, the use of predictive biomarkers to identify responders along with new strategies to expand the benefit to a larger subset of patients are current areas of active investigation. The inadequate representation of minority patients on immunotherapy clinical trials could perpetuate outcome disparity because the unique biology of the host and the tumors from this subpopulation is not accounted for as new treatment algorithms to guide optimal use of immunotherapy are developed for use in the real world.
Keywords: article; cancer immunotherapy; clinical trial (topic); human; malignant neoplasm; minority group; priority journal; race difference

Treatment of childhood nasopharyngeal carcinoma with induction chemotherapy and concurrent chemoradiotherapy: Results of the Children's Oncology Group ARAR0331 study - Rodriguez-Galindo, C.; Krailo, M.D.; Krasin, M.J.; Huang, L.; Beth McCarville, M.; Hicks, J.; Pashankar, F.; Pappo, A.S. (Journal of Clinical Oncology, 2019)
PURPOSE The treatment of childhood nasopharyngeal carcinoma has been adapted from adult regimens; pediatric-specific studies are limited. The ARAR0331 study sought to evaluate the impact of induction chemotherapy (IC) and concurrent chemoradiotherapy (CCR). PATIENTS AND METHODS Patients with American Joint Committee on Cancer stages IIb to IV were scheduled to receive three cycles of IC with cisplatin and fluorouracil, followed by CCR with three cycles of cisplatin. Patients with complete or partial response to IC received 61.2 Gy to the nasopharynx and neck, and patients with stable disease received 71.2 Gy. RESULTS Between February 2006 and January 2012, 111 patients (75 male) were enrolled. Median age was 15 years, and 46.8% of the patients were African American. After a feasibility analysis, the study was amended to reduce cisplatin to two cycles during CCR. The 5-year event-free survival (EFS) and overall survival estimates were 84.3% and 89.2%, respectively. The 5-year EFS for stages IIb, III, and IV were 100%, 82.8%, and 82.7%, respectively. The 5-year cumulative incidence estimates of local, distant, and combined relapse were 3.7%, 8.7%, and 1.8%, respectively. Patients treated with three versus two CCR cycles of cisplatin had improved 5-year postinduction EFS (90.7% v 81.2%, P = .14). CONCLUSION Patients in ARAR0331 were characterized by advanced disease and by a high proportion of black children and adolescents. Treatment with IC and CRT resulted in excellent outcomes. A radiation dose reduction is possible for patients responding to IC. Although the outcomes are comparable, we observed a trend toward decreased EFS for patients assigned to receive fewer doses of cisplatin during CCR.
Keywords: amifostine; cisplatin; fluorouracil; adolescent; adult; article; bone metastasis; cancer recurrence; cancer survival; chemoradiotherapy; child; childhood cancer; clinical trial; conformal radiotherapy; continuous infusion; epithelioid sarcoma; event free survival; female; follow up; human; induction chemotherapy; intensity modulated radiation therapy; lung metastasis; major clinical study; male; multiple cycle treatment; nasopharynx; nasopharynx carcinoma; neck; overall survival; priority journal; radiation dose; radiation dose reduction

Disease-Free and Overall Survival among Patients with Operable HER2-Positive Breast Cancer Treated with Sequential vs Concurrent Chemotherapy: The ACOSOG Z1041 (Alliance) Randomized Clinical Trial - Buzdar, A.U.; Suman, V.J.; Meric-Bernstam, F.; Leitch, A.M.; Ellis, M.J.; Boughey, J.C.; Unzeitig, G.W.; Royce, M.E.; Hunt, K.K. (JAMA Oncology, 2019)
Importance: Pathologic complete response rate (pCR), the primary end point of the ACOSOG (American College of Surgeons Oncology Group) Z1041 (Alliance) trial, and disease-free survival (DFS) and overall survival (OS) in women with operable HER2-positive breast cancer are similar between treatment regimens. Objective: To assess DFS and OS for patients treated with sequential vs concurrent anthracycline plus trastuzumab. Design, Setting, and Participants: Phase 3 randomized clinical trial conducted at 36 centers in the continental United States and Puerto Rico. Women 18 years or older with invasive operable HER2-positive breast cancer were enrolled from September 15, 2007, to December 15, 2011, and randomized to 1 of 2 treatment arms. The analysis data set was locked on October 15, 2017, and analysis was completed on December 15, 2017. Interventions: Patients randomized to arm 1 received 500 mg/m2 of fluorouracil, 75 mg/m2 of epirubicin, and 500 mg/m2 of cyclophosphamide (FEC) every 3 weeks for 12 weeks followed by the combination of 80 mg/m2 of paclitaxel and 2 mg/kg (except initial dose of 4 mg/kg) of trastuzumab weekly for 12 weeks. Patients randomized to arm 2 received the same combination of paclitaxel with trastuzumab weekly for 12 weeks followed by FEC every 3 weeks with weekly trastuzumab for 12 weeks. Women with hormone receptor-positive disease received endocrine therapy, and radiotherapy was delivered at physician discretion. Main Outcomes and Measures: The primary outcomes were DFS and OS and pCR in the breast and nodes. Results: Two hundred eighty-two women with HER2-positive breast cancer were enrolled in the trial, and 2 withdrew consent before treatment. Among the remaining 280 women, the median age was 50 years (range, 28-76 years), 232 (82.9%) were white, 29 (10.3%) were black, 8 (2.9%) were Asian, 4 (1.4%) were American Indian or Alaskan Native, and 7 (2.5%) did not report race/ethnicity. There were 22 disease events in arm 1 and 27 in arm 2. Disease-free survival rates did not differ with respect to treatment arm (stratified log-rank P =.96; stratified hazard ratio [HR] [arm 2 to arm 1], 1.02; 95% CI, 0.56-1.83). Overall survival did not differ with respect to treatment arm (stratified log-rank P =.73; stratified HR [arm 2 to arm 1], 1.17; 95% CI, 0.48-2.88). Conclusions and Relevance: Across a median follow-up of 5.1 years (range, 26 days to 6.2 years), pCR, DFS, and OS did not differ with respect to sequential or concurrent administration of FEC with trastuzumab. Trial Registration: ClinicalTrials.gov identifier: NCT00513292.
Keywords: anthracycline; cyclophosphamide; epirubicin; fluorouracil; paclitaxel; trastuzumab; adult; aged; Alaska Native; American Indian; article; Asian; Black person; breast surgery; cancer chemotherapy; cancer combination chemotherapy; cancer hormone therapy; cancer patient; cancer radiotherapy; cancer surgery; cancer survival; Caucasian; clinical outcome; controlled study; disease free survival; female; human; human epidermal growth factor receptor 2 positive breast cancer; human tissue; informed consent; major clinical study; medical decision making; multicenter study; multiple cycle treatment; overall survival; phase 3 clinical trial; Puerto Rico; randomized controlled trial; survival rate; treatment duration; tumor invasion; United States

Feasibility randomised controlled trial of a guided workbook intervention to support work-related goals among cancer survivors in the UK - Grunfeld, E.A.; Schumacher, L.; Armaou, M.; Woods, P.L.; Rolf, P.; Sutton, A.J.; Zarkar, A.; Sadhra, S.S. (BMJ Open, 2019)
Objectives Employment following illness is associated with better physical and psychological functioning. This study aimed to assess the feasibility and acceptability of a theoretically led workbook intervention designed to support patients with cancer returning to work. Design Parallel-group randomised controlled trial with embedded qualitative interviews. Setting Oncology clinics within four English National Health Service Trusts. Participants Patients who had received a diagnosis of breast, gynaecological, prostate or colorectal cancer and who had been receiving treatment for a minimum of two weeks. Intervention A self-guided WorkPlan workbook designed to support patients with cancer to return to work with fortnightly telephone support calls to discuss progress. The control group received treatment as usual and was offered the workbook at the end of their 12-month follow-up. Outcome measures We assessed aspects of feasibility including eligibility, recruitment, data collection, attrition, feasibility of the methodology, acceptability of the intervention and potential to calculate cost-effectiveness. Results The recruitment rate of eligible patients was 44%; 68 participants consented and 58 (85%) completed baseline measures. Randomisation procedures were acceptable, data collection methods (including cost-effectiveness data) were feasible and the intervention was acceptable to participants. Retention rates at 6-month and 12-month follow-up were 72% and 69%, respectively. At 6-month follow-up, 30% of the usual care group had returned to full-time or part-time work (including phased return to work) compared with 43% of the intervention group. At 12 months, the percentages were 47% (usual care) and 68% (intervention). Conclusions The findings confirm the feasibility of a definitive trial, although further consideration needs to be given to increasing the participation rates among men and black and ethnic minority patients diagnosed with cancer.
Keywords: ISRCTN56342476; adult; aged; article; cancer survivor; controlled study; feasibility study; female; follow up; full time employment; human; major clinical study; male; parttime employment; randomized controlled trial; return to work; social support; telemonitoring; United Kingdom

Engaging African American Men as Citizen Scientists to Validate a Prostate Cancer Biomarker: Work-in-Progress - Watson, K.S.; Henderson, V.; Murray, M.; Murphy, A.B.; Levi, J.B.; McDowell, T.; Holloway-Beth, A.; Gogana, P.; Dixon, M.A.; Moore, L.; Hall, I.; Kimbrough, A.; et al. (Progress in community health partnerships : research, education, and action, 2019)
BACKGROUND: African American men (AAM) are under-represented in prostate cancer (PCa) research despite known disparities. Screening with prostate-specific antigen (PSA) has low specificity for high-grade PCa leading to PCa over diagnosis. The Prostate Health Index (PHI) has higher specificity for lethal PCa but needs validation in AAM. Engaging AAM as citizen scientists (CSs) may improve participation of AAM in PCa research.Results and Lessons Learned: Eight CSs completed all training modules and 139 AAM were recruited. Challenges included equity in research leadership among multiple principal investigators (PIs) and coordinating CSs trainings. CONCLUSIONS: Engaging AAM CSs can support engaging/recruiting AAM in PCa biomarker validation research. Equity among multiple stakeholders can be challenging, but proves beneficial in engaging AAM in research. OBJECTIVES: Assess feasibility of mobilizing CSs to recruit AAM as controls for PHI PCa validation biomarker study. METHODS: We highlight social networks/assets of stakeholders, CSs curriculum development/implementation, and recruitment of healthy controls for PHI validation.
Keywords: prostate specific antigen; adult; African American; age; blood; community participation; early cancer diagnosis; human; male; middle aged; motivation; organization and management; participatory research; patient selection; procedures; prostate tumor; social network; socioeconomics

Perspectives from Project Brotherhood: Facilitating Engagement of African American Men in Research - Murray, M.; Campbell, C.; Kendall, L.; Whitt-Glover, M.C.; Watson, K.S. (Progress in community health partnerships : research, education, and action, 2019)
BACKGROUND: Community-academic partnerships play a vital role in ensuring the engagement of African American (AA) men in research. Project Brotherhood (PB) is a community organization that has played an integral role in advancing prostate cancer (PCa) research within two pilot projects supported by the Chicago Cancer Health Equity Collaborative (ChicagoCHEC).Community Perspective: It is rare to see community organizations led by AA men acknowledged for their role in advancing health equity research. We provide a community perspective of PB as a model in engaging AA men in research. PB has been recognized nationally by the Centers for Disease Control and Prevention (CDC) and others demonstrating their national footprint in advancing the inclusion of AA men in all aspects of research. We hope to demonstrate that engagement of AA men in research is important and feasible and to highlight PB as a national model in engaging AA men in research.
Keywords: African American; community participation; ethnology; human; Illinois; male; organization and management; participatory research; patient selection; prostate tumor; public relations; United States

Cognitive and Affective Responses to Mass-media Based Genetic Risk Information in a Socio-demographically Diverse Sample of Smokers - Waters, E.A.; Ackerman, N.; Wheeler, C.S. (Journal of health communication, 2019)
Many individuals receive information about genomics from the mass media. When media reports are about conditions that are considered behavioral, such as smoking, they may negatively affect some health-promoting cognitions. We examined how informing adult smokers about the genetic basis for nicotine addiction influenced smoking-related health cognitions and affect and whether responses varied by socio-demographics or genetics beliefs. We recruited 392 smokers (Mage = 44.5, 52.8% African American, 51.3% no college experience, 66.2% women) from public locations in a mid-sized Midwestern city. They were randomly assigned to read a news article describing either a pharmacy's decision to stop selling tobacco (n = 78) or the discovery of a gene associated with increased risk of nicotine addiction and lung cancer (n = 314). Participants also completed a survey assessing socio-demographics, health cognitions (quit intentions, self-efficacy, response efficacy, perceived risk), affect (worry, anticipated regret), genetic determinism, and other genetics beliefs. ANOVAs revealed no statistically significant main effects of genetic information on any health cognitions or affects. Linear regressions revealed that socio-demographics and genetics beliefs moderated very few effects. This suggests that concerns that mass media-based dissemination of genetic discoveries may have detrimental effects on smoking-related cognitions and affects are likely unwarranted.
Keywords: adolescent; adult; affect; aged; cognition; controlled study; female; genetic predisposition; genetics; human; male; mass medium; medical information; middle aged; psychology; questionnaire; randomized controlled trial; risk assessment; smoking; socioeconomics; tobacco dependence; young adult

Prospective assessment of demographic characteristics associated with worse health related quality of life measures following definitive chemoradiation in patients with locally advanced non-small cell lung cancer - Vogel, J.; Wang, X.; Troxel, A.B.; Simone, C.B.; Rengan, R.; Lin, L.L. (Translational Lung Cancer Research, 2019)
Background: The purpose of this study was to evaluate baseline demographic characteristics which may be associated with worse health related quality of life (HRQOL) for patients with locally advanced non-small cell lung cancer (NSCLC) receiving definitive chemoradiation (CRT). Materials: Patients with NSCLC were prospectively enrolled on an Institutional Review Board-approved clinical trial between 2009 and 2012. HRQOL assessments were collected pre-radiation therapy (RT), during RT, and within 3 months post-RT using Euroqol (EQ-5D), MD Anderson Symptom Inventory (MDASI), and Functional Assessment of Cancer Therapy General (FACT-G). HRQOL correlation was assessed with categorical variables by Wilcoxon rank sum tests and with continuous variables by Pearson correlation. P<0.05 was defined as statistically significant. Results: Forty-three consecutive patients received definitive concurrent CRT and completed assessments at one or more time-points. Patients most commonly had stage IIIB disease (72%), were married or with a partner (70%) and Caucasian (91%). Median patient age was 65 (range: 39–79) years and Charlson comorbidity index (CCI) was 0 (range: 0–5). Female gender, African-American ethnicity, age, chemotherapy type, baseline hemoglobin, and CCI were associated with worse post-treatment HRQOL measures. Conclusions: We have identified novel characteristics associated with worse quality of life following definitive CRT for lung cancer. Patients at risk for worse post-treatment quality of life may benefit from earlier follow-up and greater supportive measures following treatment.
Keywords: carboplatin; cisplatin; hemoglobin; adult; advanced cancer; African American; aged; article; cancer localization; Caucasian; Charlson Comorbidity Index; chemoradiotherapy; clinical article; correlation analysis; correlation coefficient; demography; European Quality of Life 5 Dimensions questionnaire; female; Functional Assessment of Cancer Therapy General; human; male; non small cell lung cancer; prospective study; quality of life; rank sum test; symptom assessment

Variation in Accrual and Race/Ethnicity Reporting in Urological and Nonurological Related Cancer Trials - Paul, K.; Sathianathen, N.; Dahm, P.; Le, C.; Konety, B.R. (Journal of Urology, 2019)
Purpose:We performed a multiregistry analysis to assess relative differences in accrual sufficiency and race/ethnicity reporting in trials of common urological cancers and other nonurological solid organ tumors.Materials and Methods:We queried ClinicalTrials.gov and the ISRCTN (International Standard Randomised Controlled Trial Number) Registry for closed phase III and IV trials focused on prostate, colorectal, kidney, bladder, testicular, breast and lung cancer. Identified trials were cross-verified with appropriate published data sources. Comparative accrual sufficiency and rates of race/ethnicity reporting were calculated. Multivariable logistic regression analysis was performed to determine factors associated with accrual status and race/ethnicity reporting.Results:A total of 326 trials were identified based on our prespecified criteria, of which 63% reported sufficient accrual by time of closure and 58% reported data by race/ethnicity. Nonurological trials were significantly more likely to mention race data than urological trials (OR 3.25, 95% CI 1.24-8.55, p = 0.02). Industry sponsored trials were more likely to meet accrual targets than government funded projects (OR 5.44, 95% CI 1.64-18.20, p = 0.001). Although funding source did not influence race reporting, the reported recruitment of participants of African ethnicity was lower in industry sponsored trials (11.49% vs 3.18%, p <0.01). Two-thirds of the studies did not report baseline characteristics by African American race/ethnicity.Conclusions:Insufficient accrual and inadequate race/ethnicity reporting are prevalent issues, limiting interpretation of the results of clinical trials of major solid organ malignancies. Addressing these shortcomings would enhance result validity by raising statistical power and improving the transparency of reporting to better evaluate the generalizability of results.
Keywords: adult; African; African American; aged; article; bladder cancer; breast cancer; colorectal cancer; ethnic or racial aspects; female; human; kidney cancer; lung cancer; male; priority journal; prostate cancer; secondary analysis; testis cancer; urinary tract cancer

Sistas taking a stand for breast cancer research (STAR) study: A community-based participatory genetic research study to enhance participation and breast cancer equity among African American women in Memphis, TN - Smith, A.; Vidal, G.A.; Pritchard, E.; Blue, R.; Martin, M.Y.; Rice, L.J.; Brown, G.; Starlard-Davenport, A. (International Journal of Environmental Research and Public Health, 2018)
African American women are substantially underrepresented in breast cancer genetic research studies and clinical trials, yet they are more likely to die from breast cancer. Lack of trust in the medical community is a major barrier preventing the successful recruitment of African Americans into research studies. When considering the city of Memphis, TN, where the percentage of African Americans is significantly higher than the national average and it has a high rate of breast cancer mortality inequities among African American women, we evaluated the feasibility of utilizing a community-based participatory (CBPR) approach for recruiting African American women into a breast cancer genetic study, called the Sistas Taking A Stand for Breast Cancer Research (STAR) study. From June 2016 and December 2017, African American women age 18 and above were recruited to provide a 2 mL saliva specimen and complete a health questionnaire. A total of 364 African American women provided a saliva sample and completed the health questionnaire. Greater than 85% agreed to be contacted for future studies. Educational workshops on the importance of participating in cancer genetic research studies, followed by question and answer sessions, were most successful in recruitment. Overall, the participants expressed a strong interest and a willingness to participate in the STAR study. Our findings highlight the importance of implementing a CBPR approach that provides an educational component detailing the importance of participating in cancer genetic research studies and that includes prominent community advocates to build trust within the community.
Keywords: adult; African American; article; breast cancer; cancer research; female; genetic analysis; health education; health equity; health status; human; interpersonal communication; major clinical study; middle aged; participatory research; patient advocacy; patient attitude; patient participation; questionnaire; saliva analysis; Tennessee; workshop

A Prospective Adaptive Utility Trial to Validate Performance of a Novel Urine Exosome Gene Expression Assay to Predict High-grade Prostate Cancer in Patients with Prostate-specific Antigen 2–10 ng/ml at Initial Biopsy - McKiernan, J.; Donovan, M.J.; Margolis, E.; Partin, A.; Carter, B.; Brown, G.; Torkler, P.; Noerholm, M.; Skog, J.; Shore, N.; Andriole, G.; Thompson, I.; et al. (European Urology, 2018)
Background: Discriminating indolent from clinically significant prostate cancer (PCa) in the initial biopsy setting remains an important issue. Prospectively evaluated diagnostic assays are necessary to ensure efficacy and clinical adoption. Objective: Performance and utility assessment of ExoDx Prostate (IntelliScore) (EPI) urine exosome gene expression assay versus standard clinical parameters for discriminating Grade Group (GG) ≥2 PCa from GG1 PCa and benign disease on initial biopsy. Design, setting, and participants: A two-phase adaptive clinical utility study (NCT03031418) comparing EPI results with biopsy outcomes in men, with age ≥50 yr and prostate-specific antigen (PSA) 2–10 ng/ml, scheduled for initial prostate biopsy. After EPI performance assessment during phase I, a clinical implementation document (ie, CarePath) was developed for utilizing the EPI test in phase II, where the biopsy decision is uncertain. Outcome measurements and statistical analysis: Performance evaluation of the EPI test in patients enrolled in phase I and publication of a consensus CarePath for phase II. Results and limitations: In a total of 503 patients, with median age of 64 yr, median PSA 5.4 ng/ml, 14% African American, 70% Caucasian, 53% positive biopsy rate (22% GG1, 17% GG2, and 15% ≥ GG3), EPI was superior to an optimized model of standard clinical parameters with an area under the curve (AUC) 0.70 versus 0.62, respectively, comparable with previously published results (n = 519 patients, EPI AUC 0.71). Validated cut-point 15.6 would avoid 26% of unnecessary prostate biopsies and 20% of total biopsies, with negative predictive value (NPV) 89% and missing 7% of ≥GG2 PCa. Alternative cut-point 20 would avoid 40% of unnecessary biopsies and 31% of total biopsies, with NPV 89% and missing 11% of ≥GG2 PCa. The clinical investigators reached consensus recommending use of the 15.6 cut-point for phase II. Outcome of the decision impact cohort in phase II will be reported separately. Conclusions: EPI is a noninvasive, easy-to-use, gene expression urine assay, which has now been successfully validated in over 1000 patients across two prospective validation trials to stratify risk of ≥GG2 from GG1 cancer and benign disease. The test improves identification of patients with higher grade disease and would reduce the total number of unnecessary biopsies. Patient summary: It is challenging to predict which men are likely to have high-grade prostate cancer (PCa) at initial biopsy with prostate-specific antigen 2–10 ng/ml. This study further demonstrates that the ExoDx Prostate (IntelliScore) test can predict ≥GG2 PCa at initial biopsy and defer unnecessary biopsies better than existing risk calculator's and standard clinical data. ExoDx Prostate (IntelliScore) is a urine-based test that relies solely on a three-gene signature to predict high-grade prostate cancer at initial biopsy for men with prostate-specific antigen 2–10 ng/ml. The test has been prospectively validated on over 1000 men from two multisite trials.
Keywords: NCT03031418; adult; African American; aged; area under the curve; article; Asian; cancer diagnosis; Caucasian; clinical outcome; cohort analysis; consensus; controlled clinical trial; controlled study; diagnostic value; exosome; false negative result; gene expression assay; health care quality; Hispanic; human; human tissue; major clinical study; male; needle biopsy; phase 1 clinical trial; phase 2 clinical trial; predictive value; priority journal; prospective study; prostate biopsy; prostate cancer; shared decision making; transrectal ultrasonography; tumor biopsy; urine; urine volume; validation study

Racial and Ethnic Differences in Prostate Cancer Survivors' Perceived Engagement in Treatment Decision-Making - Palmer, N.R.; Gregorich, S.E.; Livaudais-Toman, J.; Jih, J.; Kaplan, C.P. (Journal of racial and ethnic health disparities, 2018)
OBJECTIVE: We examined prostate cancer patients' perceived engagement in treatment decision-making and associated factors by race/ethnicity in a multiethnic sample. METHOD: We identified patients through the California Cancer Registry. Patients completed a cross-sectional telephone interview in English, Spanish, Cantonese, or Mandarin. Multivariable logistic regression models, stratified by race/ethnicity, estimated the associations of patient demographic and health status characteristics on (1) doctor asked patient to help decide treatment plan and (2) patient and doctor worked out a treatment plan together. RESULTS: We included 855 prostate cancer patients: African American (19%), Asian American (15%), Latino (24%), and White (42%). Asian American patients were less likely than White patients to report that their doctors asked them to help decide a treatment plan (OR = 0.31; 95% CI = 0.18-0.53) and that they worked out a treatment plan with their doctors (OR = 0.54; 95% CI = 0.33-0.90). Language of interview was a significant contributing factor in stratified analysis for both outcomes. CONCLUSION: Asian American prostate cancer patients reported less engagement in treatment decision-making, with Chinese language being a significant contributing factor. Future research should identify patient-centered strategies that effectively engage underserved patients and support healthcare providers in shared decision-making with multiethnic and multilingual patients.
Keywords: adult; African American; aged; Asian American; cancer survivor; Caucasian; cross-sectional study; decision making; ethnic group; ethnology; health care disparity; Hispanic; human; male; middle aged; multivariate analysis; patient participation; prostate tumor; statistical model

Learning, Life, and Lactation: Knowledge of Breastfeeding's Impact on Breast Cancer Risk Reduction and Its Influence on Breastfeeding Practices - Ganju, A.; Suresh, A.; Stephens, J.; Palettas, M.; Burke, D.; Miles, L.; Lehman, K.; Rudesill, R.; Lustberg, M.; Bose-Brill, S.; Ramaswamy, B. (Breastfeeding medicine : the official journal of the Academy of Breastfeeding Medicine, 2018)
Introduction: The protective effects of breastfeeding against developing breast cancer are well known; however, it is unknown whether women are aware of this breastfeeding benefit. Research Aim/Questions: The aim of this investigation was to determine whether mothers received information about breast cancer risk reduction during breastfeeding counseling and whether this knowledge affected their decision to initiate and sustain breastfeeding. Materials and Methods: The survey was conducted at The Ohio State University Comprehensive Cancer Center with women aged 18-50 who had at least one live birth. Participants were recruited through primary care practice and a national clinical research registry. Results: Six hundred sixty-seven (92%) of the 724 respondents breastfed. Over half of them (56%), that is, 407 women (60.4% Caucasian, 46.9% African American), were aware before their most recent childbirth that breastfeeding reduced the risk of breast cancer. Of the 407 women, 36.4% said this knowledge affected their decision to breastfeed. Of the 39 who did not breastfeed, 23 women (59.0%) responded that awareness of risk reduction would have influenced their decision to breastfeed. Only 120 of 724 respondents (16.6%) received this information from healthcare providers. Women with this knowledge breastfed longer than those without this knowledge (13.2 versus 9.3 months; p < 0.001). More Caucasian women (76.4%) breastfed any one child for more than 6 months compared with African American women (63.2%; p = 0.011; chi-squared test). Conclusion: While several factors affect the initiation and duration of breastfeeding, this study demonstrates that knowledge of association between breastfeeding and breast cancer risk reduction may influence breastfeeding practices. Our study illustrates the need for improved counseling for mothers by healthcare providers regarding this benefit.
Keywords: adult; African American; article; awareness; breast cancer; breast feeding; cancer center; cancer risk; Caucasian; child; childbirth; clinical research; controlled study; counseling; female; health care personnel; human; human experiment; lactation; learning; live birth; major clinical study; mother; Ohio; primary medical care; risk reduction; young adult

Low-dose computed tomography lung cancer screening as a teachable moment for smoking cessation among African American smokers: A feasibility study - Sly, J.R.; Miller, S.J.; Li, Y.; Bolutayo, K.; Jandorf, L. (Journal of Psychosocial Oncology, 2018)
Low-dose computed tomography (LDCT) screening may be a teachable moment for smoking cessation among African Americans. African Americans have been understudied within the context of LDCT and smoking cessation. The study objective was to evaluate the feasibility of recruiting African Americans to a future longitudinal trial and to obtain sample size estimates for that trial. Participants (N = 18) were African Americans eligible for LDCT screening who completed a questionnaire at three time points. Self-efficacy and intention to quit smoking were compared. The results of the current study show that it is feasible to recruit African Americans eligible for LDCT.
Keywords: electronic cigarette; nicotine gum; nicotine patch; adult; African American; article; cancer screening; clinical article; comparative study; computer assisted tomography; feasibility study; female; human; longitudinal study; lung cancer; male; middle aged; radiation dose; self concept; smoking; smoking cessation; thorax radiography; tobacco dependence

Attitudes Toward Genomic Testing and Prostate Cancer Research Among Black Men - Rogers, C.R.; Rovito, M.J.; Hussein, M.; Obidike, O.J.; Pratt, R.; Alexander, M.; Berge, J.M.; Dall'Era, M.; Nix, J.W.; Warlick, C. (American Journal of Preventive Medicine, 2018)
Introduction: Black men are diagnosed with prostate cancer at nearly twice the rate of white men and are underrepresented in prostate cancer research, including validation studies of new clinical tools (e.g., genomic testing). Because healthcare system mistrust has contributed to these disparities for centuries, black men may be less inclined to pursue novel testing, and identification of facilitators to their participation in prostate cancer research studies remains warranted. Methods: A community-engaged approach involving a partnership with a community organization was used to conduct seven focus groups in Minnesota, Alabama, and California to explore black men's attitudes toward prostate cancer research participation and genomic testing for prostate cancer. Data were collected and analyzed from April 2015 to April 2017. Results: Identified genomic testing barriers included a lack of terminology understanding, healthcare system mistrust, reluctance to seek medical care, and unfavorable attitudes toward research. Facilitators included family history, value of prevention, and the desire for health education. Lack of prostate cancer knowledge, prostate-specific antigen testing confusion, healthcare system distrust, and misuse of personal health information were barriers to research study participation. Some black men were motivated to participate in research if it was seen as constructive and transparent. Conclusions: Disparities for black men can both motivate and disincentivize participation depending upon a positive or negative view of research. Confusion over prostate cancer clinical care has fueled some mistrust among black men affecting both clinical care and research participation. With increased education, health literacy, and assurances of research integrity and transparency, black men may be more willing to participate in prostate cancer testing and research. Supplement information: This article is part of a supplement entitled African American Men's Health: Research, Practice, and Policy Implications, which is sponsored by the National Institutes of Health.
Keywords: prostate specific antigen; adult; article; attitude to health; Black person; cancer research; controlled study; doctor patient relationship; educational status; genetic screening; genome analysis; health literacy; human; major clinical study; male; motivation; patient attitude; patient education; patient participation; prostate cancer; trust

Vitamin D Supplementation in Elderly Black Women Does Not Prevent Bone Loss: A Randomized Controlled Trial - Aloia, J.; Fazzari, M.; Islam, S.; Mikhail, M.; Shieh, A.; Katumuluwa, S.; Dhaliwal, R.; Stolberg, A.; Usera, G.; Ragolia, L. (Journal of Bone and Mineral Research, 2018)
Black Americans have lower levels of serum 25(OH)D but superior bone health compared to white Americans. There is controversy over whether they should be screened for vitamin D deficiency and have higher vitamin D requirements than recommended by the Institute of Medicine (IOM). The purpose of this trial was to determine whether Vitamin D supplementation in elderly black women prevents bone loss. A total of 260 healthy black American women, 60 years of age and older were recruited to take part in a two-arm, double-dummy 3-year randomized controlled trial (RCT) of vitamin D3 versus placebo. The study was conducted in an ambulatory clinical research center. Vitamin D3 dose was adjusted to maintain serum 25(OH)D above 75 nmol/L. Bone mineral density (BMD) and serum were measured for parathyroid hormone (PTH), C-terminal crosslink telopeptide (CTX), and bone-specific alkaline phosphatase (BSAP) every 6 months. Baseline serum 25(OH)D3 was 54.8 ± 16.8 nmol/L. There was no group × time interaction effect for any BMD measurement. For all BMD measurements, except for total body and spine, there was a statistically significant negative effect of time (p < 0.001). An equivalency analysis showed that the treatment group was equivalent to the control group. Serum PTH and BSAP declined, with a greater decline of PTH in the treatment group. The rate of bone loss with serum 25(OH)D above 75 nmol/L is comparable to the rate of loss with serum 25(OH)D at the Recommended Dietary Allowance (RDA) of 50 nmol/L. Black Americans should have the same exposure to vitamin D as white Americans. © 2018 American Society for Bone and Mineral Research.
Keywords: NCT011533568; 25 hydroxyvitamin D; alkaline phosphatase bone isoenzyme; calcium carbonate; carboxy terminal telopeptide; colecalciferol; parathyroid hormone; placebo; African American; aged; aging; alkaline phosphatase blood level; application site reaction; article; benign neoplasm; bone density; breast disease; clinical research; congenital disorder; connective tissue disease; controlled study; dietary reference intake; double blind procedure; drug dose increase; ear disease; endocrine disease; eye disease; familial disease; female; femur; gastrointestinal disease; genetic disorder; heart disease; hematologic disease; hepatobiliary disease; human; hypercalciuria; immunopathology; infection; infestation; injury; inner ear disease; intoxication; kidney disease; lymphatic system disease; major clinical study; malignant neoplasm; mediastinum disease; medication compliance; mental disease; metabolic disorder; musculoskeletal disease; neurologic disease; nutritional disorder; osteolysis; osteoporosis; parathyroid hormone blood level; patient compliance; prospective study; protein cross linking; randomized controlled trial; respiratory tract disease; risk reduction; serum; side effect; skin disease; spine; thorax disease; urinary tract disease; vascular disease; vitamin blood level; vitamin supplementation

Adjuvant Pelvic Radiation "sandwiched" between Paclitaxel/Carboplatin Chemotherapy in Women with Completely Resected Uterine Serous Carcinoma: Long-term Follow-up of a Prospective Phase 2 Trial - Frimer, M.; Miller, E.M.; Shankar, V.; Girda, E.; Mehta, K.; Smith, H.O.; Kuo, D.Y.S.; Goldberg, G.L.; Einstein, M.H. (International Journal of Gynecological Cancer, 2018)
Objective We prospectively evaluated patients with completely resected uterine serous carcinoma (USC) treated with radiation "sandwiched" between carboplatin/paclitaxel (C/T). The primary objective was to determine the safety profile, and the secondary outcome was to evaluate progression-free and overall survival. Methods Surgically staged patients with completely resected USC were enrolled to receive 3 cycles of paclitaxel 175 mg/m2 and carboplatin (area under the curve, 6-7.5) every 21 days, followed by radiotherapy and an additional 3 cycles of T/C at area under the curve of 5-6 (6 cycles + radiotherapy). Toxicity was graded according to National Cancer Institute Common Toxicity Criteria, version 4.03. Kaplan-Meier and log-rank tests were used to compare survival probabilities. Results One hundred forty patients were enrolled, of which 132 were evaluable, completed at least 3 cycles of chemotherapy and radiation. One hundred seven (81%) completed 6 cycles of chemotherapy and radiation. Patients with early-stage (I/II) disease have survival probabilities of 0.96 and 0.81 at 2 and 5 years. Patients with stage I USC and lymphovascular invasion have considerably worse overall survival, with 2.7 times' higher risk of death than those without lymphovascular invasion. Patients with late-stage (III/IV) disease had overall survival probabilities of 0.64 and 0.18 at 2 and 5 years, which is far higher survival than what has been reported in single-modality trials. Interestingly, and different than what is reported in other studies, there is no difference in survival in African Americans versus whites/other races who were evaluable. Of the 779 cycles administered, 22% and 14% of cycles were associated with grades 3 and 4 hematologic toxicities, respectively. Grades 3 and 4 nonhematologic toxicities occurred in 6.9% of cycles. Conclusions The long-term follow-up in this study demonstrates that "sandwich" therapy is an efficacious, well-tolerated treatment approach with acceptable toxicities. Lymphovascular invasion (LVSI) is a significantly poor prognostic factor in stage I USC. Multimodal "sandwich" therapy should be considered in all USC patients who have undergone complete surgical resection and staging.
Keywords: NCT00231868); carboplatin; paclitaxel; African American; aged; anemia; article; brachytherapy; cancer staging; Caucasian; deep vein thrombosis; external beam radiotherapy; female; follow up; gastrointestinal disease; human; infection; lung embolism; lymph vessel metastasis; major clinical study; metabolic disorder; multiple cycle treatment; neurologic disease; neutropenia; overall survival; phase 2 clinical trial; priority journal; progression free survival; prospective study; thrombocytopenia; urosepsis; uterus carcinoma

Patient Voices Network: Bringing Breast Cancer Awareness and Action into Underserved Communities - Reilly, S.M.; Wilson Crowley, M.; Harold, P.; Hemphill, D.; Tumiel Berhalter, L. (Journal of the National Medical Association, 2018)
Background/Purpose: African American women are diagnosed with breast cancer at later stages and have higher mortality rates than white women. The Patient Voices Network (PVN), a community group whose vision is “a community of educated and involved patients working hand in hand with physicians in making decisions about their own health care,” conceived of and implemented a walk to raise awareness of breast cancer and link women to screening resources in a low-income, urban community Objectives: To describe the planning and implementation of the Concerned About You: Breast Cancer Awareness Walk & Wellness Event and its impact on an academic community partnership. Methods: A narrative approach was used. Meeting minutes and event planning notes were reviewed. Community participation rates and participant satisfaction were tracked using registration records and a survey administered at the event. Results: 328 community members registered and 194 attended. Responses to a satisfaction survey indicated community buy-in and interest in future events. Two women were screened at the event and 78 were screened at a follow-up opportunity at their primary care practices. The process was driven by participatory guidelines and laid the foundation for future activities. Conclusions: Community input addressed the need for screening mammography in an underserved community. The partnership approach featured complementary strengths of both patients and University staff, fostered skill building and co-learning, and ultimately strengthened our partnership. A partnered approach may be effective in engaging hard-to-reach populations to address health disparities.
Keywords: adult; aged; article; breast cancer; breast cancer awareness; cancer patient; cancer screening; community care; community participation; female; follow up; health care organization; health care planning; health program; health survey; human; major clinical study; medically underserved; middle aged; narrative; patient satisfaction; practice guideline; primary medical care; priority journal; skill; wellbeing; young adult

At What Cost to Clinical Trial Enrollment? A Retrospective Study of Patient Travel Burden in Cancer Clinical Trials - Borno, H.T.; Zhang, L.; Siegel, A.; Chang, E.; Ryan, C.J. (Oncologist, 2018)
Background: Recent literature suggests that living in a rural setting may be associated with adverse cancer outcomes. This study examines the burden of travel from home to cancer center for clinical trial (CT) enrollees. Materials and Methods: Patients from the University of California San Francisco Clinical Trial Management System database who enrolled in a cancer CT for a breast, genitourinary, or gastrointestinal malignancy between 1993 and 2014 were included. Cancer type, household zip code, race/ethnicity, phase of study, study sponsor, and year of signed consent were exported. Distance traveled from home to center was calculated using a GoogleMaps application programming interface. The relationships of distance with phase of CT, household income, and race/ethnicity were examined. Results: A total of 1,600 patients were enrolled in breast (55.8%), genitourinary (29.4%), or gastrointestinal (14.9%) cancer CTs. The overall median unidirectional distance traveled from home to study site was 25.8 miles (interquartile range [IQR] 11.5–75.3). Of the trial sponsors examined, principal investigator (56.4%), industry (22.2%), cooperative group (11.6%), and National Institutes of Health (NIH; 9.8%), the longest distance traveled was for NIH-sponsored trials, with a median of 39.4 miles (p <.001). Phase I (8.4%) studies had the longest distance traveled, with a median of 41.2 miles (IQR 14.5–101.0 miles; p =.001). White patients (83%) traveled longer compared with black patients (4.4%), with median distances of 29.9 and 13.9 miles, respectively (p <.001). Patients from lower-income areas (n = 799) traveled longer distances compared with patients from higher-income areas (n = 773; 58.3 vs. 17.8 miles, respectively; p <.001). A multivariable linear model where log10 (distance) was the outcome and adjusting for the exported variables and income revealed that cancer type, year of consent, race/ethnicity, and income were significantly associated with distance traveled. Conclusion: This study found that the burden of travel is highest among patients enrolled in NIH-sponsored trials, phase I studies, or living in low-income areas. These data suggest that travel burden for cancer CT participants may be significant. Implications for Practice: This study is one of the first to measure travel distance for patients in cancer clinical trials using a real-world GoogleMaps calculator. Out-of-pocket expenses such as travel are not typically covered by health care payers; therefore, patients may face considerable cost to attend each study visit. Using a single-center clinical trials enrollment database, this study found that the burden of travel is highest for patients enrolled in National Institutes of Health-sponsored trials and phase I studies, as well as for patients living in low-income areas. Results suggest that a significant proportion of patients enrolled in clinical trials face a substantial travel burden.
Keywords: article; breast cancer; cancer patient; cancer research; clinical trial (topic); cost; digestive system cancer; ethnicity; home; human; income; major clinical study; national health organization; phase 1 clinical trial (topic); phase 2 clinical trial (topic); phase 3 clinical trial (topic); phase 4 clinical trial (topic); race; retrospective study; travel; urogenital tract cancer

A randomized phase II trial of MOVING ON: An intervention to increase exercise outcome expectations among breast cancer survivors - Hirschey, R.; Kimmick, G.; Hockenberry, M.; Shaw, R.; Pan, W.; Page, C.; Lipkus, I. (Psycho-Oncology, 2018)
Objective: The objective of the study is to test theoretical intervention fidelity and feasibility of MOVING ON, a self-directed, home-based, randomized controlled trial to increase exercise outcome expectations (OEs) (what one expects to obtain or avoid as a result of a behavior or lack thereof), among breast cancer survivors. Method: Stage Ia to IIb survivors (n = 60) were given the MOVING ON intervention or control booklet. Data were collected through online surveys and an accelerometer at baseline, 4, 8, and 12 weeks postintervention. Fidelity was measured by questions assessing participant perceptions of MOVING ON (score ≥2) and direction of intervention effects. Feasibility was measured by recruitment rate (target of 60 participants in 6 months), retention (total attrition <17%), and acquisition of accelerometer data (% ≥subjective exercise data obtained). Analyses consisted of descriptive statistics, mixed models, and content analysis. Results: Fidelity met a priori criteria (mean = 3.31, SD = 0.87). Outcome expectations increased 0.01 points, and weekly steps increased by 970 every 4 weeks in the intervention arm compared to the control arm. All effect sizes were small, ranging from 0.01 to 0.09. Target enrollment, achieved in 17 weeks, met a priori feasibility criteria. Retention (66%) and accelerometer data acquisition (60%) (compared to 73% of subjective exercise data) did not. Conclusion: MOVING ON influenced OEs as intended and was well received by participants. A fully powered study, of this low-cost, easy-to-implement intervention, is warranted. Intervention and measurement strategies used in MOVING ON can be incorporated in any study targeting OEs as a mediator of exercise or collecting exercise data with an accelerometer.
Keywords: NCT02348710; accelerometer; Fitbit; anastrozole; exemestane; letrozole; adult; African American; article; Black person; breast cancer; cancer staging; cancer survivor; Caucasian; content analysis; controlled study; data analysis; descriptive research; effect size; employment status; exercise; expectation; feasibility study; human; information processing; lumpectomy; major clinical study; marriage; mastectomy; medical research; middle aged; online system; outcome assessment; partial mastectomy; patient attitude; patient participation; phase 2 clinical trial; randomized controlled trial; arimidex; aromasin; femara; Fitbit

Secondary spontaneous pneumothorax in patients with sarcoma treated with Pazopanib, a case control study - Sabath, B.; Muhammad, H.A.; Balagani, A.; Ost, D.E.; Vakil, E.; Ahmed, T.; Vial, M.R.; Grosu, H.B. (BMC Cancer, 2018)
Background: The tyrosine kinase inhibitor pazopanib is used for treatment of sarcoma. Recent studies have suggested that the use of pazopanib may lead to the development of pneumothorax, an unexpected adverse effect in patients with sarcoma metastatic to the chest. Methods: We conducted a retrospective case control study of patients with sarcoma with metastases to the chest with pneumothorax (cases) and without pneumothorax (controls). The control population was selected from tumor registry in a 1:4 (cases to controls) ratio. The primary outcome of interest was the association between pazopanib and pneumothorax risk in patients with sarcoma metastatic to the chest. Secondary objective was to evaluate risk factors for pneumothorax. Results: We identified 41 cases and 164 controls. Using purposeful selection method the odds of developing pneumothorax while being on pazopanib was not significant in univariate (p =.06) and multivariable analysis (p =.342). On univariate analysis risk factors of pneumothorax in patients with sarcoma were age, male sex, African American race, the presence of cavitary lung nodules/masses, and the presence of pleural-based nodules/masses. On multivariate analysis, only the presence of cavitary lung nodules/masses (P <.001) and the presence of pleural-based nodules/masses (P <.001) remained as risk factors for developing pneumothorax. Conclusion: Pazopanib does not increase the risk of pneumothorax in patients with sarcoma and evidence of metastatic disease to the chest. Presence of cavitary lung nodules/masses and the presence of pleural-based nodules/masses were found to be risk factors for pneumothorax.
Keywords: pazopanib; adult; African American; age; article; cancer registry; cancer risk; case control study; case report; clinical article; controlled study; disease association; disease course; human; lung nodule; metastasis; outcome assessment; patient selection; retrospective study; risk factor; sarcoma; sex difference; spontaneous pneumothorax

Exercise in african American and white colorectal cancer survivors: A mixed-methods approach - Ray, A.D.; Masucci Twarozek, A.; Williams, B.T.; Erwin, D.O.; Underwood, W.; Mahoney, M.C. (Rehabilitation Oncology, 2018)
Background: African American (AA) colorectal cancer (CRC) survivors tend to be more obese and less physically active than white survivors. Purpose/Objective: To test the feasibility of an aerobic exercise program as well as explore perceptions about supervised exercise among AA CRC survivors. Methods: A prospective supervised exercise intervention performed on a cycle ergometer 2 d/wk for 12 weeks. Peak (o2peak) and submaximal exercise (Six-Minute Walk Test [6MWT]) along with questionnaires (36-Item Short Form Health Survey [SF-36], Memorial Sloan Kettering Cancer Center Bowel Function Instrument [BFI], Functional Assessment of Cancer Therapy-Colorectal (FACT-C) and Fatigue (FACIT-F), and Brief Symptom Inventory [BSI]). A second group of survivors participated in an interview evaluating perceptions regarding exercise. Design: Prospective case series and qualitative interview. Setting: Research university and academic medical center. Patients: AA and white CRC survivors. Results: Quantitative: A total of 237 letters were mailed to CRC survivors (112 whites, 126 AAs). From the letters, 25 whites and 15 AAs expressed interest; only 5 whites (4.5%) and 4 AAs (3.2%) enrolled. Two AA and 5 white survivors (7/9) finished the program. There was an improvement in peak exercise (P =.011) and quality of life (QOL) (SF-36 total, P =.035) posttraining. Qualitative: 30 CRC survivors (12 AAs and 18 whites) participated in qualitative interviews and selected comorbidity, motivation, and location as primary barriers to exercise. Limitations: Small sample size. Conclusions: Recruiting CRC survivors (regardless of race) into an exercise program is challenging; however, there are exercise and QOL benefits associated with participation. Barriers to exercise are similar between AA and white CRC survivors.
Keywords: bicycle ergometer; Ergoselect 100; adult; aerobic exercise; African American; aged; article; Bowel Function Instrument; Brief Symptom Inventory; cancer center; cancer survivor; cardiopulmonary exercise test; case study; Caucasian; colorectal cancer; comorbidity; digestive system disease assessment; exploratory research; female; Functional Assessment of Cancer Therapy Colorectal; Functional Assessment of Cancer Therapy Fatigue; functional status assessment; human; intervention study; major clinical study; male; middle aged; motivation; multicenter study; patient participation; perception; program feasibility; prospective study; qualitative research; quality of life; quality of life assessment; quantitative study; race difference; self report; semi structured interview; Short Form 36; six minute walk test; university hospital; Ergoselect 100

Long-term outcomes following conventionally fractionated stereotactic boost for high-grade gliomas in close proximity to critical organs at risk - Repka, M.C.; Lei, S.; Campbell, L.; Suy, S.; Voyadzis, J.-M.; Kalhorn, C.; McGrail, K.; Jean, W.; Subramaniam, D.S.; Lischalk, J.W.; Collins, S.P.; Collins, B.T. (Frontiers in Oncology, 2018)
Purpose/Objective: High-grade glioma is the most common primary malignant tumor of the CNS, with death often resulting from uncontrollable intracranial disease. Radiation dose may be limited by the tolerance of critical structures, such as the brainstem and optic apparatus. In this report, long-term outcomes in patients treated with conventionally fractionated stereotactic boost for tumors in close proximity to critical structures are presented. Materials/Methods: Patients eligible for inclusion in this single institution retrospective review had a pathologically confirmed high-grade glioma status post-surgical resection. Inclusion criteria required tumor location within one centimeter of a critical structure, including the optic chiasm, optic nerve, and brainstem. Radiation therapy consisted of external beam radiation followed by a conventionally fractionated stereotactic boost. Oncologic outcomes and toxicity were assessed. Results: Thirty patients eligible for study inclusion underwent resection of a high-grade glioma. The median initial adjuvant EBRT dose was 50 Gy with a median conventionally fractionated stereotactic boost of 10 Gy. All stereotactic treatments were given in 2 Gy daily fractions. Median follow-up time for the entire cohort was 38 months with a median overall survival of 45 months and 5-year overall survival of 32.5%. The median freedom from local progression was 45 months, and the 5-year freedom from local progression was 29.7%. Two cases of radiation retinopathy were identified following treatment. No patient experienced toxicity attributable to the optic chiasm, optic nerve, or brainstem and no grade 3+ radionecrosis was observed. Conclusions: Oncologic and toxicity outcomes in high-grade glioma patients with tumors in unfavorable locations treated with conventionally fractionated stereotactic boost are comparable to those reported in the literature. This treatment strategy is appropriate for those patients with resected high-grade glioma in close proximity to critical structures.
Keywords: lomustine; procarbazine; temozolomide; vincristine; adjuvant chemotherapy; adjuvant radiotherapy; adolescent; adult; African American; aged; article; brain stem; cancer chemotherapy; cancer patient; cancer radiotherapy; cancer survival; Caucasian; cause of death; cerebrovascular accident; clinical article; clinical outcome; conformal radiotherapy; disease exacerbation; electrocorticography; external beam radiotherapy; female; follow up; glioma; histology; human; intensity modulated radiation therapy; laser coagulation; lung embolism; male; middle aged; occipital lobe; optic chiasm; optic nerve; organs at risk; overall survival; parietal lobe; patient selection; prescription; radiation dose fractionation; radiation field; radiation injury; radiation necrosis; radiation retinopathy; retinopathy; stereotactic radiosurgery; stereotactic treatment; temporal lobe; tumor growth; tumor localization; tumor recurrence; visual acuity; x-ray computed tomography

Representation of Minorities and Elderly Patients in Multiple Myeloma Clinical Trials - Duma, N.; Azam, T.; Riaz, I.B.; Gonzalez-Velez, M.; Ailawadhi, S.; Go, R. (Oncologist, 2018)
Multiple myeloma (MM) occurs in all races, but the incidence in non-Hispanic black patients (NHBs) is two to three times higher than in non-Hispanic white patients (NHWs). We determined the representation of minorities and elderly patients in MM clinical trials. Enrollment data from all therapeutic trials reported in ClinicalTrials.gov from 2000 to 2016 were analyzed. Enrollment fraction (EF) was defined as the number of trial enrollees divided by the 2014 MM prevalence. Participation in MM clinical trials varied significantly across racial and ethnic groups; NHWs were more likely to be enrolled in clinical trials (EF 0.18%) than NHBs (EF 0.06%, p <.0001) and Hispanic patients (EF 0.04%, p <.0001). The median age of trial participants was 62 years, with 7,956 participants (66%) being less than 65 years of age. Collaborations between investigators, sponsors, and the community are necessary to increase access to clinical trials to our minority and elderly patients.
Keywords: adult; age distribution; aged; article; cancer patient; female; Hispanic; human; major clinical study; male; multiple myeloma; phase 1 clinical trial; phase 2 clinical trial; phase 3 clinical trial; prevalence; priority journal

Establishment of the Alabama Hereditary Cancer Cohort - strategies for the inclusion of underrepresented populations in cancer genetics research - Bishop, M.R.; Shah, A.; Shively, M.; Huskey, A.L.W.; Omeler, S.M.; Bilgili, E.P.; Jackson, E.; Daniell, K.; Stallworth, E.; Spina, S.; Shepp, K.; Bergstresser, S.; et al. (Molecular genetics & genomic medicine, 2018)
BACKGROUND: Historically, groups that are most susceptible to health and healthcare disparities have been underrepresented in medical research. It is imperative to explore approaches that can facilitate the recruitment of underrepresented individuals into research studies. METHODS: Two approaches, hospital and community-based recruitment (CBR), were developed and implemented over 36 months to study the genetics of hereditary breast cancer and associated cancers in Alabama, a medically underserved state with double the national percentage of self-identifying African Americans, establishing the Alabama Hereditary Cancer Cohort. RESULTS: Overall, 242 individuals enrolled. This included 84 cancer probands through hospital recruitment, as well as 76 probands and 82 family members through CBR. Eighty-one percent of the study participants' counties of residence are completely medically underserved. Furthermore, African Americans represent 26% of the hospital probands compared to 49% and 70% of the probands and family members who, respectively, enrolled through CBR. CONCLUSION: Although both recruitment mechanisms were instrumental, the unique trust building, educational, and traveling components of CBR facilitated the enrollment of African Americans resulting in large families for genetic analyses. The ultimate goal is to gain insight from these rudimentary efforts in order to expand recruitment and accrue a unique resource for cancer genetics research.
Keywords: adult; aged; Alabama; clinical trial; cohort analysis; family; female; genetics; human; male; medical genetics; middle aged; multicenter study; neoplasm

An estrogen-related lifestyle score is associated with risk of postmenopausal breast cancer in the PLCO cohort - Guinter, M.A.; McLain, A.C.; Merchant, A.T.; Sandler, D.P.; Steck, S.E. (Breast Cancer Research and Treatment, 2018)
Purpose: Healthy or unhealthy lifestyle behaviors are often adopted together. We aimed to investigate the combined effect of estrogen-related lifestyle factors on postmenopausal breast cancer risk. Methods: Data from 27,153 women enrolled in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial were used. We created an estrogen-related lifestyle score (ERLS) by incorporating a previously developed measure of estrogenic diet, alcohol intake, body mass index (BMI), and physical activity. The scores ranged from 0 to 6 with alcohol and BMI accounting for higher weights than the other factors. To evaluate the preventive possibilities of a low estrogen-related lifestyle and to be consistent with other published lifestyle scores, higher scores were set to correspond with potentially lower estrogenic lifestyle. The association between the ERLS and incident breast cancer was examined using Cox proportional hazards models. Results: Participants with an ERLS of 4 or ≥ 5 had a 23% (HR 0.77; 95% CI 0.67–0.89) and 34% (HR 0.66; 95% CI 0.56–0.78) lower risk of breast cancer, respectively, compared to those with an ERLS ≤ 2 after multivariable adjustment. Estimates were similar when restricting to invasive cases or estrogen receptor-positive subtypes. No single lifestyle component appeared to drive the association. Conclusions: Our findings suggest that the combined effect of a lifestyle characterized by a low estrogenic diet, low alcohol consumption, low body weight, and high levels of physical activity are associated with a reduction in postmenopausal breast cancer risk, possibly through an influence on estrogen metabolism.
Keywords: CA 125 antigen; adult; alcohol consumption; article; Asian; Black person; body mass; body weight; breast cancer; breast carcinoma; caloric intake; cancer incidence; cancer screening; Caucasian; cohort analysis; controlled study; diet; diet therapy; dietary questionnaire; estrogen metabolism; estrogen receptor positive breast cancer; estrogen related lifestyle score; estrogenic diet; family history; female; food frequency questionnaire; healthy lifestyle; Hispanic; human; lifestyle; lifestyle modification; liquid chromatography; major clinical study; menopause; obesity; ovariectomy; parity; physical activity; postmenopausal breast cancer; postmenopause; priority journal; questionnaire; risk factor; scoring system; sigmoidoscopy; smoking; tandem mass spectrometry

Evaluating the effectiveness of faith-based breast health education - Brown, M.T.; Cowart, L.W. (Health Education Journal, 2018)
Objective: In an effort to evaluate the effectiveness of faith-based health promotion programmes in educating African American women about breast cancer knowledge and risks, the local affiliate of a national breast cancer research foundation funded the Genesis Health Project (GHP) Network, a community-designed, culturally competent intervention, to develop, implement and evaluate the Breast Cancer Awareness and Education Program. This article reports on the faith-based education model used and uses evaluation data to determine whether the intervention improved awareness of breast cancer risk, methods for reducing risk, the importance of early detection and the availability of low-cost or free mammograms. Design: Pastoral health messaging and culturally appropriate strategies were used to heighten awareness of breast cancer risks and prevention, promote mammography and early detection, increase awareness of free/low-cost mammography and encourage the adoption of healthier behaviours. Setting: African American churches and collaborators targeting African American women in a mid-sized city in the northeastern USA. Method: Summative evaluations used paper and pencil pre- and post-event surveys, with measures for objectives targeted by the programme to evaluate the impact of activities. Results: Overall, participants in the Breast Cancer Awareness and Education Program showed improvements in general knowledge about breast cancer, higher breast cancer mortality among African American women, warning signs, risks and ways to mitigate risk, and the availability of low-cost or free mammograms. Conclusion: Findings confirm that faith-based health promotion programmes can be effective in helping to educate inner-city African American women about breast cancer and associated risk factors.
Keywords: adult; African American; aged; article; breast cancer; cancer mortality; community participation; cultural sensitivity; early cancer diagnosis; faith-based organization; female; health behavior; health care availability; health education; health promotion; human; male; mammography; priority journal; risk reduction; United States

Race-, Age-, and Gender-Based Characteristics and Toxicities of Targeted Therapies on Phase i Trials - Owonikoko, T.K.; Busari, A.K.; Kim, S.; Chen, Z.; Akintayo, A.; Lewis, C.; Carthon, B.C.; Alese, O.B.; El-Rayes, B.F.; Ramalingam, S.S.; Harvey, R.D. (Oncology (Switzerland), 2018)
Background: The impact of age-, gender-, and race-based differences on safety and efficacy in phase I clinical trials has not been well studied. Methods: We analyzed data from phase I clinical trials evaluating targeted biologic agents in patients with advanced solid malignancies. Race and gender distribution of enrolled patients was compared to the referral population demographics at the city, metro, and state levels. The association between age, gender, and race with type, frequency, and severity of treatment-emergent toxicities and clinical benefit was assessed using univariate and multivariable models. Results: Data from 117 eligible patients - Blacks/Caucasians/Others (27/85/5); male/female (66/51) - were obtained. Blacks were younger than Caucasian patients (median age of 56 vs. 62 years, p = 0.004). Nausea/vomiting was more frequent in female patients (43 vs. 24%, p = 0.03), while hematologic toxicity was more likely in Whites. While median time on treatment was comparable (113 vs. 91; p = 0.840), the median overall survival was significantly shorter for Blacks versus Caucasians (7.4 vs. 11.4 months; p = 0.0227). Black race (HR 2.11; 95% CI 1.24-3.60; p = 0.006) and older age (HR 1.03; 95% CI 1.00-1.06; p = 0.029) were associated with an increased risk of death. Conclusions: Age-, gender-, and race-based disparities were observed with specific toxicity and survival outcomes on phase I clinical trials of anticancer agents.
Keywords: NCT00406276; NCT00720148; NCT01183364; NCT01218555; NCT01529138; antineoplastic agent; axitinib; bortezomib; docetaxel; everolimus; ganetespib; lenalidomide; sunitinib; temsirolimus; adult; age; article; Black person; cancer survival; Caucasian; colorectal cancer; demography; disease severity; drug efficacy; drug safety; female; head and neck cancer; hematologic disease; human; kidney cancer; lung cancer; major clinical study; male; malignant neoplasm; middle aged; molecularly targeted therapy; mortality risk; nausea and vomiting; overall survival; pancreas cancer; phase 1 clinical trial (topic); priority journal; race difference; salivary gland cancer; sex difference; thyroid cancer; toxic hepatitis; treatment duration; United States; university hospital

Effect of exercise on metabolic syndrome in black women by family history and predicted risk of breast cancer: The FIERCE Study - Dash, C.; Taylor, T.R.; Makambi, K.H.; Hicks, J.; Hagberg, J.M.; Adams-Campbell, L.L. (Cancer, 2018)
Background: This study examined the effects of supervised and home-based exercise interventions on changes in metabolic syndrome (MetS) according to breast cancer risk (high vs low) in black women enrolled in the Focused Intervention on Exercise to Reduce Cancer (FIERCE) trial. Methods: Postmenopausal, obese, metabolically unhealthy black women, 45 to 65 years old, were randomized to supervised aerobic exercise (73 women), home-based walking-based exercise (69 women), or a control arm (71 women). Participants in the exercise arms underwent a 6-month intervention with study assessments conducted at the baseline and 6 months. The primary outcome measure was MetS (fasting glucose, waist circumference, blood pressure, serum triglycerides, and high-density lipoprotein [HDL]). The intervention effects on MetS, stratified by breast cancer risk as measured by the family history of breast cancer and model-based projected breast cancer risk, were examined with intent-to-treat analyses using generalized estimating equation models. Results: Among women with a family history of breast cancer, the exercise arms had lower mean MetS z scores, which suggested an improvement in the metabolic profile, than controls at 6 months (controls, + 0.55; home-based arm, –0.97, P <.01; supervised arm, –0.89, P <.01). Stratified analyses by projected breast cancer risk suggested similar but statistically nonsignificant findings, with those at high risk having more favorable changes in the MetS z score in the exercise arms versus the control arm. These changes were primarily attributable to changes in blood pressure, triglycerides, and HDL. Conclusions: Short-term aerobic activity regimens may improve the metabolic profile and thereby reduce breast cancer risk in obese, metabolically unhealthy black women at high risk for cancer. © 2018 American Cancer Society.
Keywords: glucose; high density lipoprotein; triacylglycerol; adult; aerobic exercise; aged; article; Black person; blood pressure; breast cancer; cancer risk; controlled study; exercise intensity; family history; female; glucose blood level; high risk population; human; lipoprotein blood level; low risk population; major clinical study; metabolic syndrome X; obesity; postmenopause; prediction; priority journal; randomized controlled trial; therapy effect; triacylglycerol blood level; waist circumference; walking

Disease and outcome disparities in multiple myeloma: Exploring the role of race/ethnicity in the Cooperative Group clinical trials - Ailawadhi, S.; Jacobus, S.; Sexton, R.; Stewart, A.K.; Dispenzieri, A.; Hussein, M.A.; Zonder, J.A.; Crowley, J.; Hoering, A.; Barlogie, B.; Orlowski, R.Z.; Rajkumar, S.V. (Blood Cancer Journal, 2018)
Multiple myeloma (MM) is an incurable hematologic malignancy with disparities in outcomes noted among racial-ethnic subgroups, likely due to disparities in access to effective treatment modalities. Clinical trials can provide access to evidence-based medicine but representation of minorities on therapeutic clinical trials has been dismal. We evaluated the impact of patient race-ethnicity in pooled data from nine large national cooperative group clinical trials in newly diagnosed MM. Among 2896 patients enrolled over more than two decades, only 18% were non-White and enrollment of minorities actually decreased in most recent years (2002-2011). African-Americans were younger and had more frequent poor-risk markers, including anemia and increased lactate dehydrogenase. Hispanics had the smallest proportion of patients on trials utilizing novel therapeutic agents. While adverse demographic (increased age) and clinical (performance status, stage, anemia, kidney dysfunction) factors were associated with inferior survival, patient race-ethnicity did not have an effect on objective response rates, progression-free, or overall survival. While there are significant disparities in MM incidence and outcomes among patients of different racial-ethnic groups, this disparity seems to be mitigated by access to appropriate therapeutic options, for example, as offered by clinical trials. Improved minority accrual in therapeutic clinical trials needs to be a priority.
Keywords: bortezomib; carmustine; cyclophosphamide; dexamethasone; interferon; lactate dehydrogenase; lenalidomide; melphalan; prednisone; thalidomide; vincristine; adult; African American; age; aged; anemia; article; cancer incidence; cancer staging; cancer survival; clinical evaluation; clinical outcome; clinical trial; cohort analysis; correlation analysis; demography; drug megadose; ethnic group; ethnicity; female; functional status; health disparity; Hispanic; human; kidney dysfunction; low drug dose; major clinical study; male; middle aged; multiple myeloma; overall survival; progression free survival; race; stem cell transplantation; whole body radiation

Modelling attrition and nonparticipation in a longitudinal study of prostate cancer - Spiers, S.; Oral, E.; Fontham, E.T.H.; Peters, E.S.; Mohler, J.L.; Bensen, J.T.; Brennan, C.S. (BMC medical research methodology, 2018)
BACKGROUND: Attrition occurs when a participant fails to respond to one or more study waves. The accumulation of attrition over several waves can lower the sample size and power and create a final sample that could differ in characteristics than those who drop out. The main reason to conduct a longitudinal study is to analyze repeated measures; research subjects who drop out cannot be replaced easily. Our group recently investigated factors affecting nonparticipation (refusal) in the first wave of a population-based study of prostate cancer. In this study we assess factors affecting attrition in the second wave of the same study. We compare factors affecting nonparticipation in the second wave to the ones affecting nonparticipation in the first wave. METHODS: Information available on participants in the first wave was used to model attrition. Different sources of attrition were investigated separately. The overall and race-stratified factors affecting attrition were assessed. Kaplan-Meier survival curve estimates were calculated to assess the impact of follow-up time on participation. RESULTS: High cancer aggressiveness was the main predictor of attrition due to death or frailty. Higher Charlson Comorbidity Index increased the odds of attrition due to death or frailty only in African Americans (AAs). Young age at diagnosis for AAs and low income for European Americans (EAs) were predictors for attrition due to lost to follow-up. High cancer aggressiveness for AAs, low income for EAs, and lower patient provider communication scores for EAs were predictors for attrition due to refusal. These predictors of nonparticipation were not the same as those in wave 1. For short follow-up time, the participation probability of EAs was higher than that of AAs. CONCLUSIONS: Predictors of attrition can vary depending on the attrition source. Examining overall attrition (combining all sources of attrition under one category) instead of distinguishing among its different sources should be avoided. The factors affecting attrition in one wave can be different in a later wave and should be studied separately.
Keywords: adult; African American; aged; Caucasian; ethnology; follow up; human; Kaplan Meier method; longitudinal study; male; middle aged; patient participation; prostate tumor; psychology; risk factor; statistical model; statistics and numerical data; United States

Recruiting and engaging African-American men in health research - Randolph, S.; Coakley, T.; Shears, J. (Nurse researcher, 2018)
BACKGROUND: Improving the health of black and minority ethnic (BME) men in the US continues to be a public health priority. Compared with men of other races and ethnicities, African-American men have higher rates of mortality and morbidity from chronic illness and diseases including cancer, heart disease, prostate cancer, diabetes and HIV/AIDS. One way to address these disparities is to include African-American men in health research, to elicit their perspectives on health risks and protective factors. These can then inform interventions aimed at reducing health disparities. However, challenges remain in recruiting and engaging African-American men in health research. AIM: To provide strategies for recruiting African-American men in health research, using as an exemplar a qualitative study of fathers' perspectives of sexual health promotion with young African-American males. DISCUSSION: Efforts are needed to increase the representation of African-American men in health research. Ensuring that researchers are aware of the cultural, social and environmental factors related to decisions to participate in research can lead to effective methods to recruit and engage them. CONCLUSION: There are several essential strategies for increasing African-American men's participation in health research: ensuring the research team is culturally and gender-sensitive; recruiting in trusted environments; using respected gatekeepers; developing trust with participants; and being transparent. IMPLICATIONS FOR PRACTICE: Implementing strategies to include African-American men in health research has the potential to improve health disparities in the US.
Keywords: adult; African American; aged; ethnic group; female; human; male; medical research; middle aged; minority group; patient selection; procedures; qualitative research; socioeconomics; statistics and numerical data; United States; very elderly

A Multi-Institutional Prospective Trial Confirms Noninvasive Blood Test Maintains Predictive Value in African American Men - Punnen, S.; Freedland, S.J.; Polascik, T.J.; Loeb, S.; Risk, M.C.; Savage, S.; Mathur, S.C.; Uchio, E.; Dong, Y.; Silberstein, J.L. (Journal of Urology, 2018)
Purpose: The 4Kscore® test accurately detects aggressive prostate cancer and reduces unnecessary biopsies. However, its performance in African American men has been unknown. We assessed test performance in a cohort of men with a large African American representation. Materials and Methods: Men referred for prostate biopsy at 8 Veterans Affairs medical centers were prospectively enrolled in the study. All men underwent phlebotomy for 4Kscore test assessment prior to prostate biopsy. The primary outcome was the detection of Grade Group 2 or higher cancer on biopsy. We assessed the discrimination, calibration and clinical usefulness of 4Kscore to predict Grade Group 2 or higher prostate cancer and compared it to a base model consisting of age, digital rectal examination and prostate specific antigen. Additionally, we compared test performance in African American and nonAfrican American men. Results: Of the 366 enrolled men 205 (56%) were African American and 131 (36%) had Grade Group 2 or higher prostate cancer. The 4Kscore test showed better discrimination (AUC 0.81 vs 0.74, p <0.01) and higher clinical usefulness on decision curve analysis than the base model. Test prediction closely approximated the observed risk of Grade Group 2 or higher prostate cancer. There was no difference in test performance in African American and nonAfrican American men (0.80 vs 0.84, p = 0.32), The test outperformed the base model in each group. Conclusions: The 4Kscore test accurately predicts aggressive prostate cancer for biopsy decision making in African American and nonAfrican American men.
Keywords: kallikrein; prostate specific antigen; 4Kscore test; African American; article; blood sampling; calibration; cancer diagnosis; cohort analysis; controlled study; diagnostic test accuracy study; digital rectal examination; human; human tissue; major clinical study; male; non invasive procedure; predictive value; priority journal; prospective study; prostate biopsy; prostate cancer; scoring system; task performance; tumor biopsy

PALINA: A phase II safety study of palbociclib in combination with letrozole or fulvestrant in African American women with hormone receptor positive HER2 negative advanced breast cancer - Lynce, F.; Saleh, M.; Shajahan-Haq, A.; Gallagher, C.; Dilawari, A.; Hahn, O.; Abu-Khalaf, M.; Cai, L.; Pohlmann, P.; Mohebtash, M.; Kamugisha, L.; Isaacs, C. (Contemporary Clinical Trials Communications, 2018)
Palbociclib has been shown to be a highly effective therapy in hormone receptor positive metastatic breast cancer when used in combination with letrozole or fulvestrant. Grade 3/4 neutropenia is a common side effect although febrile neutropenia is relatively uncommon. Insufficient data exist to describe the hematological safety of palbociclib in African American women (AAW) known to have a high incidence of benign ethnic neutropenia (BEN). PALOMA 1, 2 and 3, the initial phase II/III studies that led to the U.S. Food and Drug Administration (FDA) approval of palbociclib in metastatic breast cancer, only included participants with baseline absolute neutrophil count (ANC) of 1500/mm3 or higher. African American women (AAW) were underrepresented in the PALOMA trials and this may be partially explained by strict requirements for minimal ANC ≥1500/mm3. The ANC of 1500/mm3 for initiation of treatment in those with BEN has been previously challenged. In this study, we propose to lower the ANC cutoff for enrollment to 1000/mm3. PALINA (NCT02692755) is a phase II, single arm, multicenter clinical trial that will enroll 35 patients. The primary endpoint is to assess the proportion of patients who complete therapy without the development of febrile neutropenia or treatment discontinuation due to neutropenia. The secondary endpoints include number of patients who required dose delays or dose reductions in palbociclib attributed to neutropenia, rate of grade 3/4 neutropenia, clinical benefit rate at 24 weeks, the association between metabolite and exosomal signature with disease response and the association between baseline ANC prior to cancer diagnosis and the Duffy Null polymorphism (SNP rs2814778) with hematological safety. PALINA will provide important information about the hematologic safety of palbociclib in AAW with advanced breast cancer.
Keywords: NCT02692755; fulvestrant; letrozole; palbociclib; anemia; article; breast cancer; clinical article; drug dose reduction; drug safety; female; fever; human; human epidermal growth factor receptor 2 negative breast cancer; human epidermal growth factor receptor 2 positive breast cancer; infection; mass fragmentography; mass spectrometry; metabolomics; multicenter study; neutropenia; neutrophil count; phase 2 clinical trial; priority journal; thrombocytopenia; treatment duration; ultra performance liquid chromatography

Conducting a randomized trial in rural and urban safety-net health centers: Added value of community-based participatory research - Muthukrishnan, M.; Sutcliffe, S.; Hunleth, J.M.; Wang, J.S.; Colditz, G.A.; James, A.S. (Contemporary Clinical Trials Communications, 2018)
Background: Colorectal cancer (CRC) is the second most common cancer in the US. Despite evidence that screening reduces CRC incidence and mortality, screening rates are sub-optimal with disparities by race/ethnicity, income, and geography. Rural-urban differences in CRC screening are understudied even though approximately one-fifth of the US population lives in rural areas. This focus on urban populations limits the generalizability and dissemination potential of screening interventions. Methods: Using community-based participatory research (CBPR) principles, we designed a cluster-randomized trial, adaptable to a range of settings, including rural and urban health centers. We enrolled 483 participants across 11 health centers representing 2 separate networks. Both networks serve medically-underserved communities; however one is primarily rural and one primarily urban. Results: Our goal in this analysis is to describe baseline characteristics of participants and examine setting-level differences. CBPR was a critical for recruiting networks to the trial. Patient respondents were predominately female (61.3%), African-American (66.5%), and earned <$1200 per month (87.1%). The rural network sample was older; more likely to be female, white, disabled or retired, and have a higher income, but fewer years of education. Conclusions: Variation in the samples partly reflects the CBPR process and partly reflects inherent differences in the communities. This confirmed the importance of using CBPR when planning for eventual dissemination, as it enhanced our ability to work within diverse settings. These baseline findings indicate that using a uniform approach to implementing a trial or intervention across diverse settings might not be effective or efficient.
Keywords: adult; African American; aged; article; cancer screening; Caucasian; colonoscopy; colorectal cancer; disabled person; educational status; female; human; income; major clinical study; male; medically underserved; occult blood test; participatory research; pensioner; priority journal; randomized controlled trial (topic); rural health care; rural population; safety net hospital; sigmoidoscopy; urban health; urban population; urban rural difference

The early dissemination of patient navigation interventions: Results of a respondent-driven sample survey - Valverde, P.A.; Calhoun, E.; Esparza, A.; Wells, K.J.; Risendal, B.C. (Translational Behavioral Medicine, 2018)
Patient navigators (PNs) coordinate medical services and connect patients with resources to improve outcomes, satisfaction, and reduce costs. Little national information is available to inform workforce development. We analyzed 819 responses from an online PN survey conducted in 2009-2010. Study variables were mapped to the five Consolidated Framework for Implementation Research (CFIR) constructs to explore program variations by type of PN. Five logistic regression models compared each PN type to all others while adjusting for covariates. Thirty-five percent of respondents were nurse navigators, 28% lay navigators, 20% social work (SW)/counselor navigators, 7% allied health navigators, and 10% were "other" types of PNs. Most were non-Hispanic White (71%), female (94%), and at least college educated (70%). The primary differences were observed among: the core intervention tasks; position structure; work setting; health conditions navigated; navigator race/ethnicity; personal cancer experiences; navigation training; and patient populations served. Lay PNs had fewer odds of identifying as Hispanic, work in rural settings and assist underserved populations compared to others. Nurse navigators showed greater odds of clinical responsibilities, work in hospital or government settings and fewer odds of navigating minority populations compared to others. SW/counselor navigators also had additional duties, provided greater assistance to Medicare patient populations, and less odds of navigating underserved populations than others. In summary, our survey indicates that the type of PN utilized is an indicator of other substantial differences in program implementation. CFIR provides a robust method to compare differences and should incorporate care coordination outcomes in future PN research.
Keywords: adult; African American; article; Asian; breast cancer; cancer survivor; caregiver support; Caucasian; community participation; comparative study; cooperation; counseling; counselor; cross-sectional study; early intervention; educational status; English (language); ethnicity; female; government; health care disparity; health care organization; Hispanic; human; Human immunodeficiency virus infection; major clinical study; male; medically underserved; medicare; nurse; online system; paramedical personnel; patient care; peer group; personal experience; priority journal; responsibility; rural area; social work; social worker; treatment outcome; urban area; uterine cervix cancer; volunteer

A statewide program providing colorectal cancer screening to the uninsured of South Carolina - Eberth, J.M.; Thibault, A.; Caldwell, R.; Josey, M.J.; Qiang, B.; Peña, E.; LaFrance, D.; Berger, F.G. (Cancer, 2018)
BACKGROUND: Cancer screening rates are lowest in those without insurance or a regular provider. Since 2008, the Colorectal Cancer Prevention Network (CCPN) has provided open access colonoscopy to uninsured residents of South Carolina through established, statewide partnerships and patient navigation. Herein, we describe the structure, implementation, and clinical outcomes of this program. METHODS: The CCPN provides access to colonoscopy screening at no cost to uninsured, asymptomatic patients aged 50-64 years (African Americans age 45-64 years are eligible) who live at or below 150% of the poverty line and seek medical care in free medical clinics, federally qualified health centers, or hospital-based indigent practices in South Carolina. Screening is performed by board-certified gastroenterologists. Descriptive statistics and regression analysis are used to describe the population screened, and to assess compliance rates and colonoscopy quality metrics. RESULTS: Out of >4000 patients referred to the program, 1854 were deemed eligible, 1144 attended an in-person navigation visit, and 1030 completed a colonoscopy; 909 were included in the final sample. Nearly 90% of participants exhibited good-to-excellent bowel preparation. An overall cecal intubation rate of 99% was measured. The polyp detection rate and adenoma detection rate were 63% and 36%, respectively, with male sex and urban residence positively associated with adenoma detection. Over 13% of participants had an advanced polyp, and 1% had a cancer diagnosis or surgical intervention. CONCLUSION: The CCPN program is characterized by strong collaboration with clinicians statewide, low no-show rates, and high colonoscopy quality. Future work will assess the effectiveness of the navigation approach and will explore the mechanisms driving higher adenoma detection in urban participants. Cancer 2018;124:1912-20. © 2018 American Cancer Society.
Keywords: adult; advanced cancer; African American; article; cancer screening; certification; clinical outcome; clinical practice; colonoscopy; colorectal adenoma; colorectal cancer; colorectal polyp; digestive tract intubation; disease association; female; gastroenterologist; gender; health care planning; health care quality; health center; health program; help seeking behavior; human; intestine preparation; major clinical study; male; medically uninsured; middle aged; patient care; patient compliance; patient participation; patient referral; poverty; priority journal; South Carolina; urban population

Recruitment Techniques and Strategies in a Community-Based Colorectal Cancer Screening Study of Men and Women of African Ancestry - Davis, S.N.; Govindaraju, S.; Jackson, B.; Williams, K.R.; Christy, S.M.; Vadaparampil, S.T.; Quinn, G.P.; Shibata, D.; Roetzheim, R.; Meade, C.D.; Gwede, C.K. (Nursing research, 2018)
BACKGROUND: Recruiting ethnically diverse Black participants to an innovative, community-based research study to reduce colorectal cancer screening disparities requires multipronged recruitment techniques. OBJECTIVES: This article describes active, passive, and snowball recruitment techniques, and challenges and lessons learned in recruiting a diverse sample of Black participants. METHODS: For each of the three recruitment techniques, data were collected on strategies, enrollment efficiency (participants enrolled/participants evaluated), and reasons for ineligibility. RESULTS: Five hundred sixty individuals were evaluated, and 330 individuals were enrolled. Active recruitment yielded the highest number of enrolled participants, followed by passive and snowball. Snowball recruitment was the most efficient technique, with enrollment efficiency of 72.4%, followed by passive (58.1%) and active (55.7%) techniques. There were significant differences in gender, education, country of origin, health insurance, and having a regular physician by recruitment technique (p < .05). DISCUSSION: Multipronged recruitment techniques should be employed to increase reach, diversity, and study participation rates among Blacks. Although each recruitment technique had a variable enrollment efficiency, the use of multipronged recruitment techniques can lead to successful enrollment of diverse Blacks into cancer prevention and control interventions.
Keywords: African American; colorectal tumor; early cancer diagnosis; educational status; female; health insurance; human; male; middle aged; migrant; participatory research; patient selection; sex factor; United States

Challenges in recruiting African-American women for a breast cancer genetics study - Compadre, A.J.; Simonson, M.E.; Gray, K.; Runnells, G.; Kadlubar, S.; Zorn, K.K. (Hereditary Cancer in Clinical Practice, 2018)
Background: African-American women, especially in the southern United States, are underrepresented in cancer genetics research. A study was designed to address this issue by investigating the germline mutation rate in African-American women in Arkansas with a personal and/or family history of breast cancer. Women were tested for these mutations using a large panel of breast cancer susceptibility genes. In this analysis, we discuss the challenges encountered in recruiting African-American women from an existing biorepository to participate in this study. Methods: We attempted to contact 965 African-American women with a personal and/or family history of breast cancer who participated in Spit for the Cure (SFTC) between 2007 and 2013 and provided consent to be recontacted. The SFTC participants were invited by telephone and email to participate in the genetic study. Enrollment required completion of a phone interview to obtain a family and medical history and return of a signed consent form. Results: Among eligible SFTC participants, 39.6% (382/965) were able to be contacted with the phone numbers and email addresses they provided. Of these, 174 (45.5%) completed a phone interview and returned a signed consent form. Others were not able to be contacted (n=583), declined to participate (n=57), did not keep phone interview appointments (n=82), completed the phone interview but never returned a signed consent (n=54), were deceased (n=13), or were too confused to consent to participate (n=2). Conclusions: Recruiting African-American women into our breast cancer genetics study proved challenging primarily due to difficulty establishing contact with potential participants. Given their prior participation in breast cancer research, we anticipated that this would be a highly motivated population. Indeed, when we were able to contact SFTC participants, only 14.9% declined to participate in our study. Innovative communication, retention, and recruitment strategies are needed in future studies to address the recruitment challenges we faced.
Keywords: adult; African American; aged; Arkansas; article; biobank; breast cancer; cancer genetics; family history; female; genetic analysis; germline mutation; human; human experiment; informed consent; interview; medical history; patient participation; United States

The effect of a randomized controlled physical activity trial on health related quality of life in metabolically unhealthy African-American women: FIERCE STUDY - Taylor, T.R.; Dash, C.; Sheppard, V.; Makambi, K.; Ma, X.; Adams-Campbell, L.L. (Contemporary Clinical Trials, 2018)
Purpose: African-American women (AAW) are more likely to be metabolically unhealthy than White women (WW). Metabolic syndrome (MetS) is associated with increased breast cancer risk and mortality from breast cancer is greater in AAW compared to WW. Data show MetS affects health-related quality of life (HRQoL). Exercise studies report improvements in MetS, however, no study to date has examined HRQoL in metabolically unhealthy AAW enrolled in an exercise trial. Methods: This report examined the effect of a 6-month, 3-arm (supervised exercise, home-based exercise, control) randomized exercise controlled trial on HRQoL among 213 obese, metabolically unhealthy, postmenopausal AAW at high risk for breast cancer. Results: Certain baseline participant characteristics were related to baseline HRQoL dimensions. The “exercise group” (supervised group combined with the home-based group) showed significantly greater improvement in health change scores (M = 13.6, SD = 3.1) compared to the control group (M = 0.7, SD = 4.4) (p = 0.02) over the 6-month study period. There were no significant differences in HRQoL change scores between the 3 study groups, however, although non-significant, data indicated most HRQoL change scores were more favorable in the supervised group. Conclusion: While significant improvement occurred in health change scores in the combined supervised and home-based group compared to the control group, we did not observe any significant differences on HRQoL change scores between all three study groups. However, while non-significant, there was a trend for more favorable HRQoL change scores in the supervised group versus the home-based and control groups. Additional research is needed to further explore this topic.
Keywords: adult; aerobic exercise; African American; article; breast cancer; cancer mortality; cancer risk; comparative study; controlled study; exercise intensity; female; high risk patient; human; major clinical study; metabolic syndrome X; middle aged; physical activity; postmenopause; quality of life; randomized controlled trial; Short Form 36; social interaction; Theory of Planned Behavior

Men's Eating and Living (MEAL) study (CALGB 70807 [Alliance]): recruitment feasibility and baseline demographics of a randomized trial of diet in men on active surveillance for prostate cancer - Parsons, J.K.; Pierce, J.P.; Mohler, J.; Paskett, E.; Jung, S.-H.; Morris, M.J.; Small, E.; Hahn, O.; Humphrey, P.; Taylor, J.; Marshall, J. (BJU International, 2018)
Objective: To assess the feasibility of performing national, randomized trials of dietary interventions for localized prostate cancer. Methods: The Men's Eating and Living (MEAL) study (CALGB 70807 [Alliance]) is a phase III clinical trial testing the efficacy of a high-vegetable diet to prevent progression in patients with prostate cancer on active surveillance (AS). Participants were randomized to a validated diet counselling intervention or to a control condition. Chi-squared and Kruskal–Wallis analyses were used to assess between-group differences at baseline. Results: Between 2011 and 2015, 478 (103%) of a targeted 464 patients were randomized at 91 study sites. At baseline, the mean (sd) age was 64 (6) years and mean (sd) PSA concentration was 4.9 (2.1) ng/mL. Fifty-six (12%) participants were African-American, 17 (4%) were Hispanic/Latino, and 16 (3%) were Asian-American. There were no significant between-group differences for age (P = 0.98), race/ethnicity (P = 0.52), geographic region (P = 0.60), time since prostate cancer diagnosis (P = 0.85), PSA concentration (P = 0.96), clinical stage (T1c or T2a; P = 0.27), or Gleason sum (Gleason 6 or 3+4 = 7; P = 0.76). In a pre-planned analysis, the baseline prostate biopsy samples of the first 50 participants underwent central pathology review to confirm eligibility, with an expectation that <10% would become ineligible. One of 50 participants (2%) became ineligible. Conclusion: The MEAL study shows the feasibility of implementing national, multi-institutional phase III clinical trials of diet for prostate cancer and of testing interventions to prevent disease progression in AS.
Keywords: NCT01238172; adult; African American; age; aged; article; Asian American; cancer control; cancer diagnosis; cancer epidemiology; cancer growth; cancer localization; cancer screening; cancer staging; clinical effectiveness; controlled study; demography; diet therapy; ethnicity; feasibility study; geographic distribution; Gleason score; Hispanic; histopathology; human; human tissue; major clinical study; male; multicenter study; patient counseling; phase 3 clinical trial; priority journal; prostate biopsy; prostate cancer; race; randomized controlled trial; validity; vegetable

High baseline anal human papillomavirus and abnormal anal cytology in a phase 3 trial of the quadrivalent human papillomavirus vaccine in human immunodeficiency virus-infected individuals older than 26 years: ACTG 5298 - Cranston, R.D.; Cespedes, M.S.; Paczuski, P.; Yang, M.; Coombs, R.W.; Dragavon, J.; Saah, A.; Godfrey, C.; Webster-Cyriaque, J.Y.; Chiao, E.Y.; Bastow, B.; Wilkin, T. (Sexually Transmitted Diseases, 2018)
Background The quadrivalent human papillomavirus (HPV) vaccine (qHPV; types 6, 11, 16, 18) is indicated for men and women aged 9 to 26 years to prevent HPV associated anogenital high-grade squamous intraepithelial lesions (HSIL) and cancer. ACTG 5298 was a randomized placebo controlled Phase 3 study in human immunodeficiency virus (HIV)-infected men who have sex with men, and women of qHPV to prevent persistent anal HPV infection. Baseline data are presented here. Methods Human immunodeficiency virus-infected men who have sex with men, and women 27 years or older without previous anogenital or oral cancer were enrolled. Baseline anal cytology, high-resolution anoscopy and collection of anal, oral, and vaginal specimens for HPV genotyping were performed and acceptability assessed. Results Five hundred seventy-five (575) participants were enrolled (82% men and 18% women). Median age was 47 years. Race/ethnicity was 46% white, 31% black, and 20% Hispanic. Plasma HIV-1 RNA was less than 50 copies/mL in 83% and median CD4 T count was 602 cells/μL. Abnormal anal cytology was detected in 62%, with corresponding HSIL on biopsy (bHSIL) in 33%. Anal HPV 6, 11, 16, and 18 were detected in 25%, 13%, 32%, and 18% of the participants, respectively. Prevalence of 0, 1, 2, 3, and 4 qHPV types was 40%, 38%, 17%, 4%, and 1%, respectively. Oral infection with 1 or more qHPV type was detected in 10% of the participants. Study procedures were generally acceptable. Conclusions At study baseline, there was a high prevalence of abnormal anal cytology, bHSIL, and HPV infection. Sixty percent of the participants had anal infection with preventable qHPV types.
Keywords: NCT01461096; antiretrovirus agent; placebo; virus RNA; Wart virus vaccine; adult; anus cancer; article; cancer screening; CD4 lymphocyte count; controlled study; cytology; disease marker; double blind procedure; female; genital tract cancer; genotype; human; Human immunodeficiency virus infection; Human papillomavirus type 11; Human papillomavirus type 16; Human papillomavirus type 18; Human papillomavirus type 6; human tissue; major clinical study; male; men who have sex with men and women; middle aged; mouth cancer; mouth infection; multicenter study; oral biopsy; persistent infection; phase 3 clinical trial; prevalence; randomized controlled trial; serology; virus detection; Wart virus

Prevalence and Predictors of Low Serum 25-Hydroxyvitamin D among Female African-American Breast Cancer Survivors - Sheean, P.; Arroyo, C.; Woo, J.; Schiffer, L.; Stolley, M. (Journal of the Academy of Nutrition and Dietetics, 2018)
BACKGROUND: African-American breast cancer survivors commonly demonstrate low serum 25-hydroxyvitamin D (25(OH)D). Decreased cutaneous conversion, high levels of adiposity, and even breast cancer treatment may influence vitamin D status. Previous investigations have analyzed African-American women in aggregate with other breast cancer survivors and have not comprehensively addressed these influential factors. OBJECTIVES: To determine the prevalence of low serum 25(OH)D in an exclusively African-American cohort of female breast cancer survivors with overweight/obesity and to evaluate the role of ultraviolet (UV) light exposure, body composition, and dietary sources of vitamin D on serum 25(OH)D levels. DESIGN: Cross-sectional. PARTICIPANTS: Pre- and postmenopausal African-American breast cancer survivors (n=244) were recruited from various neighborhoods in the city of Chicago, IL, between September 2011 and September 2014 for a larger weight loss trial. MAIN OUTCOME MEASURES: Demographic, clinical, anthropometric (body mass index [calculated as kg/m2], waist circumference, and hip circumference), blood specimen, dietary intake (food frequency questionnaire), and sun behavior data were collected by trained study personnel before trial participation. Dual-energy x-ray absorptiometry was used to quantify adiposity (total, percentage, regional, visceral) and lean mass. Serum 25(OH)D was used as the biomarker reflective of vitamin D status. STATISTICAL ANALYSES: Mean (±standard deviation), frequencies, and multivariate linear regression modeling. RESULTS: The average participant was 57.4 years old (±10.0), 6.9 years (±5.2) from initial breast cancer diagnosis with a body mass index of 36.2 (±6.2). The majority of participants (60%) reported habitual oral vitamin D supplementation with mean intake of 327 IU (±169). Vitamin D deficiency was prevalent in 81% and 43%, when the cut points of the Endocrine Society (<30 ng/mL or <75 nmol/L) and the Institute of Medicine (<20 ng/mL or <50 nmol/L) were applied, respectively. A multivariate model adjusting for age, seasonality of blood draw, total energy intake, use of supplemental vitamin D, darker skin pigmentation, breast cancer stage, and waist-to-hip ratio was able to explain 28.8% of the observed variance in serum 25(OH)D concentrations. No significant associations were detected for body mass index or any dual-energy x-ray absorptiometry measures of body composition. CONCLUSIONS: Considering the number of women who endorsed use of vitamin D supplementation, the prevalence of vitamin D deficiency among these African-American breast cancer survivors was high. Vitamin D supplementation, sun behavior, and waist-to-hip ratio may serve as future points of intervention to improve the vitamin D status of this minority survivor population.
Keywords: 25 hydroxyvitamin D; vitamin D; adult; African American; blood; breast tumor; cancer survivor; complication; cross-sectional study; dietary supplement; female; human; Illinois; middle aged; nutritional status; prevalence; vitamin D deficiency

Racial Disparity in Delivering Definitive Therapy for Intermediate/High-risk Localized Prostate Cancer: The Impact of Facility Features and Socioeconomic Characteristics - Friedlander, D.F.; Trinh, Q.-D.; Krasnova, A.; Lipsitz, S.R.; Sun, M.; Nguyen, P.L.; Kibel, A.S.; Choueiri, T.K.; Weissman, J.S.; Menon, M.; Abdollah, F. (European Urology, 2018)
Background: The gap in prostate cancer (PCa) survival between Blacks and Whites has widened over the past decade. Investigators hypothesize that this disparity may be partially attributable to differences in rates of definitive therapy between races. Objective: To examine facility level variation in the use of definitive therapy among Black and White men for localized PCa. Design, setting, and participants: Using data from the National Cancer Data Base, we identified 223 873 White and 59 262 Black men ≥40 yr of age receiving care within the USA with biopsy confirmed localized intermediate/high-risk PCa diagnosed between January 2004 and December 2013. Outcome measurements and statistical analysis: Multilevel logistic regression was fitted to predict the odds of receiving definitive therapy for PCa. Sensitivity and subgroup analyses were performed to adjust for inherent patient and facility-level differences when appropriate. Results and limitations: Eighty-three percent (n = 185 647) of White men received definitive therapy compared with 74% (n = 43 662) of Black men between 2004 and 2013. Overall rates of definitive therapy during that time increased for both White (81% vs 83%, p < 0.001) and Black (73% vs 75%, p = 0.001) men. However, 39% of treating facilities demonstrated significantly higher rates of definitive therapy in White men, compared with just 1% favoring Black men. Our study is limited by potential selection bias and effect modification. Conclusions: After adjusting for sociodemographic and clinical factors, we found that most facilities favored definitive therapy in Whites. Health care providers should be aware of these inherit biases when counseling patients on treatment options for localized PCa. Our study is limited by the retrospective nature of the cohort. Patient summary: We found significant differences in rates of radiation and surgical treatment for prostate cancer among White and Black men, with most facilities favoring Whites. Nonclinical factors such as treatment facility type and location influenced rates of therapy. We show that significant variation in rates of definitive therapy for intermediate/high-risk localized prostate cancer exists between White and Black men. This nonclinical variation represents a potential target for quality of care initiatives recently launched by US health care agencies.
Keywords: adult; aged; article; Black person; cancer localization; cancer patient; cancer risk; cancer staging; cancer therapy; Caucasian; Charlson Comorbidity Index; Charlson Deyo Comorbidity Index; cohort analysis; Gleason score; health care delivery; health care disparity; high risk patient; highest income group; human; human tissue; insurance; intermediate risk patient; major clinical study; male; medicare; middle aged; outcome assessment; patient selection; priority journal; prostate adenocarcinoma; prostate biopsy; race difference; reference database; social status; tumor biopsy

Barriers to non-small cell lung cancer trial eligibility - Hardesty, J.J.; Kanarek, N.F. (Contemporary Clinical Trials Communications, 2018)
Introduction Cancer clinical trial (CCT) enrollment is low potentially threatening the generalizability of trial results and expedited regulatory approvals. We assessed whether type of initial patient appointment for non-small cell lung cancer (NSCLC) is associated with CCT eligibility. Methods Using a patient-to-accrual framework, we conducted a quasi-retrospective cohort pilot study at Sidney Kimmel Comprehensive Cancer Center (SKCCC), Baltimore, Maryland. 153 NSCLC patients new to SKCCC were categorized based on type of initial appointment: patients diagnosed or treated and patients seen for a consultation. CCT eligibility was determined by comparing eligibility criteria for each open trial to the electronic medical record (EMR) of each patient at every office visit occurring within 6-months of initial visit. Results We found no association between type of initial appointment and CCT eligibility (OR, 1.15; 95% CI, 0.49–2.73). Analyses did suggest current smokers were less likely to be eligible for trials compared to never smokers (OR, 0.15; 95% CI, 0.03–0.64), and stage 4 patients with second line therapy or greater were more likely to be eligible than stage 1 or 2 patients (OR, 5.18; 95% CI, 1.08–24.75). Additional analyses suggested most current smokers and stage 1 or 2 patients had trials available but were still ineligible. Conclusions SKCCC has a diverse portfolio of trials available for NSCLC patients and should consider research strategies to re-examine eligibility criteria for future trials to ensure increased enrollment of current smokers and stage 1 or 2 patients. We could not confirm whether type of initial visit was related to eligibility.
Keywords: adult; African American; aged; article; cancer patient; cancer staging; clinical trial (topic); cohort analysis; female; human; major clinical study; male; middle aged; non small cell lung cancer; open study; outcome assessment; pilot study; priority journal; race; retrospective study; smoking

Updates on Uterine Artery Embolization - Kohi, M.P.; Spies, J.B. (Seminars in Interventional Radiology, 2018)
Uterine fibroids (leiomyomas) are the most common benign neoplasm of the female pelvis and have a lifetime prevalence exceeding 80% among African American women and approaching 70% among Caucasian women. Approximately 50% of women with fibroids experience symptoms which may include menorrhagia that may result in anemia, bulk symptoms with bladder and bowel dysfunction and abdominal protrusion, dysmenorrhea, and infertility. Hysterectomy remains the most common treatment option for fibroids and concerns have been raised about the overuse of this procedure. Uterine artery embolization (UAE) is now a well-established uterine preserving and minimally invasive therapy for symptomatic fibroids. Since its introduction, strong evidence for safety and efficacy of UAE has been generated with low rates of complications. This review will discuss UAE for the management of symptomatic uterine fibroids with special focus on emerging technical approaches and novel periprocedural patient care.
Keywords: NCT02884960; intrauterine contraceptive device; gonadorelin agonist; lidocaine; steroid; adenomyosis; amenorrhea; analgesia; article; blood vessel injury; clinical outcome; disability severity; female fertility; femoral artery; human; hypogastric nerve; infection; leiomyosarcoma; lung embolism; medical device complication; minimally invasive procedure; myomectomy; nuclear magnetic resonance imaging; pain; patient care; patient safety; patient satisfaction; patient selection; postmenopause; pregnancy; preoperative treatment; priority journal; septicemia; therapy effect; tumor vascularization; urinary tract infection; uterine artery embolization; uterus myoma; vagina discharge; vascular access

Sistas inspiring sistas through activity and support (SISTAS): Study design and demographics of participants - Bevel, M.; Babatunde, O.A.; Heiney, S.P.; Brandt, H.M.; Wirth, M.D.; Hurley, T.G.; Khan, S.; Johnson, H.; Wineglass, C.M.; Warren, T.Y.; Angela Murphy, E.; Sercy, E.; et al. (Ethnicity and Disease, 2018)
Introduction: Recruiting racial, ethnic, and other underserved minorities into conventional clinic-based and other trials is known to be challenging. The Sistas Inspiring Sistas Through Activity and Support (SISTAS) Program was a one-year randomized controlled trial (RCT) to promote physical activity and healthy eating among AA women in SC to reduce inflammatory biomarkers, which are linked to increased breast cancer (BrCa) risk and mortality. This study describes the development, recruitment, and implementation of the SISTAS clinical trial and provides baseline characteristics of the study participants. Methods: SISTAS was developed using community-based participatory research (CBPR) approaches. At baseline, study participants completed assessments and underwent clinical measurements and blood draws to measure C-reactive protein (CRP) and interleukin-6 (IL-6). Participants randomized to the intervention received 12 weekly classes followed by nine monthly booster sessions. Post-intervention measurements were assessed at 12-week and 12-month follow-ups. Results: We recruited a total of 337 women who tended to: be middle-aged (mean age 48.2 years); have some college education; be employed full-time; have Medicare as their primary insurance; be non-smokers; and perceive their personal health as good. On average, the women were pre-hypertensive at baseline (mean systolic blood pressure = 133.9 mm Hg; mean diastolic blood pressure = 84.0 mm Hg) and morbidly obese (mean BMI >40.0 kg/m2); the mean fat mass and fat-free mass among participants were 106.4 lb and 121.0 lb, respectively. Conclusion: The SISTAS RCT addresses some of the gaps in the literature with respect to CBPR interventions targeting AA women, such as implementing diet and physical activity in CBPR-based studies to decrease BrCa risk.
Keywords: C reactive protein; interleukin 6; adult; African American; article; controlled study; diastolic blood pressure; educational status; fat free mass; female; follow up; full time employment; health program; human; major clinical study; medicare; middle aged; participatory research; physical activity; Sistas Inspiring Sistas Through Activity and Support Program; smoking; South Carolina; systolic blood pressure; urban area

Speed of processing training in middle-aged and older breast cancer survivors (SOAR): results of a randomized controlled pilot - Meneses, K.; Benz, R.; Bail, J.R.; Vo, J.B.; Triebel, K.; Fazeli, P.; Frank, J.; Vance, D.E. (Breast Cancer Research and Treatment, 2018)
Purpose: Cognitive changes are common among breast cancer survivors. There is limited evidence to guide management of cognitive changes. This randomized controlled pilot evaluated the preliminary efficacy of a speed of processing (SOP) training among middle-aged and older breast cancer survivors. Methods: Sixty breast cancer survivors with self-reported cognitive changes were recruited to the SOAR study. Participants were randomized to either a home-based SOP training (n = 30) or no-contact control group (n = 30). Primary outcomes were SOP (Useful Field of View Test®), and executive function (NIH Toolbox Cognition Battery). Neuropsychological assessments were completed at baseline, 6 weeks, and 6 months post study entry. Data were analyzed using repeated measures t tests, analysis of covariance, and sensitivity analyses. Results: SOP training resulted in improvement in objective measures of SOP and executive function. Immediate (6 week) posttest and 6-month follow-up demonstrated large SOP training effects over time. Large representation of African American women (51.2%) and 96% retention in the SOAR study add to study strengths. Conclusion: Home-based SOP training shows promise for remediating cognitive changes following breast cancer treatment, particularly improved SOP, and executive function.
Keywords: adult; African American; article; breast cancer; cancer survivor; clinical effectiveness; cognition; cognitive defect; cognitive therapy; controlled study; executive function; female; follow up; general condition improvement; geography; home care; human; major clinical study; middle aged; neuropsychological test; outcome assessment; pilot study; pretest posttest design; priority journal; randomized controlled trial; self report; speed of processing training

Designing a randomized controlled trial to evaluate a community-based narrative intervention for improving colorectal cancer screening for African Americans - Ellis, E.M.; Erwin, D.O.; Jandorf, L.; Saad-Harfouche, F.; Sriphanlop, P.; Clark, N.; Dauphin, C.; Johnson, D.; Klasko-Foster, L.B.; Martinez, C.; Sly, J.; White, D.; et al. (Contemporary Clinical Trials, 2018)
Objective To describe the methodology of a 2-arm randomized controlled trial that compared the effects of a narrative and didactic version of the Witness CARES (Community Awareness, Reach, & Empowerment for Screening) intervention on colorectal cancer screening behavior among African Americans, as well as the cognitive and affective determinants of screening. Methods Witness CARES targeted cognitive and affective predictors of screening using a culturally competent, community-based, narrative or didactic communication approach. New and existing community partners were recruited in two New York sites. Group randomization allocated programs to the narrative or didactic arm. Five phases of data collection were conducted: baseline, post-intervention, three-month, six-month, and qualitative interviews. The primary outcome was screening behavior; secondary outcomes included cognitive and affective determinants of screening. Results A total of 183 programs were conducted for 2655 attendees. Of these attendees, 19.4% (N = 516) across 158 programs (50% narrative; 50% didactic) were study-eligible and consented to participate. Half (45.6%) of the programs were delivered to new community partners and 34.8% were delivered at faith-based organizations. Mean age of the total sample was 64.7 years and 75.4% were female. Conclusion The planned number of programs was delivered, but the proportion of study-eligible attendees was lower than predicted. This community-based participatory research approach was largely successful in involving the community served in the development and implementation of the intervention and study.
Keywords: adult; African American; article; cancer screening; colorectal cancer; community; controlled study; female; follow up; human; interpersonal communication; major clinical study; male; middle aged; narrative; randomized controlled trial

Feasibility of the mobile mindfulness-based stress reduction for breast cancer (mMBSR(BC)) program for symptom improvement among breast cancer survivors - Lengacher, C.A.; Reich, R.R.; Ramesar, S.; Alinat, C.B.; Moscoso, M.; Cousin, L.; Marino, V.R.; Elias, M.N.; Paterson, C.L.; Pleasant, M.L.; Rodriguez, C.S.; Wang, H.-L.; et al. (Psycho-Oncology, 2018)
Objective: The purpose of this pilot study was to test the feasibility of delivering the mobile mindfulness-based stress reduction for breast cancer (mMBSR(BC)) program using an iPad and to evaluate its impact on symptom improvement. Methods: A single group, pre-posttest design was implemented among female stages 0-III breast cancer survivors (BCS) who completed treatment. Data were collected at baseline and week 6 on measures of psychological and physical symptoms and quality of life. The mMBSR(BC) program is a standardized, stress-reducing intervention that combines sitting and walking meditation, body scan, and yoga and is designed to deliver weekly 2-hour sessions for 6 weeks using an iPad. Results: The mean age of the 15 enrolled BCS was 57 years; one participant was non-Hispanic black, and 14 were non-Hispanic white. Of the 13 who completed the study, there were significant improvements from baseline to 6 weeks post-mMBSR(BC) in psychological and physical symptoms of depression, state anxiety, stress, fear of recurrence, sleep quality, fatigue, and quality of life (P's <.05). Effect sizes for improvements of multiple symptoms ranged from medium to large. Conclusions: These results provide preliminary support that the mMBSR(BC) program may be feasible and acceptable, showing a clinical impact on decreasing psychological and physical symptoms. This mobile-based program offers a delivery of a standardized MBSR(BC) intervention to BCS that is convenient for their own schedule while decreasing symptom burden in the survivorship phase after treatment for breast cancer.
Keywords: tablet computer; mobile phone; adult; anxiety disorder; article; breast cancer; cancer pain; cancer survivor; clinical article; cognition; controlled study; depression; fatigue; fear; feasibility study; female; human; meditation; mindfulness; mobile application; outcome assessment; patient compliance; quality of life; randomized controlled trial; sleep quality; physiological stress; stress management; walking; yoga; iPad

Biospecimen donation among black and white breast cancer survivors: opportunities to promote precision medicine - Sheppard, V.B.; Hurtado-de-Mendoza, A.; Zheng, Y.-L.; Wang, Y.; Graves, K.D.; Lobo, T.; Xu, H.; Jennings, Y.; Tolsma, D.; Trout, M.; Robinson, B.E.; McKinnon, B.; et al. (Journal of cancer survivorship : research and practice, 2018)
PURPOSE: Advances in precision medicine (PM) have potential to reduce and/or eliminate breast cancer disparities in both treatment and survivorship. However, compared to white Americans, black Americans are often underrepresented in genetic research. This report assessed factors that influence receipt of buccal cells via saliva kits. METHODS: This prospective study recruited women with confirmed hormonal-positive (HR+) breast cancer (BC). A standardized telephone survey collected sociodemographic, socio-cultural (e.g., religiosity), and healthcare process factors. Clinical information was abstracted from medical records. After the baseline survey, return postage-paid envelopes and mouthwash collection kits were mailed. Univariate and adjusted logistic regression models estimated the probability of biospecimen donation. RESULTS: Seventy percent of the sample provided buccal cells which were of good quality. No differences were noted by race or other demographic factors. In the multivariable logistic model, time spent with providers (OR 1.61 per 1-point increase; 95% CI 1.242, 2.088) and religiosity (OR 0.957 per 1-point increase; 95% CI 0.931, 0.984) remained associated with biospecimen provision. Women with lower-stage cancer (vs. higher stage III+) were more likely to donate biospecimens (p < 0.05). CONCLUSIONS: Cancer care experiences predicted specimen donation. Understanding the contextual reasons for lower receipt among women with higher religiosity scores and higher stage warrants further examination. IMPLICATIONS FOR CANCER SURVIVORS: PM is relevant to cancer survivors because of its potential to inform targeted therapies, understand disease resistance, and aide in prediction of toxicity and/or recurrence. Future efforts to launch precision medicine trials with BC survivors may benefit from engaging medical oncologists and/or leveraging patient-provider encounters for trial participation.
Keywords: adult; African American; aged; biobank; breast tumor; cancer survivor; Caucasian; ethnology; female; human; middle aged; mortality; pathology; personalized medicine; procedures; specimen handling; standards; statistics and numerical data; very elderly

Feasibility Test of a Community-Relevant Intervention Designed to Promote African American Participation in Translational, Breast Cancer Disparities Research: Know About Health Options for Women (Know HOW) - Yeary, K.H.-C.K.; Moore, P.; Turner, J.; Dawson, L.; Heo, S.; Greene, P. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2018)
There are marked racial differences in breast cancer, the second leading cause of death among US women. Understanding the causes of these differences is essential to eliminate breast cancer inequities. More prevalent in African American than in Caucasian women, metabolic syndrome has been associated with breast cancer outcomes. Further research is needed to understand metabolic syndrome's role in breast cancer disparities, thus novel strategies to increase minority participation in research are important. We embedded two approaches (comprehensive, focused) to increase African American participation in breast cancer research in a state-wide service program and pilot tested both approaches in rural African American women. We conducted three comprehensive and three focused outreach programs (n = 48) and assessed research participation through consent and actual provision of data for four types of data: survey, anthropometric, blood, and mammography records. The majority of participants provided written consent for all data collection procedures (96 % survey; 92 % anthropometric; 94 %, blood; 100 % mammography). There were no between group differences in consent rates. There was variation in the overall proportion of participants who provided data (96 % survey; 92 % anthropometric; 73 % blood; 40 % mammography). Women in the comprehensive approach were less likely to return for a scheduled mammogram than women in the focused approach (19 % vs 64 %, p = 0.0236). Both outreach programs promoted African American engagement in research. Differences in the provision of data by type may have been due to participant burden (i.e., time required to provide data). Study designs that embed research in service programs have promise to increase minority research participation.
Keywords: adult; African American; aged; attitude to health; breast tumor; ethnology; feasibility study; female; health disparity; health promotion; human; mammography; medical research; middle aged; minority group; patient selection; questionnaire; rural population; statistics and numerical data; United States

Patient-reported Adherence to Adjuvant Aromatase Inhibitor Therapy Using the Morisky Medication Adherence Scale: An Evaluation of Predictors - Kesmodel, S.B.; Goloubeva, O.G.; Rosenblatt, P.Y.; Heiss, B.; Bellavance, E.C.; Chumsri, S.; Bao, T.; Thompson, J.; Nightingale, G.; Tait, N.S.; Nichols, E.M.; Feigenberg, S.J.; et al. (American Journal of Clinical Oncology: Cancer Clinical Trials, 2018)
Objectives: Endocrine therapy is part of standard adjuvant therapy for patients with hormone receptor-positive breast cancer and has been shown to improve recurrence-free and overall survival. However, adherence to endocrine therapy is suboptimal and is difficult to measure. In this study we evaluate the feasibility of using the Morisky Medication Adherence Scale (MMAS) to assess patient adherence to aromatase inhibitor (AI) therapy. Methods: Patients with stage 1 to 3, hormone receptor-positive breast cancer receiving adjuvant AI therapy were prospectively enrolled on an Institutional Review Board approved protocol. The MMAS questionnaire was administered to each patient and adherence was measured. Information on duration of AI therapy, patient and tumor characteristics, and treatment was collected. A multivariable logit model approach was utilized to evaluate potential barriers to adherence. Results: Between 2011 and 2014, 100 patients were enrolled. The distribution of adherence levels was 13% low, 37% medium, and 50% high. High adherence was reported more frequently in white women (58%), patients with stage 2 and 3 disease (54%), and patients who did not receive chemotherapy (62%). Multivariable analysis demonstrated that higher adherence was more likely in white women compared with African American women (estimated odds ratio=2.8). Conclusions: Using the MMAS, only 50% of women with stage 1 to 3 breast cancer reported high adherence to AI therapy, consistent with other reports showing suboptimal adherence to adjuvant endocrine therapy. The MMAS allows for the rapid assessment of adherence to oral adjuvant endocrine therapy and is valuable in a busy clinical setting.
Keywords: aromatase inhibitor; adjuvant therapy; adult; African American; aged; article; breast cancer; cancer adjuvant therapy; cancer patient; Caucasian; clinical trial; early cancer; female; human; major clinical study; medication compliance; Morisky Medication Adherence Scale; patient-reported outcome; postmenopause; prospective study; questionnaire

Educational Colonoscopy Video Enhances Bowel Preparation Quality and Comprehension in an Inner City Population - Pillai, A.; Menon, R.; Oustecky, D.; Ahmad, A. (Journal of Clinical Gastroenterology, 2018)
Background: Quality of bowel preparation and patient knowledge remains a major barrier for completing colorectal cancer screening. Few studies have tested unique ways to impact patient understanding centering on interactive computer programs, pictures, and brochures. Two studies explored instructional videos but focused on patient compliance and anxiety as endpoints. Furthermore, excessive video length and content may limit their impact on a broad patient population. No study so far has studied a video's impact on preparation quality and patient understanding of the colonoscopy procedure. Methods: We conducted a single blinded prospective study of inner city patients presenting for a first time screening colonoscopy. During their initial visit patients were randomized to watch an instructional colonoscopy video or a video discussing gastroesophageal reflux disease (GERD). All patients watched a 6 minutes long video with the same spokesperson, completed a demographic questionnaire (Supplemental Digital Content 1, http://links.lww.com/JCG/A352) and were enrolled only if screened within 30 days of their visit. On the day of the colonoscopy, patients completed a 14 question quiz of their knowledge. Blinded endoscopist graded patient preparations based on the Ottawa scale. All authors had access to the study data and reviewed and approved the final manuscript. Results: Among the 104 subjects enrolled in the study, 56 were in the colonoscopy video group, 48 were in GERD video group, and 12 were excluded. Overall, 48% were male and 52% female; 90% of patients had less than a high school education, 76% were African American, and 67% used a 4 L split-dose preparation. There were no differences between either video group with regard to any of the above categories. Comparisons between the 2 groups revealed that the colonoscopy video group had significantly better Ottawa bowel preparation score (4.77 vs. 6.85; P=0.01) than the GERD video group. The colonoscopy video group also had less-inadequate repeat bowel preparations versus the GERD video group (9% vs. 23%; P<0.01). The overall score on the knowledge questionnaire (Supplemental Digital Content 1, http://links.lww.com/JCG/A352) was significantly higher in the colonoscopy video group as compared with the GERD video group (12.77 vs. 11.08; P<0.001. In all patients the overall quiz score positively correlated with preparation quality (odds ratio, 2.31; confidence interval, 1.35-3.94; P<0.001). Conclusions: Our unique population represented an overwhelmingly under-educated (85% had a high school education or less) and minority group (76% African American). They are one of the most at risk of having multiple barriers such as comprehension and reading difficulties resulting in poor preparation examinations and no shows to procedures. Our instructional video proved to be high yield in this population. The patients assigned to watch the colonoscopy video showed a significant increase in "excellent" grade adequate bowel preparation quality by >23% and a significant decrease in "inadequate" bowel preparations by almost 50%. Our study proves that an educational video can improve both comprehension with regard to all aspects of colonoscopy. ClinicalTrials.gov number, NCT02906969.
Keywords: NCT02906969; bicarbonate plus bisacodyl plus macrogol 3350 plus potassium chloride plus sodium chloride; adult; African American; anxiety; article; cancer screening; colonoscopy; comparative study; comprehension; controlled clinical trial; controlled study; digestive system disease assessment; educational status; endoscopist; evening dosage; female; gastroesophageal reflux; high school; human; intestine preparation; knowledge; major clinical study; male; morning dosage; Ottawa bowel preparation score; patient compliance; patient education; priority journal; scoring system; single blind procedure; urban population; videorecording; halflytely

Strategic recruitment of an ethnically diverse cohort of overweight survivors of breast cancer with lymphedema - Sturgeon, K.M.; Hackley, R.; Fornash, A.; Dean, L.T.; Laudermilk, M.; Brown, J.C.; Sarwer, D.B.; DeMichele, A.M.; Troxel, A.B.; Schmitz, K.H. (Cancer, 2018)
BACKGROUND: Black women are more likely to experience adverse effects from cancer treatment such as lymphedema. Thus, black women may particularly benefit from research regarding interventions to improve lymphedema. Herein, the authors report the challenges and strategies related to the recruitment of minority survivors of breast cancer and to the recruitment of survivors of breast cancer with lymphedema into the Women In Steady Exercise Research (WISER) Survivor Clinical Trial. METHODS: Subjects for this community-based trial were recruited from the Philadelphia area through active (mailings) and passive (printed materials and Web site) recruitment strategies. In addition, education sessions coordinated through partner hospitals in communities with a predominantly minority population were conducted to increase awareness of lymphedema in survivors of breast cancer. Women who were interested in the study were screened for lymphedema via telephone questionnaire and invited to see a study-related certified lymphedema therapist to confirm the presence of lymphedema. RESULTS: Screening was conducted among 2295 women: 628 were eligible, 450 consented, and 351 were randomized. Minority women comprised 38% of the study population. Letters to women on state and hospital registries resulted in a 0.4% randomization rate; education sessions yielded a 10% randomization rate. The authors observed that approximately 23.6% of the study sample had no previous diagnosis of lymphedema. CONCLUSIONS: The WISER Survivor Clinical Trial faced multiple recruitment challenges and used unique strategies to successfully enroll minority survivors of breast cancer into a lifestyle intervention. Cancer 2018;124:95-104. © 2017 American Cancer Society.
Keywords: telephone; adult; aged; article; breast cancer; cancer patient; cancer survivor; cohort analysis; community; controlled study; ethnicity; exercise; female; hospital; human; Internet; lifestyle modification; lymphedema; major clinical study; middle aged; obesity; patient education; Pennsylvania; physiotherapist; priority journal; questionnaire; randomization; randomized controlled trial; register; research subject; screening test; body weight loss

Genome-wide meta-analyses identifies novel taxane-induced peripheral neuropathy-associated loci - Sucheston-Campbell, L.E.; Clay-Gilmour, A.I.; Barlow, W.E.; Budd, G.T.; Stram, D.O.; Haiman, C.A.; Sheng, X.; Yan, L.; Zirpoli, G.; Yao, S.; Jiang, C.; Owzar, K.; et al. (Pharmacogenetics and Genomics, 2018)
Objective Taxane containing chemotherapy extends survival for breast cancer patients. However, taxane-induced peripheral neuropathy (TIPN) cannot be predicted, prevented or effectively treated. Using genome-wide analyses, we sought to identify common risk variants for TIPN. Patients and methods Women with high-risk breast cancer enrolled in SWOG 0221 were genotyped using the Illumina 1M chip. Genome-wide analyses were performed in relation to ≥grade 3 Common Terminology Criteria for Adverse Events (CTCAE) neuropathy in European and African Americans. Data were meta-analyzed with GW associations of CTCAE ≥grade 3 versus <grade 3 in CALGB 40101 assuming a fixed effects model. Results The percentage of ≥grade 3 TIPN in 1269 European Americans and 139 African Americans in S0221, was 11.6 and 22.3%, respectively. CALGB 40101 ≥grade 3 TOPN was 7.2%. The most significant association with ≥grade 3 TIPN was the G allele of rs1858826 in GNGT1 (P meta =1.1×10 -7), which showed a decrease in risk of ≥grade 3 TIPN (odds ratio=0.29, 95% confidence interval: 0.18-0.46). Conclusion The genetic variants associated with ≥grade 3 TIPN are hypothesized to have biochemical functions and reside in and near genes involved in diabetes and diabetic neuropathy. This finding is consistent with results from CALGB 40101 pathway analyses. Larger homogeneous trials with similar dosing and criteria for defining neuropathy are needed to properly assess the relationship of genomics with the neuropathy spectrum.
Keywords: NCT00041119; cyclophosphamide; doxorubicin; fibroblast growth factor receptor 4; paclitaxel; pegfilgrastim; African American; article; breast cancer; cancer combination chemotherapy; cancer risk; cancer staging; coding; European American; gene frequency; gene function; gene linkage disequilibrium; gene locus; genetic heterogeneity; genetic susceptibility; genetic variability; genome-wide association study; human; major clinical study; paclitaxel induced peripheral neuropathy; peripheral neuropathy; pharmacogenetics; priority journal; single nucleotide polymorphism

Assessment of lymph node metastasis in elderly patients with colorectal cancer by sentinel lymph node identification using carbon nanoparticles - Sun, J.; Zhang, J. (Journal of B.U.ON., 2018)
Purpose: To evaluate the value of sentinel lymph node (SLN) identification using carbon nanoparticles in abdominal lymph node metastasis in elderly (>60 years old) patients with colorectal cancer. Methods: Eighty patients admitted at Weihai Second Municipal Hospital affiliated to Qingdao University from November 2014 to February 2017 were selected and divided into the control group (n=40) and the observation group (n=40) using the random number method. The control group was treated with surgery, while the observation group was administered carbon nanoparticle tracer for intraoperative dye detection and positioning; the first to four black-stained lymph nodes were marked as SLN, then radical surgery for colorectal cancer was performed. Pathological examination of intraoperative specimens was performed to assess the effect of SLN in the abdominal lymph node metastasis. Results: There were no statistically significant differences in the metastasis rate and lymph node metastasis rate between the two groups (p>0.05). The total number of lymph nodes and the number of lymph nodes with micrometastases (<2mm) in the observation group were larger than those in the control group (p<0.05); the ratio of fewer than 12 lymph nodes in the observation group was lower than that in the control group (p<0.05). In the observation group, 8 out of 40 cases had lymph node metastasis, the detection rate of SLN using carbon nanoparticles was 92.50%, the accuracy rate 94.59%, the specificity of diagnosis 87.50%, the false negative rate 12.50% and the negative predictive value 21.88%. There was no statistically significant difference in the metastasis rate of black-stained and non-black-stained lymph nodes in the observation group (p>0.05). The blackstained rate of micro lymph nodes was higher than the total black-stained rate (p<0.05); the rate of micro lymph node metastasis was lower than that of lymph node metastasis >5mm (p<0.05). Conclusion: Preoperative SLN examination can evaluate the abdominal lymph node status in elderly patients with colorectal cancer, which is simple and accurate and can guide the clinical treatment, so it is worthy of popularization and application.
Keywords: carbon nanoparticle; abdomen; adult; aged; aging; article; cancer patient; cancer size; cancer surgery; colorectal cancer; controlled study; diagnostic accuracy; diagnostic test accuracy study; female; hospital admission; human; human tissue; intraoperative period; lymph node dissection; lymph node metastasis; major clinical study; male; micrometastasis; middle aged; observational study; pathophysiology; patient selection; predictive value; radical resection; sensitivity and specificity; sentinel lymph node; sentinel lymph node biopsy; staining; university hospital

Improving the accrual of racial and ethnic minority patients in clinical trials: Time to raise the stakes - Ibraheem, A.; Polite, B. (Cancer, 2017)
Keywords: advanced cancer; article; Asian; basal like breast cancer; Black person; breast cancer; cancer diagnosis; cancer incidence; cancer mortality; Caucasian; clinical trial (topic); colon cancer; ethnic group; gender; health care disparity; Hispanic; human; mortality rate; outcome assessment; Pacific Islander; patient attitude; patient participation; patient preference; priority journal; prostate cancer; quality of life; social status; study design; triple negative breast cancer

Partnering around cancer clinical trials (PACCT): Study protocol for a randomized trial of a patient and physician communication intervention to increase minority accrual to prostate cancer clinical trials - Eggly, S.; Hamel, L.M.; Heath, E.; Manning, M.A.; Albrecht, T.L.; Barton, E.; Wojda, M.; Foster, T.; Carducci, M.; Lansey, D.; Wang, T.; Abdallah, R.; et al. (BMC Cancer, 2017)
Background: Cancer clinical trials are essential for testing new treatments and represent state-of-the-art cancer treatment, but only a small percentage of patients ever enroll in a trial. Under-enrollment is an even greater problem among minorities, particularly African Americans, representing a racial/ethnic disparity in cancer care. One understudied cause is patient-physician communication, which is often of poor quality during clinical interactions between African-American patients and non-African-American physicians. Partnering Around Cancer Clinical Trials (PACCT) involves a transdisciplinary theoretical model proposing that patient and physician individual attitudes and beliefs and their interpersonal communication during racially discordant clinical interactions influence outcomes related to patients' decisions to participate in a trial. The overall goal of the study is to test a multilevel intervention designed to increase rates at which African-American and White men with prostate cancer make an informed decision to participate in a clinical trial. Methods/design: Data collection will occur at two NCI-designated comprehensive cancer centers. Participants include physicians who treat men with prostate cancer and their African-American and White patients who are potentially eligible for a clinical trial. The study uses two distinct research designs to evaluate the effects of two behavioral interventions, one focused on patients and the other on physicians. The primary goal is to increase the number of patients who decide to enroll in a trial; secondary goals include increasing rates of physician trial offers, improving the quality of patient-physician communication during video recorded clinical interactions in which trials may be discussed, improving patients' understanding of trials offered, and increasing the number of patients who actually enroll. Aims are to 1) determine the independent and combined effects of the two interventions on outcomes; 2) compare the effects of the interventions on African-American versus White men; and 3) examine the extent to which patient-physician communication mediates the effect of the interventions on the outcomes. Discussion: PACCT has the potential to identify ways to increase clinical trial rates in a diverse patient population. The research can also improve access to high quality clinical care for African American men bearing the disproportionate burden of disparities in prostate and other cancers. Trial registration: Clinical Trials.gov registration number: NCT02906241(September 8, 2016).
Keywords: NCT02906241; African American; article; cancer center; Caucasian; clinical protocol; doctor patient relationship; health disparity; human; information processing; prostate cancer; randomized controlled trial (topic); videorecording

Comparative Effectiveness Research: The Impact of Biologic Agents in Ethnic Minorities With Metastatic Colorectal Cancer - Goel, S.; Negassa, A.; Khot, A.; Goyal, D.; Guo, S.; Nandikolla, A.; Bakirhan, K.; Polineni, R.; Shah, U.; Chaudhary, I.; Ghalib, M.H.; Rajdev, L.; et al. (Clinical Colorectal Cancer, 2017)
Micro-Abstract The survival advantage of biologic agents for patients treated for metastatic colorectal cancer was generated from trials from a predominantly white population. We carried out a comparative effectiveness research study in our center that caters to an ethnic minority population. Using a robust multi variable analysis we demonstrate that black and Hispanic patients do not enjoy a similar benefit. Background Biologic agents have improved the outcomes of patients with metastatic colorectal cancer (mCRC). However, the clinical trials included a predominately white population (85%), with Hispanic and black patients underrepresented. Thus, the real world benefit for the latter remains unknown. Comparative effectiveness research is a tool allowing for this exploration. Patients and Methods The demographic and clinical characteristics of patients treated for mCRC from 2000 to 2011 were extracted from the medical records of Montefiore Medical Center. A semiparametric accelerated failure time model was used to assess the survival differences between patients receiving chemotherapy (CT) alone versus CT plus biologic agents (CBT). Results Of the 290 patients (black, 45.9%; Hispanic, 26.2%; and white, 27.9%), 53.8% received biologic agents. The median overall survival was 15.2 months in the CT-alone group and 25.6 months in CBT group (P =.004). On univariate analysis, a lower number of metastatic sites, carcinoembryonic antigen < 41 ng/mL, and more lines of CT were associated with improved overall survival. In a propensity score-based analysis of the entire cohort, CBT offered a survival benefit compared with CT alone (increased median survival, 1.44-fold; 95% confidence interval [CI], 1.11-1.86; P =.038). The results of the subgroup analysis suggested a survival benefit for white patients (2.01; 95% CI, 1.26-3.23; P =.031) but not for Hispanic (1.42; 95% CI, 0.91-2.20; P =.370) or black (1.12; 95% CI, 0.76-1.66; P =.596) patients. Conclusion In the present cohort, CBT was associated with longer survival, with the effect mainly driven by the outcomes for white patients, with black patients not appearing to benefit. These data are provocative and warrant further confirmation. Efforts to increase ethnic minority patients' enrollment in clinical trials is required to prospectively define the benefit from novel therapies.
Keywords: antineoplastic agent; bevacizumab; carcinoembryonic antigen; cetuximab; panitumumab; adult; African American; article; cancer chemotherapy; cancer registry; cancer survival; Caucasian; clinical outcome; comparative effectiveness; controlled study; ethnic group; female; health care disparity; Hispanic; human; major clinical study; male; metastatic colorectal cancer; outcome assessment; overall survival; propensity score; secondary analysis

Addressing Patient Emotional and Existential Needs During Serious Illness: Results of the Outlook Randomized Controlled Trial - Steinhauser, K.E.; Alexander, S.; Olsen, M.K.; Stechuchak, K.M.; Zervakis, J.; Ammarell, N.; Byock, I.; Tulsky, J.A. (Journal of Pain and Symptom Management, 2017)
Context Few interventions exist to address patients' existential needs. Objectives Determine whether an intervention to address seriously ill patients' existential concerns improves preparation, completion (elements of quality of life [QOL] at end of life), and reduces anxiety and depression. Methods A randomized controlled trial comparing outlook intervention, relaxation meditation (RM), and usual care (UC). Measures included primary—a validated measure of QOL at the end of life and secondary—Functional Assessment of Cancer Therapy—General, anxiety (Profile of Mood States), depression (Center for Epidemiological Studies—Depression Scale), and spiritual well-being (Functional Assessment of Chronic Illness Therapy—Spiritual Well-Being). Qualitative interviews assessed outlook intervention acceptability. Enrolled patients were nonhospice eligible veterans with advanced cancer, congestive heart failure, chronic obstructive pulmonary disease, end-stage renal disease, or end-stage liver disease. Results Patients (n = 221) were randomly assigned 1:1:1 to outlook, RM, and UC. Patients were 96% males, 46% with cancer, 58.4% married, and 43.9% of African American origin. Compared with UC, outlook participants had higher preparation (a validated measure of QOL at the end of life) (mean difference 1.1; 95% CI 0.2, 2.0; P = 0.02) and mean completion (1.6; 95% CI 0.05, 3.1; P = 0.04) at the first but not second postassessment. Compared with RM, outlook participants did not show significant differences over time. Exploratory analyses indicated that in subgroups with cancer and low sense of peace, outlook participants had improved preparation at first and not second postassessment, as compared with UC (mean difference 1.4; 95% CI 0.03, 2.7; P = 0.04) (mean difference = 1.8; 95% CI 0.3, 3.3; P = 0.02), respectively. Conclusion Outlook had an impact on social well-being and preparation compared with UC. The lack of impact on anxiety and depression differs from previous results among hospice patients. Results suggest that outlook is not demonstratively effective in populations not experiencing existential or emotional distress.
Keywords: advanced cancer; aged; anxiety; article; chronic obstructive lung disease; congestive heart failure; controlled study; coping behavior; depression; emotion; end stage liver disease; end stage renal disease; exploratory research; female; follow up; general aspects of disease; human; interview; major clinical study; male; malignant neoplasm; marriage; metastasis; qualitative analysis; quality of life; randomized controlled trial; social status; wellbeing

Comparative transcriptome profiling reveals coding and noncoding RNA differences in NSCLC from African Americans and European Americans - Mitchell, K.A.; Zingone, A.; Toulabi, L.; Boeckelman, J.; Ryan, B.M. (Clinical Cancer Research, 2017)
Purpose: To determine whether racial differences in gene and miRNA expression translates to differences in lung tumor biology with clinical relevance in African Americans (AAs) and European Americans (EAs). Experimental Design: The NCI-Maryland Case Control Study includes seven Baltimore City hospitals and is overrepresented with AA patients (∼40%). Patients that underwent curative NSCLC surgery between 1998 and 2014 were enrolled. Comparative molecular profiling used mRNA (n = 22 AAs and 19 EAs) and miRNA (n = 42 AAs and 55 EAs) expression arrays to track differences in paired fresh frozen normal tissues and lung tumor specimens from AAs and EAs. Pathway enrichment, predicted drug response, tumor microenvironment infiltration, cancer immunotherapy antigen profiling, and miRNA target enrichment were assessed. Results: AA-enriched differential gene expression was characterized by stem cell and invasion pathways. Differential gene expression in lung tumors from EAs was primarily characterized by cell proliferation pathways. Population-specific gene expression was partly driven by population-specific miRNA expression profiles. Drug susceptibility predictions revealed a strong inverse correlation between AA resistance and EA sensitivity to the same panel of drugs. Statistically significant differences in M1 and M2 macrophage infiltration were observed in AAs (P < 0.05); however, PD-L1, PD-L2 expression was similar between both. Conclusions: Comparative transcriptomic profiling revealed clear differences in lung tumor biology between AAs and EAs. Increased participation by AAs in lung cancer clinical trials are needed to integrate, and leverage, transcriptomic differences with other clinical information to maximize therapeutic benefit in both AAs and EAs.
Keywords: biperiden; bisoprolol; bromocriptine; budesonide; canadine; chelidonine; diphenhydramine; fenoprofen; fluphenazine; hexestrol; irinotecan; microRNA; mimosine; minaprine; monensin; mycophenolic acid; nalbuphine; nilutamide; prednisolone; primaquine; prostaglandin E2; proxyphylline; sertaconazole; staurosporine; succinylsulfathiazole; sulfaguanidine; sulindac sulfone; transcriptome; unindexed drug; untranslated RNA; adult; African American; article; cancer immunotherapy; cancer staging; case control study; cell proliferation; cohort analysis; comparative study; controlled study; drug sensitivity; European American; female; gene expression; gene expression profiling; human; lung tumor; macrophage; major clinical study; male; non small cell lung cancer; priority journal; race difference; sensitivity analysis; tumor microenvironment

Can Women Facilitate Men's Prostate Cancer Screening Informed Decision-Making? The M-PACT Trial - Holt, C.L.; Le, D.; Slade, J.L.; Muwwakkil, B.; Saunders, D.R.; Williams, R.; Atkinson, N.L.; Naslund, M. (Journal of health communication, 2017)
The M-PACT study compared an all-male with a mixed-sex intervention to increase informed decision-making for prostate cancer screening among African-American men in church settings. We recruited 262 men in 18 churches randomized to the two intervention approaches. Trained and certified lay peer community health advisors in each church led a series of four men's health workshops on informed decision-making for prostate cancer screening. African-American male workshop participants completed baseline, post-workshop, and 12-month follow-up surveys. Contrary to our expectations, including women in the workshops did not result in increased intervention efficacy for the informed decision-making outcomes as both groups showed significant improvement over time in several study outcomes including stage of decision-making for prostate cancer screening, preference for role in decision-making, prostate cancer knowledge, and self-reports of prostate specific antigen testing. Finally, men who attended multiple workshops had better informed decision-making outcomes on several indicators. The current findings suggest mixed results from including women in this men's health educational intervention. Future work should consider optimal ways of providing family support for African-American men's health promotion.
Keywords: African American; aged; controlled study; decision making; early cancer diagnosis; ethnology; faith-based organization; female; follow up; health promotion; human; human relation; male; middle aged; procedures; program evaluation; prostate tumor; psychology; randomized controlled trial; statistics and numerical data; utilization

Patient and Physician Factors Associated with Undisclosed Prostate Cancer Screening in a Sample of Predominantly Immigrant Black Men - Lepore, S.J.; Nair, R.G.; Davis, S.N.; Wolf, R.L.; Basch, C.E.; Thomas, N.; Shmukler, C.; Ullman, R. (Journal of immigrant and minority health, 2017)
Medical guidelines do not recommend prostate cancer screening, particularly without informed and shared decision making. This study investigates undisclosed opportunistic screening using prostate specific antigen (PSA) testing in black immigrant and African American men. Participants (N = 142) were insured urban men, 45- to 70-years old. Patients' reports of testing were compared with medical claims to assess undisclosed PSA testing. Most (94.4 %) men preferred to share in screening decisions, but few (46.5 %) were aware PSA testing was performed. Four factors predicted being unaware of testing: low formal education, low knowledge about prostate cancer, no intention to screen, and no physician recommendation (all p's < .05). Undisclosed PSA testing was common. Both patient and provider factors increased risk of being uninformed about prostate cancer screening. Interventions combining patient education and physician engagement in shared decision making may better align practice with current prostate cancer screening guidelines.
Keywords: prostate specific antigen; African American; aged; attitude to health; decision making; early cancer diagnosis; ethnology; human; male; middle aged; migrant; patient participation; procedures; prostate tumor; socioeconomics; statistics and numerical data

African American Women's Perspectives on Donating Healthy Breast Tissue for Research: Implications for Recruitment - Ridley-Merriweather, K.E.; Head, K.J. (Health communication, 2017)
African American women die of breast cancer at a higher rate than any other racial group. The Komen Tissue Bank (KTB) is an ongoing clinical trial that collects healthy breast tissue from women of all racial groups to use as controls in research and represents a critical tool in efforts to treat and prevent breast cancer; however, African Americans display reticence toward donating breast tissue to the KTB. Through the lens of the Integrated Behavioral Model, this study recruited African American women to share their perspectives on donating breast tissue for research purposes. Seventy-one (N = 71) eligible Black women who were previous tissue donors to the KTB responded to an online questionnaire. Findings revealed that (a) participants had positive instrumental attitudes or reasons for donating; (b) participants felt generally supported in their decision to donate, but revealed that the lack of Black women participating in the KTB meant that they themselves were setting the norm for others; and (c) their race was an important element in their donation decision. While acknowledging the negative history of African Americans in medical research, they offered their perceptions regarding the importance of involving themselves in medical research, and suggested that health communication strategies to recruit African Americans into research should embrace race as part of the message. The findings from this study have important implications for other those who work in applied clinical settings and are interested in addressing racial disparities in medical research through more effective and targeted recruitment messaging.
Keywords: African American; breast; breast tumor; donor; ethnology; female; human; Internet; patient selection; psychology; qualitative research; questionnaire

Recommendation of colorectal cancer testing among primary care patients younger than 50 with elevated risk - Skinner, C.S.; Ahn, C.; Halm, E.A.; Bishop, W.P.; McCallister, K.; Sanders, J.M.; Farrell, D.; Santini, N.; Singal, A.G. (Preventive Medicine, 2017)
In the era of precision medicine, efforts are needed to identify and tailor screening recommendations among elevated-risk patients. Individuals younger than 50 years are an important target population, as they comprise 15% of colorectal (CRC) cases and often present with more advanced disease than their 50 + counterparts. In this large study, 2470 patients ages 25–49 used a tablet-based program that assessed risks, matched risks with screening guidelines, and generated tailored printed guideline-concordant recommendations for patients and their providers. The tablet-based program identified 121 (4.9%) patients with risk factors warranting screening before age 50. Likelihood of risk warranting screening was greater for ages 40–49 than < 40 years (OR: 2.38), females than males (OR: 1.82), and African Americans (OR: 1.69) and non-Hispanic Whites (OR: 2.89) compared to Hispanics. Most common risk factors were family history of polyps (23.1%), personal history of inflammatory bowel disease (19.8%), and combined family history of CRC + polyps (18.2%). Receipt of guideline-concordant screening within 6 months of identification was low, including only 5.3% of those who needed colonoscopy and 13.3% for whom colonoscopy or FIT was recommended. Although elevated-risk patients younger than 50 years can be readily identified, more than notification is necessary to facilitate screening participation.
Keywords: adult; African American; age; article; cancer risk; cancer screening; Caucasian; colon polyp; colonoscopy; colorectal cancer; ethnic difference; family history; female; high risk patient; Hispanic; human; inflammatory bowel disease; major clinical study; male; medical history; mobile application; patient identification; patient participation; practice guideline; primary medical care; priority journal; risk assessment; sex ratio

Patient Navigation for Colonoscopy Completion: Results of an RCT - DeGroff, A.; Schroy, P.C.; Morrissey, K.G.; Slotman, B.; Rohan, E.A.; Bethel, J.; Murillo, J.; Ren, W.; Niwa, S.; Leadbetter, S.; Joseph, D. (American Journal of Preventive Medicine, 2017)
Introduction Colorectal cancer is a leading cause of cancer-related death in the U.S. Although screening reduces colorectal cancer incidence and mortality, screening rates among U.S. adults remain less than optimal, especially among disadvantaged populations. This study examined the efficacy of patient navigation to increase colonoscopy screening. Study design RCT. Setting/participants A total of 843 low-income adults, primarily Hispanic and non-Hispanic blacks, aged 50–75 years referred for colonoscopy at Boston Medical Center were randomized into the intervention (n=429) or control (n=427) groups. Participants were enrolled between September 2012 and December 2014, with analysis following through 2015. Intervention Two bilingual lay navigators provided individualized education and support to reduce patient barriers and facilitate colonoscopy completion. The intervention was delivered largely by telephone. Main outcome measure Colonoscopy completion within 6 months of study enrollment. Results Colonoscopy completion was significantly higher for navigated patients (61.1%) than control group patients receiving usual care (53.2%, p=0.021). Based on regression analysis, the odds of completing a colonoscopy for navigated patients was one and a half times greater than for controls (95% CI=1.12, 2.03, p=0.007). There were no differences between navigated and control groups in regard to adequacy of bowel preparation (95.3% vs 97.3%, respectively). Conclusions Navigation significantly improved colonoscopy screening completion among a racially diverse, low-income population. Results contribute to mounting evidence demonstrating the efficacy of patient navigation in increasing colorectal cancer screening. Screening can be further enhanced when navigation is combined with other evidence-based practices implemented in healthcare systems and the community.
Keywords: adult; aged; article; Black person; cancer screening; colonoscopy; colorectal cancer; controlled study; female; Hispanic; human; individualization; lowest income group; major clinical study; male; patient care; patient education; patient referral; randomized controlled trial; support group; teleconsultation; telephone

Community-Based, Preclinical Patient Navigation for Colorectal Cancer Screening Among Older Black Men Recruited From Barbershops: The MISTER B Trial - Cole, H.; Thompson, H.S.; White, M.; Browne, R.; Trinh-Shevrin, C.; Braithwaite, S.; Fiscella, K.; Boutin-Foster, C.; Ravenell, J. (American journal of public health, 2017)
OBJECTIVES: To test the effectiveness of a preclinical, telephone-based patient navigation intervention to encourage colorectal cancer (CRC) screening among older Black men. METHODS: We conducted a 3-parallel-arm, randomized trial among 731 self-identified Black men recruited at barbershops between 2010 and 2013 in New York City. Participants had to be aged 50 years or older, not be up-to-date on CRC screening, have uncontrolled high blood pressure, and have a working telephone. We randomized participants to 1 of 3 groups: (1) patient navigation by a community health worker for CRC screening (PN), (2) motivational interviewing for blood pressure control by a trained counselor (MINT), or (3) both interventions (PLUS). We assessed CRC screening completion at 6-month follow-up. RESULTS: Intent-to-treat analysis revealed that participants in the navigation interventions were significantly more likely than those in the MINT-only group to be screened for CRC during the 6-month study period (17.5% of participants in PN, 17.8% in PLUS, 8.4% in MINT; P < .01). CONCLUSIONS: Telephone-based preclinical patient navigation has the potential to be effective for older Black men. Our results indicate the importance of community-based health interventions for improving health among minority men.
Keywords: African American; aged; attitude to health; colorectal tumor; community care; controlled study; early cancer diagnosis; ethnology; hairdresser; health care disparity; human; male; middle aged; New York; patient care; procedures; psychology; randomized controlled trial

Comparing Asian American Women's Knowledge, Self-Efficacy, and Perceived Risk of Heart Attack to Other Racial and Ethnic Groups: The mPED Trial - Fukuoka, Y.; Lisha, N.E.; Vittinghoff, E. (Journal of women's health (2002), 2017)
RESULTS: Asian/Pacific Islander women had significantly lower total scores for knowledge of heart attack and self-efficacy for heart attack recognition and care seeking behavior compared to the Caucasian women (p = 0.001 and p = 0.002, respectively). However, perceived risk did not differ among the groups. Forty-six percent of the Asian American women, compared to 25% of Caucasian women, falsely believed "breast cancer is the number one cause of death for women (p = 0.002)." In addition, Asian/Pacific Islander women were less likely to report "arm pain, numbness, tingling, or radiating" as one of the heart attack symptoms compared to the Caucasian and the multiracial group (34%, 63% [p < 0.001], and 66% [p = 0.004], respectively). OBJECTIVE: The aim of the study was to compare knowledge and awareness of heart attacks/heart disease and perceived risk for future heart attack in Asian/Pacific Islander women, compared to other racial and ethnic groups. MATERIALS AND METHODS: In this cross-sectional study, 318 women enrolled in a mobile phone-based physical activity education trial were analyzed. Heart attack knowledge, self-efficacy for recognizing and responding to heart attack symptoms, and perceived risk for a future heart attack were measured. Analyses were conducted using logistic, proportional odds, and linear regression models, depending on the outcome and adjusting for age. Pairwise differences between Asian/Pacific Islanders and the other four groups were assessed using a Bonferroni correction (p < 0.0125). CONCLUSIONS: These findings highlight the urgent need to develop effective, tailored campaigns to close the knowledge gap between Asian/Pacific Islander women and Caucasian women.
Keywords: adult; African American; Asian American; attitude to health; California; Caucasian; controlled study; cross-sectional study; cultural factor; epidemiology; ethnic group; ethnology; female; health survey; heart disease; heart infarction; Hispanic; human; middle aged; patient attitude; psychology; randomized controlled trial; risk factor; self concept; statistics and numerical data

Racial Variation in Patient-Reported Outcomes Following Treatment for Localized Prostate Cancer: Results from the CEASAR Study - Tyson, M.D.; Alvarez, J.; Koyama, T.; Hoffman, K.E.; Resnick, M.J.; Wu, X.-C.; Cooperberg, M.R.; Goodman, M.; Greenfield, S.; Hamilton, A.S.; Hashibe, M.; Paddock, L.E.; et al. (European Urology, 2017)
Background Relatively little is known about the relationship between race/ethnicity and patient-reported outcomes after contemporary treatments for localized prostate cancer. Objective To test the hypothesis that treatment-related changes in urinary, bowel, sexual, and hormonal function vary by race/ethnicity. Design, setting, and participants The Comparative Effectiveness Analysis of Surgery and Radiation (CEASAR) study is a prospective, population-based, observational study that enrolled 3708 men diagnosed with localized prostate cancer in 2011–2012. Outcome measurements and statistical analysis Patient-reported disease-specific function was measured using the 26-item Expanded Prostate Index Composite (EPIC) at baseline and 6 and 12 mo after enrollment. Mean treatment differences in function were compared by race using risk-adjusted generalized estimating equations. Results and limitations While all race/ethnic groups reported considerable declines in scores for urinary incontinence after radical prostatectomy (RP) when compared to active surveillance, African-American men reported a greater difference than white men did (adjusted difference-in-differences 8.4 points, 95% confidence interval 2.0–14.8; p = 0.01). No difference in bother scores was noted and the overall proportion of explained variation attributable to race/ethnicity was relatively small in comparison to primary treatment and baseline function. No clinically significant racial variation was noted for the sexual, bowel, irritative voiding, or hormone domains. Limitations include the lack of well-established thresholds for clinical significance using the EPIC instrument. Conclusion While these data demonstrate that incontinence at 1 yr after RP may be worse for African-American compared to white men, the difference appears to be modest overall. Treatment selection and baseline function explain a much greater proportion of the variation in function after treatment. Patient summary We observed that the effect of treatment for prostate cancer on patient-reported function did not vary dramatically by race/ethnicity. Compared to white men, African-American men experienced a somewhat more pronounced decline in urinary continence after radical prostatectomy, but the corresponding changes in bother scores were not significantly different between the two groups.
Keywords: NCT0136286; prostate specific antigen; adult; African American; aged; article; cancer patient; cancer radiotherapy; cancer surgery; Caucasian; comparative effectiveness; controlled clinical trial; controlled study; ethnic difference; Expanded Prostate Index Composite; genital system disease assessment; Hispanic; human; intensity modulated radiation therapy; intestine function; kidney function; longitudinal study; major clinical study; male; observational study; patient-reported outcome; priority journal; prospective study; prostate cancer; prostatectomy; race difference; sensitivity analysis; sexual function; urine incontinence

Effect of combined patient decision aid and patient navigation vs usual care for colorectal cancer screening in a vulnerable patient population: A randomized clinical trial - Reuland, D.S.; Brenner, A.T.; Hoffman, R.; McWilliams, A.; Rhyne, R.L.; Getrich, C.; Tapp, H.; Weaver, M.A.; Callan, D.; Cubillos, L.; Urquieta De Hernandez, B.; Pignone, M.P. (JAMA Internal Medicine, 2017)
IMPORTANCE Colorectal cancer (CRC) screening is underused, especially among vulnerable populations. Decision aids and patient navigation are potentially complementary interventions for improving CRC screening rates, but their combined effect on screening completion is unknown. OBJECTIVE To determine the combined effect of a CRC screening decision aid and patient navigation compared with usual care on CRC screening completion. DESIGN, SETTING, AND PARTICIPANTS In this randomized clinical trial, datawere collected from January 2014 to March 2016 at 2 community health center practices, 1 in North Carolina and 1 in New Mexico, serving vulnerable populations. Patients ages 50 to 75 years who had average CRC risk, spoke English or Spanish, were not current with recommended CRC screening, and were attending primary care visits were recruited and randomized 1:1 to intervention or control arms. INTERVENTIONS Intervention participants viewed a CRC screening decision aid in English or Spanish immediately before their clinician encounter. The decision aid promoted screening and presented colonoscopy and fecal occult blood testing as screening options. After the clinician encounter, intervention patients received support for screening completion from a bilingual patient navigator. Control participants viewed a food safety video before the encounter and otherwise received usual care. MAIN OUTCOMES AND MEASURES The primary outcomewas CRC screening completion within 6 months of the index study visit assessed by blinded medical record review. RESULTS Characteristics of the 265 participants were as follows: their mean age was 58 years; 173 (65%) were female, 164 (62%) were Latino; 40 (15%) were white non-Latino; 61 (23%) were black or of mixed race; 191 (78%) had a household income of less than $20 000; 101 (38%) had low literacy; 75 (28%) were on Medicaid; and 91 (34%) were uninsured. Intervention participants were more likely to complete CRC screening within 6 months (68% vs 27%); adjusted-difference, 40 percentage points (95%CI, 29-51 percentage points). The intervention was more effective in women than in men (50 vs 21 percentage point increase, interaction P = .02). No effect modification was observed across other subgroups. CONCLUSIONS AND RELEVANCE A patient decision aid plus patient navigation increased the rate of CRC screening completion in compared with usual care in vulnerable primary care patients.
Keywords: adult; aged; article; Black person; cancer risk; cancer screening; clinical decision support system; colonoscopy; colorectal adenoma; colorectal cancer; colorectal polyp; controlled study; female; Hispanic; household income; human; intestine obstruction; literacy; major clinical study; male; medicaid; medically uninsured; New Mexico; North Carolina; occult blood test; patient care; patient decision making; primary medical care; priority journal; randomized controlled trial; vulnerable population

Prostate-specific antigen response in black and white patients treated with abiraterone acetate for metastatic castrate–resistant prostate cancer - Ramalingam, S.; Humeniuk, M.S.; Hu, R.; Rasmussen, J.; Healy, P.; Wu, Y.; Harrison, M.R.; Armstrong, A.J.; George, D.J.; Zhang, T. (Urologic Oncology: Seminars and Original Investigations, 2017)
Purpose Evidence suggests differences in androgen receptor AR signaling between black (B) and white (W) patients with prostate cancer, but pivotal trials of abiraterone acetate (AA) for patients with metastatic castration–resistant prostate cancer (mCRPC) enrolled few black patients, a population with a higher mortality from prostate cancer. Our primary objective was to determine differences in response to AA between B and W patients. Methods We performed a retrospective case-control study of B vs. W patients treated with AA between May 1, 2008 and June 16, 2015 at Duke University Medical Center. Patients were identified (W control patients were matched 2:1 to B patients stratified based on previous docetaxel exposure) through pharmacy records and were eligible if treated with AA for metastatic castration–resistant prostate cancer. Patients with previous enzalutamide use were excluded. The primary objective was to compare the rate of≥90% prostate-specific antigen (PSA) decline from baseline between B vs. W patients. Secondary outcomes included comparing time on therapy, time to PSA progression, and overall survival among groups. Results Baseline characteristics among patients (n = 45 B, n = 90 W) were identified; these included Karnofsky performance status, PSA, Gleason score, alkaline phosphatase, albumin, hemoglobin, lactate dehydrogenase, opiate use for pain, and metastatic sites. Baseline characteristics among groups were similar except for median hemoglobin (B = 11.4 g/dl, W = 12.3 g/dl). The proportion of B patients achieving a≥90% PSA level decline was 37.8% vs. 28.9% for W patients (P = 0.296). Statistically significant differences were found in the proportion of patients achieving a≥50% PSA level decline (B = 68.9%, W = 48.9% [P = 0.028]) and≥30% PSA level decline (B = 77.8%, W = 54.4% [P = 0.008]). Rates of primary abiraterone-refractory disease (PSA increase as best response) trended higher in W (31.1%) than in B (15.6%) patients (P = 0.052). Median treatment duration (B = 9.4 mo, W = 8.3 mo) did not differ (Wilcoxon P = 0.444). Median overall survival (B = 27.3 mo [95% CI: 13.9, not estimable], W = 24.8 mo [95% CI: 19, 31.6] [P = 0.669]) and median time to PSA progression (B = 11.0 mo [95% CI: 4.3, 18.0], W = 9.4 mo [95% CI: 6.2, 13.0] [P = 0.917]) did not differ. Conclusions Black patients may have a higher PSA response to AA than white patients. An ongoing prospective clinical study (NCT01940276) is evaluating outcomes between black and white patients treated with AA.
Keywords: NCT01940276; abiraterone acetate; albumin; alkaline phosphatase; hemoglobin; lactate dehydrogenase; opiate; prostate specific antigen; albumin blood level; alkaline phosphatase blood level; article; Black person; cancer chemotherapy; cancer patient; castration resistant prostate cancer; Caucasian; clinical trial (topic); controlled study; Gleason score; hemoglobin blood level; human; Karnofsky Performance Status; lactate dehydrogenase blood level; major clinical study; male; metastasis; overall survival; pain; post treatment survival; priority journal; race difference; retrospective study; time to treatment; treatment duration; treatment response

Patient characterization and usage trends of proton beam therapy for localized prostate cancer in the United States: A study of the National Cancer Database - Amini, A.; Raben, D.; Crawford, E.D.; Flaig, T.W.; Kessler, E.R.; Lam, E.T.; Maroni, P.; Pugh, T.J. (Urologic Oncology: Seminars and Original Investigations, 2017)
Purpose To evaluate usage trends and identify factors associated with proton beam therapy (PBT) compared to alternative forms of external beam radiation therapy (RT) (EBRT) for localized prostate cancer. Patients and Methods The National Cancer Database was queried for men with localized (N0, M0) prostate cancer diagnosed between 2004 and 2013, treated with EBRT, with available data on EBRT modality (photon vs. PBT). Binary multiple logistic regression identified variables associated with EBRT modality. Results In total, 143,702 patients were evaluated with relatively few men receiving PBT (5,709 [4.0%]). Significant differences in patient and clinical characteristics were identified between those men treated with PBT compared to those treated with photon (odds ratio [OR]; 95% CI). Patients treated with PBT were generally younger (OR = 0.73; CI: 0.67–0.82), National Comprehensive Cancer Network low-risk compared to intermediate (0.71; 0.65–0.78) or high (0.44; 0.38–0.5) risk, white vs. black race (0.66; 0.58–0.77), with less comorbidity (Charlson-Deyo 0 vs. 2+; 0.70; 0.50–0.98), live in higher income counties (1.55; 1.36–1.78), and live in metropolitan areas compared to urban (0.21; 0.18–0.23) or rural (0.14; 0.10–0.19) areas. Most patients treated with PBT travelled more than 100 miles to the treatment facility. Annual PBT utilization significantly increased in both total number and percentage of EBRT over time (2.7%–5.6%; P<0.001). PBT utilization increased mostly in men classified as National Comprehensive Cancer Network low-risk (4%–10.2%). Conclusion PBT for men with localized prostate cancer significantly increased in the United States from 2004 to 2013. Significant demographic and prognostic differences between those men treated with photons and protons were identified.
Keywords: prostate specific antigen; aged; androgen deprivation therapy; article; brachytherapy; cancer radiotherapy; cancer staging; comorbidity; data base; demography; Gleason score; high income country; human; major clinical study; male; patient selection; priority journal; prostate cancer; proton therapy; radiation dose; United States; urban area

Poor Outcomes of Gastric Cancer Surgery After Admission Through the Emergency Department - Solsky, I.; Friedmann, P.; Muscarella, P.; In, H. (Annals of Surgical Oncology, 2017)
Background: Outcomes after nonelective surgery for gastric cancer (GC) are poorly defined. Our objective was to compare outcomes of patients undergoing nonelective GC surgery after admission through the emergency department (EDSx) with patients receiving elective surgery or surgery after planned admission (non-EDSx) nationally. Methods: The Nationwide Inpatient Sample (NIS) database was used to examine patients undergoing GC surgery between 2008 and 2012. Demographics and outcomes were compared between EDSx and non-EDSx. Multivariable logistic regression was used to examine predictors of discharge to home. Results: Of 9279 patients, 1143 (12%) underwent EDSx. They were more likely to be female (42 vs. 35%), nonwhite (56 vs. 33%), aged ≥75 years (40 vs. 26%), in the lowest quartile for household income (31 vs. 25%), have one or more comorbidities (87 vs. 70%), treated at a nonteaching hospital (46 vs. 25%), and have a concomitant diagnosis of obstruction, perforation, or bleeding (30 vs. 6%). They had longer total length of stay (LOS; 16 vs. 9 days), longer median postoperative stays (10 vs. 9 days), higher in-hospital mortality (8 vs. 3%), and were less likely to be discharged home (63 vs. 82%). EDSx was more expensive ($125,300 vs. $83,604). EDSx was associated with a lower likelihood of discharge to home (odds ratio 0.52, 95% CI 0.43–0.62). Conclusions: Nationally, 12% of GC surgeries are performed after emergency department admission, which occurs more frequently in vulnerable populations and results in worse outcomes. Understanding factors leading to increased EDSx and developing strategies to decrease EDSx may improve GC surgery outcomes.
Keywords: adult; aged; article; Black person; cancer surgery; Caucasian; central nervous system disease; comorbidity; controlled study; deep vein thrombosis; elective surgery; emergency ward; ethnic difference; female; heart disease; Hispanic; hospital admission; hospital discharge; hospital mortality; hospitalization; household income; human; length of stay; lung disease; lung embolism; major clinical study; male; obstruction; outcome assessment; patient selection; perforation; postoperative complication; postoperative hemorrhage; postoperative period; sepsis; stomach cancer; stomach surgery; surgical infection; vulnerable population

Clinical research participation among adolescent and young adults at an NCI-designated Comprehensive Cancer Center and affiliated pediatric hospital - Sanford, S.D.; Beaumont, J.L.; Snyder, M.A.; Reichek, J.; Salsman, J.M. (Supportive Care in Cancer, 2017)
Purpose: Minimal clinical trial participation among adolescents and young adults (AYAs) with cancer limits scientific progress and ultimately their clinical care and outcomes. These analyses examine the current state of AYA clinical research participation at a Midwestern comprehensive cancer center and affiliated pediatric hospital to advise program development and increase availability of trials and AYA participation. Enrollment is examined across all diagnoses, the entire AYA age spectrum (15–39), and both cancer therapeutic and supportive care protocols. Methods: his study was a retrospective review of electronic medical records via existing databases and registries for all AYAs. Data were collected for AYAs seen by an oncologist at the adult outpatient cancer center or at the pediatric hospital between the years 2010 and 2014. Descriptive statistics and logistic regression analyses were conducted to characterize this sample. Results: In the pediatric setting, 42.3% of AYAs were enrolled in a study compared to 11.2% in the adult setting. Regression analyses in the pediatric setting revealed that AYAs with private insurance or Caucasian race were more likely to participate. Within the adult setting, ethnicity, race, insurance, and diagnosis were associated with study participation; 54.8% of study enrollments were for cancer therapeutic and 43.4% for supportive care studies. Conclusions: These results are comparable to previously published data and support the need for new local and national AYA initiatives to increase the availability of and enrollment in therapeutic clinical trials. The same is true for supportive care studies which play a crucial role in improving quality of life.
Keywords: adolescent; adult; article; Black person; brain cancer; breast cancer; cancer center; cancer patient; Caucasian; central nervous system tumor; clinical research; digestive system cancer; female; female genital tract cancer; head and neck cancer; Hispanic; human; leukemia; lymphoma; major clinical study; male; medicaid; myeloma; patient participation; pediatric hospital; priority journal; private health insurance; retrospective study; sarcoma; skin cancer; urogenital tract cancer; young adult

Association of antioxidant supplement use and dementia in the prevention of Alzheimer's disease by Vitamin E and selenium trial (PREADViSE) - Kryscio, R.J.; Abner, E.L.; Caban-Holt, A.; Lovell, M.; Goodman, P.; Darke, A.K.; Yee, M.; Crowley, J.; Schmitt, F.A. (JAMA Neurology, 2017)
IMPORTANCE Oxidative stress is an established dementia pathway, but it is unknown if the use of antioxidant supplements can prevent dementia. OBJECTIVE To determine if antioxidant supplements (Vitamin E or selenium) used alone or in combination can prevent dementia in asymptomatic older men. DESIGN, SETTING, AND PARTICIPANTS The Prevention of Alzheimer's Disease by Vitamin E and Selenium (PREADViSE) trial began as a double-blind randomized clinical trial in May 2002, which transformed into a cohort study from September 2009 to May 2015. The PREADViSE trial was ancillary to the Selenium and Vitamin E Cancer Prevention Trial (SELECT), a randomized clinical trial of the same antioxidant supplements for preventing prostate cancer, which closed in 2009 owing to findings from a futility analysis. The PREADViSE trial recruited 7540 men, of whom 3786 continued into the cohort study. Participants were at least 60 years old at study entry and were enrolled at 130 SELECT sites, and Cox proportional hazards models were used in a modified intent-to-treat analysis to compare hazard rates among the study arms. INTERVENTIONS Participants were randomized to Vitamin E, selenium, Vitamin E and selenium, or placebo. While taking study supplements, enrolled men visited their SELECT site and were evaluated for dementia using a 2-stage screen. During the cohort study, men were contacted by telephone and assessed using an enhanced 2-stage cognitive screen. In both phases, men were encouraged to visit their physician if the screen results indicated possible cognitive impairment. MAIN OUTCOMES AND MEASURES Dementia case ascertainment relied on a consensus review of the cognitive screens and medical records for men with suspected dementia who visited their physician for an evaluation or by review of all available information, including a functional assessment screen. RESULTS The mean (SD) baseline age of the 7540 participants was 67.5 (5.3) years, with 3936 (52.2%) reporting a college education or better, 754 (10.0%) reporting black race, and 505 (6.7%) reporting Hispanic ethnicity. Dementia incidence (325 of 7338 men [4.4%]) was not different among the 4 study arms. A Cox model, which adjusted incidence for participant demographic information and baseline self-reported comorbidities, yielded hazard ratios of 0.88 (95%CI, 0.64-1.20) for Vitamin E, 0.83 (0.60-1.13) for selenium, and 1.00 (0.75-1.35) for the combination compared with placebo. CONCLUSIONS AND RELEVANCE Neither supplement prevented dementia. To our knowledge, this is the first study to investigate the long-term association of antioxidant supplement use and dementia incidence among asymptomatic men.
Keywords: alpha tocopherol; placebo; selenium; aged; Alzheimer disease; article; Black person; chemoprophylaxis; cohort analysis; combination drug therapy; comorbidity; controlled study; double blind procedure; drug use; educational status; Hispanic; human; incidence; major clinical study; male; monotherapy; priority journal; randomized controlled trial

A randomized controlled trial of a multicomponent, targeted, low-literacy educational intervention compared with a nontargeted intervention to boost colorectal cancer screening with fecal immunochemical testing in community clinics - Davis, S.N.; Christy, S.M.; Chavarria, E.A.; Abdulla, R.; Sutton, S.K.; Schmidt, A.R.; Vadaparampil, S.T.; Quinn, G.P.; Simmons, V.N.; Ufondu, C.B.; Ravindra, C.; Schultz, I.; et al. (Cancer, 2017)
BACKGROUND: The objective of the current study was to improve colorectal cancer (CRC) screening uptake with the fecal immunochemical test (FIT). The current study investigated the differential impact of a multicomponent, targeted, low-literacy educational intervention compared with a standard, nontargeted educational intervention. METHODS: Patients aged 50 to 75 years who were of average CRC risk and not up-to-date with CRC screening were recruited from either a federally qualified health center or a primary care community health clinic. Patients were randomized to the intervention condition (targeted photonovella booklet/DVD plus FIT kit) or comparison condition (standard Centers for Disease Control and Prevention brochure plus FIT kit). The main outcome was screening with FIT within 180 days of delivery of the intervention. RESULTS: Of the 416 participants, 54% were female; the participants were racially and ethnically diverse (66% white, 10% Hispanic, and 28% African American), predominantly of low income, and insured (the majority had county health insurance). Overall, the FIT completion rate was 81%, with 78.1% of participants in the intervention versus 83.5% of those in the comparison condition completing FIT (P =.17). In multivariate analysis, having health insurance was found to be the primary factor predicting a lack of FIT screening (adjusted odds ratio, 2.10; 95% confidence interval, 1.04-4.26 [P =.04]). CONCLUSIONS: The multicomponent, targeted, low-literacy materials were not found to be significantly different or more effective in increasing FIT uptake compared with the nontargeted materials. Provision of a FIT test plus education may provide a key impetus to improve the completion of CRC screening. The type of educational material (targeted vs nontargeted) may matter less. The findings of the current study provide a unique opportunity for clinics to adopt FIT and to choose the type of patient education materials based on clinic, provider, and patient preferences. Cancer 2017;123:1390–1400. © 2016 American Cancer Society.
Keywords: adult; African American; aged; article; awareness; cancer awareness score; cancer control; cancer prevention; cancer risk; cancer screening; clinical effectiveness; clinical study; colonoscopy; colorectal cancer; community care; controlled study; demography; educational status; ethnicity; family history; fecal immunochemical testing; female; health belief; health care system; health insurance; health literacy; Hispanic; human; immunochemistry; lowest income group; major clinical study; male; multicomponent study; patient preference; physical examination; polyp; prediction; randomized controlled trial; rectum cancer; religion; self concept; social support; socioeconomics; trust

Correlates of Patient Intent and Preference on Colorectal Cancer Screening - Jimbo, M.; Sen, A.; Plegue, M.A.; Hawley, S.T.; Kelly-Blake, K.; Rapai, M.; Zhang, M.; Zhang, Y.; Ruffin, M.T. (American Journal of Preventive Medicine, 2017)
Introduction Information is limited on patient characteristics that influence their preference among screening options and intent to be screened for colorectal cancer (CRC). A mechanistic pathway to intent and preference was examined through a formal mediation analysis. Methods From 2012 to 2014, a total of 570 adults aged 50–75 years were recruited from 15 primary care practices in Metro Detroit for a trial on decision aids for CRC screening. Confirmatory factor, regression, and mediation analyses were performed in 2015–2016 on baseline cross-sectional data. Main outcomes were patient intent and preference. Perceived risk and self-efficacy were secondary outcomes. Covariates included demographic information, health status, previous CRC screening experience, patient attitudes, and knowledge. Results Mean age was 57.7 years, 56.1% were women, and 55.1% white and 36.6% black. Women had 32% and 41% lower odds than men of perceiving CRC to be high/moderate risk (OR=0.68, 95% CI=0.47, 0.97, p=0.03) and having high self-efficacy (OR=0.59, 95% CI=0.42, 0.85, p=0.006), respectively. Whites had 63% and 47% lower odds than blacks of having high self-efficacy (OR=0.37, 95% CI=0.25, 0.57, p<0.001) and intent to undergo CRC screening (OR=0.53, 95% CI=0.34, 0.84, p=0.007), respectively. Younger age, higher knowledge, lower level of test worries, and medium/high versus low self-efficacy increased the odds of intent of being screened. Self-efficacy, but not perceived risk, significantly mediated the association between race, attitude, and test worries and patient screening intent. Conclusions Self-efficacy mediated the association between race, attitude, and test worries and patient intent.
Keywords: NCT01514786; adult; aged; article; cancer screening; colonoscopy; colorectal cancer; demography; female; health status; human; knowledge; major clinical study; male; medical decision making; occult blood test; patient attitude; patient preference; primary medical care

Prognostic Significance of a Negative Prostate Biopsy: An Analysis of Subjects Enrolled in a Prostate Cancer Screening Trial - Lewicki, P.; Shoag, J.; Golombos, D.M.; Oromendia, C.; Ballman, K.V.; Halpern, J.A.; Stone, B.V.; O'Malley, P.; Barbieri, C.E.; Scherr, D.S. (Journal of Urology, 2017)
Purpose To our knowledge the optimal treatment of patients following a negative prostate biopsy is unknown. Consequently, resources are increasingly being directed toward risk stratification in this cohort. However, the risk of prostate cancer mortality in this group before the introduction of supplemental biomarkers and imaging techniques is unclear. Materials and Methods The PLCO (Prostate, Lung, Colorectal and Ovarian Cancer) Screening Trial provides survival data prior to the implementation of new diagnostic interventions. We divided men with an initial positive screen and a subsequent prostate biopsy into cohorts based on positive or negative results. Prostate cancer specific mortality was then compared to that in the trial control arm to estimate the prognostic significance of biopsy results relative to the general population. Results A total of 36,525 and 36,560 patients comprised the screening and control arms, respectively. Of 4,064 subjects with a positive first screen 1,233 underwent a linked biopsy, of which 473 were positive and 760 were negative. At a median followup of 12.9 years, 1.1% of men in the negative biopsy cohort had died of prostate cancer. The difference in mortality rates between the negative biopsy and control arms was 0.734 deaths per 1,000 person-years. The proportional subhazard ratios of prostate cancer specific mortality for negative biopsy and positive biopsy relative to the control arm were 2.93 (95% CI 1.44–5.99) and 18.77 (95% CI 12.62–27.93), respectively. Conclusions After a negative prostate biopsy, men face a relatively low risk of death from prostate cancer when followed with traditional markers and biopsy techniques. This suggests limited potential for new diagnostic interventions to improve survival in this group.
Keywords: adult; African American; aged; article; cancer incidence; cancer mortality; cancer prognosis; cancer risk; cancer screening; cancer survival; Caucasian; controlled study; family history; follow up; Gleason score; human; major clinical study; male; medical record review; mortality rate; priority journal; prognostic assessment; prostate biopsy; prostate cancer; prostate cancer prognostic test; randomized controlled trial (topic); tumor biopsy

Adoption, reach, and implementation of a cancer education intervention in African American churches - Santos, S.L.; Tagai, E.K.; Scheirer, M.A.; Bowie, J.; Haider, M.; Slade, J.; Wang, M.Q.; Holt, C.L. (Implementation science : IS, 2017)
BACKGROUND: Use of technology is increasing in health promotion and has continued growth potential in intervention research. Guided by the Reach, Effectiveness, Adoption, Implementation, ﻿and Maintenance (RE-AIM) framework, this paper reports on the adoption, reach, and implementation of Project HEAL (Health through Early Awareness and Learning)-a community-based implementation trial of a cancer educational intervention in 14 African American churches. We compare adoption, reach, and implementation at the organizational and participant level for churches in which lay peer community health advisors (CHAs) were trained using traditional classroom didactic methods compared with a new online system. METHODS: Fifteen churches were randomized to one of two study groups in which two CHAs per church were trained through either classroom ("Traditional"; n = 16 CHAs in 8 churches) or web-based ("Technology"; n = 14 CHAs in 7 churches) training methods. Once trained and certified, all CHAs conducted a series of three group educational workshops in their churches on cancer early detection (breast, prostate, and colorectal). Adoption, reach, and implementation were assessed using multiple data sources including church-level data, participant engagement in the workshops, and study staff observations of CHA performance. RESULTS: The project had a 41% overall adoption rate at the church level. In terms of reach, a total of 375 participants enrolled in Project HEAL-226 participants in the Traditional group (43% reach) and 149 in the Technology group (21% reach; p < .10). Implementation was evaluated in terms of adherence, dosage, and quality. All churches fully completed the three workshops; however, the Traditional churches took somewhat longer (M = 84 days) to complete the workshop series than churches in the Technology group (M = 64 days). Other implementation outcomes were comparable between both the Traditional and Technology groups (p > .05). CONCLUSIONS: Overall, the Project HEAL intervention had reasonable adoption, though reach could have been better. Implementation was strong across both study groups, suggesting the promise of using web-based methods to disseminate and implement evidence-based interventions in faith-based settings and other areas where community health educators work to eliminate health disparities.
Keywords: adult; African American; aged; attitude to health; cluster analysis; controlled study; female; health education; health promotion; human; male; middle aged; neoplasm; procedures; randomized controlled trial; religion

Phase Ib Trial of Cabazitaxel and Tasquinimod in Men With Heavily Pretreated Metastatic Castration Resistant Prostate Cancer (mCRPC): The CATCH Trial - Armstrong, A.J.; Humeniuk, M.S.; Healy, P.; Szmulewitz, R.; Winters, C.; Kephart, J.; Harrison, M.R.; Martinez, E.; Mundy, K.; Halabi, S.; George, D. (Prostate, 2017)
BACKGROUND: Tasquinimod is an immunomodulating and anti-antiangiogenic oral agent with anti-prostate cancer activity in preclinical studies and in clinical trials of men with metastatic castration resistant prostate cancer (mCRPC), including single agent activity and in combination with taxanes. We sought to identify the maximum tolerated dose (MTD) and recommended phase 2 dose (RP2D) of tasquinimod in combination with cabazitaxel and prednisone in men with chemorefractory mCRPC. METHODS: Men with mCRPC who had failed prior docetaxel chemotherapy received cabazitaxel 25 mg/m2 every 3 weeks with oral tasquinimod at 1 of 3 escalating dose levels (0.25, 0.5, and 1.0 mg once daily) with prednisone and PEG-filgastrim support, using a 3 + 3 dose escalation design. Treatment continued until progressive disease or unacceptable toxicity. RESULTS: We enrolled 25 men with chemorefractory mCRPC. The RP2D was 0.5 mg tasquinimod based on excess DLTs (two of three men) observed at dose level 3 (1.0 mg) including grade 3 sensory neuropathy and grade 3 atrial fibrillation. Dose level 2 was expanded to 14 men, where 3 DLTs were observed: grade 3 fatigue, grade 4 febrile neutropenia, and grade 3 liver function abnormalities. The proportion of men with a ≥30% PSA decline was 63% and the median composite progression-free survival (PFS) was 8.5 months (95% CI 4.2–16.4 months) based on 12 PFS events. The median number of cycles of cabazitaxel was 6 (range 1–13), with six men receiving >10 cycles. Best overall RECIST responses (CR + PR) were observed in three men (12%), with stable disease in 12 (48%). No pharmacokinetic interactions were observed. CONCLUSIONS: We determined the RP2D of tasquinimod combined with cabazitaxel to be 0.5 mg daily following a 3 week lead-in of tasquinimod 0.25 mg with growth factor support. No unexpected toxicities occurred. Prostate 77: 385–395, 2017. © 2016 Wiley Periodicals, Inc.
Keywords: NCT01513733; abiraterone acetate; cabazitaxel; docetaxel; enzalutamide; opiate; pegfilgrastim; prednisone; prostate specific antigen; tasquinimod; abdominal pain; adult; African American; aged; alopecia; anemia; anorexia; antineoplastic activity; area under the curve; article; atrial fibrillation; bleeding; bone metastasis; cancer immunotherapy; cancer pain; cancer survival; castration resistant prostate cancer; Caucasian; circulating tumor cell; clinical article; colon perforation; constipation; controlled study; diarrhea; dizziness; drug clearance; drug dose escalation; drug response; drug safety; drug tolerability; lack of drug effect; dysgeusia; dyspepsia; electrolyte disturbance; fatigue; febrile neutropenia; gastritis; headache; human; hypertransaminasemia; hypotension; insomnia; Karnofsky Performance Status; leg swelling; liver dysfunction; liver metastasis; lung metastasis; lymph node metastasis; male; maximum tolerated dose; metastasis potential; multiple cycle treatment; musculoskeletal pain; nausea; oral mucositis; overall survival; pain; peripheral edema; phase 1 clinical trial; progression free survival; prostate adenocarcinoma; rash; recommended drug dose; sensory neuropathy; sepsis; stomach ulcer; taste disorder; thrombocytopenia; urinary tract infection; visceral metastasis; volume of distribution; vomiting

Recruiting families at risk for hereditary breast and ovarian cancer from a statewide cancer registry: a methodological study - Katapodi, M.C.; Duquette, D.; Yang, J.J.; Mendelsohn-Victor, K.; Anderson, B.; Nikolaidis, C.; Mancewicz, E.; Northouse, L.L.; Duffy, S.; Ronis, D.; Milliron, K.J.; Probst-Herbst, N.; et al. (Cancer Causes and Control, 2017)
Purpose: Cancer genetic services (counseling/testing) are recommended for women diagnosed with breast cancer younger than 45 years old (young breast cancer survivors—YBCS) and at-risk relatives. We present recruitment of YBCS, identification and recruitment of at-risk relatives, and YBCS willingness to contact their cancer-free, female relatives. Methods: A random sample of 3,000 YBCS, stratified by race (Black vs. White/Other), was identified through a population-based cancer registry and recruited in a randomized trial designed to increase use of cancer genetic services. Baseline demographic, clinical, and family characteristics, and variables associated with the Theory of Planned Behavior (TPB) were assessed as predictors of YBCS’ willingness to contact at-risk relatives. Results: The 883 YBCS (33.2% response rate; 40% Black) who returned a survey had 1,875 at-risk relatives and were willing to contact 1,360 (72.5%). From 853 invited at-risk relatives (up to two relatives per YBCS), 442 responded (51.6% response rate). YBCS with larger families, with a previous diagnosis of depression, and motivated to comply with recommendations from family members were likely to contact a greater number of relatives. Black YBCS were more likely to contact younger relatives and those living further than 50 miles compared to White/Other YBCS. Conclusion: It is feasible to recruit diverse families at risk for hereditary cancer from a population-based cancer registry. This recruitment approach can be used as a paradigm for harmonizing processes and increasing internal and external validity of large-scale public health genomic initiatives in the era of precision medicine.
Keywords: adult; age distribution; article; Black person; cancer survivor; Caucasian; controlled study; depression; educational status; family history; female; gene mutation; genetic counseling; health care access; hereditary breast and ovarian cancer syndrome; high risk population; human; major clinical study; motivation; patient preference; tumor suppressor gene

African American Women's Recollected Experiences of Adherence to Breast Cancer Treatment - Heiney, S.P.; Hilfinger Messias, D.K.; Felder, T.M.; Phelps, K.W.; Quinn, J.C. (Oncology nursing forum, 2017)
PURPOSE/OBJECTIVES: To explore African American women's recollected experiences of breast cancer treatment. . RESEARCH APPROACH: Qualitative description and narrative analysis. . SETTING: South Carolina Oncology Associates, an outpatient oncology clinic serving rural and urban populations. . PARTICIPANTS: 16 African American women with breast cancer previously enrolled in the control arm (n = 93) of a completed randomized, controlled trial.  . METHODOLOGIC APPROACH: Feminist narrative analysis of in-depth individual interviews. . FINDINGS: The authors identified three themes within the African American breast cancer survivors' recollected experiences of treatment adherence. INTERPRETATION: Although little evidence was presented of shared decision making with providers, patients were committed to completing the prescribed therapies. The narratives highlighted the value of in-depth examination of patients' perspectives, particularly among minority and underserved groups. With the exception of voicing personal choice of surgical treatment, the women trusted providers' recommendations with a resolve to "just do it." Although trust may enhance treatment adherence, it may also reflect power differentials based on gender, race, education, and culture. . IMPLICATIONS FOR NURSING: Nurses should listen to patients describe their experience with cancer treatment and compare the themes from this study with their patients' story. This comparison will help nurses support patients through various aspect of diagnosis and treatment.
Keywords: adult; African American; aged; attitude to health; breast tumor; cancer survivor; ethnology; female; human; middle aged; patient compliance; psychology; rural population; South Carolina; urban population; very elderly

Barriers and Strategies to Participation in Tissue Research Among African-American Men - Drake, B.F.; Boyd, D.; Carter, K.; Gehlert, S.; Thompson, V.S. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2017)
Before the burgeoning field of biospecimen collection can advance prevention and treatment methods, researchers must access diverse molecular data samples. However, minorities, especially African-American men, remain reticent to join these studies. This study, using theory-based approaches, investigated African-American men's barriers to participating in biorepository research. Fourteen focus groups were conducted among 70 African-American men (ages 40 to 80). The groups were stratified by prostate cancer history and educational attainment background. Participants identified perceived factors that promoted or hindered study participation when questioned about their knowledge and attitudes about biospecimen research. Ninety-four percent of participants indicated never participating in a study that collected biological samples. Barriers to their participation included lack of knowledge and understanding regarding biospecimen research practices and uses. In addition, they extensively cited a prevalent mistrust of the medical community and discomfort with study recruitment practices. African-American males were more willing to participate in biorepository studies with physician endorsement or if they understood that participation could benefit future generations. Men also wanted more recruitment and advertising done in familiar places.
Keywords: adult; African American; aged; attitude to health; human; information processing; male; medical research; middle aged; patient selection; procedures; prostate tumor; specimen handling; statistics and numerical data; United States; very elderly

Barriers to Recruitment and Adherence in a Randomized Controlled Diet and Exercise Weight Loss Intervention Among Minority Breast Cancer Survivors - Aycinena, A.C.; Valdovinos, C.; Crew, K.D.; Tsai, W.Y.; Mata, J.M.; Sandoval, R.; Hershman, D.; Greenlee, H. (Journal of immigrant and minority health, 2017)
Minority recruitment to cancer trials is low and there are limited data on minority adherence to lifestyle modification interventions. We examined factors related to recruitment and adherence to a pilot weight loss intervention among Hispanic and black breast cancer survivors. Participants completed a detailed screening interview to assess barriers to enrollment. An index was created to assess adherence at 6 months. 112 potentially eligible women were identified; 66 consented and completed a screening interview. After screening, 9 were ineligible; 15 opted to not enroll; and 42 were randomized. Among eligible women, earlier stage at diagnosis, treatment type, and negative beliefs related to exercise and diet after diagnosis were negatively associated with study enrollment (P < 0.05). Self-reported barriers to adherence included fatigue, family responsibilities, illness, work, transportation, and negative perceptions of exercise and diet. Results from this study emphasize the need to adapt recruitment and adherence strategies to address these factors.
Keywords: adult; African American; aged; attitude to health; breast tumor; cancer staging; cancer survivor; diet; ethnology; exercise; female; health behavior; Hispanic; human; lifestyle; mental health; middle aged; pathology; patient compliance; patient selection; perception; pilot study; procedures; psychology; quality of life; randomized controlled trial (topic); self concept; social support; sociobiology; weight loss program; young adult

The effect of demographics and patient location on the outcome of patients with acute respiratory distress syndrome - El-Haddad, H.; Jang, H.; Chen, W.; Haider, S.; Soubani, A.O. (Annals of Thoracic Medicine, 2017)
OBJECTIVE: Outcome of acute respiratory distress syndrome (ARDS) in relation to age, gender, race, pre-Intensive Care Unit (ICU) location, and type of ICU. METHODS: Retrospective cohort study of patients enrolled in the ARDS network randomized controlled trials. RESULTS: A total of 2914 patients were included in these trials. Outcomes were adjusted to baseline covariates including APACHE III score, vasopressor use, cause of lung injury, lung injury score, diabetes, cancer status, body mass index, and study ID. Older patients had significantly higher mortality at both 28- and 60-day (odds ratio [OR] 2.59 [95% confidence interval [CI]: 2.12-3.18] P < 0.001 and 2.79, 95% CI: 2.29-3.39, P < 0.001, respectively); less ICU and ventilator free days (relative risk [RR] 0.92, 95% CI: 0.87-0.96, P < 0.001 and 0.92, 95% CI: 0.88-0.96, P < 0.001, respectively). For preadmission location, the 28- and 60-day mortality were lower if the patient was admitted from the operating room (OR)/recovery room (OR 0.65, 95% CI: 0.44-0.95, P = 0.026; and OR = 0.66, 95% CI: 0.46-0.95, P = 0.025, respectively) or emergency department (OR = 0.78, 95% CI: 0.61-0.99, P = 0.039; and OR = 0.71, 95% CI: 0.56-0.89, P = 0.004, respectively), but no statistical differences in ICU and ventilator free days between different preadmission locations. Races other than white and black had a statistically higher mortality (28- and 60-day mortality: OR = 1.47, 95% CI: 1.09-1.98, P = 0.011; and OR 1.53, 95% CI: 1.15-2.04, P = 0.004, respectively). Between whites and blacks, females and males there were no statistically significant differences in all outcomes. CONCLUSION: Older patients and races other than blacks and whites have higher mortality associated with ARDS. Mortality is affected by patients preadmission location. There are no differences in outcome in relation to the type of ICU, gender, or between blacks and whites.
Keywords: hypertensive factor; ketoconazole; adolescent; adult; adult respiratory distress syndrome; aged; APACHE; article; artificial ventilation; cohort analysis; controlled study; diabetes mellitus; female; human; intensive care unit; lung injury; major clinical study; male; mortality rate; pneumonia; pulmonary aspiration; randomized controlled trial; retrospective study; sepsis; treatment outcome

Incidental findings on chest computed tomography are common and linked to inflammation in HIV-infected adults - Park, M.S.; Hileman, C.O.; Sattar, A.; Gilkeson, R.; McComsey, G.A. (Antiviral Therapy, 2017)
Background: Chest imaging is performed for a variety of reasons in HIV-infected adults. There are limited data on the prevalence of incidental findings, progression of these findings over time and the relationship with inflammation in antiretroviral therapy (ART)-treated HIV-infected adults. Methods: This study utilized data from a randomized clinical trial of rosuvastatin in HIV-infected adults on ART. Incidental findings were reported from chest computed tomography (CT) scans obtained for coronary artery calcium score at entry, week 48 and 96. Markers of immune activation and inflammation were measured concurrently. Poisson regression and generalized estimating equations were used. Results: A total of 147 participants were enrolled. Median age was 46 years, 78% were male, 68% African American and 63% current smokers. At baseline, 57% of participants had at least one incidental lung finding (ILF) and four additional participants had at least one ILF by week 96. At baseline, older age, current smoking, lower nadir CD4+ T-cell count and low-density lipoprotein and higher lipoprotein-associated phospholipase A2 (Lp-PLA2) were independently associated with having a greater number of ILFs. In the longitudinal analyses, older age, lower nadir CD4+ T-cell count and higher baseline soluble tumour necrosis factor α-receptor I (sTNF-RI) were independently associated with having a greater number of ILFs over 96 weeks. Conclusions: Over half of participants had at least one incidental finding on chest CT. Beyond traditional factors of older age and smoking, lower nadir CD4+ T-cell count and higher markers of inflammation were associated with having a greater number of ILFs in HIV-infected adults on ART.
Keywords: NCT01218802; 1 alkyl 2 acetylglycerophosphocholine esterase; low density lipoprotein; placebo; rosuvastatin; tumor necrosis factor receptor 1; adult; African American; age; antiretroviral therapy; article; atelectasis; CD4 lymphocyte count; computed tomography scanner; computer assisted tomography; coronary artery calcium score; female; human; Human immunodeficiency virus infection; incidental finding; latent tuberculosis; lung disease; lung nodule; major clinical study; male; parenchymal scar; Pneumocystis pneumonia; priority journal; randomized controlled trial (topic); smoking; Somatom Sensation 64

Mutational landscapes of smoking-related cancers in Caucasians and African Americans: Precision oncology perspectives at Wake Forest Baptist comprehensive Cancer Center - Kytola, V.; Topaloglu, U.; Miller, L.D.; Bitting, R.L.; Goodman, M.M.; D'Agostino, R.B.; Desnoyers, R.J.; Albright, C.; Yacoub, G.; Qasem, S.A.; DeYoung, B.; Thorsson, V.; et al. (Theranostics, 2017)
Background: Cancers related to tobacco use and African-American ancestry are under-characterized by genomics. This gap in precision oncology research represents a major challenge in the health disparities in the United States. Methods: The Precision Oncology trial at the Wake Forest Baptist Comprehensive Cancer Center enrolled 431 cancer patients from March 2015 to May 2016. The composition of these patients consists of a high representation of tobacco-related cancers (e.g., lung, colorectal, and bladder) and African-American ancestry (13.5%). Tumors were sequenced to identify mutations to gain insight into genetic alterations associated with smoking and/or African-American ancestry. Results: Tobacco-related cancers exhibit a high mutational load. These tumors are characterized by high-frequency mutations in TP53, DNA damage repair genes (BRCA2 and ATM), and chromatin remodeling genes (the lysine methyltransferases KMT2D or MLL2, and KMT2C or MLL3). These tobacco-related cancers also exhibit augmented tumor heterogeneities. Smoking related genetic mutations were validated by The Cancer Genome Atlas dataset that includes 2,821 cases with known smoking status. The Wake Forest and The Cancer Genome Atlas cohorts (431 and 7,991 cases, respectively) revealed a significantly increased mutation rate in the TP53 gene in the African-American subgroup studied. Both cohorts also revealed 5 genes (e.g. CDK8) significantly amplified in the African-American population. Conclusions: These results provide strong evidence that tobacco is a major cause of genomic instability and heterogeneity in cancer. TP53 mutations and key oncogene amplifications emerge as key factors contributing to cancer outcome disparities among different racial/ethnic groups.
Keywords: NCT02566421; ATM protein; BRCA2 protein; protein p53; African American; article; ATM gene; bladder cancer; BRCA2 gene; Caucasian; chromosomal instability; colorectal cancer; gene; gene amplification; gene mutation; genetic association; genomic instability; head and neck cancer; high frequency mutation; human; human tissue; KMT2C gene; KMT2D gene; lung cancer; major clinical study; malignant neoplasm; MLL2 gene; MLL3 gene; mutation rate; mutational load; smoking; smoking related cancer; TP53 gene

History of diabetes and survival outcome among participants 65 years or older in SWOG clinical trials - Hershman, D.L.; Till, C.; Wright, J.D.; Ramsey, S.; Barlow, W.E.; Unger, J.M. (JCO Clinical Cancer Informatics, 2017)
Purpose Diabetes is common, increases with age, and may affect outcomes among people with cancer. Understanding the association between diabetes and cancer outcome is challenging, because patients with diabetes have increased all-cause mortality compared with patients without diabetes. Methods We systematically examined the phase III trial database of SWOG to identify patients enrolled in trials during the period from 1999 to 2011. We linked the SWOG clinical records to Medicare claims data according to Social Security number, sex, and date of birth. Medicare claims were used to identify diabetes with at least 6 months of continuous Medicare coverage immediately before registration. Multivariable Cox regression was used to compare survival outcomes between patients with and without diabetes for each of 10 tumor cohorts. The primary outcome was overall survival. We also examined progression-free survival and cancer-free survival. Results In total, 6,422 patients from 15 trials were ≥ 65.5 years of age, of whom 3,173 patients (49%) met the criteria for linkage to Medicare claims. Thirty percent (n = 952) had claims for diabetes before registration. Patients with diabetes were more likely to be black (P < .001), but no other differences in demographic characteristics were observed. In multivariable Cox regression, no association was found between baseline diabetes and overall or progression-free survival; in one case, patients with diabetes had marginally worse cancer-free survival (advanced non-small-cell lung cancer; P = .05). A global test found that baseline diabetes was associated with worse overall survival (P = .03) across the entire panel of analyses. Conclusion Diabetes is common among elderly patients enrolled in clinical trials. Unlike prior observational studies, among patients treated with uniform treatment regimens, and controlling for known prognostic factors, we did not observe an association between diabetes and progression-free or cancerfree survival.
Keywords: advanced cancer; aged; article; body weight loss; breast cancer; cancer patient; cancer prognosis; castration resistant prostate cancer; cause of death; controlled study; demography; diabetes mellitus; female; human; major clinical study; male; medicare; non small cell lung cancer; overall survival; priority journal; progression free survival; questionnaire; self report

Biases in recommendations for and acceptance of prostate biopsy significantly affect assessment of prostate cancer risk factors: Results from two large randomized clinical trials - Tangen, C.M.; Goodman, P.J.; Till, C.; Schenk, J.M.; Lucia, M.S.; Thompson, I.M. (Journal of Clinical Oncology, 2016)
Purpose To identify factors related to who undergoes a prostate biopsy in a screened population and to estimate the impact of biopsy verification on risk factor-prostate cancer associations. Patients and Methods Men who were screened regularly from the placebo arms of two large prostate cancer prevention trials (Prostate Cancer Prevention Trial [PCPT] and Selenium and Vitamin E Cancer Prevention Trial [SELECT]) were examined to define incident prostate cancer cohorts. Because PCPT had an end-ofstudy biopsy, prostate cancer cases were categorized by a preceding prostate-specific antigen/digital rectal examination prompt (yes/no) and noncases by biopsy-proven negative status (yes v no). We estimated the association of risk factors (age, ethnicity, family history, body mass index, medication use) with prostate cancer and quantified differences in risk associations across cohorts. Results Men 60 to 69 years of age, those with benign prostatic hyperplasia, and those with a family history of prostate cancer were more likely, and those with a higher body mass index ($ 25), diabetes, or a smoking history were less likely, to undergo biopsy, adjusting for age and longitudinal prostatespecific antigen and digital rectal examination. Medication use, education, and marital status also influenced who underwent biopsy. Some risk factor estimates for prostate cancer varied substantially across cohorts. Black (v other ethnicities) had odds ratios (ORs) that varied from 1.20 for SELECT (community screening standards, epidemiologic-like cohort) to 1.83 for PCPT (end-of-study biopsy supplementedwith imputed end points). Statin use in SELECT provided anOR of 0.65 and statin use in in PCPT provided an OR of 0.99, a relative difference of 34%. Conclusion Among screenedmen enrolled in prostate cancer prevention trials, differences in risk factor estimates for prostate cancer likely underestimate the magnitude of bias found in other cohorts with varying screening and biopsy recommendations and acceptance. Risk factors for prostate cancer derived from epidemiologic studies not only may be erroneous but may lead to misdirected research efforts.
Keywords: acetylsalicylic acid; alpha tocopherol; hydroxymethylglutaryl coenzyme A reductase inhibitor; placebo; prostate specific antigen; selenium; adult; age; aged; article; Black person; body mass; cancer prevention; cancer risk; cancer screening; controlled study; diabetes mellitus; digital rectal examination; education; ethnicity; family history; human; human tissue; major clinical study; male; marriage; middle aged; patient attitude; priority journal; prospective study; prostate biopsy; prostate cancer; prostate hypertrophy; randomized controlled trial; risk factor; smoking; tumor biopsy; vasectomy

Focus on You: Cancer clinical trials perspectives - Robinson, B.N.; Newman, A.F.; Wallington, S.F.; Swain, S.M. (Contemporary Clinical Trials Communications, 2016)
Background Clinical trials test new ways to prevent, detect, diagnose, or treat diseases. Researchers have found that minority patients are willing to participate in clinical trials, yet these patients have barriers which hinder their access to trials. Methods To explore African American women's participation in breast cancer clinical trials, eight focus groups were conducted with breast cancer patients, family members/care givers, religious leaders, and healthcare providers to gather information on the perspectives and opinions on the topic. The focus group conversations were transcribed, and transcripts were imported into QSR International's NVivo 10 software. The transcripts were organized into folders based on four categories. The content analysis performed was based on recordings and notes. Results The following themes were generated as a result of conducting these focus groups and gathering information on the perspectives and opinions about participating in clinical trials, based on the groups who participated: Promoting participation in research; Personal experience with cancer; Support and support services; Awareness, knowledge, and experience with clinical trials; Providers' roles in clinical trials. Conclusion The data collected in this study present several actionable themes that, if addressed by individual researchers and the medical community at large, could increase participation in clinical trials by African American patients. They also provide a deeper and more nuanced understanding of the factors influencing African American patients' decisions around participating in clinical trials.
Keywords: African American; article; awareness; breast cancer; cancer patient; cancer research; caregiver; clergy; clinical trial (topic); content analysis; family; health care personnel; human; information processing; information seeking; knowledge; medical information; patient participation; personal experience; priority journal

Unit nonresponse in a population-based study of prostate cancer - Oral, E.; Simonsen, N.; Brennan, C.; Berken, J.; Su, L.J.; Mohler, J.L.; Bensen, J.T.; Fontham, E.T.H. (PLoS ONE, 2016)
Low unit response rates can increase bias and compromise study validity. Response rates have continued to fall over the past decade despite all efforts to increase participation. Many factors have been linked to reduced response, yet relatively few studies have employed multivariate approaches to identify characteristics that differentiate respondents from nonrespondents since it is hard to collect information on the latter. We aimed to assess factors contributing to enrollment of prostate cancer (PCa) patients. We combined data from the North Carolina-Louisiana (LA) PCa Project's LA cohort, with additional sources such as US census tract and LA tumor registry data. We included specific analyses focusing on blacks, a group often identified as hard to enroll in health-related research. The ability to study the effect of Hurricane Katrina, which occurred amidst enrollment, as a potential determinant of nonresponse makes our study unique. Older age (≥ 70) for blacks (OR 0.65) and study phase with respect to Hurricane Katrina for both races (OR 0.59 for blacks, OR 0.48 for whites) were significant predictors of participation with lower odds. Neighborhood poverty for whites (OR 1.53) also was a significant predictor of participation, but with higher odds. Among blacks, residence in Orleans parish was associated with lower odds of participation (OR 0.33) before Katrina. The opposite occurred in whites, with lower odds (OR 0.43) after Katrina. Our results overall underscore the importance of tailoring enrollment approaches to specific target population characteristics to confront the challenges posed by nonresponse. Our results also show that recruitment-related factors may change when outside forces bring major alterations to a population's environment and demographics.
Keywords: adult; age; aged; article; Black person; cancer patient; Caucasian; controlled study; demography; environment; human; hurricane; major clinical study; male; patient participation; prostate cancer; sampling; unit nonresponse

Individual Patient Data Analysis of Randomized Clinical Trials: Impact of Black Race on Castration-resistant Prostate Cancer Outcomes - Spratt, D.E.; Chen, Y.-W.; Mahal, B.A.; Osborne, J.R.; Zhao, S.G.; Morgan, T.M.; Palapattu, G.; Feng, F.Y.; Nguyen, P.L. (European Urology Focus, 2016)
Background Population data suggest that black men have a higher risk of dying from prostate cancer (PCa) than other racial ethnicities. Objective To examine the impact of black race on progression-free survival (PFS) and overall survival (OS) among men with metastatic castration-resistant PCa (mCRPC) enrolled in randomized controlled trials (RCTs). Design, setting, and participants A pooled analysis was performed on individual patient data from five modern PCa RCTs available from Project Data Sphere. Outcome measurements and statistical analysis Adjusted hazard ratios (HRs) were calculated to compare black and white race regarding PFS and OS. Subgroup analyses of mCRPC trials were performed based on the control arm treatments (mitoxantrone or docetaxel). Relevant covariates were used for adjustment in all analyses. Results and limitations A total of 1613 patients were included; 77 were black (4.7%). No significant differences between black and white men's baseline characteristics were noted regarding age, performance status, or pretreatment prostate-specific antigen. The pooled HRs for black race for OS and PFS were 1.01 (95% confidence interval [CI], 0.73–1.35) and 1.29 (95% CI, 0.95–1.76), respectively. The median OS for black compared with white men was 254 versus 238 d (p = 0.92), respectively, with mitoxantrone and 581 versus 546 d (p = 0.53), respectively, with docetaxel. The primary limitation was the relatively small number of black men enrolled in mCRPC clinical trials. Conclusions In the context of RCTs, in which patients receive generally uniform treatment, a significant difference in OS for black men could not be detected in mCRPC. Black men continue to be dramatically underrepresented in RCTs, and efforts are needed to increase minority accrual to these trials. Patient summary We looked at the outcomes of men treated in randomized controlled trials to determine the impact of black race on survival. We found that in the context of modern clinical trials, there does not appear to be a significant difference in survival between black and white races; however, a trend for greater progression in black men was noted.
Keywords: aflibercept; cabazitaxel; docetaxel; mitoxantrone; prednisone; prostate specific antigen; siltuximab; adult; age; aged; article; Black person; cancer prognosis; castration resistant prostate cancer; Caucasian; data analysis; human; major clinical study; male; metastasis; multicenter study (topic); overall survival; patient information; performance; performance status; phase 2 clinical trial (topic); phase 3 clinical trial (topic); progression free survival; race difference; randomized controlled trial (topic); cnto 328; xrp 6258

Do Men Receive Information Required for Shared Decision Making About PSA Testing? Results from a National Survey - Leyva, B.; Persoskie, A.; Ottenbacher, A.; Hamilton, J.G.; Allen, J.D.; Kobrin, S.C.; Taplin, S.H. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2016)
Most professional organizations, including the American College of Physicians and U.S. Preventive Services Task Force, emphasize that screening for prostate cancer with the prostate-specific antigen (PSA) test should only occur after a detailed discussion between the health-care provider and patient about the known risks and potential benefits of the test. In fact, guidelines strongly advise health-care providers to involve patients, particularly those at elevated risk of prostate cancer, in a "shared decision making" (SDM) process about PSA testing. We analyzed data from the National Cancer Institute's Health Information National Trends Survey 2011-2012-a nationally representative, cross-sectional survey-to examine the extent to which health professionals provided men with information critical to SDM prior to PSA testing, including (1) that patients had a choice about whether or not to undergo PSA testing, (2) that not all doctors recommend PSA testing, and (3) that no one is sure if PSA testing saves lives. Over half (55 %) of men between the ages of 50 and 74 reported ever having had a PSA test. However, only 10 % of men, regardless of screening status, reported receiving all three pieces of information: 55 % reported being informed that they could choose whether or not to undergo testing, 22 % reported being informed that some doctors recommend PSA testing and others do not, and 14 % reported being informed that no one is sure if PSA testing actually saves lives. Black men and men with lower levels of education were less likely to be provided this information. There is a need to improve patient-provider communication about the uncertainties associated with the PSA test. Interventions directed at patients, providers, and practice settings should be considered.
Keywords: prostate specific antigen; tumor marker; aged; attitude to health; blood; cross-sectional study; decision making; early cancer diagnosis; epidemiology; human; interpersonal communication; male; middle aged; patient care; patient participation; physician; procedures; prostate tumor; psychology; questionnaire; risk factor; United States

Research engagement among black men with prostate cancer - Toms, C.; Cahill, F.; George, G.; Van Hemelrijck, M. (ecancermedicalscience, 2016)
Background: Black men are three times more likely to develop prostate cancer (PCa) and often present with more aggressive disease. Nevertheless, black men are consistently underrepresented in research studies. We aimed to get more insight into the reasons for this reduced recruitment, as it is important for future research to include results that are also applicable to black men with PCa. Methods: Two focus groups (n = 10 and n = 6) of black males currently under treatment for PCa at Guys Hospital, London, UK were held to gather information regarding the understanding of and exposure to research, as well as the barriers and facilitators for recruitment into research studies. Results: Barriers to recruitment included; mistrust of researchers, lack of understanding of the research process and the mechanisms of PCa and a reliance on herbal medicine. Suggested facilitators for recruitment improvement included thorough explanations of the research process, media advertisement and word of mouth. Financial incentives were also discussed but received mixed reception. Conclusion: We uncovered a number of barriers to recruitment of black men with PCa into research and accompanying strategies for improving involvement. Many are consistent with the literature, emphasising that current efforts have not been successful in ameliorating the concerns of the black community. Beliefs in herbal medicine and aversion to financial incentives appear to be novel themes, and so further insight into these issues could prove beneficial.
Keywords: adult; advertising; article; Black person; cancer research; clinical article; comprehension; controlled study; health belief; herbal medicine; human; information processing; male; patient participation; prostate cancer; trust

Enrollment trends and disparity among patients with lung cancer in national clinical trials, 1990 to 2012 - Pang, H.H.; Wang, X.; Stinchcombe, T.E.; Wong, M.L.; Cheng, P.; Ganti, A.K.; Sargent, D.J.; Zhang, Y.; Hu, C.; Mandrekar, S.J.; Redman, M.W.; Manola, J.B.; et al. (Journal of Clinical Oncology, 2016)
Purpose: Under-representation of elderly, women, and racial/ethnic minority patients with cancer in clinical trials is of national concern. The goal of this study was to characterize enrollment trends and disparities by age, sex, and race/ethnicity in lung cancer trials. Methods: We analyzed data for 23,006 National Cancer Institute cooperative group lung cancer trial participants and 578,476 patients with lung cancer from the SEER registry from 1990 to 2012. The enrollment disparity difference (EDD) and enrollment disparity ratio (EDR) were calculated on the basis of the proportion of each subgroup in the trial population and the US lung cancer population. Annual percentage changes (APCs) in the subgroup proportions in each population were compared over time. Results: Enrollment disparity for patients ≥ 70 years of age with non-small-cell lung cancer improved from 1990 to 2012 (test of parallelism, P = .020), with a remaining EDD of 0.22 (95% CI, 0.19 to 0.25) and EDR of 1.65 (95% CI, 1.51 to 1.82) in 2010 to 2012. No improvement was seen for elderly patients with small-cell lung cancer (SCLC), with an APC of 0.20 (P = .714) among trial participants, despite a rising proportion of elderly patients with SCLC in the US population (APC, 0.32; P = .020). Enrollment disparity for women with lung cancer improved overall, with the gap closing by 2012 (EDD, 0.03 [95% CI, 0.00 to 0.06]; EDR, 1.07 [95% CI, 1.00 to 1.16]). Enrollment disparities persisted without significant improvement for elderly women, blacks, Asians/Pacific Islanders, and Hispanics. Conclusion: Under-representation in lung cancer trials improved significantly from 1990 to 2012 for elderly patients with non-small-cell lung cancer and for women, but ongoing efforts to improve the enrollment of elderly patients with SCLC and minorities are needed. Our study highlights the importance of addressing enrollment disparities by demographic and disease subgroups to better target under-represented groups of patients with lung cancer.
Keywords: age; aged; article; Asian; Black person; cancer registry; clinical trial (topic); comparative study; ethnic group; ethnicity; female; health care disparity; Hispanic; human; lung cancer; major clinical study; male; non small cell lung cancer; oncological parameters; overall survival; priority journal; race; senescence; sensitivity analysis; sex; small cell lung cancer; trend study; United States

A community-based trial of educational interventions with fecal immunochemical tests for colorectal cancer screening uptake among blacks in community settings - Christy, S.M.; Davis, S.N.; Williams, K.R.; Zhao, X.; Govindaraju, S.K.; Quinn, G.P.; Vadaparampil, S.T.; Lin, H.-Y.; Sutton, S.K.; Roethzeim, R.R.; Shibata, D.; Meade, C.D.; et al. (Cancer, 2016)
BACKGROUND: Intervention studies among individuals in diverse community settings are needed to reduce health disparities in colorectal cancer (CRC) screening and mortality rates. The current study compared the efficacy of 2 intervention conditions promoting CRC screening among black individuals. METHODS: Black individuals ages 50 to 75 years (N = 330) were recruited in community settings in 4 Tampa Bay counties. After obtaining consent and conducting a baseline interview to assess sociodemographic and health-related variables, participants received either a culturally targeted CRC photonovella booklet plus a fecal immunochemical test (FIT) kit or a standard CRC screening brochure plus an FIT kit. The primary outcome was FIT kit screening uptake. RESULTS: FIT screening uptake at 6 months was 86.7% overall (90.3% in the brochure group and 81.9% in the photonovella group). Controlling for baseline between-group differences, there was no influence of intervention on FIT kit uptake (P =.756). Significant predictors of not returning an FIT kit included being unable to work (P =.010), having higher religious belief scores (P =.015), and living farther from the cancer center (P =.015). CONCLUSIONS: Providing FIT kits and educational print materials to black individuals in community settings resulted in high rates of CRC screening. The study also identified subgroups of participants who were less likely to return an FIT kit and provides insight for future interventions. Cancer 2016;122:3288–3296. © 2016 American Cancer Society.
Keywords: adult; aged; article; Black person; cancer screening; colorectal cancer; occult blood test; feces analysis; female; health behavior; health care utilization; health education; health promotion; human; immunochemistry; immunology test kit; intermethod comparison; male; priority journal; religion; residential area; risk factor; work

Zinc intake and risk of prostate cancer: Case-control study and meta-analysis - Mahmoud, A.M.; Al-Alem, U.; Dabbous, F.; Ali, M.M.; Batai, K.; Shah, E.; Kittles, R.A. (PLoS ONE, 2016)
Zinc is an essential dietary element that has been implicated in the pathogenesis of prostate cancer, a cancer that disproportionately affects men of African descent. Studies assessing the association of zinc intake and prostate cancer have yielded inconsistent results. Furthermore, very little is known about the relationship between zinc intake and prostate cancer among African Americans. We examined the association between self-reported zinc intake and prostate cancer in a hospital-based case-control study of African Americans. We then compared our results with previous studies by performing a meta-analysis to summarize the evidence regarding the association between zinc and prostate cancer. Newly diagnosed African American men with histologically confirmed prostate cancer (n = 127) and controls (n = 81) were recruited from an urban academic urology clinic in Washington, DC. Controls had higher zinc intake, with a mean of 14 mg/day versus 11 mg/day for cases. We observed a non-significant, non-linear increase in prostate cancer when comparing tertiles of zinc intake (OR <6.5sv6.5-12.5mg/day 1.8, 95% CI: 0.6,5.6; OR <6.5 vs>12.5mg/day 1.3, 95% CI: 0.2,6.5). The pooled estimate from 17 studies (including 3 cohorts, 2 nested case-control, 11 case-control studies, and 1 randomized clinical trial, with a total of 111,199 participants and 11,689 cases of prostate cancer) was 1.07hi vs lo 95% CI: 0.98-1.16. Using a dose-response meta-analysis, we observed a non-linear trend in the relationship between zinc intake and prostate cancer (p for nonlinearity = 0.0022). This is the first study to examine the relationship between zinc intake in black men and risk of prostate cancer and systematically evaluate available epidemiologic evidence about the magnitude of the relationship between zinc intake and prostate cancer. Despite of the lower intake of zinc by prostate cancer patients, our meta-analysis indicated that there is no evidence for an association between zinc intake and prostate cancer.
Keywords: zinc; adult; African American; aged; article; cancer risk; cohort analysis; controlled study; dietary intake; disease association; District of Columbia; evidence based practice; histopathology; hospital based case control study; human; major clinical study; male; prostate cancer; randomized controlled trial (topic); risk assessment; self report; systematic review; trend study

Colorectal Cancer Screening in Vulnerable Patients: Promoting Informed and Shared Decisions - Brenner, A.T.; Hoffman, R.; McWilliams, A.; Pignone, M.P.; Rhyne, R.L.; Tapp, H.; Weaver, M.A.; Callan, D.; de Hernandez, B.U.; Harbi, K.; Reuland, D.S. (American Journal of Preventive Medicine, 2016)
Introduction Low-income, low-literacy, limited English-proficient populations have low colorectal cancer (CRC) screening rates and experience poor patient-provider communication and decision-making processes around screening. The purpose of this study was to test the effect of a CRC screening decision aid on screening-related communication and decision making in primary care visits. Study design RCT with data collected from patients at baseline and immediately after the provider encounter. Setting/participants Patients aged 50–75 years, due for CRC screening, were recruited from two safety net clinics in North Carolina and New Mexico (data collection, January 2014–September 2015; analysis, 2015). Intervention Participants viewed a CRC screening decision aid or a food safety (control) video immediately before their provider encounter. Main outcome measures CRC screening-related knowledge, discussion, intent, test preferences, and test ordering. Results The study population (N=262) had a mean age of 58.3 years and was 66% female, 61% Latino, 17% non-Latino black, and 16% non-Latino white. Among Latino participants, 71% preferred Spanish. Compared with controls, intervention participants had greater screening-related knowledge (on average 4.6 vs 2.8 of six knowledge items correct, adjusted difference [AD]=1.8, 95% CI=1.5, 2.1) and were more likely to report screening discussion (71.0% vs 45.0%, AD=26.1%, 95% CI=14.3%, 38.0%) and high screening intent (93.1% vs 84.7%, AD=9.0%, 95% CI=2.0%, 16.0%). Intervention participants were more likely to indicate a specific screening test preference (93.1% vs 68.0%, AD=26.5%, 95% CI=17.2%, 35.8%) and to report having a test ordered (56.5% vs 32.1%, AD=25.8%, 95% CI=14.4%, 37.2%). Conclusions Viewing a CRC screening decision aid before a primary care encounter improves knowledge and shared decision making around screening in a racially, ethnically, and linguistically diverse safety net clinic population. Trial registration This study is registered at www.clinicaltrials.gov NCT02054598.
Keywords: adult; aged; article; cancer screening; colorectal cancer; controlled study; female; food safety; Hispanic; human; information dissemination; intervention study; knowledge; major clinical study; male; New Mexico; North Carolina; patient decision making; patient information; patient preference; primary medical care; randomized controlled trial; screening test; vulnerable population

Use of Cancer Genetics Services in African-American Young Breast Cancer Survivors - Jones, T.; Lockhart, J.S.; Mendelsohn-Victor, K.E.; Duquette, D.; Northouse, L.L.; Duffy, S.A.; Donley, R.; Merajver, S.D.; Milliron, K.J.; Roberts, J.S.; Katapodi, M.C. (American Journal of Preventive Medicine, 2016)
Introduction African-American women have higher rates of early-onset breast cancer compared with their Caucasian counterparts; yet, when diagnosed with breast cancer at a young age, they underuse genetic counseling and testing to manage their risk of developing future cancers. Methods Self-reported baseline data were collected between September 2012 and January 2013 and analyzed in 2014 from a subpopulation of 340 African-American young breast cancer survivors (YBCSs) enrolled in an RCT. YBCSs were diagnosed with invasive breast cancer or ductal carcinoma in situ between ages 20 and 45 years and were randomly selected from a statewide cancer registry. Logistic regression examined predictors of using cancer genetics services. Results Overall, 28% of the sample reported having genetic counseling and 21% reported having genetic testing, which were significantly lower (p≤0.005) compared with white/other YBCSs participating in the parent study. In a multivariate analysis, income was positively associated with counseling (B=0.254, p≤0.01) and testing (B=0.297, p≤0.01), whereas higher education levels (B=−0.328, p≤0.05) and lack of access to healthcare services owing to cost (B=−1.10, p≤0.03) were negatively associated with genetic counseling. Lower income and lack of care because of high out-of-pocket costs were commonly reported barriers. Conclusions Despite national recommendations for genetic evaluation among women with early-onset breast cancer, few African-American YBCSs reported undergoing genetic counseling and testing. Most reported that their healthcare provider did not recommend these services. Interventions addressing patient, provider, and structural healthcare system barriers to using genetic counseling and testing in this population are needed.
Keywords: NCT01612338; adult; African American; article; breast cancer; breast carcinoma; cancer genetics; cancer registry; cancer survivor; controlled study; educational status; female; genetic counseling; genetic screening; genetic service; health care cost; health service; human; logistic regression analysis; major clinical study; multivariate analysis; patient-reported outcome; randomized controlled trial; tumor invasion

Chemoprevention in African american men with prostate cancer - Kumar, N.B.; Pow-Sang, J.M.; Spiess, P.E.; Park, J.Y.; Chornokur, G.; Leone, A.R.; Phelan, C.M. (Cancer Control, 2016)
Background: Recommendations for cancer screening are uncertain for the early detection or prevention of prostate cancer in African American men. Thus, chemoprevention strategies are needed to specifically target African American men. Methods: The evidence was examined on the biological etiology of disparities in African Americans related to prostate cancer. Possible chemopreventive agents and biomarkers critical to prostate cancer in African American men were also studied. Results: High-grade prostatic intraepithelial neoplasia may be more prevalent in African American men, even after controlling for age, prostate-specific antigen (PSA) level, abnormal results on digital rectal examination, and prostate volume. Prostate cancer in African American men can lead to the overexpression of signaling receptors that may mediate increased proliferation, angiogenesis, and decreased apoptosis. Use of chemopreventive agents may be useful for select populations of men. Conclusions: Green tea catechins are able to target multiple pathways to address the underlying biology of prostate carcinogenesis in African American men, so they may be ideal as a chemoprevention agent in these men diagnosed with high-grade prostatic intraepithelial neoplasia.
Keywords: dutasteride; epigallocatechin gallate; finasteride; sinecatechins; placebo; prostate specific antigen; African American; age; apoptosis; article; cancer grading; cell proliferation; chemoprophylaxis; digital rectal examination; drug efficacy; drug safety; gene overexpression; health care disparity; human; male; nonhuman; patient selection; phase 1 clinical trial (topic); phase 2 clinical trial (topic); phase 3 clinical trial (topic); prevalence; prostate cancer; prostate volume; tumor vascularization

Cluster Randomized Trial of a Church-Based Peer Counselor and Tailored Newsletter Intervention to Promote Colorectal Cancer Screening and Physical Activity Among Older African Americans - Leone, L.A.; Allicock, M.; Pignone, M.P.; Walsh, J.F.; Johnson, L.-S.; Armstrong-Brown, J.; Carr, C.C.; Langford, A.; Ni, A.; Resnicow, K.; Campbell, M.K. (Health education & behavior : the official publication of the Society for Public Health Education, 2016)
Action Through Churches in Time to Save Lives (ACTS) of Wellness was a cluster randomized controlled trial developed to promote colorectal cancer screening and physical activity (PA) within urban African American churches. Churches were recruited from North Carolina (n = 12) and Michigan (n = 7) and were randomized to intervention (n = 10) or comparison (n = 9). Intervention participants received three mailed tailored newsletters addressing colorectal cancer screening and PA behaviors over approximately 6 months. Individuals who were not up-to-date for screening at baseline could also receive motivational calls from a peer counselor. The main outcomes were up-to-date colorectal cancer screening and Metabolic Equivalency Task (MET)-hours/week of moderate-vigorous PA. Multivariate analyses examined changes in the main outcomes controlling for church cluster, gender, marital status, weight, and baseline values. Baseline screening was high in both intervention (75.9%, n = 374) and comparison groups (73.7%, n = 338). Screening increased at follow-up: +6.4 and +4.7 percentage points for intervention and comparison, respectively (p = .25). Baseline MET-hours/week of PA was 7.8 (95% confidence interval [6.8, 8.7]) for intervention and 8.7 (95% confidence interval [7.6, 9.8]) for the comparison group. There were no significant changes (p = .15) in PA for intervention (-0.30 MET-hours/week) compared with the comparison (-0.05 MET-hours/week). Among intervention participants, PA increased more for those who participated in church exercise programs, and screening improved more for those who spoke with a peer counselor or recalled the newsletters. Overall, the intervention did not improve PA or screening in an urban church population. These findings support previous research indicating that structured PA opportunities are necessary to promote change in PA and churches need more support to initiate effective peer counselor programs.
Keywords: African American; aged; attitude to health; clinical trial; colonoscopy; colorectal tumor; controlled study; counseling; early cancer diagnosis; ethnology; exercise; female; health promotion; human; male; Michigan; middle aged; multicenter study; multivariate analysis; North Carolina; procedures; program evaluation; psychology; publication; questionnaire; randomized controlled trial; religion; social support

Casting a Wider Net: Engaging Community Health Worker Clients and Their Families in Cancer Prevention - Roman, L.A.; Zambrana, R.E.; Ford, S.; Meghea, C.; Williams, K.P. (Preventing chronic disease, 2016)
Engaging family members in an intervention to prevent breast and cervical cancer can be a way to reach underserved women; however, little is known about whether family member recruitment reaches at-risk women. This study reports the kin relationship and risk characteristics of family members who chose to participate in the Kin Keeper(SM) cancer prevention intervention, delivered by community health workers (CHWs) via existing community programs. African American, Latina, and Arab family members reported risk factors for inadequate screening, including comorbid health conditions and inadequate breast or cervical cancer literacy. CHW programs can be leveraged to reach underserved families with cancer preventive interventions.
Keywords: adult; attitude to health; breast tumor; controlled study; early cancer diagnosis; education; ethnic group; family; female; health auxiliary; human; mass screening; Michigan; middle aged; neoplasm; patient attitude; randomized controlled trial; statistics and numerical data; uterine cervix tumor

Management of uterine fibroids: A focus on uterine-sparing interventional techniques - Silberzweig, J.E.; Powell, D.K.; Matsumoto, A.H.; Spies, J.B. (Radiology, 2016)
Uterine fibroids occur in approximately 50% of women over the age of 40 years, and an estimated 50% of those are symptomatic. Menorrhagia is the most common symptom and the primary indication for treatment, although bulk symptoms often occur and can be treated. Pharmacotherapy is typically inadequate unless it can be expected to successfully bridge to menopause or allow for a less-invasive intervention. However, hormonal therapies have risks. Hysterectomy is still the most commonly performed procedure for symptomatic fibroids and has the lowest rate of reintervention (compared with myomectomy or uterine artery embolization [UAE]), but rates of more serious complications are higher and patient satisfaction and ability to return to normal activities may also be less favorable. Myomectomy is not necessarily less morbid than hysterectomy and may have a greater failure rate than UAE. Techniques and devices vary with little standardization, and operator experience is crucial to success. The largest studies of UAE show very low rates of serious complications and rapid recovery. UAE significantly improves symptoms related to uterine fibroids in 85%-90% of patients. Herein, this article will discuss the nature of fibroids and their diagnosis, pharmacotherapy, surgical treatment, and nonsurgical interventional treatment, including UAE and magnetic resonance-guided focused ultrasound.
Keywords: chemokine; cytokine; growth factor; leuprorelin; levonorgestrel; oral contraceptive agent; progesterone receptor; acne; adenomyosis; African American; anemia; aortography; arterial embolization; article; Asian; body weight disorder; breast tenderness; Caucasian; cerebrovascular accident; connective tissue; conservative treatment; diabetes mellitus; extracellular matrix; female; fluid retention; gallstone; high intensity focused ultrasound; Hispanic; hormonal therapy; human; hypertension; hysterectomy; liver adenoma; menopausal syndrome; menopause; menorrhagia; menstruation; mood disorder; myomectomy; nuclear magnetic resonance; nuclear magnetic resonance imaging; pathogenesis; patient satisfaction; patient selection; priority journal; risk reduction; sexual dysfunction; sexual function; standardization; symptomatology; treatment indication; ultrasound therapy; uterine artery; uterine artery embolization; uterus myoma; venous thromboembolism; eligard

Factors associated with continuous low-dose heparin infusion for central venous catheter patency in critically ill children worldwide - Onyeama, S.-J.N.; Hanson, S.J.; Dasgupta, M.; Hoffmann, R.G.; Faustino, E.V.S. (Pediatric Critical Care Medicine, 2016)
Objectives: To identify patient, hospital, and central venous catheter factors that may influence the use of low-dose heparin infusion for central venous catheter patency in critically ill children. Design: Secondary analysis of an international multicenter observational study. Setting: Fifty-nine PICUs over four study dates in 2012, involving seven countries. Patients: Children less than 18 years old with a central venous catheter who were admitted to a participating unit and enrolled in the completed Prophylaxis against Thrombosis Practice study were included. All overflow patients were excluded. Interventions: None. Measurements and Main Results: Of the 2,484 patients in the Prophylaxis against Thrombosis Practice study, 1,312 patients had a central venous catheter. Five hundred seven of those patients used low-dose heparin infusion. The frequency of low-dose heparin infusion was compared across various patient, hospital, and central venous catheter factors using chi-square, Mann-Whitney U, and Fisher exact tests. In the multivariate analysis, age was not a significant factor for low-dose heparin infusion use. Patients with pulmonary hypertension had decreased low-dose heparin infusion use, whereas those with active surgical or trauma diagnoses had increased low-dose heparin infusion use. All centrally inserted central venous catheters were more likely to use low-dose heparin infusion when compared with peripherally inserted central venous catheters. The Asia-Pacific region showed increased low-dose heparin infusion use, along with community hospitals and smaller ICUs (< 10 beds). Conclusions: Patient, central venous catheter, and hospital factors are associated with the use of low-dose heparin infusion in critically ill children. Further study is needed to evaluate the efficacy and persistence of low-dose heparin infusion use.
Keywords: central venous catheter; peripherally inserted central venous catheter; acetylsalicylic acid; antivitamin K; heparin; low molecular weight heparin; adolescent; age; article; Asia; Asian; Australia; Black person; bleeding tendency; brain hemorrhage; Canada; catheter thrombosis; Caucasian; cavopulmonary connection; central venous catheter; cerebrovascular accident; child; childhood cancer; community hospital; continuous infusion; craniotomy; critically ill patient; femoral vein; heart catheterization; heart surgery; heparinization; Hispanic; home care; hospitalized child; human; infant; intensive care unit; internal jugular vein; low drug dose; major clinical study; multicenter study (topic); New Zealand; newborn; parenteral nutrition; peripheral vascular system; peripherally inserted central venous catheter; Portugal; priority journal; pulmonary hypertension; race difference; retrospective study; secondary analysis; sickle cell anemia; Spain; subclavian vein; thorax; thrombosis prevention; umbilical cord; United States

Impact of race, ethnicity, and BMI on achievement of pathologic complete response following neoadjuvant chemotherapy for breast cancer: a pooled analysis of four prospective Alliance clinical trials (A151426) - Warner, E.T.; Ballman, K.V.; Strand, C.; Boughey, J.C.; Buzdar, A.U.; Carey, L.A.; Sikov, W.M.; Partridge, A.H. (Breast Cancer Research and Treatment, 2016)
Previous studies demonstrated poor response to neoadjuvant systemic therapy (NST) for breast cancer among black women and women who are overweight or obese, but this may be due to chemotherapy underdosing. We assessed associations of race, ethnicity, and body mass index (BMI) with pathologic complete response (pCR) in clinical trial populations. 1797 women enrolled in four NST trials (CALGB 40601, 40603; ACOSOG Z1041, Z1071) were included. Tumor subtypes were defined by estrogen receptor (ER) and HER2 status. Logistic regression generated odds ratios (OR) and 95 % confidence intervals (CI) for the associations of race, ethnicity, and BMI with in-breast pCR adjusting for subtype, study arm, lymph node status, tumor size, and tumor grade. 253 (14.1 %) were black, 199 (11.1 %) Hispanic, 520 (28.9 %) overweight, and 743 (41.4 %) obese. Compared to whites, Blacks and Hispanics were more likely to be obese and Blacks were more likely to have triple-negative cancer. pCR rates differed significantly by tumor subtype. In multivariate analyses, neither race (black vs white: OR 1.18, 95 % CI 0.85–1.62) nor ethnicity (Hispanic vs non-Hispanic; OR 1.30, 95 % CI 0.67–2.53) were significant predictors of pCR overall or by subtype. Overweight and obese women had lower pCR rates in ER+/HER2+, but higher pCR rates in ER−/HER2+ cancers. There was no difference in pCR according to race or ethnicity. Overall, there was no major difference in pCR rates by BMI. These findings suggest that pCR with optimally dosed NST is a function of tumor, rather than patient, biology.
Keywords: epidermal growth factor receptor 2; estrogen receptor; adjuvant chemotherapy; adult; article; Black person; body mass; breast cancer; cancer grading; Caucasian; ethnic difference; ethnicity; female; Hispanic; human; major clinical study; obesity; priority journal; prospective study; treatment response; triple negative breast cancer; tumor volume

Black hood assisted colonoscopy for detection of colorectal polyps: A prospective randomized controlled study - Huang, R.-X.; Xiao, Z.-L.; Li, F.; Ji, D.-N.; Zhou, J.; Xiang, P.; Bao, Z.-J. (European Review for Medical and Pharmacological Sciences, 2016)
OBJECTIVE: Colonoscopy is considered as a standard method for detecting various kinds of colorectal polyps. However, conventional colonoscopy (CC) still has chances to miss some lesions. Some scholars have already repor ted that transparent hood assisted colonoscopy (THAC) can improve the detection rate of colorectal polyps. However, the efficacy of detection of colorectal polyps with black hood assisted colonoscopy (BHAC) is still unclear. In this study, BHAC was compared with CC for evaluating the efficacy of detection of colorectal polyps. PATIENTS AND METHODS: Between Sep 2014 and Apr 2015, 542 patients underwent CC and meanwhile 534 patients underwent BHAC were enrolled into this prospective randomized controlled study. Comparison of baseline characteristics, cecal intubation time, withdrawal time, total number of detected polyps, detection rate of polyps, location, size, morphology and pathological diagnosis of polyps between these two groups was performed. RESULTS: Cecal intubation time was significantly shorter in BHAC group than in CC group (6.31 ± 3.51 min vs. 7.05 ± 4.15 min, p = 0.002). The total number of detected polyps and detection rate of polyps were significantly higher in BHAC group than in CC group (349/65.36% vs. 264/48.71%, p = 0.004). CONCLUSIONS: Compared with CC, BHAC could significantly improve the detection rate of colorectal polyps, and cecal intubation time was significantly reduced by BHAC.
Keywords: DCD-15006755; black hood; endoscopic accessory; adult; article; black hood; black hood assisted colonoscopy; cancer diagnosis; cancer morphology; cecum intubation time; cecum intubation withdrawal time; colonoscope; colonoscopy; colorectal polyp; comparative effectiveness; controlled study; conventional colonoscopy; demography; endoscopic accessory; female; follow up; human; intermethod comparison; major clinical study; male; middle aged; polyp detection rate; prospective study; randomized controlled trial; time; total number of detected polyp; tumor localization; tumor volume; CF-H260; MAJ-1991

Tamoxifen dose escalation in patients with diminished CYP2D6 activity normalizes endoxifen concentrations without increasing toxicity - Hertz, D.L.; Deal, A.; Ibrahim, J.G.; Walko, C.M.; Weck, K.E.; Anderson, S.; Magrinat, G.; Olajide, O.; Moore, S.; Raab, R.; Carrizosa, D.R.; Corso, S.; et al. (Oncologist, 2016)
Background. Polymorphic CYP2D6 is primarily responsible for metabolic activation of tamoxifen to endoxifen. We previously reported that by increasing the daily tamoxifen doseto 40mg/day in CYP2D6 intermediate metabolizer (IM), but not poor metabolizer (PM), patients achieve endoxifen concentrations similar to those of extensive metabolizer patients on 20 mg/day. We expanded enrollment to assess the safety of CYP2D6 genotypeguided dose escalation and investigate concentration differences between races. Methods. PM and IM breast cancer patients currently receiving tamoxifen at 20 mg/day were enrolled for genotype-guided escalation to 40 mg/day. Endoxifen was measured at baseline and after 4 months. Quality-of-life datawere collected using the Functional Assessment of Cancer Therapy-Breast (FACT-B) and Breast Cancer Prevention Trial Menopausal Symptom Scale at baseline and after 4 months. Results. In 353 newly enrolled patients, genotype-guided dose escalation eliminated baseline concentration differences in IM (p = .08), but not PM (p = .009), patients. Endoxifen concentrations were similar in black and white patients overall (p = .63) and within CYP2D6 phenotype groups (p>.05). In the quality-oflife analysis of 480 patients, dose escalation did not meaningfully diminish quality of life; infact,improvements were seen in several measures including the FACT Breast Cancer subscale (p 5 .004) and limitations in range of motion (p>.0001) in IM patients. Conclusion. Differences in endoxifen concentration during treatment can be eliminated by doubling the tamoxifen dose in IM patients, without an appreciable effecton quality of life. Validation of the association between endoxifen concentration and efficacy or prospective demonstration of improvedefficacy is necessary to warrant clinical uptake of this personalized treatment strategy.
Keywords: cytochrome P450 2D6; endoxifen; tamoxifen; adult; article; blood sampling; breast cancer; breast tenderness; cancer patient; drug dose escalation; drug dose increase; enzyme activity; female; genotype; high performance liquid chromatography; hormonal therapy; human; major clinical study; menopause; phenotype; priority journal; quality of life; race; tandem mass spectrometry; vagina bleeding; vaginal dryness; vomiting

Systems analysis of the prostate transcriptome in African-American men compared with European-American men - Hardiman, G.; Savage, S.J.; Hazard, E.S.; Wilson, R.C.; Courtney, S.M.; Smith, M.T.; Hollis, B.W.; Halbert, C.H.; Gattoni-Celli, S. (Pharmacogenomics, 2016)
Aim: African-Americans (AA) have increased prostate cancer risk and a greater mortality rate than European-Americans (EA). AA exhibit a high prevalence of vitamin D deficiency. We examined the global prostate transcriptome in AA and EA, and the effect of vitamin D3 supplementation. Patients & methods: Twenty-seven male subjects (ten AA and 17 EA), slated to undergo prostatectomy were enrolled in the study. Fourteen subjects received vitamin D3 (4000 IU daily) and 13 subjects received placebo for 2 months prior to surgery. Results: AA show higher expression of genes associated with immune response and inflammation. Conclusion: Systems level analyses support the concept that Inflammatory processes may contribute to disease progression in AA. These transcripts can be modulated by a short course of vitamin D3 supplementation.
Keywords: colecalciferol; growth differentiation factor 15; placebo; transcriptome; vitamin D; adult; African American; aged; article; cancer mortality; cancer risk; clinical article; controlled study; disease course; European American; gene expression; gene expression profiling; Gleason score; high throughput sequencing; human; human tissue; immune response; inflammation; male; middle aged; open study; prevalence; prostate biopsy; prostate cancer; prostatectomy; race difference; randomized controlled trial; system analysis; vitamin D deficiency; vitamin supplementation

Promoting Mammography with African-American Women in the Emergency Department Using Lay Health Workers - Hatcher, J.; Schoenberg, N.E.; Dignan, M.; Rayens, M.K. (Journal of National Black Nurses' Association : JNBNA, 2016)
The objective of this study was to test the efficacy of a pilot intervention to increase mammography utilization among African-American women recruited from those waiting in the emergency department (ED)for non-urgent complaints. In a 3-armed pilot of a randomized controlled trial we compared the effects of a brief motivational interview delivered by a lay health worker with those of a culturally targeted brochure and a usual care control group. The results showed that one quarter (23%) of the sample reported having never had a mammogram prior to the study. There was no group difference by mammography status at the 3-month interview. More than one quarter of those retained in the study indicated they had received a mammogram during the study (27.4%). The conclusions from the study were that lay health workers are a valuable asset and may be used in innovative settings such as the ED to increase screening among vulnerable populations.
Keywords: adult; African American; aged; breast tumor; comparative study; emergency health service; female; health care personnel; health promotion; human; human relation; mammography; middle aged; patient education; pilot study; procedures; psychology; publication; United States; very elderly

Baseline subject characteristics predictive of compliance with study-mandated prostate biopsy in men at risk of prostate cancer: Results from REDUCE - Fischer, S.; Sun, S.; Howard, L.E.; Moreira, D.M.; Castro-Santamaria, R.; Andriole, G.L.; Vidal, A.C.; Freedland, S.J. (Prostate Cancer and Prostatic Diseases, 2016)
Background:Study compliance is crucial when the study outcome is determined by an invasive procedure, such as prostate biopsy. To investigate predictors of compliance in study-mandated prostate biopsies, we analyzed demographic, clinical and reported lifestyle data from the REDUCE trial.Methods:We retrospectively identified 8025 men from REDUCE with at least 2 years of follow-up, and used multivariable logistic regression to test the association between baseline demographic and clinical characteristics and undergoing the study-mandated prostate biopsy at 2 years. We then examined whether missing any of these data was associated with undergoing a biopsy.Results:In REDUCE, 22% of men did not undergo a 2-year biopsy. On multivariable analysis, the non-North American region was predictive of 42-44% increased likelihood of undergoing a 2-year biopsy (P≤0.001). Being enrolled at a center that enrolled >10 subjects (2nd and 3rd tertile) was associated with a 42-48% increased likelihood of undergoing a 2-year biopsy (P<0.001). In addition, black race predicted 44% lower rate of on-study 2-year biopsy (odds ratio (OR)=0.56; P=0.001). Finally, missing one or more baseline variables was associated with a 32% decreased likelihood of undergoing a 2-year biopsy (OR=0.68; P<0.001).Conclusions:In REDUCE, men outside North America, those at higher volume centers and those with complete baseline data were more likely to undergo study-mandated 2-year biopsies. Given prostate biopsy is becoming increasingly utilized as an endpoint in trials that are often multi-national, regional differences in compliance should be considered when designing future trials. Likewise, efforts are needed to ensure compliance in low-volume centers or among subjects missing baseline data.
Keywords: aged; alcohol consumption; article; attitude to illness; cancer risk; cancer screening; controlled study; data analysis; demography; family history; female; follow up; human; human tissue; lifestyle; major clinical study; North America; patient attitude; prediction; priority journal; prostate biopsy; prostate cancer; race difference; retrospective study; risk factor; self report; smoking

National trends in nonoperative management of rectal adenocarcinoma - Ellis, C.T.; Samuel, C.A.; Stitzenberg, K.B. (Journal of Clinical Oncology, 2016)
Purpose Neoadjuvant chemoradiation for stage II/III rectal cancer results in up to 49% of patients with a clinical complete response. As a result, many have questioned whether surgery can be omitted for this group of patients. Currently, there is insufficient evidence for chemoradiation only, or nonoperative management (NOM), to support its adoption. Despite this, anecdotal evidence suggests there is a trend toward increased use of NOM. Our objective was to examine the use of NOM for rectal cancer over time, as well as the patient- And facility-level factors associated with its use. Methods We included all incident cases of invasive, nonmetastatic rectal adenocarcinoma reported to the National Cancer Database from 1998 to 2010. We performed univariate and multivariate analyses to assess for NOM use over time, as well as associated patient- And facility-level factors. Results A total of 146,135 patients met the inclusion criteria: 5,741 had NOM and 140,394 had surgery with or without additional therapy. From 1998 to 2010, NOM doubled, from 2.4% to 5% of all cases annually. Patients who were black (adjusted odds ratio [AOR], 1.71; 95% CI, 1.57 to 1.86), uninsured (AOR, 2.35; 95% CI, 2.08 to 2.65) or enrolled in Medicaid (AOR, 2.10; 95% CI, 1.90 to 2.33), or treated at low-volume facilities (AOR, 1.53; 95% CI, 1.42 to 1.64) were more likely to receive NOM than were patients who were white, privately insured, and treated at a high-volume facility, respectively. Conclusion NOM demonstrates promise for the treatment of rectal cancer; currently, however, the most appropriate strategy is to pursue this approach with well-informed patients in the context of a clinical trial. We observed evidence of increasing NOM use, with this increase occurring more frequently in black and uninsured/Medicaid patients, raising concern that increased NOM use may actually represent increasing disparities in rectal cancer care rather than innovation. Further studies are needed to assess survival differences by treatment strategy.
Keywords: antineoplastic agent; adult; aged; article; cancer chemotherapy; cancer radiotherapy; Caucasian; Charlson Comorbidity Index; chemoradiotherapy; education; female; human; income; major clinical study; male; medicaid; priority journal; race; rectum carcinoma; social status; travel; tumor invasion; very elderly

A prospective cohort study of treatment decision-making for prostate cancer following participation in a multidisciplinary clinic - Hurwitz, L.M.; Cullen, J.; Elsamanoudi, S.; Kim, D.J.; Hudak, J.; Colston, M.; Travis, J.; Kuo, H.-C.; Porter, C.R.; Rosner, I.L. (Urologic Oncology: Seminars and Original Investigations, 2016)
Background: Patients diagnosed with prostate cancer (PCa) are presented with several treatment options of similar efficacy but varying side effects. Understanding how and why patients make their treatment decisions, as well as the effect of treatment choice on long-term outcomes, is critical to ensuring effective, patient-centered care. This study examined treatment decision-making in a racially diverse, equal-access, contemporary cohort of patients with PCa counseled on treatment options at a multidisciplinary clinic. Methods: A prospective cohort study was initiated at the Walter Reed National Military Medical Center (formerly Walter Reed Army Medical Center) in 2006. Newly diagnosed patients with PCa were enrolled before attending a multidisciplinary clinic. Patients completed surveys preclinic and postclinic to assess treatment preferences, reasons for treatment choice, and decisional regret. Results: As of January 2014, 925 patients with PCa enrolled in this study. Surgery (54%), external radiation (20%), and active surveillance (12%) were the most common primary treatments for patients with low- and intermediate-risk PCa, whereas patients with high-risk PCa chose surgery (34%) or external radiation with neoadjuvant hormones (57%). Treatment choice differed by age at diagnosis, race, comorbidity status, and calendar year in both univariable and multivariable analyses. Patients preferred to play an active role in the decision-making process and cited doctors at the clinic as the most helpful source of treatment-related information. Almost all patients reported satisfaction with their decision. Conclusions: This is one of the first prospective cohort studies to examine treatment decision-making in an equal-access, multidisciplinary clinic setting. Studies of this cohort would aid in understanding and improving the PCa decision-making process.
Keywords: adult; African American; age distribution; article; cancer adjuvant therapy; cancer center; cancer epidemiology; cancer surgery; cancer therapy; cohort analysis; comorbidity; educational status; hormonal therapy; human; intermediate risk patient; low risk patient; major clinical study; male; middle aged; patient care; patient decision making; patient participation; patient preference; priority journal; prospective study; prostate cancer; quality of life; race difference

Effects of adjuvant chemotherapy on recurrence, survival, and quality of life in stage II colon cancer patients: a 24-month follow-up - Lewis, C.; Xun, P.; He, K. (Supportive Care in Cancer, 2016)
Purpose: The purpose of this cohort study was to investigate the association of adjuvant chemotherapy with quality of life (QoL), survival, and recurrence over the 24 months following diagnosis in stage II colon cancer patients. Methods: Overall, 453 patients were recruited from North Carolina from 2009 to 2011 and interviewed with a closed-ended survey detailing quality of life, health behaviors, treatment, and cancer recurrence at three times points: diagnosis, 12-, and 24-months post-diagnosis; mortality was obtained via the National Death Index. Results: In sum, 265 patients received chemotherapy. Receipt of chemotherapy exhibited an inverse association with total Functional Assessment of Cancer Treatment (FACT)-General (P < 0.01), FACT-Colorectal (P < 0.01), physical (P < 0.01), emotional (P = 0.02), and functional (P < 0.01) well-being; the inverse association between receiving chemotherapy and emotional well-being persisted for Caucasians but not African Americans (Pinteraction = 0.049). Those who received chemotherapy demonstrated significantly higher odds of cancer recurrence (odds ratio (OR) 2.74; 95 % confidence interval (CI) 1.18, 6.35) and all-cause mortality (OR: 1.95; 95 % CI: 1.05, 3.62). Conclusions: In this study, stage II colon cancer patients who received chemotherapy treatment were more likely to have poor QoL, recurrence, and all-cause mortality after 24 months compared to those who did not receive chemotherapy. Future research focusing on subtypes of chemotherapy treatment, as well as a longer follow-up period, is needed.
Keywords: adjuvant chemotherapy; adult; African American; aged; article; cancer mortality; cancer patient; cancer prognosis; cancer recurrence; cancer survival; Caucasian; clinical assessment tool; cohort analysis; colon cancer; Colorectal Cancer Subscale; confidence interval; controlled study; correlation analysis; emotion; female; follow up; Functional Assessment of Cancer Therapy Colorectal; Functional Assessment of Cancer Therapy General; functional status; health behavior; human; major clinical study; male; Mental Component Score; Physical Component Score; Physical Social Emotional and Functional Wellbeing scale; priority journal; prospective study; quality of life; Short Form 12; treatment outcome; Trial Outcome Index Physical Functional Colorectal score; United States

Randomized sham-controlled pilot trial of weekly electro-acupuncture for the prevention of taxane-induced peripheral neuropathy in women with early stage breast cancer - Greenlee, H.; Crew, K.D.; Capodice, J.; Awad, D.; Buono, D.; Shi, Z.; Jeffres, A.; Wyse, S.; Whitman, W.; Trivedi, M.S.; Kalinsky, K.; Hershman, D.L. (Breast Cancer Research and Treatment, 2016)
To investigate the effect of electro-acupuncture (EA) as a non-pharmacological intervention to prevent or reduce chemotherapy-induced peripheral neuropathy (CIPN) in breast cancer patients undergoing chemotherapy of taxane. Women with stage I-III breast cancer scheduled to receive taxane therapy were randomized to receive a standardized protocol of 12 true or sham EA (SEA) weekly treatments concurrent with taxane treatment. Subjects completed the Brief Pain Inventory-Short Form (BPI-SF), Functional Assessment of Cancer Therapy-Taxane neurotoxicity subscale (FACT-NTX), and other assessments at baseline and weeks 6, 12, and 16. A total of 180 subjects were screened, 63 enrolled and 48 completed week 16 assessments. Mean age was 50 with 25 % white, 25 % black, and 43 % Hispanic; 52 % had no prior chemotherapy. At week 12, both groups reported an increase in mean BPI-SF worst pain score, but no mean differences were found between groups (SEA 2.8 vs. EA 2.6, P = .86). By week 16, the SEA group returned to baseline, while the EA group continued to worsen (SEA 1.7 vs. EA 3.4, P = .03). The increase in BPI-SF worst pain score was 1.62 points higher in the EA group than in the SEA group at week 16 (P = .04). In a randomized, sham-controlled trial of EA for prevention of taxane-induced CIPN, there were no differences in pain or neuropathy between groups at week 12. Of concern, subjects on EA had a slower recovery than SEA subjects. Future studies should focus on EA for treatment as opposed to prevention of CIPN.
Keywords: NCT01163682; docetaxel; paclitaxel; adult; article; breast cancer; cancer adjuvant therapy; cancer staging; chemotherapy-induced peripheral neuropathy; clinical effectiveness; controlled clinical trial; controlled study; drug efficacy; drug safety; drug tolerability; electroacupuncture; female; follow up; human; injection site contusion; injection site reaction; injection site swelling; middle aged; multiple cycle treatment; pain assessment; peripheral neuropathy; priority journal; randomized controlled trial; scoring system

Improving the detection and management of prostate cancer - Stewart, K. (Prescriber, 2016)
Despite recent advances in the treatment of prostate cancer, the death rate in the UK is continuing to rise. This article examines how improvements in screening and management could have an impact on survival rates in the future.
Keywords: abiraterone; antiandrogen; docetaxel; enzalutamide; gonadorelin agonist; gonadorelin antagonist; nicotinamide adenine dinucleotide adenosine diphosphate ribosyltransferase inhibitor; olaparib; prostate specific antigen; radioisotope; radium 223; sipuleucel T; unclassified drug; African Caribbean; age distribution; article; brachytherapy; cancer classification; cancer hormone therapy; cancer mortality; cancer screening; cancer staging; clinical competence; clinical trial (topic); ethnic difference; family history; general practitioner; health care access; health care quality; high risk population; human; male sexual dysfunction; national health service; nuclear magnetic resonance imaging; orchiectomy; outcome assessment; patient selection; personalized medicine; prostate cancer; prostatectomy; quality of life; survival rate; survival time; treatment planning; United Kingdom

Inherited Mutations in Women With Ovarian Carcinoma - Norquist, B.M.; Harrell, M.I.; Brady, M.F.; Walsh, T.; Lee, M.K.; Gulsuner, S.; Bernards, S.S.; Casadei, S.; Yi, Q.; Burger, R.A.; Chan, J.K.; Davidson, S.A.; et al. (JAMA oncology, 2016)
IMPORTANCE: Germline mutations in BRCA1 and BRCA2 are relatively common in women with ovarian, fallopian tube, and peritoneal carcinoma (OC) causing a greatly increased lifetime risk of these cancers, but the frequency and relevance of inherited mutations in other genes is less well characterized. OBJECTIVE: To determine the frequency and importance of germline mutations in cancer-associated genes in OC. DESIGN, SETTING, AND PARTICIPANTS: A study population of 1915 woman with OC and available germline DNA were identified from the University of Washington (UW) gynecologic tissue bank (n = 570) and from Gynecologic Oncology Group (GOG) phase III clinical trials 218 (n = 788) and 262 (n = 557). Patients were enrolled at diagnosis and were not selected for age or family history. Germline DNA was sequenced from women with OC using a targeted capture and multiplex sequencing assay. MAIN OUTCOMES AND MEASURES: Mutation frequencies in OC were compared with the National Heart, Lung, and Blood Institute GO Exome Sequencing Project (ESP) and the Exome Aggregation Consortium (ExAC). Clinical characteristics and survival were assessed by mutation status. RESULTS: Overall, the median (range) age at diagnosis was 60 (28-91) years in patients recruited from UW and 61 (23-87) years in patients recruited from the GOG trials. A higher number of black women were recruited from the GOG trials (4.3% vs 1.4%; P = .009); but in patients recruited from UW, there was a higher proportion of fallopian tube carcinomas (13.3% vs 5.7%; P < .001); stage I and II disease (14.6% vs 0% [GOG trials were restricted to advanced-stage cancer]); and nonserous carcinomas (29.9% vs 13.1%, P < .001). Of 1915 patients, 280 (15%) had mutations in BRCA1 (n = 182), or BRCA2 (n = 98), and 8 (0.4%) had mutations in DNA mismatch repair genes. Mutations in BRIP1 (n = 26), RAD51C (n = 11), RAD51D (n = 11), PALB2 (n = 12), and BARD1 (n = 4) were significantly more common in patients with OC than in the ESP or ExAC, present in 3.3%. Race, histologic subtype, and disease site were not predictive of mutation frequency. Patients with a BRCA2 mutation from the GOG trials had longer progression-free survival (hazard ratio [HR], 0.60; 95% CI, 0.45-0.79; P < .001) and overall survival (HR, 0.39; 95% CI, 0.25-0.60; P < .001) compared with those without mutations. CONCLUSIONS AND RELEVANCE: Of 1915 patients with OC, 347 (18%) carried pathogenic germline mutations in genes associated with OC risk. PALB2 and BARD1 are suspected OC genes and together with established OC genes (BRCA1, BRCA2, BRIP1, RAD51C, RAD51D, MSH2, MLH1, PMS2, and MSH6) bring the total number of genes suspected to cause hereditary OC to 11.
Keywords: adult; aged; disease free survival; dna mutational analysis; female; genetic predisposition; genetics; germline mutation; human; middle aged; mortality; ovary tumor; prognosis; proportional hazards model; very elderly

Recruitment of a population-based sample of young black women with breast cancer through a state cancer registry - Bonner, D.; Cragun, D.; Reynolds, M.; Vadaparampil, S.T.; Pal, T. (Breast Journal, 2016)
Given that Black women remain underrepresented in clinical research studies, we sought to recruit a population-based sample of young Black women with breast cancer through a state cancer registry. Demographic and clinical information on all Black women diagnosed with invasive breast cancer at or below age 50 between 2009 and 2012 in Florida was obtained through the state cancer registry. Survivors were invited to participate in the study through state-mandated recruitment methods. Participant demographic and clinical characteristics were compared using Chi-squared tests for categorical variables and the two sample t-test for continuous variables to identify differences between: (i) consented participants versus all other eligible; and (ii) living versus deceased. Of the 1,647 young Black women with breast cancer, mean age at diagnosis was 42.5, with the majority having localized or regional disease, unmarried, privately insured, and employed. There were no significant differences in demographic and clinical variables between the 456 consented study participants versus the remaining 1,191 presumed eligible individuals. Compared to potential participants, women determined to be deceased prior to recruitment (n = 182) were significantly more likely to have distant disease and a triple-negative phenotype. They were also significantly more likely to be unemployed, and uninsured or have public insurance (i.e., Medicaid or Medicare). Our results demonstrate that recruitment of a population-based sample of breast cancer survivors through a state cancer registry is a feasible strategy in this underserved and underrepresented population. However, survival bias, which was observed due to the lag time between diagnosis and recruitment, is important to adjust for when generalizing findings to all young Black breast cancer patients.
Keywords: adult; African American; article; breast cancer; cancer patient; cancer registry; cancer survivor; clinical research; comparative study; disease predisposition; female; health insurance; human; major clinical study; medical history; medical record; medically uninsured; unemployment

Lessons Learned from Implementing a Prostate Cancer Risk Assessment Program for Underserved High-Risk Men in the Community: the Prostate REACH Project - Fleisher, L.; Davis, S.N.; Gross, L.; Bagden, L.; Zakrzewski, D.; González, E.; Kandadai, V.; Rusten, C.; Baskett, J.; Obeid, E.; Giri, V.N. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2016)
Prostate cancer disproportionately affects Black men, who may also encounter barriers to participation in prostate cancer risk assessment. The Prostate Risk, Education and Assessment in the Community with Help (REACH) project was a community-based extension of a comprehensive prostate cancer risk assessment program at a comprehensive cancer center. The goals of the REACH project were the following: (1) establish a community prostate cancer risk assessment clinic, (2) conduct targeted recruitment, and (3) provide navigation services including follow-up for uninsured men. Key implementation steps included the following: (1) choosing a clinic site, (2) establishing patient access procedures, (3) establishing navigator services, (4) developing subsidy fund use guidelines, and (5) designing recruitment and promotion. Through community-based promotion, 64 men inquired about the program and 26 (41 %) participated. Of those screened, 46 % had abnormal results, and 2 men were diagnosed with prostate cancer. Here, we describe a unique demonstration project to implement a comprehensive prostate cancer risk assessment program in an underserved Black community and describe successes and challenges to inform future efforts to promote access to underserved men.
Keywords: adult; aged; early cancer diagnosis; education; ethnic group; follow up; human; learning; male; middle aged; patient care; patient education; patient selection; prognosis; program evaluation; prostate tumor; psychology; risk assessment; vulnerable population

Feasibility outcomes of a presurgical randomized controlled trial exploring the impact of caloric restriction and increased physical activity versus a wait-list control on tumor characteristics and circulating biomarkers in men electing prostatectomy for prostate cancer - Demark-Wahnefried, W.; Nix, J.W.; Hunter, G.R.; Rais-Bahrami, S.; Desmond, R.A.; Chacko, B.; Morrow, C.D.; Azrad, M.; Frugé, A.D.; Tsuruta, Y.; Ptacek, T.; Tully, S.A.; et al. (BMC Cancer, 2016)
Background: Obesity is associated with tumor aggressiveness and disease-specific mortality for more than 15 defined malignancies, including prostate cancer. Preclinical studies suggest that weight loss from caloric restriction and increased physical activity may suppress hormonal, energy-sensing, and inflammatory factors that drive neoplastic progression; however, exact mechanisms are yet to be determined, and experiments in humans are limited. Methods: We conducted a randomized controlled trial among 40 overweight or obese, newly-diagnosed prostate cancer patients who elected prostatectomy to explore feasibility of a presurgical weight loss intervention that promoted a weight loss of roughly one kg. week-1 via caloric restriction and physical activity, as well as to assess effects on tumor biology and circulating biomarkers. Measures of feasibility (accrual, retention, adherence, and safety) were primary endpoints. Exploratory aims were directed at the intervention's effect on tumor proliferation (Ki-67) and other tumor markers (activated caspase-3, insulin and androgen receptors, VEGF, TNFβ, NFκB, and 4E-BP1), circulating biomarkers (PSA, insulin, glucose, VEGF, TNFβ, leptin, SHBG, and testosterone), lymphocytic gene expression of corresponding factors and cellular bioenergetics in neutrophils, and effects on the gut microbiome. Consenting patients were randomized in a 1:1 ratio to either: 1) weight loss via a healthful, guidelines-based diet and exercise regimen; or 2) a wait-list control. While biological testing is currently ongoing, this paper details our methods and feasibility outcomes. Results: The accrual target was met after screening 101 cases (enrollment rate: 39.6 %). Other outcomes included a retention rate of 85 %, excellent adherence (95 %), and no serious reported adverse events. No significant differences by age, race, or weight status were noted between enrollees vs. non-enrollees. The most common reasons for non-participation were "too busy" (30 %), medical exclusions (21 %), and "distance" (16 %). Conclusions: Presurgical trials offer a means to study the impact of diet and exercise interventions directly on tumor tissue, and other host factors that are feasible and safe, though modifications are needed to conduct trials within an abbreviated period of time and via distance medicine-based approaches. Pre-surgical trials are critical to elucidate the impact of lifestyle interventions on specific mechanisms that mediate carcinogenesis and which can be used subsequently as therapeutic targets. Trial registration: NCT01886677.
Keywords: NCT01886677; androgen receptor; biological marker; caspase 3; glucose; immunoglobulin enhancer binding protein; initiation factor 4E binding protein 1; insulin; insulin receptor; Ki 67 antigen; leptin; lymphotoxin; phosphatidylinositol 3 kinase; phosphatidylinositol 3,4,5 trisphosphate 3 phosphatase; prostate specific antigen; protein kinase B; sex hormone binding globulin; testosterone; vasculotropin; adult; African American; article; bioenergy; body composition; body fat; body mass; caloric intake; caloric restriction; cancer growth; cancer mortality; cancer patient; cardiorespiratory fitness; Caucasian; clinical article; controlled study; feasibility study; hospital admission; human; male; obesity; physical activity; prostate cancer; prostatectomy; quality of life; randomized controlled trial; risk factor; tumor growth; waist circumference; body weight gain; body weight loss

Correlates of quality of life in overweight or obese breast cancer survivors at enrollment into a weight loss trial - Pakiz, B.; Ganz, P.A.; Sedjo, R.L.; Flatt, S.W.; Demark-Wahnefried, W.; Liu, J.; Wolin, K.Y.; Rock, C.L. (Psycho-Oncology, 2016)
Objective The purpose of this analysis was to examine the correlates of the physical and psychosocial domains of quality of life (QOL) in a cohort of breast cancer survivors participating in a weight loss intervention trial. Methods Correlates of QOL and psychosocial functioning were examined in 692 overweight or obese breast cancer survivors at entry into a weight loss trial. QOL was explored with three measures: Short-form 36 (SF-36), Impact of Cancer scale (IOC), and the Breast Cancer Prevention Trial (BCPT) symptom scales. Available data included information on weight and physical activity, as well as demographic and medical characteristics. Multivariate analyses were used to identify associations adjusted for other characteristics. Results In multivariate analysis, younger age was associated with higher negative impact scores (p < 0.0001). Hispanic, African-American, and Asian women had higher positive IOC impact scores compared with White non-Hispanic women (p < 0.01). Increased number of comorbidities was associated with lower physical and mental QOL scores (p < 0.01). Body mass index was not independently associated with QOL measures. Physical activity was directly associated with physical and mental QOL and IOC positive impact, and inversely related to IOC negative impact and Breast Cancer Prevention Trial symptom scales. Conclusions Quality-of-life measures in breast cancer survivors are differentially associated with demographic and other characteristics. When adjusted for these characteristics, degree of adiposity among overweight or obese women does not appear to be independently associated with QOL. Among overweight or obese breast cancer survivors, higher level of physical activity is associated with higher QOL across various scales and dimensions.
Keywords: antiestrogen; antineoplastic agent; aromatase inhibitor; adult; African American; age distribution; aged; altruism; article; Asian; awareness; body mass; breast cancer; cancer chemotherapy; cancer hormone therapy; cancer survival; Caucasian; comorbidity; controlled clinical trial; controlled study; ethnic difference; female; Hispanic; human; major clinical study; mental function; multicenter study; obesity; physical activity; quality of life; randomized controlled trial; rating scale; Short Form 36; social status; body weight loss

Excising Additional Margins at Initial Breast-Conserving Surgery (BCS) Reduces the Need for Re-excision in a Predominantly African American Population: A Report of a Randomized Prospective Study in a Public Hospital - Jones, V.; Linebarger, J.; Perez, S.; Gabram, S.; Okoli, J.; Bumpers, H.; Burns, B.; Mosunjac, M.; Rizzo, M. (Annals of Surgical Oncology, 2016)
Background: Margin status is an important prognostic factor for local recurrence after breast conserving surgery (BCS) for breast cancer. We designed a prospective randomized trial to evaluate the effect of shave margins on positive margins and locoregional recurrence (LRR). Methods: Patients were randomized to BCS or BCS with resection of 5 additional margins (BCS + M). Tumor margins were classified as negative [>2 mm for ductal carcinoma in situ (DCIS); >1 mm for invasive carcinoma] based on guidelines at the time of accrual. Results: A total of 75 patients with stage 0–III breast cancer (76 samples) were randomized, mean age 59.6 years with median follow-up 39.5 months. Overall, 21 patients (27.6 %) had positive margins: 14 had undergone BCS and 7 BCS + M (p = 0.005). Of the 21 patients with positive margins, 19 had DCIS on final pathology (OR 7.56; 95 % CI 1.52–37.51).All patients with positive margins were offered re-excision; 11 had negative final margins after re-excision surgery. Overall, 6 patients (8.3 %) developed LRR with recurrence being more common in the BCS group when compared with the BCS + M group (17.2 vs 2.3 %; p = 0.025). Conclusions: Taking additional cavity shave margins at the time of initial excision resulted in a reduction in positive margin rate, a decrease in return to operating room for re-excision, and lower LRR.
Keywords: antineoplastic agent; adult; African American; aged; article; breast cancer; cancer adjuvant therapy; cancer recurrence; cancer surgery; controlled study; excision; female; human; intraductal carcinoma; invasive carcinoma; locoregional recurrence; major clinical study; partial mastectomy; pathology; practice guideline; prospective study; public hospital; randomized controlled trial; re excision; reoperation

Effect of Patient Navigation on Breast Cancer Screening Among African American Medicare Beneficiaries: A Randomized Controlled Trial - Marshall, J.K.; Mbah, O.M.; Ford, J.G.; Phelan-Emrick, D.; Ahmed, S.; Bone, L.; Wenzel, J.; Shapiro, G.R.; Howerton, M.; Johnson, L.; Brown, Q.; Ewing, A.; et al. (Journal of General Internal Medicine, 2016)
BACKGROUND: There is growing evidence that patient navigation improves breast cancer screening rates; however, there are limited efficacy studies of its effect among African American older adult women. OBJECTIVE: To evaluate the effect of patient navigation on screening mammography among African American female Medicare beneficiaries in Baltimore, MD. DESIGN: The Cancer Prevention and Treatment Demonstration (CPTD), a multi-site study, was a randomized controlled trial conducted from April 2006 through December 2010. SETTING: Community-based and clinical setting. PARTICIPANTS: The CPTD Screening Trial enrolled 1905 community-dwelling African American female Medicare beneficiaries who were ≥65 years of age and resided in Baltimore, MD. Participants were recruited from health clinics, community centers, health fairs, mailings using Medicare rosters, and phone calls. INTERVENTIONS: Participants were randomized to either: printed educational materials on cancer screening (control group) or printed educational materials + patient navigation services designed to help participants overcome barriers to cancer screening (intervention group). MAIN MEASURE: Self-reported receipt of mammography screening within 2 years of the end of the study. KEY RESULTS: The median follow-up period for participants in this analysis was 17.8 months. In weighted multivariable logistic regression analyses, women in the intervention group had significantly higher odds of being up to date on mammography screening at the end of the follow-up period compared to women in the control group (odds ratio [OR] 2.26, 95 % confidence interval [CI]1.59–3.22). The effect of the intervention was stronger among women who were not up to date with mammography screening at enrollment (OR 3.63, 95 % CI 2.09–6.38). CONCLUSION: Patient navigation among urban African American Medicare beneficiaries increased self-reported mammography utilization. The results suggest that patient navigation for mammography screening should focus on women who are not up to date on their screening.
Keywords: African American; aged; article; breast cancer; cancer screening; controlled study; female; follow up; health care utilization; health promotion; human; incidence; major clinical study; mammography; medicare; multicenter study; patient care; randomized controlled trial; urban population

Enrolling Minority and Underserved Populations in Cancer Clinical Research - Wallington, S.F.; Dash, C.; Sheppard, V.B.; Goode, T.D.; Oppong, B.A.; Dodson, E.E.; Hamilton, R.N.; Adams-Campbell, L.L. (American Journal of Preventive Medicine, 2016)
Research suggests that community involvement is integral to solving public health problems, including involvement in clinical trials - a gold standard. Significant racial/ethnic disparities exist in the accrual of participants for clinical trials. Location and cultural aspects of clinical trials influence recruitment and accrual to clinical trials. It is increasingly necessary to be aware of defining characteristics, such as location and culture of the populations from which research participants are enrolled. Little research has examined the effect of location and cultural competency in adapting clinical trial research for minority and underserved communities on accrual for clinical trials. Utilizing embedded community academic sites, the authors applied cultural competency frameworks to adapt clinical trial research in order to increase minority participation in nontherapeutic cancer clinical trials. This strategy resulted in successful accrual of participants to new clinical research trials, specifically targeting participation from minority and underserved communities in metropolitan Washington, DC. From 2012 to 2014, a total of 559 participants enrolled across six nontherapeutic clinical trials, representing a 62% increase in the enrollment of blacks in clinical research. Embedding cancer prevention programs and research in the community was shown to be yet another important strategy in the arsenal of approaches that can potentially enhance clinical research enrollment and capacity. The analyses showed that the capacity to acquire cultural knowledge about patients - their physical locales, cultural values, and environments in which they live - is essential to recruiting culturally and ethnically diverse population samples.
Keywords: African American; article; breast cancer; cancer prevention; cancer research; clinical research; cultural competence; cultural value; environmental factor; gold standard; human; knowledge; minority group; population; public health problem; smoking cessation

Improved Bowel Preparation with Multimedia Education in a Predominantly African-American Population: A Randomized Study - Garg, S.; Girotra, M.; Chandra, L.; Verma, V.; Kaur, S.; Allawy, A.; Secco, A.; Anand, R.; Dutta, S.K. (Diagnostic and Therapeutic Endoscopy, 2016)
Background and Aim. Inadequate bowel preparation is a major impediment in colonoscopy quality outcomes. Aim of this study was to evaluate the role of multimedia education (MME) in improving bowel preparation quality and adenoma detection rate. Methods. This was an IRB-approved prospective randomized study that enrolled 111 adult patients undergoing outpatient screening or surveillance colonoscopy. After receiving standard colonoscopy instructions, the patients were randomized into MME group (n = 48) and control group (n = 46). The MME group received comprehensive multimedia education including an audio-visual program, a visual aid, and a brochure. Demographics, quality of bowel preparation, and colonoscopy findings were recorded. Results. MME group had a significantly better bowel preparation in the entire colon (OR 2.65, 95% CI 1.16-6.09) and on the right side of the colon (OR 2.74, 95% CI 1.12-6.71) as compared to control group (p < 0.05). Large polyps (>1 cm) were found more frequently in the MME group (11/31, 35.5% versus 0/13; p < 0.05). More polyps and adenomas were detected in MME group (57 versus 39 and 31 versus 13, resp.) but the difference failed to reach statistical significance. Conclusion. MME can lead to significant improvement in the quality of bowel preparation and large adenoma detection in a predominantly African-American population.
Keywords: bicarbonate plus macrogol 3350 plus potassium chloride plus sodium chloride plus sodium sulfate; adult; African American; article; audiovisual aid; colon adenoma; colon carcinoma; colon polyp; colonoscopy; controlled study; demography; female; groups by age; human; intestine preparation; major clinical study; male; middle aged; multimedia; multimedia education; outpatient; patient education; prospective study; race difference; randomized controlled trial; sex difference; single blind procedure; statistical significance; visual aid

Phase II trial of abiraterone acetate plus prednisone in black men with metastatic prostate cancer - Tsao, C.-K.; Sfakianos, J.; Liaw, B.; Gimpel-Tetra, K.; Kemeny, M.; Bulone, L.; Shahin, M.; Oh, W.K.; Galsky, M.D. (Oncologist, 2016)
BACKGROUND: Self-identified black men have higher incidence and mortality from prostate cancer in the United States compared with white men but are dramatically underrepresented in clinical trials exploring novel therapies for metastatic castration-resistant prostate cancer (mCRPC). METHODS: Black men with mCRPC were treated with abiraterone acetate (AA), 1,000 mg daily, and prednisone (P), 5 mg twice daily. The primary objective was to determine antitumor activity (defined by a ≥ 30% decline in prostate-specific antigen [PSA] level) and to correlate germline polymorphisms in androgen metabolism genes with antitumor activity. Secondary objectives included determining safety, post-treatment changes in measurable disease, and time to disease progression. RESULTS: From April 2013 to March 2016, a total of 11 black men were enrolled and received AA plus P (AA+P); 7 of 10 evaluable patients were docetaxel naive. Post-treatment declines in PSA level of ≥ 30% were achieved in 90% of patients. The side effect profile was consistent with prior clinical trials exploring AA+P in mCRPC. Due to poor accrual, the study was closed prematurely with insufficient sample size for the planned pharmacogenetic analyses. CONCLUSION: In this small prospective study terminated for poor accrual, the safety and activity of AA+P in black men with mCRPC was similar to that reported in prior studies exploring AA in largely white populations. Further efforts are needed to address underrepresentation of black men in mCRPC trials.
Keywords: NCT01735396; abiraterone acetate; alanine aminotransferase; alkaline phosphatase; aspartate aminotransferase; docetaxel; prednisone; prostate specific antigen; adult; aged; anorexia; article; backache; Black person; castration resistant prostate cancer; clinical article; coughing; diarrhea; drug safety; fatigue; hot flush; human; hyperglycemia; hypoalbuminemia; hypocalcemia; hypokalemia; hypophosphatemia; limb weakness; lymphocyte count; male; metastasis; nausea and vomiting; phase 2 clinical trial; priority journal; prospective study; platelet count; urine incontinence; zytiga

Study design and protocol for moving forward: A weight loss intervention trial for African-American breast cancer survivors - Stolley, M.R.; Sharp, L.K.; Fantuzzi, G.; Arroyo, C.; Sheean, P.; Schiffer, L.; Campbell, R.; Gerber, B. (BMC Cancer, 2015)
Background: Breast cancer survival rates are significantly lower among African-American women compared to white women. In addition, African-American women with breast cancer are more likely than white women to die from co-morbid conditions. Obesity is common among African-American women, and it contributes to breast cancer progression and the development and exacerbation of many weight-related conditions. Intervening upon obesity may decrease breast cancer and all-cause mortality among African-American breast cancer survivors. Methods/Design: Moving Forward is a weight loss intervention being evaluated in a randomized trial with a projected sample of 240 African American breast cancer survivors. Outcomes include body mass index, body composition, waist:hip ratio, and behavioral, psychosocial and physiological measures. Survivors are randomized to either a 6-month guided weight loss intervention that involves twice weekly classes and text messaging or a self-guided weight loss intervention based on the same materials offered in the guided program. The guided intervention is being conducted in partnership with the Chicago Park District at park facilities in predominantly African-American neighborhoods in Chicago. Recruitment strategies include direct contact to women identified in hospital cancer registries, as well as community-based efforts. Data collection occurs at baseline, post-intervention (6 months) and at a 12-month follow-up. Discussion: This study evaluates a community-based, guided lifestyle intervention designed to improve the health of African-American breast cancer survivors. Few studies have addressed behavioral interventions in this high-risk population. If successful, the intervention may help reduce the risk for breast cancer recurrence, secondary cancers, and co-morbid conditions, as well as improve quality of life. Trial registration: U.S. Clinicaltrials.gov number: NCT02482506 , April 2015
Keywords: NCT02482506; adult; African American; article; body composition; body mass; breast cancer; cancer recurrence; cancer registry; cancer survivor; clinical protocol; community sample; comorbidity; conceptual framework; controlled study; diet therapy; feeding behavior; female; health behavior; health status; high risk population; human; major clinical study; metastasis; obesity; outcome assessment; patient guidance; physical activity; quality of life; randomized controlled trial; recurrence risk; risk reduction; self report; social psychology; social support; study design; text messaging; treatment duration; United States; waist hip ratio; weight loss program

Feasibility, acceptability, and preliminary efficacy of a technology-assisted psychosocial intervention for racially diverse men with advanced prostate cancer - Yanez, B.; McGinty, H.L.; Mohr, D.C.; Begale, M.J.; Dahn, J.R.; Flury, S.C.; Perry, K.T.; Penedo, F.J. (Cancer, 2015)
BACKGROUND The utility of psychosocial interventions in reducing symptom burden and improving health-related quality of life (HRQOL) for men with localized prostate cancer has been demonstrated. However, studies have yet to demonstrate the efficacy of interventions in advanced prostate cancer (APC). This study examined the feasibility, acceptability, and preliminary efficacy of a technology-assisted, 10-week, group-based psychosocial intervention for diverse men with APC. METHODS The participants were 74 men (mean age, 68.84 years; non-Hispanic white, 57%; black, 40.5%) who were randomized to a cognitive-behavioral stress management (CBSM) treatment or health promotion (HP) attention-control condition. The participants were assessed at the baseline, weekly throughout the 10-week program, and 6 months after the baseline. Outcomes were assessed with the Patient-Reported Outcomes Measurement Information System along with established measures of HRQOL, CBSM intervention targets (eg, relaxation skills), and patient-reported acceptability. RESULTS Feasibility was demonstrated through good retention rates (>85%) and acceptable average attendance rates (>70%), and acceptability was demonstrated through very favorable weekly session evaluations (mean score, 4/5) and exit surveys (mean score, 3.6/4). Men randomized to the CBSM condition reported significant reductions (P <.05) in depressive symptoms and improvements in relaxation self-efficacy (P <.05) at the 6-month follow-up. CBSM participants reported trends for improvement in distress and functional well-being (P <.08) in comparison with those in the HP condition. Effect sizes ranged from medium (0.54) to large (1.87) and, in some instances, were clinically meaningful. CONCLUSIONS Technology-based CBSM interventions among diverse men with APC may be feasible, acceptable, and efficacious. Cancer 2015;121:4407-15.
Keywords: advanced cancer; aged; article; Black person; Caucasian; clinical effectiveness; cognitive behavioral stress management; controlled study; depression; feasibility study; health promotion; human; intermethod comparison; Internet; leisure; major clinical study; male; patient compliance; patient satisfaction; priority journal; program acceptability; prostate cancer; quality of life; randomized controlled trial; self concept; self report; treatment duration; wellbeing; wireless communication

Phase II Trial of Carboplatin, Everolimus, and Prednisone in Metastatic Castration-resistant Prostate Cancer Pretreated with Docetaxel Chemotherapy: A Prostate Cancer Clinical Trial Consortium Study - Vaishampayan, U.; Shevrin, D.; Stein, M.; Heilbrun, L.; Land, S.; Stark, K.; Li, J.; Dickow, B.; Heath, E.; Smith, D.; Fontana, J. (Urology, 2015)
Objective To conduct a phase II trial of the combination of carboplatin, prednisone, and everolimus in metastatic castrate-resistant prostate cancer (mCRPC) as mTOR inhibition can overcome resistance to chemotherapy in prostate cancer. Methods Patients with progressive mCRPC pretreated with docetaxel-based regimen were eligible. Performance status of 0-1 and adequate bone marrow, renal, and liver function were required. Primary end point was time to progression. Treatment consisted of carboplatin (starting dose equal to area under the curve (AUC of 5) intravenously every 21 days along with oral everolimus 5 mg once daily and prednisone 5 mg twice daily. Results Twenty-six patients were enrolled with median age of 69 years with 8 patients of African American origin. Grade 3 or 4 thrombocytopenia or neutropenia in 4 of 6 initial patients required dose adjustment of carboplatin to AUC of 4 for subsequent patients. There were no pharmacokinetic interactions between carboplatin and everolimus. The median time to progression was 2.5 months (90% confidence interval [CI], 1.8-4.3 months), and median overall survival was 12.5 months (90% CI, 7.7-18.7 months). Of 10 patients, 8 that demonstrated positive nuclear phosphorylated AKT (pAKT) staining on immunohistochemistry progressed within 9 weeks, whereas 2 patients with negative staining continued without progression for prolonged durations of 30 and 48 weeks. TSC1 gene mutations did not correlate with clinical outcome. Conclusion The addition of the mTOR inhibitor everolimus to carboplatin demonstrated minimal clinical efficacy in metastatic prostate cancer. pAKT testing warrants further evaluation as a predictive marker of response to everolimus therapy.
Keywords: NCT01051570; carboplatin; docetaxel; everolimus; prednisone; protein kinase B; African American; aged; area under the curve; article; bone marrow; cancer combination chemotherapy; cancer growth; cancer patient; cancer prognosis; cancer resistance; cancer survival; castration resistant prostate cancer; chronotherapy; clinical article; dose response; drug dose reduction; drug efficacy; drug safety; gene mutation; histopathology; human; human tissue; immunohistochemistry; kidney function; liver function; male; multiple cycle treatment; mutator gene; neutropenia; overall survival; phase 2 clinical trial; priority journal; survival rate; survival time; thrombocytopenia; treatment duration; treatment outcome; treatment response; tuberous sclerosis gene 1; rad 001

Treatment decisions for localized prostate cancer: a concept mapping approach - McFall, S.L.; Mullen, P.D.; Byrd, T.L.; Cantor, S.B.; Le, Y.-C.; Torres-Vigil, I.; Pettaway, C.; Volk, R.J. (Health expectations : an international journal of public participation in health care and health policy, 2015)
OBJECTIVE: Few decision aids emphasize active surveillance (AS) for localized prostate cancer. Concept mapping was used to produce a conceptual framework incorporating AS and treatment. METHODS: Fifty-four statements about what men need to make a decision for localized prostate cancer were derived from focus groups with African American, Latino and white men previously screened for prostate cancer and partners (n = 80). In the second phase, 89 participants sorted and rated the importance of statements. RESULTS: An eight cluster map was produced for the overall sample. Clusters were labelled Doctor-patient exchange, Big picture comparisons, Weighing the options, Seeking and using information, Spirituality and inner strength, Related to active treatment, Side-effects and Family concerns. A major division was between medical and home-based clusters. Ethnic groups and genders had similar sorting, but some variation in importance. Latinos rated Big picture comparisons as less important. African Americans saw Spirituality and inner strength most important, followed by Latinos, then whites. Ethnic- and gender-specific concept maps were not analysed because of high similarity in their sorting patterns. CONCLUSIONS: We identified a conceptual framework for management of early-stage prostate cancer that included coverage of AS. Eliciting the conceptual framework is an important step in constructing decision aids which will address gaps related to AS.
Keywords: aged; decision making; decision support system; disease management; doctor patient relationship; ethnology; human; information processing; male; middle aged; patient participation; procedures; prostate tumor; watchful waiting

Knowledge and attitudes regarding clinical trials and willingness to participate among prostate cancer patients - Kaplan, C.P.; Nápoles, A.M.; Narine, S.; Gregorich, S.; Livaudais-Toman, J.; Nguyen, T.; Leykin, Y.; Roach, M.; Small, E.J. (Contemporary Clinical Trials, 2015)
Background: Enrollment of minorities in clinical trials remains low. Through a California population-based study of men with early stage prostate cancer, we examined the relationships between race/ethnicity and 1) attitudes, 2) knowledge and 3) willingness to participate in clinical trials. Methods: From November 2011-November 2012, we identified all incident cases of prostate cancer in African American, Latino, and Asian American men ages 18-75. years, and a random sample of white men diagnosed in 2008, through the California Cancer Registry, living within 60 miles of a site offering ≥. 1 clinical trial. Participants completed a 30-min telephone interview in English, Spanish, or Chinese. In this cross-sectional population-based study, multivariable logistic regression was used to estimate associations between race/ethnicity and 1) attitudes, 2) knowledge and 3) willingness to participate. Results: Of 855 participants, 52% were ≥. 65 years, 42% were white, 24% Latino, 19% African American and 15% Asian American. The majority (81%) had medium-to-high health literacy. Compared to non-Latino white men, African American men were less likely to have above average knowledge of clinical trials (OR. = 0.55; CI. = 0.35-0.86), as were Asian American (OR. = 0.55; CI. = 0.33-0.93) and Latino men (OR. = 0.30; CI. = 0.18-0.48). There were no racial/ethnic differences in willingness to participate. The attitude that "researchers are the main beneficiaries" was negatively associated with willingness (OR. = 0.63; CI. = 0.43-0.93); the attitude that "patients are the main beneficiaries" was positively associated with willingness to participate (OR. = 1.57; CI. = 1.07-2.29). Conclusions: Men with early stage prostate cancer are willing to take part in clinical trials and this willingness does not vary by race/ethnicity.
Keywords: adult; African American; aged; article; Asian American; cancer patient; clinical trial (topic); cross-sectional study; ethnic difference; health literacy; Hispanic; human; knowledge; major clinical study; male; patient attitude; patient participation; prostate cancer; race difference; telephone interview

Do lung cancer eligibility criteria align with risk among blacks and hispanics? - Fiscella, K.; Winters, P.; Farah, S.; Sanders, M.; Mohile, S.G. (PLoS ONE, 2015)
Background: Black patients have higher lung cancer risk despite lower pack years of smoking. We assessed lung cancer risk by race, ethnicity, and sex among a nationally representative population eligible for lung cancer screening based on Medicare criteria. Methods: We used data from the National Health and Nutrition Examination Survey, 2007-2012 to assess lung cancer risk by sex, race and ethnicity among persons satisfying Medicare age and pack-year smoking eligibility criteria for lung cancer screening. We assessed Medicare eligibility based on age (55-77 years) and pack-years (>30). We assessed 6-year lung cancer risk using a risk prediction model from Prostate, Lung, Colorectal and Ovarian Cancer Screening trial that was modified in 2012 (PLCOm2012). We compared the proportions of eligible persons by sex, race and ethnicity using Medicare criteria with a risk cut-point that was adjusted to achieve comparable total number of persons eligible for screening. Results: Among the 29.7 million persons aged 55-77 years who ever smoked, we found that 7.3 million (24.5%) were eligible for lung cancer screening under Medicare criteria. Among those eligible, Blacks had statistically significant higher (4.4%) and Hispanics lower lung cancer risk (1.2%) than non-Hispanic Whites (3.2%). At a cut-point of 2.12% risk for lung screening eligibility, the percentage of Blacks and Hispanics showed statistically significant changes. Blacks eligible rose by 48% and Hispanics eligible declined by 63%. Black men and Hispanic women were affected the most. There was little change in eligibility among Whites. Conclusion: Medicare eligibility criteria for lung cancer screening do not align with estimated risk for lung cancer among Blacks and Hispanics. Data are urgently needed to determine whether use of risk-based eligibility screening improves lung cancer outcomes among minority patients.
Keywords: adult; aged; article; Black person; cancer risk; cancer screening; controlled study; ethnic difference; female; health care delivery; health survey; high risk population; Hispanic; human; lung cancer; major clinical study; male; medicare; minority group; outcome assessment; patient selection; population research; race difference; risk assessment; sex difference; smoking; United States

Exploring research participation among cancer patients: Analysis of a national survey and an in-depth interview study - Mc Grath-Lone, L.; Day, S.; Schoenborn, C.; Ward, H. (BMC Cancer, 2015)
Background: Inequalities in cancer research participation are thought to exist with certain groups under-represented in research populations; however, much of the evidence is based on small-scale studies. The aim of this study was to explore data from in-depth interviews with cancer patients and a large national survey to investigate variation in who is asked to participate in research and who takes part. Methods: Factors associated with research discussion and participation were explored in National Cancer Patient Experience Survey data using multivariate logistic regression and during in-depth interviews with 25 breast cancer patients. Results: Survey data were available for 66,953 cancer patients; 30.4 % reported having discussions about, and 18.9 % took part in, research. Barriers to participation at staff, patient and trust level were evident; for example, staff were less likely to discuss research with older patients, Asian and black patients were less likely to take part and patients treated at specialist or teaching trusts had higher levels of discussion and participation. Interviews showed that patients' willingness to participate changed over time and was not synonymous with participation as some were ineligible. Conclusion: Some patient groups were less likely to have discussions about or participate in research. Analysis of this variation vis-à-vis the composition of the patient population may be useful to ensure that there is equity regarding the potential benefits of research participation and that research findings are applicable to target populations in the translational model.
Keywords: adolescent; adult; age distribution; aged; article; Asian; Black person; breast cancer; cancer patient; cancer research; Caucasian; disease association; ethnicity; female; health survey; human; major clinical study; male; middle aged; patient participation

Randomized trial to increase colorectal cancer screening in an ethnically diverse sample of first-degree relatives - Bastani, R.; Glenn, B.A.; Maxwell, A.E.; Ganz, P.A.; Mojica, C.M.; Alber, S.; Crespi, C.M.; Chang, L.C. (Cancer, 2015)
BACKGROUND: Ethnic minorities, especially African Americans and Latinos, bear a disproportionate burden of colorectal cancer (CRC), as reflected in incidence, cancer stage, and mortality statistics. In all ethnic groups, first-degree relatives (FDRs) of CRC cases are at an elevated disease risk. However, underuse of CRC screening persists and is particularly evident among minority groups. The current study tested a stepped intervention to increase CRC screening among an ethnically diverse sample of FDRs of CRC cases. METHODS: A statewide cancer registry was used to recruit CRC cases and through them their FDRs. Relatives who were not current on CRC screening were randomized to intervention or usual-care control arms. The stepped intervention consisted of ethnically targeted and individually tailored print materials followed by telephone counseling for those unscreened at 6 months. RESULTS: The study sample of 1280 individuals consisted of 403 Latino, 284 African American, 242 Asian, and 351 white FDRs. Statistically significant effects were observed for the cumulative print plus telephone intervention at 12 months (26% in the intervention vs 18% in the control group) and the print intervention alone at 6 months (15% in the intervention vs 10% in the control group). The effect of the print intervention alone versus the cumulative interventions was not statistically significantly different. Stratified analyses indicated that the intervention was effective among white, Latino, and Asian individuals, but not among African-Americans. CONCLUSIONS: Overall, the intervention was effective in increasing screening rates. Oversampling racial/ethnic minorities allowed for the examination of effects within subgroups, revealing no effect among African American individuals. This finding illustrates the importance of including sufficient numbers of participants from diverse ethnic subgroups in intervention research to enable such stratified analyses. Cancer 2015;121:2951-2959.
Keywords: adult; African American; aged; article; Asian; cancer risk; cancer screening; Caucasian; colorectal cancer; controlled study; counseling; ethnicity; family history; female; first-degree relative; Hispanic; human; intervention study; major clinical study; male; priority journal; risk assessment

A phase II/III randomized study to compare the efficacy and safety of rigosertib plus gemcitabine versus gemcitabine alone in patients with previously untreated metastatic pancreatic cancer - O'Neil, B.H.; Scott, A.J.; Ma, W.W.; Cohen, S.J.; Aisner, D.L.; Menter, A.R.; Tejani, M.A.; Cho, J.K.; Granfortuna, J.; Coveler, L.; Olowokure, O.O.; Baranda, J.C.; et al. (Annals of Oncology, 2015)
Background: Rigosertib (ON 01910.Na), a first-in-class Ras mimetic and small-molecule inhibitor of multiple signaling pathways including polo-like kinase 1 (PLK1) and phosphoinositide 3-kinase (PI3K), has shown efficacy in preclinical pancreatic cancer models. In this study, rigosertib was assessed in combination with gemcitabine in patients with treatment-naïve metastatic pancreatic adenocarcinoma. Materials and methods: Patients with metastatic pancreatic adenocarcinoma were randomized in a 2:1 fashion to gemcitabine 1000 mg/m2 weekly for 3 weeks of a 4-week cycle plus rigosertib 1800 mg/m2 via 2-h continuous IV infusions given twice weekly for 3 weeks of a 4-week cycle (RIG + GEM) versus gemcitabine 1000 mg/m2 weekly for 3 weeks in a 4-week cycle (GEM). Results: A total of 160 patients were enrolled globally and randomly assigned to RIG + GEM (106 patients) or GEM (54). The most common grade 3 or higher adverse events were neutropenia (8% in the RIG + GEM group versus 6% in the GEM group), hyponatremia (17% versus 4%), and anemia (8% versus 4%). The median overall survival was 6.1 months for RIG + GEM versus 6.4 months for GEM [hazard ratio (HR), 1.24; 95% confidence interval (CI) 0.85-1.81]. The median progression-free survival was 3.4 months for both groups (HR = 0.96; 95% CI 0.68-1.36). The partial response rate was 19% versus 13% for RIG + GEM versus GEM, respectively. Of 64 tumor samples sent for molecular analysis, 47 were adequate for multiplex genetic testing and 41 were positive for mutations. The majority of cases had KRAS gene mutations (40 cases). Other mutations detected included TP53 (13 cases) and PIK3CA (1 case). No correlation between mutational status and efficacy was detected. Conclusions: The combination of RIG + GEM failed to demonstrate an improvement in survival or response compared with GEM in patients with metastatic pancreatic adenocarcinoma. Rigosertib showed a similar safety profile to that seen in previous trials using the IV formulation.
Keywords: gemcitabine; rigosertib; adult; African American; aged; anemia; article; Asian; Black person; Caucasian; continuous infusion; controlled study; correlation analysis; decreased appetite; diarrhea; drug efficacy; drug safety; drug withdrawal; fatigue; female; gene; gene mutation; genetic analysis; hazard ratio; Hispanic; human; human tissue; hypertransaminasemia; hypoalbuminemia; hyponatremia; liver metastasis; lung metastasis; major clinical study; male; multicenter study; multiple cycle treatment; nausea; neutropenia; oncogene K ras; overall survival; pancreas adenocarcinoma; peritoneum metastasis; phase 2 clinical trial; phase 3 clinical trial; PIK3CA gene; priority journal; progression free survival; randomized controlled trial; retroperitoneal cancer; thrombocytopenia; treatment response; tumor suppressor gene; very elderly; vomiting; on 01910

Getting Black Men to Undergo Prostate Cancer Screening: The Role of Social Capital - Dean, L.T.; Subramanian, S.V.; Williams, D.R.; Armstrong, K.; Zubrinsky Charles, C.; Kawachi, I. (American journal of men's health, 2015)
Despite higher rates of prostate cancer-related mortality and later stage of prostate cancer diagnosis, Black/African American men are significantly less likely than non-Hispanic White men to use early detection screening tools, like prostate-specific antigen (PSA) testing for prostate cancer. Lower screening rates may be due, in part, to controversy over the value of prostate cancer screenings as part of routine preventive care for men, but Black men represent a high-risk group for prostate cancer that may still benefit from PSA testing. Exploring the role of social factors that might be associated with PSA testing can increase knowledge of what might promote screening behaviors for prostate cancer and other health conditions for which Black men are at high risk. Using multilevel logistic regression, this study analyzed self-report lifetime use of PSA test for 829 Black men older than 45 years across 381 Philadelphia census tracts. This study included individual demographic and aggregated social capital data from the Public Health Management Corporation's 2004, 2006, and 2008 waves of the Community Health Database, and sociodemographic characteristics from the 2000 U.S. Census. Each unit increase in community participation was associated with a 3 to 3.5 times greater likelihood of having had a PSA test (odds ratio = 3.35). Findings suggest that structural forms of social capital may play a role in screening behaviors for Black men in Philadelphia. A better understanding of the mechanism underlying the link between social capital and screening behaviors can inform how researchers and interventionists develop tools to promote screening for those who need it.
Keywords: prostate specific antigen; age; Black person; blood; community participation; epidemiology; health insurance; health survey; human; income; insurance; male; mass screening; middle aged; multivariate analysis; Pennsylvania; prostate tumor; social capital; statistics and numerical data

Reaching Hard to Reach Populations with Hard to Communicate Messages: Efficacy of a Breast Health Research Champion Training Program - Rafie, C.; Ayers, A.; Cadet, D.; Quillin, J.; Hackney, M.H. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2015)
A Breast Health Research Champion training program was a developed targeting self-identified community breast health advocates from a predominant African-American community with a significant breast cancer mortality disparity. Twelve individuals completed the program that provided training in breast cancer risk and screening, breast cancer research, biospecimen in cancer research, and human research subject protection. The training emphasized four key messages to be disseminated to the community. Trainees hosted a minimum of two social chats with individuals from their social networks and functioned as community researchers, acquiring consent and gathering follow-up data from attendees. Trainees reached 199 individuals from their social networks, and chats were diverse in the venue selected, mode of message transmission, and the audience reached. Post/pre questionnaire data from attendees at the chats showed significant improvement in knowledge, attitudes, and intended behaviors as it relates to breast cancer screening, clinical research, and biospecimen in research. Forty percent of attendees provided 4-week follow-up information. Of respondents eligible for mammography, 38 % had taken action to be screened, and 86 % of respondents had spoken about the information to someone else in their social network. Trainees expressed feelings of empowerment after completing the project, "feeling like the expert," and all trainees were surprised at the enthusiastic response from attendees of their chats. Trainees continued to disseminate the information learned from the training program during the 6 months following the training, reaching an additional 786 individuals in the community.
Keywords: adult; African American; aged; attitude to health; breast tumor; early cancer diagnosis; education; ethnology; female; health auxiliary; health disparity; health education; human; information dissemination; mammography; medical research; middle aged; organization and management; procedures; research subject; risk assessment; risk factor

Informed Decision-Making and Satisfaction with a Church-Based Men's Health Workshop Series for African-American Men: Men-Only vs. Mixed-Gender Format - Holt, C.L.; Le, D.; Saunders, D.R.; Wang, M.Q.; Slade, J.L.; Muwwakkil, B.; Williams, R.; Atkinson, N.L.; Whitehead, T.L.; Naslund, M. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2015)
Prostate cancer incidence and mortality are highest among African-American men, and coupled with the controversy around routine prostate cancer screening, reaching African-American men with interventions to help them make an informed decision about whether or not to be screened is critical. This study compares two approaches to delivering a church-based peer community health advisor intervention consisting of a series of four men's health workshops on informed decision-making for prostate cancer screening. In the men-only group, male community health advisors teach group workshops consisting only of men. In the health partner group, male-female pairs of community health advisors teach workshops in a mixed-gender format in which enrolled men are asked to invite a significant woman in their lives (e.g., wife/partner, sister, daughter, friend) with them to the workshops. Eighteen African-American churches were randomized to receive one of the two approaches, and 283 eligible men enrolled in the intervention. Main findings suggested that the workshops had an impact on stage of decision-making, and this increased significantly over time in the health partner group only. The intervention was highly rated by men in both groups, and these ratings increased over time, with some study group differences. Within-workshop study group differences favored the health partner group in some instances; however, men in the men-only groups reported greater increases in their ratings of trust in the workshops over time. The health partner intervention strategy appears to be promising for reaching men of color with health information.
Keywords: NCT02131779; African American; aged; attitude to health; controlled study; decision making; early cancer diagnosis; ethnology; female; health education; human; information processing; male; men's health; middle aged; organization and management; patient attitude; prostate tumor; psychology; randomized controlled trial; religion; satisfaction; sex difference; United States

A Model of Cancer Clinical Trial Decision-making Informed by African-American Cancer Patients - Wenzel, J.A.; Mbah, O.; Xu, J.; Moscou-Jackson, G.; Saleem, H.; Sakyi, K.; Ford, J.G. (Journal of racial and ethnic health disparities, 2015)
BACKGROUND: Clinical trials are critical to advancing cancer treatment. Minority populations are underrepresented among trial participants, and there is limited understanding of their decision-making process and key determinants of decision outcomes regarding trial participation. METHODS: To understand research decision-making among clinical trial-eligible African-American cancer patients at Johns Hopkins, we conducted seven focus groups (n=32) with trial-offered patients ≥ 18 years diagnosed with lung, breast, prostate, or colorectal cancer ≤ 5 years. Three "acceptor" and four "decliner" focus groups were conducted. Questions addressed: attitudes towards clinical trials, reasons for accepting or declining participation, and recommendations to improve minority recruitment and enrollment. Data were transcribed and analyzed using traditional approaches to content and thematic analysis in NVivo 9.0. Data coding resulted in themes that supported model construction. RESULTS: Participant experiences revealed the following themes when describing the decision-making process: Information gathering, Intrapersonal perspectives, and Interpersonal influences. Decision outcomes included the presence or absence of decision regret and satisfaction. From these themes, we generated a Model of Cancer Clinical Trial Decision-making. CONCLUSION: Our model should be tested in hypothesis-driven research to elucidate factors and processes influencing decision balance and outcomes of trial-related decision-making. The model should also be tested in other disparities populations and for diagnoses other than cancer.
Keywords: adult; African American; aged; clinical trial (topic); decision making; ethnology; female; health disparity; human; information processing; male; middle aged; neoplasm; psychological model; psychology; statistics and numerical data

Vegetarian dietary patterns and the risk of colorectal cancers - Orlich, M.J.; Singh, P.N.; Sabaté, J.; Fan, J.; Sveen, L.; Bennett, H.; Knutsen, S.F.; Beeson, W.L.; Jaceldo-Siegl, K.; Butler, T.L.; Herring, R.P.; Fraser, G.E. (JAMA Internal Medicine, 2015)
IMPORTANCE Colorectal cancers are a leading cause of cancer mortality, and their primary prevention by diet is highly desirable. The relationship of vegetarian dietary patterns to colorectal cancer risk is not well established. OBJECTIVE To evaluate the association between vegetarian dietary patterns and incident colorectal cancers. DESIGN, SETTING, AND PARTICIPANTS The Adventist Health Study 2 (AHS-2) is a large, prospective, North American cohort trial including 96 354 Seventh-Day Adventist men and women recruited between January 1, 2002, and December 31, 2007. Follow-up varied by state and was indicated by the cancer registry linkage dates. Of these participants, an analytic sample of 77 659 remained after exclusions. Analysis was conducted using Cox proportional hazards regression, controlling for important demographic and lifestyle confounders. The analysis was conducted between June 1, 2014, and October 20, 2014. EXPOSURES Diet was assessed at baseline by a validated quantitative food frequency questionnaire and categorized into 4 vegetarian dietary patterns (vegan, lacto-ovo vegetarian, pescovegetarian, and semivegetarian) and a nonvegetarian dietary pattern. MAIN OUTCOMES AND MEASURES The relationship between dietary patterns and incident cancers of the colon and rectum; colorectal cancer cases were identified primarily by state cancer registry linkages. RESULTS During a mean follow-up of 7.3 years, 380 cases of colon cancer and 110 cases of rectal cancer were documented. The adjusted hazard ratios (HRs) in all vegetarians combined vs nonvegetarians were 0.78 (95%CI, 0.64-0.95) for all colorectal cancers, 0.81 (95%CI, 0.65-1.00) for colon cancer, and 0.71 (95%CI, 0.47-1.06) for rectal cancer. The adjusted HR for colorectal cancer in vegans was 0.84 (95%CI, 0.59-1.19); in lacto-ovo vegetarians, 0.82 (95%CI, 0.65-1.02); in pescovegetarians, 0.57 (95%CI, 0.40-0.82); and in semivegetarians, 0.92 (95%CI, 0.62-1.37) compared with nonvegetarians. Effect estimates were similar for men and women and for black and nonblack individuals. CONCLUSIONS AND RELEVANCE Vegetarian diets are associated with an overall lower incidence of colorectal cancers. Pescovegetarians in particular have a much lower risk compared with nonvegetarians. If such associations are causal, theymay be important for primary prevention of colorectal cancers.
Keywords: acetylsalicylic acid; hydroxymethylglutaryl coenzyme A reductase inhibitor; saturated fatty acid; adult; alcohol consumption; article; calcium intake; caloric intake; cancer incidence; cancer risk; cohort analysis; colon cancer; colonoscopy; colorectal cancer; comparative study; controlled study; diabetes mellitus; dietary fiber; disease association; fat intake; female; follow up; food frequency questionnaire; human; lactoovovegetarian diet; lifestyle; major clinical study; male; peptic ulcer; pescovegetarian diet; priority journal; processed meat; prospective study; rectum cancer; red meat; Seventh-day Adventist; sigmoidoscopy; smoking; vegan; vegetarian diet

Nationwide bowel cancer screening programme in England: Cohort study of lifestyle factors affecting participation and outcomes in women - Blanks, R.G.; Benson, V.S.; Alison, R.; Brown, A.; Reeves, G.K.; Beral, V.; Patnick, J.; Green, J. (British Journal of Cancer, 2015)
Background:In 2006, the National Health Service Bowel Cancer Screening Programme in England (NHSBCSP) began offering routine population-based biennial faecal occult blood testing (FOBt) at ages 60-69. There is, however, limited information on how characteristics of individuals affect participation and outcomes of screening, and we studied this association by linking NHSBCSP data to a large prospective cohort of women.Methods:Electronic linkage of the NHSBCSP and Million Women Study records identified 899 166 women in the study cohort with at least one invitation for screening. NHSBCSP provided information on screening acceptance, FOBt results, screen-detected colorectal cancer and other outcomes. The Million Women Study provided prospectively collected information on personal and lifestyle factors. Multiple regression was used to estimate relative risks (RRs) of factors associated with acceptance and outcomes of screening.Results:Overall, 70% of women (628 976/899 166) accepted their first invitation for bowel cancer screening, of whom 9133 (1.5%) were FOBt-positive, 743 (0.1%) had screen-detected colorectal cancer and 3056 (0.5%) had screen-detected colorectal adenoma. Acceptance was lower in women from the most than the least deprived tertile, in South Asians and in Blacks than in Whites, in current than in never smokers and in obese than in normal weight women: adjusted RRs (95% confidence interval) for acceptance vs not, 0.90 (0.90-0.90); 0.77 (0.75-79); 0.94 (0.92-0.96); 0.78 (0.77-0.78); and 0.88 (0.88-0.89), respectively: P<0.001 for each. These factors were also associated with an increased risk of being FOBt-positive and of having screen-detected adenoma, but were not strongly associated with the risk of screen-detected colorectal cancer. Relative risks for screen-detected adenoma were 1.22 (1.12-1.34), 2.46 (1.75-3.45), 1.61 (1.05-2.48), 1.53 (1.38-1.68) and 1.77 (1.60-1.95), respectively (P<0.001 for all, except for Blacks vs Whites P=0.03). Use of hormone therapy for menopause was associated with reduced risk of screen-detected adenoma, RR ever vs never use, 0.87 (0.81-0.93), P<0.001 and colorectal cancer, 0.78 (0.68-0.91), P=0.001.Interpretation:Among women in England, socioeconomic and lifestyle factors strongly affect participation in routine bowel cancer screening, risk of being FOBt-positive and risk of having screen-detected colorectal adenoma. However, screen-detected colorectal cancer risk is not strongly related to these factors.
Keywords: oral contraceptive agent; aged; alcohol consumption; article; Black person; body mass; body weight; cancer risk; cancer screening; Caucasian; cohort analysis; colonoscopy; colorectal adenoma; colorectal cancer; diagnostic test; exercise; female; hormonal therapy; human; lifestyle; major clinical study; menopause; outcome assessment; patient participation; physical activity; priority journal; prospective study; risk factor; smoking; South Asian

Demographic and HIV-specific characteristics of participants enrolled in the INSIGHT Strategic Timing of AntiRetroviral Treatment (START) trial - Sharma, S.; Babiker, A.; Emery, S.; Gordin, F.; Lundgren, J.; Neaton, J.; Bakowska, E.; Schechter, M.; Wiselka, M.; Wolff, M. (HIV Medicine, 2015)
Objectives: The risks and benefits of initiating antiretroviral treatment (ART) at high CD4 cell counts have not been reliably quantified. The Strategic Timing of AntiRetroviral Treatment (START) study is a randomized international clinical trial that compares immediate with deferred initiation of ART for HIV-positive individuals with CD4 cell counts above 500cells/μL. We describe the demographics, HIV-specific characteristics and medical history of this cohort. Methods: Data collected at baseline include demographics, HIV-specific laboratory values, prior medical diagnoses and concomitant medications. Baseline characteristics were compared by geographical region, gender and age. Results: START enrolled 4685 HIV-positive participants from 215 sites in 35 countries. The median age is 36 years [interquartile range (IQR) 29-44 years], 27% are female, and 45% self-identify as white, 30% as black, 14% as Latino/Hispanic, 8% as Asian and 3% as other. The route of HIV acquisition is reported as men who have sex with men in 55% of participants, heterosexual sex in 38%, injecting drug use in 1% and other/unknown in 5%. Median time since HIV diagnosis is 1.0 year (IQR 0.4-3.0 years) and the median CD4 cell count and HIV RNA values at study entry are 651cells/μL (IQR 584-765cells/μL) and 12754 HIV RNA copies/mL (IQR 3014-43607 copies/mL), respectively. Conclusions: START has enrolled a diverse group of ART-naïve individuals with high CD4 cell counts who are comparable to the HIV-positive population from the regions in which they were enrolled. The information collected with this robust study design will provide a database with which to evaluate the risks and benefits of early ART use for many important outcomes.
Keywords: NCT00867048; antidepressant agent; antilipemic agent; antiretrovirus agent; benzodiazepine derivative; nonsteroid antiinflammatory agent; proton pump inhibitor; RNA; acute heart infarction; adult; alcoholism; antiviral therapy; article; CD4 lymphocyte count; cerebrovascular accident; chronic kidney failure; cohort analysis; congestive heart failure; coronary artery disease; deep vein thrombosis; demography; drug use; end stage renal disease; fatty liver; female; heart muscle revascularization; heterosexuality; hormonal therapy; human; Human immunodeficiency virus; Human immunodeficiency virus infection; liver cirrhosis; lung embolism; major clinical study; male; medical history; men who have sex with men; mental disease; myocarditis; pancreatitis; pericarditis; peripheral occlusive artery disease; priority journal; self injection; skin cancer; substance abuse

In patients with a previous negative prostate biopsy and a suspicious lesion on magnetic resonance imaging, is a 12-core biopsy still necessary in addition to a targeted biopsy? - Salami, S.S.; Ben-Levi, E.; Yaskiv, O.; Ryniker, L.; Turkbey, B.; Kavoussi, L.R.; Villani, R.; Rastinehad, A.R. (BJU International, 2015)
ObjectivesTo evaluate the performance of multiparametric magnetic resonance imaging (mpMRI) in predicting prostate cancer on repeat biopsy; and to compare the cancer detection rates (CDRs) of MRI/transrectal ultrasonography (TRUS) fusion-guided biopsy with standard 12-core biopsy in men with at least one previous negative biopsy. Patients and Methods We prospectively enrolled men with elevated or rising PSA levels and/or abnormal digital rectal examination into our MRI/TRUS fusion-guided prostate biopsy trial. Participants underwent a 3 T mpMRI with an endorectal coil. Three radiologists graded all suspicious lesions on a 5-point Likert scale. MRI/TRUS fusion-guided biopsies of suspicious prostate lesions and standard TRUS-guided 12-core biopsies were performed. Analysis of 140 eligible men with at least one previous negative biopsy was performed. We calculated CDRs and estimated area under the receiver operating characteristic curves (AUCs) of mpMRI in predicting any cancer and clinically significant prostate cancer. Results The overall CDR was 65.0% (91/140). Higher level of suspicion on mpMRI was significantly associated with prostate cancer detection (P < 0.001) with an AUC of 0.744 compared with 0.653 and 0.680 for PSA level and PSA density, respectively. The CDRs of MRI/TRUS fusion-guided and standard 12-core biopsy were 52.1% (73/140) and 48.6% (68/140), respectively (P = 0.435). However, fusion biopsy was more likely to detect clinically significant prostate cancer when compared with the 12-core biopsy (47.9% vs 30.7%; P < 0.001). Of the cancers missed by 12-core biopsy, 20.9% (19/91) were clinically significant. Most cancers missed by 12-core biopsy (69.6%) were located in the anterior fibromuscular stroma and transition zone. Using a fusion-biopsy-only approach in men with an MRI suspicion score of ≥4 would have missed only 3.5% of clinically significant prostate cancers. Conclusions Using mpMRI and subsequent MRI/TRUS fusion-guided biopsy platform may improve detection of clinically significant prostate cancer in men with previous negative biopsies. Addition of a 12-core biopsy may be needed to avoid missing some clinically significant prostate cancers.
Keywords: NCT01566045; prostate specific antigen; 12 core prostate biopsy; adult; African American; aged; article; cancer prognosis; cancer screening; controlled study; diagnostic test accuracy study; diffusion coefficient; digital rectal examination; false negative result; false positive result; family history; Gleason score; human; image guided biopsy; intermethod comparison; major clinical study; male; nuclear magnetic resonance imaging; priority journal; prospective study; prostate biopsy; prostate cancer; prostate fusion biopsy; protein blood level; receiver operating characteristic; risk assessment; transrectal ultrasonography

Prospective approach to breast cancer risk prediction in African American women: The black women's health study model - Boggs, D.A.; Rosenberg, L.; Adams-Campbell, L.L.; Palmer, J.R. (Journal of Clinical Oncology, 2015)
Purpose Breast cancer risk prediction models have underestimated risk for African American women, contributing to lower recruitment rates in prevention trials. A model previously developed for African American women was found to underestimate risk in the Black Women's Health Study (BWHS). Methods We developed a breast cancer risk model for African American women using relative risks derived from 10 years of follow-up of BWHS participants age 30 to 69 years at baseline. Using the subsequent 5 years of follow-up data, we evaluated calibration as the ratio of expected to observed number of breast cancers and assessed discriminatory accuracy using the concordance statistic. Results The BWHS model included family history, previous biopsy, body mass index at age 18 years, age at menarche, age at first birth, oral contraceptive use, bilateral oophorectomy, estrogen plus progestin use, and height. There was good agreement between predicted and observed number of breast cancers overall (expected-to-observed ratio, 0.96; 95% CI, 0.88 to 1.05) and in most risk factor categories. Discriminatory accuracy was higher for women younger than age 50 years (area under the curve [AUC], 0.62; 95% CI, 0.58 to 0.65) than for women age ≥ 50 years (AUC, 0.56; 95% CI, 0.53 to 0.59). Using a 5-year predicted risk of 1.66% or greater as a cut point, 2.8% of women younger than 50 years old and 32.2% of women ≥ 50 years old were classified as being at elevated risk of invasive breast cancer. Conclusion The BWHS model was well calibrated overall, and the predictive ability was best for younger women. The proportion of women predicted to meet the 1.66% cut point commonly used to determine eligibility for breast cancer prevention trials was greatly increased relative to previous models.
Keywords: estrogen; gestagen; adult; African American; aged; area under the curve; article; biopsy; body mass; breast biopsy; breast cancer; cancer diagnosis; cancer risk; controlled study; family history; female; follow up; human; major clinical study; menarche; oral contraceptive use; ovariectomy; priority journal; prospective study; women's health

Cancer fear and fatalism: How African American participants construct the role of research subject in relation to clinical cancer research - Somayaji, D.; Cloyes, K.G. (Cancer Nursing, 2015)
Background: Lack of African American participation in cancer clinical trials has been identified as a critical problem. Historical interactions related to race, identity, and power may contribute to continued inequity in healthcare and research participation. Objective: The aim of this study was to explore the perceptions of African Americans regarding cancer and research and how these perceptions shape their beliefs about participating as cancer research subjects. Methods: Three African American focus groups were conducted including people who had never participated in cancer research, those who had, and those who were asked but refused (n = 16). Discussion focused on their perceptions of cancer research and actual or potential participation as research subjects. Data were coded using both structured and inductive coding methods. Results: Fear and fatalism emerged in relation to research, race, power, and identity and were related to larger historical and social issues rather than only individual thoughts or feelings. Participants described fears of the unknown, death, mistrust, conspiracy, and discrimination together with positive/negative tensions between self, family, and community responsibilities. Conclusion: Complex identities linked perceptions of cancer and cancer research with broader historical and cultural issues. Fear, fatalism, and current and historical relationships influence how people perceive themselves as research subjects and may influence their decisions to participate in cancer research. Implication for Practice: Acknowledging how complex factors including race and racism contribute to health disparities may give nurses and other healthcare providers a better appreciation of how historical, social, and cultural dynamics at individual, community, and organizational levels influence access to and participation in cancer research.
Keywords: adult; African American; aged; article; breast cancer; cancer research; clinical research; clinical trial (topic); community; educational status; family; fatality; fear; female; health belief; human; information processing; male; medical information; middle aged; nurse patient relationship; patient referral; perception; priority journal; prostate cancer; research subject; social discrimination; social interaction; Spiritualism; unemployment; young adult

Diminutive polyps among black and Latino populations undergoing screening colonoscopy: Evidence supporting a resect and discard approach - Lee, K.K.; Jandorf, L.; Itzkowitz, S.H. (Gastrointestinal Endoscopy, 2015)
Background: A resect and discard strategy for diminutive (≤5 mm) colon polyps has been proposed to save costs of screening colonoscopy (SC). Prior studies on neoplasia prevalence based on polyp size have involved mostly white patients. Objective: To determine the prevalence of adenomas and advanced histologic features by size among primarily black and Latino patients enrolled in a prospective SC study. Design: Retrospective analysis of data from a prospective clinical trial. Setting: Urban academic medical center. Patients: Average risk, asymptomatic, minority patients aged ≤50 years undergoing SC. Interventions: Screening colonoscopy. Main Outcome Measurements: Rates of neoplasia and advanced histologic features (villous histology, highgrade dysplasia, or cancer) by polyp size and location. Results: A total of 566 polyps from 295 patients were analyzed. Diminutive polyps and small (6-9 mm) polyps had lower prevalence of ≤1 advanced feature compared with large (≤10 mm) polyps (0.9% and 2.7%, respectively, vs 13.6%; P < .001 for both comparisons). Distal polyps were less likely to be neoplastic (31.7% vs 61.4%; P < .001) than proximal polyps in all size categories (P < .001 for all comparisons). After adjusting for sex, ethnicity, age, and location, large polyps were more likely to have ≤1 advanced feature than diminutive polyps (adjusted odds ratio [OR] 19.5; 95% CI, 4.4-85.6) or small polyps (adjusted OR 6.1; 95% CI, 2.2-16.9). Limitations: Use of pathology reports for polyp size. Conclusion: Among a cohort of minority patients, advanced histologic features were very rare in diminutive polyps. Distal polyps were less likely to be neoplastic than proximal polyps in all size categories. This supports a resect and discard strategy for diminutive polyps, especially in the distal colon.
Keywords: adult; article; Black person; clinical trial (topic); colonoscopy; colorectal adenoma; colorectal polyp; controlled study; female; Hispanic; histology; human; human tissue; major clinical study; male; middle aged; prevalence; priority journal; tumor localization; tumor volume

Strategies for enrollment of African Americans into cancer genetic studies - Ewing, A.; Thompson, N.; Ricks-Santi, L. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2015)
The enrollment of ethnically diverse populations in genetic and genomic research is vital to the parity of benefits resulting from research with biological specimens. Herein, we discuss strategies that may effectively improve the recruitment of African Americans into genetics studies. Specifically, we show that engaging physicians, genetic counselors, and community members is essential to enrolling participants into genetic studies. We demonstrate the impact of utilizing African American genetic counselors on study enrollment rates and implementing a two-page consent form that improved on a lengthy and inefficient consenting process. Lastly, we provided participants with the option of donating saliva instead of blood for study purposes. Descriptive statistics were used. Using the aforementioned strategies, recruitment goals for the Genetic Basis of Breast Cancer Subtype Study at Howard University (HU) were met. Our overall results yielded 182 participants in 18 months. Recruitment strategies that involve the engagement of physicians, genetic counselors, and community members may help researchers increase the enrollment of ethnically diverse and hard-to-reach participants into genetic studies.
Keywords: African American; attitude to health; breast tumor; female; genetics; human; medical research; organization and management; patient compliance; patient participation; patient selection

Exploring the influence of demographic and medical characteristics of African-American and Latinas on enrollment in a behavioral intervention study for breast cancer survivors - Ashing, K.; Rosales, M.; Fernandez, A. (Quality of life research : an international journal of quality of life aspects of treatment, care and rehabilitation, 2015)
PURPOSE: To better understand research participation among hard-to-reach populations, this exploratory investigation examined characteristics of enrollees and non-enrollees from a population-based longitudinal study with African-American and Latina-American breast cancer survivors. METHODS: A mixed-method recruitment approach was utilized to enroll participants from cancer registries and community groups who were 1-6 years post-diagnosis. RESULTS: Four hundred and sixty-eight participants agreed to participate constituting an 81% participation rate; 65 and 55% completed Time-1, and both Time-1 and Time-2 assessments, respectively. African-Americans were more likely to agree to participate and complete the T1 assessment (73%) than Latinas (62%) (p < 0.05). Participation was influenced by educational attainment and comorbidities (p < 0.05) for African-Americans. Among Latinas, language proficiency, comorbidities and psychological difficulties (p < 0.01) influenced participation. CONCLUSIONS: Our findings suggest that enrollment in research studies may be influenced by complex and multi-dimensional factors stemming from subjects' characteristics including ethnicity, culture, language proficiency and literary, and socioeconomic status, as well as medical characteristics including co-occurring chronic illness and psychological status. Thus, comprehensive, multi-method research studies are urgently needed to better understand and address the challenge of minority recruitment in biomedical research. To increase research participation among cancer survivors, it is imperative to implement focused strategies that will support and encourage individuals' enrollment and continued participation in studies.
Keywords: adult; African American; aged; breast tumor; comorbidity; cultural anthropology; ethnology; female; health behavior; Hispanic; human; longitudinal study; middle aged; patient selection; psychology; questionnaire; statistical model; survivor; United States

A pilot randomized controlled trial testing a minimal intervention to prepare breast cancer survivors for recovery - Sterba, K.R.; Armeson, K.; Franco, R.; Harper, J.; Patten, R.; Kindall, S.; Bearden, J.; Zapka, J. (Cancer Nursing, 2015)
Background: Interventions addressing cancer survivors' posttreatment concerns can be time-intensive and require specialized staff. Research is needed to identify feasible minimal intervention strategies to improve survivors' quality of life after treatment. Objectives: The objective of this study was to evaluate the feasibility and short-term impact of a minimal clinic intervention on breast cancer survivors' quality of life, unmet needs, distress, and cancer worry. Interventions/Methods: In this randomized controlled pilot trial, we enrolled breast cancer survivors at the end of treatment and administered baseline surveys. Participants were randomized to study arm (4-week video plus educational booklet intervention group and usual care group) and completed follow-up surveys at 10 weeks. Linear regression was used to examine intervention effects on quality of life outcomes controlling for clinical and demographic factors. Open-ended questions were used to examine program satisfaction and obtain feedback to improve the intervention. Results: We enrolled 92 survivors in the trial. Participants rated the intervention highly and reported feeling less isolated and having more realistic expectations about their recovery after completing the program. Despite positive qualitative findings, no significant intervention effects were observed for quality of life, unmet needs, distress, or cancer worry in unadjusted or adjusted analyses. Conclusions: Future research is needed to define optimal intervention elements to prepare breast cancer survivors for the posttreatment period. Implications for Practice: Effective survivorship interventions may require more intensive components such as clinical input and longer follow-up periods.
Keywords: antineoplastic agent; adult; African American; aged; article; breast cancer; cancer chemotherapy; cancer hormone therapy; cancer survivor; caregiver; Caucasian; controlled study; convalescence; depression; distress syndrome; expectation; feasibility study; female; follow up; health care survey; health program; human; human needs; intervention study; minimal clinic intervention; nutrition education; open-ended questionnaire; patient attitude; patient education; patient satisfaction; patient worry; pilot study; priority journal; program feasibility; quality of life; randomized controlled trial; treatment outcome

Exploratory subset analysis of African Americans from the PointBreak study: Pemetrexed-carboplatin-bevacizumab followed by maintenance pemetrexed-bevacizumab versus paclitaxel-carboplatin-bevacizumab followed by maintenance bevacizumab in patients with stage IIIB/IV nonsquamous non-small-cell lung cancer - Reynolds, C.H.; Patel, J.D.; Garon, E.B.; Olsen, M.R.; Bonomi, P.; Govindan, R.; Pennella, E.J.; Liu, J.; Guba, S.C.; Li, S.; Spigel, D.R.; Hermann, R.C.; et al. (Clinical Lung Cancer, 2015)
Introduction African Americans have a greater incidence of lung cancer than whites and have been underrepresented in clinical trials. In the PointBreak trial (pemetrexed-carboplatin-bevacizumab and maintenance pemetrexed-bevacizumab [PemCBev] vs. paclitaxel-carboplatin-bevacizumab and maintenance bevacizumab [PacCBev]), 10% of the patients were African American. PointBreak had negative findings; PemCBev did not demonstrate superior overall survival (OS). Materials and Methods PointBreak subgroup efficacy and safety data were retrospectively analyzed: African Americans versus whites for PemCBev; PemCBev versus PacCBev in African Americans; and academic versus community settings for African Americans. Hazard ratios (HRs) and P values were derived from a multivariate Cox proportional hazards model after adjusting for covariates. Results Of 939 intent-to-treat (ITT) patients, 94 were African American and 805 were white. African-American enrollment was uniform across the study sites (median, 1 African American per site). In the PemCBev arm, OS (HR, 1.125; P =.525), progression-free survival (PFS) (HR, 1.229; P =.251), response (P =.607), and toxicity profiles were similar in African Americans versus whites. For African Americans, OS (HR, 1.375; P =.209), PFS (HR, 0.902; P =.670), response (P = 1.000), and toxicity profiles were similar in the PemCBev versus PacCBev arm. For African Americans, no significant differences were seen in OS (HR, 0.661; P =.191) or PFS (HR, 0.969; P =.915) in academic versus community practice settings. Conclusion In the PemCBev arm, this exploratory analysis showed no significant differences between African Americans and whites for the efficacy outcomes or toxicity profiles. Consistent with the ITT population negative trial result, for African Americans, the median OS was not superior for either arm. For African Americans, PFS and OS were similar in the academic and community settings. Additional outcomes data for African Americans should be collected in lung cancer studies.
Keywords: NCT00762034; bevacizumab; carboplatin; paclitaxel; pemetrexed; adult; African American; aged; alopecia; area under the curve; article; bleeding; cancer combination chemotherapy; cancer incidence; cancer staging; cancer survival; Caucasian; drug delivery system; drug efficacy; drug safety; fatigue; febrile neutropenia; female; gastrointestinal toxicity; hazard ratio; human; induction chemotherapy; intention to treat analysis; maintenance therapy; major clinical study; male; non small cell lung cancer; open study; overall survival; premedication; progression free survival; pulmonary hypertension; race difference; retrospective study; sensory neuropathy; thrombosis; treatment response; alimta; avastin

Impact of race on selecting appropriate patients for active surveillance with seemingly low-risk prostate cancer - Pietzak, E.J.; Van Arsdalen, K.; Patel, K.; Malkowicz, S.B.; Wein, A.J.; Guzzo, T.J. (Urology, 2015)
Objective To evaluate active surveillance (AS) criteria on their ability to predict favorable pathology at prostatectomy within a low-risk African American (AA) cohort. Methods The sensitivity, specificity, positive predictive value, receiver operator curve, and area under the curve (AUC) were compared for 6 published AS criteria (National Comprehensive Cancer Network; Memorial Sloan-Kettering Cancer Center; Prostate Cancer Research International: Active Surveillance Study; Johns Hopkins-Epstein; University of California at San Francisco; and University of Miami) to predict organ-confined Gleason score 6 disease at prostatectomy in AAs and white Americans (WAs) with low-risk cancer. We also compared clinical parameters for AAs with favorable prostatectomy pathology with those for AAs with unfavorable pathology, and then used preoperative variables associated with unfavorable pathology as an additional exclusion criteria for AS. Results Of 468 patients with low-risk disease, 308 of 402 (76.6%) WAs and 55 of 66 (83.3%) AAs were eligible for AS by one or more criteria (P =.23). For WAs, Prostate Cancer Research International: Active Surveillance Study criteria had the highest rate of favorable pathology (81.7%) and the best performance (AUC = 0.70) in determining appropriate candidates for AS. However, all 6 AS criteria performed poorly for AA patients, with all AUCs 0.52. When comparing AAs with favorable pathology with AAs with unfavorable pathology, only family history of prostate cancer was statistically significant (11 of 25 [47.8%] vs 8 of 41 [22.2%]; P =.04). When adjusting AS criteria in AAs to exclude those with a positive family history, the AUC increased most for the University of California at San Francisco (from 0.52 to 0.6) and Memorial Sloan-Kettering Cancer Center criteria (from 0.50 to 0.58). Conclusion Current criteria underperform in appropriately selecting AAs for AS. AAs considering AS should be counseled about their increased risk for occult adverse pathology, particularly if a family history of prostate cancer is present.
Keywords: active surveillance; adult; African American; article; cancer center; cancer epidemiology; cancer patient; cancer surgery; cohort analysis; controlled study; diagnostic test accuracy study; hereditary tumor syndrome; family history; Gleason score; human; low risk patient; major clinical study; male; middle aged; multicenter study; parameters; pathophysiology; patient selection; predictive value; predictor variable; preoperative evaluation; priority journal; prostate cancer; prostatectomy; race difference; receiver operating characteristic; risk factor; sensitivity and specificity; trend study

Understanding disparity: Researchers strive to recruit more African Americans and other minorities to studies - Printz, C. (Cancer, 2015)
Keywords: African American; breast cancer; cancer center; cancer incidence; cancer mortality; cancer prevention; cancer research; Caucasian; colorectal cancer; diet; ethnic group; health disparity; human; lifestyle; lung cancer; medical society; neoplasm; prostate cancer; residential area; risk factor; short survey; smoking

A phase 1 safety study of veliparib combined with cisplatin and etoposide in extensive stage small cell lung cancer: A trial of the ECOG-ACRIN Cancer Research Group (E2511) - Owonikoko, T.K.; Dahlberg, S.E.; Khan, S.A.; Gerber, D.E.; Dowell, J.; Moss, R.A.; Belani, C.P.; Hann, C.L.; Aggarwal, C.; Ramalingam, S.S. (Lung Cancer, 2015)
Objectives: Veliparib (V) potentiated therapeutic efficacy of cisplatin (C) and etoposide (E) in preclinical models of SCLC. We conducted this phase 1 study to establish the safety of the combination in human subjects. Materials and methods: The study employed the 3+3 dose escalation design to establish the safety and recommended phase 2 dose (RP2D) of V when combined with fixed doses of C (75mg/m2 on day 1) and E (100mg/m2 on days 1-3) in a 21-day cycle. The starting dose of V was 60mg (bid days 1-7) with plan to escalate to 100mg (days 1-7) or de-escalate to 40mg (days 1-7) depending on the dose limiting toxicity (DLT) experience during cycle 1. Patients with treatment-naïve, extensive stage SCLC were included. Results: The study enrolled 9 patients: M/F (4/5); median age (60); White/African American (8/1). V was tolerated at the 60. mg (DLT in 0 of 3 patients) and 100. mg dose (DLT in 1 of 6 patients; grade 5 cardiac failure). Veliparib at 100. mg in combination with standard doses of C and E was established as the RP2D. Grades 3-5 adverse events irrespective of attribution during cycle 1 included: dehydration (1), diarrhea (1), fatigue (1), febrile neutropenia (1), heart failure (1), leukopenia (6), lymphopenia (1), nausea (2), neutropenia (8), respiratory failure (1), and thrombocytopenia (2). Investigator-assessed efficacy outcome in 7 evaluable patients were stable disease in 2/7 (28.6%), partial response in 4/7 (57.1%), and complete response in 1/7 (14.3%) patients. Conclusions: This study demonstrated the safety of combining veliparib with cisplatin and etoposide in previously untreated SCLC patients.
Keywords: NCT01642251; cisplatin; etoposide; veliparib; adult; African American; aged; alopecia; anemia; article; cancer combination chemotherapy; cancer patient; cancer research; cancer staging; cancer survival; chemotherapy induced emesis; chill; clinical article; constipation; dehydration; depression; diarrhea; drug dose escalation; drug efficacy; drug fever; drug induced headache; drug safety; drug tolerability; dysgeusia; European American; fatigue; febrile neutropenia; female; flushing; follow up; heart failure; human; hyperpigmentation; hypokalemia; hyponatremia; infusion related reaction; leukopenia; lymphocytopenia; male; medical assessment; mucosa inflammation; multicenter study; multiple cycle treatment; nausea; neutropenia; optimal drug dose; oral mucositis; outcome assessment; overall survival; peripheral neuropathy; phase 1 clinical trial; phase 2 clinical trial; priority journal; recommended drug dose; respiratory failure; side effect; small cell lung cancer; sore throat; thrombocytopenia; tinnitus; treatment response

Risk-benefit profiles of women using tamoxifen for chemoprevention - Nichols, H.B.; DeRoo, L.A.; Scharf, D.R.; Sandler, D.P. (Journal of the National Cancer Institute, 2015)
Background: Tamoxifen has been US Food and Drug Administration-approved for primary prevention of breast cancer since 1998 but has not been widely adopted, in part because of increased risk of serious side effects. Little is known about the risk-benefit profiles of women who use chemoprevention outside of a clinical trial. We examined characteristics associated with initiation and discontinuation of tamoxifen for primary prevention of breast cancer within a large cohort of women with a first-degree family history of breast cancer. Methods: This research was conducted within The Sister Study, a cohort of 50 884 US and Puerto Rican women age 35 to 74 years enrolled from 2003 to 2009. Eligible women were breast cancer-free at enrollment and had a sister who had been diagnosed with breast cancer. Participants reported tamoxifen use, ages started and stopped taking tamoxifen, and total duration of use at enrollment. We identified 788 tamoxifen users and 3131 nonusers matched on age and year of enrollment who had no history of contraindicating factors (stroke, transient ischemic attack, cataract, endometrial or uterine cancer). Characteristics associated with tamoxifen initiation were evaluated with multivariable conditional logistic regression. All statistical tests were two-sided. Results: Based on published risk-benefit indices, 20% of women who used tamoxifen had insufficient evidence that the benefits of tamoxifen outweigh the risk of serious side effects. After 4.5 years, 46% of women had discontinued tamoxifen. Conclusions: While the majority of women who used tamoxifen for primary prevention of breast cancer were likely to benefit, substantial discontinuation of tamoxifen before five years and use by women at risk of serious side effects may attenuate benefits for breast cancer prevention.
Keywords: tamoxifen; adult; African American; age; aged; article; breast cancer; cancer prevention; cancer risk; Caucasian; cohort analysis; drug use; family history; female; first-degree relative; human; hysterectomy; major clinical study; ovariectomy; primary prevention; priority journal; Puerto Rican; race difference; risk benefit analysis; sensitivity analysis; telephone interview; treatment duration

A phase II double-blinded study to evaluate the efficacy of EW02 in reducing chemotherapy-induced neutropenia in breast cancer - Wu, Y.-Y.; Liu, H.-Y.; Huang, T.-C.; Chen, J.-H.; Chang, P.-Y.; Ho, C.-L.; Chao, T.-Y. (Oncology Letters, 2015)
EW02, a polysaccharide-enriched crude extract from black soybean, has been shown to assist hematopoiesis in chemotherapy‑treated animals. The present study aimed to clarify the safety, quality of life (QOL) and efficacy for myelopoiesis of EW02 administration in early breast cancer (EBC) patients receiving adjuvant chemotherapy. A total of 60 eligible EBC patients were enrolled in a randomized, double‑blinded trial, 40 of whom were prescribed 700 mg oral EW02 three times daily for 15 days in chemotherapy cycle (C)2. The remainder were prescribed a placebo. All subjects took EW02 in C3 for 15 days. Blood samples were collected at different time‑points for determining the blood cell count, and the serum level of granulocyte colony‑stimulating factor (G‑CSF) and interleukin (IL)‑6. All patients tolerated EW02 well without severe side‑effects. QOL evaluation showed that only the score of one questionnaire section (QLQ‑C30) was significantly increased at C1 day (D)8 to C2D8 when the EW02 and placebo groups were compared (P=0.045). No significant myelopoiesis recovery, and no incremental change in IL‑6 and G‑CSF levels were found in C2. Subgroup analysis showed a slightly lower decrease in absolute neutrophil count (ANC) in the EW02 patients who underwent Adriamycin + cyclophosphamide treatment compared with the placebo group. Although EW02 failed to show efficacy for myelopoiesis in the present study, EW02 was still well tolerated in EBC patients who underwent adjuvant chemotherapy.
Keywords: NCT00555516; cyclophosphamide; doxorubicin; ew02; fluorouracil; granulocyte colony stimulating factor receptor; interleukin 6; placebo; soybean extract; unclassified drug; adult; anorexia; article; asthenia; breast cancer; cancer adjuvant therapy; cardiovascular disease; crossover procedure; double blind procedure; drug efficacy; drug safety; drug tolerability; febrile neutropenia; follow up; gastrointestinal symptom; human; insomnia; leukocyte count; leukopenia; major clinical study; middle aged; myelopoiesis; nausea and vomiting; neutropenia; neutrophil count; phase 2 clinical trial; pilot study; quality of life; randomized controlled trial; skin disease

A phase II clinical trial of weekly paclitaxel and carboplatin in combination with panitumumab in metastatic triple negative breast cancer - Cowherd, S.; Miller, L.D.; Melin, S.A.; Akman, S.; Isom, S.; Cole, J.; Pullikuth, A.; Lawrence, J.A. (Cancer Biology and Therapy, 2015)
Purpose: Women with metastatic triple negative breast cancer (TNBC) can have a poor prognosis with treatment limited to cytotoxic chemotherapy. The identification of effective therapies that may limit exposure to cytotoxic chemotherapy and lead to prolonged survival is an unmet medical need. We tested an inhibitor of the epidermal growth factor receptor, panitumumab in combination with chemotherapy. Methods: We conducted a single arm clinical trial in women with metastatic or locally advanced TNBC to paclitaxel 80 mg/m2 and carboplatin AUC of 2 on days 1, 8, and 15 and panitumumab 6 mg/kg on days 1 and 15 for a cycle length of 28 days. The objectives were to evaluate the response rate and safety of the combination in comparison to historical controls. Results: Fourteen patients with TNBC were enrolled with a median age of 53 years. The majority of women were African American (64.3%) with visceral metastasis (64.2%). Hematologic toxicities, particularly neutropenia and thrombocytopenia, were a major cause of missed chemotherapy and delayed treatment in this study. The overall response rate (complete and partial response) of the 13 evaluable patients was 46%. The median time to best response was 2.4 months and the median time to disease progression was 3.6 months. We were able to perform the PAM50 analysis on tumors from 7 of our subjects. All the samples tested clustered within the basal-like subtype. Conclusions: In our experience the response rate of carboplatin, paclitaxel and panitumumab was consistent with other reports of response for cytotoxic chemotherapy in metastatic TNBC.
Keywords: carboplatin; paclitaxel; panitumumab; acne; adult; African American; aged; area under the curve; article; metastatic breast cancer; cancer combination chemotherapy; cancer growth; clinical article; controlled clinical trial; controlled study; desquamation; diarrhea; drug eruption; drug safety; dry skin; female; gene expression; hand foot syndrome; human; hypocalcemia; hypokalemia; hypomagnesemia; multiple cycle treatment; nail disease; neutropenia; phase 2 clinical trial; pruritus; skin toxicity; survival time; therapy delay; thrombocytopenia; treatment response; triple negative breast cancer; visceral metastasis

Addressing health disparities in Hispanic breast cancer: Accurate and inexpensive sequencing of BRCA1 and BRCA2 - Dean, M.; Boland, J.; Yeager, M.; Im, K.M.; Garland, L.; Rodriguez-Herrera, M.; Perez, M.; Mitchell, J.; Roberson, D.; Jones, K.; Lee, H.J.; Eggebeen, R.; et al. (GigaScience, 2015)
Background: Germline mutations in the BRCA1 and BRCA2 genes account for 20-25 % of inherited breast cancers and about 10 % of all breast cancer cases. Detection of BRCA mutation carriers can lead to therapeutic interventions such as mastectomy, oophorectomy, hormonal prevention therapy, improved screening, and targeted therapies such as PARP-inhibition. We estimate that African Americans and Hispanics are 4-5 times less likely to receive BRCA screening, despite having similar mutation frequencies as non-Jewish Caucasians, who have higher breast cancer mortality. To begin addressing this health disparity, we initiated a nationwide trial of BRCA testing of Latin American women with breast cancer. Patients were recruited through community organizations, clinics, public events, and by mail and Internet. Subjects completed the consent process and questionnaire, and provided a saliva sample by mail or in person. DNA from 120 subjects was used to sequence the entirety of BRCA1 and BRCA2 coding regions and splice sites, and validate pathogenic mutations, with a total material cost of $85/subject. Subjects ranged in age from 23 to 81 years (mean age, 51 years), 6 % had bilateral disease, 57 % were ER/PR+, 23 % HER2+, and 17 % had triple-negative disease. Results: A total of seven different predicted deleterious mutations were identified, one newly described and the rest rare. In addition, four variants of unknown effect were found. Conclusions: Application of this strategy on a larger scale could lead to improved cancer care of minority and underserved populations.
Keywords: BRCA1 protein; BRCA2 protein; DNA; epidermal growth factor receptor 2; estrogen receptor; progesterone receptor; adult; age distribution; aged; article; breast cancer; controlled study; cost benefit analysis; DNA determination; DNA splicing; genetic variability; health disparity; Hispanic; human; informed consent; major clinical study; population research; priority journal; questionnaire; saliva analysis; sequence analysis; South and Central America; triple negative breast cancer; very elderly

Communication preference moderates the effect of a tailored intervention to increase colorectal cancer screening among African Americans - Resnicow, K.; Zhou, Y.; Hawley, S.; Jimbo, M.; Ruffin, M.T.; Davis, R.E.; Shires, D.; Lafata, J.E. (Patient Education and Counseling, 2014)
Objective: Test the impact of tailoring CRC screening messages for African Americans (AAs) using novel theoretical variables and to examine moderating effect of communication preferences. Methods: Participants were randomized to receive two minimally tailored or two enhanced tailored print newsletters addressing CRC. The enhanced intervention was tailored on Self-Determination Theory and other novel psychological constructs. Minimal tailoring only used information available in the patient's EHR. The primary outcome was CRC screening based on EHR. Participants were AA members aged 50-74 of an integrated health care delivery system not up to date on CRC screening. Results: We enrolled 881 participants. CRC screening participation rates at 1-year follow up were 20.5% and 21.5% in the minimally and enhanced tailored groups, respectively. Communication preferences moderated the impact of the intervention. Specifically, among those with an autonomous communication preference, screening rates in the minimally and enhanced tailored groups were 17.1% and 25.9%, respectively, while no intervention effect was evident among those with a directive preference. Conclusion: Future research is needed to explore the impact of communication preference tailoring for other health behaviors and among other populations. Practice implications: Tailored communications should consider communication style preference to help guide the content and tone of messages.
Keywords: adult; African American; aged; article; cancer screening; colorectal cancer; electronic medical record; female; health behavior; health care; health care utilization; human; major clinical study; male; medical information; patient attitude; patient participation; patient preference; publication; randomized controlled trial

Implementation intentions and colorectal screening: A randomized trial in safety-net clinics - Greiner, K.A.; Daley, C.M.; Epp, A.; James, A.; Yeh, H.-W.; Geana, M.; Born, W.; Engelman, K.K.; Shellhorn, J.; Hester, C.M.; Lemaster, J.; Buckles, D.C.; et al. (American Journal of Preventive Medicine, 2014)
Context Low-income and racial/ethnic minority populations experience disproportionate colorectal cancer (CRC) burden and poorer survival. Novel behavioral strategies are needed to improve screening rates in these groups. Background The study aimed to test a theoretically based "implementation intentions" intervention for improving CRC screening among unscreened adults in urban safety-net clinics. Design Randomized controlled trial. Setting/participants Adults (N=470) aged ≥50 years, due for CRC screening, from urban safety-net clinics were recruited. Intervention The intervention (conducted in 2009-2011) was delivered via touchscreen computers that tailored informational messages to decisional stage and screening barriers. The computer then randomized participants to generic health information on diet and exercise (Comparison group) or "implementation intentions" questions and planning (Experimental group) specific to the CRC screening test chosen (fecal immunochemical test or colonoscopy). Main outcome measures The primary study outcome was completion of CRC screening at 26 weeks based on test reports (analysis conducted in 2012-2013). Results The study population had a mean age of 57 years and was 42% non-Hispanic African American, 28% non-Hispanic white, and 27% Hispanic. Those receiving the implementation intentions-based intervention had higher odds (AOR=1.83, 95% CI=1.23, 2.73) of completing CRC screening than the Comparison group. Those with higher self-efficacy for screening (AOR=1.57, 95% CI=1.03, 2.39), history of asthma (AOR=2.20, 95% CI=1.26, 3.84), no history of diabetes (AOR=1.86, 95% CI=1.21, 2.86), and reporting they had never heard that "cutting on cancer" makes it spread (AOR=1.78, 95% CI=1.16, 2.72) were more likely to complete CRC screening. Conclusions The results of this study suggest that programs incorporating an implementation intentions approach can contribute to successful completion of CRC screening even among very low-income and diverse primary care populations. Future initiatives to reduce CRC incidence and mortality disparities may be able to employ implementation intentions in large-scale efforts to encourage screening and prevention behaviors.
Keywords: adult; article; asthma; cancer screening; colonoscopy; colorectal cancer; software; controlled study; female; follow up; health behavior; human; implementation intention; male; occult blood test; outcome assessment; patient decision making; randomized controlled trial; safety net hospital

Neighborhood factors associated with time to resolution following an abnormal breast or cervical cancer screening test - Plascak, J.J.; Llanos, A.A.; Pennell, M.L.; Weier, R.C.; Paskett, E.D. (Cancer Epidemiology Biomarkers and Prevention, 2014)
Background: The effect of neighborhood and healthcare access factors on cancer outcomes among patients enrolled in navigator programs is not clearly understood. This study assessed associations between: (i) neighborhood factors and diagnostic time to resolution (TTR) and (ii) geographic access and TTR following an abnormal breast or cervical cancer screening test among women participating in the Ohio Patient Navigator Research Program (OPNRP). Methods: Patient (demographic, socioeconomic status, home-to-clinic distance) and neighborhood (deprivation, racial segregation) characteristics of 801 women living in one of 285 census tracts (CT) in greater Columbus, Ohio were examined. Randomization to receive navigation occurred at the clinic level. Multilevel Cox regression and spatial analysis were used to estimate effects of various factors on TTR and assess model assumptions, respectively. Results: TTR increased as neighborhood deprivation increased. After adjustment for age, friend social support, education, and healthcare status, the TTR among women living in a neighborhood with a moderate median household income (between $36,147 and $53,099) was shorter compared with women living in low median household income neighborhoods (<$36,147; P < 0.05). There is little evidence that unmeasured confounders are geographically patterned. Conclusions: Increased neighborhood socioeconomic deprivation was associated with longer TTR following an abnormal breast or cervical cancer screening test. Impact: These results highlight the need for addressing patient- and neighborhood-level factors to reduce cancer disparities among underserved populations.
Keywords: adult; African American; age; article; breast cancer; cancer screening; educational status; European American; female; health care concepts; health care disparity; human; income; major clinical study; medical record review; medically uninsured; multicenter study (topic); neighborhood; private health insurance; public health insurance; randomized controlled trial (topic); social status; social support; time to resolution; uterine cervix cancer

Retention of black and white participants in the selenium and vitamin E cancer prevention trial (SWOG-coordinated intergroup study S0000) - Arnold, K.B.; Hermos, J.A.; Anderson, K.B.; Minasian, L.; Tangen, C.M.; Probstfield, J.F.; Cook, E.D. (Cancer Epidemiology Biomarkers and Prevention, 2014)
Background: Disproportionally low retention of minority populations can adversely affect the generaliz-ability of clinical research trials. We determine the overall retention rates for White and Black participants from the Selenium and Vitamin E Cancer Prevention Trial (SELECT) and explore participant and site characteristics associated with retention failure (study disengagement) for these groups. Methods: A secondary analysis of 28,118 White (age ≥55), and 4,322 Black (age ≥ 50) SELECT participants used multivariate Cox regression to estimate overall retention rates and to calculate HRs and 95% confidence intervals (CI). Results: Blacks had higher age-adjusted risk of disengagement than Whites (HR, 1.92; 95% CI, 1.77-2.08). Among Black participants, those ages 50 to 54 were at three times the risk of disengagement than those ≥65 years of age (HR, 3.61; 95% CI, 2.41-5.41). Blacks age ≥65 had 1.6 times the risk of disengagement than Whites age >65 (HR, 1.60; 95% CI, 1.38-1.87). By 6 years after randomization, 84% of Whites and 69% of Blacks remained engaged in the study. Current smoking status was an independent risk factor for study disengagement for both White and Black participants. For both groups, sites whose staffs missed SELECT training sessions or who received SELECT Retention and Adherence grants were associated with increased and decreased disengagement risks, respectively. Conclusions: SELECT retention was disproportionately lower for Blacks than for Whites. Impact: The observed difference in retention rates for Blacks and Whites and factors identified by race for study disengagement in SELECT may inform retention efforts for future long-term, cancer prevention trials.
Keywords: NCT00006392; alpha tocopherol; selenium; adult; aged; article; Black person; cancer prevention; Caucasian; comorbidity; controlled clinical trial; controlled study; double blind procedure; human; major clinical study; male; phase 3 clinical trial; prostate cancer; race difference; risk factor; smoking

A community-based, culturally relevant intervention to promote healthy eating and physical activity among middle-aged African American women in rural Alabama: findings from a group randomized controlled trial - Scarinci, I.C.; Moore, A.; Wynn-Wallace, T.; Cherrington, A.; Fouad, M.; Li, Y. (Preventive medicine, 2014)
OBJECTIVE: We examined the efficacy of a community-based, culturally relevant intervention to promote healthy eating and physical activity among African American (AA) women between the ages of 45-65 years, residing in rural Alabama. METHODS: We conducted a group randomized controlled trial with counties as the unit of randomization that evaluated two interventions based on health priorities identified by the community: (1) promotion of healthy eating and physical activity; and (2) promotion of breast and cervical cancer screening. A total of 6 counties with 565 participants were enrolled in the study between November 2009 and October 2011. RESULTS: The overall retention rate at 24-month follow-up was 54.7%. Higher retention rate was observed in the "healthy lifestyle" arm (63.1%) as compared to the "screening" arm (45.3%). Participants in the "healthy lifestyle" arm showed significant positive changes compared to the "screening" arm at 12-month follow-up with regard to decrease in fried food consumption and an increase in both fruit/vegetable intake and physical activity. At 24-month follow-up, these positive changes were maintained with healthy eating behaviors, but not engagement in physical activity. CONCLUSIONS: A culturally relevant intervention, developed in collaboration with the target audience, can improve (and maintain) healthy eating among AA women living in rural areas.
Keywords: adult; African American; Alabama; controlled study; cultural anthropology; ethnology; exercise; feeding behavior; female; health behavior; health promotion; human; middle aged; participatory research; randomized controlled trial; rural population

Communication preference moderates the effect of a tailored intervention to increase colorectal cancer screening among African Americans - Resnicow, K.; Zhou, Y.; Hawley, S.; Jimbo, M.; Ruffin, M.T.; Davis, R.E.; Shires, D.; Lafata, J.E. (Patient education and counseling, 2014)
OBJECTIVE: Test the impact of tailoring CRC screening messages for African Americans (AAs) using novel theoretical variables and to examine moderating effect of communication preferences. METHODS: Participants were randomized to receive two minimally tailored or two enhanced tailored print newsletters addressing CRC. The enhanced intervention was tailored on Self-Determination Theory and other novel psychological constructs. Minimal tailoring only used information available in the patient's EHR. The primary outcome was CRC screening based on EHR. Participants were AA members aged 50-74 of an integrated health care delivery system not up to date on CRC screening. RESULTS: We enrolled 881 participants. CRC screening participation rates at 1-year follow up were 20.5% and 21.5% in the minimally and enhanced tailored groups, respectively. Communication preferences moderated the impact of the intervention. Specifically, among those with an autonomous communication preference, screening rates in the minimally and enhanced tailored groups were 17.1% and 25.9%, respectively, while no intervention effect was evident among those with a directive preference. CONCLUSION: Future research is needed to explore the impact of communication preference tailoring for other health behaviors and among other populations. PRACTICE IMPLICATIONS: Tailored communications should consider communication style preference to help guide the content and tone of messages.
Keywords: African American; aged; attitude to health; colorectal tumor; controlled study; early cancer diagnosis; education; ethnology; female; human; male; mass screening; medical information; Michigan; middle aged; patient attitude; patient compliance; patient education; patient preference; procedures; psychology; randomized controlled trial; statistics and numerical data; teaching; utilization

Phase II clinical trial of gefitinib for the treatment of chemonaïve patients with advanced non-small cell lung cancer with poor performance status - Karim, N.A.; Musaad, S.; Zarzour, A.; Patil, S.; Jazieh, A.R. (Clinical Medicine Insights: Oncology, 2014)
Background: Patients with advanced non-small cell lung cancer (NSCLC) have no curative treatment options; therefore, improving their quality of life (QOL) is an important goal. Gefitinib, an epidermal growth factor receptor (EGFR) inhibitor, is a safe oral agent that may be of benefit to a specific population of NSCLC. Patients and methods: A Phase II clinical trial included chemonaïve patients with advanced NSCLC and poor performance status (PS). Response rate, progression-free survival, overall survival, QOL using the Functional Assessment of Cancer Therapy – Lung (FACT-L) questionnaire, and Trial Outcome Index (TOI) were evaluated. Results: Twelve out of 19 enrolled patients were evaluable. The median age for the evaluable patients was 68.8 years (59.7–74.6). Out of all the patients, 7 (58.3%) had adenocarcinoma and 5 (41.7%) had squamous cell carcinoma. The median duration of treatment was 62.5 days (26.5–115.0) in the evaluable patients. Grade 3/4 toxicities included fatigue, rash, diarrhea, and nausea. One patient had partial response, eight patients had stable disease (SD), and three patients progressed. The median overall survival for the evaluable population was 4.9 months (2.3–16). The median progression-free survival was 3.7 months (1.9–6.6). TOI was marginally associated with the overall survival, with a hazard ratio of 0.92 (95% confidence interval: 0.84, 1.0) (P = 0.061). FACT-L score and the TOI were highly correlated (r = 0.96, P < 0.0001). TOI scores were higher in African Americans compared to Caucasians and increased with age. Conclusion: Our results suggest that gefitinib use in patients with NSCLC and poor PS may improve the QOL of older patients and African American patients.
Keywords: gefitinib; adenocarcinoma; advanced cancer; African American; aged; anemia; article; cancer survival; Caucasian; clinical article; controlled study; diarrhea; drug efficacy; drug response; drug safety; fatigue; female; fever; human; male; multiple cycle treatment; nausea; nephrotoxicity; non small cell lung cancer; overall survival; pain; phase 2 clinical trial; progression free survival; quality of life; rash; scoring system; squamous cell carcinoma; survival rate; thrush; treatment duration

A community-based, culturally relevant intervention to promote healthy eating and physical activity among middle-aged African American women in rural Alabama: Findings from a group randomized controlled trial - Scarinci, I.C.; Moore, A.; Wynn-Wallace, T.; Cherrington, A.; Fouad, M.; Li, Y. (Preventive Medicine, 2014)
Objective: We examined the efficacy of a community-based, culturally relevant intervention to promote healthy eating and physical activity among African American (AA) women between the ages of 45-65 years, residing in rural Alabama. Methods: We conducted a group randomized controlled trial with counties as the unit of randomization that evaluated two interventions based on health priorities identified by the community: (1) promotion of healthy eating and physical activity; and (2) promotion of breast and cervical cancer screening. A total of 6 counties with 565 participants were enrolled in the study between November 2009 and October 2011. Results: The overall retention rate at 24-month follow-up was 54.7%. Higher retention rate was observed in the "healthy lifestyle" arm (63.1%) as compared to the "screening" arm (45.3%). Participants in the "healthy lifestyle" arm showed significant positive changes compared to the "screening" arm at 12-month follow-up with regard to decrease in fried food consumption and an increase in both fruit/vegetable intake and physical activity. At 24-month follow-up, these positive changes were maintained with healthy eating behaviors, but not engagement in physical activity. Conclusions: A culturally relevant intervention, developed in collaboration with the target audience, can improve (and maintain) healthy eating among AA women living in rural areas.
Keywords: adult; African American; aged; article; breast cancer; cancer screening; cultural factor; eating; feeding behavior; female; food intake; fruit vegetable; health promotion; human; lifestyle; major clinical study; physical activity; randomized controlled trial; United States; uterine cervix cancer

Discussions about clinical trials among patients with newly diagnosed lung and colorectal cancer - Kehl, K.L.; Arora, N.K.; Schrag, D.; Ayanian, J.Z.; Clauser, S.B.; Klabunde, C.N.; Kahn, K.L.; Fletcher, R.H.; Keating, N.L. (Journal of the National Cancer Institute, 2014)
Background: Clinical trials are essential to establish the effectiveness of new cancer therapies, but less than 5% of adults with cancer enroll in trials. In addition to ineligibility or lack of available trials, barriers to enrollment may include limited patient awareness about the option of participation. Methods: We surveyed a multiregional cohort of patients with lung or colorectal cancer (or their surrogates) three to six months after diagnosis. We assessed whether respondents reported learning that clinical trial participation might be an option, and, if so, with whom they discussed trials. We used logistic regression to assess the association of patient characteristics with discussing trial participation and enrolling in trials. All statistical tests were two-sided. Results: Of 7887 respondents, 1114 (14.1%) reported discussing the possibility of clinical trial participation; most learned about trials from their physicians, and 287 patients (3.6% of all patients, 25.8% of trial discussants) enrolled. Among 2173 patients who received chemotherapy for advanced (stage III/IV lung or stage IV colorectal) cancer, 25.7% discussed trials, and 7.6% (29.5% of trial discussants) enrolled. Discussions were less frequent among older patients, African American or Asian vs white patients, and those with lower incomes and more comorbidity. Enrollment was higher among patients reporting shared vs physician-driven decisions (all P <.05). Conclusions: In this population-based cohort, only 14% of patients discussed participation in clinical trials. Discussions were more frequent among advanced cancer patients but were still reported by a minority of patients. Strategies to expand access to trials and facilitate patient-provider communication about participation may accelerate development of better cancer therapeutics.
Keywords: adult; African American; age; age; aged; aged; article; article; Asian American; cancer chemotherapy; cancer staging; cancer staging; Caucasian; clinical trial (topic); clinical trial (topic); cohort analysis; cohort analysis; colorectal cancer; colorectal tumor; comorbidity; comorbidity; decision making; diagnosis; diagnosis; female; female; health survey; human; human; income; income; information seeking; interpersonal communication; lung cancer; lung tumor; major clinical study; male; male; middle aged; middle aged; observational study; outcome assessment; pathology; patient participation; patient participation; patient selection; priority journal; questionnaire; race difference; sensitivity analysis; socioeconomics; statistics; therapy; therapy; United States; very elderly

Decisional conflict in economically disadvantaged men with newly diagnosed prostate cancer: Baseline results from a shared decision-making trial - Kaplan, A.L.; Crespi, C.M.; Saucedo, J.D.; Connor, S.E.; Litwin, M.S.; Saigal, C.S. (Cancer, 2014)
BACKGROUND Decisional conflict is a source of anxiety and stress for men diagnosed with prostate cancer given uncertainty surrounding myriad treatment options. Few data exist to help clinicians identify which patients are at risk for decisional conflict. The purpose of this study was to examine factors associated with decisional conflict in economically disadvantaged men diagnosed with prostate cancer before any treatment choices were made. METHODS A total of 70 men were surveyed at a Veterans Administration clinic with newly diagnosed localized prostate cancer enrolled in a randomized trial testing a novel shared decision-making tool. Baseline demographic, clinical, and functional data were collected. Independent variables included age, race, education, comorbidity, relationship status, urinary/sexual dysfunction, and prostate cancer knowledge. Tested outcomes were Decisional Conflict Scale, Uncertainty Subscale, and Perceived Effectiveness Subscale. Multiple linear regression modeling was used to identify factors associated with decisional conflict. RESULTS Mean age was 63 years, 49% were African American, and 70% reported an income less than $30,000. Poor prostate cancer knowledge was associated with increased decisional conflict and higher uncertainty (P<.001 and P=0.001, respectively). Poor knowledge was also associated with lower perceived effectiveness (P=0.003) whereas being in a relationship was associated with higher decisional conflict (P=0.03). CONCLUSIONS Decreased patient knowledge about prostate cancer is associated with increased decisional conflict and lower perceived effective decision-making. Interventions to increase comprehension of prostate cancer and its treatments may reduce decisional conflict. Further work is needed to better characterize this relationship and identify effective targeted interventions. Cancer 2014;120:2721-2727. © 2014 American Cancer Society. In economically disadvantaged men with newly diagnosed prostate cancer, a poor understanding of the disease is associated with personal conflict surrounding the treatment decision. Targeted educational interventions may mitigate the decisional burden. © 2014 American Cancer Society.
Keywords: adult; African American; age distribution; aged; article; attitude to illness; cohort analysis; controlled study; cross-sectional study; decisional conflict; Decisional Conflict Scale Perceived Efficacy subscale; Decisional Conflict Scale Uncertainty subscale; economically disadvantaged man; educational status; high risk population; human; income; major clinical study; male; marriage; assessment of humans; outcome assessment; patient attitude; patient decision making; population and population related phenomena; priority journal; prostate cancer; risk assessment; risk factor

"We both just trusted and leaned on the Lord": a qualitative study of religiousness and spirituality among African American breast cancer survivors and their caregivers - Sterba, K.R.; Burris, J.L.; Heiney, S.P.; Ruppel, M.B.; Ford, M.E.; Zapka, J. (Quality of life research : an international journal of quality of life aspects of treatment, care and rehabilitation, 2014)
PURPOSE: Most breast cancer (BC) survivorship research focuses on the general population of survivors. Scant research investigates the potentially unique experiences of minorities, especially during and after the difficult transition from primary treatment to post-treatment. This qualitative study explored African American BC survivors' and caregivers' quality-of-life in the post-treatment period with a focus on social and spiritual well-being. METHODS: Participants included a convenience sample of African American women with stage I-III BC (N = 23) who completed treatment 6-24 months before enrollment. Primary caregivers (N = 22) included friends, spouses and other family members (21 complete dyads). Participants completed separate semi-structured telephone interviews. Template analysis was used to evaluate themes related to religiousness and spirituality, both across and within dyads. RESULTS: After treatment, religiousness and spirituality played a major role in both survivors' and caregivers' lives by: (1) providing global guidance, (2) guiding illness management efforts and (3) facilitating recovery. Participants described a spiritual connectedness with God and others in their social networks. Dyad members shared the goal of keeping a positive attitude and described positive growth from cancer. Few future concerns were expressed due to the belief that survivors were healed and "done" with cancer. Beyond practical and emotional support, provision of spiritual assistance was common. CONCLUSIONS: Results highlight the principal, positive role of religiousness and spirituality for African American BC survivors and caregivers after treatment. Findings emphasize the need to assess the importance of religious and spiritual beliefs and practices, and if appropriate, to provide resources that promote spiritual well-being.
Keywords: adult; African American; aged; attitude to health; breast tumor; caregiver; clinical trial; cultural anthropology; female; human; middle aged; multicenter study; psychology; qualitative research; quality of life; religion; social support; survivor

Risk factors for self-reported arm lymphedema among female breast cancer survivors: A prospective cohort study - Togawa, K.; Ma, H.; Sullivan-Halley, J.; Neuhouser, M.L.; Imayama, I.; Baumgartner, K.B.; Smith, A.W.; Alfano, C.M.; McTiernan, A.; Ballard-Barbash, R.; Bernstein, L. (Breast Cancer Research, 2014)
Introduction: Lymphedema is a potentially debilitating condition that occurs among breast cancer survivors. This study examines the incidence of self-reported lymphedema, timing of lymphedema onset, and associations between sociodemographic, clinical and lifestyle factors and lymphedema risk across racial-ethnic groups using data from a multicenter, multiethnic prospective cohort study of breast cancer survivors, the Health, Eating, Activity and Lifestyle Study. Methods: A total of 666 women diagnosed with breast cancer staged as in situ, localized or regional disease at ages 35 to 64years were recruited through the Surveillance, Epidemiology, and End Results registries in New Mexico (non-Hispanic white and Hispanic white), Los Angeles County (black), and Western Washington (non-Hispanic white) and followed for a median of 10.2years. We evaluated sociodemographic factors, breast cancer- and treatment-related factors, comorbidities, body mass index (BMI), hormonal factors, and lifestyle factors in relation to self-reported lymphedema by fitting Cox proportional hazards models, estimating hazard ratios (HR) and 95% confidence intervals (CI). Results: Over the follow-up period, 190 women (29%) reported lymphedema. The median time from breast cancer diagnosis to onset of lymphedema was 10.5months (range: 0.5 to 134.9months). Factors independently associated with lymphedema were total/modified radical mastectomy (versus partial/less than total mastectomy; HR = 1.37, 95% CI: 1.01 to 1.85), chemotherapy (versus no chemotherapy; HR = 1.48, 95% CI: 1.09 to 2.02), no lymph nodes removed (versus ≥10 lymph nodes removed; HR = 0.17, 95% CI: 0.08 to 0.33), pre-diagnostic BMI ≥30kg/m2 (versus BMI <25kg/m2; HR = 1.59, 95% CI: 1.09 to 2.31), and hypertension (versus no hypertension; HR = 1.49, 95% CI: 1.06 to 2.10). After adjusting for demographics and breast cancer- and treatment-related factors, no significant difference in lymphedema risk was observed across racial/ethnic groups. Analyses stratified by race/ethnicity showed that hypertension and chemotherapy were lymphedema risk factors only for black women. Conclusions: Breast cancer patients who have undergone extensive surgery or extensive lymph node dissection, or who have a higher BMI should be closely monitored for detection and treatment of lymphedema. Further studies are needed to understand the roles of chemotherapy and hypertension in the development of lymphedema.
Keywords: contraceptive agent; estrogen; gestagen; tamoxifen; adult; article; Black person; body mass; breast cancer; cancer chemotherapy; cancer staging; cancer survivor; Caucasian; cohort analysis; comorbidity; controlled clinical trial; controlled study; demography; female; follow up; Hispanic; human; hypertension; lifestyle; lymphedema; major clinical study; mastectomy; multicenter study; prospective study; risk assessment; risk factor; self report; social status

Characterization of black raspberry functional food products for cancer prevention human clinical trials - Gu, J.; Ahn-Jarvis, J.H.; Riedl, K.M.; Schwartz, S.J.; Clinton, S.K.; Vodovotz, Y. (Journal of agricultural and food chemistry, 2014)
Our team is designing and fully characterizing black raspberry (BRB) food products suitable for long-term cancer prevention studies. The processing, scale-up, and storage effects on the consistency, quality, bioactive stability, and sensory acceptability of two BRB delivery systems of various matrices are presented. BRB dosage, pH, water activity, and texture were consistent in the scale-up production. Confections retained >90% of anthocyanins and ellagitannin after processing. Nectars had >69% of anthocyanins and >66% of ellagitannin retention, which varied with BRB dosage due to the processing difference. Texture remained unchanged during storage. BRB products consumed in a prostate cancer clinical trial were well accepted in sensory tests. Thus, this study demonstrates that two different BRB foods can be formulated to meet quality standards with a consistent bioactive pattern and successfully scaled up for a large human clinical trial focusing on cancer risk and other health outcomes.
Keywords: anthocyanin; antioxidant; analysis; chemistry; clinical trial; diet therapy; food handling; fruit; functional food; human; male; metabolism; middle aged; neoplasm; prostate tumor; Rubus

Vitamin D deficiency predicts prostate biopsy outcomes - Murphy, A.B.; Nyame, Y.; Martin, I.K.; Catalona, W.J.; Hollowell, C.M.P.; Nadler, R.B.; Kozlowski, J.M.; Perry, K.T.; Kajdacsy-Balla, A.; Kittles, R. (Clinical Cancer Research, 2014)
Purpose: The association between vitamin D and prostate biopsy outcomes has not been evaluated. We examine serum vitamin D levels with prostate biopsy results in men with an abnormal prostate-specific antigen and/or digital rectal examination. Experimental Design: Serum 25-hydroxyvitamin D (25-OH D) was obtained from 667 men, ages 40 to 79 years, prospectively enrolled from Chicago urology clinics undergoing first prostate biopsy. Logistic regression was used to evaluate the associations between 25-OH D status and incident prostate cancer, Gleason score, and tumor stage. Results: Among European American (EA) men, there was an association of 25-OH D <12 ng/mL with higher Gleason score≥4+4 [OR, 3.66;95%confidence interval (CI), 1.41-9.50; P=0.008] and tumor stage [stage≥cT2b vs. ≤cT2a, OR, 2.42 (1.14-5.10); P=0.008]. In African American (AA) men, we find increased odds of prostate cancer diagnosis on biopsy with 25-OHD< 20 ng/mL [OR, 2.43 (1.20-4.94); P=0.01]. AA men demonstrated an association between 25-OH D < 12 ng/mL and Gleason ≥ 4+4 [OR, 4.89 (1.59-15.07); P=0.006]. There was an association with tumor stage≥cT2b vs.≤cT2a [OR, 4.22 (1.52-11.74); P= 0.003]. Conclusions: In AA men, vitamin D deficiency was associated with increased odds of prostate cancer diagnosis on biopsy. In both EA and AAmen, severe deficiency was positively associated with higher Gleason grade and tumor stage. © 2014 AACR.
Keywords: 25 hydroxyvitamin D; prostate specific antigen; vitamin D; 25 hydroxycolecalciferol blood level; adult; African American; aged; article; cancer diagnosis; cancer staging; controlled clinical trial; controlled study; digital rectal examination; disease association; European American; Gleason score; human; human tissue; major clinical study; male; outcome assessment; prediction; priority journal; prospective study; prostate biopsy; prostate cancer; urology; vitamin blood level; vitamin D deficiency; vitamin supplementation

Treat or eat: Food insecurity, cost-related medication underuse, and unmet needs - Berkowitz, S.A.; Seligman, H.K.; Choudhry, N.K. (American Journal of Medicine, 2014)
Background Adults with chronic disease are often unable to meet medication and food needs, but no study has examined the relationship between cost-related medication underuse and food insecurity in a nationally representative sample. We examined which groups most commonly face unmet food and medication needs. Methods Cross-sectional analysis of data from chronically ill participants (self-report of arthritis, diabetes mellitus, cancer, asthma, chronic obstructive pulmonary disease, stroke, hypertension, coronary heart disease, or presence of a "psychiatric problem") aged ≥20 years, in the 2011 National Health Interview Survey. We fit logistic regression models to identify factors associated with food insecurity, cost-related medication underuse, or both. Results There were 9696 adult National Health Interview Survey (NHIS) participants who reported chronic illness; 23.4% reported cost-related medication underuse; 18.8% reported food insecurity; and 11% reported both. Adults who reported food insecurity were significantly more likely to report cost-related medication underuse (adjusted odds ratio [aOR] 4.03). Participants with both cost-related medication underuse and food insecurity were more likely to be Hispanic (aOR 1.58), non-Hispanic black (aOR 1.58), and have more chronic conditions (aOR per additional chronic condition 1.56) than patients reporting neither. They also were less likely to have public, non-Medicare insurance (aOR 0.70) and report participation in the Special Supplemental Nutrition Assistance Program for Woman, Infants, and Children (aOR 0.39). Conclusions Approximately 1 in 3 chronically ill NHIS participants are unable to afford food, medications, or both. WIC and public health insurance participation are associated with less food insecurity and cost-related medication underuse. © 2014 Elsevier Inc. All rights reserved.
Keywords: adult; arthritis; article; asthma; basic needs; cerebrovascular accident; chronic disease; chronic obstructive lung disease; chronic patient; controlled study; cost related medication underuse; cross-sectional study; diabetes mellitus; drug cost; female; food assistance; food insecurity; health survey; Hispanic; human; hypertension; ischemic heart disease; major clinical study; male; malignant neoplasm; medically underserved; medication compliance; mental disease; middle aged; needs assessment; patient participation; priority journal; public health insurance; self report; socioeconomics; young adult

Racial/ethnic differences in clinical trial enrollment, refusal rates, ineligibility, and reasons for decline among patients at sites in the National Cancer Institute's Community Cancer Centers Program - Langford, A.T.; Resnicow, K.; Dimond, E.P.; Denicoff, A.M.; Germain, D.S.; McCaskill-Stevens, W.; Enos, R.A.; Carrigan, A.; Wilkinson, K.; Go, R.S. (Cancer, 2014)
BACKGROUND This study examined racial/ethnic differences among patients in clinical trial (CT) enrollment, refusal rates, ineligibility, and desire to participate in research within the National Cancer Institute's Community Cancer Centers Program (NCCCP) Clinical Trial Screening and Accrual Log. METHODS Data from 4509 log entries were evaluated in this study. Four logistic regression models were run using physical/medical conditions, enrollment into a CT, patient eligible but declined a CT, and no desire to participate in research as dependent variables. RESULTS Age ≥ 65 years (OR = 1.51, 95% CI = 1.28-1.79), males (OR = 2.28, 95% CI = 1.92-2.71), and non-Hispanic black race (OR = 1.53, 95% CI = 1.2-1.96) were significantly associated with more physical/medical conditions. Age ≥ 65 years was significantly associated with lower CT enrollment (OR = 0.83, 95% CI = 0.7-0.98). Males (OR = 0.78, 95% CI = 0.65-0.94) and a higher grade level score for consent form readability (OR = 0.9, 95% CI = 0.83-0.97) were significantly associated with lower refusal rates. Consent page length ≥ 20 was significantly associated with lower odds of "no desire to participate in research" among CT decliners (OR = 0.75, 95% CI = 0.58-0.98). CONCLUSIONS There were no racial/ethnic differences in CT enrollment, refusal rates, or "no desire to participate in research" as the reason given for CT refusal. Higher odds of physical/medical conditions were associated with older age, males, and non-Hispanic blacks. Better management of physical/medical conditions before and during treatment may increase the pool of eligible patients for CTs. Future work should examine the role of comorbidities, sex, age, and consent form characteristics on CT participation. Cancer 2014;120:877-884. © 2013 American Cancer Society. There were no racial/ethnic differences in clinical trial (CT) enrollment, refusal rates, or "no desire to participate in research" as the reason given for CT refusal; however, higher odds of physical/medical conditions were associated with older age, males, and non-Hispanic blacks. Better management of physical/medical conditions before and during treatment may increase the pool of eligible patients for CTs. © 2013 American Cancer Society.
Keywords: adult; aged; article; breast cancer; clinical trial (topic); colorectal cancer; ethnic difference; female; human; informed consent; interpersonal communication; logistic regression analysis; major clinical study; male; middle aged; Black person; priority journal; race difference; refusal to participate; scoring system; urogenital tract cancer

Dose response to vitamin D supplementation in African Americans: Results of a 4-arm, randomized, placebo-controlled trial - Ng, K.; Scott, J.B.; Drake, B.F.; Chan, A.T.; Hollis, B.W.; Chandler, P.D.; Bennett, G.G.; Giovannucci, E.L.; Gonzalez-Suarez, E.; Meyerhardt, J.A.; Emmons, K.M.; Fuchs, C.S. (American Journal of Clinical Nutrition, 2014)
Background: Association studies have suggested that lower circulating 25-hydroxyvitamin D [25(OH)D] in African Americans may partially underlie higher rates of cardiovascular disease and cancer in this population. Nonetheless, the relation between vitamin D supplementation and 25(OH)D concentrations in African Americans remains undefined. Objective: Our primary objective was to determine the doseresponse relation between vitamin D and plasma 25(OH)D. Design: A total of 328 African Americans in Boston, MA, were enrolled over 3 winters from 2007 to 2010 and randomly assigned to receive a placebo or 1000, 2000, or 4000 IU vitamin D3/d for 3 mo. Subjects completed sociodemographic and dietary questionnaires, and plasma samples were drawn at baseline and 3 and 6 mo. Results: Median plasma 25(OH)D concentrations at baseline were 15.1, 16.2, 13.9, and 15.7 ng/mL for subjects randomly assigned to receive the placebo or 1000, 2000, or 4000 IU/d, respectively (P = 0.63). The median plasma 25(OH)D concentration at 3 mo differed significantly between supplementation arms at 13.7, 29.7, 34.8, and 45.9 ng/mL, respectively (P < 0.001). An estimated 1640 IU vitamin D3/d was needed to raise the plasma 25(OH)D concentration to ≥20 ng/mL in ≥97.5% of participants, whereas a dose of 4000 IU/d was needed to achieve concentrations ≥33 ng/mL in ≥80% of subjects. No significant hypercalcemia was seen in a subset of participants. Conclusions: Within African Americans, an estimated 1640 IU vitamin D3/d was required to achieve concentrations of plasma 25(OH)D recommended by the Institute of Medicine, whereas 4000 IU/d was needed to reach concentrations predicted to reduce cancer and cardio-vascular disease risk in prospective observational studies. These results may be helpful for informing future trials of disease prevention. This trial was registered at clinicaltrials.gov as NCT00585637. © 2014 American Society for Nutrition.
Keywords: NCT00585637; 25 hydroxyvitamin D; calcium; colecalciferol; placebo; absence of side effects; adult; African American; aged; article; calcium blood level; cancer prevention; colorectal cancer; controlled study; correlational study; demography; dietary compliance; dose response; double blind procedure; drug eruption; drug withdrawal; female; human; hypercalcemia; major clinical study; male; middle aged; polydipsia; questionnaire; randomized controlled trial; side effect; socioeconomics; treatment response; very elderly; vitamin blood level; vitamin supplementation; winter

Evaluation of the effect of blackcurrant products on gut microbiota and on markers of risk for colon cancer in humans - Molan, A.-L.; Liu, Z.; Plimmer, G. (Phytotherapy Research, 2014)
The purpose of this study was to determine in healthy humans whether First Leaf (FL; composed of blackcurrant extract powder, lactoferrin and lutein) and Cassis Anthomix 30 (CAM30; blackcurrant extract powder) can positively modify the colonic microbiota by enhancing the growth of the beneficial bacteria and inactivating the toxic bacterial enzymes which are known to be involved in colonic carcinogenesis. Thirty healthy adult male and female volunteers were recruited for this study. Fluorescent in situ hybridization was carried out to analyse the populations of fecal microbiota. Consumption of FL and CAM30 led to significant increases (P < 0.0001) in the population sizes of lactobacilli and bifidobacteria whereas the population sizes of Clostridium spp. and Bacteroides spp were decreased significantly (P < 0.0001). In addition, feeding of FL and CAM30 decreases the activity of β-glucuronidase (bacterial enzyme which is considered to be one of the enzymes that increases risk for colorectal cancer) and significantly decreased (P < 0.05) the fecal pH. In conclusion, the results of this study open up the possibility that consumption of FL and CAM30 can offer various benefits to human health through acting as novel prebiotic agents via increasing the numbers of beneficial bacteria (lactobacilli and bifidobacteria) in the gut. © 2013 John Wiley & Sons, Ltd.
Keywords: bacterial enzyme; beta glucuronidase; black currant extract; lactoferrin; prebiotic agent; xanthophyll; adult; antimicrobial activity; article; bacterial growth; Bifidobacteriales; cancer risk; colorectal cancer; controlled study; diet supplementation; drug dosage form comparison; enzyme activity; feces microflora; female; fluorescence in situ hybridization; human; human experiment; intestine flora; Lactobacillus casei; male; normal human; pH; randomized controlled trial; risk benefit analysis

Active surveillance for low-risk prostate cancer in African American Men: A multi-institutional experience - Odom, B.D.; Mir, M.C.; Hughes, S.; Senechal, C.; Santy, A.; Eyraud, R.; Stephenson, A.J.; Ylitalo, K.; Miocinovic, R. (Urology, 2014)
Objective To compare the outcomes of active surveillance (AS) series between African American men (AAM) and non-AAM diagnosed with low-risk prostate cancer at 3 medical centers. Methods Between 2005 and 2012, 214 men accepted AS on the basis of favorable clinical features and parameters after initial and repeat biopsy. Failure was defined as increase in Gleason score >6, total positive cores >33%, maximum cancer volume in any core >50%, or a prostate-specific antigen >10 ng/mL. Disease progression and overall AS failure were compared between the 2 groups. Results Of 214 men, 75 were excluded, leaving 67 AAM and 72 non-AAM on AS. Median age at diagnosis was 64 and 67 years for AAM and non-AAM, respectively, and median follow-up was 34 and 46 months, respectively. During this time, 44 AAM (66%) remained on AS, and 23 (34%) underwent treatment, of whom 6 (26%) were treated by patient choice and 17 (74%) because of disease progression. In the non-AAM group, 59 (82%) men remained on AS, and 13 (18%) underwent treatment, 8 (62%) were treated by patient choice and 5 (38%) because of disease progression. The 3-year freedom from overall treatment was 74% and did not differ by race (P =.06). The 3-year freedom from disease progression was 85%, where AAM were at significantly higher risk of disease progression (hazard ratio = 3.8; 95% confidence interval: 1.4-10.4; P =.01). Conclusion Our study suggests a higher disease progression rate in AAM who choose AS for low-risk prostate cancer compared with non-AAM, signifying a potential need for closer follow-up and more stringent enrollment criteria in AAM. © 2014 Published by Elsevier Inc.
Keywords: prostate specific antigen; adult; African American; aged; article; cancer epidemiology; cancer growth; cancer radiotherapy; cancer surgery; follow up; Gleason score; human; human tissue; low risk population; major clinical study; male; middle aged; multicenter study (topic); oncological parameters; onset age; outcome assessment; patient decision making; priority journal; prostate biopsy; prostate cancer; prostatectomy; time to treatment; work experience

Patient-reported outcomes in women with breast cancer enrolled in a dual-center, double-blind, randomized controlled trial assessing the effect of acupuncture in reducing aromatase inhibitor-induced musculoskeletal symptoms - Bao, T.; Cai, L.; Snyder, C.; Betts, K.; Tarpinian, K.; Gould, J.; Jeter, S.; Medeiros, M.; Chumsri, S.; Bardia, A.; Tan, M.; Singh, H.; et al. (Cancer, 2014)
Background Aromatase inhibitors (AIs) have been associated with decrements in patient-reported outcomes (PROs). The objective of this study was to assess whether real acupuncture (RA), compared with sham acupuncture (SA), improves PROs in patients with breast cancer who are receiving an adjuvant AI. Methods Postmenopausal women with a stage 0 through III breast cancer who received an AI and had treatment-associated musculoskeletal symptoms were randomized to receive 8 weekly RA versus SA in a dual-center, randomized controlled trial. The National Surgical Adjuvant Breast and Bowel Project (NSABP) menopausal symptoms questionnaire, the Center for Epidemiological Studies Depression (CESD) scale, the Hospital Anxiety and Depression Scale (HADS), the Pittsburgh Sleep Quality Index (PSQI), the hot flash daily diary, the Hot Flash-Related Daily Interference Scale (HFRDI), and the European quality-of-life survey (EuroQol) were used to assess PROs at baseline and at 4weeks, 8 weeks, and 12 weeks. Results The intention-to-treat analysis included 23 patients in the RA arm and 24 patients in the SA arm. There were no significant differences in baseline characteristics between the 2 groups. Compared with baseline, scores in the RA arm improved significantly at week 8 on the CESD (P =.022), hot flash severity (P =.006), hot flash frequency (P =.011), the HFRDI (P =.014), and NSABP menopausal symptoms (P =.022); scores in the SA arm improved significantly on the EuroQol (P =.022),the HFRDI (P =.043), and NSABP menopausal symptoms (P =.005). Post-hoc analysis indicated that African American patients (n = 9) benefited more from RA than SA compared with non-African American patients (n = 38) in reducing hot flash severity (P <.001) and frequency (P <.001) scores. Conclusions Both RA and SA were associated with improvement in PROs among patients with breast cancer who were receiving AIs, and no significant difference was detected between arms. Racial differences in response to acupuncture warrant further study. © 2013 American Cancer Society.
Keywords: NCT00641303; aromatase inhibitor; acupuncture; adult; aged; analysis of covariance; analytic method; article; breast cancer; clinical article; controlled study; disease severity; double blind procedure; female; Hospital Anxiety and Depression Scale; hot flash daily diary; Hot Flash Related Daily Interference Scale; human; middle aged; multicenter study; musculoskeletal disease; National Surgical Adjuvant Breast and Bowel Project menopausal symptomn questionnaire; outcome assessment; patient-reported outcome; Pittsburgh Sleep Quality Index; postmenopause; priority journal; psychometry; quality of life; race difference; randomized controlled trial; very elderly

Ethnicity and outcome of young breast cancer patients in the United Kingdom: The POSH study - Copson, E.; Maishman, T.; Gerty, S.; Eccles, B.; Stanton, L.; Cutress, R.I.; Altman, D.G.; Durcan, L.; Simmonds, P.; Jones, L.; Tapper, W.; Eccles, D. (British Journal of Cancer, 2014)
Background:Black ethnic groups have a higher breast cancer mortality than Whites. American studies have identified variations in tumour biology and unequal health-care access as causative factors. We compared tumour pathology, treatment and outcomes in three ethnic groups in young breast cancer patients treated in the United Kingdom.Methods:Women aged ≤40 years at breast cancer diagnosis were recruited to the POSH national cohort study (MREC: 00/06/69). Personal characteristics, tumour pathology and treatment data were collected at diagnosis. Follow-up data were collected annually. Overall survival (OS) and distant relapse-free survival (DRFS) were assessed using Kaplan-Meier curves, and multivariate analyses were performed using Cox regression.Results:Ethnicity data were available for 2915 patients including 2690 (91.0%) Whites, 118 (4.0%) Blacks and 87 (2.9%) Asians. Median tumour diameter at presentation was greater in Blacks than Whites (26.0 mm vs 22.0 mm, P=0.0103), and multifocal tumours were more frequent in both Blacks (43.4%) and Asians (37.0%) than Whites (28.9%). ER/PR/HER2-negative tumours were significantly more frequent in Blacks (26.1%) than Whites (18.6%, P=0.043). Use of chemotherapy was similarly high in all ethnic groups (89% B vs 88.6% W vs 89.7% A). A 5-year DRFS was significantly lower in Blacks than Asians (62.8% B vs 77.0% A, P=0.0473) or Whites (62.8 B% vs 77.0% W, P=0.0053) and a 5-year OS for Black patients, 71.1% (95% CI: 61.0-79.1%), was significantly lower than that of Whites (82.4%, 95% CI: 80.8-83.9%, W vs B: P=0.0160). In multivariate analysis, Black ethnicity had an effect on DRFS in oestrogen receptor (ER)-positive patients that is independent of body mass index, tumour size, grade or nodal status, HR: 1.60 (95% CI: 1.03-2.47, P=0.035).Conclusion:Despite equal access to health care, young Black women in the United Kingdom have a significantly poorer outcome than White patients. Black ethnicity is an independent risk factor for reduced DRFS particularly in ER-positive patients. © 2014 Cancer Research UK.
Keywords: antineoplastic agent; estrogen receptor; article; Asian; body mass; breast cancer; cancer adjuvant therapy; cancer chemotherapy; cancer grading; cancer recurrence; cancer risk; cancer surgery; cancer survival; Caucasian; cohort analysis; distant recurrence free survival; estrogen receptor positive breast cancer; ethnic group; ethnicity; female; follow up; human; major clinical study; Black person; outcome assessment; overall survival; partial mastectomy; priority journal; recurrence free survival; survival rate; tumor volume; United Kingdom

African-American breast cancer survivors' preferences for various types of physical activity interventions: A Sisters Network Inc. web-based survey - Paxton, R.J.; Nayak, P.; Taylor, W.C.; Chang, S.; Courneya, K.S.; Schover, L.; Hodges, K.; Jones, L.A. (Journal of Cancer Survivorship, 2014)
Background: Needs assessments are essential to developing lifestyle interventions for minority populations. To our knowledge, no physical activity (PA) needs assessment studies have been conducted for African-American (AA) breast cancer survivors. The purpose of this study was to determine the PA intervention preferences of AA breast cancer survivors and determine whether these preferences differ according to medical and sociodemographic factors. Methods: AA breast cancer survivors (n = 475, mean age = 54 years) were recruited using ads sent via email and social media sites. Preferences for the mode of intervention delivery were assessed via web-based questionnaires. Descriptive statistics were used to characterize their interests in PA interventions, and subgroup differences were assessed. Results: About 49 % (142 out of 291) of the participants who completed the survey were obese and 54 % did not meet the recommended guidelines for PA. Most (90 %) participants reported that they could participate in PA, and many (67 %) indicated that they were interested in receiving program materials. Participants expressed the greatest interest in email (50 %)-, web (48 %)-, or mail-based (45 %) over group (39 %), and telephone (10 %). Women also expressed the greatest interest in participating in studies that promoted walking and resistance or strength training. Intervention preferences did not differ significantly (P > 0.05) across sociodemographic or medical factors. Conclusion: Most AA breast cancer survivors can participate in PA, and many are interested in interventions that promoted walking and resistance training and were delivered via the email or web. The development of culturally sensitive interventions that provide activities consistent with preferences can assist AA breast cancer survivors to adopt and maintain a healthy lifestyle. Implications for Cancer Survivors: Despite evidence that AA breast cancer survivors are at increased risk for poor breast cancer-specific outcomes, they are underrepresented in clinical trials promoting positive health behaviors. In this study, we propose to assess their exercise preferences and receptivity to a culturally appropriate PA intervention developed in collaboration with the Sisters Network Inc. Health promotion programs developed in collaboration with a community-based organization may aid in the development of research tools and resources that AA breast cancer survivors are receptive to using. © 2013 Springer Science+Business Media New York.
Keywords: adult; African American; aged; article; breast tumor; comorbidity; compact disk; e-mail; female; habit; health service; human; information processing; Internet; lifestyle; methodology; middle aged; motor activity; obesity; patient education; patient preference; practice guideline; psychological aspect; publication; quality of life; questionnaire; resistance training; sedentary lifestyle; survivor; telephone; United States

Individual, provider, and system risk factors for breast and cervical cancer screening among underserved black, Latina, and Arab women - Roman, L.; Meghea, C.; Ford, S.; Penner, L.; Hamade, H.; Estes, T.; Williams, K.P. (Journal of Women's Health, 2014)
Background: Socioeconomic and racial/ethnic disparities in breast and cervical cancer screening persist. An exploratory study was conducted to better understand co-occurring risk factors in underserved groups that could inform interventions to improve screening adherence. The objective of this study was to examine associations between breast and cervical cancer screening adherence and co-occurring risk factors in three racial/ethnic groups of underserved women. Methods: Black, Latina, and Arab women (N=514), ages 21 to 70 years, were enrolled into the Kin KeeperSM randomized controlled trial in communities around Detroit, Michigan. We used participant baseline assessments (e.g., demographic characteristics, health literacy) to explore screening risks using an additive approach and multivariate logistic analyses. Results: For black women, having more health literacy risks were associated with reduced odds of a clinical breast exam (CBE), mammogram, and Papanicolaou (Pap) test; more competing priorities were associated with reduced odds of a Pap test; lack of doctor mammogram recommendation was significantly associated with decreased odds of CBE. For Latina women, lack of doctor recommendations were significantly associated with decreased odds of CBE, mammogram, and Pap test. For Arab women, lack of doctor recommendations were significantly associated with decreased odds of CBE, mammogram, and Pap test; more competing priorities were significantly associated with reduced odds of CBE and Pap test. All results were significant at p<0.05. Conclusions: Characteristics associated with breast and cervical screening adherence differs among Black, Latina, and Arab underserved women. Interventions to improve screening should be tailored for racial/ethnic groups with particular attention to competing survival priorities, health literacy risks factors, and provider recommendations. © Copyright 2014, Mary Ann Liebert, Inc. 2014.
Keywords: adult; aged; Arab; article; breast cancer; breast examination; cancer screening; ethnic group; female; health literacy; Hispanic; human; mammography; Black person; Papanicolaou test; priority journal; race; risk factor; United States; uterine cervix cancer; young adult

Nutrition and physical activity cancer prevention guidelines, cancer risk, and mortality in the women's health initiative - Thomson, C.A.; McCullough, M.L.; Wertheim, B.C.; Chlebowski, R.T.; Martinez, M.E.; Stefanick, M.L.; Rohan, T.E.; Manson, J.E.; Tindle, H.A.; Ockene, J.; Vitolins, M.Z.; Wactawski-Wende, J.; et al. (Cancer Prevention Research, 2014)
Healthy lifestyle behaviors are recommended to reduce cancer risk and overall mortality. Adherence to cancer-preventive health behaviors and subsequent cancer risk has not been evaluated in a diverse sample of postmenopausal women. We examined the association between the American Cancer Society (ACS) Nutrition and Physical Activity Cancer Prevention Guidelines score and risk of incident cancer, cancer-specific mortality, and all-cause mortality in 65,838 postmenopausal women enrolled in the Women's Health Initiative Observational Study. ACS guidelines scores (0-8 points) were determined from a combined measure of diet, physical activity, body mass index (current and at age 18 years), and alcohol consumption. After a mean follow-up of 12.6 years, 8,632 incident cancers and 2,356 cancer deaths were identified. The highest ACS guidelines scores compared with the lowest were associated with a 17% lower risk of any cancer [HR, 0.83; 95% confidence interval (CI), 0.75-0.92], 22% lower risk of breast cancer (HR, 0.78; 95% CI, 0.67-0.92), 52% lower risk of colorectal cancer (HR, 0.48; 95% CI, 0.32-0.73), 27% lower risk of all-cause mortality, and 20% lower risk of cancer-specific mortality (HR, 0.80; 95% CI, 0.71-0.90). Associations with lower cancer incidence and mortality were generally strongest among Asian, black, and Hispanic women and weakest among non-Hispanic whites. Behaviors concordant with Nutrition and Physical Activity Cancer Prevention Guidelines were associated with lower risk of total, breast, and colorectal cancers and lower cancer-specific mortality in postmenopausal women. ©2013 American Association for Cancer Research.
Keywords: estrogen; gestagen; nonsteroid antiinflammatory agent; adult; alcohol consumption; american cancer society physical activity cancer prevention guidelines score; article; Asian; breast cancer; cancer incidence; cancer mortality; cancer prevention; cancer risk; cause of death; colonoscopy; colorectal cancer; endometrium cancer; female; follow up; health behavior; Hispanic; human; lifestyle; lung cancer; middle aged; Black person; non profit organization; nutrition; observational study; ovary cancer; physical activity; postmenopause; practice guideline; priority journal; scoring system; body weight gain; women's health

Effective recruitment strategies and community-based participatory research: Community networks program centers' recruitment in cancer prevention studies - Greiner, K.A.; Friedman, D.B.; Adams, S.A.; Gwede, C.K.; Cupertino, P.; Engelman, K.K.; Meade, C.D.; Hebert, J.R. (Cancer Epidemiology Biomarkers and Prevention, 2014)
Background: Community-based participatory research (CBPR) approaches that involve community and academic partners in activities ranging from protocol design through dissemination of study findings can increase recruitment of medically underserved and underrepresented racial/ethnic minority populations into biomedical research. Methods: Five cancer screening and prevention trials in three National Cancer Institute (Bethesda, MD)-funded Community Networks Program Centers (CNPC), in Florida, Kansas, and South Carolina, were conducted across diverse populations. Data were collected on total time period of recruitment, ratios of participants enrolled over potential participants approached, selected CBPR strategies, capacity-building development, and systematic procedures for community stakeholder involvement. Results: Community-engaged approaches used included establishing colearning opportunities, participatory procedures for community-Academic involvement, and community and clinical capacity building. A relatively large proportion of individuals identified for recruitment was actually approached (between 50% and 100%). The proportion of subjects who were eligible among all those approached ranged from 25% to more than 70% (in the community setting). Recruitment rates were very high (78%-100% of eligible individuals approached) and the proportion who refused or who were not interested among those approached was very low (5%-11%). Conclusions: Recruitment strategies used by the CNPCs were associated with low refusal and high enrollment ratios of potential subjects. Adherence to CBPR principles in the spectrum of research activities, from strategic planning to project implementation, has significant potential to increase involvement in biomedical research and improve our ability to make appropriate recommendations for cancer prevention and control programming in underrepresented diverse populations. Impact: CBPR strategies should be more widely implemented to enhance study recruitment. © 2014 American Association for Cancer Research.
Keywords: African American; article; breast cancer; cancer prevention; cancer screening; community; community care; controlled study; ethnic group; female; follow up; health program; human; major clinical study; male; national health organization; participatory research; pilot study; priority journal; prostate cancer; randomized controlled trial; social network; strategic planning; United States

Treatment of small cell lung cancer in academic and community settings: Factors associated with receiving standard therapy and survival - Parsons, H.M.; Harlan, L.C.; Stevens, J.L.; Ullmann, C.D. (Cancer Journal (United States), 2014)
PURPOSE: Small cell lung cancer (SCLC) historically has had poor prognosis. Clinical trials have demonstrated improved survival among patients receiving standard platinum-/etoposide-based chemotherapy. Whereas treatment patterns and outcomes have been evaluated for patients with SCLC in clinical trials, population-based practice patterns are not well known. METHODS: The National Cancer Institute's Patterns of Care study was used to evaluate patient and provider factors associated with standard treatment, clinical trial enrollment, and 12-month relative hazard of death. RESULTS: Among 931 patients with SCLC diagnosed in 2007 in academic and community settings, 72.2% of patients with limited-stage (LS) disease received chemoradiation and 42.2% of patients with extensive-stage (ES) disease received chemotherapy only; the expected treatment scenarios by stage. Less than 1% of the patients enrolled in clinical trials and 2.1% of the patients with LS disease and 3.4% of the patients with ES disease refused any type of treatment. Patients 80 years or older at diagnosis and those with pneumonia/lung collapse were less likely to receive chemoradiation for LS disease. Patients treated in hospitals with residency programs were more likely to receive chemotherapy for ES disease, and patients 80 years or older were less likely to receive chemotherapy for ES disease. Finally, female patients with LS disease, black patients with ES disease, and all patients who received chemotherapy compared to receiving radiation alone or no therapy experienced significantly lower mortality. DISCUSSION: Despite the demonstrated lower mortality, a relatively large proportion of patients with SCLC are not treated with a standard treatment regimen. Future studies should evaluate efforts to promote use of appropriate treatment regimens and encourage clinical trial participation. Copyright © 2014 Lippincott Williams & Wilkins.
Keywords: antineoplastic agent; carboplatin; cisplatin; etoposide; irinotecan; adult; aged; article; atelectasis; cancer chemotherapy; cancer mortality; cancer radiotherapy; cancer staging; cancer survival; cancer therapy; chemoradiotherapy; clinical trial (topic); community hospital; controlled study; female; health hazard; human; small cell lung cancer; major clinical study; male; national health organization; phase 3 clinical trial (topic); pneumonia; positron emission tomography; priority journal; residential care; treatment planning; treatment refusal; United States; university hospital

Commentary on "Intermittent versus continuous androgen deprivation in prostate cancer." - Eggener, S. (Urologic Oncology: Seminars and Original Investigations, 2014)
Background: Castration resistance occurs in most patients with metastatic hormone-sensitive prostate cancer who are receiving androgen-deprivation therapy. Replacing androgens before progression of the disease is hypothesized to prolong androgen dependence. Methods: Men with newly diagnosed, metastatic, hormone-sensitive prostate cancer, a performance status of 0 to 2, and a prostate-specific antigen (PSA) level of 5. ng per milliliter or higher received a luteinizing hormone-releasing hormone analogue and an antiandrogen agent for 7 months. We then randomly assigned patients in whom the PSA level fell to 4. ng per milliliter or lower to continuous or intermittent androgen deprivation, with patients stratified according to prior or no prior hormonal therapy, performance status, and extent of disease (minimal or extensive). The coprimary objectives were to assess whether intermittent therapy was noninferior to continuous therapy with respect to survival, with a one-sided test with an upper boundary of the hazard ratio of 1.20, and whether quality of life differed between the groups 3 months after randomization. Results: A total of 3040 patients were enrolled, of whom 1535 were included in the analysis: 765 randomly assigned to continuous androgen deprivation and 770 assigned to intermittent androgen deprivation. The median follow-up period was 9.8 years. Median survival was 5.8 years in the continuous-therapy group and 5.1 years in the intermittent-therapy group (hazard ratio for death with intermittent therapy, 1.10; 90% confidence interval, 0.99 to 1.23). Intermittent therapy was associated with better erectile function and mental health (P<0.001 and P=0.003, respectively) at month 3 but not thereafter. There were no significant differences between the groups in the number of treatment-related high-grade adverse events. Conclusions: Our findings were statistically inconclusive. In patients with metastatic hormone-sensitive prostate cancer, the confidence interval for survival exceeded the upper boundary for noninferiority, suggesting that we cannot rule out a 20% greater risk of death with intermittent therapy than with continuous therapy, but too few events occurred to rule out significant inferiority of intermittent therapy. Intermittent therapy resulted in small improvements in quality of life. (Funded by the National Cancer Institute and others; ClinicalTrials.gov number, NCT00002651.). © 2014 Elsevier Inc.
Keywords: African American; cancer epidemiology; cancer mortality; cancer risk; follow up; health disparity; human; low risk patient; nuclear magnetic resonance imaging; practice guideline; priority journal; prostate biopsy; prostate cancer; prostatectomy; race difference; randomized controlled trial; short survey

A community-based, culturally relevant intervention to promote healthy eating and physical activity among middle-aged African American women in rural Alabama: Findings from a group randomized controlled trial - Scarinci, I.C.; Moore, A.; Wynn-Wallace, T.; Cherrington, A.; Fouad, M.; Li, Y. (Preventive Medicine, 2014)
Objective: We examined the efficacy of a community-based, culturally relevant intervention to promote healthy eating and physical activity among African American (AA) women between the ages of 45-65 years, residing in rural Alabama. Methods: We conducted a group randomized controlled trial with counties as the unit of randomization that evaluated two interventions based on health priorities identified by the community: (1) promotion of healthy eating and physical activity; and (2) promotion of breast and cervical cancer screening. A total of 6 counties with 565 participants were enrolled in the study between November 2009 and October 2011. Results: The overall retention rate at 24-month follow-up was 54.7%. Higher retention rate was observed in the "healthy lifestyle" arm (63.1%) as compared to the "screening" arm (45.3%). Participants in the "healthy lifestyle" arm showed significant positive changes compared to the "screening" arm at 12-month follow-up with regard to decrease in fried food consumption and an increase in both fruit/vegetable intake and physical activity. At 24-month follow-up, these positive changes were maintained with healthy eating behaviors, but not engagement in physical activity. Conclusions: A culturally relevant intervention, developed in collaboration with the target audience, can improve (and maintain) healthy eating among AA women living in rural areas. © 2014 Elsevier Inc.
Keywords: adult; African American; aged; article; behavior change; breast cancer; cancer screening; controlled study; eating; employment status; family health; feeding behavior; female; follow up; food intake; fruit; fruit vegetable; health care planning; health care utilization; health disparity; health promotion; human; income; lifestyle; lifestyle modification; major clinical study; marriage; medicaid; medicare; middle aged; participatory research; physical activity; priority journal; randomized controlled trial; rural area; rural population; United States; uterine cervix cancer; vegetable

African american primary care physicians' prostate cancer screening practices. - Ross, L.E.; Hall, I.J. (Journal of primary care & community health, 2014)
Prostate cancer is the most common cancer and the second leading cause of cancer death among men in the United States. African American (AA) men have greater prostate cancer burden than other men. Little is known about AA primary care physicians' (PCPs) practices regarding prostate cancer screening. We analyzed data from the 2007-2008 National Survey of Primary Care Physicians' Practices Regarding Prostate Cancer Screening. The current study included 604 AA PCPs. Outcomes assessed were (a) offering screening using the prostate-specific antigen (PSA) test, (b) use of screening discussions to involve patients in the decision to screen, and (c) having a discussion policy to try to talk the patient into getting the screening tests. Most AA PCPs were male (52%), younger than 50 years (61%), and had 21% to 100% AA patients in their practices (74%). The majority (94%) of AA PCPs offered prostate cancer screening using PSA, discussed the tests with their male patients to involve them in the decision to screen (83%), and had a policy to try to talk the patient into getting the screening tests (77%). Multivariate analysis showed that offering screening, use of discussions, and a usual policy to encourage taking the screening tests varied mainly by practice-related factors, including practice type, practice location, and percentage of AA patients in the practice. Data from this study indicate that most AA PCPs reported high proscreening behaviors for all 3 outcomes. Additionally, practice- and screening-related factors may be important when examining AA PCP screening behaviors.
Keywords: prostate specific antigen; adult; African American; African American primary care physicians; article; clinical practice; decision making; doctor patient relationship; female; general practice; human; male; mass screening; methodology; middle aged; multivariate analysis; patient participation; patient referral; physician practices; prostate cancer; prostate tumor; screening; statistics; United States

Recruiting and motivating black subjects to complete a lengthy survey in a large cohort study: an exploration of different strategies. - Herring, P.; Butler, T.; Hall, S.; Bennett, H.; Montgomery, S.B.; Fraser, G. (BMC medical research methodology, 2014)
The effectiveness of multiple innovative recruitment strategies for enrolling Black/African American participants to the Adventist Health Study-2 (AHS-2) is described. The study's focus is diet and breast, prostate and colon cancer. Promotions centered on trust, relationship building and incentives for increasing enrollment and questionnaire return rate. Of the sub-studies described, one had a randomized control group, and the others, informal controls. The subjects are from all states of the U.S. and some provinces of Canada. The offer of a Black art piece, follow-up calls, a competitive tournament as well as other strategies accounted for nearly 3,000 additional returns even though they were often used in small subsets. Flexibility and multiple strategies proved advantageous in gaining the cooperation of Blacks, who are usually reluctant to participate in research studies. Lessons learned during initial enrollment should help us retain our final Black cohort of 26,000, and obtain new information when required.
Keywords: African American; article; breast tumor; Canada; cohort analysis; colon tumor; cost benefit analysis; diet; doctor patient relationship; female; human; male; motivation; patient selection; prostate tumor; psychological aspect; questionnaire; reward; United States

Knowledge and prevention practices before breast cancer diagnosis in a cross-sectional study among survivors: impact on patients' involvement in the decision making process. - Taioli, E.; Joseph, G.R.; Robertson, L.; Eckstein, S.; Ragin, C. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2014)
Disparities exist in breast cancer knowledge and education, which tend to influence symptom interpretation and decision to seek screening/care. The present project describes a cohort of women's experiences, knowledge, and health behavior prior to and after a diagnosis of breast cancer. It also studies how knowledge and demographic factors are associated with level of involvement participants had in the treatment of their breast cancer. Women >18 years who have been diagnosed and treated for breast cancer within 10 years were recruited in Pittsburgh, PA, through the Healthy People Cohort Registry, a database of volunteers from the community, and Brooklyn, NY, through the American Cancer Society breast cancer survivor database. Subsequent to institutional ethics approval, a questionnaire was administered by mail and through an electronic interactive format. The study included 124 breast cancer survivors, one-quarter of whom were of African ancestry. Roughly half of the women indicated that their overall knowledge of breast cancer was limited before diagnosis; no significant association between overall knowledge before diagnosis and stage at diagnosis or an active role of the patient in treatment choices was observed. Two-third of the women reported using personal research on internet, books, and other media to increase knowledge on breast cancer after diagnosis; the improvement of knowledge was associated with an active role in therapy choice. White women's self report of breast cancer knowledge prior to diagnosis was higher than that of women of African origin (p = 0.03); the latter experienced more delays in getting results about the diagnosis (p = 0.002), in starting treatment (p = 0.03), and in having treatment available at local facilities (p = 0.007) than white women. White women were more likely to improve their knowledge through their own research (p = 0.08) and through the contribution of their physician (p = 0.06) than women of African origin.There is still a need for addressing breast cancer knowledge among black women, and improvement in physician emotional support and in their contribution to the patient's knowledge is necessary. These efforts may have a positive impact on breast cancer knowledge among black women in the US.
Keywords: adult; aged; article; attitude to health; breast tumor; cross-sectional study; decision making; female; follow up; health behavior; human; mammography; middle aged; patient participation; psychological aspect; questionnaire; survivor

An evaluation of a community-academic-clinical partnership to reduce prostate cancer disparities in the South. - Friedman, D.B.; Owens, O.L.; Jackson, D.D.; Johnson, K.M.; Gansauer, L.; Dickey, J.; Miller, R.; Payne, J.; Bearden, J.D.; Hebert, J.R. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2014)
Engaging partners in the planning, implementation, and evaluation of cancer education programs is critical for improving the health of our communities. A 2-year pilot education intervention on prostate cancer decision making and participation in medical research was funded by the National Cancer Institute. The partnership involving community members and clinical staff at a cancer center was used to develop recruitment strategies and plan for the implementation of the intervention with African-American middle-age and older men and female family members. We assessed partners' perceptions of this community-academic-clinical research collaboration. In year 2, eight project advisory council members were selected among existing partners and year 1 participants to serve as a formal committee. Council members were required to participate in telephone and in person meetings and actively support recruitment/implementation efforts. At the conclusion of the project, 20 individuals (all clinical and community partners, including the eight advisory council members) were invited to complete a survey to assess their perceived impact of the collaboration on the community and provide suggestions for future collaborations. Most partners agreed that their organization benefitted from the collaboration and that various aspects of the advisory council process (e.g., both formal and informal communication) worked well. The most noted accomplishment of the partnership related to leveraging the collaboration to make men more knowledgeable about prostate cancer decision making. Suggested improvements for future collaborations included distributing more frequent updates regarding project successes. Evaluating partners' perceptions of this collaboration provided important recommendations for future planning, implementation, and evaluation of community-based cancer education programs.
Keywords: article; community care; cooperation; ethnology; evaluation study; health care delivery; health care disparity; health education; human; male; organization and management; pilot study; prognosis; prostate tumor; United States; university hospital

Voluntary participation and comprehension of informed consent in a genetic epidemiological study of breast cancer in Nigeria. - Marshall, P.A.; Adebamowo, C.A.; Adeyemo, A.A.; Ogundiran, T.O.; Strenski, T.; Zhou, J.; Rotimi, C.N. (BMC medical ethics, 2014)
Studies on informed consent to medical research conducted in low or middle-income settings have increased, including empirical investigations of consent to genetic research. We investigated voluntary participation and comprehension of informed consent among women involved in a genetic epidemiological study on breast cancer in an urban setting of Nigeria comparing women in the case and control groups. Surveys were administered in face-to-face interviews with 215 participants following their enrollment in the genetic study (106 patients, 109 controls). Audio-taped in-depth interviews were conducted with a sub-sample of 17 (8%) women who completed the survey. The majority of all participants reported being told that participation in the genetic study was voluntary (97%), that they did not feel pressured to participate in the study (99%), and that they could withdraw from the study (81%). The majority of the breast cancer patients (83%) compared to 58% of women in the control group reported that the study purpose was to learn about the genetic inheritance of breast cancer (OR 3.44; 95% CI =1.66, 7.14, p value = 0.001). Most participants reported being told about study procedures (95%) and study benefits (98%). Sixty-eight percent of the patients, compared to 47% of the control group reported being told about study risks (p-value <0.001). Of the 165 married women, 19% reported asking permission from their husbands to enroll in the breast cancer study; no one sought permission from local elders. In-depth interviews highlight the use of persuasion and negotiation between a wife and her husband regarding study participation. The global expansion of genetic and genomic research highlights our need to understand informed consent practices for studies in ethnically diverse cultural environments such as Africa. Quantitative and qualitative empirical investigations of the informed consent process for genetic and genomic research will further our knowledge of complex issues associated with communication of information, comprehension, decisional authority and voluntary participation. In the future, the development and testing of innovative strategies to promote voluntary participation and comprehension of the goals of genomic research will contribute to our understanding of strategies that enhance the consent process.
Keywords: adult; article; attitude to health; Black person; breast tumor; comprehension; ethics; ethnology; female; genetic predisposition; genetics; human; informed consent; male; molecular epidemiology; Nigeria; patient selection; psychological aspect; questionnaire; refusal to participate; statistics

Body mass index and mortality among blacks and whites adults in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial - Xiao, Q.; Hsing, A.W.; Park, Y.; Moore, S.C.; Matthews, C.E.; De González, A.B.; Kitahara, C.M. (Obesity, 2014)
Objective In a large prospective cohort, we examined the relationship of body mass index (BMI) with mortality among blacks and compared the results to those among whites in this population. Design and Methods The study population consisted of 7,446 non-Hispanic black and 130,598 white participants, ages 49-78 at enrollment, in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial. BMI at baseline, BMI at age 20, and BMI change were calculated using self-reported and recalled height and weight. Relative risks were stratified by race and sex and adjusted for age, education, marital status, and smoking. Results During follow-up, 1,495 black and 18,236 white participants died (mean = 13 years). Clear J-shaped associations between BMI and mortality were observed among white men and women. Among black men and women, the bottoms of these curves were flatter, and increasing risks of death with greater BMI were observed only at higher BMI levels (≥35.0). Associations for BMI at age 20 and BMI change also appeared to be stronger in magnitude in whites versus blacks, and these racial differences appeared to be more pronounced among women. Conclusion Our results suggest that BMI may be more weakly associated with mortality in blacks, particularly black women, than in whites. Copyright © 2013 The Obesity Society.
Keywords: adult; age distribution; aged; article; body height; body mass; body weight; cancer mortality; cancer risk; cancer screening; Caucasian; cohort analysis; colorectal cancer; controlled study; education; female; follow up; human; lung cancer; major clinical study; male; marriage; middle aged; Black person; ovary cancer; population research; prospective study; prostate cancer; race difference; self report; sex difference; smoking

Mortality and complications after prostate biopsy in the Prostate, Lung, Colorectal and Ovarian Cancer Screening (PLCO) trial - Pinsky, P.F.; Parnes, H.L.; Andriole, G. (BJU International, 2014)
Objective To examine mortality and morbidity after prostate biopsy in the intervention arm of the Prostate, Lung, Colorectal and Ovarian Cancer Screening (PLCO) trial. Subjects and Methods Abstractors from the PLCO trial recorded the types and dates of diagnostic follow-up procedures after positive screens and documented the types and dates of resultant complications. Cancers and deaths among the participants were tracked. The mortality rate in the 120-day period after prostate biopsy was compared with a control rate of deaths in the 120-day period after a negative screen in men without biopsy. Multivariate analysis was performed to control for potential confounders, including age, comorbidities and smoking. Rates of any complication, infectious and non-infectious complications were computed among men with a negative biopsy. Multivariate analysis was used to examine the risk factors for complications. Results Of the 37 345 men enrolled in the PLCO trial (intervention arm), 4861 had at least one biopsy after a positive screen and 28 661 had a negative screen and no biopsy. The 120-day mortality rate after biopsy was 0.95 (per 1000), compared with the control group rate of 1.8; the multivariate relative risk was 0.49 (95% CI: 0.2-1.1). Among 3706 negative biopsies, the rates (per 1000) of any complication, infectious and non-infections complications were 20.2, 7.8 and 13.0, respectively. A history of prostate enlargement or inflammation was significantly associated with higher rates of both infectious (odds ratio [OR] = 3.7) and non-infectious (OR = 2.2) complications. Black race was associated with a higher infectious complications rate (OR = 7.1) and repeat biopsy was associated with lower rates of non-infectious complications (OR = 0.3). Conclusion Mortality rates were not found to be higher after prostate biopsy in the PLCO trial and complications were relatively infrequent, with several risk factors identified. © Published 2013. This article has been contributed to by US Government employees and their work is in the public domain in the USA. BJU International © 2013 BJU International.
Keywords: adult; age distribution; aged; article; cancer mortality; cancer screening; colorectal cancer; comorbidity; controlled study; disease association; ethnic difference; follow up; human; human tissue; iatrogenic disease; infectious complication; lung cancer; major clinical study; male; medical history; morbidity; multicenter study; ovary cancer; priority journal; prostate biopsy; prostate cancer; prostate hypertrophy; prostatitis; randomized controlled trial; risk assessment; risk factor; smoking

Breast cancer survivors willingness to participate in an acupuncture clinical trial: A qualitative study - Schapira, M.M.; Mackenzie, E.R.; Lam, R.; Casarett, D.; Seluzicki, C.M.; Barg, F.K.; Mao, J.J. (Supportive Care in Cancer, 2014)
Purpose: Acupuncture is a complementary and alternative medicine (CAM) modality that shows promise as a component of supportive breast cancer care. Lack of robust recruitment for clinical trial entry has limited the evidence base for acupuncture as a treatment modality among breast cancer survivors. The objective of this study is to identify key decision-making factors among breast cancer survivors considering entry into an acupuncture clinical trial for treatment of symptoms. Methods: Semistructured interviews were conducted among African-American (n=12) and Caucasian (n=13) breast cancer survivors. Verbatim transcripts were made and analyzed by two or more independent coders using NVivo software. Major recurring themes were identified and a theoretical framework developed. Results: Six themes emerged reflecting key attributes of the decision to enter a clinical trial: (1) symptom appraisal, (2) practical barriers (e.g., distance and travel), (3) beliefs about the interventions (e.g., fear of needles and dislike of medications), (4) comfort with elements of clinical trial design (e.g., randomization, the nature of the control intervention, and blinding), (5) trust, and (6) altruism. African-American and Caucasian women weighed similar attributes but differed in the information sources sought regarding clinical trial entry and in concerns regarding the use of a placebo in a clinical trial. Conclusions: Our findings contribute to the development of a theoretical model of decision making for breast cancer survivors considering participation in a CAM clinical trial. Insights regarding the decision making process can inform interventions to support informed decision making and robust recruitment to CAM trials among cancer survivors. © 2013 Springer-Verlag.
Keywords: acupuncture; adult; African American; aged; alternative medicine; altruism; article; breast cancer; cancer staging; cancer survivor; cancer therapy; Caucasian; clinical article; clinical trial (topic); female; health belief; health status; hot flush; human; menopause; patient decision making; patient participation; placebo effect; polypharmacy; primary tumor; priority journal; qualitative research; quality of life; semi structured interview; theoretical model; trust

The effects of a brief educational intervention on human papillomavirus knowledge and intention to initiate HPV vaccination in 18-26 year old young adults - Kester, L.M.; Shedd-Steele, R.B.; Dotson-Roberts, C.A.; Smith, J.; Zimet, G.D. (Gynecologic Oncology, 2014)
Objectives Despite the Advisory Committee on Immunization Practices (ACIP) recommendations for young adult females and males to receive the three-dose human papillomavirus (HPV) vaccine, most recent findings show that only 30% of the U.S. females aged 19-26, 2.8% of males aged 19-21, and only 1.7% of males aged 22-26 are initiating vaccination. This study evaluates the effects of a brief (5-10 min) group HPV educational intervention on knowledge and intent to vaccinate among young adults. Methods A sample of 131 18-26 year old females and males was recruited from the 2012 INShape Black and Minority Health Fair in Indiana. We randomized participants into one of two groups: (1) survey completion prior to education (control group) or (2) survey completion following education (intervention group). Written surveys assessed HPV knowledge, vaccination history, and vaccination intent (for unvaccinated participants). Results Respondents were primarily female (70%), single (85%), and the majority self-identified as non-Hispanic Black (77%). Thirty-seven percent had initiated HPV vaccination (≥ 1 dose) and 19% had completed the series. The intervention group had higher HPV knowledge scores (M = 9.1; SD = 1.8) than the control group (M = 7.0; SD = 2.9; F = 22.53). Among unvaccinated individuals (n = 79), the intervention group had higher HPV vaccination intent (86%) compared to the control group (67%) (OR = 3.09; 95%CI = 1.02-9.36). Conclusions Despite ACIP recommendations, young adults continue to have low awareness of vaccine benefits and low vaccination rates. This study suggests that educational interventions to increase HPV awareness and vaccination may help to boost vaccination rates. © 2013 Published by Elsevier Inc.
Keywords: Wart virus vaccine; adult; anus cancer; article; awareness; condyloma acuminatum; controlled study; female; Hispanic; human; major clinical study; male; Black person; patient attitude; patient education; priority journal; randomized controlled trial; uterine cervix cancer; vaccination; young adult

Simulation-based training for thoracoscopic lobectomy: A randomized controlled trial: Virtual-reality versus black-box simulation - Jensen, K.; Ringsted, C.; Hansen, H.J.; Petersen, R.H.; Konge, L. (Surgical Endoscopy, 2014)
Background: Video-assisted thoracic surgery is gradually replacing conventional open thoracotomy as the method of choice for the treatment of early-stage non-small cell lung cancers, and thoracic surgical trainees must learn and master this technique. Simulation-based training could help trainees overcome the first part of the learning curve, but no virtual-reality simulators for thoracoscopy are commercially available. This study aimed to investigate whether training on a laparoscopic simulator enables trainees to perform a thoracoscopic lobectomy. Methods: Twenty-eight surgical residents were randomized to either virtual-reality training on a nephrectomy module or traditional black-box simulator training. After a retention period they performed a thoracoscopic lobectomy on a porcine model and their performance was scored using a previously validated assessment tool. Results: The groups did not differ in age or gender. All participants were able to complete the lobectomy. The performance of the black-box group was significantly faster during the test scenario than the virtual-reality group: 26.6 min (SD 6.7 min) versus 32.7 min (SD 7.5 min). No difference existed between the two groups when comparing bleeding and anatomical and non-anatomical errors. Conclusion: Simulation-based training and targeted instructions enabled the trainees to perform a simulated thoracoscopic lobectomy. Traditional black-box training was more effective than virtual-reality laparoscopy training. Thus, a dedicated simulator for thoracoscopy should be available before establishing systematic virtual-reality training programs for trainees in thoracic surgery. © 2014 Springer Science+Business Media.
Keywords: adult; article; controlled study; female; human; intermethod comparison; lung lobectomy; male; outcome assessment; priority journal; randomized controlled trial; resident; simulation; simulator; thoracoscopic lobectomy; video assisted thoracoscopic surgery; virtual reality

The prognostic significance of perineural invasion and race in men considering active surveillance - Cohn, J.A.; Dangle, P.P.; Wang, C.E.; Brendler, C.B.; Novakovic, K.R.; McGuire, M.S.; Helfand, B.T. (BJU International, 2014)
Objective To determine the importance of perineural invasion (PNI) on diagnostic biopsy in men enrolled in active surveillance (AS). Patients and Methods Eligibility criteria for AS included clinical stage ≤ T2a and Gleason score ≤6, ≤3 cores positive, maximum single core involvement <50%, and total tumour volume ≤5% on diagnostic biopsy. All men received 12-core confirmation biopsy at ≤6 months. AS 'failure' on confirmatory biopsy was defined as failure to meet one or more eligibility criteria. Risk of AS failure was compared in men with and without PNI. Results For the 165 men comprising the study population, the mean (sd) age was 66.9 (6.5) years and the median (interquartile, IQR) PSA level of men at study entry was 4.4 (3.2-6.0) ng/mL. The median (IQR) follow-up was 5.5 (1.1-9.9) months. In all, 8.5% (14/165 men) had PNI on diagnostic biopsy. Compared with those without PNI, men with PNI tended to have more cores involved with cancer, at a mean (sd) of 2.0 (0.7) vs 1.6 (0.8) cores (P = 0.08) but did not have significantly a greater mean (sd) total tumour length on diagnostic biopsy, at 3.0 (2.1) vs 2.3 (3.6) mm (P = 0.27). Men with PNI on diagnostic biopsy were significantly more likely to meet criteria for disease progression on confirmatory biopsy (57% [8/14] vs 21% [32/151]; P = 0.006). PNI remained a significant predictor for AS failure after adjustment for number of positive cores, maximum percentage core involvement, and total tumour length (odds ratio 4.4, 95% confidence interval 1.4-14.2). Conclusions PNI on diagnostic biopsy is associated with disease progression on confirmatory biopsy. The presence of PNI should factor into appropriate patient selection and counselling in AS. © 2013 BJU International.
Keywords: African American; aged; article; cancer growth; cancer prognosis; cancer staging; Caucasian; disease association; disease surveillance; follow up; human; major clinical study; male; men's health; patient counseling; patient selection; perineural invasion; population research; prediction; priority journal; prostate biopsy; prostate cancer; prostate volume; race difference; risk assessment; tumor volume

Vaccine for cocaine dependence: A randomized double-blind placebo-controlled efficacy trial - Kosten, T.R.; Domingo, C.B.; Shorter, D.; Orson, F.; Green, C.; Somoza, E.; Sekerka, R.; Levin, F.R.; Mariani, J.J.; Stitzer, M.; Tompkins, D.A.; Rotrosen, J.; et al. (Drug and Alcohol Dependence, 2014)
Aims: We evaluated the immunogenicity, efficacy, and safety of succinylnorcocaine conjugated to cholera toxin B protein as a vaccine for cocaine dependence. Methods: This 6-site, 24 week Phase III randomized double-blind placebo-controlled trial assessed efficacy during weeks 8 to 16. We measured urine cocaine metabolites thrice weekly as the main outcome. Results: The 300 subjects (76% male, 72% African-American, mean age 46 years) had smoked cocaine on average for 13 days monthly at baseline. We hypothesized that retention might be better and positive urines lower for subjects with anti-cocaine IgG levels of ≥42. μg/mL (high IgG), which was attained by 67% of the 130 vaccine subjects receiving five vaccinations. Almost 3-times fewer high than low IgG subjects dropped out (7% vs 20%). Although for the full 16 weeks cocaine positive urine rates showed no significant difference between the three groups (placebo, high, low IgG), after week 8, more vaccinated than placebo subjects attained abstinence for at least two weeks of the trial (24% vs 18%), and the high IgG group had the most cocaine-free urines for the last 2 weeks of treatment (OR. = 3.02), but neither were significant. Injection site reactions of induration and tenderness differed between placebo and active vaccine, and the 29 serious adverse events did not lead to treatment related withdrawals, or deaths. Conclusions: The vaccine was safe, but it only partially replicated the efficacy found in the previous study based on retention and attaining abstinence.
Keywords: cocaine; drugs used in the treatment of addiction; immunoglobulin G antibody; placebo; succinylnorcocaine cholera toxin B conjugate; unclassified drug; vaccine; adult; alcohol intoxication; article; breast disease; chronic obstructive lung disease; cocaine dependence; cognitive therapy; controlled study; depression; double blind procedure; drug efficacy; drug fatality; drug safety; drug tolerability; drug withdrawal; ear disease; erectile dysfunction; eye disease; female; gastrointestinal disease; heart disease; hematologic disease; human; immunogenicity; immunopathology; infection; injection site induration; injection site reaction; kidney disease; leg ulcer; major clinical study; male; mental disease; middle aged; multicenter study; musculoskeletal disease; neoplasm; neurologic disease; phase 3 clinical trial; priority journal; randomized controlled trial; respiratory tract disease; side effect; skin disease; suicidal behavior; urinary tract disease; urogenital tract disease; vaccination; vascular disease

Patient trust in physician influences colorectal cancer screening in low-income patients - Gupta, S.; Brenner, A.T.; Ratanawongsa, N.; Inadomi, J.M. (American Journal of Preventive Medicine, 2014)
Background: Colorectal cancer (CRC) screening is effective but underutilized. Although physician recommendation is an important predictor of screening, considerable variation in CRC screening completion remains. Purpose: To characterize the influence of patient trust in care providers on CRC screening behavior. Methods: Data were collected as part of a cluster-randomized CRC screening intervention trial performed in the San Francisco Community Health Network from March 2007 to January 2012 (analysis, Spring 2012). All study participants received a recommendation to complete CRC screening from their primary care provider (PCP). Included participants were aged 50-79 years, not current with screening, and completed the Wake Forest Trust Scale (WFTS) measuring trust in PCPs and doctors in general. Primary outcome was CRC screening completion (colonoscopy or fecal occult blood testing) within 12 months following enrollment. Multivariable association adjusted for race/ethnicity, language, and other sociodemographics was estimated using generalized estimating equations with logit link and binomial distribution. Results: WFTS response was 70.3% (701). Most participants (83%) were Latino, Asian, or black. Most had income <$30,000 (96%) and public health insurance (86%). Higher trust in PCP was associated with screening completion (OR=1.11, 95% CI=1.03, 1.17), but trust in doctors was not (OR=1.02, 95% CI=0.82, 1.28). Race, language, and other sociodemographic factors were not significant in multivariable analysis. Conclusions: After controlling for traditional factors, trust in PCP remained the only significant driver of CRC screening completion in low-income patients. Interventions to promote CRC screening may be improved by including efforts to enhance patient trust in PCP.
Keywords: adult; article; Asian; Black person; cancer screening; colonoscopy; colorectal cancer; controlled study; doctor patient relationship; ethnicity; female; follow up; Hispanic; human; intervention study; language; lowest income group; major clinical study; male; middle aged; occult blood test; outcome assessment; primary medical care; public health insurance; trust; United States

Participation in cancer clinical trials: why are patients not participating? - Byrne, M.M.; Tannenbaum, S.L.; Glück, S.; Hurley, J.; Antoni, M. (Medical decision making : an international journal of the Society for Medical Decision Making, 2014)
Participation in cancer clinical trials is low, particularly in racial and ethnic minorities in some cases, which has negative consequences for the generalizability for study findings. The objective of this study was to determine what factors are associated with patients' participation or willingness to participate and whether these factors vary by race/ethnicity. or . White, Hispanic, and black participants were obtained through the Florida cancer registry and who were diagnosed with breast, lung, colorectal, or prostate cancer (N = 1100). Participants were surveyed via telephone to obtain demographic information, past participation, and willingness to participate in clinical trials, as well as barriers and facilitators to participation. Logistic and Poisson regressions were performed. . Respondents were on average 67.4 years old, 42.7% were male, and 50.1% were married. In this population, 7.7% of respondents had participated in a clinical trial, and 36.5% stated that they would be willing to participate. In multivariate models, blacks and Hispanics were equally likely as whites to be willing to participate in cancer trials, but Hispanics were less likely to have participated, and this was especially more likely in non-English-speaking Hispanics compared with English-speaking Hispanics. Notable barriers across race/ethnicity were mistrust and lack of knowledge of clinical trials. Limitations. Cross-sectional design limits cause-and-effect conclusions. . There are racial differences in participation rates but not in willingness to participate. We hypothesize that willingness to participate is not very high because people are uninformed about participating, particularly in non-English-speaking Hispanics. Barriers and facilitators to participation vary by race. Improved understanding of cultural differences that can be addressed by physicians may restore faith, comprehension, and acceptability of clinical trials by all patients.
Keywords: aged; article; clinical trial (topic); cohort analysis; cross-sectional study; female; human; male; middle aged; neoplasm; patient decision making; patient participation; population-based studies; psychological aspect; United States

What Women Want: Patient Recommendations for Improving Access to Breast and Cervical Cancer Screening and Follow-up - Ragas, D.M.; Nonzee, N.J.; Tom, L.S.; Phisuthikul, A.M.; Luu, T.H.; Dong, X.; Simon, M.A. (Women's Health Issues, 2014)
Background: The patient voice remains underrepresented in clinical and public health interventions. To inform interventions that strive to improve access to breast and cervical cancer screening and follow-up among low-income populations, we explored recommendations from low-income women pursuing health care in the safety net. Methods: Semi-structured interviews were conducted among women receiving follow-up care for an abnormal breast or cervical cancer screening result or a positive cancer diagnosis in federally qualified health centers, free clinics, or an academic cancer center in the Chicago metropolitan area. Findings: Of the 138 women interviewed in the parent study, 52 women provided recommendations for improving access to screening and follow-up care. Most were between 41 and 65years old (62%) and African American (60%) or White (25%). Recommendations included strengthening community-based health education with more urgent messaging, strategic partnerships, and active learning experiences to increase patient engagement, which women regarded as a key driver of access. Women also suggested increasing access by way of changes to health care delivery systems and policy, including more direct patient-provider and patient-clinic communications, addressing delays caused by high patient volume, combining preventive services, expanding insurance coverage, and adjusting screening guidelines. Conclusions: This exploratory study demonstrates important insights from the patient lens that may help to increase the acceptability and efficacy of community and clinical interventions aimed at improving access to breast and cervical cancer screening and follow-up. Further research is needed to identify appropriate integration of patient input into interventions, practice, and policy change.
Keywords: adult; aged; article; breast cancer; cancer screening; exploratory research; female; follow up; health care access; health care delivery; health care policy; health education; human; information dissemination; insurance; interpersonal communication; lowest income group; major clinical study; medical information; multicenter study; patient care; patient participation; practice guideline; preventive health service; psychosocial care; public-private partnership; qualitative research; therapy delay; uterine cervix cancer; young adult

Under-representation of racial minorities in prostate cancer studies submitted to the US Food and Drug Administration to support potential marketing approval, 1993-2013 - Wissing, M.D.; Kluetz, P.G.; Ning, Y.-M.; Bull, J.; Merenda, C.; Murgo, A.J.; Pazdur, R. (Cancer, 2014)
BACKGROUND US Food and Drug Administration (FDA) approval of new drugs depends on results from clinical trials that must be generalized to the US population. However, racial minorities are frequently under-represented in clinical studies. The enrollment of racial minorities was compared in key clinical studies submitted to the FDA in the last 10 years in support of potential marketing approval for prostate cancer (PCa) prevention or treatment. METHODS Patient demographic data were obtained from archival data sets of large registration trials submitted to the FDA to support proposed PCa indications. Six countries/regions were analyzed: the United States, Canada, Australia, Europe, the United Kingdom, and Eastern Europe. Background racial demographics were collected from national census data. RESULTS Seventeen key PCa clinical trials were analyzed. These trials were conducted in the past 20 years, comprising 39,574 patients with known racial information. Most patients were enrolled in the United States, but there appeared to be a trend toward increased non-US enrollment over time. In all countries, racial minorities were generally under-represented. There was no significant improvement in racial minority enrollment over time. The United States enrolled the largest nonwhite population (7.1%). CONCLUSIONS Over the past 20 years, racial minorities were consistently under-represented in key PCa trials. There is a need for effective measures that will improve enrollment of racial minorities. With increased global enrollment, drug developers should aim to recruit a patient population that resembles the racial demographics of the patient population to which drug use will be generalized upon approval.
Keywords: abiraterone acetate; atrasentan; cabazitaxel; degarelix; denosumab; docetaxel; dutasteride; enzalutamide; finasteride; leuprorelin; radium chloride ra 223; satraplatin; sipuleucel T; triptorelin; Alaska Native; American Indian; article; Asian; Australia; Black person; Canada; Canadian; cancer prevention; castration resistant prostate cancer; Caucasian; clinical trial; controlled study; drug approval; drug marketing; drug use; Eastern Europe; Europe; Food and Drug Administration; Hispanic; human; indigenous people; major clinical study; minority group; Pacific Islander; priority journal; prostate cancer; trend study; United Kingdom; United States

Does a community-based stress management intervention affect psychological adaptation among underserved black breast cancer survivors? - Lechner, S.C.; Whitehead, N.E.; Vargas, S.; Annane, D.W.; Robertson, B.R.; Carver, C.S.; Kobetz, E.; Antoni, M.H. (Journal of the National Cancer Institute - Monographs, 2014)
Background: In this randomized trial, Project CARE, we examined whether participation in a cognitive-behavioral stress management and breast cancer wellness and education program improved psychological outcomes among a sample of underserved black breast cancer survivors. Methods: Both complementary medicine interventions were 10-sessions, manualized, group-based, and were culturally adapted for black women in the community from evidence-based interventions. Participants were 114 black women (mean age = 51.1, 27-77 years) who had completed breast cancer treatment 0-12 months before enrollment (stages 0-IV, mean time since cancer diagnosis = 14.1 months). Women were enrolled upon completion of curative treatment (ie, surgical, chemotherapy, radiation oncology) and randomized to receive cognitivebehavioral stress management or cancer wellness and education program. Results: There was a remarkable 95% retention rate from baseline to 6-month follow-up. Participants in both conditions showed statistically significant improvement on indices of psychological well-being, including overall quality of life (Functional Assessment of Cancer Therapy-Breast), intrusive thoughts (Impact of Event Scale-Revised), depressive symptoms (Center for Epidemiologic Studies-Depression), and stress levels (Perceived Stress Scale) over the 6-month postintervention follow-up (all repeated measures analysis of variance within-subjects time effects: P < .05, except for overall mood; Profile of Mood States-Short Version). Contrary to hypotheses, however, condition × time effects were not statistically significant. Conclusions: Findings suggest that improvements in multiple measures over time may have been due to intensive training in stress management, extensive provision of breast cancer information, or participation in an ongoing supportive group of individuals from a similar racial background. Implications bear on decisions about appropriate control groups, the timing of intervention delivery during the treatment trajectory, and perceived support from the research team.
Keywords: adult; aged; alternative medicine; article; breast cancer; cancer diagnosis; cancer staging; cancer survivor; Center for Epidemiologic Studies Depression; cognitive behavioral stress management; community care; controlled study; education program; female; follow up; Functional Assessment of Cancer Therapy Breast; human; Impact of Events Scale; major clinical study; Perceived Stress Scale; priority journal; Profile of Mood States; psychological aspect; psychological well-being; psychophysiologic assessment; quality of life; randomized controlled trial; relaxation training; social adaptation

Hyperphosphatemia is a combined function of high serum PTH and high dietary protein intake in dialysis patients - Streja, E.; Lau, W.L.; Goldstein, L.; Sim, J.J.; Molnar, M.Z.; Nissenson, A.R.; Kovesdy, C.P.; Kalantar-Zadeh, K. (Kidney International Supplements, 2013)
Elevated serum phosphorus is associated with higher death risk in hemodialysis patients. Previous studies have suggested that both higher serum parathyroid hormone (PTH) level and higher dietary protein intake may contribute to higher serum phosphorus levels. However, it is not well known how these two factors simultaneously contribute to the combined risk of hyperphosphatemia in real patient-care scenarios. We hypothesized that the likelihood of hyperphosphatemia increases across higher serum PTH and higher normalized protein catabolic rate (nPCR) levels, a surrogate of protein intake. Over an 8-year period (July 2001-June 2009), we identified 69,355 maintenance hemodialysis patients with PTH, nPCR, and phosphorus data in a large dialysis provider. Logistic regression models were examined to assess the association between likelihood of hyperphosphatemia (serum phosphorus >5.5mg/dl) and serum PTH and nPCR increments. Patients were 61±15 years old and included 46% women, 33% blacks, and 57% diabetics. Both higher serum PTH level and higher protein intake were associated with higher risk of hyperphosphatemia in dialysis patients. Compared with patients with PTH level 150-<300 pg/ml and nPCR level 1.0-<1.2 g/kg/day, patients with iPTH4600 pg/ml and nPCR>1.2 g/kg/day had a threefold higher risk of hyperphosphatemia (OR: 3.17, 95% CI: 2.69-3.75). Hyperphosphatemia is associated with both higher dietary protein intake and higher serum PTH level in maintenance hemodialysis patients. Worsening or resistant hyperphosphatemia may be an under-appreciated consequence of secondary hyperparathyroidism independent of dietary phosphorus load. Management of hyperphosphatemia should include diligent correction of hyper-parathyroidism while maintaining adequate intake of high protein foods with low phosphorus content. © 2013 International Society of Nephrology.
Keywords: albumin; alkaline phosphatase; bicarbonate; calcium; creatinine; ferritin; hemoglobin; parathyroid hormone; phosphorus; acquired immune deficiency syndrome; adult; aged; albumin blood level; alkaline phosphatase blood level; article; atherosclerosis; coronary artery atherosclerosis; bicarbonate blood level; calcium blood level; cardiovascular disease; case mix; catabolism; cerebrovascular disease; chronic obstructive lung disease; comorbidity; congestive heart failure; creatinine blood level; diabetes mellitus; disease association; female; ferritin blood level; hemodialysis patient; hemoglobin blood level; human; Human immunodeficiency virus infection; hyperparathyroidism; hyperphosphatemia; hypertension; hypothesis; insurance; iron binding capacity; leukocyte count; lymphocyte count; maintenance therapy; major clinical study; male; malignant neoplasm; marriage; middle aged; parathyroid hormone blood level; patient selection; peripheral vascular disease; phosphate blood level; prevalence; protein intake; renal replacement therapy; secondary hyperparathyroidism; treatment duration

Stage-adjusted lung cancer survival does not differ between low-income blacks and whites - Aldrich, M.C.; Grogan, E.L.; Munro, H.M.; Signorello, L.B.; Blot, W.J. (Journal of Thoracic Oncology, 2013)
Introduction: Few lung cancer studies have focused on lung cancer survival in underserved populations. We conducted a prospective cohort study among 81,697 racially diverse and medically underserved adults enrolled in the Southern Community Cohort Study throughout an 11-state area of the Southeast from March 2002 to September 2009. Methods: Using linkages with state cancer registries, we identified 501 incident non-small-cell lung cancer cases. We applied Cox proportional hazards models to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for subsequent mortality among black and white participants. Results: The mean observed follow-up time (the time from diagnosis to death or end of follow-up) was 1.25 years (range, 0-8.3 years) and 75% (n = 376) of cases died during follow-up. More blacks were diagnosed at distant stage than whites (57 versus 45%; p = 0.03). In multivariable analyses adjusted for pack-years of smoking, age, body mass index, health insurance, socioeconomic status and disease stage, the lung cancer mortality HR was higher for men versus women (HR = 1.41; 95% CI, 1.09-1.81) but similar for blacks versus whites (HR = 0.99; 95% CI, 0.74-1.32). Conclusion: These findings suggest that although proportionally more blacks present with distant-stage disease there is no difference in stage-adjusted lung cancer mortality between blacks and whites of similar low socioeconomic status. Copyright © 2013 by the International Association for the Study of Lung Cancer.
Keywords: adult; age; article; body mass; cancer diagnosis; cancer incidence; cancer mortality; cancer registry; cancer staging; cancer survival; Caucasian; cohort analysis; confidence interval; controlled study; female; follow up; health insurance; human; lowest income group; non small cell lung cancer; major clinical study; male; middle aged; Black person; priority journal; proportional hazards model; prospective study; randomized controlled trial; smoking; social status

Efficacy to effectiveness transition of an Educational Program to Increase Colorectal Cancer Screening (EPICS): study protocol of a cluster randomized controlled trial. - Smith, S.A.; Blumenthal, D.S. (Implementation science : IS, 2013)
African Americans have the highest incidence and mortality and are less likely than whites to have been screened for colorectal cancer (CRC). Many interventions have been shown to increase CRC screening in research settings, but few have been evaluated specifically for use in African-American communities in real world settings. This study aims to identify the most efficacious approach to disseminate an evidence-based intervention in promoting colorectal screening in African Americans and to identify the factors associated with its efficacy. In this study, investigators will recruit 20 community coalitions and 7,200 African-Americans age 50 to 74 to test passive and active approaches to disseminating the Educational Program to Increase Colorectal Cancer Screening (EPICS); to measure the extent to which EPICS is accepted and the fidelity of implementation in various settings and to estimate the potential translatability and public health impact of EPICS. This four-arm cluster randomized trial compares the following implementation strategies: passive arms, (web access to facilitator training materials and toolkits without technical assistance (TA) and (web access, but with technical assistance (TA); active arms, (in-person access to facilitator training materials and toolkits without TA and (in-person access with TA). Primary outcome measures are the reach (the proportion of representative community coalitions and individuals participating) and efficacy (post-intervention changes in CRC screening rates). Secondary outcomes include adoption (percentage of community coalitions implementing the EPICS sessions) and implementation (quality and consistency of the intervention delivery). The extent to which community coalitions continue to implement EPICS post-implementation (maintenance) will also be measured. Cost-effectiveness analysis will be conducted. Implementing EPICS in partnership with community coalitions, we hypothesized, will result in more rapid adoption than traditional top-down approaches, and resulting changes in community CRC screening practices are more likely to be sustainable over time. With its national reach, this study has the potential to enhance our understanding of barriers and enablers to the uptake of educational programs aimed at eliminating cancer disparities. http://www.ClinicalTrials.gov NCT01805622.
Keywords: NCT01805622; African American; aged; article; cluster analysis; colorectal tumor; controlled clinical trial; controlled study; early diagnosis; ethnology; female; health disparity; health promotion; human; male; methodology; middle aged; organization and management; patient education; randomized controlled trial; treatment outcome

Coaching intervention as a strategy for minority recruitment to cancer clinical trials - Fracasso, P.M.; Goodner, S.A.; Creekmore, A.N.; Morgan, H.P.; Foster, D.M.; Hardmon, A.A.; Engel, S.J.; Springer, B.C.; Mathews, K.J.; Fisher, E.B.; Walker, M.S. (Journal of Oncology Practice, 2013)
Purpose: Lack of trust and rapport with health care providers has been identified in the under-representation of racial/ethnic minorities within clinical trials. Our study used a coach to promote trust among minority patients with advanced cancer. Patients and Methods: Minority patients with advanced breast, colorectal, lung, or prostate carcinoma were randomly assigned to receive a coach Intervention (CI) or usual care (UC). All patients completed baseline and 6-month telephone interviews to assess demographics, trust in health care providers, attitudes toward clinical trials, and quality of life. Patients randomly assigned to CI were assigned a coach, who made bi-weekly contacts for 6 months to address general issues, progress or development in cancer care, and available resources. Patients randomly assigned to UC received the standard of care, without this intervention. Clinical trial enrollment was assessed. Results: Over 21 months, we screened 268 patients and enrolled 73 African Americans and two Asian Americans. Patients were randomly assigned to CI (n = 38) or to UC (n = 37). Longitudinal analyses were conducted on 69 patients who completed the 6-month follow-up assessment. Trial enrollment was 16 and 13 patients for the CI and UC groups, respectively. This difference was not significant (P = .351). Higher quality of life (1-point odds ratio on Functional Assessment of Cancer Treatment-General = 1.033, P = .036) and positive attitudes toward trials predicted enrollment. There was no significant difference between these groups in quality of life, attitudes toward clinical trials, perceptions of racism, trust in doctors, or depression. Conclusions: Quality of life and positive attitude toward trials predicted trial enrollment, regardless of assignment to CI or UC. Copyright © 2013 by American Society of Clinical Oncology.
Keywords: adult; advanced cancer; African American; aged; article; Asian American; breast cancer; coach intervention; colorectal cancer; controlled study; depression; female; follow up; functional assessment; health care personnel; hospital readmission; human; lung cancer; major clinical study; male; patient; patient education; prostate carcinoma; quality of life; racism; randomized controlled trial; telephone interview; trust; usual care; very elderly

Psychosocial benefits of a novel mindfulness intervention versus standard support in distressed women with breast cancer - Monti, D.A.; Kash, K.M.; Kunkel, E.J.; Moss, A.; Mathews, M.; Brainard, G.; Anne, R.; Leiby, B.E.; Pequinot, E.; Newberg, A.B. (Psycho-Oncology, 2013)
Objective: It is well documented that stress is associated with negative health outcomes in cancer patients. The purpose of this study was to assess the effects of a novel mindfulness intervention called mindfulness-based art therapy (MBAT) versus standard educational support, on indices of stress and quality of life in breast cancer patients with high stress levels. Methods: A total of 191 women were enrolled, stratified by age and stress level, and randomized to receive either an 8-week MBAT intervention or a breast cancer educational support program of equal time and duration. Psychosocial stress was measured using the Symptoms Checklist-90-Revised, and quality of life was measured using the Medical Outcomes Study Short-Form Health Survey at baseline, immediately post-intervention, and at 6 months. Results: Results showed overall significant improvements in psychosocial stress and quality of life in both the MBAT and educational support groups immediately post-intervention; however, participants with high stress levels at baseline had significantly improved overall outcomes only in the MBAT group, both immediately post-intervention and at 6 months. In addition, at 6 months follow-up, participants attending five or more sessions trended toward retaining treatment effects better in the MBAT than in the control group. Finally, black women and white women were similar in terms of how they benefited from the MBAT intervention, even though white participants tended to have higher educational level and marital status. Conclusions: In conclusion, MBAT is associated with significant, sustained benefits across a diverse range of breast cancer patients, particularly those with high stress levels. Copyright © 2013 John Wiley & Sons, Ltd.
Keywords: adult; aged; art therapy; article; breast cancer; controlled study; female; follow up; health program; health survey; human; major clinical study; mental stress; mindfulness based art therapy; outcome assessment; quality of life; randomized controlled trial; social care; standard educational support; support group; Symptom Checklist 90

Behavioral treatment for weight gain prevention among black women in primary care practice: A randomized clinical trial - Bennett, G.G.; Foley, P.; Levine, E.; Whiteley, J.; Askew, S.; Steinberg, D.M.; Batch, B.; Greaney, M.L.; Miranda, H.; Wroth, T.H.; Holder, M.G.; Emmons, K.M.; et al. (JAMA Internal Medicine, 2013)
Importance Few weight loss treatments produce clinically meaningful weight loss outcomes among black women, particularly in the primary care setting. New weight management strategies are necessary for this population. Weight gain prevention might be an effective treatment option, with particular benefits for overweight and class 1 obese black women. OBJECTIVE To compare changes in weight and cardiometabolic risk during a 12-month period among black women randomized to a primary care-based behavioral weight gain prevention intervention, relative to usual care. DESIGN. SETTING. AND PARTICIPANTS Two-arm randomized clinical trial (the Shape Program). We recruited patients from a 6-site community health center system. We randomized 194 overweight and class 1 obese (body mass index [calculated as weight in kilograms divided by height in meters squared], 25-34.9) premenopausal black women aged 25 to 44 years. Enrollment began on December 7,2009; 12- and 18-month assessments were completed in February and October 2,2012. interventions The medium-intensity intervention included tailored behavior change goals, weekly self-monitoring via interactive voice response, monthly counseling calls, tailored skills training materials, and a gym membership. MAIN OUTCOMES AND MEASURES Twelve-month change in weight and body mass index and maintenance of change at 18 months. RESULTS Participants had a mean age of 35.4 years, a mean weight of 81.1 kg. and a mean body mass index of 30.2 at baseline. Most were socioeconomically disadvantaged (79.7% with educational level less than a college degree; 74.3% reporting annual income <$30 000). The 12-month weight change was larger among intervention participants (mean [SD], -1.0 [0.5] kg), relative to usual care (0.5 [0.5] kg; mean difference, -1.4 kg [95% CI. -2.8 to -0.1 kg]; P = .04). At month 12,62% of intervention participants were at or below their baseline weights compared with 45% of usual-care participants (P = .03). By 18 months, intervention participants maintained significantly larger changes in weight (mean difference, -1.7 kg; 95% CI.-3.3 to-0.2 kg). CONCLUSIONS and relevance A medium-intensity primary care-based behavioral intervention demonstrated efficacy for weight gain prevention among socioeconomically disadvantaged black women. A "maintain, don't gain" approach might be a useful alternative treatment for reducing obesity-associated disease risk among some premenopausal black women.
Keywords: NCT00938535; high density lipoprotein cholesterol; low density lipoprotein cholesterol; triacylglycerol; adult; article; behavior change; behavior modification; body mass; breast abscess; cancer diagnosis; cardiometabolic risk; comparative study; controlled study; female; health care practice; human; income; knee arthroplasty; major clinical study; musculoskeletal injury; Black person; obesity; physical activity; primary medical care; priority journal; randomized controlled trial; risk assessment; socioeconomics; body weight change; body weight gain

Racial disparities in treatment patterns and clinical outcomes in patients with HER2-positive metastatic breast cancer - Rugo, H.S.; Brufsky, A.M.; Yood, M.U.; Tripathy, D.; Kaufman, P.A.; Mayer, M.; Yoo, B.; Abidoye, O.O.; Yardley, D.A. (Breast Cancer Research and Treatment, 2013)
Data characterizing demographics, treatment patterns, and clinical outcomes in black patients with human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (MBC) are limited. registHER is a large, observational cohort study of patients (n = 1,001) with HER2-positive MBC diagnosed ≤6 months of enrollment and followed until death, disenrollment, or June 2009 (median follow-up of 27 months). Demographics, treatment patterns, and clinical outcomes were described for black (n = 126) and white patients (n = 793). Progression-free survival (PFS) following first-line therapy and overall survival (OS) were examined. Multivariate analyses adjusted for baseline and treatment factors. Black patients were more likely than white patients to be obese (body mass index ≥30), to have diabetes, and to have a history of cardiovascular disease; they were also less likely to have estrogen receptor or progesterone receptor positive disease. In patients treated with trastuzumab, the incidence of cardiac safety events (grade ≥3) was higher in black patients (10.9 %) than in white patients (7.9 %). Unadjusted median OS and PFS (months) were significantly lower in black patients than in white patients (OS: black: 27.1, 95 % confidence interval [CI] 21.3-32.1; white: 37.3, 95 % CI 34.6-41.1; PFS: black: 7.0, 95 % CI 5.7-8.2; white: 10.2, 95 % CI 9.3-11.2). The adjusted OS hazard ratio (HR) for black patients compared with white patients was 1.29 (95 % CI 1.00-1.65); adjusted PFS HR was 1.29 (95 % CI 1.05-1.59). This real-world evaluation of a large cohort of patients with HER2-positive MBC shows poorer prognostic factors and independently worse clinical outcomes in black versus white patients. Further research is needed to identify potential biologic differences that could have predictive impact for black patients or that could explain these differences. © 2013 The Author(s).
Keywords: NCT00105456; epidermal growth factor receptor 2; estrogen receptor; hormone; progesterone receptor; trastuzumab; adult; aged; angina pectoris; article; metastatic breast cancer; cancer chemotherapy; cancer hormone therapy; cardiovascular disease; Caucasian; cohort analysis; congestive heart failure; demography; diabetes mellitus; drug efficacy; drug safety; female; follow up; heart atrium arrhythmia; heart disease; heart infarction; heart left ventricle failure; heart ventricle arrhythmia; HER2 positive metastatic breast cancer; human; incidence; major clinical study; male; medical history; multicenter study (topic); Black person; obesity; observational study; outcome assessment; overall survival; pericardial effusion; priority journal; prognosis; progression free survival; race difference

Rethinking sources of representative controls for the conduct of case-control studies in minority populations. - Bandera, E.V.; Chandran, U.; Zirpoli, G.; McCann, S.E.; Ciupak, G.; Ambrosone, C.B. (BMC medical research methodology, 2013)
Recruitment of controls remains a challenge in case-control studies and particularly in studies involving minority populations. We compared characteristics of controls recruited through random digit dialing (RDD) to those of community controls enrolled through churches, health events and other outreach sources among women of African ancestry (AA) participating in the Women's Circle of Health Study, a case-control study of breast cancer. Odds ratios and 95% confidence intervals were also computed using unconditional logistic regression to evaluate the impact of including the community controls for selected variables relevant to breast cancer and for which there were significant differences in distribution between the two control groups. Compared to community controls (n=347), RDD controls (n=207) had more years of education and higher income, lower body mass index, were more likely to have private insurance, and less likely to be single. While the percentage of nulliparous women in the two groups was similar, community controls tended to have more children, have their first child at a younger age, and were less likely to breastfeed their children. Dietary intake was similar in the two groups. Compared to census data, the combination of RDD and community controls seems to be more representative of the general population than RDD controls alone. Furthermore, the inclusion of the community group had little impact on the magnitude of risk estimates for most variables, while enhancing statistical power. Community-based recruitment was found to be an efficient and feasible method to recruit AA controls.
Keywords: adult; aged; article; breast tumor; case control study; Caucasian; control group; female; human; intraductal carcinoma; male; methodology; middle aged; minority group; Black person; patient selection; risk factor

A novel community-based study to address disparities in hypertension and colorectal cancer: A study protocol for a randomized control trial - Ravenell, J.; Thompson, H.; Cole, H.; Plumhoff, J.; Cobb, G.; Afolabi, L.; Boutin-Foster, C.; Wells, M.; Scott, M.; Ogedegbe, G. (Trials, 2013)
Background: Black men have the greatest burden of premature death and disability from hypertension (HTN) in the United States, and the highest incidence and mortality from colorectal cancer (CRC). While several clinical trials have reported beneficial effects of lifestyle changes on blood pressure (BP) reduction, and improved CRC screening with patient navigation (PN), the effectiveness of these approaches in community-based settings remains understudied, particularly among Black men.Methods/design: MISTER B is a two-parallel-arm randomized controlled trial that will compare the effect of a motivational interviewing tailored lifestyle intervention (MINT) versus a culturally targeted PN intervention on improvement of BP and CRC screening among black men aged ≥50 with uncontrolled HTN who are eligible for CRC screening. Approximately 480 self-identified black men will be randomly assigned to one of the two study conditions. This innovative research design allows each intervention to serve as the control for the other. Specifically, the MINT arm is the control condition for the PN arm, and vice-versa. This novel, simultaneous testing of two community-based interventions in a randomized fashion is an economical and yet rigorous strategy that also enhances the acceptability of the project. Participants will be recruited during scheduled screening events at barbershops in New York City. Trained research assistants will conduct the lifestyle intervention, while trained community health workers will deliver the PN intervention. The primary outcomes will be 1) within-patient change in systolic and diastolic BP from baseline to six months and 2) CRC screening rates at six months.Discussion: This innovative study will provide a unique opportunity to test two interventions for two health disparities simultaneously in community-based settings. Our study is one of the first to test culturally targeted patient navigation for CRC screening among black men in barbershops. Thus, our study has the potential to improve the reach of hypertension control and cancer prevention efforts within a high-risk population that is under-represented in primary care settings.Trial registration: ClinicalTrials.gov, NCT01092078. © 2013 Ravenell et al.; licensee BioMed Central Ltd.
Keywords: NCT01092078; adult; article; blood pressure regulation; cancer screening; colorectal cancer; community program; comparative effectiveness; controlled study; diastolic blood pressure; health auxiliary; health care disparity; human; hypertension; intermethod comparison; intervention study; lifestyle modification; major clinical study; male; motivational interviewing; Black person; patient care; randomized controlled trial; study design; systolic blood pressure

Inclusion of minorities and women in cancer clinical trials, a decade later: Have we improved? - Kwiatkowski, K.; Coe, K.; Bailar, J.C.; Swanson, G.M. (Cancer, 2013)
BACKGROUND Inclusion of diverse groups of participants in cancer clinical trials is an important methodological and clinical issue. The quality of the science and generalizability of results depends on the inclusion of study participants who represent all populations among whom these treatment and prevention approaches will be used. METHODS We conducted a systematic review using OVID as the primary source of reports included. Based on 304 peer-reviewed publications, diversity in the inclusion and reporting of study participants during a decade of cancer treatment and prevention trials (2001-2010) is summarized. Recommendations are made for improvements in the science and reporting of cancer clinical trials. RESULTS Of the 277 treatment trials and 27 prevention trials included in this report, more than 80% of participants were white and 59.8% were male. In the recent decade, race and sex are rarely used as selection criteria unless the trial is focused on a sex-specific cancer. CONCLUSIONS Women and racial/ethnic minorities remain severely underrepresented in cancer clinical trials, thus limiting the generalizability of cancer clinical research. © 2013 American Cancer Society.
Keywords: African American; American Indian; article; Asian; breast carcinoma; cancer mortality; cancer prevention; cancer recurrence; cancer research; cancer risk; cancer survival; cancer therapy; Caucasian; clinical trial (topic); endometrium carcinoma; ethnic difference; ethnic group; gender; Hispanic; human; ovary carcinoma; patient selection; priority journal; prostate carcinoma; publication; quality of life; race difference; risk reduction; sex difference; systematic review; testis carcinoma; uterine cervix carcinoma

Navigating veterans with an abnormal prostate cancer screening test: a quasi-experimental study - Simon, M.A.; Nonzee, N.J.; McKoy, J.M.; Liu, D.; Luu, T.H.; Byer, P.; Eklund, E.A.; Richey, E.A.; Wu, Z.; Dong, X.; Rademaker, A.W. (BMC health services research, 2013)
BACKGROUND: Prostate cancer disproportionately affects low-income and minority men. This study evaluates the impact of a patient navigation intervention on timeliness of diagnostic resolution and treatment initiation among veterans with an abnormal prostate cancer screen. METHODS: Participants were enrolled between 2006 and 2010. The intervention involved a social worker and lay health worker navigation team that assisted patients in overcoming barriers to care. For navigated (n = 245) versus control (n = 245) participants, we evaluated rates of diagnostic resolution and treatment and adjusted for race, age, and Gleason score. RESULTS: Of 490 participants, 68% were African American, 47% were ≥ 65 years old, and 35% had cancer. Among those with an abnormal screen, navigation did not have a significant effect on time to diagnostic resolution compared to controls (median days of 97 versus 111; adj. HR 1.17, 95% CI, 0.96-1.43, p = 0.12). On analysis of the period beyond 80 days, navigated men reached resolution faster than controls (median of 151 days versus 190 days; adj. HR 1.41, 95% CI, 1.07-1.86, p = 0.01). Among those with cancer, navigation did not have a significant effect on time to treatment initiation compared to controls (median of 93 days versus 87 days; adj. HR 1.15, 95% CI, 0.82-1.62, p = 0.41). CONCLUSION: Our navigation program did not significantly impact the overall time to resolution or treatment for men with prostate cancer compared to controls. The utility of navigation programs may extend beyond targeted navigation times, however, and future studies focusing on other outcomes measures are therefore needed.
Keywords: prostate specific antigen; adult; aged; blood; clinical trial; early cancer diagnosis; human; male; middle aged; organization and management; patient care; procedures; prostate tumor; public hospital; social work; time factor; United States; very elderly; veteran

Adherence to World Cancer Research Fund/American institute for cancer research lifestyle recommendations reduces prostate cancer aggressiveness among African and Caucasian Americans - Arab, L.; Su, J.; Steck, S.E.; Ang, A.; Fontham, E.T.H.; Bensen, J.T.; Mohler, J.L. (Nutrition and Cancer, 2013)
The effect of adherence to the World Cancer Research Fund (WCRF) lifestyle recommendations on cancer aggressiveness is unknown. We examined associations between adherence to recommendations and risk of highly aggressive prostate cancer in research subjects enrolled in the North Carolina-Louisiana Prostate Cancer Project (PCaP). We examined associations between adherence to WCRF recommendations and risk of highly aggressive prostate cancer among 2212 newly diagnosed African Americans (AA) or Caucasian Americans (CA) aged 40-70 years in PCaP. Prostate cancer aggressiveness was based on Gleason scores, serum prostate-specific antigens, and TNM stage. Adherence to WCRF recommendations was based on point scores and odds ratios estimated. Results showed that adherence to recommendations was significantly and negatively associated with risk of a highly aggressive prostate cancer. Each additional point in the total adherence score corresponded to a 13% risk reduction. Total adherence score <4 predicted increased risk in both AA (OR = 1.36; 95% CI = 1.01-1.85) and CA (OR = 1.41; 95% CI = 1.01-1.98). Consumption of <500 g red meat per week or ≤125 total kcal/100 g solid food per day is a statistically significant protective factor in the overall cohort. Recommendations aimed at preventing all cancers also may reduce risk of highly aggressive prostate cancer. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: prostate specific antigen; adult; African American; aged; article; cancer prevention; cancer staging; clinical assessment tool; cohort analysis; cross-sectional study; European American; food intake; Gleason score; human; lifestyle modification; major clinical study; male; patient compliance; prediction; prostate cancer; red meat; research subject; risk factor; risk reduction; World Cancer Research Fund lifestyle recommendation

National evidence on the use of shared decision making in prostate-specific antigen screening. - Han, P.K.; Kobrin, S.; Breen, N.; Joseph, D.A.; Li, J.; Frosch, D.L.; Klabunde, C.N. (Annals of family medicine, 2013)
Recent clinical practice guidelines on prostate cancer screening using the prostate-specific antigen (PSA) test (PSA screening) have recommended that clinicians practice shared decision making-a process involving clinician-patient discussion of the pros, cons, and uncertainties of screening. We undertook a study to determine the prevalence of shared decision making in both PSA screening and nonscreening, as well as patient characteristics associated with shared decision making. A nationally representative sample of 3,427 men aged 50 to 74 years participating in the 2010 National Health Interview Survey responded to questions on the extent of shared decision making (past physician-patient discussion of advantages, disadvantages, and scientific uncertainty associated with PSA screening), PSA screening intensity (tests in past 5 years), and sociodemographic and health-related characteristics. Nearly two-thirds (64.3%) of men reported no past physician-patient discussion of advantages, disadvantages, or scientific uncertainty (no shared decision making); 27.8% reported discussion of 1 to 2 elements only (partial shared decision making); 8.0% reported discussion of all 3 elements (full shared decision making). Nearly one-half (44.2%) reported no PSA screening, 27.8% reported low-intensity (less-than-annual) screening, and 25.1% reported high-intensity (nearly annual) screening. Absence of shared decision making was more prevalent in men who were not screened; 88% (95% CI, 86.2%-90.1%) of nonscreened men reported no shared decision making compared with 39% (95% CI, 35.0%-43.3%) of men undergoing high-intensity screening. Extent of shared decision making was associated with black race, Hispanic ethnicity, higher education, health insurance, and physician recommendation. Screening intensity was associated with older age, higher education, usual source of medical care, and physician recommendation, as well as with partial vs no or full shared decision making. Most US men report little shared decision making in PSA screening, and the lack of shared decision making is more prevalent in nonscreened than in screened men. Screening intensity is greatest with partial shared decision making, and different elements of shared decision making are associated with distinct patient characteristics. Shared decision making needs to be improved in decisions for and against PSA screening.
Keywords: prostate specific antigen; tumor marker; adult; aged; article; attitude to health; blood; decision making; early diagnosis; human; male; mass screening; methodology; middle aged; patient care; patient participation; prevalence; prostate tumor; psychological aspect; risk factor; United States

A culturally adapted family intervention for African American families coping with parental cancer: Outcomes of a pilot study - Davey, M.P.; Kissil, K.; Lynch, L.; Harmon, L.-R.; Hodgson, N. (Psycho-Oncology, 2013)
Objectives The primary objective of this 2-year pilot study was to evaluate the effectiveness of a culturally adapted family intervention in improving family communication among African American parents coping with cancer and their school-age children. A secondary objective was to determine its impact on other symptoms of psychosocial distress (depression and anxiety). The third objective was to assess for acceptability and feasibility. Methods Using a two-arm pre-intervention and post-intervention prospective design, 12 African American families received five bi-monthly sessions of either a culturally adapted family intervention (n = 7 families) or psycho-education treatment (n = 5 families). Parents and their children completed pre-intervention and post-intervention questionnaires assessing perceptions of family communication, quality of their relationship, and symptoms of depression. School-age children additionally completed a questionnaire assessing their levels of anxiety. Consumer satisfaction was also evaluated at post-intervention. Results Parents and school-age children who completed the culturally adapted family intervention reported significantly better communication with each other and were more satisfied compared with the psycho-education control group. No changes were noted in symptoms of anxiety or depression. The culturally adapted family intervention was acceptable based on our findings, families' feedback, and rates of retention. Feasibility is uncertain because our oncology clinic approach to recruitment was slower than expected. Conclusions Providing culturally adapted family intervention programs to African American families who are coping with parental cancer may result in improved family communication. This pilot study serves as the first step in the development of culturally adapted family intervention programs to help African American families cope with parental cancer. Copyright © 2012 John Wiley & Sons, Ltd. Copyright © 2012 John Wiley & Sons, Ltd.
Keywords: antineoplastic agent; adult; African American; anxiety; article; breast cancer; cancer surgery; chemoradiotherapy; child; child parent relation; clinical article; clinical effectiveness; clinical trial; cultural factor; depression; family coping; family interaction; family therapy; female; human; kidney cancer; lung cancer; male; melanoma; mental stress; pancreas cancer; patient satisfaction; pilot study; psychoeducation; questionnaire; school child

Psychoneuroimmunology-based stress management during adjuvant chemotherapy for early breast cancer - Robins, J.L.W.; McCain, N.L.; Elswick, R.K.; Walter, J.M.; Gray, D.P.; Tuck, I. (Evidence-based Complementary and Alternative Medicine, 2013)
Objective. In a randomized trial of women with early stage breast cancer undergoing adjuvant chemotherapy, two stress management interventions, tai chi training and spiritual growth groups, were compared to a usual care control group, to evaluate psychosocial functioning, quality of life (QOL), and biological markers thought to reflect cancer- and treatment-specific mechanisms. Method. The sample consisted of 145 women aged 27-75 years; 75% were Caucasian and 25% African American. A total of 109 participants completed the study, yielding a 75% retention rate. Grounded in a psychoneuroimmunology framework, the overarching hypothesis was that both interventions would reduce perceived stress, enhance QOL and psychosocial functioning, normalize levels of stress-related neuroendocrine mediators, and attenuate immunosuppression. Results. While interesting patterns were seen across the sample and over time, the interventions had no appreciable effects when delivered during the period of chemotherapy. Conclusions. Findings highlight the complex nature of biobehavioral interventions in relation to treatment trajectories and potential outcomes. Psychosocial interventions like these may lack sufficient power to overcome the psychosocial or physiological stress experienced during the chemotherapy treatment period. It may be that interventions requiring less activity and/or group attendance would have enhanced therapeutic effects, and more active interventions need to be tested prior to and following recovery from chemotherapy. © 2013 Jo Lynne W. Robins et al.
Keywords: endorphin; adult; African American; aged; article; breast cancer; cancer adjuvant therapy; Caucasian; clinical evaluation; controlled study; depression; early cancer; female; human; immune deficiency; major clinical study; mental stress; priority journal; protein blood level; psychophysiology; quality of life; randomized controlled trial; religion; social psychology; stress management; Tai Chi

Association between race and follow-up diagnostic care after a positive prostate cancer screening test in the Prostate, Lung, Colorectal, and Ovarian cancer screening trial - Barocas, D.A.; Grubb III, R.; Black, A.; Penson, D.F.; Fowke, J.H.; Andriole, G.; Crawford, E.D. (Cancer, 2013)
background Follow-through of a positive screening test is necessary to reap the potential benefits of cancer screening. Racial variation in follow-through diagnostic care may underlie a proportion of the known disparity in prostate cancer mortality. The authors used data from the screening arm of the Prostate, Lung, Colorectal, and Ovarian (PLCO) cancer screening trial to determine whether race is associated with the use of follow-up diagnostic testing after a positive initial screening evaluation. methods Men who had a prostate-specific antigen (PSA) level >4 ng/mL at any time during the study were included. The proportion of men who underwent follow-up evaluation with a repeat PSA, a prostate biopsy, or either test within 9 months was determined, and the authors tested for differences in follow-through according to race using mixed-effects multivariate models with a random effect for accrual site to account for clustering. Models were stratified according to age (<65 years and ≥65 years). results Among 6294 men who had a PSA elevation during the study period, 70% underwent a repeat PSA or prostate biopsy within 9 months. Non-Hispanic black men aged <65 years had 45% lower odds of undergoing a repeat PSA test or prostate biopsy compared with non-Hispanic white men (odds ratio, 0.55; 95% confidence interval, 0.37-0.82), whereas there was no racial difference in follow-through among older men. conclusions The current results suggest that limitations in access to care among non-Hispanic black men under the age of Medicare eligibility may underlie the paradoxically low use of follow-through diagnostic care among non-Hispanic black men in the United States. © 2013 American Cancer Society.
Keywords: prostate specific antigen; adult; aged; article; cancer diagnosis; cancer incidence; cancer mortality; cancer screening; colorectal cancer; controlled study; digital rectal examination; female; health care; health care access; human; human tissue; lung cancer; major clinical study; male; ovary cancer; priority journal; prostate biopsy; prostate cancer; race; race difference; screening test; United States

Gender differences in correlates of colorectal cancer screening among black medicare beneficiaries in Baltimore - Martinez, K.A.; Pollack, C.E.; Phelan, D.F.; Markakis, D.; Bone, L.; Shapiro, G.; Wenzel, J.; Howerton, M.; Johnson, L.; Garza, M.A.; Ford, J.G. (Cancer Epidemiology Biomarkers and Prevention, 2013)
Background: Previous research has shown colorectal cancer (CRC) screening disparities by gender. Little research has focused primarily on gender differences among older Black individuals, and reasons for existing gender differences remain poorly understood. Methods: Weused baseline data from the Cancer Prevention and Treatment Demonstration Screening Trial. Participants were recruited from November 2006 to March 2010. In-person interviews were used to assess selfreported CRC screening behavior. Up-to-date CRC screening was defined as self-reported colonoscopy or sigmoidoscopy in the past 10 years or fecal occult blood testing in the past year. We used multivariable logistic regression to examine the association between gender and self-reported screening, adjusting for covariates. The final model was stratified by gender to examine factors differentially associated with screening outcomes for males and females. Results: The final sample consisted of 1,552 female and 586 male Black Medicare beneficiaries in Baltimore, Maryland. Males were significantly less likely than females to report being up-to-date with screening (77.5% vs. 81.6%, P = 0.030), and this difference was significant in the fully adjusted model (OR: 0.72; 95% confidence interval, 0.52-0.99). The association between having a usual source of care and receipt of cancer screening was stronger among males compared with females. Conclusions: Although observed differences in CRC screening were small, several factors suggest that gender-specific approaches may be used to promote screening adherence among Black Medicare beneficiaries. Impact: Given disproportionate CRC mortality between White and Black Medicare beneficiaries, genderspecific interventions aimed at increasing CRC screening may be warranted among older Black patients. © 2013 American Association for Cancer Research.
Keywords: NCT00379743; aged; article; cancer screening; colorectal cancer; female; human; interview; major clinical study; male; medicare; occult blood test; outcome assessment; priority journal; self report; sex difference; sigmoidoscopy; smoking; United States

Development of a question prompt list as a communication intervention to reduce racial disparities in cancer treatment. - Eggly, S.; Tkatch, R.; Penner, L.A.; Mabunda, L.; Hudson, J.; Chapman, R.; Griggs, J.J.; Brown, R.; Albrecht, T. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2013)
Racial disparities have been found in the use of chemotherapy as cancer treatment. These disparities may be, in part, due to well-documented differences in the quality of communication during clinical interactions with oncologists and Black versus White patients. In this study using a community-based participatory research approach, academic researchers, community members, and oncologists formed a partnership to develop a communication intervention to address racial disparities in cancer care. Partners developed a question prompt list (QPL), a simple tool that can be used to improve communication, and thus treatment, during clinical interactions in which oncologists and Black patients discuss chemotherapy. Partners endorsed the use of a QPL, provided specific suggestions for content and format, conducted and analyzed qualitative interviews with Black patients receiving chemotherapy, and approved the final version. The feasibility and effectiveness of the QPL that resulted from this research process are currently under evaluation in a separate study.
Keywords: adjuvant chemotherapy; adjuvant therapy; adult; African American; aged; article; breast tumor; colon tumor; doctor patient relationship; ethnology; female; health care disparity; human; interpersonal communication; male; middle aged; neoplasm; participatory research; patient education; patient participation; patient satisfaction; psychologic test; psychological aspect; questionnaire; rectum tumor

Development of a question prompt list as a communication intervention to reduce racial disparities in cancer treatment - Eggly, S.; Tkatch, R.; Penner, L.A.; Mabunda, L.; Hudson, J.; Chapman, R.; Griggs, J.J.; Brown, R.; Albrecht, T. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2013)
Racial disparities have been found in the use of chemotherapy as cancer treatment. These disparities may be, in part, due to well-documented differences in the quality of communication during clinical interactions with oncologists and Black versus White patients. In this study using a community-based participatory research approach, academic researchers, community members, and oncologists formed a partnership to develop a communication intervention to address racial disparities in cancer care. Partners developed a question prompt list (QPL), a simple tool that can be used to improve communication, and thus treatment, during clinical interactions in which oncologists and Black patients discuss chemotherapy. Partners endorsed the use of a QPL, provided specific suggestions for content and format, conducted and analyzed qualitative interviews with Black patients receiving chemotherapy, and approved the final version. The feasibility and effectiveness of the QPL that resulted from this research process are currently under evaluation in a separate study.
Keywords: adjuvant chemotherapy; adjuvant therapy; adult; African American; aged; breast tumor; colon tumor; doctor patient relationship; ethnology; female; health care disparity; human; interpersonal communication; male; middle aged; neoplasm; participatory research; patient education; patient participation; patient satisfaction; psychologic test; psychology; questionnaire; rectum tumor

Relationship of early-onset baldness to prostate cancer in african-american men - Zeigler-Johnson, C.; Morales, K.H.; Spangler, E.; Chang, B.-L.; Rebbeck, T.R. (Cancer Epidemiology Biomarkers and Prevention, 2013)
Background: Early-onset baldness has been linked to prostate cancer; however, little is known about this relationship in AfricanAmericans who are at elevated prostate cancer risk. Methods: We recruited 219 African-American controls and 318 African-American prostate cancer cases. We determined age-stratified associations of baldness with prostate cancer occurrence and severity defined by high stage (T3/T4) or high grade (Gleason 7+.) Associations of androgen metabolism genotypes (CYP3A4, CYP3A5, CYP3A43, AR-CAG, SRD5A2 A49T, and SRD5A2 V89L), family history, alcohol intake, and smoking were examined by baldness status and age group by using multivariable logistic regression models. Results: Baldness was associated with odds of prostate cancer [OR 1.69; 95% confidence interval (CI), 1.05- 2.74]. Frontal baldness was associated with high-stage (OR 2.61; 95% CI, 1.10-6.18) and high-grade (OR 2.20; 95% CI, 1.05-4.61) tumors. Formendiagnosed less than the age of 60 years, frontal baldness was associated with high stage (OR 6.51; 95% CI, 2.11-20.06) and high grade (OR 4.23; 95% CI, 1.47-12.14). We also observed a suggestion of an interaction among smoking, median age, and any baldness (P 0.02). Conclusions: We observed significant associations between early-onset baldness and prostate cancer in African-American men. Interactions with age and smoking were suggested in these associations. Studies are needed to investigate the mechanisms influencing the relationship between baldness and prostate cancer in African-American men. Impact: African-American men present with unique risk factors including baldness patterns that may contribute to prostate cancer disparities. © 2013 American Association for Cancer Research.
Keywords: androgen; cytochrome P450 3A5; steroid 5alpha reductase 2; adult; African American; aged; alcohol consumption; alopecia; androgen metabolism; article; cancer grading; cancer risk; cancer staging; controlled study; disease severity; early onset baldness; family history; genotype; Gleason score; human; major clinical study; male; men's health; onset age; priority journal; prostate cancer; smoking

National surgical adjuvant breast and bowel project study of tamoxifen and raloxifene trial: Advancing the science of recruitment and breast cancer risk assessment in minority communities - McCaskill-Stevens, W.; Wilson, J.W.; Cook, E.D.; Edwards, C.L.; Gibson, R.V.; McElwain, D.L.; Figueroa-Moseley, C.D.; Paskett, E.D.; Roberson, N.L.; Wickerham, D.L.; Wolmark, N. (Clinical Trials, 2013)
Background One of the first chemoprevention trials conducted in the western hemisphere, the National Surgical Adjuvant Breast and Bowel Project's (NSABP) Breast Cancer Prevention Trial (BCPT), demonstrated the need to evaluate all aspects of recruitment in real time and to implement strategies to enroll racial and ethnic minority women. Purpose The purpose of this report is to review various patient recruitment efforts the NSABP developed to enhance the participation of racial and ethnic minority women in the Study of Tamoxifen and Raloxifene (STAR) trial and to describe the role that the recruitment process played in the implementation and understanding of breast cancer risk assessment in minority communities. Methods The NSABP STAR trial was a randomized, double-blinded study comparing the use of tamoxifen 20 mg/day to raloxifene 60 mg/day, for a 5-year period, to reduce the risk of developing invasive breast cancer. Eligible postmenopausal women were required to have a 5-year predicted breast cancer risk of 1.66% based on the modified Gail Model. For the current report, eligibility and enrollment data were tabulated by race/ethnicity for women who submitted STAR risk assessment forms (RAFs). Results A total of 184,460 RAFs were received, 145,550 (78.9%) from white women and 38,910 (21.1%) from minority women. Of the latter group, 21,444 (11.6%) were from African Americans/blacks, 7913 (4.5%) from Hispanics/Latinas, and 9553 (5.2%) from other racial or ethnic groups. The percentages of risk-eligible women among African Americans, Hispanics/Latinas, others, and whites were 14.2%, 23.3%, 13.7%, and 57.4%, respectively. Programs targeting minority enrollment submitted large numbers of RAFs, but the eligibility rates of the women referred from those groups tended to be lower than the rates among women referred outside of those programs. The average number of completed risk assessments increased among minority women over the course of the recruitment period compared to those from whites. Limitations We have not addressed all identified barriers to the recruitment of minorities in clinical research. Our risk assessments and recruitment results do not reflect the modified Gail Model for African Americans. Conclusions Recruitment strategies used in STAR for racial and ethnic minorities contributed to doubling the minority enrollment compared to that in the BCPT and increased the awareness of breast cancer risk assessment in minority communities. Incorporation of new information into models to improve the risk estimation of diverse populations should prove beneficial. © The Author(s) 2013.
Keywords: NCT00003906; raloxifene; tamoxifen; African American; article; breast cancer; cancer prevention; cancer risk; Caucasian; drug efficacy; ethnic group; ethnicity; female; Hispanic; human; major clinical study; outcome assessment; patient selection; postmenopause; priority journal; race; randomized controlled trial (topic); risk assessment; treatment duration

Clinicopathologic features and determinants of Gleason score of prostate cancer in Ghanaian men - Yarney, J.; Vanderpuye, V.; Mensah, J. (Urologic Oncology: Seminars and Original Investigations, 2013)
Objective: Prostate cancer is reported to be more aggressive in Blacks. We studied the clinicopathologic features of prostate cancer in Ghana, in order to determine the factors responsible for them and to find out if there is any relationship between them. Method: Patients referred with a biopsy proven diagnosis of carcinoma of the prostate to the Cancer Center of Korle Bu Teaching Hospital, Accra, Ghana, from 2003 to 2007 were studied. Information with respect to age at diagnosis, presenting symptoms, initial PSA (iPSA), Gleason score, and disease extent were studied. Age was partitioned into 50-65 and >65 years, Gleason score into 2-6, 7, and 8-10, iPSA into 4-20 ng/ml and >20, and disease extent into T1, T2, vs. T3, T4, M1, and the relationship between them was determined. Various presenting symptoms were described. Known risk factors and screening in a context of high grade disease is discussed. Results: A total of 170 patients were studied. Mean age was 65.4 years. Majority of patients (73.7%) presented with an iPSA > 20 ng/ml, whilst 22 (14.1%) had PSA < 10 ng/ml. Gleason score ≥ 7 was found in 95 (56%) of patients. Asymptomatic patients constituted 24.0%, the rest had bone pain (22.6%), urinary (50.4%), and neurologic symptoms (3.0%).There was a statistically significant relationship between age and Gleason score (. P = 0.049), PSA and Gleason score (. P = 0.0001), and between extent of disease and Gleason score (. P = 0.0002). High fat diet and low intake of fruits and vegetables are probable risk factors in Ghana. Conclusion: Majority of patients present with symptomatic disease at a relatively older age. These patients tend to have high Gleason score partly attributable to advanced disease, age, PSA at the time of diagnosis, and race. Screening with PSA should be recommended and individualized in this group of patients in order to allow diagnosis of less aggressive disease until better screening tools are identified. © 2013 Elsevier Inc.
Keywords: prostate specific antigen; adult; age distribution; aged; article; bone pain; cancer center; cancer patient; chronic inflammation; controlled study; fruit; Ghana; Gleason score; human; human tissue; lipid diet; major clinical study; male; neurologic disease; priority journal; prostate cancer; randomized controlled trial; risk factor; sexually transmitted disease; urine retention; vegetable

Are race-specific ERCC1 haplotypes in melanoma cases versus controls related to the predictive and prognostic value of ERCC1 N118N? - Gao, R.; Reece, K.M.; Sissung, T.; Fu, S.H.; Venzon, D.J.; Reed, E.; Spencer, S.D.; Price, D.K.; Figg, W.D. (BMJ Open, 2013)
Objectives: Although it does not alter the ERCC1 phenotype, the ERCC1 500C>T (rs11615) polymorphism has undergone a myriad of investigations into its role as a marker for nucleotide excision repair (NER) function in different races, diseases and treatment outcomes. The goal of our study was to test the hypothesis that 500C>T is in linkage disequilibrium (LD) with causative alleles, and that these haplotypes are more frequent in Caucasians with melanoma than in healthy Caucasians or African Americans. Design: In this case-control study, we selected racespecific ERCC1 single-nucleotide polymorphism (SNPs), conducted LD analysis with ERCC1 500C>T and compared the frequency of ERCC1 diplotypes in Caucasians with melanoma (n=165), healthy Caucasians (n=150) and healthy African Americans (n=159). The haplotype was further studied using a fusion gene containing multiple ERCC1 SNPs. Setting: Large cancer institute in the USA. Participants: A total of 165 Caucasian melanoma patients, 159 healthy Caucasian controls and 159 African American healthy controls. Men and women were enrolled in the clinical trial; however, since the screening trial included prostate cancer screening in addition to screening for other cancers, only male controls were available. Outcome measures: The outcome measures were melanoma risk in Caucasians, and LD between ERCC1 SNP, N118N and other race-specific allelic variants. Results: When compared to ERCC1 500C>T alone, a race-specific three-SNP variant haplotype in ERCC1 (comprised of rs11615, rs3212950 and rs3212948) was even more frequent in Caucasians with melanoma than in healthy Caucasians (p=0.0034) or African Americans (p<0.0001). A plasmid containing the variant haplotype was not differentially expressed. Conclusions: We demonstrate that ERCC1 500C>T participates in a previously characterised cancer-risk haplotype found more frequently in Caucasians, while LD is weak in African Americans; this haplotype appears to also be related to melanoma. It is therefore likely that ERCC1 500C>T is only a valid NER, disease or treatment outcome marker in Caucasians.
Keywords: excision repair cross complementing protein 1; African American; amino acid substitution; article; cancer prognosis; cancer risk; cancer screening; case control study; Caucasian; controlled study; fusion gene; gene expression; gene frequency; gene linkage disequilibrium; genetic analysis; genetic risk; genetic screening; genetic variability; haplotype; human; major clinical study; male; melanoma; outcome assessment; plasmid; predictive value; prostate cancer; race difference; single nucleotide polymorphism; United States

Kin KeeperSM: Design and baseline characteristics of a community-based randomized controlled trial promoting cancer screening in Black, Latina, and Arab women - Williams, K.P.; Roman, L.; Meghea, C.I.; Penner, L.; Hammad, A.; Gardiner, J. (Contemporary Clinical Trials, 2013)
Background: Although breast and cervical cancer deaths have declined due to early screening, detection, and more effective treatment, racial and ethnic disparities persist. This paper describes the study design and baseline characteristics of a randomized controlled trial (RCT) evaluating the effectiveness of the Kin KeeperSM Cancer Prevention Intervention, a family-focused educational intervention for underserved women applied in a community-based setting to promote health literacy and screening adherence to address cancer disparities. Methods: Female public health community health workers (CHWs) were trained to administer the intervention. They recruited female clients from their public health program caseload and asked each to assemble two to four adult female family members for the breast and cervical cancer home-based education sessions the CHWs would deliver in English, Spanish or Arabic. We randomized the clients into the kin keeper group (treatment) or the participant client group (control). Results: Complete data were obtained on 514 Black, Latina, and Arab women. Close to half were unemployed and had yearly family income below $20,000. Thirty-four percent had no medical insurance, and 21% had diabetes. Almost 40% had no mammography in the last year. Treatment and control groups were similar on most sociodemographics but showed differences in breast and cervical screening history. Conclusions: This innovative study demonstrates the implementation of an RCT using community-based participatory research, while delivering cancer prevention education across woman's life span with women not connected to the health care system. © 2012 Elsevier Inc.
Keywords: adult; aged; Arab; article; cancer screening; controlled study; educational status; employment status; ethnicity; female; health education; health promotion; human; major clinical study; medical history; Black person; Papanicolaou test; randomized controlled trial; study design; uterine cervix cancer

Racial/ethnic differences in use and duration of adjuvant hormonal therapy for breast cancer in the women's health initiative - Livaudais, J.C.; LaCroix, A.; Chlebowski, R.T.; Li, C.I.; Habel, L.A.; Simon, M.S.; Thompson, B.; Erwin, D.O.; Hubbell, F.A.; Coronado, G.D. (Cancer Epidemiology Biomarkers and Prevention, 2013)
Background: Five-year breast cancer survival rates are lower among Hispanic and African-American women than among Non-Hispanic White women. Differences in breast cancer treatment likely play a role. Adjuvant hormonal therapies increase overall survival among women with hormone receptor-positive breast cancer. Methods: We examined racial/ethnic differences in use and duration of adjuvant hormonal therapy among 3,588 postmenopausal women enrolled in the Women's Health Initiative (WHI) Extension Study. Women diagnosed with hormone receptor-positive localized or regional stage breast cancer after study enrollment were surveyed between September 2009 and August 2010 and asked to recall prior use and duration of adjuvant hormonal breast cancer therapy. ORs comparing self-reported use and duration with race/ethnicity (Hispanic, African-American, Asian/Pacific Islander vs. Non-Hispanic White) were estimated using multivariableadjusted logistic regression. Results: Of the 3,588 women diagnosed from 1994 to 2009; 3,039 (85%) reported any use of adjuvant hormonal therapy, and 67% of women reporting ever-use who were diagnosed before 2005 reported using adjuvant hormonal therapy for the optimal duration of 5 years or more. In adjusted analysis, no statistically significant differences in use or duration by race/ethnicity were observed. Conclusions: This study did not find significant differences in use or duration of use of adjuvant hormonal therapy by race/ethnicity. Impact: Findings should be confirmed in other population-based samples, and potential reasons for discontinuation of therapy across all racial/ethnic groups should be explored. © 2013 American Association for Cancer Research.
Keywords: anastrozole; exemestane; letrozole; tamoxifen; toremifene; adult; aged; article; body mass; breast cancer; cancer adjuvant therapy; cancer diagnosis; cancer epidemiology; cancer grading; cancer hormone therapy; cancer size; cancer staging; cancer survival; drug use; ethnic difference; female; follow up; health insurance; histology; human; major clinical study; observational study; postmenopause; priority journal; questionnaire; survival rate; treatment duration; women's health

Establishing a minority-based community clinical oncology program: The University of Medicine and Dentistry of New Jersey, New Jersey Medical School-University Hospital Cancer Center experience - Wieder, R.; Teal, R.; Saunders, T.; Weiner, B.J. (Journal of Oncology Practice, 2013)
The Minority-Based Community Clinical Oncology Program (MB-CCOP) at University of Medicine and Dentistry of New Jersey, New Jersey Medical School-University Hospital Cancer Center was established to serve an unmet need in a medically, educationally, and socioeconomically underserved community of primarily African American and Latino patients in Newark and Essex County, New Jersey. The MB-CCOP was built on an existing infrastructure of multidisciplinary teams of cancer specialists who collaborated in patient care and an existing clinical research program, which included multilingual staff and a breast cancer navigator. This article highlights some of the unique opportunities and challenges involved in the startup of an MB-CCOP specifically relevant to an academic setting. We present a guide to the necessary infrastructure and institutional support that must be in place before considering such a program and some of the steps an institution can take to overcome barriers preventing successful enrollment of patients onto clinical trials. Copyright © 2012 by American Society of Clinical Oncology.
Keywords: African American; article; breast cancer; cancer center; clinical research; clinical trial (topic); community program; cooperation; health program; Hispanic; human; medical school; minority based community clinical oncology program; patient care; practice guideline; United States; university hospital

Short- and long-term risk of colorectal adenoma recurrence among whites and blacks - Laiyemo, A.O.; Doubeni, C.; Brim, H.; Ashktorab, H.; Schoen, R.E.; Gupta, S.; Charabaty, A.; Lanza, E.; Smoot, D.T.; Platz, E.; Cross, A.J. (Gastrointestinal Endoscopy, 2013)
Background: It is unclear whether the higher burden from colorectal cancer among blacks is due to an increased biological susceptibility. Objective: To determine whether non-Hispanic blacks (blacks) have a higher risk of adenoma recurrence than non-Hispanic whites (whites) after removal of colorectal adenoma. Design: Secondary analysis of the Polyp Prevention Trial (PPT) data. Setting: United States. Patients: Patients were 1668 self-identified whites and 153 blacks who completed the 4-year trial. Of these, 688 whites and 55 blacks enrolled in a posttrial, passive Polyp Prevention Trial Continued Follow-up Study (PPT-CFS) and underwent another colonoscopy. Main Outcome Measurements: Recurrence and location of the adenoma and advanced adenoma by race-ethnicity during PPT and cumulative recurrence over a mean follow-up of 8.3 years (range, 4.9-12.4 years) among PPT-CFS enrollees. Results: Blacks had similar risk of recurrence of adenoma (39.2% vs 39.4%; incidence risk ratio [RR] =.98; 95% CI,.80-1.20) and advanced adenoma (8.5% vs 6.4%; RR = 1.18; 95% CI,.68-2.05) as whites at the end of PPT. Recurrence risk did not differ by colon subsite. Among PPT-CFS enrollees, the cumulative recurrence rate over a maximal follow-up period of 12 years was similar for blacks and whites for adenoma (67.3% vs 67.0%; RR = 1.01; 95% CI,.84-1.21) and advanced adenoma (14.5% vs 16.9%; RR = 1.03; 95% CI,.60-1.79). Limitation: There were few blacks in the long-term follow-up study. Conclusions: Adenoma and advanced adenoma recurrence did not differ by race. Our study does not support more frequent surveillance colonoscopies for blacks with a personal history of adenoma as an intervention to reduce colorectal cancer disparity. © 2013 American Society for Gastrointestinal Endoscopy.
Keywords: adult; article; Caucasian; colonoscopy; colorectal adenoma; controlled study; ethnicity; female; follow up; health disparity; human; major clinical study; male; medical history; Black person; priority journal; race difference; recurrence risk; risk assessment; tumor localization; United States

A randomized, double-blind, placebo-controlled study of oral coenzyme Q10 to relieve self-reported treatment-related fatigue in newly diagnosed patients with breast cancer - Lesser, G.J.; Case, D.; Stark, N.; Williford, S.; Giguere, J.; Astrid Garino, L.; Naughton, M.J.; Vitolins, M.Z.; Lively, M.O.; Shaw, E.G. (Journal of Supportive Oncology, 2013)
Background: Coenzyme Q10 (CoQ10) is a common antioxidant supplement with known cardioprotective effects and potential anticancer benefits. Objectives We performed a randomized, double-blind, placebo-controlled study of oral CoQ10 in female breast cancer patients with the primary objective of determining CoQ10's effects on self-reported fatigue, depression, and quality of life (QOL). Methods: Eligible women with newly diagnosed breast cancer and planned adjuvant chemotherapy were randomized to oral supplements of 300 mg CoQ10 or placebo, each combined with 300 IU vitamin E, divided into 3 daily doses. Treatment was continued for 24 weeks. Blood tests, QOL measures, and levels of plasma CoQ10 and vitamin E were obtained at baseline and at 8, 16, and 24 weeks. Mixed-effects models were used to assess treatment differences in outcomes over time. Results: Between September 2004 and March 2009, 236 women were enrolled. Treatment arms were well balanced with respect to age (range, 28-85 years), pathologic stage (stage 0, 91%; stage I, 8%; stage II, 1%), ethnicity (white, 87%; black, 11%; Hispanic, 2%), and planned therapy. Baseline CoQ10 levels in the CoQ10 and placebo arms were 0.70 and 0.73 μg/mL, respectively; the 24-week CoQ10 levels were 1.83 and 0.79 μg/mL, respectively. There were no significant differences between the CoQ10 and placebo arms at 24 weeks for scores on the Profile of Mood States-Fatigue questionnaire (least squares means, 7.08 vs 8.24, P = .257), the Functional Assessment of Chronic Illness Therapy-Fatigue tool (37.6 vs 37.6, P = .965), the Functional Assessment of Cancer Therapy-Breast Cancer instrument (111.9 vs 110.4, P = .577), or the Center for Epidemiologic Studies-Depression scale (11.6 vs 12.3, P = .632). Conclusions: Supplementation with conventional doses of CoQ10 led to sustained increases in plasma CoQ10 levels but did not result in improved self-reported fatigue or QOL after 24 weeks of treatment.
Keywords: NCT00096356; alpha tocopherol; anthracycline; placebo; ubidecarenone; adult; aged; article; Black person; breast cancer; cancer chemotherapy; cancer fatigue; cancer radiotherapy; Caucasian; Center for Epidemiologic Studies Depression scale; controlled study; double blind procedure; drug blood level; female; Functional Assessment of Cancer Therapy Breast Cancer instrument; Functional Assessment of Chronic Illness Therapy Fatigue tool; Hispanic; human; limit of quantitation; major clinical study; Mood States Fatigue questionnaire; patient compliance; questionnaire; randomized controlled trial; self report; treatment duration; treatment outcome

Effect of socioeconomic status as measured by education level on survival in breast cancer clinical trials - Herndon, J.E.; Kornblith, A.B.; Holland, J.C.; Paskett, E.D. (Psycho-Oncology, 2013)
Objectives This paper aims to investigate the effect of socioeconomic status, as measured by education, on the survival of breast cancer patients treated on 10 studies conducted by the Cancer and Leukemia Group B. Methods Sociodemographic data, including education, were reported by the patient at trial enrollment. Cox proportional hazards model stratified by treatment arm/study was used to examine the effect of education on survival among patients with early stage and metastatic breast cancer, after adjustment for known prognostic factors. Results The patient population included 1020 patients with metastatic disease and 5146 patients with early stage disease. Among metastatic patients, factors associated with poorer survival in the final multivariable model included African American race, never married, negative estrogen receptor status, prior hormonal therapy, visceral involvement, and bone involvement. Among early stage patients, significant factors associated with poorer survival included African American race, separated/widowed, post/perimenopausal, negative/unknown estrogen receptor status, negative progesterone receptor status, >4 positive nodes, tumor diameter >2 cm, and education. Having not completed high school was associated with poorer survival among early stage patients. Among metastatic patients, non-African American women who lacked a high school degree had poorer survival than other non-African American women, and African American women who lacked a high school education had better survival than educated African American women. Conclusions Having less than a high school education is a risk factor for death among patients with early stage breast cancer who participated in a clinical trial, with its impact among metastatic patients being less clear. Post-trial survivorship plans need to focus on women with low social status, as measured by education. Copyright © 2011 John Wiley & Sons, Ltd.
Keywords: carmustine; cisplatin; cyclophosphamide; doxorubicin; estrogen receptor; fluorouracil; granulocyte colony stimulating factor; megestrol acetate; paclitaxel; progesterone receptor; tamoxifen; topotecan; trastuzumab; adult; African American; aged; article; bone marrow transplantation; bone metastasis; breast cancer; cancer hormone therapy; cancer mortality; cancer patient; cancer prognosis; cancer radiotherapy; cancer staging; cancer survival; drug megadose; educational status; female; human; major clinical study; postmenopause; risk factor; social status; tumor volume; visceral metastasis

Representativeness of participants in the cancer care outcomes research and surveillance consortium relative to the surveillance, epidemiology, and end results program - Catalano, P.J.; Ayanian, J.Z.; Weeks, J.C.; Kahn, K.L.; Landrum, M.B.; Zaslavsky, A.M.; Lee, J.; Pendergast, J.; Harrington, D.P. (Medical Care, 2013)
Background: The research goals of the Cancer Care Outcomes Research and Surveillance (CanCORS) Consortium are to determine how characteristics and beliefs of patients, providers, and health care organizations influence the treatments and outcomes of individuals with newly diagnosed lung and colorectal cancers. As CanCORS results will inform national policy, it is important to know how they generalize to the United States population with these cancers. Research Design: This study assessed the representativeness of the CanCORS cohort of 10,547 patients with lung cancer (LC) or colorectal cancer (CRC) enrolled between 2003 and 2005. We compared characteristics (sex, race, age, and disease stage) with the Surveillance, Epidemiology, and End Results (SEER) population of 234,464 patients with new onset of these cancers during the CanCORS recruitment period. Results: The CanCORS sample is well matched to the SEER Program for both cancers. In CanCORS, 41% LC/47% CRC were female versus 47% LC/49% CRC in SEER. African American, Hispanic, and Asian cases differed by no more than 5 percentage points between CanCORS and SEER. The SEER population is slightly older, with the percentage of patients older than 75 years 33.1% LC/37.3% CRC in SEER versus 26.9% LC/29.4% in CanCORS, and also has a slightly higher proportion of early stage patients. We also found that the CanCORS cohort was representative within specific SEER regions that map closely to CanCORS sites. Conclusions: This study demonstrates that the CanCORS Consortium was successful in enrolling a demographically representative sample within the CanCORS regions. © 2012 by Lippincott Williams & Wilkins.
Keywords: adult; African American; aged; article; Asian; Cancer Care Outcomes Research and Surveillance Consortium; cancer diagnosis; cancer patient; cancer registry; cancer research; cohort analysis; colorectal cancer; controlled study; demography; disease severity; female; groups by age; health program; health survey; Hispanic; human; lung cancer; major clinical study; male; medical record review; multicenter study; priority journal; race difference; risk factor; sex difference; United States

Cost analysis of a patient navigation system to increase screening colonoscopy adherence among urban minorities - Jandorf, L.; Stossel, L.M.; Cooperman, J.L.; Graff Zivin, J.; Ladabaum, U.; Hall, D.; Thélémaque, L.D.; Redd, W.; Itzkowitz, S.H. (Cancer, 2013)
Background: Patient navigation (PN) is being used increasingly to help patients complete screening colonoscopy (SC) to prevent colorectal cancer. At their large, urban academic medical center with an open-access endoscopy system, the authors previously demonstrated that PN programs produced a colonoscopy completion rate of 78.5% in a cohort of 503 patients (predominantly African Americans and Latinos with public health insurance). Very little is known about the direct costs of implementing PN programs. The objective of the current study was to perform a detailed cost analysis of PN programs at the authors' institution from an institutional perspective. Methods: In 2 randomized controlled trials, average-risk patients who were referred for SC by primary care providers were recruited for PN between May 2008 and May 2010. Patients were randomized to 1 of 4 PN groups. The cost of PN and net income to the institution were determined in a cost analysis. Results: Among 395 patients who completed colonoscopy, 53.4% underwent SC alone, 30.1% underwent colonoscopy with biopsy, and 16.5% underwent snare polypectomy. Accounting for the average contribution margins of each procedure type, the total revenue was 95,266.00. The total cost of PN was 14,027.30. Net income was 81,238.70. In a model sample of 1000 patients, net incomes for the institutional completion rate (approximately 80%), the historic PN program (approximately 65%), and the national average (approximately 50%) were compared. The current PN program generated additional net incomes of 35,035.50 and 44,956.00, respectively. Conclusions: PN among minority patients with mostly public health insurance generated additional income to the institution, mainly because of increased colonoscopy completion rates. Cancer 2013. © 2012 American Cancer Society.
Keywords: adult; aged; article; cancer screening; colon biopsy; colonoscopy; colorectal cancer; controlled study; cost benefit analysis; female; health care cost; health insurance; human; income; major clinical study; male; patient attitude; patient care; polypectomy; priority journal; randomized controlled trial; urban area

Surgical treatment of colon cancer in patients aged 80 years and older: Analysis of 31,574 patients in the SEER-Medicare database - Neuman, H.B.; O'Connor, E.S.; Weiss, J.; Loconte, N.K.; Greenblatt, D.Y.; Greenberg, C.C.; Smith, M.A. (Cancer, 2013)
Background: Age-related disparities in colon cancer treatment exist, with older patients being less likely to receive recommended therapy. However, to the authors' knowledge, few studies to date have focused on receipt of surgery. The objective of the current study was to describe patterns of surgery in patients aged ≥ 80 years with colon cancer and examine outcomes with and without colectomy. Methods: Medicare beneficiaries aged ≥ 80 years with colon cancer who were diagnosed between 1992 and 2005 were identified from the Surveillance, Epidemiology, and End Results-Medicare database. Multivariable logistic regression analysis was used to assess factors associated with nonoperative management. Kaplan-Meier survival analysis determined 1-year overall and colon cancer-specific survival. Results: Of 31,574 patients, 80% underwent colectomy. Approximately 46% were diagnosed during an urgent/emergent hospital admission, with decreased 1-year overall survival (70% vs 86% for patients diagnosed during an elective admission) noted among these individuals. Factors found to be most predictive of nonoperative management included older age, black race, more hospital admissions, use of home oxygen, use of a wheelchair, being frail, and having dementia. For both operative and nonoperative patients, the 1-year overall survival rate was lower than the colon cancer-specific survival rate (operative patients: 78% vs 89%; nonoperative patients: 58% vs 78%). Conclusions: The majority of older patients with colon cancer undergo surgery, with improved outcomes noted compared with nonoperative management. However, many patients who are not selected for surgery die of unrelated causes, reflecting good surgical selection. Patients undergoing surgery during an urgent/emergent admission have an increased short-term mortality risk. Because the earlier detection of colon cancer may increase the percentage of older patients undergoing elective surgery, the findings of the current study may have policy implications for colon cancer screening and suggest that age should not be the only factor driving cancer screening recommendations. Cancer 2013. © 2012 American Cancer Society.
Keywords: oxygen; age distribution; aged; article; cancer diagnosis; cancer mortality; cancer prognosis; cancer registry; cancer specific survival; cancer surgery; colon cancer; colon resection; controlled study; dementia; elective surgery; female; frail elderly; hospital admission; human; major clinical study; male; Black person; outcome assessment; overall survival; oxygen therapy; patient selection; priority journal; survival time; treatment outcome

A tailored prostate cancer education intervention for low-income African Americans: impact on knowledge and screening - Ukoli, F.A.; Patel, K.; Hargreaves, M.; Beard, K.; Moton, P.J.; Bragg, R.; Beech, D.; Davis, R. (Journal of health care for the poor and underserved, 2013)
African American men bear disproportionate burden of prostate cancer (PCa) that can be reduced by early detection. A 15-minute culturally appropriate PCa education intervention developed to communicate effective, relevant, and balanced PCa screening information to low-income African American men was evaluated in men 42 years and older who had not been screened in one year. Of 539 men enrolled, 392 (72.7%) completed the six-month follow-up. Mean age was 54.4±8.9, 34.7% had no high school diploma, and 65.3% earned less than $25,000 annually. Barriers to screening included health insurance (41.4%), discomfort of digital rectal exam (32.1%), and fear of cancer diagnosis (29.9%). Mean knowledge score of 21 points increased from 13.27±3.51 to 14.95±4.14 (p<.001), and prostate-specific antigen screening from 22.1% to 62.8%. Men without high school diploma recorded the lowest post-intervention PCa knowledge and screening rate (47.7%), suggestive of the need for more than a single education session. Annual physicals with free prostate examination can maintain the positive trend observed.
Keywords: adult; African American; aged; attitude to health; clinical trial; early diagnosis; education; health care delivery; human; male; middle aged; patient education; poverty; procedures; prostate tumor; psychology; statistics and numerical data; very elderly

A randomized controlled Alzheimer's disease prevention trial's evolution into an exposure trial: The preadvise trial - Kryscio, R.J.; Abner, E.L.; Schmitt, F.A.; Goodman, P.J.; Mendiondo, M.; Caban-Holt, A.; Dennis, B.C.; Mathews, M.; Klein, E.A.; Crowley, J.J. (Journal of Nutrition, Health and Aging, 2013)
Objectives: To summarize the ongoing Prevention of Alzheimer's Disease (AD) by Vitamin E and Selenium (PREADViSE) trial as an ancillary study to SELECT (a large prostate cancer prevention trial) and to present the blinded results of the first year as an exposure study. Design: PREADViSE was designed as a double blind randomized controlled trial (RCT). Setting: SELECT terminated after median of 5.5 years of exposure to supplements due to a futility analysis. Both trials then converted into an exposure study. Participants: In the randomized component PREADViSE enrolled 7,547 men age 62 or older (60 if African American). Once the trial terminated 4,246 of these men volunteered for the exposure study. Demographics were similar for both groups with exposure volunteers having baseline mean age 67.3 ± 5.2 years, 15.3 ± 2.4 years of education, 9.8% African Americans, and 22.0% reporting a family history of dementia. Intervention: In the RCT men were randomly assigned to either daily doses of 400 IU of vitamin E or placebo and 200 μg of selenium or placebo using a 2×2 factorial structure. Measurements: In the RCT, participants completed the Memory Impairment Screen (MIS), and if they failed, underwent a longer screening (based on an expanded Consortium to Establish a Registry in AD [CERAD] battery). CERAD failure resulted in visits to their clinician for medical examination with records of these examinations forwarded to the PREADViSE center for further review. In the exposure study, men are contacted by telephone and complete the telephone version of the memory impairment screen (MIS-T) screen. If they fail the MIS-T, a Modified Telephone Interview of Cognitive Status (TICS-M) exam is given. A failed TICS-M exam also leads to a visit to their clinician for an in-depth examination and forwarding of records for a centralized consensus diagnosis by expert clinicians. A subgroup of the men who pass the MIS-T also take the TICS-M exam for validation purposes. Results: While this ancillary trial was open to all 427 SELECT clinical sites, only 130 (30.0%) of the sites chose to participate in PREADViSE. Staff turnover at the sites presented challenges when training persons unfamiliar with cognitive testing procedures to conduct the memory screens. In the RCT few participants (1.6%) failed the MIS screen and among those who passed this screen a significant practice effect was encountered. In the exposure study 3,581 men were reached by phone in year 1, 15.7% could not be reached after 5 calls, and of those contacted 6.0% refused the screen even after consenting to the procedures at their clinical site. Most notable is that the failure rate for the MIS-T increased fourfold to 7.2%. Of the 257 men who took the TICS-M, 84.0% failed and were asked to contact their physicians for a more detailed memory assessment, and approximately half of these had some form of dementia or cognitive impairment. Several of these dementia cases are not AD. Conclusion: Partnering with SELECT led to an AD prevention trial conducted at a very reasonable cost by taking advantage of the experience and efficient clinical trial management found in a cancer cooperative group (Southwest Oncology Group or SWOG). Once unblinded, the RCT and exposure study data have the potential to yield new information on long term exposure to antioxidant supplements under controlled conditions. © 2013 Serdi and Springer-Verlag France.
Keywords: alpha tocopherol; placebo; selenium; adult; African American; aged; Alzheimer disease; article; cognition; cognitive defect; controlled study; drug exposure; family history; human; major clinical study; male; memory; memory disorder; priority journal; randomized controlled trial; teleconsultation; treatment outcome

Tetrabenazine for treatment of chorea associated with Huntington's disease and other potential indications - Jimenez-Shahed, J.; Jankovic, J. (Expert Opinion on Orphan Drugs, 2013)
Introduction: Tetrabenazine (TBZ) is a centrally acting, dopamine (DA) depleting drug that has been used for treatment of hyperkinetic movement disorders. It was not commercially available in the USA until 2008, when the Food and Drug Administration (FDA) approved TBZ for the management of chorea associated with Huntington's disease (HD) under an orphan drug designation. Areas covered: This article provides a brief overview of HD, and highlights key studies on pharmacodynamics, pharmacokinetics, clinical efficacy and safety of TBZ for treatment of HD chorea. Expert opinion: TBZ, the first FDA-approved therapy for HD, provides symptomatic relief of chorea but there is no evidence that it alters the natural course of HD through a disease-modifying effect. While sedation, insomnia, mood changes, parkinsonism and restlessness may occur, these adverse effects can be managed effectively with appropriate titration and monitoring. A black box warning against depression and suicidality warrants careful patient selection, close monitoring and judicious use of antidepressants. TBZ possesses a unique mechanism of action as a pre-synaptic DA depletor that offers possible advantages over DA receptor blocking drugs. TBZ has a strong potential for application in other hyperkinetic movement disorders, particularly tardive dyskinesia and Tourette syndrome, but randomized controlled clinical trials are lacking. © Informa UK, Ltd.
Keywords: amantadine; apomorphine; dopamine; fluoxetine; memantine; nabilone; orphan drug; paroxetine; placebo; pridopidine; quinidine; riluzole; tetrabenazine; akathisia; article; binding affinity; breast cancer; depression; drug binding; drug bioavailability; drug blood level; drug brain level; drug dose reduction; drug dose titration; drug efficacy; drug excretion; drug half life; drug indication; drug induced cancer; drug megadose; drug metabolism; drug safety; drug tolerability; drug withdrawal; emotional disorder; fatigue; Gilles de la Tourette syndrome; human; Huntington chorea; insomnia; long term care; maximum plasma concentration; mood change; motor dysfunction; nonhuman; parkinsonism; patient compliance; patient selection; phase 1 clinical trial (topic); phase 3 clinical trial (topic); prostatitis; quality of life; randomized controlled trial (topic); restlessness; sedation; side effect; somnolence; subarachnoid hemorrhage; suicidal ideation; suicide attempt; systematic review (topic); tardive dyskinesia; xenazine

A pilot randomized controlled trial of a commercial diet and exercise weight loss program in minority breast cancer survivors - Greenlee, H.A.; Crew, K.D.; Mata, J.M.; McKinley, P.S.; Rundle, A.G.; Zhang, W.; Liao, Y.; Tsai, W.Y.; Hershman, D.L. (Obesity, 2013)
Objective: Obesity is associated with poorer breast cancer outcomes and losing weight postdiagnosis may improve survival. As Hispanic and black women have poorer breast cancer prognosis than non-Hispanic whites diagnosed at similar age and stage, and have higher rates of obesity, effective weight loss strategies are needed. We piloted a randomized, waitlist-controlled, crossover study to examine the effects and feasibility of the commercial Curves weight loss program among Hispanic, African American and Afro- Caribbean breast cancer survivors. Design and Methods: Women with stage 0-IIIa breast cancer ≥6 months posttreatment, sedentary, and BMI ≥25 kg/m2 were randomized to the immediate arm (IA): 6 months of the Curves program followed by 6 months of observation; or the waitlist control arm (WCA): 6 months of observation followed by 6 months of the Curves program. The Curves program uses a 30-min exercise circuit and a highvegetable/low-fat/calorie-restricted diet. Results: A total of 42 women enrolled (79% Hispanic, 21% black), mean age 51 (range 32-69) and mean BMI 33.2(±5.9) kg/m2; 91% were retained at month 12. At month 6, women in the IA lost an average 3.3% (±3.5%) of body weight (range: 1.7% gain to 10.6% loss), as compared with 1.8% (62.9%) weight loss in the WCA (P = 0.04). At month 12, on average women in the IA regained some but not all of the weight lost during the first 6 months (P = 0.02). Conclusions: Minority breast cancer survivors were recruited and retained in a weight loss study. Six months of the Curves program resulted in moderate weight loss, but weight loss was not maintained postintervention. Future interventions should identify methods to increase uptake and maintenance of weight loss behaviors.
Keywords: C reactive protein; adult; African American; aged; article; body mass; body weight; breast cancer; caloric restriction; cancer recurrence; cancer staging; cancer survivor; clinical article; clinical observation; controlled study; crossover procedure; diet; dietary intake; exercise; female; Hispanic; human; low fat diet; male; physical activity; pilot study; randomized controlled trial; risk reduction; sitting; body weight loss

African American prostate cancer survivors' treatment decision-making and quality of life - Palmer, N.R.A.; Tooze, J.A.; Turner, A.R.; Xu, J.; Avis, N.E. (Patient Education and Counseling, 2013)
Objective: To examine African-American prostate cancer (PCa) survivors' involvement in treatment decision-making (TDM), and examine the association between TDM and quality of life (QOL), using secondary data. Methods: African-American PCa survivors (181) were recruited from the North Carolina Central Cancer Registry. Participants completed a cross-sectional survey that asked about their chosen cancer treatment, TDM factors, and PCa-specific QOL (using the Expanded Prostate Cancer Index Composite - EPIC). Multivariate analysis of covariance was conducted to determine the association between TDM and QOL, controlling for confounders. Results: Most men reported being active (44.2%) or collaborative (38.1%) in TDM, while 14.4% preferred a passive role. Adjusting for marital status, education and treatment, passive patients reported somewhat better QOL compared to active patients in the following QOL domains: urinary summary (p=0.04), urinary function (p=0.01), and urinary incontinence (p=0.03). Conclusion: Most African-American PCa survivors preferred to be, and were, actively or collaboratively involved in TDM. However, those who preferred a passive role reported better PCa-specific QOL for the urinary domain compared to others. Practice implications: It is important to assess patients' TDM preference. Patients' QOL may differ by their TDM role, such that active patients may be more bothered by treatment side effects than other patients. © 2012 Elsevier Ireland Ltd.
Keywords: adult; African American; aged; article; cancer survivor; Expanded Prostate Cancer Index Composite; human; major clinical study; male; medical decision making; patient decision making; patient participation; patient preference; priority journal; prostate cancer; quality of life; questionnaire; self report; United States

Implementation of culturally targeted patient navigation system for screening colonoscopy in a direct referral system. - Jandorf, L.; Cooperman, J.L.; Stossel, L.M.; Itzkowitz, S.; Thompson, H.S.; Villagra, C.; Thélémaque, L.D.; McGinn, T.; Winkel, G.; Valdimarsdottir, H.; Shelton, R.C.; Redd, W. (Health education research, 2013)
Low-income minorities often face system-based and personal barriers to screening colonoscopy (SC). Culturally targeted patient navigation (CTPN) programs employing professional navigators (Pro-PNs) or community-based peer navigators (Peer-PNs) can help overcome barriers but are not widely implemented. In East Harlem, NY, USA, where approximately half the residents participate in SC, 315 African American patients referred for SC at a primary care clinic with a Direct Endoscopic Referral System were recruited between May 2008 and May 2010. After medical clearance, 240 were randomized to receive CTPN delivered by a Pro-PN (n = 106) or Peer-PN (n = 134). Successful navigation was measured by SC adherence rate, patient satisfaction and navigator trust. Study enrollment was 91.4% with no significant differences in SC adherence rates between Pro-PN (80.0%) and Peer-PN (71.3%) (P = 0.178). Participants in both groups reported high levels of satisfaction and trust. These findings suggest that CTPN Pro-PN and Peer-PN programs are effective in this urban primary care setting. We detail how we recruited and trained navigators, how CTPN was implemented and provide a preliminary answer to our questions of the study aims: can peer navigators be as effective as professionals and what is the potential impact of patient navigation on screening adherence?
Keywords: African American; article; colonoscopy; colorectal tumor; controlled clinical trial; controlled study; cultural competence; human; mortality; organization and management; patient care; patient compliance; patient referral; patient satisfaction; peer group; poverty; program development; psychological aspect; randomized controlled trial; trust; United States

Efficacy to effectiveness transition of an Educational Program to Increase Colorectal Cancer Screening (EPICS): study protocol of a cluster randomized controlled trial - Smith, S.A.; Blumenthal, D.S. (Implementation science : IS, 2013)
BACKGROUND: African Americans have the highest incidence and mortality and are less likely than whites to have been screened for colorectal cancer (CRC). Many interventions have been shown to increase CRC screening in research settings, but few have been evaluated specifically for use in African-American communities in real world settings. This study aims to identify the most efficacious approach to disseminate an evidence-based intervention in promoting colorectal screening in African Americans and to identify the factors associated with its efficacy. METHODS/DESIGN: In this study, investigators will recruit 20 community coalitions and 7,200 African-Americans age 50 to 74 to test passive and active approaches to disseminating the Educational Program to Increase Colorectal Cancer Screening (EPICS); to measure the extent to which EPICS is accepted and the fidelity of implementation in various settings and to estimate the potential translatability and public health impact of EPICS. This four-arm cluster randomized trial compares the following implementation strategies: passive arms, (web access to facilitator training materials and toolkits without technical assistance (TA) and (web access, but with technical assistance (TA); active arms, (in-person access to facilitator training materials and toolkits without TA and (in-person access with TA). Primary outcome measures are the reach (the proportion of representative community coalitions and individuals participating) and efficacy (post-intervention changes in CRC screening rates). Secondary outcomes include adoption (percentage of community coalitions implementing the EPICS sessions) and implementation (quality and consistency of the intervention delivery). The extent to which community coalitions continue to implement EPICS post-implementation (maintenance) will also be measured. Cost-effectiveness analysis will be conducted. DISCUSSION: Implementing EPICS in partnership with community coalitions, we hypothesized, will result in more rapid adoption than traditional top-down approaches, and resulting changes in community CRC screening practices are more likely to be sustainable over time. With its national reach, this study has the potential to enhance our understanding of barriers and enablers to the uptake of educational programs aimed at eliminating cancer disparities. TRIAL REGISTRATION: http://www.ClinicalTrials.gov NCT01805622.
Keywords: ClinicalTrials.gov; African American; aged; cluster analysis; colorectal tumor; controlled study; early diagnosis; ethnology; female; health disparity; health promotion; human; male; middle aged; organization and management; patient education; procedures; randomized controlled trial; treatment outcome

Spiritually based intervention to increase colorectal cancer awareness among african americans: intermediate outcomes from a randomized trial. - Holt, C.L.; Scarinci, I.C.; Debnam, K.; McDavid, C.; Litaker, M.; McNeal, S.F.; Southward, V.; Lee, C.; Eloubeidi, M.; Crowther, M.; Bolland, J.; Martin, M.Y. (Journal of health communication, 2012)
Colorectal cancer screening, while effective for reducing mortality, remains underutilized particularly among underserved populations such as African Americans. The present study evaluated a spiritually based approach to increasing Health Belief Model-based pre-screening outcomes in a Community Health Advisor-led intervention conducted in African American churches. Sixteen urban churches were randomized to receive either the spiritually based intervention or a nonspiritual comparison of the same structure and core colorectal cancer content. Trained Community Health Advisors led a series of two educational sessions on colorectal cancer early detection. The educational sessions were delivered over a 1-month period. Participants (N = 316) completed a baseline survey at enrollment and a follow-up survey one month after the first session. Both interventions resulted in significant pre/post increases in knowledge, perceived benefits of screening, and decreases in perceived barriers to screening. Among women, the spiritually based intervention resulted in significantly greater increases in perceived benefits of screening relative to the nonspiritual comparison. This finding was marginal in the sample as a whole. In addition, perceived benefits to screening were associated with behavioral intention for screening. It is concluded that in this population, the spiritually based was generally as effective as the nonspiritual (secular) communication.
Keywords: African American; aged; article; attitude to health; clinical trial; colorectal tumor; controlled clinical trial; controlled study; education; ethnology; female; follow up; health care quality; health education; human; male; methodology; middle aged; psychological aspect; randomized controlled trial; religion; urban population

Predicting participation in and successful outcome of a penile rehabilitation programme using a phosphodiesterase type 5 inhibitor with a vacuum erection device after radical prostatectomy - Kimura, M.; Caso, J.R.; Bañez, L.L.; Koontz, B.F.; Gerber, L.; Senocak, C.; Donatucci, C.F.; Vujaskovic, Z.; Moul, J.W.; Polascik, T.J. (BJU International, 2012)
OBJECTIVES • To investigate baseline demographic and clinicopathological characteristics of men who participate in our penile rehabilitation programme after radical prostatectomy (RP). • To determine predictors for participation in rehabilitation, as well as successful rehabilitation outcome using multivariable logistic regression analyses. PATIENTS AND METHODS • We analysed data on 2345 consecutive patients who underwent RP between 2001 and 2009 in our institution. • The decision to participate in penile rehabilitation using phosphodiesterase type 5 inhibitor (PDE5i) with a vacuum erection device (VED) was based on the patient's choice after post-RP discussions. • Rehabilitation success was defined using the following criteria: (i) patients who continued the penile rehabilitation programme and did not switch treatment from PDE5i to other erectile aids, (ii) success was noted in men who had an Expanded Prostate Cancer Index Composite (EPIC) sexual function (SF) score of > 75% of the patient's baseline EPIC score, and (iii) patients who answered that they achieved adequate erections with a PDE5i. • Logistic regression analysis was used to identify factors associated with treatment participation and its success. RESULTS • Of 676 patients, 354 (53.2%) men participated in a penile rehabilitation programme. Among 329 rehabilitation participants with available data, 96 (29.2%) had treatment success. • In multivariable regression analysis, African-Americans (odds ratio [ OR ] 3.47, P < 0.001), and higher preoperative SF (OR 1.02, P < 0.001) were associated with participation in rehabilitation. • Higher preoperative PSA concentration (OR 0.50, P =0.004) and presence of positive surgical margins (OR 0.68, P =0.042) were found to be independent predictors for non-participation in the rehabilitation. • For rehabilitation outcomes, being older at surgery (OR 0.93, P =0.001) and adjuvant therapy (OR 0.34, P =0.047) had a negative association with successful outcome. • There was a trend in the relationship between primary surgeon and rehabilitation success (OR 1.05, P =0.053) CONCLUSIONS • Those patients who have risk factors, e.g. adverse prostate cancer features, need to be carefully counselled and encouraged to participate in the penile rehabilitation programme. • Clinicians could lead patients toward successful outcomes if appropriate surgical techniques and rehabilitation are provided. © 2012 THE AUTHORS.
Keywords: phosphodiesterase V inhibitor; prostate specific antigen; adjuvant therapy; adult; African American; age; article; clinical feature; controlled study; demography; human; major clinical study; male; outcome assessment; patient assessment; patient decision making; patient participation; penile rehabilitation program; penis erection; postoperative care; priority journal; prostate cancer; prostatectomy; protein blood level; rehabilitation care; scoring system; sexual function; urological therapeutic device; vacuum erection assistance device

Using incentives in surveys of cancer patients: Do "best practices" apply? - Vangeest, J.B.; Johnson, T.P. (Cancer Causes and Control, 2012)
Purpose: Surveys of cancer patients are an important means of collecting data necessary to improve cancer prevention and control. However, health surveys generally are characterized by declining response rates, with incentives often employed to encourage participation. While successful, magnitude of effect is partially dependent upon situational characteristics of respondents, including health status. Given the health challenges experienced by cancer patients, it is unclear to what extent incentives can improve survey participation. In this study, we examine the effectiveness of monetary and non-monetary incentives in improving response to cancer patient surveys. Methods: We reviewed the available experimental literature regarding efforts to improve response rates among cancer patients/survivors via incentives. Relevant studies were identified through searches of the MEDLINE, PubMed, and PsychINFO databases from 1975 to 2012. Seed sources (e.g., Cancer Causes & Control, Cancer Epidemiology, Biomarkers & Prevention, and BMC Medical Research Methodology) were also referenced extensively in order to establish a comprehensive set of studies. Results: Although limited, evidence does suggest that token incentives may be less effective for improving survey participation among cancer patients, relative to other population groups. These results are contrary to well-established evidence regarding the efficacy of incentives in improving survey participation generally. Potential reasons why incentives may be less effective in this population are explored. Conclusions: While more research is necessary, results suggest that survey research strategies targeting cancer patients be purposively designed in a manner that gives consideration to the distress associated with the condition, including selection of alternative strategies to improve response. © 2012 Springer Science+Business Media Dordrecht.
Keywords: adult; African American; aged; article; Asian; cancer patient; cancer research; cancer survivor; childhood cancer; colorectal cancer; cooperation; disease surveillance; economic aspect; ethnic difference; health survey; Hispanic; human; incentive; major clinical study; patient participation; population research; priority journal; race difference

Out-of-pocket expenses and treatment choice for men with prostate cancer - Jung, O.S.; Guzzo, T.; Lee, D.; Mehler, M.; Christodouleas, J.; Deville, C.; Hollis, G.; Shah, A.; Vapiwala, N.; Wein, A.; Pauly, M.; Bekelman, J.E. (Urology, 2012)
Objective: To describe the knowledge of, and attitudes toward, out-of-pocket expenses (OOPE) associated with prostate cancer treatment and the influence of OOPE on the treatment choices of patients with prostate cancer. Materials and Methods: We undertook a qualitative research study for which we recruited patients with clinically localized prostate cancer. Patients answered a series of open-ended questions during a semistructured interview and completed a questionnaire about the physician's role in discussing OOPE, the burden of OOPE, the effect of OOPE on treatment decisions, and previous knowledge of OOPE. Results: A total of 41 (26 white and 15 black) eligible patients were enrolled from the urology and radiation oncology practices of the University of Pennsylvania. Qualitative assessment revealed 5 major themes: (a) "my insurance takes care of it"; (b) "health is more important than cost"; (c) "I did not look into it"; (d) "I cannot afford it but would have chosen the same treatment"; and (e) "It is not my doctor's business." Most patients (38 of 41, 93%) reported that they would not have chosen a different treatment even if they had known the actual OOPE of their treatment. Patients who reported feeling burdened by OOPE were socioeconomically heterogeneous, and their treatment choices remained unaffected. Only 2 patients stated they knew "a lot" about the likely OOPE for different prostate cancer treatments before choosing their treatment. Conclusion: Among insured patients with prostate cancer treated at a large academic medical center, few had knowledge of OOPE before making treatment choices. © 2012 Elsevier Inc. All Rights Reserved.
Keywords: adult; aged; article; clinical article; clinical trial; cost; external beam radiotherapy; health; health care cost; human; male; out of pocket expense; priority journal; prospective study; prostate cancer; prostatectomy; qualitative research; questionnaire; semi structured interview

Patients' willingness to participate in a breast cancer biobank at screening mammogram - Lee, C.I.; Bassett, L.W.; Leng, M.; Maliski, S.L.; Pezeshki, B.B.; Wells, C.J.; Mangione, C.M.; Naeim, A. (Breast Cancer Research and Treatment, 2012)
To characterize patients' willingness to donate a biospecimen for future research as part of a breast cancer-related biobank involving a general screening population. We performed a prospective cross-sectional study of 4,217 women aged 21-89 years presenting to our facilities for screening mammogram between December 2010 and October 2011. This HIPAA-compliant study was approved by our institutional review board. We collected data on patients' interest in and actual donation of a biospecimen, motivators and barriers to donating, demographic information, and personal breast cancer risk factors. A multivariate logistic regression analysis was performed to identify patient-level characteristics associated with an increased likelihood to donate. Mean patient age was 57.8 years (SD 11.1 years). While 66.0 % (2,785/4,217) of patients were willing to donate blood or saliva during their visit, only 56.4 % (2,378/4,217) actually donated. Women with a college education (OR = 1.27, p = 0.003), older age (OR = 1.02, p < 0.001), previous breast biopsy (OR = 1.23, p = 0.012), family history of breast cancer (OR = 1.23, p = 0.004), or a comorbidity (OR = 1.22, p = 0.014) were more likely to donate. Asian-American women were significantly less likely to donate (OR = 0.74, p = 0.005). The major reason for donating was to help all future patients (42.3 %) and the major reason for declining donation was privacy concerns (22.3 %). A large proportion of women participating in a breast cancer screening registry are willing to donate blood or saliva to a biobank. Among minority participants, Asian-American women are less likely to donate and further qualitative research is required to identify novel active recruitment strategies to insure their involvement. © 2012 Springer Science+Business Media New York.
Keywords: adult; African American; aged; article; Asian American; attitude to health; biobank; blood donor; breast biopsy; breast cancer; cancer screening; Caucasian; cerebrovascular accident; cohort analysis; comorbidity; controlled study; cross-sectional study; diabetes mellitus; educational status; ethnicity; family history; female; health care facility; heart disease; Hispanic; human; human tissue; hypertension; kidney disease; liver disease; major clinical study; mammography; medical history; patient participation; priority journal; prospective study

Recruitment and retention strategies of African American and Latina American breast cancer survivors in a longitudinal psycho-oncology study - Ashing-Giwa, K.; Rosales, M. (Oncology Nursing Forum, 2012)
Keywords: adult; African American; aged; article; breast tumor; female; follow up; health survey; Hispanic; human; income; middle aged; patient; patient education; patient participation; patient selection; prospective study; psychological aspect; publication; quality of life; socioeconomics; survivor; telephone; United States

The prostate cancer intervention versus observation trial: VA/NCI/AHRQ cooperative studies program #407 (PIVOT): Design and baseline results of a randomized controlled trial comparing radical prostatectomy with watchful waiting for men with clinically localized prostate cancer - Wilt, T.J. (Journal of the National Cancer Institute - Monographs, 2012)
Prostate cancer is the most common noncutaneous malignancy and the second leading cause of cancer death in men. In the United States, 90% of men with prostate cancer are more than age 60 years, diagnosed by early detection with the prostate-specific antigen (PSA) blood test, and have disease believed confined to the prostate gland (clinically localized). Common treatments for clinically localized prostate cancer include watchful waiting (WW), surgery to remove the prostate gland (radical prostatectomy), external-beam radiation therapy and interstitial radiation therapy (brachytherapy), and androgen deprivation. Little is known about the relative effectiveness and harms of treatments because of the paucity of randomized controlled trials. The Department of Veterans Affairs/National Cancer Institute/Agency for Healthcare Research and Quality Cooperative Studies Program Study #407:Prostate Cancer Intervention Versus Observation Trial (PIVOT), initiated in 1994, is a multicenter randomized controlled trial comparing radical prostatectomy with WW in men with clinically localized prostate cancer. We describe the study rationale, design, recruitment methods, and baseline characteristics of PIVOT enrollees. We provide comparisons with eligible men declining enrollment and men participating in another recently reported randomized trial of radical prostatectomy vs WW conducted in Scandinavia. We screened 13 022 men with prostate cancer at 52 US medical centers for potential enrollment. From these, 5023 met initial age, comorbidity, and disease eligibility criteria, and a total of 731 men agreed to participate and were randomized. The mean age of enrollees was 67 years. Nearly one-third were African American. Approximately 85% reported that they were fully active. The median PSA was 7.8ng/mL (mean 10.2ng/mL). In three-fourths of men, the primary reason for biopsy leading to a diagnosis of prostate cancer was a PSA elevation or rise. Using previously developed tumor risk categorizations incorporating PSA levels, Gleason histologic grade, and tumor stage, it was found that approximately 40% had low-risk, 34% had medium-risk, and 21% had high-risk prostate cancer based on local histopathology. Comparison to our national sample of eligible men declining PIVOT participation as well as to men enrolled in the Scandinavian trial indicated that PIVOT enrollees are representative of men being diagnosed and treated in the United States and quite different from men in the Scandinavian trial. PIVOT enrolled an ethnically diverse population representative of men diagnosed with prostate cancer in the United States. Results will yield important information regarding the relative effectiveness and harms of surgery compared with WW for men with predominately PSA-detected clinically localized prostate cancer. Published by Oxford University Press 2012.
Keywords: prostate specific antigen; adult; African American; aged; article; cancer localization; cancer mortality; cancer patient; cancer risk; clinical observation; comorbidity; controlled study; diagnostic test accuracy study; disease severity; ethnic difference; Gleason score; health program; high risk patient; histopathology; human; laboratory test; major clinical study; male; multicenter study; patient selection; predictive value; priority journal; prostate biopsy; prostate cancer; prostatectomy; protein blood level; randomized controlled trial; risk assessment; risk factor; Scandinavia; United States; watchful waiting

Beliefs and attitudes about lung cancer screening among smokers - Jonnalagadda, S.; Bergamo, C.; Lin, J.J.; Lurslurchachai, L.; Diefenbach, M.; Smith, C.; Nelson, J.E.; Wisnivesky, J.P. (Lung Cancer, 2012)
The National Lung Screening Trial (NLST) recently reported that annual computed tomography (CT) screening is associated with decreased lung cancer mortality in high-risk smokers. Beliefs about lung cancer and screening, particularly across race and ethnicity, and their influence on CT screening utilization are largely unexamined. Our study recruited asymptomatic, high-risk smokers, 55-74 years of age from primary care clinics in an academic urban hospital. Guided by the self-regulation theory, we evaluated cognitive and affective beliefs about lung cancer. Intention to screen for lung cancer with a CT scan was assessed by self-report. We used univariate and logistic regression analyses to compare beliefs about screening and intention to screen among minority (Blacks and Hispanics) and non-minority participants. Overall, we enrolled 108 participants, of which 40% were Black and 34% were Hispanic; the mean age was 62.3 years, and median pack-years of smoking was 26. We found that intention to screen was similar among minorities and non-minorities (p= 0.19); however, Hispanics were less likely to report intention to screen if they had to pay for the test (p= 0.02). Fatalistic beliefs, fear of radiation exposure, and anxiety related to CT scans were significantly associated with decreased intention to screen (p< 0.05). Several differences were observed in minority versus non-minority participants' beliefs toward lung cancer and screening. In conclusion, we found that concerns about cost, which were particularly prominent among Hispanics, as well as fatalism and radiation exposure fears may constitute barriers to lung cancer screening. Lung cancer screening programs should address these factors to ensure broad participation, particularly among minorities. © 2012 Elsevier Ireland Ltd.
Keywords: adult; aged; anxiety; article; cancer screening; cigarette smoking; cognition; computer assisted tomography; conceptual framework; controlled study; cross-sectional study; educational status; ethnic difference; female; health care cost; high risk population; Hispanic; human; lung cancer; lung nodule; major clinical study; male; medical history; outpatient care; patient attitude; primary medical care; priority journal; race difference; radiation exposure; self report; thorax radiography; urban area

A randomized controlled Alzheimer's disease Prevention trial's evolution into an exposure trial: The Preadvise trial - Kryscio, R.J.; Abner, E.L.; Schmitt, F.A.; Goodman, P.J.; Mendiondo, M.; Caban-Holt, A.; Dennis, B.C.; Mathews, M.; Klein, E.A.; Crowley, J.J. (Journal of Nutrition, Health and Aging, 2012)
Objectives: To summarize the ongoing Prevention of Alzheimer's Disease (AD) by Vitamin E and Selenium (PREADViSE) trial as an ancillary study to SELECT (a large prostate cancer prevention trial) and to present the blinded results of the first year as an exposure study. Design: PREADViSE was designed as a double blind randomized controlled trial (RCT). Setting: SELECT terminated after median of 5.5 years of exposure to supplements due to a futility analysis. Both trials then converted into an exposure study. Participants: In the randomized component PREADViSE enrolled 7,547 men age 62 or older (60 if African American). Once the trial terminated 4,246 of these men volunteered for the exposure study. Demographics were similar for both groups with exposure volunteers having baseline mean age 67.3 ± 5.2 years, 15.3 ± 2.4 years of education, 9.8% African Americans, and 22.0% reporting a family history of dementia. Intervention: In the RCT men were randomly assigned to either daily doses of 400 IU of vitamin E or placebo and 200 μg of selenium or placebo using a 2x2 factorial structure. Measurements: In the RCT, participants completed the Memory Impairment Screen (MIS), and if they failed, underwent a longer screening (based on an expanded Consortium to Establish a Registry in AD [CERAD] battery). CERAD failure resulted in visits to their clinician for medical examination with records of these examinations forwarded to the PREADViSE center for further review. In the exposure study, men are contacted by telephone and complete the telephone version of the memory impairment screen (MIS-T) screen. If they fail the MIS-T, a Modified Telephone Interview of Cognitive Status (TICS-M) exam is given. A failed TICS-M exam also leads to a visit to their clinician for an in-depth examination and forwarding of records for a centralized consensus diagnosis by expert clinicians. A subgroup of the men who pass the MIS-T also take the TICS-M exam for validation purposes. Results: While this ancillary trial was open to all 427 SELECT clinical sites, only 130 (30.0%) of the sites chose to participate in PREADViSE. Staff turnover at the sites presented challenges when training persons unfamiliar with cognitive testing procedures to conduct the memory screens. In the RCT few participants (1.6%) failed the MIS screen and among those who passed this screen a significant practice effect was encountered. In the exposure study 3,581 men were reached by phone in year 1, 15.7% could not be reached after 5 calls, and of those contacted 6.0% refused the screen even after consenting to the procedures at their clinical site. Most notable is that the failure rate for the MIS-T increased fourfold to 7.2%. Of the 257 men who took the TICS-M, 84.0% failed and were asked to contact their physicians for a more detailed memory assessment, and approximately half of these had some form of dementia or cognitive impairment. Several of these dementia cases are not AD. Conclusion: Partnering with SELECT led to an AD prevention trial conducted at a very reasonable cost by taking advantage of the experience and efficient clinical trial management found in a cancer cooperative group (Southwest Oncology Group or SWOG). Once unblinded, the RCT and exposure study data have the potential to yield new information on long term exposure to antioxidant supplements under controlled conditions. © 2012 Serdi and Springer Verlag France.
Keywords: placebo; alpha tocopherol; selenium; antioxidant; telephone; screening; prophylaxis; prevention study; exposure; Alzheimer disease; prevention; human; male; dementia; tic; memory disorder; African American; procedures; memory; examination; randomized controlled trial; physician; prostate cancer; diagnosis; cancer prevention; teleconsultation; medical examination; register; consensus; turnover rate; family history; education; volunteer; cognitive defect; long term exposure; oncology; neoplasm; clinical trial; France

Coffee consumption and prostate cancer aggressiveness among African and caucasian americans in a population-based study - Arab, L.; Su, L.J.; Steck, S.E.; Ang, A.; Fontham, E.T.H.; Bensen, J.T.; Mohler, J.L. (Nutrition and Cancer, 2012)
This study evaluated the relationship between caffeinated and decaffeinated coffee and prostate cancer (CaP) aggressiveness using data from a population-based incident CaP study within the North Carolina-Louisiana Prostate Cancer Project (PCaP). Classification of CaP aggressiveness at diagnosis was based on clinical criteria for 1,049 African-American (AA) and 1,083 Caucasian-American (CA) research subjects. Coffee consumption was measured using a modified NCI Dietary History Questionnaire. No significant associations were found between CaP aggressiveness and consumption of either caffeinated or decaffeinated coffee. The OR for high aggressive CaP among consumers of more than 4 cups per day was 0.92 (95%CI = 0.61, 1.39), compared to non-coffee-drinkers. Results stratified by race found no significant associations and no noticeable trends in either AAs (P for trend = 0. 62) or CAs (P for trend = 0.42). In contrast to a recent report on a select population that has less complete information on CaP aggressiveness suggesting that coffee prevents aggressive CaP, this rapid case ascertainment population-based study, in a biracial population with differing risks of CaP did not demonstrate a protective relationship between high coffee consumption and risk of high aggressive CaP. Copyright © 2012, Taylor & Francis Group, LLC.
Keywords: adult; African American; aged; article; coffee; consumer; disease association; disease course; European American; food intake; human; major clinical study; male; prostate cancer; questionnaire; research subject; risk factor

Black box warnings: What do they mean to pharmacists and patients - Martin, C.M.; Borgelt, L. (Consultant Pharmacist, 2012)
The Food and Drug Administration (FDA), which oversees and regulates prescription and over-the-counter medications, issues several types of advisories about medication safety. Pharmacists and other practitioners are responsible for carefully evaluating these communications and assessing the potential risk for their individual patients. Focusing on black box warnings - the most serious type of warning from FDA - this article discusses a strategy for evaluating and implementing FDA's safety warnings to provide optimal patient care. © 2012 American Society of Consultant Pharmacists, Inc. All rights reserved.
Keywords: aminoglycoside; amiodarone; antianemic agent; antidepressant agent; atypical antipsychotic agent; beta adrenergic receptor blocking agent; beta adrenergic receptor stimulating agent; carbamazepine; cilostazol; clopidogrel; clozapine; disopyramide; dronedarone; estrogen derivative; etanercept; ketoconazole; lamotrigine; long acting beta agonist; loop diuretic agent; low molecular weight heparin; metformin; methadone; methotrexate; methylphenidate; metronidazole; midodrine; modafinil; paracetamol; quinolone derivative; unclassified drug; unindexed drug; absence of side effects; agranulocytosis; article; black box warning; blood dyscrasia; bone marrow suppression; bone necrosis; cardiovascular disease; cerebrovascular disease; clinical evaluation; clinical protocol; dementia; drug approval; drug dependence; drug efficacy; drug fatality; drug labeling; drug manufacture; drug packaging; drug safety; drug withdrawal; electrolyte disturbance; endometrium carcinoma; Food and Drug Administration; general practitioner; atrial fibrillation; heart failure; hematoma; human; hypotension; infection; lactic acidosis; liver dysfunction; liver toxicity; lung toxicity; lymphoma; medicine; medicolegal aspect; mental disease; muscle weakness; myasthenia gravis; neoplasm; nephrotoxicity; nerve paralysis; neurotoxicity; nonhuman; orthostatic hypotension; patient care; patient selection; pharmacist; pneumonia; QT prolongation; respiration depression; risk assessment; seizure; skin manifestation; Stevens Johnson syndrome; suicide attempt; tachycardia; tendon inflammation; tendon inflammation; tendon rupture; tuberculosis; tumor lysis syndrome

Randomized double-blind phase 2 trial of 3 doses of TAS-108 in patients with advanced or metastatic postmenopausal breast cancer - Buzdar, A.; Vogel, C.; Schwartzberg, L.; Garin, A.; Perez, A.; Ingle, J.; Houghton, M.; Zergebel, C.; Kimball, B. (Cancer, 2012)
BACKGROUND: The objective of this study was to evaluate 3 different doses of (7α)-21-(4-[(diethylamino)methyl]-2 methoxyphenoxy)-7 methyl-19 norpregna-1,3,5(10)-trien-3-ol 2-hydroxy-1,2,3-propanetricarboxylate (TAS-108) in patients with recurrent, hormone-responsive breast cancer. METHODS: In this randomized, double-blind, multicenter study, TAS-108 was administered daily at a dose of 40 mg, 80 mg, or 120 mg to postmenopausal patients with locally advanced, or inoperable, or metastatic hormone-receptor positive breast cancer. The primary efficacy outcome was clinical benefit (CB), defined as the total number of patients who achieved a complete response, a partial response, or stable disease for ≥24 weeks. The study was a 2-stage design in which 19 patients per dose group were planned in the first stage. If at least 3 patients in any dose group achieved a CB, then that dose group was to be allowed to continue enrolling for the second stage, and the group could include up to a total of 60 patients. RESULTS: The 40-mg and 80-mg groups met the criterion and enrolled patients into the second stage. In the 40-mg group, there were 13 CB events in 60 patients (21.7%); and, in the 80-mg group, there were 12 CB events in 60 patients (20%). The 120-mg daily dose was stopped early, because it failed to achieve the criterion. For the 40-mg and 80-mg groups, the median time to progression was 15.0 weeks and 15.9 weeks, respectively. Only 1 drug-related serious adverse event (grade 3 hyperglycemia) was reported. CONCLUSIONS: TAS-108 at 40 mg and 80 mg daily demonstrated clinical activity with an encouraging duration of benefit. Because of its superior safety profile, TAS-108 40 mg daily is recommended for further development. © 2011 American Cancer Society.
Keywords: 21 (4 diethylaminomethyl 2 methoxyphenoxy) 7alpha methyl 19 norpregna 1,3,5(10) trien 3 ol; aromatase inhibitor; estrogen receptor; progesterone receptor; tamoxifen; adult; arthralgia; article; Asian; backache; bone density; breast cancer; cancer grading; Caucasian; Chile; constipation; controlled study; coughing; diarrhea; double blind procedure; drug dose comparison; drug efficacy; drug fatality; drug safety; drug withdrawal; dyspnea; ethnic difference; fatigue; female; headache; Hispanic; hot flush; human; hyperglycemia; major clinical study; Mexico; multicenter study; multiple cycle treatment; nausea; Black person; Pacific Islander; phase 2 clinical trial; postmenopause; priority journal; progression free survival; randomized controlled trial; cancer recurrence; Russian Federation; sample size; side effect; thromboembolism; treatment duration; treatment outcome; treatment response; United States; vomiting; tas 108

Effect of patient perceptions on dementia screening in primary care - Fowler, N.R.; Boustani, M.A.; Frame, A.; Perkins, A.J.; Monahan, P.; Gao, S.; Sachs, G.A.; Hendrie, H.C. (Journal of the American Geriatrics Society, 2012)
OBJECTIVES: To determine individuals' perceptions concerning dementia screening and to evaluate the possibility of an association between their perceptions and their willingness to undergo screening. DESIGN: Cross-sectional study of primary care patients aged 65 and older. SETTING: Urban primary care clinics in Indianapolis, Indiana, in 2008 to 2009. PARTICIPANTS: Five hundred fifty-four primary care patients without a documented diagnosis of dementia. MEASUREMENTS: The Perceptions Regarding Investigational Screening for Memory in Primary Care Questionnaire (PRISM-PC) and agreement or refusal to undergo dementia screening. RESULTS: Of the 554 study participants who completed the PRISM-PC, 65.5% were aged 70 and older, 70.0% were female, and 56.5% were African American; 57 (10.3%) refused screening for dementia. Of the 497 (89.7%) who agreed to screening, 63 (12.7%) screened positive. After adjusting for age, perception of depression screening, perception of colon cancer screening, and belief that no treatment is currently available for Alzheimer's disease, the odds of refusing screening were significantly lower in participants who had higher PRISM-PC domain scores for benefits of dementia screening (odds ratio (OR) = 0.85, 95% confidence interval (CI) = 0.75-0.97; P = .02). In the same regression model, the odds of refusing screening were significantly higher in participants aged 70 to 74 (OR = 5.65, 95% CI = 2.27-14.09; P < .001) and those aged 75 to 79 (OR = 3.63, 95% CI = 1.32-9.99; P = .01) than in the reference group of patients aged 65 to 69. CONCLUSION: Age and perceived benefit of screening are associated with acceptance of dementia screening in primary care. © 2012, Copyright the Authors Journal compilation © 2012, The American Geriatrics Society.
Keywords: African American; aged; Alzheimer disease; article; attitude to illness; colon cancer; cross-sectional study; dementia; depression; female; human; major clinical study; male; mass screening; perception; primary medical care; questionnaire; refusal to participate; sex difference; statistical significance; United States; urban population

A randomized, placebo controlled trial of oral zinc for chemotherapy-related taste and smell disorders - Lyckholm, L.; Heddinger, S.P.; Parker, G.; Coyne, P.J.; Ramakrishnan, V.; Smith, T.J.; Henkin, R.I. (Journal of Pain and Palliative Care Pharmacotherapy, 2012)
Abnormalities in taste and smell are commonly reported in patients receiving chemotherapy and may hinder appetite, dietary intake, nutritional well-being, and quality of life. Oral zinc has been used to treat taste and smell abnormalities in several altered physiologic states, including renal failure, liver disease, head trauma, and pregnancy, with varying results. The authors conducted a double-blinded, placebo-controlled randomized clinic trial over 3 months. Eligible patients were those taking chemotherapy that had alterations in taste and/or smell. The measurement of the primary end point, improvement in altered taste and smell, was made using a 0100 scale (100 describing no loss or distortion in taste and smell, and 0 describing the worst distortion or loss of taste and smell). Twenty-nine subjects were enrolled in each treatment group, of whom 31 were white, 26 African American, and 1 Native American. Forty-one patients were female. A wide range of cancer types was represented, with breast the most common (21 patients). The zinc dose was 220 mg orally twice daily (equivalent of 50 mg elemental zinc twice daily). There was no statistically significant improvement in loss or distortion of taste or smell with the addition of zinc. There was a trend toward improvement over time in all groups, except in the zinc group where there was a nonsignificant worsening in loss of smell over time. Zinc at standard doses did not provide significant benefit to taste or smell in patients receiving chemotherapy. © 2012 Informa Healthcare USA, Inc.
Keywords: antineoplastic agent; bevacizumab; capecitabine; carboplatin; cisplatin; cyclophosphamide; cytarabine; dactinomycin; docetaxel; doxorubicin; etoposide; fluorouracil; gemcitabine; idarubicin; ifosfamide; irinotecan; mitoxantrone; vinorelbine tartrate; oxaliplatin; paclitaxel; placebo; rituximab; trastuzumab; vincristine; zinc; absence of side effects; adult; article; cancer chemotherapy; cancer radiotherapy; clinical article; controlled study; diet supplementation; double blind procedure; female; head and neck cancer; head injury; human; liver disease; male; neoplasm; quality of life; randomized controlled trial; smelling disorder; taste disorder; wellbeing

A pilot program in collaboration with African American churches successfully increases awareness of the importance of cancer research and participation in cancer translational research studies among African Americans. - Colon-Otero, G.; Albertie, M.; Lesperance, M.; Weis, J.A.; Coles, A.; Smith, N.; Mills, L.; Woodward, T.; Aspitia, A.M.; Vishnu, P.; Willis, F.; Isley, A.; et al. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2012)
African Americans are underrepresented in cancer research. We evaluate whether collaboration with African American churches can improve cancer awareness and increase participation in translational research protocols among African Americans. From February to April 2010, the Mayo Clinic partnered with African American Jacksonville churches to provide educational programs focused on cancer research and healthy behaviors. Education on multiple myeloma and on-site access to a translational cancer research pilot project evaluating the prevalence of monoclonal gammopathies and t(14,18) in African Americans was offered. Seventy-four percent, 236 out of 318 participants, returned the questionnaires. The majority of participants had never received information on multiple myeloma (67%), had never received clinical research study information (57%), and were enrolled in the translational research studies (55%). Partnerships with African American churches in community education projects that bring research to church venues are effective in improving cancer awareness and in increasing research participation among African Americans.
Keywords: adult; African American; aged; article; attitude to health; awareness; ethnology; female; health education; human; male; mass screening; middle aged; multiple myeloma; organization and management; participatory research; patient education; pilot study; translational research

Effect of comorbid conditions on adherence to colorectal cancer screening. - Lukin, D.J.; Jandorf, L.H.; Dhulkifl, R.J.; Thélémaque, L.D.; Christie, J.A.; Itzkowitz, S.H.; Duhamel, K.N. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2012)
Potential barriers to colorectal cancer (CRC) screening include preexisting medical conditions (comorbidities), physician recommendation, psychosocial factors, and screening preparedness. This study's purpose was to investigate the impact of comorbid conditions on CRC screening among African Americans. A stage-matched randomized clinical trial was performed. Asymptomatic African Americans over age 50, with a primary care physician, and eligible for CRC screening were recruited at The Mount Sinai Hospital from 2005 to 2008. One hundred sixty-one patients were assessed for referral for, and completion of, CRC screening, comorbid conditions, "readiness to change," and number of physician visits within the observation period. Data was compared to a pretrial index to predict the likely effect of comorbid conditions on CRC screening. One hundred fifty-nine patients completed the study; 108 (68.9%) were referred for and 34 (21.2%) completed CRC screening. No demographic characteristics were associated with CRC screening completion. CRC screening referrals were similar for all patients, regardless of comorbidities or clinical visits. Comorbidities rated as having extreme influence on CRC screening showed a trend toward lower screening rates. There was a significant increase in screening rates among participants in advanced stages of readiness at enrollment. These data suggest that while comorbidities did not predict colonoscopy completion, they may play a role in concert with other factors. This is the only study to assess the effect of screening colonoscopy in an African American primary care setting. We must continue to explore interventions to narrow the disparate gap in screening and mortality rates.
Keywords: article; clinical trial; colorectal tumor; comorbidity; controlled clinical trial; controlled study; early diagnosis; female; human; male; mass screening; methodology; middle aged; patient compliance; prospective study; randomized controlled trial; risk factor

Developing partnerships and recruiting dyads for a prostate cancer informed decision making program: lessons learned from a community-academic-clinical team. - Friedman, D.B.; Johnson, K.M.; Owens, O.L.; Thomas, T.L.; Dawkins, D.S.; Gansauer, L.; Bartelt, S.; Waddell, N.M.; Talley, P.J.; Bearden 3rd., J.D.; Hébert, J.R. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2012)
Prostate cancer (PrCA) is the most commonly diagnosed non-skin cancer among men. PrCA mortality in African-American (AA) men in South Carolina is ~50% higher than for AAs in the U.S as a whole. AA men also have low rates of participation in cancer research. This paper describes partnership development and recruitment efforts of a Community-Academic-Clinical research team for a PrCA education intervention with AA men and women that was designed to address the discordance between high rates of PrCA mortality and limited participation in cancer research. Guided by Vesey's framework on recruitment and retention of minority groups in research, recruitment strategies were selected and implemented following multiple brainstorming sessions with partners having established community relationships. Based on findings from these sessions culturally appropriate strategies are recommended for recruiting AA men and women for PrCA education research. Community-based research recruitment challenges and lessons learned are presented.
Keywords: African American; article; attitude to health; decision making; demography; female; health education; human; information processing; male; middle aged; organization and management; patient selection; pilot study; prostate tumor; psychological aspect; United States; university hospital

Quality of breast cancer care: Perception versus practice - Bickell, N.A.; Neuman, J.; Fei, K.; Franco, R.; Joseph, K.-A. (Journal of Clinical Oncology, 2012)
Purpose: Because insurers use performance and quality metrics to inform reimbursement, identifying remediable causes of poor-quality cancer care is imperative. We undertook this descriptive cohort study to assess key predictors of women's perceived quality of their breast cancer care and actual guideline-concordant quality of care received. Patients and Methods: We surveyed inner-city women with newly diagnosed and surgically treated early-stage breast cancer requiring adjuvant treatment who were enrolled onto a randomized controlled trial (RCT) of patient assistance to reduce disparities in care. We assessed women's perceived quality of care and perceived quality of the process of getting care, such as getting referrals, test results, and treatments; we abstracted records to determine the actual quality of care. Results: Of the 374 new patients with early-stage breast cancer enrolled onto the RCT, only a slight majority of women (55%) perceived their quality of care as excellent; 88% actually received good-quality, guideline-concordant care. Excellent perceived quality (P < .001) was significantly associated with patients' perception of the quality of the process of getting care (adjusted relative risk [RR], 1.78; 95% CI, 1.65 to 1.87). Also associated with perceived quality - and mediated by race - were trust in one's physician (adjusted RR, 1.43; 95% CI, 1.16 to 1.64) and perceived racism, which affected black women more than women of other races/ethnicities (black race-adjusted RR for perceived racism, 0.33 [95% CI, 0.10 to 0.87]; black race-adjusted RR for trust, 1.61 [95% CI, 0.97 to 1.90]; c = 0.82 for the model; P < .001). Actual quality of care provided did not affect perceived quality of care received. Conclusion: Patients' perceived quality of care differs from their receipt of high-quality care. Mutable targets to improve perceived quality of care include the processes of getting care and trusting their physician. © 2012 by American Society of Clinical Oncology.
Keywords: adult; African American; aged; article; breast cancer; clinical practice; ethnicity; female; health care disparity; health care quality; health survey; human; major clinical study; patient care; patient referral; perception; physician; priority journal; reimbursement

Adherence to colorectal cancer screening: A randomized clinical trial of competing strategies - Inadomi, J.M.; Vijan, S.; Janz, N.K.; Fagerlin, A.; Thomas, J.P.; Lin, Y.V.; Munõz, R.; Lau, C.; Somsouk, M.; El-Nachef, N.; Hayward, R.A. (Archives of Internal Medicine, 2012)
Background: Despite evidence that several colorectal cancer (CRC) screening strategies can reduce CRC mortality, screening rates remain low. This study aimed to determine whether the approach by which screening is recommended influences adherence. Methods: We used a cluster randomization design with clinic time block as the unit of randomization. Persons at average risk for development of CRC in a racially/ethnically diverse urban setting were randomized to receive recommendation for screening by fecal occult blood testing (FOBT), colonoscopy, or their choice of FOBT or colonoscopy. The primary outcome was completion of CRC screening within 12 months after enrollment, defined as performance of colonoscopy, or 3 FOBT cards plus colonoscopy for any positive FOBT result. Secondary analyses evaluated sociodemographic factors associated with completion of screening. Results: A total of 997 participants were enrolled; 58% completed the CRC screening strategy they were assigned or chose. However, participants who were recommended colonoscopy completed screening at a significantly lower rate (38%) than participants who were recommended FOBT (67%) (P<.001) or given a choice between FOBT or colonoscopy (69%) (P<.001). Latinos and Asians (primarily Chinese) completed screening more often than African Americans. Moreover, nonwhite participants adhered more often to FOBT, while white participants adhered more often to colonoscopy. Conclusions: The common practice of universally recommending colonoscopy may reduce adherence to CRC screening, especially among racial/ethnic minorities. Significant variation in overall and strategy-specific adherence exists between racial/ethnic groups; however, this may be a proxy for health beliefs and/or language. These results suggest that patient preferences should be considered when making CRC screening recommendations. Trial Registration: clinicaltrials.gov Identifier: NCT00705731. ©2012 American Medical Association. All rights reserved.
Keywords: NCT00705731; adult; African American; article; cancer patient; cancer risk; cancer screening; Chinese; cluster analysis; colonoscopy; colorectal cancer; controlled study; demography; ethnic difference; female; Hispanic; human; major clinical study; male; occult blood test; outcome assessment; priority journal; randomization; randomized controlled trial (topic); urban area

Phase II efficacy and pharmacogenomic study of selumetinib (AZD6244; ARRY-142886) in iodine-131 refractory papillary thyroid carcinoma with or without follicular elements - Hayes, D.N.; Lucas, A.S.; Tanvetyanon, T.; Krzyzanowska, M.K.; Chung, C.H.; Murphy, B.A.; Gilbert, J.; Mehra, R.; Moore, D.T.; Sheikh, A.; Hoskins, J.; Hayward, M.C.; et al. (Clinical Cancer Research, 2012)
Purpose: A multicenter, open-label, phase II trial was conducted to evaluate the efficacy, safety, and tolerability of selumetinib in iodine-refractory papillary thyroid cancer (IRPTC). Experimental Design: Patients with advanced IRPTC with or without follicular elements and documented disease progression within the preceding 12 months were eligible to receive selumetinib at a dose of 100 mg twice daily. The primary endpoint was objective response rate using Response Evaluation Criteria in Solid Tumors. Secondary endpoints were safety, overall survival, and progression-free survival (PFS). Tumor genotype including mutations in BRAF, NRAS, and HRAS was assessed. Results: Best responses in 32 evaluable patients out of 39 enrolled were 1 partial response (3%), 21 stable disease (54%), and 11 progressive disease (28%). Disease stability maintenance occurred for 16 weeks in 49%, 24 weeks in 36%. Median PFS was 32 weeks. BRAF V600E mutants (12 of 26 evaluated, 46%) had a longer median PFS compared with patients with BRAF wild-type (WT) tumors (33 versus 11 weeks, respectively, HR = 0.6, not significant, P = 0.3). The mostcommonadverse events and grades 3 to 4 toxicities included rash, fatigue, diarrhea, and peripheral edema. Two pulmonary deaths occurred in the study and were judged unlikely to be related to the study drug. Conclusions: Selumetinib was well tolerated but the study was negative with regard to the primary outcome. Secondary analyses suggest that future studies of selumetinib and other mitogen-activated protein (MAP)/extracellular signal-regulated kinase (ERK; MEK) inhibitors in IRPTC should consider BRAF V600E mutation status in the trial design based on differential trends in outcome. ©2012 AACR.
Keywords: axitinib; iodine 131; motesanib; selumetinib; sorafenib; adult; African American; aged; article; Asian; BRAF gene; cancer grading; Caucasian; clinical article; controlled study; diarrhea; disease course; drug dose reduction; drug efficacy; drug eruption; drug fatality; drug half life; drug safety; drug tolerability; drug withdrawal; fatigue; female; gene mutation; genotype; genotyping technique; HRAS gene; human; human cell; human tissue; iodine refractory papillary thyroid cancer; male; multicenter study; multiple cycle treatment; NRAS gene; oncogene; onset age; open study; overall survival; peripheral edema; pharmacogenomics; phase 2 clinical trial; priority journal; progression free survival; takotsubo cardiomyopathy; thyroid follicular carcinoma; thyroid papillary carcinoma; treatment outcome; treatment response; arry 142886; azd 6244

Increasing minority patient participation in cancer clinical trials using oncology nurse navigation - Holmes, D.R.; Major, J.; Lyonga, D.E.; Alleyne, R.S.; Clayton, S.M. (American Journal of Surgery, 2012)
Background: Residential distance from an academic or cancer center is a significant barrier to minority patient participation in cancer research. Most cancer clinical trials (CTs) are only accessible at academic and cancer centers, yet most cancer patients receive treatment in their home communities where access to CTs may be limited. Oncology nurse navigation is an innovative approach for increasing minority CT participation by facilitating access to cancer CTs in communities where minority patients live. The purpose of this study was to evaluate the impact of oncology nurse navigation on community-based recruitment of black patients to breast cancer CTs at a major cancer center. Methods: We merged the roles of a traditional oncology research nurse and a professional patient navigator to create a novel health care provider role, the oncology nurse navigator. The primary duties of the oncology nurse navigator were to engage black cancer patients in the offices of their community physicians and to collaborate with community physicians to increase black patient participation in cancer research. The oncology nurse navigator played a key role in all phases of the CT participation process (e.g., screening for eligibility and completion of informed consent and clinical research forms) and guided each patient around barriers in the health care system. The accrual of eligible patients to breast cancer CTs was used to assess the impact of oncology nurse navigation on community-based recruitment of blacks to cancer CTs. Results: Between January 2007 and December 2008, a total of 132 black breast cancer patients were screened by a single oncology nurse navigator for eligibility to University of Southern Californiasponsored breast cancer CTs. Fifty-nine patients were eligible for CTs, and each was invited to participate in 1 or more CTs for which they were eligible. Fifty-one of 59 eligible black patients (86% of eligible patients) were enrolled to 1 or more research protocols. The estimated cost per enrolled patient was $5,677, nearly half the expected per patient cost of treating patients on CT at an academic or cancer center. Conclusions: Oncology nurse navigation is an effective outreach strategy for increasing black patient participation in cancer research and may be achieved at nearly half the cost of traditional methods of enrolling patients in CTs at cancer centers. © 2012 Elsevier Inc. All rights reserved.
Keywords: African American; article; breast cancer; cancer center; cancer research; clinical trial (topic); community health nursing; cost benefit analysis; cost effectiveness analysis; health care personnel; health care system; human; major clinical study; oncology nursing; patient participation; priority journal

Prognostic value and agreement of achieving lactate clearance or central venous oxygen saturation goals during early sepsis resuscitation - Puskarich, M.A.; Trzeciak, S.; Shapiro, N.I.; Arnold, R.C.; Heffner, A.C.; Kline, J.A.; Jones, A.E. (Academic Emergency Medicine, 2012)
Objectives: Lactate clearance (LC) and central venous oxygen saturation (ScvO2) have been proposed as goals of early sepsis resuscitation. The authors sought to determine the agreement and prognostic value of achieving ScvO2 or LC goals in septic shock patients undergoing emergency department (ED)-based early resuscitation. Methods: This was a preplanned analysis of a multicenter ED randomized controlled trial of early sepsis resuscitation targeting three variables: central venous pressure, mean arterial pressure, and either ScvO2 or LC. Inclusion criteria included suspected infection, two or more systemic inflammation criteria, and either systolic blood pressure of <90 mm Hg after intravenous fluid bolus or lactate level of >4 mmol/L. Both ScvO2 and LC were measured simultaneously. The ScvO2 goal was defined as ≥70%. Lactate was measured at enrollment and every 2 hours until the goal was reached or up to 6 hours. LC goal was defined as a decrease of ≥10% from initial measurement. The primary outcome was in-hospital mortality. Results: A total of 203 subjects were included, with an overall mortality of 19.7%. Achievement of the ScvO 2 goal only was associated with a mortality rate of 41% (9/22), while achievement of the LC goal only was associated with a mortality rate of 8% (2/25; proportion difference = 33%; 95% confidence interval [CI] = 9% to 55%). No agreement was found between goal achievement (κ = -0.02), and exact test for matched pairs demonstrated no significant difference between discordant pairs (p = 0.78). Conclusions: No agreement was found between LC and ScvO 2 goal achievement in early sepsis resuscitation. Achievement of a ScvO2≥ 70% without LC ≥ 10% was more strongly associated with mortality than achievement of LC ≥ 10% with failure to achieve ScvO 2≥ 70%. © 2012 by the Society for Academic Emergency Medicine.
Keywords: NCT00372502; activated protein C; dobutamine; infusion fluid; lactic acid; abdominal infection; adult; African American; antibiotic therapy; article; artificial ventilation; bloodstream infection; breathing rate; Caucasian; central vein; central venous oxygen saturation; central venous pressure; chronic obstructive lung disease; comorbidity; controlled study; corticosteroid therapy; crystalloid; diabetes mellitus; disease severity; early intervention; emergency treatment; erythrocyte transfusion; female; Glasgow coma scale; heart rate; Hispanic; human; Human immunodeficiency virus infection; kidney failure; lactate blood level; lung infection; major clinical study; male; malignant neoplasm; mean arterial pressure; mortality; multicenter study; multiple organ failure; nursing home patient; organ transplantation; outcome assessment; oxygen saturation; priority journal; prognosis; prospective study; randomized controlled trial; resuscitation; septic shock; skin infection; systolic blood pressure; urinary tract infection

Immunogenicity of the quadrivalent human papillomavirus (type 6/11/16/18) vaccine in males 16 to 26 years old - Hillman, R.J.; Giuliano, A.R.; Palefsky, J.M.; Goldstone, S.; Moreira Jr., E.D.; Vardas, E.; Aranda, C.; Jessen, H.; Ferris, D.G.; Coutlee, F.; Marshall, J.B.; Vuocolo, S.; et al. (Clinical and Vaccine Immunology, 2012)
Human papillomavirus (HPV) infection can lead to significant disease in males, including anogenital warts, intraepithelial neoplasias, and several types of oral and anogenital cancers. The quadrivalent HPV (type 6/11/16/18) L1 virus-like particle (VLP) vaccine (qHPV vaccine; Gardasil) has recently been demonstrated to prevent persistent infection and associated disease related to vaccine HPV types in males. We report the overall immunogenicity results from a trial of the quadrivalent HPV vaccine in males. Overall, 3,463 heterosexual men and 602 men who had sex with men were enrolled into a randomized, placebo-controlled, double-blind safety, immunogenicity, and efficacy study. Serum samples were collected prior to vaccination at day 1 and at months 7, 24, and 36 postvaccination. Immunogenicity was evaluated with a multiplex, competitive Luminex immunoassay. Almost all subjects (97.4 to 99.2%) seroconverted for vaccine HPV types by month 7. At month 36, 88.9%, 94.0%, 97.9%, and 57.0% of subjects were still seropositive for HPV-6, -11, -16, and -18, respectively. For all vaccine HPV types, black subjects had significantly higher antibody titers at month 7 than did both Caucasian and Asian subjects. An anamnestic antibody response was seen in men seropositive before vaccination. The vaccine was highly immunogenic in males 16 to 23 years of age; responses were comparable to those observed in women. Furthermore, the immune responses were consistent with the established efficacy of the vaccine in the prevention of incident and persistent HPV infection, anogenital warts, and anal intraepithelial neoplasia. Copyright © 2012, American Society for Microbiology. All Rights Reserved.
Keywords: NCT00090285; aluminum hydroxyphosphate sulfate; immunological adjuvant; placebo; unclassified drug; virus antibody; Wart virus vaccine; adolescent; adult; African American; age; antibody response; antibody titer; article; Asian; blood sampling; Caucasian; controlled study; double blind procedure; drug dose regimen; drug efficacy; drug safety; ethnic difference; heterosexual male; Hispanic; human; human experiment; Human papillomavirus type 11; Human papillomavirus type 16; Human papillomavirus type 18; Human papillomavirus type 6; immunoassay; immunogenicity; male; multicenter study; normal human; priority journal; randomized controlled trial; seroconversion; sexuality; smoking; vaccination; gardasil; silgard

Detection of small metastatic brain tumors: Comparison of 3D contrast-enhanced whole-brain black-blood imaging and MP-RAGE imaging - Park, J.; Kim, J.; Yoo, E.; Lee, H.; Chang, J.-H.; Kim, E.Y. (Investigative Radiology, 2012)
Objective: Early and accurate diagnosis of small metastatic brain tumors may affect outcomes and treatment strategies. For this reason, 3-dimensional (3D) thin-section imaging is preferred. However, with conventional contrast-enhanced (CE) 3D imaging, such as magnetization-prepared rapid gradient echo (MP-RAGE), many visually enhanced vessels may mimic small metastatic tumors, hindering tumor detection. CE black-blood single-slab 3D turbo-spin echo imaging (BB-ssTSE) was recently developed, which uses variable refocusing flip angles and flow-sensitizing gradient schemes, to enhance metastatic brain tumors while selectively suppressing blood vessels. The purpose of this work was to investigate the efficiency of the proposed CE BB-ssTSE in detecting small metastatic brain tumors as compared with conventional MP-RAGE. Materials and Methods: Numerical comparisons of MP-RAGE and BB-ssTSE were performed by simulation studies to investigate the signal/contrast behaviors of flowing blood and stationary CE tumors. For in vivo studies, we enrolled 35 patients (18 women; mean age, 58.1 years) with breast or lung cancer who underwent brain magnetic resonance imaging. After administering a double dose of contrast medium, whole-brain 2-dimensional T1-weighted imaging followed by high-resolution isotropic 3D BB-ssTSE and MP-RAGE was performed at 3.0 T. Two reviewers independently evaluated the presence of metastatic brain tumors using: (1) MP-RAGE; (2) BB-ssTSE; and (3) MP-RAGE + BB-ssTSE sequentially in 3 review sessions, 2 weeks apart. The lesions were classified by size into 2 groups: large (<5 mm) and small (<5 mm). Both reviewers marked all tumors detected at each session. Another reviewer combined the results of the 2 reviewers and compared the detection rates of metastatic brain tumors between BB-ssTSE and MP-RAGE by using follow-up imaging. Intraclass correlation coefficients between the 2 reviewers were measured. Results: Numerical simulations showed that the proposed BB-ssTSE effectively attenuated the signal intensity of flowing blood over the entire echo train, resulting in CE tumor-to-white matter contrast comparable with conventional MP-RAGE. The combined evaluation of MP-RAGE + BB-ssTSE showed 242 tumors in 28 patients. Of these, 153 lesions were <5 mm. MP-RAGE found 111 small metastatic brain tumors, BB-ssTSE found 150, and MP-RAGE + BB-ssTSE found 153. Significantly, more small tumors were detected by BB-ssTSE than MP-RAGE (P = 0.001, Wilcoxon signed-rank test). All large tumors were detected similarly by both MP-RAGE and BB-ssTSE. By combined results for MP-RAGE + BB-ssTSE, sensitivities for detection of small metastatic tumors were 72.5% for MP-RAGE and 98.0% for BB-ssTSE (P < 0.0001, McNemar test). Intraclass correlation coefficients between the 2 reviewers were 0.826 for MP-RAGE and 0.954 for BB-ssTSE. Conclusion: Compared with conventional MP-RAGE, the proposed CE BB-ssTSE imaging, which enhances tumors while selectively suppressing blood vessels, leads to significantly better detection of small metastatic brain tumors <5 mm. © 2012 by Lippincott Williams & Wilkins.
Keywords: gadolinium pentetate meglumine; adult; aged; article; brain blood flow; brain metastasis; breast cancer; cancer diagnosis; clinical article; clinical trial; contrast enhanced black blood single slab three dimensional turbo spin echo imaging; contrast enhancement; diagnostic accuracy; female; follow up; human; image analysis; intermethod comparison; lung cancer; magnetization prepared rapid gradient echo; male; mathematical computing; nuclear magnetic resonance imaging; priority journal; small metastatic brain tumor; tumor localization; tumor volume; white matter

Long-term follow-up of a prospective trial of trimodality therapy of weekly paclitaxel, radiation, and androgen deprivation in high-risk prostate cancer with or without prior prostatectomy - Hussain, A.; Wu, Y.; Mirmiran, A.; Dibiase, S.; Goloubeva, O.; Bridges, B.; Mannuel, H.; Engstrom, C.; Dawson, N.; Amin, P.; Kwok, Y. (International Journal of Radiation Oncology Biology Physics, 2012)
Purpose: Weekly paclitaxel, concurrent radiation, and androgen deprivation (ADT) were evaluated in patients with high-risk prostate cancer (PC) with or without prior prostatectomy (RP). Methods and Materials: Eligible post-RP patients included: pathological T3 disease, or rising prostate-specific antigen (PSA) ≥0.5 ng/mL post-RP. Eligible locally advanced PC (LAPC) patients included: 1) cT2b-4N0N+, M0; 2) Gleason score (GS) 8-10; 3) GS 7 + PSA 10-20 ng/mL; or 4) PSA 20-150 ng/mL. Treatment included ADT (4 or 24 months), weekly paclitaxel (40, 50, or 60 mg/m2/wk), and pelvic radiation therapy (total dose: RP = 64.8 Gy; LAPC = 70.2 Gy). Results: Fifty-nine patients were enrolled (LAPC, n = 29; RP, n = 30; ADT 4 months, n = 29; 24 months, n = 30; whites n = 29, African Americans [AA], n = 28). Baseline characteristics (median [range]) were: age 67 (45-86 years), PSA 5.9 (0.1-92.1 ng/mL), GS 8 (6-9). At escalating doses of paclitaxel, 99%, 98%, and 95% of doses were given with radiation and ADT, respectively, with dose modifications required primarily in RP patients. No acute Grade 4 toxicities occurred. Grade 3 toxicities were diarrhea 15%, urinary urgency/incontinence 10%, tenesmus 5%, and leukopenia 3%. Median follow-up was 75.3 months (95% CI: 66.8-82.3). Biochemical progression occurred in 24 (41%) patients and clinical progression in 11 (19%) patients. The 5- and 7-year OS rates were 83% and 67%. There were no differences in OS between RP and LAPC, 4- and 24-month ADT, white and AA patient categories. Conclusions: In addition to LAPC, to our knowledge, this is the first study to evaluate concurrent chemoradiation with ADT in high-risk RP patients. With a median follow-up of 75.3 months, this trial also represents the longest follow-up of patients treated with taxane-based chemotherapy with EBRT in high-risk prostate cancer. Concurrent ADT, radiation, and weekly paclitaxel at 40 mg/m2/week in RP patients and 60 mg/m2/week in LAPC patients is feasible and well-tolerated. Copyright © 2012 Elsevier Inc. Printed in the USA. All rights reserved.
Keywords: gonadorelin agonist; metronidazole; paclitaxel; prostate specific antigen; adult; African American; aged; alopecia; androgen deprivation therapy; anemia; antibiotic therapy; arthralgia; article; cancer chemotherapy; cancer growth; cancer hormone therapy; cancer patient; cancer radiotherapy; cancer survival; chemoradiotherapy; Clostridium difficile infection; computer assisted radiotherapy; constipation; controlled clinical trial; controlled study; deep vein thrombosis; dehydration; diarrhea; drug dose escalation; drug dose reduction; drug fever; edema; erectile dysfunction; external beam radiotherapy; fatigue; fever; follow up; gastrointestinal reflux; gastrointestinal symptom; Gleason score; gynecomastia; rectum hemorrhage; hematuria; high risk patient; hot flush; human; infection; leukopenia; long term care; major clinical study; male; multimodality cancer therapy; myalgia; nausea; neuropathy; neutropenia; overall survival; partial body radiation; pelvis; phase 1 clinical trial; priority journal; proctitis; prostate cancer; prostatectomy; radiation dermatitis; radiation dose; radiation dose fractionation; radiation sickness; tenesmus; thrombocytopenia; urinary tract obstruction; urinary urgency; urine incontinence; urogenital tract disease

Community-based participatory approach to reduce breast cancer disparities in south Dallas. - Cardarelli, K.; Jackson, R.; Martin, M.; Linnear, K.; Lopez, R.; Senteio, C.; Weaver, P.; Hill, A.; Banda, J.; Epperson-Brown, M.; Morrison, J.; Parrish, D.; et al. (Progress in community health partnerships : research, education, and action, 2011)
South Dallas experiences significant disparities in breast cancer mortality, with a high proportion of stage III and IV diagnoses. To address these rates, the Dallas Cancer Disparities Community Research Coalition created an educational intervention to promote breast health and early detection efforts. The goals of the intervention were to increase (a) knowledge regarding the chief contributing factors for breast cancer, (b) awareness of the importance of screening for early detection, and (c) the proportion of women who have engaged in appropriate breast cancer screening practices. Eligibility criteria for this nonrandomized, controlled trial included women age 40 and older, English-speaking, and having no personal history of cancer. Control participants received written breast health educational materials. Intervention participants attended 8 weekly sessions that included interactive educational materials, cooking demonstrations, and discussions emphasizing primary and secondary breast cancer prevention. All study participants completed a 1-hour survey at baseline and 4 months later. There were 59 women were enrolled in the intervention and 60 in the control group. At follow-up, after controlling for baseline mammography status, women in the intervention group were 10.4 times more likely (95% confidence interval [CI], 2.9-36.4) to have received a screening mammogram in the last year compared with the control group. Intervention participants demonstrated statistically significantly higher rates of breast self-examination (odds ratio [OR], 3.0; 95% CI, 1.0-8.6) and breast cancer knowledge (p=.003). Lessons learned from this community-based participatory research (CBPR) study can be used to create sustainable cancer disparity reduction models that can be replicated in similar communities.
Keywords: adult; African American; article; attitude to health; breast tumor; clinical trial; diet; early diagnosis; ethnology; exercise; female; health behavior; health disparity; health education; human; methodology; middle aged; organization and management; participatory research; psychological aspect; social support; socioeconomics; United States; women's health

A lay patient navigation training curriculum targeting disparities in cancer clinical trials. - Bryant, D.C.; Williamson, D.; Cartmell, K.; Jefferson, M. (Journal of National Black Nurses' Association : JNBNA, 2011)
African-Americans experience a disproportionate share of thoracic cancer burden compared to Whites. Low socioeconomic status (SES) and race are factors in low clinical trial enrollment, accounting for the disparities between African-Americans and Whites. Less than 3% of newly diagnosed cancer patients enroll in clinical trials, and of that number, only 10% represent ethnic minorities. The value of clinical trials research is not generalizable without sufficient representation by ethnic minorities. Patient navigation, an intervention designed to ensure timely and efficient access to healthcare, may improve clinical trial enrollment among African-Americans in lung and esophageal trials by influencing a patient's perception of clinical trials. The lack of navigation programs and training may negatively influence standardization of navigation techniques. The purpose of this project was to deliver and evaluate an evidence-based navigation-training curriculum for "lay" navigators. The primary outcomes measured were confidence in the role as navigator, understanding a navigator's role, and knowledge and perception of clinical trials. The results revealed overall confidence in the role as lay navigators increased from pre-to-post test. Lessons learned included the need for preparatory classes to build the navigator's confidence, and additional training components in death and dying. A larger study is warranted to confirm the findings.
Keywords: African American; article; clinical trial; clinical trial (topic); curriculum; education; educational model; ethnology; female; health auxiliary; health care delivery; health care disparity; human; male; multicenter study; neoplasm; patient attitude; patient selection; pilot study; social support; United States

A pilot phase II trial of all-trans retinoic acid (Vesanoid) and paclitaxel (Taxol) in patients with recurrent or metastatic breast cancer - Bryan, M.; Pulte, E.D.; Toomey, K.C.; Pliner, L.; Pavlick, A.C.; Saunders, T.; Wieder, R. (Investigational New Drugs, 2011)
Purpose: We investigated a combination therapy with weekly paclitaxel and all trans-retinoic acid (ATRA) for tolerability, response to treatment, time to progression and survival in previously treated patients with metastatic or recurrent breast cancer. Our rationale was based on preclinical studies demonstrating potentiation of the cytotoxic effects of taxanes and induction of differentiation by ATRA. Patients and methods: Seventeen patients with previously treated metastatic or recurrent breast cancer were enrolled to a regimen of all-trans retinoic acid (Vesanoid, tretinoin, Hoffman-La Roche, Inc.) 45 mg/m2 PO daily for 4 days starting 2 days before a 1 h treatment with paclitaxel (Taxol, Bristol-Myers Squibb, Plainsboro, NJ) 80 mg/m 2 IV administered weekly for 3 weeks, repeated in 28 day cycles until disease progression or until no longer tolerated. Patients were evaluated for toxicity, response, time to progression and survival. Patients were primarily African American and Latino, representative of the population served by our Cancer Center. Results: The regimen was relatively well tolerated. There were nine grade 3 and one grade 4 toxic events. We administered 162 treatment cycles with a mean of 7.5 per patient (range 1-22, median 5). Three patients had a partial response (17.6%) and ten patients had stable disease (58.8%), with an overall clinical benefit of 76.4%. Median time to progression was 6.0 months (range 1-21, mean 7.7 months). Fourteen evaluable patients had a median survival of 16 months (range 1-68 months, mean 25.2 months). Conclusions: The data suggest this is a well tolerated regimen with modest response rates but with time to progression and survival rates similar to those reported for paclitaxel alone and relatively high rates of stable disease in this sample of patients. © Springer Science+Business Media, LLC 2010.
Keywords: paclitaxel; retinoic acid; adult; aged; alopecia; anemia; article; ataxia; bone metastasis; breast cancer; cancer combination chemotherapy; cancer growth; cancer staging; cancer survival; clinical article; constipation; disease severity; dose response; drug efficacy; drug safety; drug tolerability; drug withdrawal; edema; fatigue; female; gastrointestinal hemorrhage; headache; human; leukopenia; lung embolism; metastasis; multicenter study; multiple cycle treatment; nausea; neuropathy; neutropenia; outcome assessment; pain; phase 2 clinical trial; priority journal; cancer recurrence; repeated drug dose; seizure; supraventricular tachycardia; treatment duration; visceral metastasis; vomiting; taxol; tretinoin; vesanoid

I had already made up my mind: Patients and caregivers' perspectives on making the decision to participate in research at a us cancer referral center - Shannon-Dorcy, K.; Drevdahl, D.J. (Cancer Nursing, 2011)
Background: Hematopoietic cell transplants (HCTs) are associated with high morbidity and mortality, which complicate the decision-making process for people considering HCT clinical trials. There is a lack of research examining longitudinally how patients make clinical trial participation decisions in US cancer referral centers. Objective: A qualitative study was conducted to examine how patients and their family caregivers decide to participate in HCT research at a US cancer referral center. Methods: Semistructured interviews were conducted with 25 patients enrolled in early-stage phase 2 HCT research studies and with 20 family caregivers. Interviews were conducted before HCT and approximately days 80 and 365 after HCT. Results: Most patients (92%) and their caregivers (75%) decided to participate in research well before consent conferences at the cancer referral center. Patients' reasons for deciding to participate included having "no other option," seeking a cure, and following their home oncologists' recommendations. Conclusion: Currently, US researchers are primarily guided by Federal regulations that view the decision-making process as a cognitive one. Findings confirmed cognition was a part of consent; however, most patients made the decision to participate in high-risk clinical trials long before they had been apprised of the specific information about the study and before the consent conference. Implications for Practice: The high risk of death from the disease and/or the HCT underscored the emotional component of decision making and affirmed that researchers need to acknowledge this emotional component to meet the ethical imperative of providing "informed consent. © 2011 Lippincott Williams & Wilkins.
Keywords: adult; African American; aged; American Indian; article; cancer research; caregiver; chronic lymphatic leukemia; clinical article; clinical decision making; clinical trial (topic); controlled clinical trial; controlled study; engraftment; female; follow up; government regulation; graft versus host reaction; hematopoietic stem cell transplantation; high risk patient; Hispanic; Hodgkin disease; human; informed consent; male; medical ethics; medical information; multiple myeloma; phase 2 clinical trial; priority journal; promyelocytic leukemia; qualitative research; refractory anemia; semi structured interview; United States

The neighborhood voice: Evaluating a mobile research vehicle for recruiting african americans to participate in cancer control studies - Alcaraz, K.I.; Weaver, N.L.; Andresen, E.M.; Christopher, K.; Kreuter, M.W. (Evaluation and the Health Professions, 2011)
The Neighborhood Voice is a vehicle customized for conducting health research in community settings. It brings research studies into neighborhoods affected most by health disparities and reaches groups often underrepresented in research samples. This paper reports on the experience and satisfaction of 599 African American women who participated in research on board the Neighborhood Voice. Using bivariate, psychometric, and logistic regression analyses, we examined responses to a brief post-research survey. Most women (71%) reported that they had never previously participated in research, and two-thirds (68%) rated their Neighborhood Voice experience as excellent. Satisfaction scores were highest among first-time research participants (p <.05). Women's ratings of the Neighborhood Voice on Comfort (OR = 4.9; 95% CI = 3.0, 7.9) and Convenience (OR = 1.8; 95% CI = 1.2, 2.9) significantly predicted having an excellent experience. Mobile research facilities may increase participation among disadvantaged and minority populations. Our brief survey instrument is a model for evaluating such outreach. © The Author(s) 2011.
Keywords: African American; article; breast tumor; car; ethnology; evaluation study; female; health disparity; human; medical research; methodology; middle aged; patient selection; United States

A multimodal intervention to promote mammography and colorectal cancer screening in a safety-net practice - Fiscella, K.; Humiston, S.; Hendren, S.; Winters, P.; Idris, A.; Li, S.X.L.; Ford, P.; Specht, R.; Marcus, S. (Journal of the National Medical Association, 2011)
Background: There are limited data regarding interventions designed to improve cancer screening rates in safety-net practices with "real world" patients. Objective: To examine the impact of a multimodal intervention on mammography and colorectal cancer (CRC) screening rates in a safety-net practice caring for under-served patients. Methods: At an inner-city family medicine practice, all patients past due for mammography or CRC screening were assigned to receive or not receive a screening promotion intervention based on their medical record number. The 12-month intervention included outreach to patients (tailored letters, automated and personal phone calls) and point-of-care patient and clinician prompts. The trial was registered at clinicaltrials.gov, NCT00818857. Results: We enrolled 469 participants aged 40 to 74 years, including 28% African Americans, 5% Latinos, 25% with Medicaid, and 10% without any form of insurance. Participants in the intervention group showed statistically significantly higher rates of cancer screening; rates were 41% vs 16.8% for mammography and 28.8% vs 10% for CRC screening. These findings were confirmed in multivariable analysis. Similar relative improvements in screening were seen across race, ethnicity, socioeconomic status, and insurance groups. Discussion: A multimodal intervention shows promise for improving rates of mammography and colorectal cancer screening within a safety-net practice. Further study will identify the most cost-effective components of the intervention.
Keywords: NCT00818857; adult; African American; aged; article; breast cancer; cancer screening; colorectal cancer; controlled clinical trial; controlled study; cost effectiveness analysis; ethnicity; female; general practice; health insurance; Hispanic; human; major clinical study; male; mammography; medicaid; medicare; multivariate analysis; point of care testing; priority journal; race difference; safety; socioeconomics; statistical significance

Racial differences in colorectal cancer incidence and mortality in the women's health initiative - Simon, M.S.; Thomson, C.A.; Pettijohn, E.; Kato, I.; Rodabough, R.J.; Lane, D.; Hubbell, F.A.; O'Sullivan, M.J.; Adams-Campbell, L.; Mouton, C.P.; Abrams, J.; Chlebowski, R.T. (Cancer Epidemiology Biomarkers and Prevention, 2011)
Background: Colorectal cancer (CRC) incidence and mortality rates are higher in African-Americans as compared with other racial/ethnic groups. The women's health initiative (WHI) study sample was used to determine whether differences in CRC risk factors explain racial/ethnic differences in incidence and mortality. Methods: The WHI is a longitudinal study of postmenopausal women recruited from 40 centers. Baseline questionnaires were used to collect sociodemographic and health status information. All CRC diagnoses were centrally adjudicated. Cox regression models were used to compute hazard ratios (HRs) and 95% confidence intervals (CIs) for invasive CRC by race/ethnicity. Results: The study sample included 131,481 (83.7%) White, 14,323 (9.1%) African-American, 6,362 (4.1%) Hispanic, 694 (0.4%) Native American and 4,148 (2.6%) Asian/Pacific Islanders. After a mean follow-up of 10.8 years (SD 2.9), CRC incidence was the highest in African-Americans (annualized rate = 0.14%), followed by Whites and Native Americans (0.12% each), Asian/Pacific Islanders (0.10%), and Hispanics (0.08%). After adjustment for age and trial assignment, Hispanics had a lower risk compared with Whites, HR 0.73 (95% CI: 0.54-0.97) (P = 0.03), and African-Americans had a marginally greater risk, HR 1.16 (95% CI: 0.99-1.34), P = 0.06. Multivariable adjustment attenuated the difference in incidence between African-Americans and Whites (HR 0.99, 95% CI: 0.82-1.20), while strengthening the lower HR for Hispanics (HR 0.68, 95% CI: 0.48-0.97). Conclusions: African-American/White differences in CRC risk are likely due to sociodemographic/cultural factors other than race. Impact: A number of modifiable exposures could be a focus for reducing CRC risk in African-Americans. ©2011 AACR.
Keywords: adult; African American; aged; American Indian; article; cancer incidence; cancer mortality; cancer risk; colorectal cancer; confidence interval; controlled study; demography; female; follow up; hazard ratio; health status; Hispanic; human; longitudinal study; major clinical study; multivariate analysis; Pacific Islander; postmenopause; priority journal; proportional hazards model; questionnaire; race difference; risk factor; sample; women's health

Changes in Risk Perceptions in Relation to Self-Reported Colorectal Cancer Screening Among First-Degree Relatives of Colorectal Cancer Cases Enrolled in a Randomized Trial - Glenn, B.A.; Herrmann, A.K.; Crespi, C.M.; Mojica, C.M.; Chang, L.C.; Maxwell, A.E.; Bastani, R. (Health Psychology, 2011)
Objective: This secondary data analysis was conducted to evaluate the applicability of the Risk Reappraisal Hypothesis, which has been proposed to explain the influence of performing a health behavior on perceived risk. Data were collected in the context of a randomized trial, which found that an individually tailored, multicomponent intervention was successful in increasing colorectal cancer (CRC) screening among first-degree relatives of CRC cases. Method: The ethnically diverse study sample (N = 841; 29% Latino, 21% African American, 20% Asian) consisted of adult siblings and children (40-80 years) of CRC cases, identified through the California Cancer Registry. Data were collected at baseline and at 6- and 12-month follow-up. Changes in self-reported risk perception (perceived likelihood of developing CRC) were examined over the study period in relation to study condition and screening status. Results: Greater increases in perceived risk were observed among intervention versus control-group participants over the study period, but increases were limited to intervention participants who had not been screened. We also examined trajectories of perceived risk in relation to timing of screening receipt (e.g., before 6 months, 6-12 months, never). Continued upward shifts in risk were observed during the study period among intervention participants not screened during the study. In contrast, participants screened by 6 months displayed a reduction or leveling off in perceived risk between 6- and 12-month follow-up. Conclusion: Results provide support for the applicability of the Risk Reappraisal Hypothesis within a high-risk sample enrolled in a CRC screening promotion trial. Future research is needed to explore the impact of short-term risk reductions on future CRC screening behavior. © 2011 American Psychological Association.
Keywords: adult; African American; article; cancer registry; cancer risk; cancer screening; child; clinical evaluation; clinical examination; colorectal cancer; controlled study; data analysis; data collection method; ethnic group; female; follow up; health behavior; human; hypothesis; illness trajectory; major clinical study; male; randomized controlled trial; relative; sample; self report; United States

Racial disparities in traumatic stress in prostate cancer patients: Secondary analysis of a National URCC CCOP Study of 317 men - Purnell, J.Q.; Palesh, O.G.; Heckler, C.E.; Adams, M.J.; Chin, N.; Mohile, S.; Peppone, L.J.; Atkins, J.N.; Moore, D.F.; Spiegel, D.; Messing, E.; Morrow, G.R. (Supportive Care in Cancer, 2011)
Introduction African American men have the highest rates of prostate cancer of any racial group, but very little is known about the psychological functioning of African American men in response to prostate cancer diagnosis and treatment. Purpose In this secondary analysis of a national trial testing a psychological intervention for prostate cancer patients, we report on the traumatic stress symptoms of African American and non-African American men. Methods This analysis includes 317 men (African American: n=30, 9%; non-African American: n=287, 91%) who were enrolled in the intervention trial, which included 12 weeks of group psychotherapy and 24 months of follow-up. Using mixed model analysis, total score on the Impact of Events Scale (IES) and its Intrusion and Avoidance subscales were examined to determine mean differences in traumatic stress across all time points (0, 3, 6, 12, 18, and 24 months). In an additional analysis, relevant psychosocial, demographic, and clinical variables were added to the model. Results Results showed significantly higher levels of traumatic stress for African American men compared to non-African American men in all models independently of the intervention arm, demographics, and relevant clinical variables. African Americans also had a consistently higher prevalence of clinically significant traumatic stress symptoms (defined as IES total score ≥27). These elevations remained across all time points over 24 months. Conclusions This is the first study to showa racial disparity in traumatic stress specifically as an aspect of overall psychological adjustment to prostate cancer. Recommendations are made for appropriate assessment, referral, and treatment of psychological distress in this vulnerable population. © 2011 Springer-Verlag.
Keywords: bicalutamide; flutamide; gonadorelin agonist; adult; African American; aged; article; cancer staging; controlled study; demography; educational status; employment status; follow up; group therapy; human; Impact of Events Scale; income; major clinical study; male; marriage; orchiectomy; patient education; posttraumatic stress disorder; prevalence; priority journal; Profile of Mood States; prostate cancer; psychotherapy; race difference; randomized controlled trial; secondary analysis; social psychology; time

Engaging African American breast cancer survivors in an intervention trial: Culture, responsiveness and community - Germino, B.B.; Mishel, M.H.; Alexander, G.R.; Jenerette, C.; Blyler, D.; Baker, C.; Vines, A.I.; Green, M.; Long, D.G. (Journal of Cancer Survivorship, 2011)
Introduction: Younger breast cancer survivors often lead extremely busy lives with multiple demands and responsibilities, making them difficult to recruit into clinical trials. African American women are even more difficult to recruit because of additional historical and cultural barriers. In a randomized clinical trial of an intervention, we successfully used culturally informed, population-specific recruitment and retention strategies to engage younger African-American breast cancer survivors. Methods: Caucasian and African American breast cancer survivors were recruited from multiple communities and sites. A variety of planned recruitment and retention strategies addressed cultural and population-specific barriers and were guided by three key principals: increasing familiarity with the study in the communities of interest; increasing the availability and accessibility of study information and study participation; and using cultural brokers. Results: Accrual of younger African-American breast cancer survivors increased by 373% in 11 months. The steepest rise in the numbers of African-American women recruited came when all strategies were in place and operating simultaneously. Retention rates were 87% for both Caucasian and African American women. Discusssion/Conclusions: To successfully recruit busy, younger African American cancer survivors, it is important to use a multifaceted approach, addressing cultural and racial/ethnic barriers to research participation; bridging gaps across cultures and communities; including the role of faith and beliefs in considering research participation; recognizing the demands of different life stages and economic situations and the place of research in the larger picture of peoples' lives. Designs for recruitment and retention need to be broadly conceptualized and specifically applied. Implications for Cancer Survivors: For busy cancer survivors, willingness to participate in and complete research participation is enhanced by strategies that address barriers but also acknowledge the many demands on their time by making research familiar, available, accessible and credible. © 2010 Springer Science+Business Media, LLC.
Keywords: African American; article; breast tumor; carcinoma; communication disorder; counseling; cultural anthropology; demography; ethnology; evaluation study; fear; female; health care delivery; human; methodology; patient attitude; patient selection; physiology; psychological aspect; psychotherapy; randomized controlled trial (topic); recurrent disease; statistics; survivor

Effectiveness of a web-based colorectal cancer screening patient decision aid: A randomized controlled trial in a mixed-literacy population - Miller Jr., D.P.; Spangler, J.G.; Case, L.D.; Goff Jr., D.C.; Singh, S.; Pignone, M.P. (American Journal of Preventive Medicine, 2011)
Background: Colorectal cancer (CRC) screening reduces mortality yet remains underutilized. Low health literacy may contribute to this underutilization by interfering with patients' ability to understand and receive preventive health services. Purpose: To determine if a web-based multimedia CRC screening patient decision aid, developed for a mixed-literacy audience, could increase CRC screening. Design: RCT. Patients aged 5074 years and overdue for CRC screening were randomized to the web-based decision aid or a control program seen immediately before a scheduled primary care appointment. Setting/participants: A large community-based, university-affiliated internal medicine practice serving a socioeconomically disadvantaged population. Main outcome measures: Patients completed surveys to determine their ability to state a screening test preference and their readiness to receive screening. Charts were abstracted by masked observers to determine if screening tests were ordered and completed. Results: Between November 2007 and September 2008, a total of 264 patients enrolled in the study. Data collection was completed in 2009, and data analysis was completed in 2010. A majority of participants (mean age=57.8 years) were female (67%), African-American (74%), had annual household incomes of <$20,000 (76%), and had limited health literacy (56%). When compared to control participants, more decision-aid participants had a CRC screening preference (84% vs 55%, p<0.0001) and an increase in readiness to receive screening (52% vs 20%, p=0.0001). More decision-aid participants had CRC screening tests ordered (30% vs 21%) and completed (19% vs 14%), but no statistically significant differences were seen (AOR=1.6, 95% CI=0.97, 2.8, and AOR=1.7, 95% CI=0.88, 3.2, respectively). Similar results were found across literacy levels. Conclusions: The web-based decision aid increased patients' ability to form a test preference and their intent to receive screening, regardless of literacy level. Further study should examine ways the decision aid can be combined with additional system changes to increase CRC screening. © 2011 American Journal of Preventive Medicine.
Keywords: NCT00558233; adult; African American; aged; article; cancer screening; colorectal cancer; controlled study; female; health survey; human; income; information literacy; Internet; major clinical study; male; medical decision making; medical practice; outcome assessment; population research; primary medical care; reading

A pilot phase II trial of magnesium supplements to reduce menopausal hot flashes in breast cancer patients - Park, H.; Parker, G.L.; Boardman, C.H.; Morris, M.M.; Smith, T.J. (Supportive Care in Cancer, 2011)
Background We tested if magnesium would diminish bothersome hot flashes in breast cancer patients. Methods Breast cancer patients with at least 14 hot flashes a week received magnesium oxide 400 mg for 4 weeks, escalating to 800 mg if needed. Hot flash score (frequency× severity) at baseline was compared to the end of treatment. Results Of 29 who enrolled, 25 women completed treatment. The average age was 53.5 years; six African American, the rest Caucasian; eight were on tamoxifen, nine were on aromatase inhibitors, and 14 were on antidepressants. Seventeen patients escalated the magnesium dose. Hot flash frequency/week was reduced from 52.2 (standard error (SE), 13.7) to 27.7 (SE, 5.7), a 41.4% reduction, p=0.02, two-sided paired t test. Hot flash score was reduced from 109.8 (SE, 40.9) to 47.8 (SE, 13.8), a 50.4% reduction, p=0.04. Of 25 patients, 14 (56%) had a >50% reduction in hot flash score, and 19 (76%) had a >25% reduction. Fatigue, sweating, and distress were all significantly reduced. Side effects were minor: two women stopped the drug including one each with headache and nausea, and two women had grade 1 diarrhea. Compliance was excellent, and many patients continued treatment after the trial. Conclusions Oral magnesium appears to have helped more than half of the patients and was well tolerated. Side effects and cost ($0.02/tablet) were minimal. A randomized placebo-controlled trial is planned. © 2011 Springer-Verlag.
Keywords: antidepressant agent; aromatase inhibitor; magnesium oxide; tamoxifen; adult; African American; aged; article; bedtime dosage; breast cancer; cancer patient; Caucasian; clinical article; constipation; controlled study; depression; diarrhea; distress syndrome; drug cost; drug dose escalation; drug response; drug withdrawal; fatigue; female; headache; hot flush; human; menopause; mood change; nausea; patient compliance; phase 2 clinical trial; priority journal; scoring system; side effect; sweating

Colorectal cancer screening among ethnically diverse, low-income patients: A randomized controlled trial - Lasser, K.E.; Murillo, J.; Lisboa, S.; Casimir, A.N.; Shah, L.V.; Emmons, K.M.; Fletcher, R.H.; Ayanian, J.Z. (Archives of Internal Medicine, 2011)
Background: Patient navigators may increase colorectal cancer (CRC) screening rates among adults in underserved communities, but prior randomized trials have been small or conducted at single sites and have not included substantial numbers of Haitian Creole-speaking or Portuguese- speaking patients. Methods: We identified 465 primary care patients from 4 community health centers and 2 public hospital- based clinics who were not up-to-date with CRC screening and spoke English, Haitian Creole, Portuguese, or Spanish as their primary language. We enrolled participants from September 1, 2008, through March 31, 2009, and followed them up for 1 year after enrollment. We randomly allocated patients to receive a patient navigation- based intervention or usual care. Intervention patients received an introductory letter from their primary care provider with educational material, followed by telephone calls from a language-concordant navigator. The navigators offered patients the option of being screened by fecal occult blood testing or colonoscopy. The primary outcome was completion of any CRC screening within 1 year. Secondary outcomes included the proportions of patients screened by colonoscopy who had adenomas or cancer detected. Results: During a 1-year period, intervention patients were more likely to undergo CRC screening than control patients (33.6% vs 20.0%; P<.001), to be screened by colonoscopy (26.4% vs 13.0%; P<.001), and to have adenomas detected (8.1% vs 3.9%; P=.06). In prespecified subgroup analyses, the navigator intervention was particularly beneficial for patients whose primary language was other than English (39.8% vs 18.6%; P<.001) and black patients (39.7% vs 16.7%; P=.004). Conclusions: Patient navigation increased completion of CRC screening among ethnically diverse patients. Targeting patient navigation to black and non-Englishspeaking patients may be a useful approach to reducing disparities in CRC screening. © 2011 American Medical Association.
Keywords: NCT01141114; adult; aged; article; cancer diagnosis; cancer patient; cancer screening; colonoscopy; colorectal adenoma; colorectal cancer; controlled study; ethnic group; female; health care personnel; human; intervention study; lowest income group; major clinical study; male; multicenter study; occult blood test; outcome assessment; patient care; primary medical care; priority journal; public hospital; randomized controlled trial; telephone

Recruitment and early retention of women with advanced breast cancer in a complementary and alternative medicine trial - Wyatt, G.K.; Sikorskii, A.; Siddiqi, A.-E.-A.; Tamkus, D. (Evidence-based Complementary and Alternative Medicine, 2011)
More than 80 of women with breast cancer are now reported to be using complementary and alternative medicine (CAM) therapies during conventional treatment. A randomized clinical trial (RCT) of reflexology with late stage breast cancer patients serves as the data source for this article. The purposes were to investigate: (i) reasons for refusal to participate in a RCT of reflexology; (ii) the differences between those who completed the baseline interview and those who dropped out before baseline; and (iii) the utility of the Palliative Prognostic Score (PPS) as a prognostic screening tool in minimizing early attrition (before baseline) from the trial. Eligible women (N = 400) approached at 12 cancer centers in the Midwest had advanced breast cancer, were on chemotherapy or hormonal therapy, and had a PPS of 11 or less. Comparisons of those who dropped out early (N = 33) to those who stayed in the trial (N = 240) were carried out using Wilcoxon rank, t-, chi-squared and Fisher's exact tests. The reasons of being too sick or overwhelmed were given by less than 12 of the women who refused to participate. There was a higher early dropout rate among black women compared to other (primarily white) women (P =.01). Cancer recurrence and metastasis, age, and the PPS were not predictive of early retention of women. Specialized techniques may be needed to ensure black women remain in the trial once consented. Women with advanced disease were likely to enter and remain in the trial despite deterioration in health. Copyright © 2011 Alla Sikorskii et al.
Keywords: adult; alternative medicine; article; breast cancer; cancer center; cancer chemotherapy; cancer recurrence; chi square distribution; controlled study; deterioration; female; Fisher exact test; hormonal therapy; human; interview; major clinical study; priority journal; prognosis; randomized controlled trial; reflexology; screening; Wilcoxon signed ranks test

Reproductive history and oral contraceptive use in relation to risk of triple-negative breast cancer - Phipps, A.I.; Chlebowski, R.T.; Prentice, R.; McTiernan, A.; Wactawski-Wende, J.; Kuller, L.H.; Adams-Campbell, L.L.; Lane, D.; Stefanick, M.L.; Vitolins, M.; Kabat, G.C.; Rohan, T.E.; et al. (Journal of the National Cancer Institute, 2011)
Background Triple-negative (ie, estrogen receptor [ER], progesterone receptor, and HER2 negative) breast cancer occurs disproportionately among African American women compared with white women and is associated with a worse prognosis than ER-positive (ER+) breast cancer. Hormonally mediated risk factors may be differentially related to risk of triple-negative and ER+ breast cancers. Methods Using data from 155723 women enrolled in the Women's Health Initiative, we assessed associations between reproductive and menstrual history, breastfeeding, oral contraceptive use, and subtype-specific breast cancer risk. We used Cox regression to evaluate associations with triple-negative (N = 307) and ER+ (N = 2610) breast cancers and used partial likelihood methods to test for differences in subtype-specific hazard ratios (HRs). Results Reproductive history was differentially associated with risk of triple-negative and ER+ breast cancers. Nulliparity was associated with decreased risk of triple-negative breast cancer (HR = 0.61, 95% confidence interval [CI] = 0.37 to 0.97) but increased risk of ER+ breast cancer (HR = 1.35, 95% CI = 1.20 to 1.52). Age-adjusted absolute rates of triple-negative breast cancer were 2.71 and 1.54 per 10000 person-years in parous and nulliparous women, respectively; by comparison, rates of ER+ breast cancer were 21.10 and 28.16 per 10000 person-years in the same two groups. Among parous women, the number of births was positively associated with risk of triple-negative disease (HR for three births or more vs one birth = 1.46, 95% CI = 0.82 to 2.63) and inversely associated with risk of ER+ disease (HR = 0.88, 95% CI = 0.74 to 1.04). Ages at menarche and menopause were modestly associated with risk of ER+ but not triple-negative breast cancer; breastfeeding and oral contraceptive use were not associated with either subtype. Conclusion The association between parity and breast cancer risk differs appreciably for ER+ and triple-negative breast cancers. These findings require further confirmation because the biological mechanisms underlying these differences are uncertain. © 2011 The Author. Published by Oxford University Press. All rights reserved.
Keywords: estrogen; estrogen receptor; gestagen; oral contraceptive agent; adult; aged; article; birth; breast cancer; breast feeding; cancer diagnosis; cancer hormone therapy; cancer incidence; cancer risk; clinical assessment; controlled study; female; hazard ratio; human; major clinical study; menarche; menopause; menstrual cycle; multicenter study; nullipara; oral contraception; priority journal; randomized controlled trial; reproduction; risk factor; women's health

Cancer screening behaviors of african american women enrolled in a community-based cancer prevention trial - Reiter, P.L.; Linnan, L.A. (Journal of Women's Health, 2011)
Background: African American women have increased mortality rates for cervical, breast, and colorectal cancers, yet not all receive the recommended screening tests for these cancers. We characterized the cancer screening behaviors of African American women enrolled in a community-based cancer prevention trial. Methods: We examined cross-sectional data from 1123 African American customers aged ≥18 years from 37 beauty salons in North Carolina who completed the North Carolina BEAUTY and Health Project baseline survey. Mixed logistic regression models were used to identify correlates of receiving cervical, breast, and colorectal cancer screening tests within recommended screening guidelines. Results: Overall, 94% (1026 of 1089) of women aged ≥18 years reported receiving a Pap smear test within the last 3 years, 70% (298 of 425) of women aged ≥40 years reported receiving a mammography within the last year, and 64% (116 of 180) of women aged ≥50 years were considered to be within recommended screening guidelines for colorectal cancer. Age was correlated with recent Pap smear testing and mammography. Women who reported receiving a recent Pap smear test were more likely to report a mammogram in the last year, and women with a recent mammogram were more likely to be within recommended screening guidelines for colorectal cancer. Many women reported multiple barriers to getting recommended cancer screening tests. Conclusions: Almost all women reported receiving a Pap smear test within the last 3 years. Future interventions should focus on increasing breast and colorectal cancer screening among African American women. © Copyright 2011, Mary Ann Liebert, Inc.
Keywords: adult; African American; age; aged; article; breast cancer; cancer prevention; cancer screening; colorectal cancer; community based rehabilitation; controlled study; correlation analysis; female; human; logistic regression analysis; major clinical study; mammography; Papanicolaou test; practice guideline; priority journal; United States; uterine cervix cancer

A pilot trial of decision aids to give truthful prognostic and treatment information to chemotherapy patients with advanced cancer - Smith, T.J.; Dow, L.A.; Virago, E.A.; Khatcheressian, J.; Matsuyama, R.; Lyckholm, L.J. (Journal of Supportive Oncology, 2011)
Most cancer patients do not have an explicit discussion about prognosis and treatment despite documented adverse outcomes. Few decision aids have been developed to assist the difficult discussions of palliative management. We developed decision aids for people with advanced incurable breast, colorectal, lung, and hormone-refractory prostate cancers facing first-, second-, third-, and fourth-line chemotherapy. We recruited patients from our urban oncology clinic after gaining the permission of their treating oncologist. We measured knowledge of curability and treatment benefit before and after the intervention. Twenty-six of 27 (96%) patients completed the aids, with a mean age of 63, 56% female, 56% married, 56% African American, and 67% with a high school education or more. Most patients (14/27, 52%) thought a person with their advanced cancer could be cured, which was reduced (to 8/26, 31%, P = 0.15) after the decision aid. Nearly all overestimated the effect of palliative chemotherapy. No distress was noted, and hope did not change. The majority (20/27, 74%) found the information helpful to them, and almost all (25/27, 93%) wanted to share the information with their family and physicians. It is possible to give incurable patients their prognosis, treatment options, and options for improving end-of-life care without causing distress or lack of hope. Almost all find the information helpful and want to share it with doctors and family. Research is needed to test the findings in a larger sample and measure the outcomes of truthful information on quality of life, quality of care, and costs. © 2011 Elsevier Inc.
Keywords: adult; advanced cancer; African American; aged; article; breast cancer; cancer chemotherapy; cancer palliative therapy; clinical article; clinical trial; colorectal cancer; decision support system; distress syndrome; educational status; female; hope; human; lung cancer; male; medical information; outcome assessment; pilot study; prognosis; prostate cancer

A review of African American-white differences in risk factors for cancer: Prostate cancer - Mordukhovich, I.; Reiter, P.L.; Backes, D.M.; Family, L.; McCullough, L.E.; O'Brien, K.M.; Razzaghi, H.; Olshan, A.F. (Cancer Causes and Control, 2011)
Objective African American men have higher prostate cancer incidence rates than White men, for reasons not completely understood. This review summarizes the existing literature of race-specific associations between risk factors and prostate cancer in order to examine whether associations differ. Methods We reviewed epidemiologic studies published between January 1970 and December 2008 that reported race-specific effect estimates. We focused mainly on modifiable risk factors related to lifestyle and health. A total of 37 articles from 21 study populations met our inclusion criteria. Results We found no evidence of racial differences in associations between prostate cancer and alcohol intake, tobacco use, and family history of prostate cancer. Research suggests that a modest positive association may exist between height and prostate cancer risk (all prostate cancer and advanced prostate cancer) among Whites only. No clear patterns were observed for associations with physical activity, weight/body mass index, dietary factors, occupational history, sexual behavior, sexually transmissible infections, and other health conditions. Discussion Our results suggest few differences in prostate cancer risk factors exist between racial groups and underscore areas where additional research is needed. Future studies should enroll higher numbers of African American participants and report results for advanced prostate cancer. © Springer Science+Business Media B.V. 2010.
Keywords: advanced cancer; African American; alcohol consumption; article; body mass; body weight; cancer risk; Caucasian; cigarette smoking; family history; health hazard; human; lifestyle; occupational hazard; physical activity; population research; priority journal; prostate cancer; race difference; risk assessment; sexual behavior; sexually transmitted disease

The neoadjuvant approach in breast cancer treatment: It is not just about chemotherapy anymore - Caudle, A.S.; Hunt, K.K. (Current Opinion in Obstetrics and Gynecology, 2011)
Purpose of Review: Although the use of neoadjuvant chemotherapy (NCT) in breast cancer was once reserved for patients with locally advanced disease or inflammatory breast cancers, it is increasingly used in patients with early-stage tumors. This review outlines the pertinent research in the field over the last year and discusses the clinical implications. Recent Findings: The present review will focus on three evolving areas in the neoadjuvant research field: factors determining response, use of endocrine and biologic therapies, and how to manage patients following response. Summary: NCT in breast cancer is a remarkable research platform providing insight into tumor biology and treatment efficacy in an expedited timeframe. Refining patient selection based on tumor and patient characteristics allows clinicians to limit potentially toxic therapy to those patients expected to receive the greatest benefit. Additionally, exploring new agents and sequencing of regimens based on these characteristics has great potential for impacting local-regional and systemic outcomes. Lastly, as the population of patients undergoing NCT grows, we must constantly adjust our treatment paradigms. We need to monitor them carefully and accurately, understand the implication of a treated tumor for future therapy, and determine how much additional therapy is necessary. © 2011 Wolters Kluwer Health | Lippincott Williams & Wilkins.
Keywords: doxorubicin; epidermal growth factor receptor 2; estrogen receptor; fluorodeoxyglucose; letrozole; metformin; nicotinamide adenine dinucleotide adenosine diphosphate ribosyltransferase inhibitor; progesterone receptor; trastuzumab; adjuvant chemotherapy; advanced cancer; African American; article; axillary lymph node; breast cancer; breast carcinoma; breast conservation therapy; cancer chemotherapy; cancer hormone therapy; cancer patient; cancer radiotherapy; cancer research; cancer therapy; diabetes mellitus; drug efficacy; event free survival; heart failure; human; breast carcinoma; lobular carcinoma; lymph node dissection; mammography; mastectomy; nuclear magnetic resonance imaging; patient monitoring; patient selection; phase 2 clinical trial (topic); positron emission tomography; postoperative care; priority journal; risk factor; sentinel lymph node biopsy; treatment response; tumor volume; herceptin

Expanding colorectal cancer screening among minority women - Shike, M.; Schattner, M.; Genao, A.; Grant, W.; Burke, M.; Zauber, A.; Russo, L.; Cuyjet, V. (Cancer, 2011)
BACKGROUND: Colorectal cancer screening (CRCS) in the United States is inadequate in minority communities and particularly among those who lack insurance. Finding ways to increase screenings in these minorities presents a healthcare challenge. The authors sought to determine whether offering CRCS at the time of mammography is an effective way to increase CRCS among minority women. METHODS: This study was offered to women attending the Breast Examination Center of Harlem (BECH), a community outreach program of Memorial Sloan-Kettering serving the primarily black and Hispanic Harlem Community. Screening was explained, medical fitness was determined, and colonoscopies were performed. Barriers to screening and ways to overcome them were ascertained. Participants had to be at least 50 years of age without a history of colorectal cancer or screening within the last 10 years. RESULTS: There were 2616 women eligible for CRCS, of these women 2005 (77%) refused to participate in the study, and 611 (23%) women were enrolled. There was a high interest in CRCS including among those who declined to participate in the study. The major barrier was lack of medical insurance, which was partially overcome by alternative funding. Of the 611 women enrolled, 337 (55%) went on to have screening colonoscopy. Forty-nine (15%) women had adenomatous polyps. CONCLUSIONS: Offering CRCS to minority women at the time of mammography and without a physician's referral is an effective way to expand screening. Screening colonoscopy findings are similar to those in the general population. Alternatives to traditional medical insurance are needed for the uninsured. © 2010 American Cancer Society.
Keywords: NCT00613873; adenomatous polyp; adult; African American; aged; article; cancer screening; colonoscopy; colorectal cancer; controlled study; family history; female; gastrointestinal symptom; health insurance; Hispanic; human; mammography; minority group; patient referral; patient satisfaction; priority journal; refusal to participate; United States; women's health

The Attitudes, communication, treatment, and support intervention to reduce breast cancer treatment disparity - Rosenzweig, M.; Brufsky, A.; Rastogi, P.; Puhalla, S.; Simon, J.; Underwood, S. (Oncology Nursing Forum, 2011)
Purpose/Objectives: to Test the Effect of A Supportive, One-time Psychoeducational Intervention on Treatm. Adherence among African Amer. Women Rec. First Adjuvant Ther. for Breast Cancer. Des.: A Pilot, Randomized, Controlled Clin. Trial, Two-Grp. Des., with One-time Intervention and Four Data Collec. Points. Setting: Two Univ. of Pittsburgh Cancer Inst. Clinics. Sample: 24 African Amer. Women. Methods: the Attitudes, Commun., Treatm., and Support Intervention Is A 45-minute One-on-one Session with An African Amer. Woman Recommended to Have Chemother. for Breast Cancer. the Interventionist Is An African Amer. Breast Cancer Survivor. the Intervention Consists of A Discussion about Chemother. and the Importance of Communicating Knowledge Needs and Distress, An Explanation of the Specific Treatm. Plan Acc. to Pathol., and Support Through the Survivor Testimonial and Video Clips from the African Amer. Comm.. Main Res. Variables: Dose of Chemother. Received and Dose of Chemother. Prescribed. Findings: Twenty Patients Completed Chemother., and Four Chose Not to Begin or Discontinued Recommended Chemother.. the Groups Were Equal in Key Sociodemographic Variables. Compared to Usual Care, the ACTS Intervention Participants Demonstrated Trends Toward Initiation of Chemother. , Overall Adherence to Chemother. , and Percentage of Total Dose of Chemother. Received or Prescribed . Compared to Usual Care, the ACTS Intervention Participants Demonstrated More Rapid Initiation of Chemother. and Better Overall Adherence to Chemother.. Conclusions: the Pilot ACTS Intervention Shows Promise As A Psychoeducational Intervention to Assist with Chemother. Decis. Making among African Amer. Women. Implications for Nursing: African Amer. Women Are at High Risk of Not Rec. the Full Dose of Prescribed Chemother. for Breast Cancer for Multiple Reasons. Nurses Must Be Sensitive to the Unique Fears and Concerns of This Pop. Regarding Chemother. Decisions. An Intervention Addressing These Fears and Concerns May Help to Increase Adherence.
Keywords: antineoplastic agent; adjuvant chemotherapy; adult; African American; article; attitude to health; breast tumor; clinical trial; controlled clinical trial; controlled study; female; health care disparity; human; methodology; middle aged; nurse patient relationship; nursing; oncology nursing; patient education; patient participation; pilot study; psychological aspect; randomized controlled trial; social support

Differential association of cytochrome p450 3a4 genotypes with onsets of breast tumors in african american versus caucasian patients - McDaniel, D.O.; Thurber, T.; Lewis-Traylor, A.; Berry, C.; Barber, W.H.; Zhou, X.; Bigler, S.; Vance, R. (Journal of Investigative Medicine, 2011)
Introduction: Malignant breast tumors are often hormone-dependent, and to this end, both estrogen and progesterone receptors are good prognostic markers for evaluation of the outcomes after therapy. In addition, HER-2/neu, whose expression is increasingly being associated with poor prognosis of breast cancer, has predictive potential after immunotherapy. Cytochrome P450 3A4 is highly involved in the metabolism of steroids. Thus, we investigated the impact of CYP 3A4 gene variants in association with clinical outcomes in African American (AFAM) versus Caucasian (CAU) patients with breast cancer diagnosis. Methods: Patients who had undergone biopsy procedures for diagnosis or for partial or radical mastectomy were recruited. The CYP 3A4 genotypes (A or G) were detected using polymerase chain reaction amplification and primers designed for a single nucleotide polymorphism. The messenger RNA (mRNA) transcriptswere screened by reverse transcription- polymerase chain reaction. Clinical data including tumor staging, pathology grades, and family history were evaluated. Results: Frequency of the CYP 3A4-G (mutated variant) was significantly increased in AFAMpatients as compared with controls (P < 0.001). No statistically significant difference was observed between the genotypes comparing the benign versus ductal carcinomas in situ (DCIS) or infiltrating ductal carcinomas (IDCAs). In AFAM patients, GG alleles were increased in IDCA with stage III tumors, and in CAU patients, the AA alleles were increased with stage III tumors. The mRNA expression was reduced in patients with IDCA versus DCIS or benign tumors (benign vs IDCA, P < 0.0009; DCIS vs IDCA, P G 0.005), as well in HER-2/ neuYpositive tumors versus samples negative for receptors (P < 0.0024). Conclusions: Genotype association was affected by race. Expression levels of total CYP 3A4 mRNA were inversely correlated with clinical diagnosis. This may suggest mRNA testing as an additional tool that accelerates improvement in the diagnosis of the onsets of breast cancer. Copyright © 2011 by The American Federation for Medical Research.
Keywords: cytochrome P450 3A4; estrogen receptor; messenger RNA; progesterone receptor; adult; African American; article; breast tumor; Caucasian; controlled study; disease association; female; gene expression; genotype; human; human tissue; immunohistochemistry; major clinical study; polymerase chain reaction; race difference; reverse transcription polymerase chain reaction; single nucleotide polymorphism

Magnifying gastroscopy using a soft black hood for difficult colonoscopy - Nakamura, H.; Fu, K.; Yamamura, A. (Surgical Endoscopy, 2011)
Background Various methods are reported as aids to cecal intubation for cases in which colonoscopy is difficult. This study aimed to investigate prospectively whether a gastroscope with magnification function, narrow-band imaging (NBI), and a soft black hood can aid insertion in cases of difficult colonoscopy and facilitate both accurate diagnosis and safe treatment. Methods This prospective study recruited 177 patients. All were examined with a magnifying gastroscope. A commercially available soft black hood was attached to the gastroscope during insertion and magnification. Difficult colonoscopy was anticipated before colonoscopy in cases of patients with at least one of the following factors: low BMI (<20 kg/m2), adhesion due to previous surgery, or previous colonoscopy that could not reach to the cecum. The success rate and duration of cecal intubation then were assessed. All detected lesions were evaluated by magnifying NBI and then classified as non-neoplastic or neoplastic for endoscopic diagnosis. Subsequently, all the lesions were removed and examined histologically for comparison. Results The overall success rate of cecal intubation was 100% (177/177), and the mean time taken to reach the cecum was 5.9 min. A total of 156 lesions were detected endoscopically, and the overall diagnostic accuracy of NBI with magnification was 98.7%. No associated complications occurred. Conclusion Magnifying gastroscopy using a soft black hood and NBI is useful for cecal intubation in cases wherein colonoscopy is difficult, facilitating accurate diagnosis and safe treatment. © 2011 Springer Science+Business Media, LLC.
Keywords: adult; aged; article; body mass; carcinoid; clinical effectiveness; clinical evaluation; colon adenoma; colon cancer; colon polyp; colonoscopy; controlled clinical trial; controlled study; diagnostic accuracy; digestive tract intubation; disease association; disease classification; female; gastroscopy; histopathology; human; human tissue; major clinical study; male; medical device; narrow band imaging; outcome assessment; patient safety; predictive value; priority journal; sensitivity and specificity

Educational inequalities in quantity, duration and type of tobacco consumption among lung cancer patients in Asturias: Epidemiological analyses - Leader, A.; Fernández-Somoano, A.; López-Cima, M.F.; González-Arriaga, P.; Pascual, T.; Marrón, M.G.; Tardón, A. (Psicothema, 2010)
Socioeconomic inequalities cause different tobacco consumption patterns. The purpose of this study was to examine the relationship between educational level and smoking behaviour, including type of tobacco consumption, in lung cancer patients. To this end, epidemiological analyses of 801 lung cancer patients recruited for a case-control study in four public hospitals in Asturias, Spain, between October 2000 and April 2006 were carried out. Smoking behaviour and educational level data were obtained through personal interview. Analyses indicated that the probability of heavy smoking among low educational-level patients was approximately twice as high as for high educational-level patients (RRR>31.2packs/years = 2.04; CI 95%= 1.15-3.62; RRR>52packs/years= 2.14; CI 95%= 0.98-4.64). Low-educated patients were more than three times as likely to be long-time smokers (RRR>40years = 3.30; CI 95%= 1.43-7.62). The probability of smoking exclusively black tobacco was almost four times greater in low educational-level patients (RRRblack only= 3.72; CI 95%= 1.23-11.19). The results show that there are broad educational inequalities with regard to the quantity, duration and type of tobacco consumption among lung cancer patients in Northern Spain. © 2010 Psicothema.
Keywords: aged; article; case control study; clinical trial; comparative study; educational status; female; human; lung tumor; male; middle aged; multicenter study; smoking; smoking cessation; socioeconomics; Spain; statistics; time

Fruit and vegetable intake in relation to risk of breast cancer in the black women's health study - Boggs, D.A.; Palmer, J.R.; Wise, L.A.; Spiegelman, D.; Stampfer, M.J.; Adams-Campbell, L.L.; Rosenberg, L. (American Journal of Epidemiology, 2010)
The authors prospectively examined the relation of fruit and vegetable intake to breast cancer risk among 51,928 women aged 21-69 years at enrollment in 1995 in the Black Women's Health Study. Dietary intake was assessed by using a validated food frequency questionnaire. Cox proportional hazards models were used to estimate incidence rate ratios and 95% confidence intervals, adjusted for breast cancer risk factors. During 12 years of follow-up, there were 1,268 incident cases of breast cancer. Total fruit, total vegetable, and total fruit and vegetable intakes were not significantly associated with overall risk of breast cancer. However, total vegetable consumption was associated with a decreased risk of estrogen receptor-negative/progesterone receptor-negative breast cancer (incidence rate ratio = 0.57, 95% confidence interval: 0.38, 0.85, for ≥2 servings/day relative to <4/week; Ptrend = 0.02). In addition, there was some evidence of inverse associations with breast cancer risk overall for cruciferous vegetable intake (Ptrend = 0.06) and for carrot intake (Ptrend = 0.02). Study findings suggest that frequent consumption of vegetables is inversely associated with risk of estrogen receptor-negative/progesterone receptor-negative breast cancer, and that specific vegetables may be associated with a decreased risk of breast cancer overall. © 2010 The Author.
Keywords: estrogen receptor; progesterone receptor; adult; African American; aged; article; breast cancer; cancer risk; clinical evaluation; clinical trial; dietary intake; female; food frequency questionnaire; fruit; health food; human; incidence; major clinical study; nutritional assessment; portion size; proportional hazards model; prospective study; vegetable

Association between folate levels and CpG island hypermethylation in normal colorectal mucosa - Wallace, K.; Grau, M.V.; Levine, A.J.; Shen, L.; Hamdan, R.; Chen, X.; Gui, J.; Haile, R.W.; Barry, E.L.; Ahnen, D.; McKeown-Eyssen, G.; Baron, J.A.; et al. (Cancer Prevention Research, 2010)
Gene-specific promoter methylation of several genes occurs in aging normal tissues and may predispose to tumorigenesis. In the present study, we investigate the association of blood folate levels and dietary and lifestyle factors with CpG island (CGI) methylation in normal colorectal mucosa. Subjects were enrolled in a multicenter chemoprevention trial of aspirin or folic acid for the prevention of large bowel adenomas. We collected 1,000 biopsy specimens from 389 patients, 501 samples from the right colon and 499 from the rectum at the follow-up colonoscopy. We measured DNA methylation of estrogen receptor alpha (ERα) and secreted frizzled related protein-1 (SFRP1), using bisulfite pyrosequencing. We used generalized estimating equations regression analysis to examine the association between methylation and selected variables. For both ERα and SFRP1, percentage methylation was significantly higher in the rectum than in the right colon (P = 0.001). For each 10 years of age, we observed a 1.7% increase in methylation level for ERα and a 2.9% increase for SFRP1 (P < 0.0001). African Americans had a significantly lower level of ERα and SFRP1 methylation than Caucasians and Hispanics. Higher RBC folate levels were associated with higher levels of both ERα (P = 0.03) and SFRP1 methylation (P = 0.01). Our results suggest that CGI methylation in normal colorectal mucosa is related to advancing age, race, rectal location, and RBC folate levels. These data have important implications regarding the safety of supplementary folate administration in healthy adults, given the hypothesis that methylation in normal mucosa may predispose to colorectal neoplasia. ©2010 AACR.
Keywords: acetylsalicylic acid; estrogen receptor alpha; folic acid; placebo; secreted frizzled related protein 1; adult; article; clinical trial; colonoscopy; colorectal cancer; controlled study; CpG island; demography; DNA methylation; double blind procedure; drug efficacy; ethnicity; female; heredity; human; large intestine cancer; lifestyle; major clinical study; male; multicenter study; priority journal; pyrosequencing; rectum mucosa; aspirin

A targeted decision aid for the elderly to decide whether to undergo colorectal cancer screening: development and results of an uncontrolled trial. - Lewis, C.L.; Golin, C.E.; DeLeon, C.; Griffith, J.M.; Ivey, J.; Trevena, L.; Pignone, M. (BMC medical informatics and decision making, 2010)
Competing causes of mortality in the elderly decrease the potential net benefit from colorectal cancer screening and increase the likelihood of potential harms. Individualized decision making has been recommended, so that the elderly can decide whether or not to undergo colorectal cancer (CRC) screening. The objective is to develop and test a decision aid designed to promote individualized colorectal cancer screening decision making for adults age 75 and over. We used formative research and cognitive testing to develop and refine the decision aid. We then tested the decision aid in an uncontrolled trial. The primary outcome was the proportion of patients who were prepared to make an individualized decision, defined a priori as having adequate knowledge (10/15 questions correct) and clear values (25 or less on values clarity subscale of decisional conflict scale). Secondary outcomes included overall score on the decisional conflict scale, and preferences for undergoing screening. We enrolled 46 adults in the trial. The decision aid increased the proportion of participants with adequate knowledge from 4% to 52% (p < 0.01) and the proportion prepared to make an individualized decision from 4% to 41% (p < 0.01). The proportion that preferred to undergo CRC screening decreased from 67% to 61% (p = 0. 76); 7 participants (15%) changed screening preference (5 against screening, 2 in favor of screening) In an uncontrolled trial, the elderly participants appeared better prepared to make an individualized decision about whether or not to undergo CRC screening after using the decision aid.
Keywords: aged; article; Caucasian; clinical trial; colonoscopy; colorectal tumor; decision support system; educational status; ethnology; female; health literacy; human; informed consent; male; mass screening; Black person; patient; patient education; patient selection; psychological aspect; statistics

Comparing narrative and informational videos to increase mammography in low-income African American women - Kreuter, M.W.; Holmes, K.; Alcaraz, K.; Kalesan, B.; Rath, S.; Richert, M.; McQueen, A.; Caito, N.; Robinson, L.; Clark, E.M. (Patient Education and Counseling, 2010)
Objective: Compare effects of narrative and informational videos on use of mammography, cancer-related beliefs, recall of core content and a range of reactions to the videos.Method: African American women (n=489) ages 40 and older were recruited from low-income neighborhoods in St. Louis, MO and randomly assigned to watch a narrative video comprised of stories from African American breast cancer survivors (Living Proof) or a content-equivalent informational video using a more expository and didactic approach (Facts for Life). Effects were measured immediately post-exposure and at 3- and 6-month follow-up.Results: The narrative video was better liked, enhanced recall, reduced counterarguing, increased breast cancer discussions with family members and was perceived as more novel. Women who watched the narrative video also reported fewer barriers to mammography, more confidence that mammograms work, and were more likely to perceive cancer as an important problem affecting African Americans. Use of mammography at 6-month follow-up did not differ for the narrative vs. informational groups overall (49% vs. 40%, p=.20), but did among women with less than a high school education (65% vs. 32%, p<.01), and trended in the same direction for those who had no close friends or family with breast cancer (49% vs. 31%, p=.06) and those who were less trusting of traditional cancer information sources (48% vs. 30%, p=.06).Conclusions: Narrative forms of communication may increase the effectiveness of interventions to reduce cancer health disparities.Practice implications: Narratives appear to have particular value in certain population sub-groups; identifying these groups and matching them to specific communication approaches may increase effectiveness. © 2010 Elsevier Ireland Ltd.
Keywords: adult; African American; article; cancer research; cancer survivor; clinical effectiveness; clinical trial; comparative effectiveness; controlled clinical trial; controlled study; educational status; female; follow up; health belief; health disparity; health education; human; human experiment; lowest income group; mammography; medical informatics; narrative; priority journal; randomized controlled trial; United States; videorecording; women's health

Patients' knowledge about 9 common health conditions: the DECISIONS survey. - Fagerlin, A.; Sepucha, K.R.; Couper, M.P.; Levin, C.A.; Singer, E.; Zikmund-Fisher, B.J. (Medical decision making : an international journal of the Society for Medical Decision Making, 2010)
To make informed decisions, patients must have adequate knowledge of key decision-relevant facts. To determine adults' knowledge about information relevant to common types of medication, screening, or surgery decisions they recently made. National sample of US adults identified by random-digit dialing. Cross-sectional survey conducted between November 2006 and May 2007. A total of 2575 English-speaking adults aged 40 y or older who reported having discussed the following medical decisions with a health care provider within the previous 2 y: prescription medications for hypertension, hypercholesterolemia, or depression; screening tests for colorectal, breast, or prostate cancer; or surgeries for knee/hip replacement, cataracts, or lower back pain. Participants answered knowledge questions and rated the importance of their health care provider, family/friends, and the media as sources of information. Accuracy rates varied widely across questions and decision contexts. For example, patients considering cataract surgery were more likely to correctly estimate recovery time than those patients considering lower back pain or knee/hip replacement (78% v. 29% and 39%, P < 0.001). Similarly, participants were more knowledgeable of facts about colorectal cancer screening than those who were asked about breast or prostate cancer. Finally, respondents were consistently more knowledgeable on comparable questions about blood pressure medication than cholesterol medication or antidepressants. The impact of demographic characteristics and sources of information also varied substantially. For example, blacks had lower knowledge than whites about cancer screening decisions (odds ratio [OR] = 0.57; 95% confidence interval [CI] = 0.43, 0.75; P = 0.001) and medication (OR = 0.77; 95% CI = 0.60, 0.97; P = 0.03) even after we controlled for other demographic factors. The same was not true for surgical decisions. The questions did not measure all knowledge relevant to informed decision making, were subject to recall biases, and may have assessed numeracy more than knowledge. Patient knowledge of key facts relevant to recently made medical decisions is often poor and varies systematically by decision type and patient characteristics. Improving patient knowledge about risks, benefits, and characteristics of medical procedures is essential to support informed decision making.
Keywords: prescription drug; adult; aged; article; attitude to health; confidence interval; cross-sectional study; decision making; early diagnosis; education; educational status; female; general surgery; human; male; middle aged; multivariate analysis; neoplasm; patient education; patient participation; risk; statistical model

Evaluating the relationships among psychological distress, executive cognitive function and economic factors on mammography use in unaffected African American women at risk for breast cancer - Laing, S.S.; Ocampo, C.; Harris, J.R. (Ethnicity and Disease, 2010)
Objective: Psychological distress impairs the cognitive function involved in planning and decision-making (executive cognitive function), and hinders engagement in health promoting behaviors. This study examined the relationship among distress, executive cognitive function (ECF) and mammography use in African American women at risk for breast cancer. Design: A cross-sectional sample of mammography screening adherers (n=44) and nonadherers (n=16) completed measures of psychological distress (Brief Symptom Inventory) and executive cognitive function, (Wisconsin Card Sort Task and Stroop Color Word Test). Results: More than one-quarter of the high-risk sample had high levels of distress. Distress scores explained 12% of the variance in two ECF components (abstract concept formation and cognitive flexibility), suggesting a significant relationship between psychological distress and cognitive function. Distress scores and ECF measures did not predict mammography use; employment status emerged as the strongest predictor of mammography screening (OR=4.36, 95% CI: 1.18-16.07). Conclusion: Elevated psychological distress is evident in high-risk African American women and appears to have an effect on the cognitive function involved in behavioral regulation and planning. Results also support the role of socioeconomic status as a significant predictor of mammography use.
Keywords: adult; African American; article; breast cancer; Brief Symptom Inventory; cancer risk; cancer screening; controlled study; correlation analysis; distress syndrome; employment status; executive function; female; health care utilization; human; major clinical study; mammography; patient participation; psychological aspect; socioeconomics; wisconsin card sort task and stroop color word test

Participation of older patients with prostate cancer in medicare eligible trials - Craig, B.M.; Gilbert, S.M.; Herndon, J.B.; Vogel, B.; Quinn, G.P. (Journal of Urology, 2010)
Purpose: On June 7, 2000 President Clinton issued an executive memorandum directing Medicare payment for routine patient care in qualifying clinical trials. We estimated the proportion of older patients with prostate cancer who were examined as part of a qualifying clinical trial, and the association between participation and patient characteristics. Materials and Methods: We performed an observational study using the Surveillance, Epidemiology and End Results Medicare database to determine participation in qualifying clinical trials in a sample of 37,216 men 66 years old or older who were enrolled in Medicare and diagnosed with prostate cancer between September 2000 and December 2002. Results: Within 3 years of diagnosis 211 men (0.567%) received routine patient care in a qualifying clinical trial. These participants were more likely to be younger than 70 years (OR 1.687, 95% CI 1.27-2.24) and less likely to be less educated and reside in low income, metropolitan neighborhoods. White men were more likely to participate in clinical trials than nonwhite men but this association was not statistically significant (OR 1.426, CI 0.97-2.09). Participation varied significantly by registry site (0% to 1.2%) but not by tumor grade or stage, or prostate specific antigen status. Conclusions: Few older patients with prostate cancer participated in qualifying trials between 2000 and 2002. Those who participated were not representative of the general population of older patients with prostate cancer. Greater efforts are required to expand trial enrollment and decrease disparities in research participation. © 2010 American Urological Association Education and Research, Inc.
Keywords: prostate specific antigen; African American; aged; article; cancer grading; cancer patient; cancer staging; educational status; European American; Hispanic; human; income; major clinical study; male; medicare; observational study; patient care; priority journal; prostate cancer; research subject

Successful subject recruitment for a prostate cancer behavioral intervention trial - Heiney, S.P.; Arp Adams, S.; Drake, B.F.; Bryant, L.H.; Bridges, L.; Hebert, J.R. (Clinical Trials, 2010)
Background Inadequate participant recruitment, which may lead to unrepresentative study samples that threaten a studys validity, is often a major challenge in the conduct of research studies. Purpose The purpose of this article is to describe the development and implementation of a recruitment plan and evaluate the different recruitment strategies for a prostate cancer behavioral intervention trial. Methods Our recruitment plan was based on a framework (The Heiney-Adams Recruitment Model) that we developed, which combines relationship building and social marketing. We evaluated the success of our model using several different recruitment sources including: mailed letters, physician referral, and self-referral. Results Recruitment rates ranged from 67% for a support services department mailing to 100% for physician referral. While our original list of contacted patients was comprised of only 13% African American (AA) men, 22% of our recruited participants were AA. Limitations One of the strongest barriers to recruitment was strict patient eligibility. Another significant barrier was the lack of electronic records systems to allow for the identification of large numbers of potential participants. Conclusions In conclusion, our model incorporating social marketing and relationship building was quite successful in recruiting for a prostate cancer behavioral study, particularly AA participants. In developing strategies, future researchers should attend to issues of staffing, financial resources, physician support, and eligibility criteria in the light of study accrual. © The Author(s), 2010.
Keywords: adult; aged; article; conceptual framework; controlled study; doctor patient relationship; health behavior; health care planning; human; intervention study; major clinical study; male; patient referral; patient selection; physician self-referral; postal mail; priority journal; prostate cancer; social marketing

African Americans' responses to genetic explanations of lung cancer disparities and their willingness to participate in clinical genetics research - White, D.B.; Koehly, L.M.; Omogbehin, A.; McBride, C.M. (Genetics in Medicine, 2010)
Purpose:To assess whether reactions to genetic explanations for disparities in lung cancer incidence among family members of African American patients with lung cancer are associated with willingness to participate in clinical genetics research. Methods: Data are reported for 67 self-identified African Americans aged 18 to 55 years who completed a telephone survey assessing reactions to explanations (i.e., genetics, toxin exposure, menthol cigarettes, and race-related stress) for lung cancer disparities. Majority were female (70%), current smokers (57%), and patients'biological relatives (70%). Results: Family members rated the four explanations similarly, each as believable, fair, and not too worrisome. Participants also indicated a high level of willingness to participate in genetics research (M = 4.1 ± 1.0; scale: 1-5). Endorsements of genetics explanations for disparities as believable and fair, and toxin exposure as believable were associated significantly with willingness to participate in genetics research. Conclusion: These results suggest that strategies to encourage African Americans'participation in genetics research would do well to inform potential participants of how their involvement might be used to better understand important environmental factors that affect health disparities. © 2010 Lippincott Williams & Wilkins.
Keywords: adult; African American; article; cancer incidence; cigarette smoking; clinical research; environmental exposure; female; health care disparity; human; lung cancer; major clinical study; male; patient attitude; patient participation; race difference

A comparison of white and african american outcomes from a three-arm, randomized, phase III multicenter trial of advanced or metastatic non-small cell lung cancer - Obasaju, C.K.; Ansari, R.H.; Socinski, M.A.; Chen, R.; Monberg, M.J.; Catalano, R.B.; Marinucci, D.M.; Liles, D.K.; Ribeiro, M.-J.; Comis, R.L.; Treat, J. (Journal of Thoracic Oncology, 2010)
PURPOSE: To investigate the effect of race on the efficacy and safety of standard chemotherapy doublet regimens in African American patients, we conducted a subgroup analysis of a phase III randomized trial. PATIENTS AND METHODS: Chemonaïve patients with a performance status of 0 or 1 and stage IIIB or IV non-small cell lung cancer were randomized to arm A: gemcitabine 1000 mg/m on days 1 and 8 plus carboplatin area under the curve 5.5 on day 1; arm B: the same schedule of gemcitabine plus paclitaxel 200 mg/m on day 1; or arm C: paclitaxel 225 mg/m on day 1 plus carboplatin area under the curve 6.0 on day 1. Cycles were repeated every 21 days up to 6. A site selection tool identified institutions with potential to recruit a minority population. Outcome and toxicity data of white and African American patients were compared. RESULTS: Of 1135 total patients, 972 were white (85.6%) and 138 were African American (12.2%). Median survival was 8.3 months for white patients (95% confidence interval [CI]: 7.7-9.3) and 9.1 months for African American patients (95% CI: 8.2-11.1). Response rates were 29.1 and 29.0%, respectively. Rates of grade 3 or 4 toxicities were comparable. Among African Americans, median survival was 7.2 months (95% CI: 5.1-10.1) for gemcitabine-carboplatin (n = 47), 10.5 months (95% CI: 7.1-15.4) for gemcitabine-paclitaxel (n = 42), and 10.2 months (95% CI: 8.5-13.2) for paclitaxel-carboplatin (n = 49). CONCLUSION: Whites and African Americans had similar outcomes, although there was some variability in survival among African Americans across the three treatment groups. © 2010 by the International Association for the Study of Lung Cancer.
Keywords: carboplatin; cimetidine; corticosteroid; diphenhydramine; gemcitabine; paclitaxel; adult; advanced cancer; African American; aged; alopecia; anemia; area under the curve; arthralgia; article; brain metastasis; cancer combination chemotherapy; cancer patient; cancer radiotherapy; cancer survival; Caucasian; clinical trial; constipation; controlled clinical trial; controlled study; diarrhea; disease severity; drug efficacy; drug safety; fatigue; febrile neutropenia; female; functional status; gastrointestinal disease; human; infection; non small cell lung cancer; major clinical study; male; multicenter study; multiple cycle treatment; nausea; neurologic disease; neutropenia; outcome assessment; phase 3 clinical trial; priority journal; race difference; randomized controlled trial; sensory neuropathy; thrombocytopenia; treatment outcome; treatment response

Factors associated with decisions to undergo surgery among patients with newly diagnosed early-stage lung cancer - Cykert, S.; Dilworth-Anderson, P.; Monroe, M.H.; Walker, P.; McGuire, F.R.; Corbie-Smith, G.; Edwards, L.J.; Bunton, A.J. (JAMA - Journal of the American Medical Association, 2010)
Context: Lung cancer is the leading cause of cancer death in the United States. Surgical resection for stage I or II non-small cell cancer remains the only reliable treatment for cure. Patients who do not undergo surgery have a median survival of less than 1 year. Despite the survival disadvantage, many patients with early-stage disease do not receive surgical care and rates are even lower for black patients. Objectives: To identify potentially modifiable factors regarding surgery in patients newly diagnosed with early-stage lung cancer and to explore why blacks undergo surgery less often than whites. Design, Setting, and Patients: Prospective cohort study with patients identified by pulmonary, oncology, thoracic surgery, and generalist practices in 5 communities through study referral or computerized tomography review protocol. A total of 437 patients with biopsy-proven or probable early-stage lung cancer were enrolled between December 2005 and December 2008. Before establishment of treatment plans, patients were administered a survey including questions about trust, patient-physician communication, attitudes toward cancer, and functional status. Information about comorbid illnesses was obtained through chart audits. Main Outcome Measure: Lung cancer surgery within 4 months of diagnosis. Results: A total of 386 patients met full eligibility criteria for lung resection surgery. The median age was 66 years (range, 26-90 years) and 29% of patients were black. The surgical rate was 66% for white patients (n=179/273) compared with 55% for black patients (n=62/113; P=.05). Negative perceptions of patient-physician communication manifested by a 5-point decrement on a 25-point communication scale (odds ratio [OR], 0.42; 95% confidence interval [CI], 0.32-0.74) and negative perception of 1-year prognosis postsurgery (OR, 0.27; 95% CI, 0.14-0.50; absolute risk, 34%) were associated with decisions against surgery. Surgical rates for blacks were particularly low when they had 2 or more comorbid illnesses (13% vs 62% for <2 comorbidities; OR, 0.04 [95% CI, 0.01-0.25]; absolute risk, 49%) and when blacks lacked a regular source of care (42% with no regular care vs 57% with regular care; OR, 0.20 [95% CI, 0.10-0.43]; absolute risk, 15%). Conclusions: A decision not to undergo surgery by patients with newly diagnosed lung cancer was independently associated with perceptions of communication and prognosis, older age, multiple comorbidities, and black race. Interventions to optimize surgery should consider these factors. ©2010 American Medical Association. All rights reserved.
Keywords: adult; aged; article; cancer diagnosis; cancer staging; clinical trial; comorbidity; computer assisted tomography; controlled clinical trial; controlled study; doctor patient relationship; female; functional status; general practice; health survey; human; lung cancer; lung resection; lung surgery; major clinical study; male; clinical audit; medical decision making; medical record review; patient attitude; patient referral; priority journal; prognosis; race difference; surgical risk; thorax surgery; treatment planning

Validation of the group-based medical mistrust scale among urban black men - Shelton, R.C.; Winkel, G.; Davis, S.N.; Roberts, N.; Valdimarsdottir, H.; Hall, S.J.; Thompson, H.S. (Journal of General Internal Medicine, 2010)
Background: Socioculturally relevant measures of medical mistrust are needed to better address health disparities, especially among Black men, a group with lower life expectancy and higher death rates compared to other race/gender groups. OBJECTIVES: The study aim was to investigate the psychometric properties of the Group-Based Medical Mistrust Scale (GBMMS) in a Black male sample. Design: Data were collected as part of a randomized controlled trial testing educational strategies to support Black men's decisions about prostate cancer screening. Participants: Participants included 201 Black men ages 40-75 years recruited in New York City during 2006-2007. MAIN MEASURES: The primary measures included: race-based medical mistrust, health care participation, avoidance of health care, perceived access to health care, health care satisfaction, racial identity, residential racial segregation, attitudes towards prostate cancer screening, and past prostate cancer screening behavior. KEY Results: An exploratory factor analysis suggested a three-factor structure. Confirmatory factor analysis supported the three-factor model. Internal consistency was high for the total GBMMS and the three sub-scales: Suspicion, Discrimination, and Lack of Support. Construct validity was supported by: significant positive correlations between GBMMS and avoidance of health care and racial identity as well as significant negative correlations with health care access, health care satisfaction, and attitudes about prostate cancer screening. ANOVA showed that the GBMMS was associated with greater residential racial segregation. Higher total GBMMS scores were associated with not visiting a physician in the last year and not having a regular physician. Conclusions: The present findings provide strong additional evidence that the GBMMS is a valid and reliable measure that may be used among urban Black men. © 2010 Society of General Internal Medicine.
Keywords: adult; aged; analysis of variance; article; attitude to health; cancer screening; construct validity; demography; exploratory research; group based medical mistrust scale; health care access; human; internal consistency; major clinical study; male; medical decision making; Black person; patient participation; patient satisfaction; physician; prostate cancer; psychometry; race; race difference; rating scale; reliability; United States; urban population; validation study

Updating and refining a study brochure for a cancer registry-based study of BRCA mutations among young African American breast cancer patients: Lessons learned - Vadaparampil, S.T.; Pal, T. (Journal of Community Genetics, 2010)
The aim of the present study was to update, refine, and evaluate a study brochure to promote participation in a population-based study of BRCA mutations among AA women with a personal history of early-onset breast cancer. A multi-step approach was used to develop this brochure and included: (1) feedback from community members (through a Community Advisory Panel (CAP)) to develop and refine the study brochure, (2) pilot testing of materials with the target audience, and (3) review of pilot testing results with the CAP. Based on the feedback received at each step, the study brochure was refined. In phase 1, the major changes included emphasizing the concept of leaving a legacy and family, using the terms Black and women of color, and use of patient vignettes and photos. In phase 2, attraction and cultural acceptability were identified as two areas for improvement in the study brochure. These results demonstrate that involvement of community members and target study population in the development of a study-specific brochure can provide invaluable feedback to optimize recruitment strategies. This approach can be readily adapted to develop study recruitment materials for individuals from a variety of cultural and ethnic backgrounds. © Springer-Verlag 2010.
Keywords: African American; article; breast cancer; cancer registry; cancer risk; cultural factor; female; gene mutation; genetic screening; health education; heredity; high risk population; human; patient participation; pilot study; population genetics; priority journal; publication; tumor suppressor gene

Strategies for recruitment of healthy premenopausal women into the African American nutrition for life (A NULIFE) study - King, D.W.; Duello, T.M.; Miranda, P.Y.; Hodges, K.P.; Shelton, A.J.; Chukelu, P.; Jones, L.A. (Journal of Women's Health, 2010)
Background: Although African American women have an overall lower incidence of breast cancer, African American women <40 years of age are more likely than Caucasian women of all ages and postmenopausal African American women to be diagnosed with breast cancer and exhibit tumor characteristics associated with poorer survival. To begin to address this disparity, studies must be conducted to examine breast cancer preventive factors in this subpopulation of women. However, the strategies needed to recruit younger African American women have not been well defined. Methods: In this study, we assessed methods used for recruiting and retaining healthy premenopausal African American women into the African American Nutrition for Life (A NULIFE) Study. The number of women contacted, enrolled, and retained by each recruitment strategy and the efficiency of individual strategies were calculated. Results: Overall, recruitment through social networking was most effective in contacting large numbers of healthy premenopausal African American women. The worksite recruitment method was the most efficient recruitment strategy employed, with a ratio of 40%. The study participants (n=164) were more likely to be ≥35 years of age and have completed some college. Additionally, the interpersonal relationships recruitment approach proved most efficient (33%) in retaining participants who completed the yearlong study. Conclusions: The findings from this study add to the evolving research literature on minority recruitment strategies for research studies but specifically address effective recruitment of healthy young premenopausal African American women. The results demonstrate the need to use multiple recruitment strategies when recruiting this subgroup of African American women. © 2010, Mary Ann Liebert, Inc.
Keywords: adult; African American; age distribution; article; cancer research; controlled study; educational status; female; high risk population; human; minority group; patient participation; premenopause; priority journal; research subject; social network; women's health

Evaluation of conceptual framework for recruitment of African American patients with breast cancer. - Heiney, S.P.; Adams, S.A.; Wells, L.M.; Johnson, H. (Oncology nursing forum, 2010)
PURPOSE/OBJECTIVES: To describe the Heiney-Adams Recruitment Framework (H-ARF); to delineate a recruitment plan for a randomized, behavioral trial (RBT) based on H-ARF; and to provide evaluation data on its implementation. DATA SOURCES: All data for this investigation originated from a recruitment database created for an RBT designed to test the effectiveness of a therapeutic group convened via teleconference for African American women with breast cancer. DATA SYNTHESIS: Major H-ARF concepts include social marketing and relationship building. The majority of social marketing strategies yielded 100% participant recruitment. Greater absolute numbers were recruited via Health Insurance Portability and Accountability Act waivers. Using H-ARF yielded a high recruitment rate (66%). CONCLUSIONS: Application of H-ARF led to successful recruitment in an RBT. The findings highlight three areas that researchers should consider when devising recruitment plans: absolute numbers versus recruitment rate, cost, and efficiency with institutional review board-approved access to protected health information. IMPLICATIONS FOR NURSING: H-ARF may be applied to any clinical or population-based research setting because it provides direction for researchers to develop a recruitment plan based on the target audience and cultural attributes that may hinder or help recruitment.
Keywords: African American; article; audiovisual equipment; breast tumor; cultural competence; education; ethnology; evaluation study; female; health care quality; human; human relation; model; nursing evaluation research; patient attitude; patient selection; program development; psychological aspect; psychological model; randomized controlled trial; self help; social marketing; telecommunication; trust

Treatment thresholds for osteoporosis in men on androgen deprivation therapy: T-score versus FRAX™ - Adler, R.A.; Hastings, F.W.; Petkov, V.I. (Osteoporosis International, 2010)
Men treated by androgen deprivation therapy (ADT) for localized prostate cancer are at risk for fracture, but it is not known which men require pharmacologic treatment. We found that 33% of men on ADT had osteoporosis of spine, hip, or forearm by dual-energy Xray absorptiometry (DXA), thus requiring treatment. Using the new fracture prediction algorithm (FRAX™) tool with corrected femoral neck T-score identified only 17% requiring treatment, and, if calculated without femoral neck, 54% were identified to need treatment. Introduction Men treated with androgen deprivation therapy (ADT) for prostate carcinoma live long enough to fracture. A new fracture prediction method, FRAX™, is based on femoral neck DXA plus risk factors. Thus, DXA or FRAX™ could determine which men should receive osteoporosis therapy. Methods Of 115 men undergoing ADT referred for DXA testing, those with bone mineral density (BMD) in spine, hip, or forearm of ≥2.5 standard deviations below a normal male ethnicity-adjusted mean were considered treatment candidates. Using FRAX™ with and without femoral neck BMD, men were treatment candidates if the 10-year hip fracture risk was≥3% or the major osteoporotic fracture risk was >20%. Results The men averaged 77 years old; 58%> were African-American, and 14.8% were current smokers. Mean femoral neck T-score was -1.4. Using DXA, 38 (33%) men would need treatment. When FRAX™ was calculated including the femoral neck T-score, only 20 men met criteria for treatment. However, when FRAX™ was calculated without the T-score, 62 men met criteria for treatment. Overlap among the groups was surprisingly modest. Conclusions DXA and FRAX™ identify different ADT men for treatment. © International Osteoporosis Foundation and National Osteoporosis Foundation 2009.
Keywords: antiandrogen; goserelin; African American; age; aged; androgen deprivation therapy; article; bone densitometry; bone density; cancer survival; cigarette smoking; software; controlled study; dual energy X ray absorptiometry; ethnicity; forearm fracture; fracture; fragility fracture; hip fracture; human; major clinical study; male; osteoporosis; patient selection; prediction; priority journal; prostate carcinoma; risk assessment; risk factor; scoring system; spine fracture; FRAX

A phase II study of dasatinib in patients with chemosensitive relapsed small cell lung cancer (Cancer and Leukemia Group B 30602) - Miller, A.A.; Pang, H.; Hodgson, L.; Ramnath, N.; Otterson, G.A.; Kelley, M.J.; Kratzke, R.A.; Vokes, E.E. (Journal of Thoracic Oncology, 2010)
Introduction: SRC is an oncogene with an essential role in the invasiveness and metastasis of solid tumors including small cell lung cancer. Dasatinib is a potent inhibitor of SRC as well as other tyrosine kinases. The primary objective of this study was to determine the efficacy of second-line dasatinib in patients with chemosensitive (relapse or progression ≥90 days after completing first-line therapy) small cell lung cancer. Methods: Patients with measurable disease; performance status 0 to 1; no more than one prior platinum-based chemotherapy regimen; and adequate hematologic, hepatic, and renal function were eligible. Dasatinib was administered orally at 70 mg twice daily continuously (1 cycle = 21 days) until disease progression or unacceptable toxicity. Response was determined after every two cycles. Patients were followed until disease progression or death. The study was prospectively designed to simultaneously discriminate between complete plus partial response rates of 5% versus 20% and progression-free survival (PFS) rates at 6 weeks of 50% versus 70.7% in 53 evaluable patients with at least 92% power. The study was to be terminated early and declared negative if 1 or less objective response and 14 or fewer instances of PFS ≥6 weeks were observed among the initial 27 patients; however, patient accrual continued while the initial 27 patients were evaluated. Results: Between April 2007 and December 2008, 45 patients were enrolled, but one patient never received any protocol therapy and one patient was ineligible: male/female, 17/26; white/black/unknown, 40/2/1; median age, 64 years (range, 35-84 years); and performance status 0/1, 12/31. No objective response was recorded among the 43 eligible and treated patients. Among the initial 27 patients, only 13 instances of PFS ≥6 weeks were observed. With a median follow-up time of 7.1 months, median estimated overall survival and PFS times for the 43 eligible and treated patients were 17.0 and 5.9 weeks, respectively. Common reasons for removal of patients from protocol treatment were progressive disease (65%) and adverse events (26%). Toxicity was generally mild to moderate: grade 3 events of >5% frequency included fatigue and pleural and pericardial effusions; and no grade 4 or 5 events were encountered. Conclusions: Dasatinib did not reach our specified efficacy criteria in this clinical setting, and the study was terminated. Copyright © 2010 by the International Association.
Keywords: antiemetic agent; dasatinib; granisetron; loperamide; platinum; abdominal pain; adult; aged; anorexia; article; asthenia; blood toxicity; cancer chemotherapy; cancer recurrence; cause of death; chemosensitivity; clinical article; clinical trial; continuous infusion; desquamation; diarrhea; disease course; drug dose reduction; drug efficacy; lack of drug effect; drug withdrawal; fatigue; female; follow up; human; human tissue; kidney function; lethargy; liver function; small cell lung cancer; malaise; male; monotherapy; multiple cycle treatment; nausea and vomiting; observational study; overall survival; pericardial effusion; phase 2 clinical trial; pleura effusion; priority journal; progression free survival; prospective study; rash; survival rate; thorax pain; treatment response; vomiting; bms 354825

A trial of 3 interventions to promote colorectal cancer screening in African Americans - Blumenthal, D.S.; Smith, S.A.; Majett, C.D.; Alema-Mensah, E. (Cancer, 2010)
BACKGROUND: Colorectal cancer (CRC) is the second leading cause of cancer death in the United States. CRC incidence and mortality rates are higher among blacks than among whites, and screening rates are lower in blacks than in whites. For the current study, the authors tested 3 interventions that were intended to increase the rate of CRC screening among African Americans. METHODS: The following interventions were chosen to address evidence gaps in the Centers for Disease Control and Prevention's Guide to Community Preventive Services: one-on-one education, group education, and reducing out-of-pocket costs. Three hundred sixty-nine African-American men and women aged ≥50 years were enrolled in this randomized, controlled community intervention trial. The main outcome measures were postintervention increase in CRC knowledge and obtaining a screening test within 6 months. RESULTS: There was substantial attrition: Two hundred fifty-seven participants completed the intervention and were available for follow-up 3 months to 6 months later. Among completers, there were significant increases in knowledge in both educational cohorts but in neither of the other 2 cohorts. By the 6-month follow-up, 17.7% (11 of 62 participants) of the Control cohort reported having undergone screening compared with 33.9% (22 of 65 participants) of the Group Education cohort (P = .039). Screening rate increases in the other 2 cohorts were not statistically significant. CONCLUSIONS: The current results indicated that group education could increase CRC cancer screening rates among African Americans. The screening rate of <35% in a group of individuals who participated in an educational program through multiple sessions over a period of several weeks indicated that there still are barriers to overcome. © 2010 American Cancer Society.
Keywords: adult; African American; aged; article; cancer screening; clinical trial; cohort analysis; colorectal cancer; controlled clinical trial; controlled study; education program; female; follow up; human; major clinical study; male; outcome assessment; priority journal; randomized controlled trial; screening test

Evaluation of the Prostate Cancer Prevention Trial Risk calculator in a high-risk screening population - Kaplan, D.J.; Boorjian, S.A.; Ruth, K.; Egleston, B.L.; Chen, D.Y.T.; Viterbo, R.; Uzzo, R.G.; Buyyounouski, M.K.; Raysor, S.; Giri, V.N. (BJU International, 2010)
Objective: To evaluate the Prostate Cancer Prevention Trial (PCPT) risk calculator in a screening cohort of young, racially diverse, high-risk men with a low baseline prostate-specific antigen (PSA) level and enrolled in the Prostate Cancer Risk Assessment Program (PRAP). The PCPT calculator provides an assessment of prostate cancer risk based on age, PSA level, race, previous biopsy, and family history. Patients and Methods: Eligibility for PRAP includes men aged 35-69 years who are African-American, have a family history of prostate cancer, or have a known BRCA1/2 mutation. PCPT risk scores were determined for PRAP participants, and were compared to observed prostate cancer rates. Results: In all, 624 participants were evaluated, including 382 (61.2%) African-American men and 242 (38.7%) men with a family history of prostate cancer; the median (range) age was 49.0 (34.0-69.0) years and the median PSA level 0.9 (0.1-27.2) ng/mL. The PCPT risk score correlated with prostate cancer diagnosis, as the median baseline risk score in patients diagnosed with prostate cancer was 31.3%, vs 14.2% in patients not diagnosed with prostate cancer (P < 0.001). The PCPT calculator similarly stratified the risk of diagnosis of Gleason score ≥7 disease, as the median risk score was 36.2% in patients diagnosed with Gleason ≥7 prostate cancer vs 15.2% in all other participants (P < 0.001). Conclusion: The PCPT risk calculator score was found to stratify prostate cancer risk in a cohort of young, primarily African-American men with a low baseline PSA level. These Results: support further evaluation of this predictive tool for assessing the risk of prostate cancer in high-risk men. © 2009 BJU International.
Keywords: BRCA1 protein; BRCA2 protein; prostate specific antigen; adult; African American; aged; article; cancer diagnosis; cancer prevention; cancer risk; cancer screening; cancer staging; clinical trial; controlled study; European American; gene mutation; Gleason score; high risk patient; human; major clinical study; male; patient assessment; population; priority journal; prostate cancer; prostate secretion; risk assessment

The role of race and trust in tissue/blood donation for genetic research - Bussey-Jones, J.; Garrett, J.; Henderson, G.; Moloney, M.; Blumenthal, C.; Corbie-Smith, G. (Genetics in Medicine, 2010)
BACKGROUND:: Public willingness to donate tissue samples is critical to genetic research. Prior work has linked minority status and mistrust with less willingness to provide specimens. Some have suggested recruitment of prior research participants to address these barriers. We present data from a genetic epidemiology study with a request for blood and/or saliva specimens to (1) measure willingness to donate tissue/blood samples, (2) identify demographic, trust, and other factors associated with willingness to donate samples, and (3) measure willingness to participate in future genetic research. METHODS:: We surveyed participants in the North Carolina Colorectal Cancer Study, which included biologic sample collection from consenting participants. Participants were later asked about sample provision; trust in researchers, and future research participation. RESULTS:: African Americans were less likely to give a blood sample, when compared with whites (21% vs. 13%, P < 0.05). After controlling for "trust," this difference was no longer statistically significant (17% vs. 13%, P = 0.27). Those who had given samples were more likely to express willingness to participate in future research. CONCLUSION:: Despite prior participation in a genetic epidemiology study, factors associated with provision of tissue samples reflected many previously identified demographic factors (race and trust). Interventions to improve and demonstrate the trustworthiness of the research team and recruitment of subjects with a record of sample donation might enhance future study participation. © 2010 Lippincott Williams & Wilkins.
Keywords: adult; aged; article; blood donor; blood sampling; colorectal cancer; controlled study; demography; female; genetic counseling; genetic epidemiology; genetics; human; human tissue; major clinical study; male; patient participation; race; racism; saliva; trust; United States

The association of plasma fatty acids with prostate cancer risk in African Americans and Africans - Ukoli, F.A.; Fowke, J.H.; Akumabor, P.; Oguike, T.; Taher, K.A.; Murff, H.J.; Amaefuna, E.R.; Kittles, R.; Ahaghotu, C.; Osime, U.; Beech, D.J. (Journal of Health Care for the Poor and Underserved, 2010)
Higher risk for prostate cancer (PCa) among African Americans is partly associated with exposure to dietary fatty-acids, the carcinogenic effects of which remain controversial. Odds ratio of PCa risk was determined by unconditional logistic regression comparing highest with lowest quartiles of plasma fatty-acids in a case-control design. Mean age for 173 African Americans and 340 Nigerians was 56.9 ± 9.8 and 60.1 ± 14.0, p<.006, median (25th, 75th percentile) plasma fatty-acid was 2598 (2306, 3035) μg/ml and 2420 (2064, 2795) μg/ml, p<.001, with 48 (27.7%) and 66 (19.4%) PCa cases, respectively. African Americans recorded higher total, omega-6, and trans, but lower saturated and omega-3 fatty-acids, with non-significant PCa risk association for total, omega-6 and trans fatty acids. Positive PCa risk trend was observed in both populations with nervonic, erucic, and arachidonic acids, with docosahexaenoic acid (DHA) among African Americans, and with behenic and stearic acids in Nigerians. Non-significant negative PCa risk trend was observed with ecosapentaenoic acid (EPA) in Nigerians only. Tese preliminary findings need to be further explored in a larger study that will include risk analysis of fatty-acid ratios to clarify their combined impact on PCa risk.
Keywords: fatty acid; African American; aged; article; blood; case control study; ethnology; fat intake; health disparity; human; male; middle aged; Black person; Nigeria; patient selection; pilot study; prostate tumor; risk; risk assessment; statistical model; statistics; United States

Impact of supplemental site grants to increase African American accrual for the selenium and vitamin e cancer prevention trial - Cook, E.D.; Arnold, K.B.; Hermos, J.A.; McCaskill-Stevens, W.; Moody-Thomas, S.; Probstfield, J.L.; Hamilton, S.J.; Campbell, R.D.; Anderson, K.B.; Minasian, L.M. (Clinical Trials, 2010)
Background African American accrual to prevention trials at rates representative of the disease burden experienced by this population requires additional resources and focused efforts. Purpose To describe the rationale, context, and criteria for selection of sites that received Minority Recruitment Enhancement Grants (MREGs) to increase African American recruitment to the Selenium and Vitamin E Cancer Prevention Trial (SELECT). To determine if African American accrual was higher among the 15 MREG sites when compared with similar nonawarded sites. Methods Changes in African American accrual at sites that received MREGs are compared with changes in a group of 15, frequency-matched, nonawarded sites using a quasi-experimental, post hoc analysis. Successful and unsuccessful recruitment strategies reported by the MREG sites are described. Results The increased number of African American participants accrued per month at MREG sites post-funding was higher than the change at comparison sites by a factor of 3.38 (p = 0.004, 95% CI: 1.51-7.57). An estimated 602 additional African American participants were recruited at MREG sites due to MREG funding, contributing to the overall 14.9% African American recruitment. Successful recruitment strategies most reported by MREG sites included increasing staff, transportation resources, recruiting through the media, mailings, and prostate cancer screening clinics during off-hours. Limitations Comparison sites were chosen retrospectively, not by randomization. Although comparison sites were selected to be similar to MREG sites with regard to potential confounding factors, it is possible that unknown factors could have biased results. Cost-effective analyses were not conducted. Conclusions MREG sites increased African American accrual in the post-funding period more than comparison sites, indicating MREG funding enhanced the sites' abilities to accrue African American participants. Targeted grants early in the accrual period may be a useful multi-site intervention to increase African American accrual for a prevention study where adequate African American representation is essential.
Keywords: NCT00006392; alpha tocopherol; selenium; African American; article; cancer prevention; cancer research; cancer screening; comparative study; controlled study; funding; human; major clinical study; male; patient participation; patient selection; prevention study; priority journal; prostate cancer; qualitative analysis; quantitative study; strategic planning

Effect of race on colon cancer treatment and outcomes in the department of defense healthcare system - Hofmann, L.J.; Lee, S.; WaddelL., B.; Davis, K.G. (Diseases of the Colon and Rectum, 2010)
Purpose: The increase in mortality noted in African Americans with colon cancer is attributed to advanced stage at presentation and disparities in treatment received. The aim of this study was to assess the influence of race on the treatments and survival of colon cancer patients in an equal-access healthcare system. Methods: This retrospective cohort study included African American and white patients with colon cancer treated at Department of Defense facilities. Disease stage, surgery performed, chemotherapy used, and overall survival were evaluated. Results: Of the 6958 colon cancer patients identified, 1115 were African American. African Americans presented more frequently with stage IV disease, 23% vs 17% for whites (P <.001). There was no difference in surgical resection rates for African American or whites (85.8% vs 85.5%, respectively; x2, P >.05). There was no difference in the use of systemic chemotherapy for stage III colon cancer (73.5% for African Americans vs 72.2% for whites; x2, P >.05) or stage IV colon cancer (56.3% for African Americans vs 54.4% for whites; x2, P >.05). The overall 5-year survival rate was similar for African American and white patients (56.1% vs 58.5%, respectively; log-rank, P >.05). After adjusting for gender, age, tumor grade, and stage, African American race was not a risk factor for survival in Cox proportional hazard analysis (hazard ratio, 0.981; 95% confidence interval, 0.888 -1.084). Conclusions: In an equal-access healthcare system, African American race is not associated with an increase in mortality. African American patients undergo surgery and chemotherapy is administered at rates equal to whites for all stages of colon cancer. © 2009 The ASCRS.
Keywords: adult; African American; article; cancer chemotherapy; cancer mortality; cancer surgery; cancer survival; cohort analysis; colon cancer; controlled study; economic aspect; female; health care access; health care system; human; major clinical study; male; outcome assessment; overall survival; patient selection; race difference; retrospective study; risk factor; statistical significance; survival rate

Reporting of race and ethnicity in breast cancer research: Room for improvement - Mitchell, K.W.; Carey, L.A.; Peppercorn, J. (Breast Cancer Research and Treatment, 2009)
Health disparities in breast cancer outcomes according to race/ethnicity are well documented. Randomized clinical trials (RCT) offer an opportunity to evaluate differences in disease biology and response to therapy that may contribute to disparities. We conducted a PubMed search to identify all English language original reports of breast cancer RCT from October 2001 to October 2006. The primary outcomes of interest were reporting of accrual and results by race or ethnicity of trial subjects. We evaluated the correlation between study characteristics and reporting of race/ethnicity. A total of 197 eligible trials were identified among 29 journals. Accrual was reported by race in 17% of studies and results analyzed by race in only 2%. Reporting of race was associated with National Cancer Institute funding (38 vs. 13%, P = 0.001), US cooperative group trials (52 vs. 13%, P < 0.0001), trials with US sites (43 vs. 5%, P < 0.0001), and trials enrolling > 500 subjects (24 vs. 12%, P = 0.055). Pharmaceutical industry funding, # of centers, stage of disease, nature of experimental intervention and study outcomes were not associated with reporting of race. Among US studies reporting trial accrual by race/ethnicity, the mean accrual distribution was 81% white, 7.6% black, 9.6% Asian, and 7.2% Hispanic subjects. The majority of breast cancer RCT fail to report the race/ethnicity of participants. Low accrual of black subjects and failure to report accrual and outcomes by race in RCT may contribute to difficulty in understanding and overcoming health disparities in breast cancer. © 2009 Springer Science+Business Media, LLC.
Keywords: article; breast cancer; cancer research; drug industry; ethnicity; health disparity; medical literature; Medline; priority journal; race

Strategies for recruiting African American men into prostate cancer screening studies - Jones, R.A.; Steeves, R.; Williams, I. (Nursing Research, 2009)
Background: Recruitment for research and clinical trials continues to be challenging. Prostate cancer is the most commonly diagnosed cancer in men and disproportionately affects African American men; thus, effective recruitment strategies are essential for this population. Objectives: The aim of this study was to focus on innovative and effective recruitment strategies for research on prostate cancer with minorities. Methods: A systematic description is provided of the recruitment efforts for a hermeneutic phenomenological qualitative study of African American men's experiences in decision making on whether to have a prostate cancer screening. Results: Seventeen African American men were enrolled from rural Central Virginia. Recruiting strategies were targeted on places where African American men usually are found but that are rarely used for recruitment: barbershops, community health centers, and churches. Word of mouth was also used, and most of the participants (n = 11) were reached through this method. Discussion: Recruitment efforts have been noted to be particularly challenging among minorities, for numerous reasons. Making minority recruitment a priority in any research or clinical trial is essential in gaining a representative sample. Word of mouth is a powerful tool that is often forgotten but should be looked at in further detail.Copyright © 2009 Lippincott Williams & Wilkins.
Keywords: adult; African American; aged; article; decision making; human; male; middle aged; patient selection; prostate tumor; psychological aspect; United States

Attrition and retention in clinical trials by ethnic origin - Sangi-Haghpeykar, H.; Meddaugh, H.M.; Liu, H.; Grino, P. (Contemporary Clinical Trials, 2009)
Context: Common perceptions exist within the medical community that retention of Hispanics in clinical trials is difficult, albeit little data is available to support this conviction. Methods: A total of 541 randomly selected charts from closed clinical trials between 2000 and 2006 were reviewed. Records were from participating institutions in Texas Medical Center, Houston, and targeted diseases of high prevalence, specifically, breast cancer, prostate cancer, and chronic obstructive pulmonary disease (COPD)/asthma. Findings: Overall, 259 participants (48%) completed the trial they were enrolled in (44% whites, 69% Hispanics, 51% blacks; p < .05). Within pediatric trials, whom all were pulmonary patients, retention rates were higher among Hispanics than whites (adjusted odds ratio [OR] = 7.49, 95% confidence interval [CI] = 1.15-58.03, p = .04). Among adults, patient's ethnicity was unrelated to study completion. All associations were adjusted for possible confounders. Reasons for not completing a trial varied by ethnicity: "patient withdrawing consent" was more common among whites (51.4%) than Hispanics (21.7%) or blacks (26.2%) (p < .05). Hispanics were more inclined to be withdrawn from the trial by the investigator (43.5%) than were whites (24%, p = .04), mostly due to non-compliance with the study protocol. Conclusions: Hispanic parents of children with COPD may be more likely to complete a trial than parents of non-Hispanic whites. Among adults, Hispanics had similar completion rates as compared to whites. Culturally sensitive, multi-factorial approaches maybe imperative to increasing patient engagement in clinical trials. © 2009 Elsevier Inc. All rights reserved.
Keywords: adult; aged; article; asthma; breast cancer; cancer epidemiology; chronic obstructive lung disease; confidence interval; controlled study; disease association; ethnic group; ethnic difference; female; human; major clinical study; male; prostate cancer; statistical significance

Prostate Cancer Early Detection Program Recruitment Methods and Show Rates in Men at High Risk - Giri, V.N.; Coups, E.J.; Ruth, K.; Goplerud, J.; Raysor, S.; Kim, T.Y.; Bagden, L.; Mastalski, K.; Zakrzewski, D.; Leimkuhler, S.; Watkins-Bruner, D. (Journal of Urology, 2009)
Purpose: Men with a family history of prostate cancer and black men are at higher risk for prostate cancer. Recruitment and retention of these men at high risk into early detection programs is challenging. We report a comprehensive analysis of recruitment methods, show rates and participant factors from the Prostate Cancer Risk Assessment Program, a prospective, longitudinal prostate cancer screening study. Materials and Methods: Men 35 to 69 years old were eligible for recruitment if they had a family history of prostate cancer, were black or had a BRCA1/2 mutation. Recruitment methods were analyzed using standard statistical methods with respect to participant demographics and presentation to the first program appointment. Results: Of 707 men recruited 64.9% presented to the initial program appointment. More men were recruited via radio than via referral or other methods (chi-square = 298.13, p <0.0001). Men recruited by radio were more likely to be black (p <0.001), less educated (p = 0.003) and not married or partnered (p = 0.007), and have no prostate cancer family history (p <0.001). Men recruited by referral had a higher income (p = 0.007) and were more likely to attend the initial program visit than those recruited by radio or other methods (chi-square = 27.08, p <0.0001). Conclusions: This comprehensive analysis shows that radio led to higher recruitment of black men with lower socioeconomic status. However, these men at high risk have a lower presentation rate for prostate cancer screening. Targeted motivational measures must be studied to improve the show rate for prostate cancer risk assessment in these men at high risk. © 2009 American Urological Association.
Keywords: BRCA1 protein; BRCA2 protein; adult; African American; aged; article; cancer diagnosis; cancer risk; cancer screening; demography; early diagnosis; educational status; family history; follow up; gene mutation; health education; high risk population; human; income; Internet; longitudinal study; major clinical study; male; marriage; motivation; patient referral; patient selection; priority journal; prospective study; prostate cancer; publication; risk assessment; social status; telecommunication; television

An experimental test of the effect of incentives on recruitment of ethnically diverse colorectal cancer cases and their first-degree relatives into a research study - Maxwell, A.E.; Bastani, R.; Glenn, B.A.; Mojica, C.M.; Chang, L.C. (Cancer Epidemiology Biomarkers and Prevention, 2009)
Background: Optimizing participant response rates is important for obtaining representative samples and the timely completion of studies. It is a common practice to use participant incentives to boost response rates, but few studies have systematically examined their effectiveness, particularly among minority groups. Methods:We experimentally tested three incentive strategies for their effectiveness in improving response rates among colorectal cancer cases (n = 3,816) and their relatives (n = 2,353). A 2 x 2 x 2 factorial design compared (a) registered versus first class mail, (b) $5 cash with the initial mailing (yes/no), and (c) $20 promise (yes/no) upon completion of the information form (for cases) or $10 promise (yes/no) upon completion of the baseline survey (for relatives). Outcome measures were provision of contact information on first-degree relatives for cases and completion of the baseline survey for relatives. Results: The response rate among cases was low in all ethnic groups (28-37%) and incentive strategies did not have an effect. Among relatives, the overall baseline survey response rate was 71%, ranging from 66% among Asians to 76% among Whites. Modest absolute increases were observed for payment schedules that included a $5 cash enclosure with the initial mailing in the total sample [odds ratio (OR), 1.65 and 1.47] and among Latinos (OR, 1.94 and 1.74) but not among Asians (OR, 1.61 and 1.55) or African Americans (OR, 1.19 and 1.02). Response rates were not influenced by registered versus firstclass mailing. Conclusion: The effects of incentives in this study were modest with some suggestion of differences by ethnic group and type of incentive. Copyright © 2009 American Association for Cancer Research.
Keywords: adult; African American; aged; article; Asian American; colorectal cancer; controlled study; ethnic difference; European American; experimental test; factorial design; female; Hispanic; human; major clinical study; male; medical research; money; normal human; patient participation; priority journal; relative; reward

Development of wagle health-specific religiousness scale - Wagle, A.M.; Champion, V.L.; Russell, K.M.; Rawl, S.M. (Cancer Nursing, 2009)
African American women have a lower rate of regular mammography screening, resulting in higher incidence of advanced-stage breast cancer at diagnosis and a lower 5-year survival rate as compared with white women. Researchers have demonstrated that several health beliefs relate to mammography screening in African American women, but little attention has been paid to the importance of religiousness. Although some authors have attempted to determine a link between religiousness and health, we lack a valid and reliable instrument to measure religiousness that can be found in the context of health behaviors. The purpose of this article is to describe the development and psychometric testing of the Wagle Health-Specific Religiousness (WHSR) scale, an instrument used to measure religious beliefs and the influence of those beliefs on mammography screening for African American women. A sample of 344 low-income African American women who were nonadherent to mammography at accrual participating in a randomized trial completed the WHSR. Data from this trial were used to determine the validity and reliability of the WHSR. The 19-item WHSR scale had a Cronbach α of. 94. Construct validity was supported via factor analysis and analysis of theoretical relationships. Although further testing is warranted, this analysis indicates that the concept of religiousness is an important component of mammography behavior in African American women. Copyright © 2009 Lippincott Williams & Wilkins.
Keywords: African American; article; breast cancer; cancer mortality; cancer screening; female; health belief; human; mammography; priority journal; psychometry; religion; self concept

Relationship of body mass, height, and weight gain to prostate cancer risk in the multiethnic cohort - Hernandez, B.Y.; Park, S.-Y.; Wilkens, L.R.; Henderson, B.E.; Kolonel, L.N. (Cancer Epidemiology Biomarkers and Prevention, 2009)
We investigated the relationship of body size and prostate cancer risk in the Multiethnic Cohort, a longitudinal study of individuals ages 45 to 75 in Hawaii and in California. Self-reported measures of height and weight were obtained at baseline. Of 83,879 men enrolled from 1993 to 1996, a total of 5,554 were diagnosed with prostate cancer during an average of 9.6 years of follow-up. The influence of baseline weight and weight change since age 21 varied by ethnic group. Whites gaining more than 10 lbs had a nonlinear, increased risk of advanced and high-grade prostate cancer [relative risks (RR), 2.12; 95% confidence intervals (CI), 1.19-3.78 for 25-39.9 lbs; P trend 0.43; and RR, 1.49; 95% CI, 1.04-2.14, for ≥40 lbs; P trend 0.20, respectively]. African American men gaining 40 lbs or more (relative to <10 lbs) had a nonmonotonic, increased risk of localized prostate cancers (RR, 1.26; 95% CI, 1.02-1.54; P trend 0.09) and those who gained 25 lbs or more were at increased risk of low-grade disease (RR, 1.28; 95% CI, 1.03-1.58, for ≥40 versus 10 lbs, respectively; P trend 0.07). Japanese men had a statistically significant, inverse association of weight gain and localized disease (RR, 0.80; 95% CI, 0.65-0.99 for ≥40 versus 10 lbs; P trend 0.05). Our findings provide evidence that adiposity and changes in adiposity between younger and older adulthood influence the development of prostate cancer. Ethnic differences in risk may be explained by variation in the distribution of accumulated body fat that could differentially affect prostate carcinogenesis. Copyright © 2009 American Association for Cancer Research.
Keywords: adult; aged; anthropometry; article; body height; body mass; body size; cancer risk; controlled study; disease severity; ethnic difference; human; major clinical study; male; obesity; priority journal; prostate cancer; United States; body weight change; body weight gain

An educational video to increase clinical trials enrollment among breast cancer patients - Du, W.; Mood, D.; Gadgeel, S.; Simon, M.S. (Breast Cancer Research and Treatment, 2009)
Only 3% of women with breast cancer participate in cancer clinical trials nationwide. The lack of awareness about clinical trials is a significant barrier towards clinical trials participation. A study was conducted at a large urban Comprehensive Cancer Center to test (1) the effectiveness of an 18-min educational video on improving attitudes toward clinical trials and trials enrollment among new breast cancer patients seen at the Karmanos Cancer Institute, and (2) to assess racial differences in attitudes regarding clinical trials. Participants were randomized to either the educational intervention prior to their first oncology clinic appointment or to standard care. A baseline and 2-week post-intervention survey to assess attitudes toward clinical trials participation was completed by participants. Of 218 subjects recruited, 196 (55% white vs. 45% African American (AA)) eligible patients were included in the analysis. A small increase in therapeutic clinical trial enrollment was observed in the intervention arm but was not statistically significant (10.4% vs. 6.1%; P = 0.277). The intervention also did not result in a clear improvement in patients' attitudes toward clinical trials at posttest. However, a lower enrollment rate for the AA women was noted after adjusting for stage (OR = 0.282, P = 0.049). Significantly more negative scores were noted in 3 out of the 5 baseline attitudinal scales for AA women. The educational video did not significantly increase enrollment in breast cancer clinical trials. The findings that AA women had significantly more negative attitudes toward clinical trials than white women may partially explain the racial disparity in enrollment. An educational video remains a simple and cost-effective way to educate patients. Future studies should focus on designing a new educational video to specifically target cultural and attitudinal barriers in the AA population to more effectively change attitudes and increase trial enrollment. © 2009 Springer Science+Business Media, LLC.
Keywords: adult; African American; aged; article; awareness; breast cancer; cancer patient; clinical trial; controlled clinical trial; controlled study; cost effectiveness analysis; cultural factor; European American; female; human; major clinical study; patient attitude; patient care; patient education; priority journal; race difference; randomized controlled trial; videorecording

Exploring the financial impact of breast cancer for African American medically underserved women: a qualitative study. - Darby, K.; Davis, C.; Likes, W.; Bell, J. (Journal of health care for the poor and underserved, 2009)
In addition to the physical suffering experienced by cancer survivors, there are considerable financial hardships and access barriers to quality health care. The current study explored the financial burden of breast cancer on African American medically underserved women. Four focus groups were conducted in three major cities across Tennessee. Research participants (N=36) were recruited by the staff of cancer support and treatment programs in the area. Findings revealed that participants' lack of insurance or inadequate insurance resulted in missed, delayed, or fewer treatment opportunities. The financial burden of cancer was not limited to the acute treatment phase. The women in the current study reported extreme economic hardship resulting from this disease into long-term survivorship. This exploratory study confirms the importance of providing care across the continuum to address the complex needs of low-income cancer survivors.
Keywords: adult; African American; article; breast tumor; economics; ethnology; female; health care cost; health care delivery; health care planning; human; information processing; middle aged; qualitative research; United States

Social workers as patient navigators for breast cancer survivors: What do african-american medically underserved women think of this idea? - Davis, C.; Darby, K.; Likes, W.; Bell, J. (Social Work in Health Care, 2009)
Patient navigation (PN) is a new initiative in health care aimed at reducing disparities by assisting patients in overcoming barriers within the health care system. As PN programs grow around the country, it is important to consult the key stakeholders in the development of these programs. The purpose of this qualitative study was to discuss the needs of medically underserved cancer patients and allow them the opportunity to provide input on models of care to meet their needs. Four focus groups were conducted in three major cities across Tennessee. Research participants (n = 36) were recruited by the staff in area cancer support programs and treatment programs across the state and through recruitment flyers at various treatment centers and community organizations. Findings revealed four key themes in the development of PN programs: (1) the PN needs to address access to quality care issues; (2) the PN needs to address the emotional and practical concerns of the cancer survivor; (3) the PN needs to address family concerns; (4) the PN needs to be involved across the continuum of care from time of diagnosis into long-term survivorship. Oncology social workers have a unique opportunity to meet the needs of medically underserved cancer patients through the PN movement. Our profession is a key stakeholder in this movement. We need to advocate for trained oncology social workers to actively pursue the role of patient navigators to ensure that the needs of medically underserved cancer survivors and their families are met.
Keywords: adult; African American; aged; article; attitude to health; breast tumor; case management; family; female; health care delivery; health care planning; human; information processing; middle aged; needs assessment; quality of life; social work; survivor; United States; urban population

An assessment of the CES-D scale factor structure in black women: The Black Women's Health Study - Makambi, K.H.; Williams, C.D.; Taylor, T.R.; Rosenberg, L.; Adams-Campbell, L.L. (Psychiatry Research, 2009)
This study investigates the dimensional structure of the Center for Epidemiologic Studies Depression (CES-D) scale in US Black women with and without history of cancer via single-group and multi-group analyses. The CES-D questionnaire was administered in 1999 to 50,774 black women who are participants in the Black Women's Health Study (BWHS). For our analysis, we utilized a group of 690 women with a history of at least one of the three types of cancer (breast cancer, colon cancer or lung cancer) and an age-matched group of 1,380 healthy women with no history of any cancer or other chronic conditions including myocardial infarctions, stroke, angina, diabetes, lupus, and sarcoidosis. Three a priori hypothesized models were tested via confirmatory factor analysis: single-, three- and four-factor structures. The four-factor model provided the best fit and remained largely invariant across the groups when tested via multi-group comparisons. Two internal consistency measures of the scale (Cronbach's α coefficient and split-half coefficient) were also shown to be satisfactory. We concluded that the CES-D scale is appropriate for use in black women regardless of their cancer status. © 2008 Elsevier Ltd. All rights reserved.
Keywords: adult; aged; angina pectoris; article; breast cancer; Center for Epidemiological Studies Depression Scale; cerebrovascular accident; chronic disease; colon cancer; controlled study; Cronbach alpha coefficient; diabetes mellitus; factor analysis; female; groups by age; heart infarction; human; internal consistency; lung cancer; lupus erythematosus; major clinical study; major depression; Black person; patient participation; priority journal; questionnaire; sarcoidosis; split half correlation; women's health

Geographic recruitment of breast cancer survivors into community-based exercise interventions - Rogerino, A.; Grant, L.L.; Wilcox, H.; Schmitz, K.H. (Medicine and Science in Sports and Exercise, 2009)
PURPOSE: There is increased interest in developing and disseminating health behavior interventions for cancer survivors. Challenges in these efforts include participant burden in traveling to central intervention sites and sustainability. The purpose of this article is to report various methods used to recruit breast cancer survivors into an exercise intervention that attempts to address both of these challenges. METHODS:: Letters were mailed within specific zip codes near community-based intervention sites in cooperation with state cancer registries. Additional recruitment methods included flyers at breast care clinics and support groups, mass media, and conferences. RESULTS:: Of the 3200 women who responded, 82% (n = 2625) identified having heard about the study through state or hospital registry and 8% (n = 243) through print and broadcast media. Thirty-five percent (n = 103) of randomized women self-identified as having a minority racial background and 31.9% (n = 94) self-identified as African American. Comparisons of participant age and racial distribution to state cancer registries indicate similar age distribution but greater racial diversity among participants. CONCLUSION:: These results support the use of population-based cancer registries to recruit survivors into community-based interventions and clinical trials.
Keywords: adult; African American; age distribution; article; breast cancer; cancer center; cancer registry; cancer survival; cancer survivor; clinical trial; controlled clinical trial; female; health behavior; human; kinesiotherapy; lymphedema; major clinical study; mass medium; race; race difference; randomized controlled trial; support group

Latinas and breast cancer outcomes: Population-based sampling, ethnic identity, and acculturation assessment - Hamilton, A.S.; Hofer, T.P.; Hawley, S.T.; Morrell, D.; Leventhal, M.; Deapen, D.; Salem, B.; Katz, S.J. (Cancer Epidemiology Biomarkers and Prevention, 2009)
Purpose: Latinas and African-Americans with breast cancer, especially those of lower socioeconomic status and acculturation, have been underrepresented in studies assessing treatment satisfaction, decision-making, and quality of life. A study was designed to recruit a large and representative sample of these subgroups. Materials and Methods: Incident cases were selected by rapid case ascertainment (RCA) in the Los Angeles Surveillance, Epidemiology, and End Results Registry from 2005 to 2006, with oversampling of Latinas and African-Americans. Patients were maileda questionnaire and $10 incentive 5 to 6 months after diagnosis; nonrespondents were contacted by telephone. Multivariate analysis was usedto assess possible response bias. The RCA definition of Hispanic origin was validated by self-reports. The Short Acculturation Scale for Hispanics index for Latina respondents was used. Results: One thousand six hundred and ninety-eight eligible breast cancer cases were selected and 1,223 participated, for a response rate of 72.0%, which varied little by race/ethnicity. Age, race/ethnicity, and clinical factors were not associated with response; however, respondents were slightly more likely to be married and from higher socioeconomic status census tracts than nonrespondents. The RCA definition of Hispanic identity was highly sensitive (94.6%) and specific (90.0%). Lower acculturation was associated with lower education and literacy among Latinas. Discussion: High response rates among all subgroups were achieved due to the use of RCA, an incentive, extensive telephone follow-up, a native Spanish-speaking interviewer, and a focused questionnaire. The low acculturation index category identified a highly vulnerable subgroup. This large sample representing subgroups with greater problems will provide a basis for developing better interventions to assist these women. Copyright © 2009 American Association for Cancer Research.
Keywords: adult; African American; aged; article; breast cancer; clinical feature; cultural factor; diagnostic accuracy; ethnic group; female; follow up; Hispanic; human; major clinical study; medical decision making; multivariate analysis; outcomes research; patient satisfaction; population research; priority journal; quality of life; questionnaire; race difference; self report; sensitivity and specificity; Short Acculturation Scale for Hispanics Index; socioeconomics; telephone; United States

Racial disparities in cancer survival among randomized clinical trials patients of the southwest oncology group - Albain, K.S.; Unger, J.M.; Crowley, J.J.; Coltman, C.A.; Hershman, D.L. (Journal of the National Cancer Institute, 2009)
BackgroundRacial disparities in cancer outcomes have been observed in several malignancies. However, it is unclear if survival differences persist after adjusting for clinical, demographic, and treatment variables. Our objective was to determine whether racial disparities in survival exist among patients enrolled in consecutive trials conducted by the Southwest Oncology Group (SWOG).MethodsWe identified 19457 adult cancer patients (6676 with breast, 2699 with lung, 1244 with colon, 1429 with ovarian, and 1843 with prostate cancers; 1291 with lymphoma; 2067 with leukemia; and 2208 with multiple myeloma) who were treated on 35 SWOG randomized phase III clinical trials from October 1, 1974, through November 29, 2001. Patients were grouped according to studies of diseases with similar histology and stage. Cox regression was used to evaluate the association between race and overall survival within each disease site grouping, controlling for available prognostic factors plus education and income, which are surrogates for socioeconomic status. Median and ten-year overall survival estimates were derived by the Kaplan-Meier method. All statistical tests were two-sided.ResultsOf 19457 patients registered, 2308 (11.9%, range = 3.9%-21.6%) were African American. After adjustment for prognostic factors, African American race was associated with increased mortality in patients with early-stage premenopausal breast cancer (hazard ratio [HR] for death = 1.41, 95% confidence interval [CI] = 1.10 to 1.82; P =. 007), early-stage postmenopausal breast cancer (HR for death = 1.49, 95% CI = 1.28 to 1.73; P <. 001), advanced-stage ovarian cancer (HR for death = 1.61, 95% CI = 1.18 to 2.18; P =. 002), and advanced-stage prostate cancer (HR for death = 1.21, 95% CI = 1.08 to 1.37; P =. 001). No statistically significant association between race and survival for lung cancer, colon cancer, lymphoma, leukemia, or myeloma was observed. Additional adjustments for socioeconomic status did not substantially change these observations. Ten-year (and median) overall survival rates for African American vs all other patients were 68% (not reached) vs 77% (not reached), respectively, for early-stage, premenopausal breast cancer; 52% (10.2 years) vs 62% (13.5 years) for early-stage, postmenopausal breast cancer; 13% (1.3 years) vs 17% (2.3 years) for advanced ovarian cancer; and 6% (2.2 years) vs 9% (2.7 years) for advanced prostate cancer.ConclusionsAfrican American patients with sex-specific cancers had worse survival than white patients, despite enrollment on phase III SWOG trials with uniform stage, treatment, and follow-up.
Keywords: adult; advanced cancer; African American; article; breast cancer; cancer survival; clinical evaluation; clinical trial; cohort analysis; colon cancer; colon surgery; controlled clinical trial; controlled study; demography; disease classification; disease severity; education; female; histology; human; income; leukemia; lung cancer; lymphoma; major clinical study; male; mortality; multiple myeloma; neoplasm; oncology; ovary cancer; overall survival; postmenopause; premenopause; priority journal; prognosis; prospective study; prostate cancer; race difference; randomized controlled trial; risk factor; social status

Knowledge, attitudes, and practices of underserved women in the rural south toward breast cancer prevention and detection - Avis-Williams, A.; Khoury, A.; Lisovicz, N.; Graham-Kresge, S. (Family and Community Health, 2009)
The goal of this study was to understand the unique needs and barriers to breast cancer control among African American women in the rural South. This population experiences barriers that surpass that of other minorities. Researchers conducted 6 focus groups to assess barriers of minority women in Mississippi toward breast cancer prevention and clinical trials. These women had little knowledge of treatment options and negative perceptions of screening and clinical trial participation. This research equips others to identify new health education strategies. Conclusions also provide insight into prevention for other minority populations, such as Latina, Asian, and American Indian women. Copyright © 2009 Wolters Kluwer Health | Lippincott Williams & Wilkins.
Keywords: adult; article; attitude to health; breast tumor; clinical trial; female; health care delivery; health care planning; human; information processing; mass screening; middle aged; patient participation; risk factor; rural population; United States

A pilot trial of spirituality counseling for weight loss maintenance in African American breast cancer survivors - Djuric, Z.; Mirasolo, J.; Kimbrough, L.; Brown, D.R.; Heilbrun, L.K.; Canar, L.; Venkatranamamoorthy, R.; Simon, M.S. (Journal of the National Medical Association, 2009)
A continuing challenge in weight loss treatment is attaining maintenance of weight loss. The goal of this study was to develop a counseling method that would assist African American breast cancer survivors with weight loss maintenance. In this pilot study, 31 obese breast cancer survivors were recruited. Individualized, dietitian-led counseling by telephone and free Weight Watchers coupons were provided to all participants for 18 months. At the 6-month time point, women were randomized to receive spirituality counseling or not in addition to the standard program. The spirituality counseling was delivered via telephone using an 8-step framework. Subjects were asked to utilize daily meditation or prayer, daily readings, and the recording of thoughts in a journal. Mean weight loss from baseline to 6 months was a modest 2.0% of baseline weight. From 6 to 18 months, there was no further weight change in the spirituality arm and a gain of 0.7% in the dietitian-only arm. Despite little effect on weight loss, it did appear that spirituality counseling positively affected spiritual well-being (FACIT-Sp) scores and dietary quality. The spirituality counseling framework therefore may be further refined and useful for other health promotion studies with African American populations.
Keywords: adult; African American; article; breast cancer; cancer survivor; clinical article; controlled study; counseling; dietitian; female; health promotion; human; meditation; pilot study; priority journal; religion; telephone; body weight loss; wellbeing

Host genetic variants in the interleukin-6 promoter predict poor outcome in patients with estrogen receptor-positive, node-positive breast cancer - DeMichele, A.; Gray, R.; Horn, M.; Chen, J.; Aplenc, R.; Vaughan, W.P.; Tallman, M.S. (Cancer Research, 2009)
Interleukin-6 modulates immune response, estrogen production, and growth pathways in breast cancer. We evaluated the effect of several common, functional interleukin-6 promoter variants in node-positive breast cancer patients enrolled on a multicenter, cooperative group, adjuvant chemotherapy trial to determine whether these variants were associated with clinical outcome overall and by estrogen receptor tumor phenotype. Genomic DNA and clinical data were collected from a clinical trial of adjuvant anthracycline-based chemotherapy followed by randomization to high-dose cyclophosphamide/thiotepa or observation (Intergroup Trial 0121). Genotyping for -174G>C (rs1800795), -597G>A (rs1800797), and -572G>C (rs1800796) was done by site-specific PCR and PyroSequencing, whereas the -373AnTn repeat was directly sequenced. Log-rank tests and Cox modeling were used to compare outcomes by genotype/haplotype and other factors. Three hundred forty-six patients (64% of trial) had corresponding genotype/clinical data available and did not differ from overall trial participants. After adjustment, patients with estrogen receptor-positive tumors and genotypes 597 GG or 174 GG had significantly worse disease-free survival [hazard ratio (HR), 1.6; P = 0.02 and HR, 1.71; P = 0.007, respectively], whereas the 373 8A12T repeat appeared to be protective (HR, 0.62; P = 0.02). The presence of at least one copy of the haplotype ([-597G, -572G, -373[10A/11T], -174G]) was associated with worse disease-free survival (HR, 1.46; P = 0.04). Kaplan-Meier plots show that all patients in this group relapsed by 24 months from diagnosis. This poor-risk haplotype was quite common overall (estimated frequency, 0.20) and twice as frequent among Blacks (estimated frequency, 0.41). ©2009 American Association for Cancer Research.
Keywords: anthracycline; cyclophosphamide; doxorubicin; estrogen receptor; fluorouracil; genomic DNA; interleukin 6; progesterone receptor; tamoxifen; thiotepa; adjuvant therapy; adult; amino acid substitution; article; breast cancer; cancer adjuvant therapy; cancer combination chemotherapy; cancer epidemiology; cancer surgery; clinical trial; controlled study; disease free survival; drug megadose; female; genetic variability; genotype; haplotype; hazard ratio; human; human cell; Kaplan Meier method; major clinical study; multicenter study; multiple cycle treatment; outcome assessment; partial mastectomy; phenotype; polymerase chain reaction; priority journal; promoter region; pyrosequencing; relapse; single nucleotide polymorphism; statistical significance; treatment outcome

African American men and self-efficacy in preventing prostate cancer - Kendrick, L.; Montgomery, S.; Ouattara, D. (Issues in Mental Health Nursing, 2009)
Keywords: adult; African American; article; attitude to health; genetic predisposition; genetics; human; male; mass screening; nursing; patient participation; practice guideline; prostate tumor; psychological aspect; self concept

Addressing social determinants of health to improve access to early breast cancer detection: Results of the boston reach 2010 breast and cervical cancer coalition women's health demonstration project - Clark, C.R.; Baril, N.; Kunicki, M.; Johnson, N.; Soukup, J.; Ferguson, K.; Lipsitz, S.; Bigby, J. (Journal of Women's Health, 2009)
Background: The Boston Racial and Ethnic Approaches to Community Health (REACH) 2010 Breast and Cervical Cancer Coalition developed a case management intervention for women of African descent to identify and reduce medical and social obstacles to breast cancer screening and following up abnormal results. Methods: We targeted black women at high risk for inadequate cancer screening and follow-up as evidenced by a prior pattern of missed clinic appointments and frequent urgent care use. Case managers provided referrals to address patient-identified social concerns (e.g., transportation, housing, language barriers), as well as navigation to prompt screening and follow-up of abnormal tests. We recruited 437 black women aged 40-75, who received care at participating primary care sites. The study was conducted as a prospective cohort study rather than as a controlled trial and evaluated intervention effects on mammography uptake and longitudinal screening rates via logistic regression and timely follow-up of abnormal tests via Cox proportional hazards models. Results: A significant increase in screening uptake was found (OR 1.53, 95% CI 1.13-2.08). Housing concerns (p<0.05) and lacking a regular provider (p<0.01) predicted poor mammography uptake. Years of participation in the intervention increased odds of obtaining recommended screening by 20% (OR 1.20, 95% CI 1.02-1.40), but this effect was attenuated by covariates (p<0.53). Timely follow-up for abnormal results was achieved by most women (85%) but could not be attributed to the intervention (HR 0.95, 95% CI 0.50-1.80). Conclusions: Case management was successful at promoting mammography screening uptake, although no change in longitudinal patterns was found. Housing concerns and lacking a regular provider should be addressed to promote mammography uptake. Future research should provide social assessment and address social obstacles in a randomized controlled setting to confirm the efficacy of social determinant approaches to improve mammography use. © 2009, Mary Ann Liebert, Inc.
Keywords: adult; African American; aged; article; breast cancer; cancer center; cancer diagnosis; cancer screening; case manager; cervical cancer coalition; cohort analysis; evaluation study; female; follow up; hazard; health care access; health care personnel; health program; high risk patient; housing; human; intervention study; language; longitudinal study; major clinical study; mammography; methodology; outpatient department; patient care; patient referral; primary medical care; priority journal; proportional hazards model; prospective study; racial and ethnic approaches to community health; social aspect; traffic and transport; uterine cervix cancer

Treatment quality and outcomes of African American versus white breast cancer patients: Retrospective analysis of southwest oncology studies S8814/S8897 - Hershman, D.L.; Unger, J.M.; Barlow, W.E.; Hutchins, L.F.; Martino, S.; Osborne, C.K.; Livingston, R.B.; Albain, K.S. (Journal of Clinical Oncology, 2009)
Purpose: Women of African ancestry (AA) have lower WBC counts and are more likely to have treatment delays and discontinue adjuvant breast cancer therapy early compared with white women. We assessed the association between race and treatment discontinuation/delay, WBC counts, and survival in women enrolled onto breast cancer clinical trials. Patients and Methods: AA and white women from Southwest Oncology Group adjuvant breast cancer trials (S8814/ S8897) were matched by age and protocol. Only the treatment arms in which patients were scheduled to receive six cycles of chemotherapy were analyzed. Results: A total of 317 pairs of patients (n = 634) were analyzed. At baseline, AA women had higher body-surface area (P < .0001) and lower WBC (P = .0009). AA women were more likely to have tumors that were ≥ 2 cm (P = .01) and hormone receptor negative (P < .0001). AA women, versus white women, were marginally more likely to discontinue treatment early (11% v 7%, respectively; P = .07) or have one or more treatment delays (85% v 79%, respectively; P = .07) and were significantly more likely to experience the combined end point (discontinuation/delay; 87% v 81%, respectively; P = .04). The mean relative dose-intensity (RDI) was similar for both groups (87% in AA women v 86% in white women); however, overall, 43% had an RDI of less than 85%. After adjusting for baseline WBC and prognostic factors in a multivariate model, AA women had worse disease-free survival (hazard ratio [HR] = 1.56; 95% CI, 1.15 to 2.11; P = .005) and overall survival (HR = 1.95; 95% CI, 1.36 to 2.78; P = .0002). The inclusion of RDI and treatment delivery/quality in the regression had little impact on the results. Conclusion: On cooperative group breast cancer trials, AA and white women had similar RDIs, but AA women were more likely to experience early discontinuation or treatment delay. Despite correcting for these factors and known predictors of outcome, AA women still had worse survival. © 2009 by American Society of Clinical Oncology.
Keywords: cyclophosphamide; doxorubicin; fluorouracil; granulocyte colony stimulating factor; hormone receptor; methotrexate; tamoxifen; adult; African American; age distribution; aged; article; body surface; breast cancer; cancer chemotherapy; cancer patient; cancer survival; clinical protocol; controlled study; disease association; disease free survival; European American; febrile neutropenia; female; health care delivery; health care quality; human; leukocyte count; major clinical study; multiple cycle treatment; overall survival; priority journal; prognosis; race difference; retrospective study; therapy delay; treatment outcome; treatment withdrawal

Acupuncture for nonpalliative radiation therapy-related fatigue: Feasibility study - Mao, J.J.; Styles, T.; Cheville, A.; Wolf, J.; Fernandes, S.; Farrar, J.T. (Journal of the Society for Integrative Oncology, 2009)
The purpose of this study was to determine the feasibility of an acupuncture clinical trial to prevent radiation therapy (RT)-induced fatigue. We conducted a cross-sectional survey study and a single-arm acupuncture clinical trial among patients undergoing RT. Patients with a Karnofsky score of less than 60, severe anemia, or substantial psychological diagnoses were excluded. Patients received up to 12 treatments of acupuncture over the entire course of their RT. The Lee Fatigue Scale (LFS) was administered at baseline, in the middle of RT, and at the end of RT, along with the Patient Global Impression of Change (PGIC). Among the 48 of 53 (91% response rate) survey participants, 20 (42%) reported that they would participate if the study were available, 13 (27%) would not participate, and 15 (31%) were unsure. Among the 16 trial participants, average fatigue and energy domains of the LFS remained stable during and after RT, without any expected statistical decline owing to RT. Based on the PGIC at the end of RT, 2 subjects (13%) reported their fatigue as worse, 8 (50%) as stable, and 6 (37%) as better. Acupuncture has the potential to prevent RT-related fatigue, which will need to be confirmed by conducting a randomized controlled trial. © 2009 BC Decker Inc.
Keywords: antineoplastic agent; acupuncture; adult; article; Asian; breast cancer; cancer radiotherapy; Caucasian; clinical article; clinical trial; controlled study; cross-sectional study; digestive system cancer; employment status; fatigue; feasibility study; female; head and neck cancer; human; Karnofsky Performance Status; lung cancer; male; medical research; Black person; patient attitude; patient participation; patient selection; prostate cancer; race difference; rating scale; treatment outcome

Issues related to implementing a smoking cessation clinical trial for cancer patients - Martinez, E.; Tatum, K.L.; Weber, D.M.; Kuzla, N.; Pendley, A.; Campbell, K.; Ridge, J.A.; Langer, C.; Miyamoto, C.; Schnoll, R.A. (Cancer Causes and Control, 2009)
Given high rates of smoking among cancer patients, smoking cessation treatment is crucial; yet limited data exist to guide integration of such trials into the oncologic context. In order to determine the feasibility of conducting smoking cessation clinical trials with cancer patients, screening and baseline data from a large randomized placebo-controlled pharmacotherapy trial were analyzed. Descriptive statistics and regression analyses were used to compare enrollees to decliners, describe program enrollees, and assess correlates of confidence in quitting smoking. Out of 14,514 screened patients, 263 (<2%) were eligible; 43 (16%) refused enrollment. Among the eligible patients, 220 (84%) enrolled. Enrollment barriers included smoking rate, medical history/contraindicated medication, lack of interest, and language. Compared to enrollees, decliners were more likely to have advanced cancer. The trial enrolled a sample of 67 (>30%) African Americans; participants had extensive smoking histories; many were highly nicotine dependent; and participants consumed about seven alcoholic beverages/week on average. Head and neck and breast cancer were the most common tumors. About 52 (25%) reported depressive symptoms. A higher level of confidence to quit smoking was related to lower depression and lower tumor stage. Integrating a smoking cessation clinical trial into the oncologic setting is challenging, yet feasible. Recruitment strategies are needed for patients with advanced disease and specific cancers. Once enrolled, addressing participant's depressive symptoms is critical for promoting cessation. © 2008 Springer Science+Business Media B.V.
Keywords: amfebutamone; nicotine patch; adult; advanced cancer; African American; alcohol consumption; alcoholic beverage; article; breast cancer; cancer patient; cancer screening; clinical trial; controlled study; data analysis; depression; disease severity; drug contraindication; feasibility study; female; head and neck cancer; human; language; major clinical study; male; nicotine replacement therapy; priority journal; smoking cessation; smoking habit; tobacco dependence; zyban

The influence of black race on treatment and mortality for early-stage breast cancer - Berz, J.P.B.; Johnston, K.; Backus, B.; Doros, G.; Rose, A.J.; Pierre, S.; Battaglia, T.A. (Medical Care, 2009)
BACKGROUND: Black Americans have higher mortality from breast cancer than white Americans. This study explores the influence of socioeconomic factors and black race on treatment and mortality for early-stage breast cancer. METHODS: A cohort of 21,848 female black and white, non-Hispanic subjects from the Massachusetts Cancer Registry diagnosed with stage I or II breast cancer between 1999-2004 was studied. Subjects with tumors larger than 5 cm were excluded. We used mixed modeling methods to assess the impact of race on guideline concordant care (GCC), defined as receipt of mastectomy or breast conserving surgery plus radiation. Cox proportional hazard regression was used to assess disease-specific mortality. RESULTS: Blacks were less likely to receive GCC after adjusting for age and clinical variables (OR: 0.75; 95% CI: 0.61, 0.92). Marital status and insurance were predictors of receipt of GCC. After adjustment for all covariates, there were no longer significant differences between black and white women regarding the receipt of GCC. Nevertheless, black women were more likely to die of early-stage breast cancer than white women after adjusting for clinical, treatment, socioeconomic variables, and reporting hospital (HR: 1.6; 95% CI: 1.1-2.1). CONCLUSIONS: Socioeconomic factors are mediators of racial differences in treatment outcomes. Significant racial differences exist in disease-specific mortality for women with early-stage breast cancer. Attention to reducing socioeconomic barriers to care may influence racial differences in breast cancer treatment and mortality. © 2009 Lippincott Williams & Wilkins, Inc.
Keywords: adult; African American; aged; article; breast carcinoma; cancer mortality; cancer radiotherapy; cancer registry; cancer staging; controlled study; European American; female; health insurance; human; major clinical study; mastectomy; patient selection; practice guideline; race difference; socioeconomics; United States

The Prostate cancer Intervention Versus Observation Trial:VA/NCI/AHRQ Cooperative Studies Program #407 (PIVOT): Design and baseline results of a randomized controlled trial comparing radical prostatectomy to watchful waiting for men with clinically localized prostate cancer - Wilt, T.J.; Brawer, M.K.; Barry, M.J.; Jones, K.M.; Kwon, Y.; Gingrich, J.R.; Aronson, W.J.; Nsouli, I.; Iyer, P.; Cartagena, R.; Snider, G.; Roehrborn, C.; et al. (Contemporary Clinical Trials, 2009)
Background: Prostate cancer is the most common noncutaneous malignancy and the second leading cause of cancer death in men. Ninety percent of men with prostate cancer are over aged 60 years, diagnosed by early detection with the prostate specific antigen (PSA) blood test and have disease believed confined to the prostate gland (clinically localized). Common treatments for clinically localized prostate cancer include watchful waiting surgery to remove the prostate gland (radical prostatectomy), external beam radiation therapy and interstitial radiation therapy (brachytherapy) and androgen deprivation. Little is known about the relative effectiveness and harms of treatments due to the paucity of randomized controlled trials. The VA/NCI/AHRQ Cooperative Studies Program Study #407: Prostate cancer Intervention Versus Observation Trial (PIVOT), initiated in 1994, is a multicenter randomized controlled trial comparing radical prostatectomy to watchful waiting in men with clinically localized prostate cancer. Methods: We describe the study rationale, design, recruitment methods and baseline characteristics of PIVOT enrollees. We provide comparisons with eligible men declining enrollment and men participating in another recently reported randomized trial of radical prostatectomy versus watchful waiting conducted in Scandinavia. Results: We screened 13,022 men with prostate cancer at 52 United States medical centers for potential enrollment. From these, 5023 met initial age, comorbidity and disease eligibility criteria and a total of 731 men agreed to participate and were randomized. The mean age of enrollees was 67 years. Nearly one-third were African-American. Approximately 85% reported they were fully active. The median prostate specific antigen (PSA) was 7.8 ng/mL (mean 10.2 ng/mL). In three-fourths of men the primary reason for biopsy leading to a diagnosis of prostate cancer was a PSA elevation or rise. Using previously developed tumor risk categorizations incorporating PSA levels, Gleason histologic grade and tumor stage, approximately 43% had low risk, 36% had medium risk and 20% had high-risk prostate cancer. Comparison to our national sample of eligible men declining PIVOT participation as well as to men enrolled in the Scandinavian trial indicated that PIVOT enrollees are representative of men being diagnosed and treated in the U.S. and quite different from men in the Scandinavian trial. Conclusions: PIVOT enrolled an ethnically diverse population representative of men diagnosed with prostate cancer in the United States. Results will yield important information regarding the relative effectiveness and harms of surgery compared to watchful waiting for men with predominately PSA detected clinically localized prostate cancer.
Keywords: prostate specific antigen; adult; African American; aged; article; cancer diagnosis; cancer localization; cancer risk; cancer staging; comorbidity; comparative study; controlled study; Gleason score; hospital admission; human; human tissue; major clinical study; male; methodology; prostate biopsy; prostate cancer; prostatectomy; randomized controlled trial; Scandinavia; United States

Sampling in population-based cancer caregivers research - Kim, Y.; Kashy, D.A.; Kaw, C.K.; Smith, T.; Spillers, R.L. (Quality of Life Research, 2009)
Background: Awareness that cancer impacts not only the person with the disease but also the family has increased, yet existing data provide limited information, primarily because of reliance on small geographically restricted samples. The current study used population-based sampling to develop a formula to compute the probability of survivors completing a survivor survey and nominating their family caregivers. Methods: Eleven SEER/NPCR state cancer registries participated in the American Cancer Society Study of Cancer Survivors survey, providing information about the survivors, including their age, race/ethnicity, gender, type of cancer, and stage of cancer. A total of 19,294 cancer survivors met the inclusion criteria (≥18 years old and diagnosed with one of the 10 common cancers). Results: Approximately 30% of survivors identified from state cancer registries completed the survivor survey, of whom 42% nominated a caregiver. Logistic regression analysis revealed that middle-aged, female, or non-black survivors and survivors diagnosed with breast or ovarian cancer were more likely to complete the survey and nominate a caregiver, whereas survivors with bladder or lung cancer and survivors with advanced-stage cancer were less likely to complete the survey and nominate a caregiver. Conclusions: Using the formula based on the logistic regression analysis results, a number of certain groups of survivors to be recruited from state registry can be calculated in order to have a present number of caregivers to contact for participation into a caregiver study. This is practical and valuable information, which fosters research that uses state cancer registries and increases the generalizability of findings to multiple types of cancer and different stages of cancer. © 2009 Springer Science+Business Media B.V.
Keywords: adult; aged; article; bladder cancer; breast cancer; cancer registry; cancer research; cancer staging; cancer survivor; caregiver; controlled study; female; groups by age; health survey; human; lung cancer; major clinical study; male; neoplasm; non profit organization; ovary cancer; priority journal; race difference; sex difference

Do preparation and life completion discussions improve functioning and quality of life in seriously ill patients? Pilot randomized control trial - Steinhauser, K.E.; Alexander, S.C.; Byock, I.R.; George, L.K.; Olsen, M.K.; Tulsky, J.A. (Journal of Palliative Medicine, 2008)
Background: Significant palliative care intervention has focused on physical pain and symptom control; yet less empirical evidence supports efforts to address the psychosocial and spiritual dimensions of experience. Objective: To evaluate the impact of an intervention (Outlook) that promotes discussions of end-of-life preparation and completion on health outcomes in dying persons, including pain and symptoms, physical function, emotional function (anxiety and depression), spiritual well-being, and quality of life at the end of life. Design: A three-arm pilot randomized control trial. Subjects were recruited from inpatient and outpatient hospital, palliative care, and hospice settings. Intervention subjects met with a facilitator three times and discussed issues related to life review, forgiveness, and heritage and legacy. Attention control subjects met with a facilitator three times and listened to a nonguided relaxation CD. True control subjects received no intervention. Measurements: Preoutcomes and postoutcomes included the Memorial Symptom Assessment Scale, QUAL-E, Rosow-Breslau ADL Scale, Profile of Mood States anxiety sub-scale, the CESD short version, and the Daily Spiritual Experience Scale. Results: Eighty-two hospice eligible patients enrolled in the study; 38 were women, 35 were African American. Participants' primary diagnoses included cancer (48), heart disease (5) lung disease (10), and other (19) Ages ranged from 28-96. Participants in the active discussion intervention showed improvements in functional status, anxiety, depression, and preparation for end of life. Conclusions: The Outlook intervention was acceptable to patients from a variety of educational and ethnic backgrounds and offers a brief, manualized, intervention for emotional and spiritual concerns. © 2008 Mary Ann Liebert, Inc.
Keywords: anxiety; article; attitude to death; clinical article; clinical trial; controlled clinical trial; controlled study; degenerative disease; depression; female; heart disease; hospice care; human; kidney failure; lung disease; male; neoplasm; outpatient care; pain assessment; palliative therapy; pilot study; quality of life; randomized controlled trial

Comparison of four different immunosuppression protocols without long-term steroid therapy in kidney recipients monitored by surveillance biopsy: Five-year outcomes - Anil Kumar, M.S.; Irfan Saeed, M.; Ranganna, K.; Malat, G.; Sustento-Reodica, N.; Kumar, A.M.S.; Meyers, W.C. (Transplant Immunology, 2008)
Induction and maintenance immunosuppression protocols with or without long-term steroid therapy in kidney transplant recipients are variable and are transplant center-specific. The aim of this prospective randomized pilot study was to compare 5-year outcomes in kidney recipients maintained on 4 different calcineurin inhibitor (CNI)-based immunosuppression protocols without long-term steroid therapy. Two hundred consenting patients who received kidney transplants between June 2000 and October 2004 were enrolled in 4 immunosuppression protocol groups, with 50 patients in each group: cyclosporine (CSA)/mycophenolate mofetil (MMF), CSA/sirolimus (SRL), tacrolimus (TAC)/MMF, and TAC/SRL. Induction therapy was done with basiliximab and methylprednisolone. Steroids were withdrawn on post-transplant day 2, and long-term steroid therapy was not used. Demographic characteristics among the four groups were comparable; approximately 50% of the recipients were African American and ≥ 80% of the kidneys transplanted were from deceased donors. Clinical acute rejection (CAR) was confirmed by biopsy and treated with intravenous pulse steroid therapy. Steroid-unresponsive CAR was treated with Thymoglobulin. Surveillance biopsies were performed at 1, 6, 12, 24, 36, 48, and 60 months to evaluate subclinical acute rejection (SCAR), chronic allograft injury (CAI), and other pathological changes per the Banff 2005 schema. The primary end point was CAR, and secondary end points were 5-year patient and graft survival rates, renal function, SCAR, CAI, and adverse events. In the first year post-transplant, the incidence of CAR was 18% in the CSA/MMF group, 8% in the CSA/SRL group, 14% in the TAC/MMF group, and 4% in the TAC/SRL group (CSA/MMF vs. TAC/SRL; p = 0.05). The incidence of SCAR was 22% in the CSA/MMF group, 8% in the CSA/SRL group, 16% in the TAC/MMF group, and 6% in the TAC/SRL group (CSA/MMF vs. CSA/SRL and TAC/SRL; p = 0.05). After the first year, the incidences of CAR and SCAR decreased and were comparable in all 4 groups. At 5 years post-transplant, cumulative CAI due to interstitial fibrosis/tubular atrophy (IF/TA), hypertension (HTN), and chronic calcineurin inhibitor (CNI) toxicity was observed in 54%, 48%, and 8% of the CSA/MMF group vs. 16%, 36%, and 12% of the CSA/SRL group vs. 38%, 24% and 6% of the TAC/MMF group vs. 14%, 25% and 12% of the TAC/SLR group (IF/TA: CSA/MMF vs. CSA/SRL and TAC/SRL; p = 0.04, HTN: CSA/MMF vs. TAC/MMF and TAC/SRL; p = 0.05, CNI toxicity: TAC/SRL and CSA/SRL vs. TAC/MMF; p = 0.05). Five-year patient and graft survival rates were 82% and 60% in the CSA/MMF group, 82% and 60% in the CSA/SRL group, 84% and 62% in the TAC/MMF group, and 82% and 64% in the TAC/SRL group (p = 0.9). Serum creatinine levels and creatinine clearances at 5 years were comparable among the groups. Our data show that the rates of CAR and SCAR in the first year post-transplant were significantly lower in the CSA/SRL and TAC/SRL groups and that cumulative CAI rates due to IF/TA and HTN at 5 years were significantly lower in the TAC/MMF, TAC/SRL, and CSA/SRL groups than in the CSA/MMF group. Despite significant differences in the incidences of CAR and SCAR and prevalence of different types of CAI at 5 years, renal function and patient and graft survival rates at 5 years were comparable among kidney recipients maintained on 4 different immunosuppression protocols without long-term steroid therapy. © 2008 Elsevier B.V. All rights reserved.
Keywords: basiliximab; calcineurin inhibitor; cotrimoxazole; creatinine; cyclosporine; erythropoietin; insulin; methylprednisolone; mycophenolate mofetil; oral antidiabetic agent; rapamycin; tacrolimus; thymocyte antibody; valganciclovir; acute graft rejection; acute kidney failure; adult; African American; anemia; article; bacterial infection; biopsy; biopsy technique; bladder cancer; breast cancer; clinical trial; colon cancer; comparative study; controlled clinical trial; controlled study; creatinine blood level; creatinine clearance; cytomegalovirus infection; delayed graft function; demography; diabetes mellitus; drug dose increase; drug withdrawal; female; fibrosing alveolitis; gastrointestinal symptom; graft recipient; graft survival; human; human tissue; hyperlipidemia; hypertension; immunosuppressive treatment; infection; kidney; kidney carcinoma; kidney donor; kidney function; kidney graft; leukemia; lung cancer; lymphoproliferative disease; major clinical study; male; monitoring; morbidity; mouth ulcer; outcome assessment; parotid gland cancer; pilot study; pneumocystosis; prevalence; priority journal; prospective study; prostate cancer; pyelonephritis; randomized controlled trial; steroid therapy; survival rate; thyroid cancer; wound healing; wound healing impairment

Racial differences in clinical outcomes from metastatic breast cancer: A pooled analysis of CALGB 9342 and 9840 - Cancer and leukemia group B - Polite, B.N.; Cirrincione, C.; Fleming, G.F.; Berry, D.A.; Seidman, A.; Muss, H.; Norton, L.; Shapiro, C.; Bakri, K.; Marcom, K.; Lake, D.; Schwartz, J.H.; et al. (Journal of Clinical Oncology, 2008)
Purpose: African American women are more likely to be diagnosed with metastatic breast cancer at the time of presentation than whites, and have shorter survival once diagnosed. This study examines racial differences in clinical outcomes in the setting of two large cooperative group randomized clinical trials. Patients and Methods: The study cohort consisted of 787 white (80%) and 195 African American (20%) patients with metastatic breast cancer enrolled in two successive Cancer and Leukemia Group B (CALGB) trials using taxanes in the metastatic setting. Differences in overall survival (OS), response incidence, and time to treatment failure (TTF) were examined by race. In addition, differences in the incidence of baseline and treatment-related toxicities were examined. Results: With 779 deaths (166 African Americans and 613 whites), median OS was 14.3 months for African Americans and 18.75 months for whites (hazard ratio [HR] = 1.37; 95% CI, 1.15 to 1.63). When adjusted for prognostic factors, African Americans had a 24% increase in the hazard of death compared with whites (HR = 1.24; 95% CI, 1.02 to 1.51). No significant differences in TTF or overall response to therapy were seen. No clinically significant toxicity differences were seen. Conclusion: African Americans with metastatic breast cancer have an increased hazard of death compared with whites despite the receipt of similar per-protocol treatment, but experience no differences in TTF or overall response to therapy. We hypothesize that more direct and robust measures of comorbidities, and perhaps other factors such as receipt of subsequent therapy could help further explain the observed survival difference. © 2008 by American Society of Clinical Oncology.
Keywords: paclitaxel; trastuzumab; adult; aged; anemia; article; breast cancer; cancer chemotherapy; cancer mortality; cancer survival; clinical trial; cohort analysis; comorbidity; confidence interval; controlled clinical trial; controlled study; female; hazard ratio; human; infection; leukopenia; lymphocytopenia; major clinical study; metastasis; motor neuropathy; priority journal; prognosis; race difference; randomized controlled trial; sensory neuropathy; thrombocytopenia; treatment failure; treatment response

Cancer incidence in elderly medicare and dually eligible beneficiaries - Bradley, C.J.; Luo, Z.; Given, C.W. (Health Services Research, 2008)
Objective. We assessed how Medicaid enrollment and race influence cancer incidence among patients age 65 years and older. Data Sources and Method. Population-based Michigan Tumor Registry was merged with Medicaid eligibility files for 1996 through 2000. All analyses were age-adjusted and gender-specific. We compared cancer incidence in the elderly Medicaid population to the cancer incidence in the Medicare population. We then examined cancer incidence in patients continuously enrolled in Medicaid 12 or more months relative to the incidence in the Medicare population. Principal Findings. When comparing cancer incidence in Medicaid patients without regard to enrollment before diagnosis, the incidence rates of prostate cancer in black men and colorectal cancer in black women were statistically higher relative to the incidence rates in white patients. The overall cancer incidence rate for all cancers combined was statistically significantly higher for black women and men compared with white women and men (incidence rate ratio=1.18 and 1.48, 95 percent confidence interval 1.05-1.32 and 1.28-1.71, respectively). In dually eligible patients enrolled 12 or more months before diagnosis, an excess cancer incident was observed for black patients relative to white patients in every cancer site examined with the exception of lung cancer. Conclusions. Medicaid data in addition to Medicare data revealed patterns of cancer incidence that varied according to Medicaid enrollment and race. These findings suggest that the cancer burden among African Americans and dually eligible patients is substantial. © Health Research and Educational Trust.
Keywords: aged; article; cancer incidence; cancer registry; colorectal cancer; elderly care; female; geriatric care; groups by age; human; male; medicaid; medicare; population research; prostate cancer; race difference; sex difference

A randomized trial comparing web-based decision aids on prostate cancer knowledge for African-American men - Ellison, G.L.; Weinrich, S.P.; Lou, M.; Xu, H.; Powell, I.J.; Baquet, C.R. (Journal of the National Medical Association, 2008)
Context: Few decision aids are tailored for African-American men. We sought to determine if web-based decision aids increased knowledge of prostate cancer screening among African men. Methods: This postintervention, quasiexperimental research measured knowledge of prostate cancer screening among African-American men following receipt of 1 of 2 web-based decision aids: enhanced or usual care. Men ages 40-65 were recruited at the annual convention of the Prince Hall Masons in the summer of 2007, which was attended by 1,170 masons. The primary outcome was knowledge of prostate cancer screening. Results: There were 87 participants in the sample with a mean age of 52 years (standard deviation=6.9). forty-six masons were randomized to the enhanced decision aid, and 41 masons were randomized to the usual care decision aid. Knowledge scores were statistically significantly higher among the men receiving the enhanced decision aid compared to the usual care decision aid after simultaneously adjusting for age, educational level, marital status, family history, previous prostate specific antigen test and digital rectal exam (ñ=0.01). Concision: We found evidence that the enhanced web decision aid was significantly more effective than the usual care decision aid in promoting knowledge of the benefits, limitations and risks of prostate cancer screening. Webbased sites may be effective in facilitating discussions about screening between patients and health care providers.
Keywords: adult; African American; anamnesis; article; bivariate analysis; cancer screening; decision support system; demography; human; Internet; knowledge base; male; multivariate analysis; priority journal; prostate cancer

Harvest health: Translation of the chronic disease self-management program for older African Americans in a senior setting - Gitlin, L.N.; Chernett, N.L.; Harris, L.F.; Palmer, D.; Hopkins, P.; Dennis, M.P. (Gerontologist, 2008)
Purpose: We describe the translation of K. R. Lorig and colleagues' Chronic Disease Self-Management Program (CDSMP) for delivery in a senior center and evaluate pre-post benefits for African American participants. Design and Methods: Modifications to the CDSMP included a name change; an additional introductory session; and course augmentations involving culturally relevant foods, stress reduction techniques, and communicating with racially/ethnically diverse physicians. We recruited participants from senior center members, area churches, and word of mouth. We conducted baseline and 4-month post-interviews. Results: A total of 569 African American elders attended an introductory session, with 519 (91%) enrolling in the 6-session program. Of the 519, 444 (86%) completed ≥4 sessions and 414 (79%) completed pre-post interviews. We found small but statistically significant improvements for exercise (p = .001), use of cognitive management strategies (p = .001), energy/fatigue (p = .001), self-efficacy (p = .001), health distress (p = .001), and illness intrusiveness in different life domains (probabilities from .001-.021). We found no changes for health utilization. Outcomes did not differ by gender, number of sessions attended, number and type of chronic conditions, facilitator, leader, or recruitment site. Implications: The CDSMP can be translated for delivery by trained senior center personnel to African American elders. Participant benefits compare favorably to original trial outcomes. The translated program is replicable and may help to address health disparities.
Keywords: adult; African American; aged; arthritis; article; asthma; chronic disease self management program; chronic obstructive lung disease; cognition; cultural factor; diabetes mellitus; distress syndrome; energy; ethnic difference; exercise; fatigue; female; food; health care delivery; health care utilization; health program; health status; heart disease; human; hypertension; interpersonal communication; interview; male; neoplasm; outcome assessment; physical activity; probability; race difference; self concept; sex difference; social stress; physiological stress

Recruiting African-American barbershops for prostate cancer education - Hart Jr., A.; Underwood, S.M.; Smith, W.R.; Bowen, D.J.; Rivers, B.M.; Jones, R.A.; Parker, D.; Allen, J. (Journal of the National Medical Association, 2008)
Prostate cancer is the most common cause of cancer in men and the second leading cause of cancer deaths. African-American men bear a disproportionate burden of prostate cancer diagnosis and mortality. Current guidelines for prostate cancer screening differ among various medical organizations. Therefore, it is important that African-American men have the appropriate information needed to make informed decisions about prostate cancer screening. Unfortunately, a large percentage of African-American men could potentially be excluded from receiving culturally appropriate prostate cancer education. Therefore, a study was designed to recruit and intervene with African-American men and barbershops for increasing prostate cancer screening decision-making. The purpose of this study was to learn effective strategies for recruiting African-American barbershops for prostate cancer education and to determine barbershop proprietors' willingness to allow their barbershops to be used for research. In this paper, we present the outcomes of our recruitment methods for African-American barbershops, including a comparative description of participating and nonparticipating barbershops using the iMark Data System. One-hundred percent of the surveyed proprietors reported that they would allow their clients to learn about prostate cancer. Ninety-six percent reported they would consider allowing their clients to have access to handheld computers to learn about prostate cancer. We conclude from this study that African-American barbershops in general are welcoming environments in which to implement community-based prostate cancer education and public health research.
Keywords: adult; African American; aged; article; computer; human; major clinical study; male; patient education; priority journal; prostate cancer; public health

Interethnic differences in drug metabolism - Goh, B.C. (Clinical Advances in Hematology and Oncology, 2008)
Keywords: gimeracil plus oteracil potassium plus tegafur; antineoplastic agent; carboplatin; cytochrome P450 3A4; docetaxel; doxorubicin; drug metabolizing enzyme; African American; American Indian; article; Asian; breast cancer; cancer research; Caucasian; Chinese; clinical trial; cultural factor; dosimetry; drug determination; drug disposition; drug industry; drug labeling; drug manufacture; drug metabolism; drug research; drug safety; ethnic difference; ethnicity; Food and Drug Administration; genetic polymorphism; hematologic disease; Hispanic; human; Indian; individualization; international cooperation; non small cell lung cancer; malignant neoplasm; metastasis potential; methodology; Black person; Pacific Islander; patient selection; population genetics; practice guideline; race difference; sample size; Singapore; social aspect; standardization; treatment outcome; United States; s 1; taxotere

Timing is everything: Methodologic issues locating and recruiting medically underserved women for abnormal mammography follow-up research - Fair, A.M.; Wujcik, D.; Lin, J.-M.S.; Egan, K.M.; Grau, A.M.; Zheng, W. (Contemporary Clinical Trials, 2008)
Objectives: Recruiting underserved women in breast cancer research studies remains a significant challenge. We present our experience attempting to locate and recruit minority and medically underserved women identified in a Nashville, Tennessee public hospital for a mammography follow-up study. Study design: The study design was a retrospective hospital-based case-control study. Methods: We identified 227 women (88 African-American, 65 Caucasian, 36 other minority, 38 race undocumented in the medical record) who had undergone screening mammography and received an abnormal result during 2003-2004. Of the 227 women identified, 159 women were successfully located with implementation of a tracking protocol and more rigorous attempts to locate the women using online directory assistance and public record search engines. Women eligible for the study were invited to participate in a telephone research survey. Study completion was defined as fully finishing the telephone survey. Results: An average of 4.6 telephone calls (range 1-19) and 2.7 months (range 1-490 days) were required to reach the 159 women contacted. Within three contact attempts, more cases were located than controls (61% cases vs. 49% controls, p = 0.03). African-American women cases were four times likely to be recruited than African-American controls, (OR, 4.07; 95% CI, 1.59-10.30) (p = 0.003). After 3 months of effort, we located 67% of African-American women, 63% of Caucasian women, and 56% of other minorities. Ultimately, after a maximum of 12 attempts to contact women, 77% of African-American women and 71% of Caucasian women were eventually found. Of these, 59% of African-American women, 69% Caucasian women, and 50% other minorities were located and completed the study survey for an overall response rate of 59%, 71%, and 47% respectively. Conclusions: Data collection and study recruitment efforts were more challenging in racial and ethnic minorities. Continuing attempts to contact women may increase minority group study participation but does not guarantee retention or study completion. © 2008 Elsevier Inc. All rights reserved.
Keywords: adult; African American; aged; article; breast cancer; cancer screening; case control study; clinical protocol; European American; female; follow up; human; lowest income group; major clinical study; mammography; minority group; patient compliance; patient participation

Using focus groups to adapt ethnically appropriate, information-seeking and recruitment messages for a prostate cancer screening program for men at high risk - Bryan, C.J.; Wetmore-Arkader, L.; Calvano, T.; Deatrick, J.A.; Giri, V.N.; Bruner, D.W. (Journal of the National Medical Association, 2008)
Purpose: To adapt ethnically appropriate radio and newspaper messages in order to increase information-seeking and recruitment to the high-risk Prostate Cancer Risk Assessment Program (PRAP) using input from focus groups. Methods: We conducted four gender- and ethnic specificfocus groups composed of up to eight participants each. Group participants ranged in age from 35-69 and were either at risk for prostate cancer or were married to someone at risk. Participants evaluated both print and radio advertisements for a PRAP media recruitment campaign, and their recommendations were used to adapt the advertisements. Results: Trigger words, e.g., "research program," were found to be a particular, issue for African-American men who cited concerns about "experimentation," while the other groups cited concerns about time commitments and cost. In the print messages, familial themes garnered an overall favorable response, but Caucasian-American participants responded negatively to the use of photos of age-appropriate models. Conclusion: Focus groups are useful in checking health professional assumptions about health messages prior to developing awareness or recruitment advertisements or materials. There was an implied preference for "younger" models among Caucasian Americans. Radio and print messages were adapted using the focus group recommendations, i.e., focusing on familial themes, adding race-specific risk estimates and using younger-than-target group models.
Keywords: adult; advertising; African American; aged; article; cancer risk; cancer screening; clinical article; ethnic difference; European American; experimentation; human; information center; information processing; male; medical research; patient participation; priority journal; prostate cancer

Influence of church attendance and spirituality in a randomized controlled trial to increase mammography use among a low-income, tri-racial, rural community - Katz, M.L.; Kauffman, R.M.; Tatum, C.M.; Paskett, E.D. (Journal of Religion and Health, 2008)
Background The influence of church attendance and spirituality on mammography use was studied among Native American, White, and African American women living in a rural county. Methods A randomized trial was conducted to increase mammography use. Women (n = 851) were randomly assigned to receive either an educational program delivered by a lay health advisor or a physician letter and brochure about cervical cancer screening (control group). Church attendance and spirituality were measured at baseline and mammography use was evaluated 12 months after enrollment using medical record review. Results Almost two-thirds of the women reported that they attended church at least once a week, and less than 4% were classified as having low spirituality. Church attendance (P = 0.299) or spirituality (P = 0.401) did not have a significant impact on mammography use. Conclusions Church attendance and spirituality did not impact mammography use. © 2008 Blanton-Peale Institute.
Keywords: adult; African American; aged; American Indian; article; breast tumor; Caucasian; clinical trial; controlled clinical trial; controlled study; ethnology; female; human; mammography; middle aged; poverty; randomized controlled trial; religion; rural population; United States; utilization review

Barriers to recruiting urban African American women into research studies in community settings - Russell, K.M.; Maraj, M.S.; Wilson, L.R.; Shedd-Steele, R.; Champion, V.L. (Applied Nursing Research, 2008)
This qualitative study identified barriers to African American women's participation in a community-based behavioral intervention trial to increase mammography screening. Four themes emerged from focus group discussions with community agency providers and research team members. These themes were (1) going to the gatekeepers; (2) knowing the culture; (3) location is everything; and (4) protocols, policies, and possibilities. A checklist of actions that nurse researchers could consider to increase African American women's participation in community trials is provided. © 2008 Elsevier Inc. All rights reserved.
Keywords: adult; African American; aged; article; breast tumor; community care; ethnology; female; human; information processing; mammography; middle aged; patient attitude; patient selection; psychological aspect; urban population

Effects of baseline comorbidities on cancer screening trial adherence among older African American men - Ford, M.E.; Havstad, S.L.; Fields, M.E.; Manigo, B.; McClary, B.; Lamerato, L. (Cancer Epidemiology Biomarkers and Prevention, 2008)
Background: The purpose of this study was to examine the effects of baseline comorbidities on screening adherence in a sample of older African American men (ages ≥55 years) enrolled in a case management intervention in a cancer screening trial. Methods: Baseline comorbidity data were obtained from 683 African American men who were randomly assigned to a case management intervention group (n = 344) or to a case management control group (n = 339). The effects of comorbidities on the screening adherence rates of each group were then assessed. Results: No statistically significant interactions were found between each health history characteristic and the intervention. Therefore, analyses were not stratified by intervention status. In general, participants with comorbidities were no less likely to adhere to trial screening than participants without comorbidities. Exceptions were current smokers and participants with chronic bronchitis. Current smokers were less likely than others to adhere to the prostate-specific antigen test (P = 0.02) and the digital rectal examination for prostate cancer screening (P = 0.01), to the chest X-ray for lung cancer screening (P < 0.01), and to the flexible sigmoidoscopy for colorectal cancer screening (P = 0.04). Participants with chronic bronchitis had lower rates of adherence to the chest X-ray (P = 0.06). Having a relative with cancer positively influenced adherence to the digital rectal examination (P = 0.05). Conclusions: Overall, older African American men with comorbidities appear to be very good candidates for participation in longitudinal cancer screening trials. However, smoking had a statistically significant and deleterious effect on adherence to all types of screening. Copyright © 2008 American Association for Cancer Research.
Keywords: prostate specific antigen; adult; African American; aged; anamnesis; article; cancer screening; chronic bronchitis; colorectal cancer; comorbidity; controlled study; digital rectal examination; human; lung cancer; major clinical study; male; men's health; priority journal; sigmoidoscopy; smoking; statistical analysis; thorax radiography

Partnership with an African American sorority to enhance participation in cancer genetics research - Olsen, S.J.; Malvern, K.T.; May, B.J.; Jenkins, I.L.; Griffin, C.A. (Community Genetics, 2008)
Background/Aims: Reduced minority participation in clinical research challenges researchers to consider novel recruitment modalities. This study describes a formal partnership between the National Educational Foundation of the Zeta Phi Beta Sorority and the Mid-Atlantic Cancer Genetics Network. The goal was to enhance awareness about inherited breast cancer and to increase enrollment in the national Cancer Genetics Network. Methods: In this descriptive, pilot study, two recruitment strategies across four states were undertaken: an onsite educational session at four Annual State Leadership Conferences and a 2-tiered direct mail campaign to the sorority membership. Results: Recruitment methods targeted over 1,200 well-educated African American women. Of the 279 attendees at the state conference educational sessions, only 3 women meeting the high risk eligibility requirement enrolled. Direct mail recruitment elicited 24 eligible women. Lessons learned are described. Conclusion: Despite low accrual, the partnership laid a foundation for broader collaboration with the Zeta Phi Beta Sorority. In the future, collaboration with minority sororities and fraternities as part of standard registry recruitment should be explored. Copyright © 2008 S. Karger AG.
Keywords: adult; African American; aged; article; breast cancer; cancer genetics; cancer research; descriptive research; hereditary tumor syndrome; female; health education; high risk population; human; organization; pilot study; postal mail; priority journal; United States

Companion participation in cancer consultations - Street, R.L.; Gordon, H.S. (Psycho-Oncology, 2008)
Objective: Companions play an important role in cancer care. This investigation compared the communication of unaccompanied patients, accompanied patients, and companions during lung cancer consultations. Factors affecting the active participation of companions were analyzed. Methods: Participants included unaccompanied patients (N = 48), accompanied patients (N = 84), and companions (N = 84) of newly diagnosed lung cancer patients seen at a large southern VA medical center. The consultations were audiotaped, then transcribed. Coded utterances included patients' and companions' active participation (asking questions, expressing concerns, and making assertions) and physicians' use of facilitative communication. Mixed linear regression was used for comparisons of accompanied patients' participation to that of their companions and to determine the independent predictors of companion participation and patient satisfaction. Results: The combined companion plus patient participation did not differ from the participation of unaccompanied patients. Patterns of companion participation varied greatly as almost half the interactions had a relatively passive companion (contributed to less than 40% of the patient plus companion active participation) but 33% of the consultations had an active companion and passive patient. Companions with less active participation accompanied black patients and received proportionally less facilitative communication from physicians. Patient satisfaction was lower when companion and patient had similar levels of participation. Conclusion: Companions vary greatly in their participation in lung cancer visits. Physicians facilitate companion participation through the use of partnership-building and supportive communication. The companions of black patients were less active than their white counterparts which parallels other research indicating that black patients are often less active than white patients. Such communicative discrepancies could contribute to racial disparities in cancer care. Copyright © 2007 John Wiley & Sons, Ltd.
Keywords: aged; article; cancer patient; Caucasian; companion; consultation; controlled study; female; human; interpersonal communication; linear regression analysis; lung cancer; major clinical study; male; miscellaneous named groups; Black person; patient care; patient participation; patient satisfaction; United States

Enrollment of racial and ethnic minorities in the prostate, lung, colorectal and ovarian cancer screening trial - Pinsky, P.F.; Ford, M.; Gamito, E.; Higgins, D.; Jenkins, V.; Lamerato, L.; Tenorio, S.; Marcus, P.M.; Gohagan, J.K. (Journal of the National Medical Association, 2008)
Background: Minority populations in the United States, especially blacks and Hispanics, are generally underrepresented among participants in clinical trials. Here, we report the experience of enrolling ethnic minorities in a large cancer screening trial. Methods: The Prostate, Colorectal, Lung and Ovarian (PLCO) Cancer Screening Trial is a multicenter randomized trial designed to evaluate the effectiveness of screening for the PLCO cancers. Subjects were recruited at 10 U.S. centers between 1993 and 2001. One screening center had a major special recruitment effort for blacks and another center had a major special recruitment effort for Hispanics. Results: Among almost 155,000 subjects enrolled in PLCO, minority enrollment was as follows: black (5.0%), Hispanic (1.8%) and Asian (3.6%). This compares to an age-eligible population in the combined catchment areas of the PLCO centers that was 14.0% black, 2.9% Hispanic and 5.4% Asian, and an age-eligible population across the U.S. that was 9.5% black, 6.5% Hispanic and 3.0% Asian. About half (45%) of Hispanics were recruited at the center with the special Hispanic recruitment effort. Seventy percent of blacks were recruited at two centers; the one with the major special recruitment effort and a center in Detroit whose catchment area was 20% black among age-eligibles. Blacks, Hispanics and (non-Hispanic) whites were all more highly educated, less likely to currently smoke and more likely to get regular exercise than their counterparts in the general population. Conclusion: Significant efforts were made to recruit racial/ethnic minorities into PLCO, and these efforts resulted in enrollment levels that were comparable to those seen in many recent cancer screening or prevention trials. Blacks and Hispanics were nonetheless underrepresented in PLCO compared to their levels among age-eligibles in the overall U.S. population or in the aggregate PLCO catchment areas.
Keywords: academic achievement; adult; age distribution; aged; article; Asian; cancer center; cancer prevention; cancer screening; clinical trial; colorectal cancer; controlled clinical trial; controlled study; demography; ethnic group; exercise; experience; female; Hispanic; human; lung cancer; major clinical study; male; multicenter study; ovary cancer; priority journal; prostate cancer; randomized controlled trial; screening test; smoking

Intraoperative detection of sentinel lymph nodes using Patent Blue V in non-small cell lung cancer - Bustos, M.E.F.; Camargo, J.J.P.; Geyer, G.R.; Andrade, C.F. (Minerva Chirurgica, 2008)
Aim The aim of this article was to determine sentinel lymph node (SLN) identification rate (IR) using Patent Blue V in patients with non-small cell lung cancer (NSCLC) and to evaluate the accuracy of SLN for the presence of mediastinal metastasis. Methods. Between 2004 and 2006 the data from 32 patients with clinical stage IA to IIB, who underwent lung resection for NSCLC, were prospectively analyzed. Patent blue V dye was injected in the peritumoral tissue, and the first lymph node to stain was identified as a sentinel node. Results. SLN was identified in fifteen patients (IR=46.9%). SLN with metastatic involvement was observed in four patients. Accuracy, sensitivity and specificity of the sentinel lymph node in predicting the status of other mediastinal lymph node stations were respectively 86.7%, 100%, and 84.6%. In 63.1% patients, the SLNs corresponded to the lymph node stations 10 and 11. In seven patients (36.9%), the SLNs were located in the N2 stations. Conclusion, Although the use of Patent Blue V for SLN identification is feasible, this technique presents relatively low identification rate. The major difficulty on the detection of SLNs was the black coloration of the lymph node, which interfered with the visualization of the dye.
Keywords: coloring agent; diagnostic agent; adult; aged; article; cancer staging; comparative study; evaluation study; feasibility study; female; human; lung; non small cell lung cancer; lung tumor; lymph node metastasis; male; mediastinum; metastasis; middle aged; pathology; patient selection; peroperative care; prospective study; sensitivity and specificity; sentinel lymph node biopsy

Retention of African American women in cancer genetics research - Halbert, C.H.; Love, D.; Mayes, T.; Collier, A.; Weathers, B.; Kessler, L.; Stopfer, J.; Bowen, D.; Domchek, S. (American Journal of Medical Genetics, Part A, 2008)
Although retention is a critical component of longitudinal cancer genetics research, limited empirical data are available on predictors of study retention among populations that are difficult to enroll. We evaluated predictors of retention in cancer genetics research among African American women at increased risk for having a BRCA1 and BRCA2 (BRCA1/2) mutation. Participants were African American women (n = 192) at increased risk for hereditary breast-ovarian cancer who were enrolled in a longitudinal genetic counseling research study. Retention was evaluated separately for the 1-and 6-month follow-ups and in terms of overall retention (e.g., completion of both telephone interviews). Seventy-three percent of women and 65% of women were retained at the 1- and 6-month follow-ups respectively; in terms of overall retention, 60% of women were retained in both follow-up telephone interviews. Predictors of retention at 1-month included being employed (OR = 2.47, 95% CI = 1.24, 4.93, P = 0.01) whereas predictors of overall retention included having a personal history of breast and/or ovarian cancer (OR = 2.06, 95% CI = 1.07, 3.95, P = 0.03) and having completed genetic counseling (OR = 2.63, 95% CI = 1.39, 4.98, P = 0.003). These data suggest that once enrolled in genetic counseling research, the majority of African American women will continue to participate, especially if concrete clinical services are provided. © 2007 Wiley-Liss, Inc.
Keywords: adult; African American; article; brca2 oncogene; breast cancer; cancer genetics; cancer research; cancer risk; hereditary tumor syndrome; female; follow up; gene mutation; genetic counseling; human; longitudinal study; major clinical study; oncogene; ovary cancer; priority journal

An examination of the influence of patient race and ethnicity on expressed interest in learning about cancer clinical trials - Markman, M.; Petersen, J.; Montgomery, R. (Journal of Cancer Research and Clinical Oncology, 2008)
Purpose: A number of factors have been identified as being associated with the documented low accrual rate of minorities into cancer-related clinical trials in the USA. An important issue is the fundamental interest, or lack thereof, of these specific patient populations in actually considering study participation. Methods: To examine this issue, aggregate data were analyzed from a proprietary Internet-based decision support program (NexProfiler Treatment Option Tools for Cancer, NexCura®, Seattle, WA, USA) embedded into approximately 100 cancer-associated Web sites where responding patients (or their families) were asked, but not required, to identify their race/ethnicity (African-American, Asian-American, Caucasian and Hispanic) and to also respond to the question, "Are you interested in learning about clinical trials?". Results: Of the >60,000 patients who both self-identified their race/ethnicity and responded to the question regarding their desire to learn about clinical trials, approximately 10% were from the minority (non-Caucasian) groups. Of note, in all four malignancies analyzed (breast, colorectal, lung, and prostate) and in both patients ≤60 and >60 years of age, each of the three non-Caucasian populations expressed an interest in learning about such studies that was equal to, if not greater than, that observed in the Caucasian respondents. Conclusion: Assuming these provocative results regarding self-declared desire to learn about clinical trials can be confirmed by others with similar Internet-associated databases, this analysis suggests Web-based recruitment strategies may be an effective method to communicate with minority populations in the US (and, perhaps, elsewhere) with a specific interest in considering participation in cancer clinical trials. © 2007 Springer-Verlag.
Keywords: article; breast cancer; cancer research; clinical research; colorectal cancer; controlled study; ethnicity; health education; health program; health promotion; human; Internet; learning; lung cancer; major clinical study; priority journal; prostate cancer; race difference

Timing of menarche and first full-term birth in relation to breast cancer risk - Li, C.I.; Malone, K.E.; Daling, J.R.; Potter, J.D.; Bernstein, L.; Marchbanks, P.A.; Strom, B.L.; Simon, M.S.; Press, M.F.; Ursin, G.; Burkman, R.T.; Folger, S.G.; et al. (American Journal of Epidemiology, 2008)
Ages at menarche and first birth are established risk factors for breast cancer. The interval between these ages may also affect risk, since the breast is more susceptible to carcinogenic insults during this period than during the parous period. However, few investigators have studied this relation. Using logistic regression, the authors evaluated associations between the timing of reproductive events and breast cancer risk among 4,013 cases and 4,069 controls enrolled in a multicenter, population-based US case-control study of White and African-American women (1994-1998). For White, parous premenopausal and postmenopausal women, those who had an interval of ≥16 years between the ages of menarche and first birth had 1.5-fold (95% confidence interval (CI): 1.0, 2.2) and 1.4-fold (95% CI: 1.1, 1.8) increased risks of breast cancer, respectively, in comparison with those who had ≤5 years between these ages. Adjusting for age at first birth altered these risk estimates somewhat, to odds ratios of 1.5 (95% CI: 0.8, 2.9) and 1.0 (95% CI: 0.6, 1.5), respectively. These associations were stronger for lobular and hormone-receptor-positive tumors but were absent among premenopausal African-American women. The authors conclude that the interval between age at menarche and age at first birth is associated with the risk of hormonally sensitive types of breast cancer, particularly among White women. © The Author 2007. Published by the Johns Hopkins Bloomberg School of Public Health. All rights reserved.
Keywords: adult; article; breast cancer; cancer risk; clinical trial; controlled study; disease association; female; health hazard; human; lung carcinoma; menarche; multicenter study; reproduction

The effect of offering different numbers of colorectal cancer screening test options in a decision aid: A pilot randomized trial - Griffith, J.M.; Lewis, C.L.; Brenner, A.R.T.; Pignone, M.P. (BMC Medical Informatics and Decision Making, 2008)
Background. Decision aids can improve decision making processes, but the amount and type of information that they should attempt to communicate is controversial. We sought to compare, in a pilot randomized trial, two colorectal cancer (CRC) screening decision aids that differed in the number of screening options presented. Methods. Adults ages 48-75 not currently up to date with screening were recruited from the community and randomized to view one of two versions of our previously tested CRC screening decision aid. The first version included five screening options: fecal occult blood test (FOBT), sigmoidoscopy, a combination of FOBT and sigmoidoscopy, colonoscopy, and barium enema. The second discussed only the two most frequently selected screening options, FOBT and colonoscopy. Main outcomes were differences in screening interest and test preferences between groups after decision aid viewing. Patient test preference was elicited first without any associated out-of-pocket costs (OPC), and then with the following costs: FOBT-$10, sigmoidoscopy-$50, barium enema-$50, and colonoscopy-$200. Results. 62 adults participated: 25 viewed the 5-option decision aid, and 37 viewed the 2-option version. Mean age was 54 (range 48-72), 58% were women, 71% were White, 24% African-American; 58% had completed at least a 4-year college degree. Comparing participants that viewed the 5-option version with participants who viewed the 2-option version, there were no differences in screening interest after viewing (1.8 vs. 1.9, t-test p = 0.76). Those viewing the 2-option version were somewhat more likely to choose colonoscopy than those viewing the 5-option version when no out of pocket costs were assumed (68% vs. 46%, p = 0.11), but not when such costs were imposed (41% vs. 42%, p = 1.00). Conclusion. The number of screening options available does not appear to have a large effect on interest in colorectal cancer screening. The effect of offering differing numbers of options may affect test choice when out-of-pocket costs are not considered. © 2008 Griffith et al; licensee BioMed Central Ltd.
Keywords: adult; aged; article; barium enema; blood examination; cancer screening; clinical trial; colonoscopy; colorectal cancer; controlled clinical trial; controlled study; female; health care cost; human; male; medical decision making; occult blood; randomized controlled trial; sigmoidoscopy

Randomized controlled trial of yoga among a multiethnic sample of breast cancer patients: Effects on quality of life - Moadel, A.B.; Shah, C.; Wylie-Rosett, J.; Harris, M.S.; Patel, S.R.; Hall, C.B.; Sparano, J.A. (Journal of Clinical Oncology, 2007)
Purpose: This study examines the impact of yoga, including physical poses, breathing, and meditation exercises, on quality of life (QOL), fatigue, distressed mood, and spiritual well-being among a multiethnic sample of breast cancer patients. Patients and Methods: One hundred twenty-eight patients (42% African American, 31% Hispanic) recruited from an urban cancer center were randomly assigned (2:1 ratio) to a 12-week yoga intervention (n = 84) or a 12-week waitlist control group (n = 44). Changes in QOL (eg, Functional Assessment of Cancer Therapy) from before random assignment (T1) to the 3-month follow-up (T3) were examined; predictors of adherence were also assessed. Nearly half of all patients were receiving medical treatment. Results: Regression analyses indicated that the control group had a greater decrease in social well-being compared with the intervention group after controlling for baseline social well-being and covariates (P < .0001). Secondary analyses of 71 patients not receiving chemotherapy during the intervention period indicated favorable outcomes for the intervention group compared with the control group in overall QOL (P < .008), emotional well-being (P < .015), social well-being (P < .004), spiritual well-being (P < .009), and distressed mood (P < .031). Sixty-nine percent of intervention participants attended classes (mean number of classes attended by active class participants = 7.00 ± 3.80), with lower adherence associated with increased fatigue (P < .001), radiotherapy (P < .0001), younger age (P < .008), and no antiestrogen therapy (P < .02). Conclusion: Despite limited adherence, this intent-to-treat analysis suggests that yoga is associated with beneficial effects on social functioning among a medically diverse sample of breast cancer survivors. Among patients not receiving chemotherapy, yoga appears to enhance emotional well-being and mood and may serve to buffer deterioration in both overall and specific domains of QOL. © 2007 by American Society of Clinical Oncology.
Keywords: adult; African American; analytic method; article; breast cancer; breathing; cancer patient; clinical trial; comparative study; controlled study; distress syndrome; ethnic difference; fatigue; female; Hispanic; human; major clinical study; male; meditation; outcome assessment; priority journal; quality of life; regression analysis; spiritual care; wellbeing; yoga

A prospective study of body size and breast cancer in black women - Palmer, J.R.; Adams-Campbell, L.L.; Boggs, D.A.; Wise, L.A.; Rosenberg, L. (Cancer Epidemiology Biomarkers and Prevention, 2007)
The relation of body mass index (BMI) and weight gain to breast cancer risk is complex, and little information is available on Black women, among whom the prevalence of obesity is high. We assessed BMI and weight gain in relation to breast cancer risk in prospective data from the Black Women's Health Study. In 1995, 59,000 African American women enrolled in the Black Women's Health Study by completing mailed questionnaires. Data on anthropometric factors were obtained at baseline and every 2 years afterwards. In 10 years of follow-up, 1,062 incident cases of breast cancer occurred. Incidence rate ratios (IRR) were computed in multivariable Cox proportional hazards regression. BMI at age 18 years of ≥25 relative to <20 was associated with a reduced risk of breast cancer among both premenopausal women (IRR, 0.68; 95% confidence interval, 0.46-0.98) and postmenopausal women (IRR, 0.53; 95% confidence interval, 0.35-0.81). There was an inverse association of current BMI with premenopausal breast cancer but no association with postmenopausal breast cancer, either overall or among never-users of hormone therapy. Weight gain was not associated with postmenopausal breast cancer risk. In analyses restricted to breast cancers that were estrogen and progesterone receptor positive, IRRs for current BMI and weight gain were elevated but not statistically significant. The findings indicate that being overweight at age 18 years is associated with a reduced risk of both premenopausal and postmenopausal breast cancer in African American women. Understanding the reasons for the association may help elucidate the pathways through which adolescent exposures influence breast cancer risk. The lack of association of obesity with receptor-negative tumors in postmenopausal African American women may partially explain why breast cancer incidence in older Black women is not high relative to other ethnic groups in spite of the high prevalence of obesity in Black women. Copyright © 2007 American Association for Cancer Research.
Keywords: adult; aged; anthropometry; article; body mass; body size; breast cancer; cancer incidence; cancer risk; confidence interval; controlled study; disease association; female; follow up; human; major clinical study; obesity; postmenopause; premenopause; priority journal; waist hip ratio; body weight gain

Prostate cancer laterality as a rationale of focal ablative therapy for the treatment of clinically localized prostate cancer - Mouraviev, V.; Mayes, J.M.; Sun, L.; Madden, J.F.; Moul, J.W.; Polascik, T.J. (Cancer, 2007)
BACKGROUND. Early detection of small-volume prostate cancer (PCa) has led to the concept of focal therapy to treat PCa as an organ-sparing, minimally invasive procedure. The authors sought to determine the frequency of unilateral cancers in the contemporary prostate-specific antigen (PSA) era to determine the percentage of patients who would be candidates for hemiablation of the prostate by using focal therapy while preserving the contralateral lobe. METHODS. Paraffin-embedded radical prostatectomy specimens (1184 specimens) from consecutive patients between 2002 and 2006 with pathologic organ confined PCa were analyzed. Pathologic assessment focused on tumor laterality and percentage of tumor involvement (PTI) along with other routine parameters such as pathological T-classification (pT), pathological Gleason Score (pGS), extracapsular extension (ECE), and surgical margins (SM). Clinical and pathologic parameters were analyzed by univariate and multivariate methods. RESULTS. Completely unilateral cancers were identified in 227 (19.2%) of 1184 patients. Of these patients, 164 (72.2%) had PTI of ≤5%, 40 (17.6%) had a PTI of 5.01%-10%, 9 (4.0%) had a PTI of 10.01%-15%, and 14 (6.2%) had a PTI of > 15%, respectively (P < .0005). African-American men had bilateral cancers more commonly that non-African-American men, eg, 90.8% versus 79.2%, respectively (P < .0005). Race, PTI, pGS, and SM were independent predictors by multivariate logistic regression (P ≤ .05). CONCLUSIONS. This study suggests that 1 in 5 men diagnosed with PCa have small volume, completely unilateral cancers that may be amenable to hemiablation of the prostate. Further study is needed to develop predictive models to select candidates for focal therapy. © 2007 American Cancer Society.
Keywords: paraffin; prostate specific antigen; adult; African American; aged; article; cancer classification; cancer localization; catheter ablation; controlled study; disease severity; Gleason score; histopathology; human; human cell; human tissue; major clinical study; male; multivariate analysis; multivariate logistic regression analysis; patient selection; prediction; priority journal; prostate cancer; race difference

Direct mailing was a successful recruitment strategy for a lung-cancer screening trial - Hinshaw, L.B.; Jackson, S.A.; Chen, M.Y. (Journal of Clinical Epidemiology, 2007)
Objective: To analyze advertising, recruitment methods, and study participant demographics for the National Lung Screening Trial (NLST) site at Wake Forest University School of Medicine to define efficient ways to recruit participants for general clinical trials. Study Design and Setting: Recruitment method data, demographics, geographic location, and date of enrollment were collected from all 1,112 NLST participants. Marketing data and financial records were analyzed to determine the effectiveness of each recruitment method. Results: The total amount spent on advertising was $144,668, with the cost of enrollment per participant averaging $130. For black participants, the recruitment cost per person was $406, whereas for white and other race participants, the cost was $122 (P < 0.0001). To encourage minority enrollment, $13,192 was spent on television advertising geared toward black viewers, resulting in eight black participants at an average cost per person of $1,649. Direct mailing cost $143 per participant recruited, whereas TV ads cost $382 per participant. Conclusion: Direct mailing to a targeted group was the most efficient way to recruit participants. Printed advertising methods, that is, newspaper ads and brochures, were quite effective, whereas television ads were expensive. Appropriate minority recruitment needs sufficient attention and resources to ensure census groups are adequately represented. © 2007 Elsevier Inc. All rights reserved.
Keywords: adult; advertising; aged; article; cancer screening; computer assisted tomography; controlled study; demography; female; financial management; human; lung cancer; major clinical study; male; marketing; priority journal; thorax radiography

Recruiting diverse patients to a breast cancer risk communication trial - Waiting rooms can improve access - Bodurtha, J.N.; Quillin, J.M.; Tracy, K.A.; Borzelleca, J.; McClish, D.; Wilson, D.B.; Jones, R.M.; Quillin, J.; Bowen, D. (Journal of the National Medical Association, 2007)
Low participation among underserved populations in health research constrains progress in public health practices. From 2003 to 2005, Women's Health Clinic patients at the VCU Health System were-recruited to a trial investigating breast cancer risk communication. In secondary analyses, we examined dimensions of the recruitment of these diverse women. The sample characteristics (age, insurance, race and previous mammograms) were compared to the overall clinic. Of recruitment attempts for eligible women, 45% consented; of those who declined, the top cited reasons were lack of time (40%) and lack of interest (18%). Of 899 participants, 35% qualified for the indigent care program, compared to 31% of the overall clinic (P<.001). Forty-five percent of participants were African American, compared to 54% of overall clinic patients (P<.001). Participants were younger (50 vs. 53 years, P<.001) than the overall clinic population. Nonrepresentative enrollment of patients in clinical trials is common and could lead to suboptimal applicability of findings. Although there were statistically significant race and age differences between the study sample and the overall population, we demonstrate that waiting room recruitment can engage diverse women in a clinical trial and cancer risk communication.
Keywords: article; breast cancer; cancer risk; health care; health insurance; human; interpersonal communication; mammography; medical research; priority journal; public health service; race difference; statistical significance; waiting room; women's health

Who Enrolls Onto Clinical Oncology Trials? A Radiation Patterns of Care Study Analysis - Movsas, B.; Moughan, J.; Owen, J.; Coia, L.R.; Zelefsky, M.J.; Hanks, G.; Wilson, J.F. (International Journal of Radiation Oncology Biology Physics, 2007)
Purpose: To identify factors significantly influencing accrual to clinical protocols by analyzing radiation Patterns of Care Study (PCS) surveys of 3,047 randomly selected radiotherapy (RT) patients. Methods and Materials: Patterns of Care Study surveys from disease sites studied for the periods 1992-1994 and 1996-1999 (breast cancer, n = 1,080; prostate cancer, n = 1,149; esophageal cancer, n = 818) were analyzed. The PCS is a National Cancer Institute-funded national survey of randomly selected RT institutions in the United States. Patients with nonmetastatic disease who received RT as definitive or adjuvant therapy were randomly selected from eligible patients at each institution. To determine national estimates, individual patient records were weighted by the relative contribution of each institution and patients within each institution. Data regarding participation in clinical trials were recorded. The factors age, gender, race, type of insurance, and practice type of treating institution (academic or not) were studied by univariate and multivariate analyses. Results: Overall, only 2.7% of all patients were accrued to clinical protocols. Of these, 57% were enrolled on institutional review board-approved institutional trials, and 43% on National Cancer Institute collaborative group studies. On multivariate analysis, patients treated at academic facilities (p = 0.0001) and white patients (vs. African Americans, p = 0.0002) were significantly more likely to participate in clinical oncology trials. Age, gender, type of cancer, and type of insurance were not predictive. Conclusions: Practice type and race significantly influence enrollment onto clinical oncology trials. This suggests that increased communication and education regarding protocols, particularly focusing on physicians in nonacademic settings and minority patients, will be essential to enhance accrual. © 2007 Elsevier Inc. All rights reserved.
Keywords: adult; African American; aged; article; breast cancer; cancer patient; clinical protocol; education; esophagus cancer; female; gender; health insurance; human; institutional care; interpersonal communication; male; medical practice; medical record; multivariate analysis; oncology; physician; priority journal; prostate cancer; race; radiation; statistical significance; United States; univariate analysis; university hospital

Diagnostic accuracy of the gail model in the black women's health study - Adams-Campbell, L.L.; Makambi, K.H.; Palmer, J.R.; Rosenberg, L. (Breast Journal, 2007)
The Gail model is used to predict the risk of breast cancer in women of diverse race/ethnic groups for clinical trial protocols. However, this model has only been validated in US white women. Using a nested case-control study design, we evaluated the diagnostic accuracy of the original Gail model (GM) and that of the revised Gail model algorithm for blacks/African-Americans (GM-B) in the Black Women's Health Study (BWHS). Risk profiles were derived via a self reported questionnaire at the time of enrollment into the BWHS in 1995. Biennial questionnaires were obtained from the participants to determine the incident cases of breast cancer. The study of 725 breast cancer cases and 725 controls revealed that the 5-year risk of breast cancer based on the GM ranged from 0.2% to 15.4% among cases and 0.2% to 13.6% among the controls. Based on the GM-B, the 5-year risk of breast cancer ranged from 0.2% to 8.7% among cases and 0.2% to 7.2% among the controls. The sensitivities of the GM and GM-B model with the standard cutoff of 1.7% were 17.9% (95% CI: 15.9-19.9%) and 4.1% (95% CI: 3.0-5.2), respectively. Both the original and the modified version of the Gail model underestimate the risk of developing breast cancer in African-American women. More importantly, the modified Gail Model (GM-B) does a worse job at predicting the development of breast cancer for blacks than the original model (GM). © 2007 Copyright the Authors.
Keywords: adult; African American; algorithm; article; breast cancer; cancer incidence; cancer risk; controlled study; diagnostic accuracy; female; human; major clinical study; mathematical model; Black person; questionnaire; self report; sensitivity and specificity; women's health

Phase II trial of paclitaxel-topotecan-etoposide followed by consolidation chemoradiotherapy for limited-stage small cell lung cancer: CALGB 30002 - Miller, A.A.; Wang, X.F.; Bogart, J.A.; Hodgson, L.D.; Lima, C.M.S.R.; Radford, J.E.; Vokes, E.E.; Green, M.R. (Journal of Thoracic Oncology, 2007)
PURPOSE: We sought to evaluate the activity and tolerance of the rationally designed sequence of paclitaxel-topotecan-etoposide, a nonplatinum regimen, as induction therapy for limited-stage small-cell lung cancer before combined chemo- and radiotherapy. PATIENTS AND METHODS: Patients with measurable disease, performance status 0 to 2, no prior therapy, and adequate organ function were eligible. Paclitaxel (110 mg/m, administered intravenously on day 1), topotecan (1.5 mg/m, administered orally on days 2 to 4), and etoposide (160 mg/m, administered orally on days 5 to 7 every 21 days), with filgrastim for two cycles, were followed by chest irradiation to 70 Gy (to postinduction tumor volume) concurrent with carboplatin (area under the curve of 5, administered intravenously on day 1) and etoposide (100 mg/m on days 1 to 3 every 21 days) without filgrastim for three cycles (five chemotherapy cycles total). We aimed to determine the response rates to induction and overall therapy, overall and failure-free survival, and toxicity. The primary statistical endpoint was to differentiate between complete response rates of 50 and 70% for the overall treatment program. RESULTS: Between June 2001 and January 2003, 65 patients were enrolled, but one never started therapy, and one was ineligible. Patient characteristics included male/female, 27/36; white/black/other/unknown, 58/3/1/1; median age 62 (range, 38-78); performance status 0/1/2, 27/33/3. Induction chemotherapy resulted in six (10%) complete responses and 35 (56%) partial responses. Overall response to chemoradiotherapy included 27 (43%; 95% confidence interval [CI] 30-56%) complete responses and 24 (38%) partial responses. Median progression-free survival is 12 months (95% CI, 9-15 months). Median overall survival is 20 months (95% CI, 16-24 months). Frequent (>20%) grade 3/4 toxicities during all therapy included neutropenia, febrile neutropenia, anemia, thrombocytopenia, fatigue, and dysphagia. One patient died of febrile neutropenia, one died of febrile neutropenia and typhlitis, and one patient who declined transfusion for anemia died of cardiac ischemia. CONCLUSIONS: This treatment regimen has significant activity in limited-stage small-cell lung cancer but did not meet our prospectively defined criteria for further investigation in this setting. The addition of etoposide and the use of a sequenced administration schedule did not seem to improve overall activity beyond our prior experience with a topotecan-paclitaxel doublet. © 2007International Association for the Study of Lung Cancer.
Keywords: carboplatin; cimetidine; dexamethasone; diphenhydramine; etoposide; famotidine; paclitaxel; ranitidine; recombinant granulocyte colony stimulating factor; topotecan; adult; aged; article; cancer chemotherapy; cancer radiotherapy; cancer survival; clinical trial; confidence interval; disease free survival; drug efficacy; drug safety; drug tolerability; female; human; small cell lung cancer; major clinical study; male; multiple cycle treatment; phase 2 clinical trial; priority journal; survival time; treatment response; unspecified side effect; vomiting

Attitudes toward participation in breast cancer randomized clinical trials in the African American community: A focus group study - Linden, H.M.; Reisch, L.M.; Hart Jr., A.; Harrington, M.A.; Nakano, C.; Jackson, J.C.; Elmore, J.G. (Cancer Nursing, 2007)
Participation of African Americans in research trials is low. Understanding the perspectives of African American patients toward participation in clinical trials is essential to understanding the disparities in participation rates compared with whites. A qualitative study was conducted to discover attitudes of the African American community regarding willingness to participate in breast cancer screening and randomized clinical trials. Six focus groups consisting of 8 to 11 African American women (N = 58), aged 30 to 65, were recruited from local churches. Focus group sessions involved a 2-hour audio-taped discussion facilitated by 2 moderators. A breast cancer randomized clinical trial involving an experimental breast cancer treatment was discussed to identify the issues related to willingness to participate in such research studies. Six themes surrounding willingness to participate in randomized clinical trials were identified: (1) Significance of the research topic to the individual and/or community; (2) level of trust in the system; (3) understanding of the elements of the trial; (4) preference for "natural treatments" or "religious intervention" over medical care; (5) cost-benefit analysis of incentives and barriers; and (6) openness to risk versus a preference for proven treatments. The majority (80%) expressed willingness or open-mindedness to the idea of participating in the hypothetical trial. Lessons learned from this study support the selection of a culturally diverse research staff and can guide the development of research protocols, recruitment efforts, and clinical procedures that are culturally sensitive and relevant. © 2007 Lippincott Williams & Wilkins, Inc.
Keywords: antiinfective agent; adult; African American; aged; article; attitude to health; breast cancer; cancer screening; cancer therapy; clinical trial; controlled clinical trial; controlled study; cost benefit analysis; female; human; major clinical study; medical care; personnel; priority journal; qualitative research; randomized controlled trial; religion; risk

Prostate cancer community collaboration and partnership: education, awareness, recruitment, and outreach to southern African-American males. - Hughes, G.D.; Sellers, D.B.; Fraser Jr., L.; Teague, R.; Knight, B. (Journal of cultural diversity, 2007)
Prostate cancer is a significant health problem for African-American men intensified by low participation in screenings, clinical trials, and prospective cohort studies. Ten focus groups were conducted with African-American males and their female partners/spouses. Perceptions and knowledge about prostate cancer, as well as willingness to participate in screening and research studies were measured. Participants had a basic level of knowledge about prostate cancer, and the importance of education was a unified theme. Dialogue with targeted African-American men and their partners/spouses may increase awareness and retention in medical research, while influencing health promotion, education and behavior.
Keywords: African American; aged; article; attitude to health; awareness; consumer; cooperation; education; ethnology; female; health education; health service; human; information dissemination; information processing; male; mass screening; methodology; middle aged; nursing methodology research; organization and management; prostate tumor; psychological aspect; public relations; trust; United States

The Patient Safety in Surgery Study: Background, Study Design, and Patient Populations - Khuri, S.F.; Henderson, W.G.; Daley, J.; Jonasson, O.; Jones, R.S.; Campbell Jr., D.A.; Fink, A.S.; Mentzer Jr., R.M.; Steeger, J.E. (Journal of the American College of Surgeons, 2007)
Background: The purpose of this article is to describe the background, design, and patient populations of the Patient Safety in Surgery Study, as a preliminary to the articles in this journal that will report the results of the Study. Study Design: The Patient Safety in Surgery Study was a prospective cohort study. Trained nurses collected preoperative risk factors, operative variables, and 30-day postoperative mortality and morbidity outcomes in patients undergoing major general and vascular operations at 128 Veterans Affairs (VA) medical centers and 14 selected university medical centers between October 1, 2001 and September 30, 2004. An Internet-based data collection system was used to input data from the different private medical centers. Semiannual feedback of observed to expected mortality and morbidity ratios was provided to the participating medical centers. Results: During the 3-year study, total accrual in general surgery was 145,618 patients, including 68.5% from the VA and 31.5% from the private sector. Accrual in vascular surgery totaled 39,225 patients, including 77.8% from the VA and 22.2% from the private sector. VA patients were older and included a larger proportion of male patients and African Americans and Hispanics. The VA population included more inguinal, umbilical, and ventral hernia repairs, although the private-sector population included more thyroid and parathyroid, appendectomy, and operations for breast cancer. Preoperative comorbidities were similar in the two populations, but the rates of comorbidities were higher in the VA. American Society of Anesthesiologists classification tended to be higher in the VA. Conclusions: The National Surgical Quality Improvement Program methodology was successfully implemented in the 14 university medical centers. The data from the study provided the basis for the articles in this issue of the Journal of the American College of Surgeons. © 2007 American College of Surgeons.
Keywords: adult; aged; appendectomy; article; cancer surgery; clinical trial; comorbidity; controlled clinical trial; controlled study; female; general surgery; human; major clinical study; male; methodology; morbidity; mortality; multicenter study; outcome assessment; patient safety; patient selection; postoperative complication; priority journal; risk factor; surgery; thyroid surgery; treatment outcome; vascular surgery

Toward a model of prostate cancer information seeking: Identifying salient behavioral and normative beliefs among African American men - Ross, L.; Kohler, C.L.; Grimley, D.M.; Green, B.L.; Anderson-Lewis, C. (Health Education and Behavior, 2007)
Public health actions to improve African American men's ability to make informed decisions about participation in prostate cancer control activities have a greater likelihood of success when they are theory driven and informed by members of the target population. This article reports on formative research to evaluate the usefulness of the theory of reasoned action as a model to explain and predict prostate cancer information-seeking behavior by African American men. Fifty-two men participated in eight focus group interviews. Positive behavioral beliefs for obtaining prostate cancer information from physicians included increasing awareness of and obtaining accurate information about the disease, early detection and screening, and treatment. Negative beliefs included fear, distrust, and inconvenience. Significant others, peers, siblings, and religious leaders were identified as individuals who could influence this behavior. These findings provide additional insight into ways to reach and intervene with African American men to influence this important cancer control activity. © 2007 by SOPHE.
Keywords: adult; African American; aged; article; human; information processing; information service; male; middle aged; patient attitude; patient education; patient participation; prostate tumor; theoretical model; United States; utilization review

Ethnic differences in decisional balance and stages of mammography adoption - Otero-Sabogal, R.; Stewart, S.; Shema, S.J.; Pasick, R.J. (Health Education and Behavior, 2007)
Behavioral theories developed through research with mainstream, English-speaking populations have been applied to ethnically diverse and underserved communities in the effort to eliminate disparities in early breast cancer detection. This study tests the validity of the transtheoretical model (TTM) decisional balance measure and the application of the TTM stages of change in a multiethnic, multilingual sample. A random sample of 1,463 Filipino, Latino, African American, Chinese, and White women aged 40 to 74 completed a phone survey of mammography beliefs and practices. Consistent with the TTM and independent of ethnicity, decisional balance was associated with mammography stage in all five ethnic groups when controlling for socioeconomic and other factors. In addition, having private insurance and a regular physician and being a long-time resident in the United States were positively associated with mammography maintenance. The application of the TTM for mammography is supported in a multiethnic and multilingual sample. © 2007 by SOPHE.
Keywords: adult; aged; article; attitude to health; ethnic group; female; human; information processing; interview; mammography; middle aged; patient attitude; patient participation; theoretical model; United States; utilization review; validation study

A double-blind placebo-controlled randomized study of Chinese herbal medicine as complementary therapy for reduction of chemotherapy-induced toxicity - Mok, T.S.K.; Yeo, W.; Johnson, P.J.; Hui, P.; Ho, W.M.; Lam, K.C.; Xu, M.; Chak, K.; Chan, A.; Wong, H.; Mo, F.; Zee, B. (Annals of Oncology, 2007)
Background: Chinese herbal medicine (CHM) is a common complementary therapy used by patients with cancer for reduction of chemotherapy-induced toxic effects. This study applied the highest standard of clinical trial methodology to examine the role of CHM in reducing chemotherapy-induced toxicity, while maintaining a tailored approach to therapy. Patients and methods: Patients with early-stage breast or colon cancer who required postoperative adjuvant chemotherapy were eligible for the study. Enrolled patients were randomly assigned to one of three Chinese herbalists who evaluated and prescribed a combination of single-item packaged herbal extract granules. Patients received either CHM or placebo packages with a corresponding serial number. The placebo package contained nontherapeutic herbs with an artificial smell and taste similar to a typical herbal tea. The primary end points were hematologic and non-hematologic toxicity according to the National Cancer Institute Common Toxicity Criteria Version 2. Results: One hundred and twenty patients were accrued at the time of premature study termination. Patient characteristics of the two groups were similar. The incidence of grade 3/4 anemia, leukopenia, neutropenia, and thrombocytopenia for the CHM and placebo groups were 5.4%, 47.3%, 52.7%, and 1.8% and 1.8%, 32.2%, 44.7%, and 3.6%, respectively (P = 0.27, 0.37, 0.63, and 0.13, respectively). Incidence of grade 2 nausea was the only non-hematologic toxicity that was significantly reduced in the CHM group (14.6% versus 35.7%, P = 0.04). Conclusions: Traditional CHM does not reduce the hematologic toxicity associated with chemotherapy. CHM, however, does have a significant impact on control of nausea. © 2007 Oxford University Press.
Keywords: antineoplastic agent; black bean extract; Chinese drug; cyclophosphamide; dexamethasone; doxorubicin; fluorouracil; folinic acid; granisetron; herbaceous agent; maltose; metoclopramide; placebo; plant extract; unclassified drug; adjuvant therapy; adult; aged; alopecia; anemia; anorexia; article; blood toxicity; breast cancer; cancer adjuvant therapy; cancer chemotherapy; chemotherapy induced emesis; Chinese medicine; clinical trial; colon cancer; constipation; controlled clinical trial; controlled study; diarrhea; disease severity; dizziness; double blind procedure; drug granule; drug induced disease; drug induced headache; drug manufacture; drug toxicity; early cancer; fatigue; febrile neutropenia; female; herbal medicine; human; incidence; insomnia; leukopenia; major clinical study; male; multiple cycle treatment; nausea; neutropenia; odor; pain; patient compliance; pigment disorder; postoperative care; prescription; priority journal; randomized controlled trial; side effect; skin manifestation; stomatitis; tea; thrombocytopenia; adriamycin

Participation in surgical oncology clinical trials: Gender-, race/ethnicity-, and age-based disparities - Stewart, J.H.; Bertoni, A.G.; Staten, J.L.; Levine, E.A.; Gross, C.P. (Annals of Surgical Oncology, 2007)
Objective: To characterize the representation of racial/ethnic minorities, women, and older persons among participants in surgical trials sponsored by the National Cancer Institute (NCI). Methods: The NCI Clinical Trial Cooperative Group surgical oncology trials database was queried for breast, colorectal, lung, and prostate cancers treated during the period 2000-2002 (n=13,991). Data from the SEER program and the Census were used to estimate age-, gender-, and race/ethnicity-specific incidence of the same cancers among U.S. adults during the same period. Enrollment fraction (EF), defined as the number of trial enrollees divided by the estimated U.S. cancer cases in each demographic group, was the primary outcome measure. Logistic regression was used to compare the enrollment of racial/ethnic, gender and age subgroups in this analysis. Results: Relative to white patients (EF=0.72%), lower EFs were noted in African-American (0.48%, odds ratio[OR] vs whites 0.67, P<0.001), Hispanic (0.54%, OR 0.76, P<0.001), and Asian/Pacific islander (0.59%, OR 0.82, P=0.001) patients. Overall, women were more likely to enroll in surgical trials (1.12%) than men (0.22%, OR 5.06, P<0.001). Patients 65-74 years of age (EF 0.45%) were less likely to be enrolled than those 20-44 years of age (EF=2.28%, OR 0.20, P=0.001). Conclusions: The enrollment in surgical oncology trials is very low across all demographics. However, racial/ethnic minorities and older persons are less likely to be enrolled in cooperative group surgical oncology trials than are whites and younger patients. The high EF for women is due to the high availability of trials for women with breast cancer. Strategies to increase accrual to surgical trials and ameliorate disparities related to race/ethnicity, gender, and age are needed. © 2007 The Society of Surgical Oncology, Inc.
Keywords: adult; African American; age distribution; aged; article; Asian; breast cancer; cancer risk; cancer surgery; colorectal cancer; comparative study; data base; demography; ethnic difference; female; Hispanic; human; logistic regression analysis; lung cancer; major clinical study; male; outcome assessment; Pacific Islander; population research; prostate cancer; race difference; sex difference

A qualitative study of factors affecting chemotherapy use in older women with breast cancer: Barriers, promoters, and implications for intervention - Kreling, B.; Figueiredo, M.I.; Sheppard, V.L.; Mandelblatt, J.S. (Psycho-Oncology, 2006)
Study objective: The incidence of breast cancer increases with advancing age and yet women 65 and older (hereinafter referred to as 'older' women) do not always receive the most intensive treatments, such as adjuvant chemotherapy. The causes of underutilization of chemotherapy in this age group are poorly delineated. The purpose of the study was to explore older breast cancer patients' attitudes towards chemotherapy and factors that influenced their decisions to use or not use this treatment modality. Design: Qualitative methods were used to conduct race/ethnicity-specific focus groups. A thematic analysis was performed using NVIVO. Setting and Participants: Drawn from the Washington, DC area, participants were 34 ethnically diverse older breast cancer survivors (18 Caucasians, 10 African-Americans, and 6 Latinas). Focus groups were conducted in a local church; a senior center, and the Lombardi Cancer Center. Main Results: Results showed that many women felt they had no 'choice' and did what the doctor told them to do. For those who reported participation in the decision, time spent exchanging information with the woman's physician and the inclusion of family members promoted perceptions of optimum decision-making leading to the use of chemotherapy. Two barriers to using chemotherapy were negative expectations about side effects and lack of information specific to the woman's individuals' circumstances. Women of color reported less physician communication and information, in part due to language difficulties and perceived bias; these factors acted as barriers to chemotherapy. Conclusion: Physicians could provide specific and limited information to patients and family members to promote realistic expectations and optimum decisions about chemotherapy, given the risks involved in this treatment modality. Interventions should be developed and tested to enhance communication that is sensitive to older women's culture, family structure, illness experiences, preferences, and expectations. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: tamoxifen; adjuvant chemotherapy; African American; aged; article; breast cancer; cancer center; cancer chemotherapy; cancer incidence; cancer patient; cancer survivor; Caucasian; clinical article; controlled study; cultural anthropology; doctor patient relationship; ethnicity; expectation; female; Hispanic; human; language; medical decision making; medical information; patient attitude; patient decision making; patient participation; personal experience; qualitative research; race; religion; thematic analysis; United States

Family history, perceived risk, and prostate cancer screening among African American men - Bloom, J.R.; Stewart, S.L.; Oakley-Girvans, I.; Banks, P.J.; Chang, S. (Cancer Epidemiology Biomarkers and Prevention, 2006)
Background: Many African American men have two major risk factors for prostate cancer. By ethnicity alone, they have twice the risk of Euro-American men of developing prostate cancer. Having a family history (brother or father with prostate cancer) also doubles their risk. The major hypotheses tested in this study are that men with a family history perceive their risk to be higher, are more worried about getting prostate cancer, and are more likely to have used cancer screening tests than men without such a history. Methods: A sample of 208 African American men, ages 40 to 74 years, were recruited through relatives or friends whose prostate cancer diagnosis was reported to the California Cancer Registry during the years 1997 to 2001 and from churches and African American social groups. Following a screening interview to determine eligibility, 88 men with self-reported, first-degree family history of prostate cancer and 120 without such history were interviewed by telephone. Logistic regression was used to create models of perceived risk, prostate cancer worries, receipt of a digital rectal exam, and/or prostate-specific antigen (PSA) testing. Results: Men with a self-reported family history of prostate cancer did not perceive their risk as higher than men without a family history, nor did they report more cancer worries. They were more likely to report having a recent PSA test, but not a digital rectal exam. Having a higher than average perceived risk was associated with younger age, a college education, and lower mental well-being, and reporting more prostate cancer worries and being more likely to have had a recent PSA test. Conclusions: Although there continues to be controversy about PSA testing, these data suggest that African American men at above-average risk are inclined to be screened. Copyright © 2006 American Association for Cancer Research.
Keywords: prostate specific antigen; adult; African American; aged; article; cancer diagnosis; cancer registry; cancer risk; cancer screening; controlled study; demography; digital rectal examination; family history; human; interview; major clinical study; male; priority journal; prostate cancer; self report; socioeconomics; telephone; United States

Clinical trial resources on the internet must be designed to reach underrepresented minorities - Wilson, J.J.; Mick, R.; Wei, S.J.; Rustgi, A.K.; Markowitz, S.D.; Hampshire, M.; Metz, J.M. (Cancer Journal, 2006)
PURPOSE: Internet-based clinical trial information services are being developed to increase recruitment to studies. However, there are limited data that evaluate their ability to reach elderly and underrepresented minority populations. This study was designed to evaluate the ability of an established clinical trials registry to reach these populations based on expected Internet use. PATIENTS AND METHODS: This study compares general Internet users to participants who enrolled in an Internet based colorectal cancer clinical trials registry established by OncoLink (www.oncolink.org) and the National Colorectal Cancer Research Alliance. Observed rates of demographic groupings were compared to those established for general Internet users. RESULTS: Two thousand, four hundred and thirty-seven participants from the continental United States used the Internet to register for the database. New England, the Mid-Atlantic region, and the Southeast had the highest relative frequency of participation in the database, whereas the Upper Midwest, California, and the South had the lowest rates. Compared to general Internet users, there was an overrepresentation of women (73% vs. 50%) and participants over 55 years old (27% vs. 14%). However, there was an underrepresentation of minorities (10.3% vs. 22%), particularly African Americans (3.1% vs. 8%) and Hispanics (2.8% vs. 9%). DISCUSSION: The Internet is a growing medium for registry into clinical trials databases. However, even taking into account the selection bias of Internet accessibility, there are still widely disparate demographics between general Internet users and those registering for clinical trials, particularly the underrepresentation of minorities. Internet-based educational and recruitment services for clinical trials must be designed to reach these underrepresented minorities to avoid selection biases in future clinical trials. Copyright © 2006 Jones and Bartlett Publishers, Inc.
Keywords: adult; African American; article; cancer prevention; cancer registry; colorectal cancer; data base; demography; education; female; Hispanic; human; human experiment; Internet; male; medical information system; minority group; priority journal

Phase II study of carboplatin, irinotecan, and thalidomide in patients with advanced non-small cell lung cancer - Miller, A.A.; Case, D.; Atkins, J.N.; Giguere, J.K.; Bearden, J.D. (Journal of Thoracic Oncology, 2006)
BACKGROUND: We hypothesized that thalidomide would improve the response and toxicity profile of chemotherapy with carboplatin and irinotecan. METHODS: The key eligibility criteria were stage IIIB (malignant pleural effusion) and IV non-small cell lung cancer, measurable disease, no prior chemotherapy, prior radiation only for brain metastasis, performance status 0 or 1, and adequate hematologic, hepatic, and renal function. Treatment consisted of carboplatin at a calculated area under the curve of 5 and infused intravenously for 30 min on day 1 and irinotecan (50 mg/m intravenously for 90 min on days 1 and 8 every 21 days). Thalidomide was given orally every evening starting on day 1 until progressive disease; the starting dose was 200 mg per day, which was escalated by 100 mg per week if tolerated (maximum 1000 mg per day). The objectives were to determine the response rate, time to progression, overall survival, and toxicity profile. RESULTS: In all, 46 patients were enrolled, but three who never received protocol treatment were excluded from the analysis. The characteristics of the 43 eligible and treated patients included median age 63 (47-79), female/male 13/30, black/white 3/40, PS 0/1 in 10/33, and stage 3/4 in 6/37. The objective response rates were complete response 1 (2%), partial response 5 (12%), stable disease 24 (56%), progressive disease 9 (21%), and unevaluable for response 4 (9%). The median time to progression was 3.7 months (95% confidence interval [CI], 2.5-4.9). The median survival time was 8.1 months (95% CI, 5.0-12.9). Frequent toxicities were neutropenia, fatigue/malaise, and nausea/vomiting. Diarrhea was uncommon and mild. CONCLUSIONS: This treatment regimen of carboplatin, irinotecan, and thalidomide was tolerable, with reversible neutropenia as the major toxicity and only minor diarrhea. The overall response rate did not meet our predetermined level of efficacy to merit further investigation. © 2006International Association for the Study of Lung Cancer.
Keywords: atropine; carboplatin; dexamethasone; granisetron; irinotecan; ondansetron; palonosetron; thalidomide; adult; advanced cancer; aged; area under the curve; article; brain metastasis; cancer patient; cancer radiotherapy; cancer staging; clinical article; clinical protocol; clinical trial; confidence interval; controlled clinical trial; controlled study; diarrhea; disease course; disease duration; drug cytotoxicity; drug dose escalation; drug efficacy; drug tolerability; fatigue; febrile neutropenia; female; hemoptysis; human; hypertension; kidney function; liver function; non small cell lung cancer; malaise; male; multiple cycle treatment; nausea; neutropenia; overall survival; phase 2 clinical trial; priority journal; survival rate; survival time; therapy effect; thrombocytopenia; treatment outcome; treatment response; vomiting

Racial differences in doctors' information-giving and patients' participation - Gordon, H.S.; Street Jr., R.L.; Sharf, B.F.; Souchek, J. (Cancer, 2006)
BACKGROUND. Whether doctor-patient communication differs by race was investigated in patients with pulmonary nodules or lung cancer. METHODS. Eligible patients (n = 137) had pulmonary nodules or lung cancer and were seen in thoracic surgery or oncology clinics for initial treatment recommendations at a large southern Veterans Affairs Medical Center from 2001-2004. Doctor-patient consultations were audiotaped. Audiotapes were transcribed, unitized into utterances, and utterances were coded as doctors' information-giving or patients' and companions' active participation (asking questions, expressing concerns, and making assertions). Data were compared by patient race and doctor-patient racial concordance using t-tests or chi-square tests as appropriate. Mixed linear regression was used to determine the independent predictors of doctor's information-giving after controlling for clustering of patients by doctor. RESULTS. Patient age, gender, marital status, clinical site, and health status were similar by race (P > .20), but black patients were somewhat less likely to have education beyond high school and to bring a companion to the visit (P = .06) than white patients. Black patients and their companions received significantly less information from doctors (49.3 vs. 87.3 mean utterances; P < .001) and produced significantly fewer active participation utterances (21.4 vs. 37.2; P < .001) than white patients. In mixed regression analyses, after adjusting for patients' and companions' participation, clustering by doctor, and other factors, race no longer predicted information-giving (P =.54). Patients in racially discordant interactions received significantly less information and were significantly less active participants (P < .001) when compared with patients in racially concordant interactions, and after controlling for patients' participation and other factors using mixed regression, racial discordance did not predict information-giving. CONCLUSIONS. The results indicate a pattern of communication that may perpetuate patient passivity and limited information exchange where black patients and patients in discordant interactions do less to prompt doctors for information and doctors in turn provide less information to these patients. © 2006 American Cancer Society.
Keywords: adult; African American; aged; article; chi square distribution; doctor patient relationship; female; gender; human; information dissemination; interpersonal communication; linear regression analysis; lung cancer; major clinical study; male; marriage; patient attitude; patient participation; priority journal; race difference; statistical significance; Student t test; United States

Ovarian volume: Determinants and associations with cancer among postmenopausal women - Sherman, M.E.; Lacey, J.V.; Buys, S.S.; Reding, D.J.; Berg, C.D.; Williams, C.; Hartge, P. (Cancer Epidemiology Biomarkers and Prevention, 2006)
Clinical studies have reported associations between ovarian stromal hyperplasia and the diagnosis of hormonally related tumors such as endometrial cancer. To assess the hypothesis that characteristics of benign ovaries among postmenopausal women are related to risk for breast, endometrial, and colon cancer, we analyzed systematically collected transvaginal ultrasound data for participants enrolled in the screening arm of the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial. Among women without cancer, median ovarian volume declined with age from 1.25 cm3 for women between ages 55 and 59 years to 1.0 cm3 for those between ages 65 and 69 years. African American and Caucasian women had larger median ovarian volumes than Asians. Larger ovarian volume was also associated with the highest quartiles of height and weight and ever having smoked. After adjusting for race, age, parity, body mass, smoking, and hormone use, women with median ovarian volumes ≥3.0 cm3 were at increased risk for breast cancer [odds ratio (OR), 1.42; 95% confidence interval (95% CI), 1.11-1.70], endometrial cancer (OR, 1.97; 95% CI, 1.12-3.48), and colon cancer (OR, 2.00; 95% CI, 1.25-3.21). Significant trends of risk with increasing volume were found only for breast and endometrial cancers. We conclude that large ovaries among postmenopausal women may represent a marker of risk for hormonally related tumors. Confirmation of these findings in future studies, including analyses of serum hormone levels and tissues, may provide insights into hormonal carcinogenesis among older women. Copyright © 2006 American Association for Cancer Research.
Keywords: adult; African American; aged; article; Asian; body height; body mass; body weight; breast cancer; cancer risk; cancer screening; Caucasian; colon cancer; confidence interval; demography; endometrium cancer; female; hormonal therapy; human; major clinical study; ovary cancer; postmenopause; priority journal; smoking; ultrasound

Enhancing adherence among older African American men enrolled in a longitudinal cancer screening trial - Ford, M.E.; Havstad, S.; Vernon, S.W.; Davis, S.D.; Kroll, D.; Lamerato, L.; Swanson, G.M. (Gerontologist, 2006)
Purpose: The purpose of this study was to enhance adherence among older (aged 55 years and older) African American men enrolled in a cancer screening trial for prostate, lung, and colorectal cancer. For this study, we defined adherence as completing the trial screenings. Design and Methods: We used a randomized trial design. Case managers contacted intervention group participants (n = 352) at least monthly by telephone and provided information and referral services. The control group included 351 participants. Results: Among participants with low income, those in the intervention group had higher screening adherence rates than did participants in the control group for (a) prostate-specific antigen test for prostate cancer (74.3% vs 53.0%, p = .001), (b) digital rectal exam for prostate cancer (66.2% vs 46.1%, p = .011), and (c) chest x-ray for lung cancer (70.9% vs 51.3%, p = .012). We found no statistically significant differences in adherence rates for flexible sigmoidoscopy screening for colorectal cancer. In contrast, among participants with moderate-to-high income, we found no statistically significant differences in adherence rates between intervention and control group participants for any of the screening tests. Implications: The case management intervention was effective in enhancing adherence among participants with the lowest income, who in many studies are the most difficult to retain. Copyright 2006 by The Gerontological Society of America.
Keywords: prostate specific antigen; adult; African American; aged; article; cancer screening; case management; clinical trial; colorectal cancer; controlled clinical trial; controlled study; digital rectal examination; elderly care; human; longitudinal study; lowest income group; lung cancer; major clinical study; male; men's health; patient compliance; patient referral; prostate cancer; randomized controlled trial; sigmoidoscopy; teleconsultation; thorax radiography

Breast cancer patients' attitudes toward clinical trials in the radiation oncology clinic versus those searching for trial information on the internet - Dolinsky, C.M.; Wei, S.J.; Hampshire, M.K.; Metz, J.M. (Breast Journal, 2006)
Web-based clinical trials matching systems including breast cancer patients are expanding rapidly. However, limited data exist regarding the demographics and attitudes of breast cancer patients using the Internet to search for clinical trials information. Biases in patient populations could be introduced by recruiting patients to trials through the Internet. This study was designed to compare breast cancer patients in the radiation oncology clinic to those using the Internet to search for clinical trials information. A piloted questionnaire assessing demographics and attitudes regarding clinical trials was offered through the radiation oncology clinic at the University of Pennsylvania and on the OncoLink website (www.oncolink.org). The questionnaire consisted of 18 questions and was answered by a total of 157 patients with breast cancer. Breast cancer patients using the Web were more likely to be interested in clinical trials testing new drugs or therapies (71 [53%] versus 4 [17%], p = 0.002). More clinic patients indicated they would need a greater than 50% chance of benefiting from a trial (12 [52%] versus 33 [25%], p = 0.01) and a less than 10% potential for serious toxicity from a trial (15 [65%] versus 51 [38%], p = 0.02) for consideration of enrollment. African Americans were more likely than other races to have never used the Internet to search for cancer-related information (4 [40%] versus 18 [12%], p = 0.01), more likely to indicate that they need a greater than 50% chance of benefit to enroll in clinical trials (8 [80%] versus 37 [25%], p = 0.001), and less likely to be interested in clinical trials testing new drugs or therapies (1 [10%] versus 73 [50%], p = 0.01). Breast cancer patients have different attitudes regarding clinical trials based on race, Internet usage, and previous trial enrollment. Biases may be introduced with recruitment for clinical trials through the Internet. Radiation oncologists must consider these issues when offering clinical trials information through the Internet. © 2006 Blackwell Publishing, Inc.
Keywords: adult; African American; article; Asian; breast cancer; cancer patient; cancer research; Caucasian; clinical research; female; Hispanic; human; information retrieval; Internet; major clinical study; patient attitude; questionnaire; race difference; United States

Breast biopsy and race/ethnicity among women without breast cancer - Jacobson, J.S.; Grann, V.R.; Hershman, D.; Troxel, A.B.; Li, H.; Neugut, A.I. (Cancer Detection and Prevention, 2006)
Background: Breast biopsy is essential for definitive breast cancer diagnosis, but may also play a role in determining eligibility for breast cancer preventive measures or clinical trials. In addition, the prevalence of a history of negative breast biopsy can be viewed as an indicator of the adequacy or intensity of health care in a given population. We therefore analyzed the association of a history of breast biopsy with race/ethnicity and other factors in a cohort of women without a cancer diagnosis who completed a risk assessment form for participation in the Study of Tamoxifen and Raloxifene (STAR) and a sociodemographic questionnaire. Methods: Subjects were recruited at our large, urban teaching hospital. We developed a logistic regression model with biopsy (ever/never) as the outcome and age, race/ethnicity, educational attainment, and insurance coverage as the independent variables. Results: Among 805 unaffected predominantly minority subjects, white women were more than three times as likely as black and Hispanic women (OR = 3.3, 95% CI 1.9-5.9), and insured women were twice as likely as uninsured women (OR = 2.0, 95% CI 1.4-2.9) to have had a biopsy. Biopsy results were also associated with race/ethnicity. Discussion: We view these observations as hypothesis-generating rather than definitive. If confirmed, the associations we observed between negative biopsies and insurance status may reflect disparities in the timeliness and effectiveness of follow-up of suspicious lesions found via mammography. Our findings may also be relevant to the well-known association of breast cancer stage at diagnosis with low income and minority race/ethnicity. © 2006 International Society for Preventive Oncology.
Keywords: raloxifene; tamoxifen; adult; article; breast biopsy; breast cancer; cancer diagnosis; cancer prevention; cancer risk; controlled study; demography; education; ethnic difference; ethnology; female; health insurance; human; human tissue; mammography; priority journal; questionnaire; risk assessment

Health parties for African American study recruitment - Sadler, G.R.; York, C.; Madlensky, L.; Gibson, K.; Wasserman, L.; Rosenthal, E.; Barbier, L.; Newman, V.A.; Tso, C. (Journal of Cancer Education, 2006)
Innovative strategies are needed to increase minorities' research participation. Using existing social networks within the African American community, "home health parties" were tested as a way to recruit African American women to a breast cancer control study. Parties included social, educational, and recruitment components. All women attending health parties consented, completed a survey, and received the study's preliminary breast cancer risk assessment. There were no differences in rates of participation for subsequent study components between women recruited via parties versus other methods. Health parties are viable recruitment strategies, reduce barriers to participation, provide a supportive environment, and are relatively inexpensive.
Keywords: adult; African American; article; breast cancer; breast examination; cancer control; cancer risk; female; genetic counseling; human; leisure; medical research; minority group; normal human; nutrition; patient participation; priority journal; risk assessment; social aspect; social network; social support

New research suggests access, genetic differences play role in high minority cancer death rate. - Whitworth, A. (Journal of the National Cancer Institute, 2006)
Keywords: African American; article; breast tumor; clinical trial; colorectal tumor; female; genetics; health care delivery; human; male; minority group; mortality; neoplasm; pathology; patient selection; poverty; statistics; trust; United States

Psychosocial factors related to repeat mammography screening over 5 years in African American women - Russell, K.M.; Champion, V.L.; Skinner, C.S. (Cancer Nursing, 2006)
The purpose of this study was to investigate health beliefs associated with repeat mammography screening in African American women 51 years or older over a 5-year period. Long-term repeat mammography screening is inconsistent in African American women; therefore, this study measured demographic, knowledge, and health belief predictors of repeat screening. The theoretical framework for this study was the health belief model. Baseline data from a larger randomized controlled trial were analyzed using descriptive statistics and logistic regression. The sample consisted of 602 African American women with no breast cancer history and at least 1 reported screening mammogram in the past 5 years. They were recruited from 3 primary care health settings. Having been screened 4 to 5 times in the past 5 years was associated with more knowledge about screening guidelines and fewer perceived barriers to screening. Results point to the importance of collaborating with African American communities to promote life-long mammography screening by increasing access to culturally appropriate information on screening guidelines and ameliorating barriers to screening within the context of the African American experience. © 2006 Lippincott Williams & Wilkins, Inc.
Keywords: adult; African American; aged; article; breast cancer; cancer screening; cultural factor; female; health belief; health care access; human; logistic regression analysis; major clinical study; mammography; primary health care; priority journal; rescreening

Acceptance of genetic testing for hereditary breast ovarian cancer among study enrollees from an African American kindred - Kinney, A.Y.; Simonsen, S.E.; Baty, B.J.; Mandal, D.; Neuhausen, S.L.; Seggar, K.; Holubkov, R.; Smith, K. (American Journal of Medical Genetics, 2006)
Clinical availability of genetic testing for cancer predisposition genes is generating a major challenge for U.S. health care systems to provide relevant genetic services to underserved populations. Here we present rates of study enrollment and utilization of genetic testing in a research study on BRCA1 testing acceptance in one large kindred. We also present data on baseline access to genetic information as well as enabling and obstructing factors to study enrollment. The study population included female and male members of an African American kindred based in the rural southern United States with an identified BRCA1 mutation. A combination of quantitative and qualitative data were collected and analyzed. Of the 161 living, eligible, and locatable kindred members. 105 (65%) enrolled in the study. Family, personal, and educational motivations were the most commonly endorsed reasons for study participation. The most commonly cited reasons for refusal to participate in the study were: lack or interest, time constraints, and negative experiences with prior participation in genetic research. Eighty three percent of the participants underwent BRCA1 testing. In multiple logistic regression analysis, age 40-49 (odds ratio (OR) = 6.9; 95% confidence interval (CI) = 1.2-39.5), increased perceived risk of being a BRCA1 mutation carrier (OR = 4.1; 95% CI = 1.1-14.6), and high cancer genetics knowledge levels (OR = 1.5; 95% CI = 1.1-2.3) were associated with BRCA1 testing acceptance. The results of this study indicate that cognitive and demographic factors may influence genetic research participation and genetic testing decisions among African Americans who are at increased risk of carrying a deleterious BRCA1 mutation. © 2006 Wiley-Liss, Inc.
Keywords: BRCA1 protein; adult; African American; aged; article; breast cancer; cancer susceptibility; cognition; demography; hereditary tumor syndrome; female; gene deletion; gene identification; gene mutation; genetic screening; health care system; human; major clinical study; male; motivation; oncogene; ovary cancer; patient decision making; priority journal; qualitative analysis; quantitative analysis; refusal to participate; rural area; United States

Physician-patient discussions about prostate-specific antigen test use among African-American men - Tannor, B.B.; Ross, L. (Journal of the National Medical Association, 2006)
Background: The purpose of this study was to examine the associations between physician-patient discussions, demographic and health-related variables, and PSA test use. Of the previous studies that examined physician-patient discussions about PSA test use, none focused on African-American men. Methods: Using a sample of African-American men (N=739) aged ≥40 years who had participated in the National Health Interview Survey (NHIS) 2000, we assessed demographic, health status and other variables related to two PSA test use outcomes: 1) had a PSA test within the past year, and 2) had ≥3 PSA tests within the past five years. Results: More than three-fourths (76.6%) of our sample reported that their doctors had discussed with them the advantages and disadvantages of the PSA test before administering it. The bivariate analysis showed a number of variables positively associated with PSA test use including men aged ≥50, having health insurance coverage and having participated in physician-patient discussions about the test. Discussion: Despite the high percentage of men who had discussions with their doctor, there was a large number of men who had neither heard of nor undergone a PSA test. More efforts should be made by the healthcare community to promote prostate cancer screening education and physician-patient discussions.
Keywords: prostate specific antigen; adult; aged; antigen detection; article; cancer screening; community care; demography; disease association; doctor patient relationship; education program; funding; health insurance; human; interview; major clinical study; male; multivariate analysis; patient participation; priority journal; prostate cancer

Randomized trial of peer counseling on reproductive health in African American breast cancer survivors - Schover, L.R.; Jenkins, R.; Sui, D.; Adams, J.H.; Marion, M.S.; Jackson, K.E. (Journal of Clinical Oncology, 2006)
Purpose: We designed a peer counseling program to improve sexual function, increase knowledge about reproductive health, and decrease menopausal symptoms and infertility-related distress for African American breast cancer survivors. Patients and Methods: Women were randomly assigned to immediate counseling or a 3-month waitlist. Three peer counselors conducted a 3-session intervention using a detailed workbook. Questionnaires at baseline, after the waitlist period, at posttreatment, and at 3-month follow-up assessed spirituality, sexual function, menopause symptoms, emotional distress, relationship satisfaction, fertility concerns, and knowledge about reproductive health and breast cancer. At the postcounseling assessment, women rated the workbook, their counselor, and the program. Results: Of 93 women screened, 60 women (65%) enrolled in the study. Women who completed counseling (80%; N = 48) had a mean age of 49 years (standard deviation [SD], 8 years) and a mean follow-up of 4.5 years (SD, 3.8 years) since cancer diagnosis. Almost all rated the workbook as very easy to understand (94%) and their counselor as very knowledgeable (96%) and very skillful (98%). Eighty-one percent rated the program as "very useful to me." Immediate counseling and waitlist groups did not differ at baseline in psychologic adjustment, nor did scores change during the waitlist period. Therefore, the groups were combined in analyzing outcomes. Knowledge of reproductive issues improved significantly from baseline to 3-month follow-up (P < .0001), as did emotional distress (P = .0047) and menopause symptoms (P = .0128). Sexually dysfunctional women became less distressed (P = .0167). Conclusion: Women valued the Sisters Peer Intervention in Reproductive Issues After Treatment program highly and found it relevant. The program had positive effects on knowledge and target symptoms. © 2006 by American Society of Clinical Oncology.
Keywords: tamoxifen; adult; African American; article; breast cancer; cancer survivor; clinical trial; controlled clinical trial; controlled study; emotional stress; female; female infertility; follow up; human; major clinical study; menopausal syndrome; peer counseling; priority journal; questionnaire; randomized controlled trial; reproductive health; sexual function

Cancer prevention trials and primary care physicians: Factors associated with recommending trial enrollment - Battaglia, T.A.; Ash, A.; Prout, M.N.; Freund, K.M. (Cancer Detection and Prevention, 2006)
Background: To explore the willingness of primary care providers (PCPs) to encourage enrollment of patients into cancer prevention trials. Methods: A self-administered survey was mailed to a random sample of PCPs in three geographic regions. Physicians were asked questions about their knowledge and attitudes towards cancer prevention trials. We presented a clinical vignette of a woman at high risk for breast cancer and asked if they would encourage her enrollment into a breast cancer chemoprevention trial (yes/no). Each survey included one of 16 possible clinical vignettes where patient characteristics (age, race socioeconomic status, physical mobility and co-morbidity) varied dichotomously. Bivariate analyses and logistic models were used to examine the independent effects of patient and physician characteristics on physician decisions. Results: Two hundred and sixty-six surveys (50% response) were analyzed. The mean age of respondents was 48; 54% were White, 35% Asian and 5% Black. By design physicians were evenly distributed by gender, specialty and geographic location. Overall, 53% would encourage enrollment into a breast cancer chemoprevention trial. Significant predictors of a recommendation to enroll were: geographic location in California or Georgia, younger vignette patient and anticipating an increase in patient trust after recommending enrollment. Conclusion: PCPs are less likely to encourage elderly patients to enroll into cancer chemoprevention trials. Decisions differ based on geographic location and perceived trust in the patient-provider relationship. To achieve successful enrollment, trial investigators must continue to educate PCPs and ensure a strong PCP-patient relationship is maintained. © 2005 International Society for Preventive Oncology. Published by Elsevier Ltd. All rights reserved.
Keywords: article; Asian; breast cancer; cancer prevention; cancer risk; Caucasian; chemoprophylaxis; clinical study; comorbidity; geographic distribution; human; Black person; physical mobility; physician; primary medical care; priority journal; race difference; social status

Patient navigation: a community centered approach to reducing cancer mortality. - Freeman, H.P. (Journal of cancer education : the official journal of the American Association for Cancer Education, 2006)
BACKGROUND: Profound advances in biomedical science have contributed to increased longevity and improved quality of life for many Americans. Despite this progress, a heavier burden of disease is borne by some population groups in the United States, particularly the poor and underserved. Landmark reports published since 1973 have highlighted these health disparities, explored their causal factors, and outlined strategies to reduce them. More recent research studies underscore the results of these early reports that identify social position, economic status, culture, and environment as critical determinants of who develops and survives cancer and of the quality of life of cancer survivors. METHODS: The Patient Navigation Program was established in Harlem, New York, in 1990 to address the dramatic disparities in breast cancer mortality among minority women in the community. RESULTS AND CONCLUSIONS: The success of the Harlem Patient Navigation Program has provided the impetus for the development of many similar patient navigation programs across the country and for federal support for Patient Navigation research to address the critical need for effective interventions to eliminate cancer health disparities, particularly among minorities and the underserved.
Keywords: African American; article; breast tumor; cancer staging; community hospital; ethnology; female; follow up; health care delivery; health care quality; health center; Hispanic; human; mass screening; minority group; mortality; patient; patient selection; poverty; primary prevention; public relations; statistics; survival rate; United States

Are racial and ethnic minorities less willing to participate in health research? - Wendler, D.; Kington, R.; Madans, J.; Van Wye, G.; Christ-Schmidt, H.; Pratt, L.A.; Brawley, O.W.; Gross, C.P.; Emanuel, E. (PLoS Medicine, 2006)
Background: It is widely claimed that racial and ethnic minorities, especially in the US, are less willing than non-minority individuals to participate in health research. Yet, there is a paucity of empirical data to substantiate this claim. Methods and Findings: We performed a comprehensive literature search to identify all published health research studies that report consent rates by race or ethnicity. We found 20 health research studies that reported consent rates by race or ethnicity. These 20 studies reported the enrollment decisions of over 70,000 individuals for a broad range of research, from interviews to drug treatment to surgical trials. Eighteen of the twenty studies were single-site studies conducted exclusively in the US or multi-site studies where the majority of sites (i.e., at least 2/3) were in the US. Of the remaining two studies, the Concorde study was conducted at 74 sites in the United Kingdom, Ireland, and France, while the Delta study was conducted at 152 sites in Europe and 23 sites in Australia and New Zealand. For the three interview or non-intervention studies, African-Americans had a nonsignificantly lower overall consent rate than non-Hispanic whites (82.2% versus 83.5%; odds ratio [OR] = 0.92; 95% confidence interval [CI] 0.84-1.02). For these same three studies, Hispanics had a nonsignificantly higher overall consent rate than non-Hispanic whites (86.1% versus 83.5%; OR = 1.37; 95% CI 0.94-1.98). For the ten clinical intervention studies, African-Americans' overall consent rate was nonsignificantly higher than that of non-Hispanic whites (45.3% versus 41.8%; OR = 1.06; 95% CI 0.78-1.45). For these same ten studies, Hispanics had a statistically significant higher overall consent rate than non-Hispanic whites (55.9% versus 41.8%; OR = 1.33; 95% CI 1.08-1.65). For the seven surgery trials, which report all minority groups together, minorities as a group had a nonsignificantly higher overall consent rate than non-Hispanic whites (65.8% versus 47.8%; OR = 1.26; 95% CI 0.89-1.77). Given the preponderance of US sites, the vast majority of these individuals from minority groups were African-Americans or Hispanics from the US. Conclusions: We found very small differences in the willingness of minorities, most of whom were African-Americans and Hispanics in the US, to participate in health research compared to non-Hispanic whites. These findings, based on the research enrollment decisions of over 70,000 individuals, the vast majority from the US, suggest that racial and ethnic minorities in the US are as willing as non-Hispanic whites to participate in health research. Hence, efforts to increase minority participation in health research should focus on ensuring access to health research for all groups, rather than changing minority attitudes. Copyright: © 2006 Wendler et al.
Keywords: anti human immunodeficiency virus agent; antiarrhythmic agent; antineoplastic agent; estrogen; neuroleptic agent; adenoidectomy; African American; alcoholism; article; Australia; breast cancer; cancer radiotherapy; cardiovascular disease; Caucasian; clinical trial; coronary artery bypass graft; coronary artery disease; ethnology; France; heart arrhythmia; heart infarction; Hispanic; human; Human immunodeficiency virus infection; informed consent; interview; Ireland; medical research; melanoma; meta analysis; minority group; New Zealand; otitis media; patient participation; percutaneous transluminal angioplasty; pharyngitis; race difference; schizophrenia; statistical significance; substance abuse; systematic review; tonsillectomy; United Kingdom; United States

Predictors of enrollment in lung cancer clinical trials - Du, W.; Gadgeel, S.M.; Simon, M.S. (Cancer, 2006)
BACKGROUND. Clinical trials may offer patients innovative therapeutic options with potentially better outcomes, which are particularly relevant for patients afflicted with lung carcinoma, because current therapies provide only modest survival benefits. Only approximately 5% of patients with newly diagnosed cancer participate in clinical trials nationwide, and African-American (AA) patients are particularly under-represented. METHODS. To determine predictors of clinical trials enrollment, the authors reviewed the medical records of 427 patients with lung carcinoma (175 AA patients and 252 non-AA patients) who were eligible for clinical trials between 1994 and 1998 at the Karmanos Cancer Institute in Detroit, Michigan. Logistic regression analysis was used to assess the association of patient demographic characteristics and clinical trial enrollment. RESULTS. Ninety-one patients (21%) were enrolled onto a lung cancer clinical trial during the period of the current study. Enrollment was associated significantly with race (P < 0.001), gender (P = 0.048), age (P = 0.005), and insurance type (P = 0.024). After multivariable adjustment, only race and gender remained significant predictors of enrollment. AA patients were less likely to enroll than non-AA patients (odds ratio [OR], 0.485; 95% confidence interval [95% CI], 0.243-0.966), and men were more likely than women to enroll (OR, 1.812; 95% CI, 1.033-3.178). CONCLUSIONS. The current results suggest disparities by race and gender in the enrollment of patients onto lung cancer clinical trials and support the need to improve educational and outreach endeavors that would make clinical trials available to a wider range of eligible patients. © 2005 American Cancer Society.
Keywords: adult; African American; age; aged; article; cancer patient; cancer survival; clinical trial; controlled clinical trial; controlled study; demography; female; gender; health insurance; human; lung cancer; lung carcinoma; major clinical study; male; priority journal; race; treatment outcome

Use of the National Cancer Data Base to develop clinical trials accrual targets that are appropriate for minority ethnicity patients: A report from the American College of Surgeons Oncology Group (ACOSOG) special populations committee - Newman, L.A.; Lee, C.T.; Parekh, L.P.; Stewart, A.K.; Thomas Jr., C.R.; Beltran, R.A.; Lucci, A.; Green, B.; Ota, D.; Nelson, H. (Cancer, 2006)
BACKGROUND. Disparities in cancer outcome among different subsets of the American population related to ethnic background have been well documented. Clinical trials represent the most powerful strategy for improving cancer treatments, but racial and ethnic minority patients are frequently underrepresented among patients accrued to these protocols. Proof of comparable efficacy for a promising cancer therapy in different groups of patients requires diversity in the clinical trial populations so that study results will be generalizable. Appropriate targets for accrual of minority ethnicity patients have not previously been defined. METHODS. The National Cancer Database (NCDB) is maintained jointly by the American Cancer Society and the American College of Surgeons. Information submitted by tumor registries throughout the United States represents an estimated 70% of newly diagnosed cancer cases. The authors analyzed NCDB reports on ethnic distribution of patients with breast, prostate, nonsmall cell lung, and colorectal cancer, stratified by stage of disease at diagnosis. RESULTS. African Americans with cancer of the breast and prostate had the most notable patterns of disproportionate representation among populations with advanced-stage disease. The authors compiled a table of suggested accrual targets for selected solid-organ cancers based on NCDB stage-specific reports. CONCLUSIONS. Clinical trial results will be more meaningful if participating patients reflect the site- and stage-specific populations that are under study. The authors recommended that clinical trial investigators incorporate accrual targets for minority ethnicity populations into the study design. © 2005 American Cancer Society.
Keywords: African American; article; breast cancer; cancer registry; cancer research; clinical research; colorectal cancer; ethnology; health care planning; health care policy; health care quality; human; non small cell lung cancer; minority group; priority journal; prostate cancer; United States

Intentions to participate in genetics research among African American smokers - Halbert, C.H.; Gandy Jr., O.H.; Collier, A.; Shaker, L. (Cancer Epidemiology Biomarkers and Prevention, 2006)
Although prior studies have shown that African American smokers are likely to carry some of the genetic variants associated with smoking risk, additional research with African American smokers is needed to replicate these findings. Limited information is available on interest in participating in research to identify genetic risk factors for smoking among African American smokers; therefore, the goals of the present study were to describe intentions to participate in smoking and genetics research, and to determine factors that are associated with participation intentions. Subjects were 128 African American male and female adult smokers. Sociodemographic characteristics, clinical factors, attitudes about genetic testing, and intentions to participate in genetics research were evaluated during a structured telephone interview. Overall, 58% of respondents reported that they would be very likely to participate in research to identify genetic risk factors for smoking. Greater beliefs about the benefits of participating in medical research (odds ratio, 3.17; 95% confidence interval, 1.45-6.94; P = 0.004) and fewer perceptions of the limitations and risks of genetic testing (odds ratio, 0.90; 95% confidence interval, 0.82-0.98; P = 0.01) had significant independent associations with reporting a high likelihood of participating in this type of research. Recruitment messages and protocols that address the benefits of research participation, as well as concerns about the limitations and risks of genetic testing, may enhance African American participation in research on genetics and smoking. Copyright © 2006 American Association for Cancer Research.
Keywords: adult; African American; article; cancer risk; carcinogenesis; clinical protocol; correlation analysis; demography; family history; female; genetic predisposition; genetic screening; genetic variability; high risk behavior; human; interview; lung cancer; lung carcinogenesis; major clinical study; male; medical research; priority journal; race difference; risk factor; smoking habit; telephone

Impact of the year 2000 medicare policy change on older patient enrollment to cancer clinical trials - Unger, J.M.; Coltman Jr., C.A.; Crowley, J.J.; Hutchins, L.F.; Martino, S.; Livingston, R.B.; Macdonald, J.S.; Blanke, C.D.; Gandara, D.R.; Crawford, E.D.; Albain, K.S. (Journal of Clinical Oncology, 2006)
Purpose: A prior analysis by the Southwest Oncology Group (SWOG) showed that women and African American patients were adequately represented on cancer clinical treatment trials but that older patients were substantially underrepresented. Twenty-five percent of patients ≥ 65 years old were enrolled onto SWOG trials from 1993 to 1996, whereas 63% of all patients with cancer were ≥ 65 years old. Recognition of this under-representation led to a change in Medicare policy in 2000 to include coverage of routine patient care costs of clinical trials. We conducted an updated analysis of accrual trends. Methods: The proportions of enrollment onto SWOG treatment trials by sex, race/ethnicity, and age (≥ 65 years) were computed for the years 1997 to 2000; corresponding rates in the United States were derived from US Census and National Cancer Institute Surveillance, Epidemiology, and End Results data. Additionally, method of payment data were analyzed over time (1993 to 2003) to assess whether patterns in method of payment changed with the new Year 2000 Medicare policy on clinical trials coverage. Results: The results showed continued adequate representation by sex and race/ethnicity. Older patient accrual on SWOG trials increased significantly since 2000, with 31 % of patients ≥ 65 years old enrolled from 1997 to 2000 and 38% enrolled from 2001 to 2003 (v 25% from 1993 to 1996). The percentage of patients using Medicare plus supplemental insurance also increased beginning in 2000, whereas the percentage of patients using Medicare alone remained the same. Conclusion: Method of payment analyses provided evidence that the Year 2000 Medicare policy change had a positive impact, but only for those patients with supplemental private coverage of coinsurance costs. Improvements in the Medicare payment structure could further increase older patient participation in clinical trials. © 2006 by American Society of Clinical Oncology.
Keywords: adolescent; adult; aged; article; breast cancer; cancer patient; child; colorectal cancer; demography; ethnicity; female; health care cost; health care policy; health service; hospital admission; human; lung cancer; major clinical study; male; medicare; patient care; patient participation; priority journal; prospective payment; prostate cancer; race difference; sex ratio; United States

Nerve stimulator-guided thoracic paravertebral ropivacaine versus general anaesthesia: Effect on stress response to breast cancer surgery - Omran, A.F.; El-Sisi, A.H. (Egyptian Journal of Anaesthesia, 2005)
Background: Breast cancer surgery is usually performed under general anaesthesia (GA) and is frequently associated with postoperative nausea, vomiting and painful restricted movement of the shoulder. GA, with the exception of large doses of opioids, does not eliminate the surgical stress response. Paravertebral nerve blockade (PVB) may be an alternative to GA for this type of surgery especially in those patients with coexisting morbid diseases. However, PVB is associated with an incidence of failed black in 5-10% of cases. The aim of this study was to detect the success rate and the safety of PVB when guided by nerve stimulator and to compare the efficacy of this technique vs. GA for inhibition of surgical stress response during breast cancer surgery. Methods: Forty women were enrolled in this prospective randomized study, to receive GA (GA group; n = 20) or PVB (PVB group; n = 20) at T1-T6, using ropivacaine 0.5 % with epinephrine 1:200,000. In the PVB group, success rate and incidence of complications were recorded. In both groups, blood samples for measurement of glucose and cortisol concentrations were obtained before skin incision; 1 hour after skin incision; and at 3 and 24 hours postoperatively. Postoperative visual analogue pain scores (VAS) at rest and on moving the ipsilateral arm at predetermined time intervals postoperatively (1, 2, 6, 12 and 24 h) as well as the incidence of postoperative nausea and vomiting (PONV) throughout the 24 hours postoperatively were recorded in both groups. Results: All PVBs were successful and inadvertent complications other than hypotension (10% incidence) were not reported. There were no significant differences in the plasma glucose or cortisol concentrations between the two groups before skin incision. They were significantly lower in the PVB group 1 h after skin incision and at 3 h postoperatively. However, there were no significant differences in glucose or cortisol concentrations, between the 2 groups, at 24 h postoperatively. Patients in the PVB group had significantly lower VAS scores both at rest and on moving the arm at all the predetermined time intervals postoperatively as well as significantly lower incidence of PONV throughout the 24 h postoperatively. Conclusion: Nerve stimulator-guided PVB at the level of T1-T6 with ropivacaine represents a suitable alternative to GA for breast cancer surgery. Important benefits of PVB include reduced surgical stress response, as evidenced by lower plasma cortisol and glucose concentrations, superior postoperative analgesia and lower incidence of PONV.
Keywords: epinephrine; atracurium besilate; fentanyl; lidocaine; propofol; ropivacaine; adult; arm movement; article; blood sampling; breast cancer; clinical article; clinical trial; controlled study; drug safety; female; general anesthesia; glucose blood level; human; hydrocortisone blood level; hypotension; nausea and vomiting; nerve block; nerve stimulation; postoperative pain; postoperative period; skin incision; physiological stress; visual analog scale

Recruiting African American women to participate in hereditary breast cancer research - Halbert, C.H.; Brewster, K.; Collier, A.; Smith, C.; Kessler, L.; Weathers, B.; Stopfer, J.E.; Domchek, S.; Wileyto, E.P. (Journal of Clinical Oncology, 2005)
Purpose: This study evaluated the process of recruiting African American women to participate in genetic counseling research for BRCA1 and BRCA2 (BHCA1/2) mutations with respect to referral, study enrollment, and participation in genetic counseling. Patients and Methods: African American women (n = 783) were referred for study enrollment. Results: Of 783 referrals, 164 (21%) women were eligible for enrollment. Eligible women were most likely to be referred from oncology clinics (44%) and were least likely to be referred from general medical practices (11%; χ2 = 96.80; P = .0001). Overall, 62% of eligible women enrolled onto the study and 50% of enrollees completed genetic counseling. Women with a stronger family history of cancer (odds ratio [OR] = 3.18; 95% CI, 1.36 to 7.44; P = .01) and those referred from oncology clinics and community oncology resources (OR = 2.97; 95% CI, 1.34 to 6.58; P = .01) were most likely to enroll onto the study. Referral from oncology clinics was associated significantly with participation in genetic counseling (OR = 5.46; 95% CI, 1.44 to 20.60; P = .01). Conclusion: Despite receiving a large number of referrals, only a small subset of women were eligible for enrollment. Oncology settings were the most effective at identifying eligible African American women and general medical practices were the least effective. Factors associated with enrollment included having a stronger family history of cancer and being referred from oncology clinics and community oncology resources. Referral from oncology clinics was the only factor associated significantly with participation in genetic counseling. Education about hereditary breast cancer may be needed among primary care providers to enhance appropriate referral of African American women to genetic counseling for BRCA1/2 mutations. © 2005 by American Society of Clinical Oncology.
Keywords: BRCA1 protein; BRCA2 protein; adult; African American; article; breast cancer; cancer center; cancer research; community care; controlled study; hereditary tumor syndrome; female; gene mutation; genetic counseling; human; major clinical study; medical practice; patient referral; priority journal

Minority recruitment to the Selenium and Vitamin E Cancer Prevention Trial (SELECT) - Cook, E.D.; Moody-Thomas, S.; Anderson, K.B.; Campbell, R.; Hamilton, S.J.; Harrington, J.M.; Lippman, S.M.; Minasian, L.M.; Paskett, E.D.; Craine, S.; Arnold, K.B.; Probstfield, J.L. (Clinical Trials, 2005)
Background: Previous large chemoprevention studies have not recruited significant numbers of minorities. The Selenium and Vitamin E Cancer Prevention Trial (SELECT) is a large phase III study evaluating the impact of selenium and vitamin E on the clinical incidence of prostate cancer. Over 400 SELECT study sites in the USA, Canada, and Puerto Rico recruited men to this trial. The SELECT recruitment goal was 24% minorities, with 20% black, 3% Hispanic, and 1% Asian participants. The goal for black participants was set at 20% because of their proportion in the United States population and their prevalence of prostate cancer. Methods: The minority recruitment strategies in SELECT were to: 1) consider minority recruitment during site selection; 2) expand the eligibility criteria by lowering the age criterion for black men and including men with controlled co-morbid illnesses; 3) develop a national infrastructure; 4) give additional funds to sites with the potential to increase black enrollment; and 5) provide resources to maximize free media opportunities to promote SELECT. Results: SELECT recruitment began in August 2001 and was intended to last five years, but concluded two years ahead of schedule in June 2004. Of the 35 534 participants enrolled, 21% were minorities, with 15% black, 5% Hispanic, and 1% Asian. Conclusions Careful planning, recruitment of large numbers of clinical centers and adequate resources accomplished by the combined efforts of the National Cancer Institute (NCI), Southwest Oncology Group (SWOG), SELECT Recruitment and Adherence Committee (RAC), SELECT Minority and Medically Underserved Subcommittee (MMUS), and the local SELECT sites resulted in attainment of the estimated sample size ahead of schedule and recruitment of the largest percentage of black participants ever randomized to a cancer prevention trial. © Society for Clinical Trials 2005.
Keywords: alpha tocopherol; selenium; article; Asian; Canada; chemoprophylaxis; clinical trial; evaluation study; Hispanic; human; medical literature; priority journal; prostate carcinoma; Puerto Rico; treatment planning; United States

Creating the basis for a breast health program for female survivors of Hodgkin disease using a participatory research approach. - Crom, D.B.; Hinds, P.S.; Gattuso, J.S.; Tyc, V.; Hudson, M.M. (Oncology nursing forum, 2005)
PURPOSE/OBJECTIVES: To learn from female survivors of Hodgkin disease about their perceptions of their current health status and future health risks, self-care practices to prevent or diminish health risks, and what kind of breast health program could benefit them, including the most effective methods and optimal times for learning about breast health. DESIGN: Participatory research using focus groups. SETTING: Urban pediatric cancer center. SAMPLE: 1 African American and 19 Caucasian female survivors of Hodgkin disease aged 16-26 years, diagnosed at least two years before the start of the study, and treated with mantle radiation therapy. Participants were recruited during visits to an outpatient clinic. METHODS: Six open-ended questions were asked during three separate focus group sessions. Transcribed data were evaluated by content analysis techniques and analyzed to identify common themes. MAIN RESEARCH VARIABLES: Current health status and perceived health risks, current health practices, and effective methods and timing for breast health teaching. FINDINGS: Survivors reported feeling damaged by their cancer and its treatment and perceived that they were at risk for breast cancer. Self-care and risky behaviors also were reported. Internal influences (e.g., fear) and external influences (e.g., family) motivated survivors to participate in health promotion activities. Effective methods identified for learning about breast health included having access to other survivors, being respected as an adult, and having one-on-one staff teaching and peer support. The preferred timing of teaching varied, but survivors generally supported a gradual provision of information. CONCLUSIONS: A positive listening environment is important for developing a breast health program for survivors. An essential first step is to create an opportunity for survivors to tell about their experiences with cancer, including its impact on their lives. Information regarding breast health must be provided in multiple formats during and after treatment if good practices are to be undertaken. IMPLICATIONS FOR NURSING: The provision of adequate information during and after therapy as well as peer counseling in a positive listening environment are important in helping survivors participate in health promotion activities.
Keywords: adolescent; adult; article; attitude to health; breast tumor; female; Hodgkin disease; human; information processing; methodology; patient education; patient participation; program development; radiation injury; radiotherapy; research; risk factor; second cancer; survivor; theoretical model

5,10-Methylenetetrahydrofolate reductase 677 and 1298 polymorphisms, folate intake, and microsatellite instability in colon cancer - Eaton, A.M.; Sandler, R.; Carethers, J.M.; Millikan, R.C.; Galanko, J.; Keku, T.O. (Cancer Epidemiology Biomarkers and Prevention, 2005)
The 5,10-methylenetetrahydrofolate reductase (MTHFR) gene plays a critical role in folate metabolism. Studies on the association between MTHFR polymorphisms and length changes in short tandem repeat DNA sequences [microsatellite instability (MSI)] are inconsistent. Using data from colon cancer cases (n = 503) enrolled as part of an existing population-based case-control study, we investigated the association between MTHFR 677 and MTHFR 1298 polymorphisms and MSI. We also examined whether the association was modified by folate intake. Participants were case subjects enrolled as part of the North Carolina Colon Cancer Study. Consenting cases provided information about lifestyle and diet during in-home interviews as well as blood specimens and permission to obtain tumor blocks. DNA from normal and tumor tissue sections was used to determine microsatellite status (MSI). Tumors were classified as MSI if two or more microsatellite markers (BAT25, BAT26, D5S346, D2S123, and D17S250) had changes in the number of DNA sequence repeats compared with matched nontumor tissue. Tumors with one positive marker (MSI-low) or no positive markers (microsatellite stable) were grouped together as non-MSI tumors (microsatellite stable). MTHFR 677 and MTHFR 1298 genotypes were determined by real-time PCR using the 5′ exonuclease (Taqman) assay. Logistic regression was used to calculate odds ratio (OR) and 95% confidence intervals (95% CI). MSI was more common in proximal tumors (OR, 3.8; 95% CI, 1.7-8.4) and in current smokers (OR, 4.0; 95% CI, 1.6-9.7). Compared with MTHFR 677 CC referent, MTHFR 677 CT/TT genotype was inversely associated with MSI among White cases (OR, 0.36; 95% CI, 0.16-0.81) but not significant among African Americans. Although not statistically significant, a similar inverse association was observed between MTHFR 677 CT/TT genotype and MSI among the entire case subjects (OR, 0.54; 95% CI, 0.26-1.10). Among those with adequate folate intake (>400 μg total folate), we found strong inverse associations between combined MTHFR genotypes and MSI (677 CC + 1298 AC/CC, OR, 0.09; 95% CI, 0.01-0.59; 677 CT/TT + 1298 AA, OR, 0.13; 95% CI, 0.02-0.85) compared with the combined wild-type genotypes (677 CC + 1298 AA). This protective effect was not evident among those with low folate (<400 μg total folate) intake. Our results suggest that MTHFR variant genotypes are associated with reduced risk of MSI tumors under conditions of adequate folate intake, although the data are imprecise due to small numbers. These results indicate that the relationship between MTHFR genotypes and MSI is influenced by folate status. Copyright © 2005 American Association for Cancer Research.
Keywords: 5,10 methylenetetrahydrofolate reductase (FADH2); folic acid; microsatellite DNA; phosphodiesterase I; adult; African American; aged; article; bioassay; blood analysis; cancer risk; case control study; Caucasian; clinical study; colon cancer; controlled study; diet; DNA sequence; female; folate metabolism; gene; genetic association; genetic polymorphism; genotype; human; human tissue; lifestyle; logistic regression analysis; major clinical study; male; microsatellite instability; microsatellite marker; MTHFR gene; population research; priority journal; real time polymerase chain reaction; short tandem repeat; smoking; vitamin intake; Taqman

The influence of gender, race, and menthol content on tobacco exposure measures - Mustonen, T.K.; Spencer, S.M.; Hoskinson Jr., R.A.; Sachs, D.P.L.; Garvey, A.J. (Nicotine and Tobacco Research, 2005)
Research has suggested that race, gender, and menthol cigarette use influence tobacco-smoke exposure measures and smoking-related disease risk. For example, a high proportion of Black smokers prefer menthol cigarettes and, despite smoking fewer cigarettes per day (CPD) than do Whites, tend to have higher cotinine levels. Additionally, Black males are more at risk for smoking-related lung cancer. High cotinine levels and smoking menthol cigarettes may lead to higher toxin intake, which contributes to increased disease risk. We explored the relationship between tobacco exposure variables (i.e., cotinine, CPD, carbon monoxide [CO], nicotine content, and nicotine dependence) with respect to race, gender, and menthol content in a sample of 307 smokers recruited from the greater Boston area to participate in a smoking cessation treatment trial. The pattern of correlations between tobacco exposure measures and cotinine showed a consistently positive correlation between cotinine and CO in all smokers and a correlation between cotinine and CPD in those who smoked nonmenthol cigarettes. Cotinine and CPD correlations varied by gender and race among menthol cigarette smokers. Consistently, we found a significant gender × race × menthol interaction on salivary cotinine level as well as cotinine/CPD ratio. These findings suggest that the relationship between number of cigarettes consumed and salivary cotinine is more complex than previously believed. It is not sufficient to look at race alone; researchers and clinicians need to look at race and gender concurrently, as well as type of cigarette consumed. © 2005 Society for Research on Nicotine and Tobacco.
Keywords: carbon monoxide; cotinine; menthol; nicotine; adult; article; blood pressure measurement; body mass; cancer risk; clinical trial; controlled clinical trial; controlled study; correlation analysis; dose response; environmental exposure; female; human; lung cancer; male; priority journal; race difference; randomized controlled trial; risk assessment; risk factor; saliva level; sex difference; smoking cessation; statistical significance; tobacco dependence; transdermal patch; United States

Barriers to minority participation in breast carcinoma prevention trials - Grann, V.R.; Jacobson, J.S.; Troxel, A.B.; Hershman, D.; Karp, J.; Myers, C.; Neugut, A.I. (Cancer, 2005)
BACKGROUND. Breast carcinoma prevention trials must recruit large cohorts of women who have an above-average risk of developing breast carcinoma. Recruitment for the Study of Tamoxifen and Raloxifene (STAR) trial required volunteers to complete a risk assessment questionnaire form (RAF). Women whose estimated risk of developing breast carcinoma in the next 5 years was ≥ 1.67% based on the Gail model were invited to participate in STAR. Less than 4% of participants in the previously conducted P1 (tamoxifen vs. placebo) trial were minority women. We, therefore, studied barriers to minority participation in STAR among black, white, and Hispanic women who completed an RAF. METHODS. The authors analyzed the association of Gail model risk factors, education, and insurance with race/ethnicity using chi-square tests and two-sided P values. They developed logistic regression models of trial eligibility, controlling for the Gail model risk factors, education, and insurance status. RESULTS. Among 823 women who completed an RAF, white women were 10 times as likely as Hispanic women and 45 times as likely as black women to be eligible for STAR. Age at first birth (P = 0.04), having an affected first-degree relative (P < 0.0001), having had a biopsy (P < 0.0001), education (P < 0.0001), and insurance status (P < 0.0001) varied by race/ethnicity. All variables except insurance status were associated with eligibility when race was excluded from the model. In a model that included race/ethnicity, the same factors remained statistically significant. CONCLUSIONS. These findings suggested that both the race/ethnicity adjustment and socioeconomic factors were barriers to eligibility for and contribute to low minority participation in breast cancer prevention trials. © 2005 American Cancer Society.
Keywords: raloxifene; tamoxifen; adult; article; breast carcinoma; cancer prevention; cancer risk; Caucasian; education; ethnology; female; health insurance; high risk population; Hispanic; human; major clinical study; minority group; Black person; priority journal; risk assessment; socioeconomics

Utility of two cancer organization websites for a multiethnic, public hospital oncology population: comparative cross-sectional survey. - Nguyen, K.D.; Hara, B.; Chlebowski, R.T. (Journal of medical Internet research, 2005)
BACKGROUND: While information websites have been developed by major cancer organizations, their appropriateness for patients in multiethnic, multilingual public hospital settings has received limited attention. OBJECTIVE: The objective of the study was to determine the utility of cancer information websites for a public hospital patient population. METHODS: A 70-item questionnaire was developed to evaluate cancer information seeking behavior, Internet access and use, and content appropriateness of two cancer information websites: People Living with Cancer from the American Society of Clinical Oncology (ASCO) and Breast Cancer Info from the Susan Komen Breast Cancer Foundation (SKF). Interviews were conducted with consecutive consenting oncology patients seen in a public hospital oncology clinic. RESULTS: Fifty-nine persons participated in the survey. The response rate was 80%. Participants were Caucasian (25%), African American (19%), Hispanic (42%), and Asian/Pacific Islander (11%). English was the primary language in 53% of participants, 56% had a high school education or less, and 74% had an annual income less than US 35000 dollars. With respect to computer and Internet use, 71% had computer access, and 44% searched for cancer information online, with more being interested in obtaining online information in the future (63%). Participants who had computer access were likely to be English speaking (P = .04). Those less likely to have previously used a computer tended to have a lower annual income (P = .02) or to be males aged 55 years or older (P < .05). When shown sample content from the two websites, almost all participants stated that it was "easy to understand" (ASCO 96%, SKF 96%) and had "easy to understand terms" (ASCO 94%, SKF 92%). Somewhat fewer respondents agreed that the websites provided "information they could use" (ASCO 88%, SKF 80%) or that they would return to these websites (ASCO 73%, SKF 68%). The majority planned to "discuss website information with their oncologists" (ASCO 82%, SKF 70%). CONCLUSIONS: Multiethnic, multilingual cancer patients at a public county hospital commonly had Internet access and found the content of two websites representative of major cancer organizations to be both understandable and useful.
Keywords: article; attitude to computers; cross-sectional study; educational status; ethnic group; female; health survey; human; income; Internet; male; neoplasm; non profit organization; organization and management; patient selection; psychological aspect; public hospital; questionnaire; reproducibility; United States

Do false-positive screening results affect screening behavior for prostate cancer? - Adolfsson, J. (Nature Clinical Practice Urology, 2005)
Keywords: prostate specific antigen; academic achievement; African American; cancer diagnosis; cancer screening; Caucasian; digital rectal examination; ethnic difference; ethnology; follow up; human; laboratory diagnosis; male; patient care; patient compliance; priority journal; prostate cancer; refusal to participate; short survey

Prostate-specific antigen screening in a high-risk population: Lessons from the community and how they relate to large-scale population-based studies - Shelton, J.B.; Barocas, D.A.; Conway, F.; Hart, K.; Nelson, K.; Richstone, L.; Gonzalez, R.R.; Raman, J.D.; Scherr, D.S. (Urology, 2005)
Objectives. To estimate the incidence of prostate cancer among African-American men and Caribbean immigrants to the United States, to assess the applicability of large-scale prostate screening trials to a community screening program, and to recruit unscreened men. Methods. African-American and Caribbean-American men were targeted with a community-based prostate cancer screening program in Jamaica, New York. Serum prostate-specific antigen determination and digital rectal examination were used to determine abnormal findings. The incidence of an abnormal screening examination was used to project the incidence of prostate cancer, which was compared with that in other reported trials. Results. The projected incidence of prostate cancer among African-Americans and Caribbean-Americans older than 50 years was 8% and 7%, respectively, similar to that reported in other trials of African-American men. The projected incidence of prostate cancer in Caribbean-American men aged 40 to 49 years was 1%, the same as the high rate reported among Caribbean men. As in other trials, a family history of prostate cancer and age were strong predictors of abnormal findings. Of the recruited men older than 50 years, 58% had never been screened compared with 42% nationally. Conclusions. Large population-based screening trials have identified ethnic groups at high risk of prostate cancer. This trial detected high rates of abnormal screening findings by targeting ethnicity. The incidence of an abnormal examination was high in Caribbean-American men younger than 50 years old. Finally, this trial successfully recruited underscreened men. © 2005 Elsevier Inc.
Keywords: prostate specific antigen; adult; African American; article; cancer incidence; cancer screening; controlled study; digital rectal examination; ethnic group; ethnology; family history; high risk population; human; major clinical study; male; prediction; priority journal; prostate cancer; race difference; United States

A combined breast health/weight loss intervention for Black women - Fitzgibbon, M.L.; Stolley, M.R.; Schiffer, L.; Sanchez-Johnsen, L.A.P.; Wells, A.M.; Dyer, A. (Preventive Medicine, 2005)
Background. Overall incidence of breast cancer is slightly lower, but mortality rates are higher, for Black women compared to White women. Higher body mass index (BMI), sedentary lifestyles, and lower compliance with recommended breast health behaviors may contribute to higher risk and mortality. Methods. A randomized pilot intervention trial was conducted to assess feasibility and efficacy of a combined breast health/weight loss intervention for 64 overweight or obese Black women, ages 35-65. The primary objectives were to determine whether a 20-week (twice weekly) intervention could decrease weight and dietary fat intake and increase physical activity and breast self-exam (BSE) proficiency. Results. The project was implemented in two cohorts and retention was high for both (96% and 89%, respectively). Both cohorts showed increased proficiency in BSE in the intervention versus the control group (2.4 vs. -0.4, P < 0.05; 3.3 vs. -0.2, P < 0.001, respectively), but only cohort 2 showed decreased percent body weight (4.0% decrease vs. 0.9% increase, P < 0.01), increased physical activity frequency (2.4 vs. 0.1 times/week, P < 0.05), and a trend for decreased dietary fat (-2.6% kcal vs. 0.0% kcal, P = 0.07) in the intervention compared to the control group. Conclusion. Few studies have documented weight loss among Black women, and no combined breast health/weight loss intervention has been conducted. This study documents the feasibility of recruiting, randomizing, and retaining women in a combined intervention and demonstrated weight loss and associated lifestyle changes. © 2004 The Institute For Cancer Prevention and Elsevier Inc. All rights reserved.
Keywords: adult; article; body weight; breast cancer; cancer prevention; clinical trial; cohort analysis; controlled clinical trial; controlled study; dietary intake; fat intake; female; health; human; major clinical study; Black person; obesity; physical activity; pilot study; priority journal; randomized controlled trial; self examination; body weight loss

Supportive-affective group experience for persons with life-threatening illness: Reducing spiritual, psychological, and death-related distress in dying patients - Miller, D.K.; Chibnall, J.T.; Videen, S.D.; Duckro, P.N. (Journal of Palliative Medicine, 2005)
Background: Attention to psycho-socio-spiritual needs is considered critical by patients with life-threatening illnesses and their caregivers. Palliative care interventions that address these needs - particularly spirituality - are lacking. Objective: To evaluate the effects of an innovative program to address psycho-socio-spiritual needs in patients with life-threatening illnesses. Design: A group intervention entitled Life-Threatening Illness Supportive-Affective Group Experience (LTI-SAGE) was developed for reducing patient spiritual, emotional, and death-related distress. Setting/subjects: African American and Caucasian patients (n = 69) from two hospitals in St. Louis, Missouri, with life-threatening medical conditions (cancer; human immunodeficiency virus/acquired immune deficiency syndrome [HIV/AIDS]; geriatric frailty; liver, kidney, pulmonary, or cardiovascular disease) were randomly assigned to intervention or control groups. Intervention patients participated in a maximum of 12 LTI-SAGE groups over a 12-month period. Control patients received standard care. Measurements: Outcome measures were depression symptoms, anxiety, spiritual well-being, and death-related emotional distress. Results: After attrition, 51 (73.9%) patients completed the trial. At the end of the trial, after factoring in compliance, intervention patients had significantly fewer depression symptoms and death-related feelings of meaninglessness and significantly better spiritual well-being than did control patients. Conclusions: The use of the LTI-SAGE model for enhancing the end-of-life illness experience is promising. © Mary Ann Liebert, Inc.
Keywords: adult; African American; anxiety; article; malignant neoplasm; cardiovascular disease; Caucasian; clinical trial; controlled clinical trial; controlled study; depression; distress syndrome; dying; emotional stress; geriatric disorder; human; Human immunodeficiency virus infection; kidney disease; liver disease; lung disease; major clinical study; outcomes research; randomized controlled trial; religion; school child; support group; terminal disease; wellbeing

Lessons learned in developing a support intervention for African American women with breast cancer. - Coward, D.D. (Oncology nursing forum, 2005)
PURPOSE/OBJECTIVES: To describe the process of planning a theory-based support group project for African American women with breast cancer. DATA SOURCES: A needs assessment and recruitment strategies consistent with the Oncology Nursing Society's Multicultural Outcomes: Guidelines for Cultural Competence were used to adapt a support group intervention for newly diagnosed African American women in urban central Texas. DATA SYNTHESIS: The reviewed literature and local cancer survivor leaders indicated the need for education and support of newly diagnosed women. Although researchers worked for several years with lay leaders to gain legitimacy and trust, not enough participants were recruited to test an intervention specifically for African American women.CONCLUSIONS: Recruiting support group research participants from a relatively small minority population is problematic even when collaborating with population leaders. IMPLICATIONS FOR NURSING: Nurses may encounter barriers to conducting research in minority populations. Starting early to build credibility with that population, being flexible with eligibility criteria, beginning with pre-experimental studies, and paying participants may be required.
Keywords: adult; African American; article; breast tumor; cultural factor; ethnology; female; human; intervention study; needs assessment; nurse attitude; nursing; patient advocacy; program development; psychological aspect; public relations; self help

The impact of socioeconomic status and race on trial participation for older women with breast cancer - Gross, C.P.; Filardo, G.; Mayne, S.T.; Krumholz, H.M. (Cancer, 2005)
BACKGROUND. Older women, and older minorities in particular, are under represented in breast cancer trials. Although socioeconomic status (SES) is associated with both race and age, to the authors' knowledge little is known regarding the impact of SES on trial enrollment among older women with breast cancer. METHODS. The authors performed a case-control study comparing women who were participants in National Cancer Institute cooperative group breast cancer trials (cases) with a population-based sample of breast cancer patients (controls) obtained from the linked Surveillance, Epidemiology, and End Results (SEER)-Medicare data base. The sample was restricted to women age a 65 years who were living in SEER areas. Proxies for SES included the proportion of the population below poverty level (by zip code) and unemployed (by county) as well those with Medicaid insurance coverage. A multivariable logistic regression model was used to test the association of SES with trial participation after accounting for other patient and county characteristics. RESULTS. In bivariate analysis, trial participants were significantly less likely than community cancer patients to reside in high-poverty zip codes (20.9% vs. 24.9%, respectively; P < 0.001) or to have Medicaid insurance (2.0% vs. 10.0%; P < 0.0001). After adjusting for race, age, and county, trial participation remained inversely related to residing in areas with high poverty (odds ratio [OR] vs. residents of remaining counties, 0.78; 95% confidence interval [95% CI], 0.62-0.98), high unemployment rates (OR vs. residents of residents of counties in the lowest quartile, 0.50; 95% CI, 0.35-0.71), and having Medicaid insurance (OR vs. women without Medicaid, 0.22; 95% CI, 0.13-0.37); black race was not found to be related to trial participation (OR for black vs. white, 1.0; 95% CI, 0.67-1.47). CONCLUSIONS. Low SES was associated inversely with trial enrollment for older women with breast cancer and appeared to account for the enrollment disparities between black patients and white patients. Future efforts to enhance enrollment of elderly women in cancer research should identify specific barriers related to SES that may be amenable to intervention. © 2004 American Cancer Society.
Keywords: African American; aged; article; Asian; breast cancer; cancer epidemiology; cancer research; case control study; Caucasian; clinical trial; controlled clinical trial; controlled study; demography; female; health behavior; health insurance; Hispanic; human; major clinical study; medicaid; Black person; patient attitude; poverty; priority journal; race difference; social status; socioeconomics; unemployment

Designing the Selenium and Vitamin E Cancer Prevention Trial (SELECT) - Lippman, S.M.; Goodman, P.J.; Klein, E.A.; Parnes, H.L.; Thompson Jr., I.M.; Kristal, A.R.; Santella, R.M.; Probstfield, J.L.; Moinpour, C.M.; Albanes, D.; Taylor, P.R.; Minasian, L.M.; et al. (Journal of the National Cancer Institute, 2005)
Prostate cancer continues to be a major health threat, especially among African American men. The Selenium and Vitamin E Cancer Prevention Trial (SELECT), which opened on July 25, 2001, was planned to study possible agents for the prevention of prostate cancer in a population of 32 400 men in the United States, including Puerto Rico, and Canada. SELECT is a phase III randomized, placebo-controlled trial of selenium (200 μg/day from L-selenomethionine) and/or vitamin E (400 IU/day of all rac α-tocopheryl acetate) supplementation for a minimum of 7 years (maximum of 12 years) in non-African American men at least 55 years of age and African American men at least 50 years of age. SELECT is a large, simple trial that conforms as closely as possible with community standards of care. This commentary discusses the design problems the SELECT investigators had to resolve in developing the trial, including the role of prostate cancer screening, the best forms and doses of the study agents, and estimation of the event (prostate cancer) rate of men on the placebo arm. © Oxford University Press 2005, all rights reserved.
Keywords: acetylsalicylic acid; alpha tocopherol; alpha tocotrienol; beta carotene; beta tocopherol; beta tocotrienol; colecalciferol; delta tocopherol; delta tocotrienol; drug metabolite; gamma tocopherol; gamma tocotrienol; inorganic compound; methylselenol; multivitamin; placebo; selenite; selenium; selenomethionine; unclassified drug; vitamin; African American; age; article; brain hemorrhage; Canada; cancer incidence; cancer prevention; cancer screening; clinical trial; community care; drug absorption; drug activity; drug blood level; drug dose regimen; drug efficacy; drug fatality; drug formulation; drug mechanism; drug potentiation; drug retention; drug safety; ethnic difference; financial management; genotoxicity; health hazard; heart protection; high risk population; human; long term care; lung cancer; male; medical decision making; methodology; patient selection; planning; population research; priority journal; prostate cancer; Puerto Rico; retinitis pigmentosa; skin cancer; standard; cerebrovascular accident; United States; vitamin blood level; vitamin supplementation; aspirin

Polymorphisms in cytochrome P4503A5 (CYP3A5) may be associated with race and tumor characteristics, but not metabolism and side effects of tamoxifen in breast cancer patients - Tucker, A.N.; Tkaczuk, K.A.; Lewis, L.M.; Tomic, D.; Lim, C.K.; Flaws, J.A. (Cancer Letters, 2005)
Tamoxifen (TAM) is widely used for treatment and prevention of breast cancer. TAM is metabolized by cytochrome P450 (CYP450) enzymes, including CYP3A5. Although two genetic polymorphisms in CYP3A5 are known (CYP3A5*3 and CYP3A5*6), the effects of these polymorphisms on TAM metabolism, TAM side effects, and tumor characteristics are unknown. Thus, this work tested the hypothesis that CYP3A5 polymorphisms are associated with differential TAM levels, TAM side effects, and tumor characteristics in breast cancer patients. Postmenopausal women with breast cancer (n=98) were recruited from a single cancer center. Polymorphic status was established using polymerase chain reactions (PCR). The associations between polymorphic status, race, TAM levels, side effects, and tumor characteristics were assessed using t-tests and logistic regression models. The data indicate that 40.7% of the breast cancer patients had the CYP3A5*3 polymorphism, and 9.1% had the CYP3A5*6 polymorphism. In addition, Caucasian women were 26 times more likely to carry the CYP3A5*3 polymorphism than African American (AA) women, whereas AA women were nine times more likely to carry the CYP3A5*6 polymorphism than Caucasian women. No significant differences were seen in TAM or TAM metabolite levels or TAM side effects by polymorphic status. There was a significant difference, however, in mean tumor size in women with the CYP3A5*6 polymorphism (3.6±0.98 cm) compared to those without the polymorphism (2.0±0.18 cm) (P<0.02). Taken together, these data suggest that racial differences in CYP3A5 polymorphisms exist although the polymorphisms do not appear to be associated with levels of TAM metabolites and side effects. © 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: cytochrome P450 3A5; tamoxifen; African American; article; breast carcinoma; Caucasian; clinical trial; depression; disease association; genetic polymorphism; hot flush; human; insomnia; irritability; migraine; nausea; polymerase chain reaction; postmenopause; priority journal; race; tumor volume; vaginal dryness

The deep south network for cancer control: Eliminating cancer disparities through community - Academic collaboration - Partridge, E.E.; Fouad, M.N.; Hinton, A.W.; Hardy, C.M.; Liscovicz, N.; White-Johnson, F.; Higginbotham, J.C. (Family and Community Health, 2005)
African Americans have a substantially increased mortality rate compared to Whites in many cancers, including breast and cervix. The Deep South Network for Cancer Control (the Network) was established to develop sustainable community infrastructure to promote cancer awareness, enhance participation of African Americans and other special populations in clinical trials, recruit and train minority investigators, and develop and test innovative community-based cancer control measures to eliminate cancer mortality disparities in special populations. This article describes the steps necessary to form the network and the process and activities required to establish it as an effective infrastructure for eliminating disparities between Whites and African Americans in the United States.
Keywords: African American; article; breast cancer; cancer center; cancer control; cancer mortality; European American; health program; human; medical research; methodology; sustainable development; United States; uterine cervix cancer

Quality-of-life concerns of African American breast cancer survivors within rural North Carolina: Blending the techniques of photovoice and grounded theory - López, E.D.S.; Eng, E.; Randall-David, E.; Robinson, N. (Qualitative Health Research, 2005)
Social norms imposing a prevailing silence around breast cancer in rural African American communities have made it difficult for survivors to express their quality-of-life (QOL) concerns. In this article, the authors describe how they blended the photovoice method (providing participants with cameras so they can record, discuss, and relate the realities of their lives) with grounded theory techniques to assist 13 African American breast cancer survivors from rural eastern North Carolina in (a) exploring how they perceive and address their QOL within their own social context and (b) developing a conceptual framework of survivorship QOL. The framework that emerged reveals that three social forces (racism, stigmas regarding cancer, and cultural expectations of African American women) drive four QOL concerns (seeking safe sources of support, adjusting to the role of cancer survivor, feeling comfortable about the future, and serving as role models) and that survivors address these concerns by relying on spiritual faith and devising strategies to maintain social standing. © 2005 Sage Publications.
Keywords: adult; African American; aged; article; breast cancer; cancer patient; cancer survival; clinical article; concept formation; cultural anthropology; female; human; methodology; patient participation; priority journal; quality of life; race difference; religion; social status; social support; theoretical study; United States; videorecorder

Importance of patient selection when determining the significance of the CYP3A5 polymorphism in clinical trials - Foti, R.S.; Fisher, M.B. (Pharmacogenomics Journal, 2004)
Keywords: alprazolam; antiestrogen; azathioprine; benzodiazepine derivative; benzothiazepine derivative; corticosteroid; cyclosporine; cytochrome P450 3A1; cytochrome P450 3A4; cytochrome P450 3A5; diltiazem; everolimus; immunosuppressive agent; midazolam; multidrug resistance protein 1; vinorelbine tartrate; nifedipine; rapamycin; tacrolimus; tamoxifen; triazolam; African American; article; breast cancer; Caucasian; dose response; drug clearance; drug hydroxylation; drug metabolism; enzyme substrate; ethnic difference; gene frequency; genetic polymorphism; genotype; heterozygote; homozygosity; human; patient selection; population genetics; priority journal

Pilot evaluation of black cohosh for the treatment of hot flashes in women - Pockaj, B.A.; Loprinzi, C.L.; Sloan, J.A.; Novotny, P.J.; Barton, D.L.; Hagenmaier, A.; Zhang, H.; Lambert, G.H.; Reeser, K.A.; Wisbey, J.A. (Cancer Investigation, 2004)
Background. Hot flashes cause significant morbidity in postmenopausal women, including women with breast cancer. We undertook a pilot study to estimate the effectiveness of black cohosh to reduce hot flashes. Methods. Women who reported significant hot flashes (≥ 14 per week) were enrolled. Black cohosh was given in the form of the commercial product Remifemin. The first week was a no-treatment baseline period, and therapy was given for the subsequent 4 weeks. Hot flash data were collected by daily questionnaires during baseline and treatment weeks. Adverse effects were recorded. Results. Twenty-one women completed the study. Their mean age was 56 years (range, 38-80). Thirteen patients had a history of breast cancer. Six patients were taking tamoxifen or raloxifene. Patients reported an average of 8.3 hot flashes per day during the baseline week. The reduction in mean daily hot flash frequency was 50% (95% CI, 34%-65%), while weekly hot flash scores were reduced 56% (95% CI, 40%-71%) at completion of the study. Overall, patients reported less trouble with sleeping, less fatigue, and less abnormal sweating. No patients stopped therapy because of adverse effects. Conclusions. Black cohosh appeared to reduce hot flashes and had a low toxicity. The efficacy found in this trial seems to be more than would be expected by a placebo effect (20%-30% hot flash reduction in previous trials). These results suggest that further evaluation of this black cohosh preparation with a phase III randomized trial is indicated.
Keywords: Actaea racemosa extract; gabapentin; placebo; raloxifene; tamoxifen; venlafaxine; adult; anorexia; anxiety disorder; article; breast cancer; Actaea racemosa; clinical article; clinical trial; constipation; controlled clinical trial; controlled study; drug efficacy; fatigue; female; hot flush; human; mood disorder; morbidity; nervousness; pilot study; postmenopause; priority journal; questionnaire; restlessness; scoring system; side effect; sleep time; somnolence; sweating; treatment outcome; xerostomia; remifemin

Phase II trial of estramustine and etoposide in androgen-sensitive metastatic prostate carcinoma - Vaishampayan, U.; Fontana, J.; Du, W.; Hussain, M. (American Journal of Clinical Oncology: Cancer Clinical Trials, 2004)
Background: Early chemohormonal therapy in metastatic prostate cancer may offer an advantage by simultaneously targeting androgen-dependent and -independent clones. Hence, a phase II trial was conducted to evaluate the efficacy and toxicity of estramustine and etoposide in hormone-sensitive metastatic prostate cancer. Patient and Methods: Eligibility consisted of untreated metastatic prostate cancer, adequate organ function, and a performance status of 0 to 2 by Zubrod criteria. A 21-day schedule of oral estramustine (10 mg/kg/day) and etoposide (50 mg/m2/day) was administered every 28 days. Hormonal therapy was allowed at the end of the protocol therapy. Toxicity was assessed weekly, PSA levels were assessed with each cycle, and objective response was evaluated every 3 cycles. Results: Twenty-one patients were enrolled (10 white, 11 black) with a median age of 59.5 years (range, 42-79 years), a median PSA of 338 ng/mL (range, 0.9-20,000 ng/mL), and a median Gleason score of 8 points. Ten patients had bone-only metastases, 11 had measurable disease, of whom 4 had visceral metastases. A total of 128 cycles were administered (median, 6 cycles). No dose reductions were required. Nineteen patients were able to be evaluated for response. Severe toxicities included thromboembolic events and anemia in 2 patients each and fatigue in 1 patient. There were no episodes of febrile neutropenia. Response was observed in 8 of 11 patients (73%) with measurable disease. Median PSA nadir after therapy was 0.45 ng/mL, and undetectable PSA (<0.1 ng/mL) was achieved in 4 patients. Median time to PSA progression was 16.65 months. At a median follow-up of 34 months, 18 patients were alive. The 1-, 2-, and 3-year overall survival rates were 90%, 82%, and 72% respectively. Median survival has not yet been reached. Conclusion: The combination of estramustine and etoposide is well tolerated, and has promising activity in newly diagnosed metastatic prostate cancer.
Keywords: androgen; estramustine; etoposide; prostate specific antigen; adult; aged; alopecia; anemia; article; asthenia; bone metastasis; cancer survival; Caucasian; clinical article; clinical trial; deep vein thrombosis; drug dose reduction; drug efficacy; drug eruption; drug tolerability; dyspnea; edema; fatigue; febrile neutropenia; fluid retention; follow up; hormonal therapy; hot flush; human; impotence; nausea and vomiting; Black person; nipple; phase 2 clinical trial; prostate carcinoma; scoring system; side effect; survival rate; thrombocytopenia; thromboembolism; visceral metastasis

Factors associated with breast cancer clinical trials participation and enrollment at a large academic medical center - Simon, M.S.; Du, W.; Flaherty, L.; Philip, P.A.; Lorusso, P.; Miree, C.; Smith, D.; Brown, D.R. (Journal of Clinical Oncology, 2004)
Purpose: The practice patterns of medical oncologists at a large National Cancer Institute Comprehensive Cancer Center in Detroit, MI were evaluated to better understand factors associated with accrual to breast cancer clinical trials. Patients and Methods: From 1996 to 1997, physicians completed surveys on 319 of 344 newly evaluated female breast cancer patients. The 19-item survey included clinical data, whether patients were offered clinical trial (CT) participation and enrollment, and when applicable, reasons why they were not. Multivariate analyses using logistic regression were performed to evaluate predictors of an offer and enrollment. Results: The patients were 57% white, 32% black, and 11% other/unknown race. One hundred six (33%) were offered participation and 36 (34%) were enrolled. In multivariate analysis, CTs were less likely offered to older women (mean age, 52 years for those offered v 57 years for those not offered; P = .0005) and black women (21% of blacks offered v 42% of whites; P = .0009). Women with stage 1 disease, poor performance status, and those who were previously diagnosed were also less likely to be offered trials. None of these factors were significant predictors of enrollment. Women were not offered trials because of ineligibility (57%), lack of available trials (41%), and noncompliance (2%). Reasons for failed enrollment included patient refusal (88%) and failed eligibility (12%). Conclusion: It is important for cooperative groups to design studies that will accommodate a broader spectrum of patients. Further work is needed to assess ways to improve communication about breast cancer CT participation to all eligible women. © 2004 by American Society of Clinical Oncology.
Keywords: article; breast cancer; cancer research; clinical trial; controlled clinical trial; controlled study; female; health survey; human; multivariate logistic regression analysis; oncology; patient participation; priority journal; university hospital

A randomized trial of recruitment methods for older African American men in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial. - Ford, M.E.; Havstad, S.L.; Davis, S.D. (Clinical trials (London, England), 2004)
BACKGROUND: Incidence rates for many types of cancer are higher among African American men than in the general population, yet African American men are less likely to participate in cancer screening trials. This paper describes the outcomes of a randomized trial (the AAMEN Project) designed to recruit African American men aged 55-74 years to a prostate, lung and colorectal cancer screening trial. METHODS: The recruitment interventions address four types of barriers to clinical trial participation: sociocultural barriers, economic barriers, individual barriers and barriers inherent in study design. Subjects were randomized to a control group or one of three increasingly intensive intervention arms, which used different combinations of mail, phone and in person church-based recruitment. RESULTS: Of the 39,432 African American men residing in the geographically defined study population (southeastern Michigan and northern Ohio), 17,770 men (45%) could be contacted, and 12,400 (31% of 39,432) were found to be eligible to participate. No statistically significant differences in age, education or income level were found among participants in the four study arms. A significantly greater enrollment yield (3.9%) was seen in the most intensive, church-based intervention arm, compared to the enrollment yields in the other two intervention arms (2.5 and 2.8%) or the control group (2.9%) (P < 0.01). CONCLUSIONS: The intervention that involved the highest rate of face-to-face contact with the study participants produced the highest enrollment yield, but several strategies that were thought could improve yield had no effect. These findings, which are consistent with current literature on population-based recruitment, should facilitate the development of future recruitment efforts involving older African American men.
Keywords: African American; aged; article; clinical trial; colorectal tumor; controlled clinical trial; controlled study; female; human; lung tumor; male; middle aged; ovary tumor; patient selection; prostate tumor; randomized controlled trial; socioeconomics; United States

A report on accrual rates for elderly and minority-ethnicity cancer patients to clinical trials of the american college of surgeons oncology group - Newman, L.A.; Hurd, T.; Leitch, M.; Kuerer, H.M.; Diehl, K.; Lucci, A.; Giuliano, A.; Hunt, K.K.; Putnam, W.; Wells, S.A. (Journal of the American College of Surgeons, 2004)
Incidence and mortality rates for cancers vary by ethnic background and patient age. Accrual of diverse patient populations to cancer clinical trials is essential in order to ensure that findings related to new management strategies can be generalized. The goal of this study was to evaluate accrual patterns for patients participating in the American College of Surgeons Oncology Group (ACOSOG) cancer protocols. Ethnic diversity among clinical trial investigators may also influence accrual patterns, so the ethnic background of the ACOSOG membership was also evaluated. Demographics for the patients registered on ACOSOG breast, thoracic, and colorectal clinical trials were evaluated and compared with data on the general population and the cancer population in the United States. Accrual patterns for patients from other reported cancer clinical trials were also presented, and the self-reported ethnic distribution of the ACOSOG membership was analyzed. Distribution of African Americans, Hispanic Americans, and Asian Americans to the ACOSOG breast and colorectal clinical trials was relatively proportionate to the cancer population. African Americans were underrepresented in the thoracic clinical trials, and this disparity was partially offset by data on the proportion of African Americans with stage-eligible lung cancer. Accrual rates for patients age 65 years and older were better than those reported by most other clinical trialists. Elderly patients are successfully recruited into surgical clinical trials, and this will provide important data for future analyses regarding cancer outcomes in this growing population of cancer patients. Aggressive outreach to minority-ethnicity cancer patients for accrual into clinical trials should continue. © 2004 American College of Surgeons.
Keywords: African American; article; Asian American; breast cancer; cancer patient; colorectal cancer; data analysis; demography; ethnology; evaluation study; human; lung cancer; minority group; population; priority journal; register

Breast cancer survivorship in a multiethnic sample: Challenges in recruitment and measurement - Ashing-Giwa, K.T.; Padilla, G.V.; Tejero, J.S.; Kim, J. (Cancer, 2004)
BACKGROUND. The inclusion of ethnic minorities in cancer-related studies continues to be an important concern for researchers. In this article, the authors present 1) a brief discussion of recruitment and measurement challenges in conducting multiethnic survivorship research, and 2) recruitment outcomes and sample characteristics for a health-related quality-of-life study with a multiethnic sample of breast cancer survivors (BCS). METHODS. A case-control, cross-sectional design with mixed sampling methods was used. The Contextual Model for Recruitment and Enrollment of Diverse Samples was used to guide the protocol. BCS were recruited from the California Cancer Surveillance Program, from hospital registries, and from community agencies. Participation rates, demographic factors, and medical factors were compared. The reliability of standard measures by ethnicity was assessed. RESULTS. Seven hundred three women participated, including 135 African-American women (19%), 206 Asian-American women (29%), 183 Latina-American women (26%), and 179 European-American women (26%). Participation was influenced by ethnicity, age, and site of recruitment. Overall, African Americans were least likely to participate, and European Americans most likely to participate. African Americans and Asian Americans were more likely to refuse, European Americans and Latina Americans were more likely to agree to participate, and European Americans and Asian Americans were most likely to complete the survey after consenting. Measures possessed moderate to excellent reliability (0.64-0.91). CONCLUSIONS. Despite important recruitment and measurement challenges, this study obtained acceptable participation rates and good internal consistency of the measures. The results demonstrate the utility of a culturally responsive approach to health disparities research. © 2004 American Cancer Society.
Keywords: adult; African American; age; arthritis; article; Asian American; body image; breast cancer; breast reconstruction; cancer chemotherapy; cancer hormone therapy; cancer radiotherapy; cancer research; cancer survival; cardiovascular disease; case control study; controlled study; cultural factor; diabetes mellitus; ethnic difference; European American; female; functional assessment; health care quality; Hispanic; human; hypertension; major clinical study; mastectomy; minority group; osteoporosis; partial mastectomy; patient satisfaction; priority journal; quality of life; reliability; religion; sampling; sexuality; physiological stress; United States

Participation in cancer clinical trials: Race-, sex-, and age-based disparities - Murthy, V.H.; Krumholz, H.M.; Gross, C.P. (Journal of the American Medical Association, 2004)
Context: Despite the importance of diversity of cancer trial participants with regard to race, ethnicity, age, and sex, there is little recent information about the representation of these groups in clinical trials. Objective: To characterize the representation of racial and ethnic minorities, the elderly, and women in cancer trials sponsored by the National Cancer Institute. Design, Setting, and Patients: Cross-sectional population-based analysis of all participants in therapeutic nonsurgical National Cancer Institute Clinical Trial Cooperative Group breast, colorectal, lung, and prostate cancer clinical trials in 2000 through 2002. In a separate analysis, the ethnic distribution of patients enrolled in 2000 through 2002 was compared with those enrolled in 1996 through 1998, using logistic regression models to estimate the relative risk ratio of enrollment for racial and ethnic minorities to that of white patients during these time periods. Main Outcome Measure: Enrollment fraction, defined as the number of trial enrollees divided by the estimated US cancer cases in each race and age subgroup. Results: Cancer research participation varied significantly across racial/ethnic and age groups. Compared with a 1.8% enrollment fraction among white patients, lower enrollment fractions were noted in Hispanic (1.3%; odds ratio [OR] vs whites, 0.72; 95% confidence interval [CI], 0.68-0.77; P<.001) and black (1.3%; OR, 0.71; 95% CI, 0.68-0.74; P<.001) patients. There was a strong relationship between age and enrollment fraction, with trial participants 30 to 64 years of age representing 3.0% of incident cancer patients in that age group, in comparison to 1.3% of 65- to 74-year-old patients and 0.5% of patients 75 years of age and older. This inverse relationship between age and trial enrollment fraction was consistent across racial and ethnic groups, Although the total number of trial participants increased during our study period, the representation of racial and ethnic minorities decreased. In comparison to whites, after adjusting for age, cancer type, and sex, patients enrolled in 2000 through 2002 were 24% less likely to be black (adjusted relative risk ratio, 0.76; 95% CI, 0.65-0.89; P<.001). Men were more likely than women to enroll in colorectal cancer trials (enrollment fractions: 2.1% vs 1.6%, respectively; OR, 1.30; 95% CI, 1.24-1.35; P<.001) and lung cancer trials (enrollment fractions: 0.9% vs 0.7%, respectively; OR, 1.23; 95% CI, 1.16-1.31; P<.001). Conclusions: Enrollment in cancer trials is low for all patient groups. Racial and ethnic minorities, women, and the elderly were less likely to enroll in cooperative group cancer trials than were whites, men, and younger patients, respectively. The proportion of trial participants who are black has declined in recent years.
Keywords: adult; African American; aged; aging; American Indian; article; breast cancer; malignant neoplasm; cancer incidence; cancer research; Caucasian; clinical trial; colorectal cancer; ethnic group; female; Hispanic; human; lung cancer; major clinical study; male; priority journal; prostate cancer; race difference; risk assessment

Detection of prostate cancer in men with prostate-specific antigen levels of 2.0 to 4.0 ng/mL equivalent to that in men with 4.1 to 10.0 ng/mL in a Japanese population - Kobayashi, T.; Nishizawa, K.; Ogura, K.; Mitsumori, K.; Ide, Y. (Urology, 2004)
Objectives To analyze prospectively whether prostate cancer (CaP) incidence differs between Japanese men with a prostate-specific antigen (PSA) level of 2.0 to 4.0 ng/mL and those with a PSA level of 4.1 to 10.0 ng/mL. Methods Men 79 years old or younger who were referred to our clinic were screened for CaP. Individuals with PSA levels of 2.0 ng/mL or greater were recommended for transrectal prostate biopsy. The prebiopsy clinical characteristics, cancer detection rate, and pathologic findings from the needle biopsy and prostatectomy specimen were compared between the low (2.0 to 4.0 ng/mL) and intermediate (4.1 to 10.0 ng/mL) PSA groups. Results Of 858 patients screened for CaP, 440 with benign findings on digital rectal examination met the criteria, and 274 (62.3%) underwent biopsy. Of those undergoing biopsy, 110 and 123 patients had a low or an intermediate PSA level, respectively. Men in the low PSA group had a higher free/total PSA ratio, smaller prostate volume, and lower PSA density compared with those in the intermediate PSA group. CaP was diagnosed in 26 (23.6%) of 110 in the low and 29 (23.6%) of 123 in the intermediate PSA group. No statistically significant difference was found between the two groups in the pathologic findings of needle biopsy, including Gleason score, number of cores per biopsy, percentage of positive cores, and cancer length in the positive cores. Conclusions No statistically significant difference was found in the incidence of CaP (23.6%) between men with low and intermediate PSA levels in a Japanese population. The diagnostic yield was comparable to that reported for both white and black men. © 2004 Elsevier Inc.
Keywords: prostate specific antigen; adult; aged; article; cancer diagnosis; cancer incidence; cancer localization; cancer screening; comparative study; concentration response; controlled study; disease marker; human; Japan; laboratory test; major clinical study; male; medical assessment; needle biopsy; patient selection; population research; priority journal; prostate biopsy; prostate cancer; relative density; scoring system; statistical significance

Recruiting Black/African American Men for Research on Prostate Cancer Prevention - Woods, V.D.; Montgomery, S.B.; Herring, R.P. (Cancer, 2004)
BACKGROUND. Black/African American men die of prostate cancer at a greater rate relative to other males. During the period from 1992 to 1998, prostate cancer incidence rates in the United States were 234.2 per 100,000 persons among non-Hispanic black males and 144.6 per 100,000 persons among white males. The reasons for these increased rates of prostate cancer among black males are largely unknown, but increased mortality is associated with late detection. The authors conducted a longitudinal study of black men that investigated prostate cancer prevention behaviors within this population. The purpose of the current article is to identify successful recruitment strategies that were reported by participants in this study of prevention behaviors. METHODS. Qualitative research methods were used to elucidate men's thoughts, attitudes, beliefs, and practices regarding prostate cancer prevention behaviors and to identify strategies for attracting black men to research programs and retaining them in these programs. RESULTS. Ethnocentric recruitment strategies that were identified included the development of tailored printed materials; the use of targeted locations; and a personalized, participatory approach for engaging potential participants. We contacted 498 black men and enrolled a cohort of 277 non-Hispanic black males (75% of whom were recruited within a 9-week period) in the current study. CONCLUSIONS. Unlike other studies that reported difficulty in recruiting African American men, the current study did not encounter such difficulties. The authors attribute their success to culturally attractive Afrocentric materials; cultural sensitivity; a caring, professional, personalized ethnic approach; respect; and participatory involvement of the target population. Nonetheless, the authors did encounter barriers, such as lack of physician interest and lack of trust in quality medical care. These barriers must be overcome before black males can be engaged and retained in research studies on prostate cancer prevention. © 2004 American Cancer Society.
Keywords: adult; African American; aged; article; cancer incidence; cancer mortality; cancer prevention; cancer research; cultural factor; ethnology; human; longitudinal study; priority journal; prostate cancer; United States

Dietary manipulation, ethnicity, and serum PSA levels - Eastham, J.A.; Riedel, E.; Latkany, L.; Fleisher, M.; Schatzkin, A.; Lanza, E.; Shike, M. (Urology, 2003)
Objectives. To examine whether a diet low in fat and high in fiber, fruits, and vegetables and ethnicity had any influence on serum prostate-specific antigen (PSA) levels, because serum PSA is a marker for the presence of prostate cancer. The incidence of prostate cancer increases with age, varies by ethnicity, and is greater among men with a first-degree relative who has had the disease. Large international variations in the rates of prostate cancer incidence and mortality, as well as the incidence changes in migrants and their offspring, also suggest that exogenous factors, including diet, have a strong influence on the development of this disease. Methods. We used data and blood samples from the Polyp Prevention Trial, a multicenter randomized trial designed to evaluate the impact of a diet low in fat and high in fiber, fruits, and vegetables on the recurrence of colorectal adenomas. Recruitment was from 1991 through 1994. Participants were followed up from their baseline recruitment date for 4 years. From this group, we identified 1100 white men and 97 black men who were 35 years of age or older, did not have prostate cancer, and had serum samples available for study. Results. At baseline, no difference was present in the fat intake for the black and white men (mean ± SE, 90 ± 3.6 g/day and 84 ± 1.0 g/day, respectively; P = 0.15). The baseline serum PSA levels did not vary by ethnicity. For black men, the mean serum PSA level was 2.2 ± 0.36 ng/mL compared with 2.0 ± 0.07 ng/mL for white men (P = 0.64). Although all men assigned to the intervention group markedly reduced their fat intake by approximately 15% and increased their fruit and vegetable intake by approximately 2.25 servings per day, no difference was noted in the kinetics of the serum PSA levels by dietary intervention or race. Conclusions. Although ethnic differences in the incidence of prostate cancer are well defined, we found no difference in the baseline fat intake among black and white men that might have contributed to this difference. Serum PSA, a marker often used in early detection programs for prostate cancer, was not associated with manipulation of the amount of fat in the diet, regardless of ethnicity. © 2003 Elsevier Inc.
Keywords: prostate specific antigen; adult; article; blood level; cancer incidence; Caucasian; clinical trial; comparative study; diet; ethnic difference; ethnology; evaluation study; fat intake; fruit; high fiber diet; human; low fat diet; male; mortality; Black person; priority journal; prostate cancer; race difference; vegetable; vegetarian diet

For the patient. Improving participation of African-American men in research studies. - Hoyo, C.; Reid, M.L.; Godley, P.A.; Parrish, T.; Smith, L.; Gammon, M. (Ethnicity & disease, 2003)
Keywords: adult; aged; article; cohort analysis; ethnology; human; male; middle aged; Black person; patient attitude; patient education; patient selection; prostate tumor; questionnaire; treatment refusal; trust; United States

Barriers and strategies for sustained participation of African-American men in cohort studies - Hoyo, C.; Reid, M.L.; Godley, P.A.; Parrish, T.; Smith, L.; Gammon, M. (Ethnicity and Disease, 2003)
Background: Prostate cancer incidence is about 70% higher among African Americans compared to Whites. Factors associated with this differential remain unclear, although several studies suggest that genetic factors may play a role. Before epidemiologic research can adequately identify factors associated with this differential, we need studies to determine the feasibility of recruiting and retaining African-American men in cohort studies, especially those that collect biological and questionnaire data. Methods: We conducted 4 focus group discussions among African-American men aged 40 to 64 years in North Carolina, and an additional group comprised of their partners, using a semi-structured interview protocol (total N=55 subjects). Data were analyzed with QRS NU*DIST to identify themes. Results: Participants' willingness to participate in cohort studies seemed to be motivated by a perceived risk of prostate cancer. Barriers to participation included mistrust of the research community, poor knowledge of cancer-site specific heterogeneity, anticipated time commitment, and the invasive nature of disease detection procedures. To foster trust and increase disease knowledge, recommended strategies included: partnering with known civic organizations that provide education on risk factors; discussing early signs and symptoms at the point of recruitment; recruiting participants from community clusters; and providing periodic feedback on biologic samples (if collected) to reassure participants of their proper usage. Conclusion: Observational cohort studies focused on African-American men are feasible if certain barriers to participation are addressed.
Keywords: adult; aged; article; attitude; cancer diagnosis; cancer incidence; cancer risk; Caucasian; clinical protocol; cohort analysis; community; controlled study; data analysis; ethnic group; ethnology; female; health education; heredity; human; illness behavior; information processing; male; Black person; patient attitude; patient selection; prostate cancer; prostate tumor; questionnaire; risk factor; spouse; symptomatology; trust; United States

Barriers and strategies for sustained participation of African-American men in cohort studies - Hughes, D.G.; Sellers, D.B.; Fraser Jr., L.B.; Knight, B.; Areghan, G.A. (Ethnicity and Disease, 2003)
Keywords: adult; aged; article; attitude; cancer risk; cancer screening; Caucasian; clinical article; clinical trial; cohort analysis; education; emotion; ethnic group; ethnology; female; human; illness behavior; male; medical decision making; medical research; methodology; Black person; Black person; patient attitude; patient selection; perception; prostate cancer; prostate tumor; questionnaire; race difference; risk factor; social status; trust; United States

Sentinel lymph node mapping with emulsion of activated carbon particles in patients with pre-mastectomy diagnosis of intraductal carcinoma of the breast - Liu, C.-L.; Yang, T.-L.; Chen, B.-F. (Journal of the Chinese Medical Association, 2003)
Background. The most common tracers used for lymphatic mapping in sentinel lymph node dissection (SLND) are blue dye and radio-colloid. The former is associated with hypersensitivity, and the latter is not available in some institutions. It is still unclear as to which subsets of patients benefit most from SLND. In this study, we tried to evaluate the usefulness of activated carbon in SLND in the early stages of breast cancer. Methods. Patients with palpable lesions diagnosed as ductal carcinoma in situ (DCIS) or intraductal carcinoma with micro-invasion (DCMI) ftorn their core-needle biopsy specimens were eligible for the study. A 0.4-0.6 cc emulsion of activated carbon particles (ACP) was injected peri-lesionally or subdermally, 5 minutes before modified radical mastectomy. When the axillary compartment was entered, the black-stained sentinel nodes (SLNs) were dissected and examined with H&E stain by frozen section. The extension of subsequent axillary lymph node dissection (ALND) was determined by the status of the sentinel nodes. Results. Twenty-eight patients were diagnosed as DCIS and 10 as DCMI initially. The SLNs were successfully localized in 33 patients (86.8%), with an average of 2.4 SLNs dissected. The SLNs were positive for metastasis in three patients, and the non-sentinel axillary lymph nodes (ALNs) were also positive in one of them. The final diagnosis of these patients turned out to be infiltrating ductal carcinoma. The SLNs were negative for metastasis in 30 patients, and all the ALNs of these patients were also negative. Among these 33 patients, the final diagnosis was up-graded in nine (27.3%), including the three patients with positive SLNs. The SLNs were not identified in five patients, and the ALNs were positive for metastasis in one of them. Conclusions. ACP is an acceptable tracer for lymphatic mapping in SLND. For patients with palpable, biopsy-proven DCIS or DCMI, SLND can be used to select patients for ALND.
Keywords: activated carbon; dye; tracer; article; axillary lymph node; breast cancer; breast carcinoma; metastatic breast cancer; cancer staging; carcinoma in situ; clinical article; clinical trial; controlled clinical trial; controlled study; dose response; emulsion; frozen section; human; human tissue; intraductal carcinoma; invasive carcinoma; lymph node dissection; mastectomy; needle biopsy; palpation; patient selection; preoperative evaluation; sentinel lymph node; staining; surgical technique; treatment outcome

Changes in the geographical and temporal patterns of cancer incidence among black gold miners working in South Africa, 1964-1996 - McGlashan, N.D.; Harington, J.S.; Chelkowska, E. (British Journal of Cancer, 2003)
We describe here the results of the final 8 years of geographical and temporal data of a 33-year study of the cancer experience of 12.8 million man-years of black miners working on the gold fields of South Africa over the period 1964-96. These workers were recruited from 15 territories, the major areas during the most recent period being Lesotho (26.8%), Transkei (21.5%) and Mozambique (15%). The earliest analyses, 1964-71 and 1972-79, showed hepatocellular and oesophageal cancers to be the most frequent cancers. The final analysis, for 1989-96, however, shows marked temporal changes in the relative position of four cancers or grouped malignancies: respiratory cancer up by 236%, hepatocellular carcinoma down to 32%, oesophageal holding steady, and lymphatic system cancers up by 420%, almost certainly because of association with HIV/AIDS infection. Significant geographical variations occurring between the home areas of the miners are important, as mining operations have little to do with the cancers that develop. The causes are essentially socio-environmental rather than occupational, and this means that the rates of the major cancers in the miners are surrogate measures of the same cancers in the home areas. © 2003 Cancer Research UK.
Keywords: gold; acquired immune deficiency syndrome; adolescent; adult; aged; article; bladder cancer; cancer incidence; colorectal cancer; environmental factor; esophagus cancer; geography; health survey; human; Human immunodeficiency virus infection; larynx cancer; leukemia; liver cell carcinoma; lung cancer; lymphatic leukemia; major clinical study; miner; mouth cancer; Mozambique; Black person; occupational disease; priority journal; social aspect; socioenvironmental factor; South Africa; statistical analysis; stomach cancer

Reported family history of cancer in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial - Pinsky, P.F.; Kramer, B.S.; Reding, D.; Buys, S. (American Journal of Epidemiology, 2003)
The authors analyzed data from almost 150,000 subjects aged 55-74 years enrolled in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial who completed a self-administered baseline questionnaire (1993-2001) that included items about family history of cancer. Male respondents reported significantly less family history of cancer than females. The relative underreporting by male respondents relative to females was greater for female family members (28% lower for sisters and 21% lower for mothers) than for male family members (13% lower for brothers and 9% lower for fathers). Black, Hispanic, and Asian respondents reported significantly less family history of cancer than Whites. Reported family history prevalences for parents decreased with respondents' age, while those for siblings increased with respondents' age. The four most commonly reported cancers in families were breast (11.8%), lung (10.1%), colorectal (9.4%), and prostate (7.3%) cancer. Expected prevalences in family members of history of cancer overall and history of specific types of cancer were calculated using incidence rates and life table data obtained from the Surveillance, Epidemiology, and End Results Program. Overall, the ratio of reported cancer rates to expected cancer rates in family members was approximately 0.7. Liver, bone, stomach, and brain cancer had greater-than-average reported: expected ratios, while lymphoma, bladder cancer, melanoma, and testicular cancer had lower-than-average ratios.
Keywords: adult; aged; article; Asian; bladder cancer; bone cancer; brain cancer; breast cancer; cancer incidence; cancer risk; cancer screening; Caucasian; clinical trial; colorectal cancer; controlled clinical trial; controlled study; ethnic group; family history; female; genetic predisposition; human; liver cancer; lung cancer; lymphoma; major clinical study; male; melanoma; Black person; ovary cancer; prevalence; prostate cancer; questionnaire; randomized controlled trial; sex difference; stomach cancer; testis cancer

Patient education for informed decision making about prostate cancer screening: a randomized controlled trial with 1-year follow-up. - Volk, R.J.; Spann, S.J.; Cass, A.R.; Hawley, S.T. (Annals of family medicine, 2003)
PURPOSE: The efficacy of prostate cancer screening is uncertain, and professional organizations recommend educating patients about potential harms and benefits. We evaluated the effect of a videotape decision aid on promoting informed decision making about prostate cancer screening among primary care patients. METHODS: A group of 160 men, 45 to 70 years of age, with no history of prostate cancer, were randomized to view or not to view a 20-minute educational videotape before a routine office visit at a university-based family medicine clinic. The subjects were contacted again 1 year after their visit to assess their receipt of prostate cancer screening (digital rectal examination [DRE] or prostate-specific antigen [PSA] testing), their satisfaction with their screening decision, and knowledge retention since the baseline assessment. RESULTS: Follow-up assessments were completed for 87.5% of the intervention subjects and 83.8% of the control subjects. The rate of DRE did not differ between the 2 groups. Prostate-specific antigen testing was reported by 24 of 70 (34.3%) intervention subjects and 37 of 67 (55.2%) control subjects (P = .01). African American men were more likely to have had PSA testing (9 of 16, 56.3%) than were white men (13 of 46, 28.3%) (P = .044). Satisfaction with the screening decision did not differ between the study groups. Intervention subjects were more knowledgeable of prostate cancer screening than were control subjects, although these differences declined within 1 year (P < .001). CONCLUSIONS: Decision aids for prostate cancer screening can have a long-term effect on screening behavior and appear to promote informed decision making.
Keywords: prostate specific antigen; aged; article; blood; clinical trial; controlled clinical trial; controlled study; decision making; follow up; human; male; mass screening; methodology; middle aged; patient education; physical examination; prostate tumor; randomized controlled trial; rectum; videorecording

Estimates of the number of U.S. women who could benefit from tamoxifen for breast cancer chemoprevention - Freedman, A.N.; Graubard, B.I.; Rao, S.R.; McCaskill-Stevens, W.; Ballard-Barbash, R.; Gail, M.H. (Journal of the National Cancer Institute, 2003)
Background: The Breast Cancer Prevention Trial demonstrated that tamoxifen treatment produced a 49% reduction in the risk of invasive breast cancer among women at elevated risk for the disease. The U.S. Food and Drug Administration (FDA) subsequently approved tamoxifen for women aged 35 years or older with a 5-year breast cancer risk of 1.67% or higher for breast cancer chemoprevention. However, tamoxifen use has been associated with adverse outcomes, and not all eligible women have a positive benefit/risk ratio. Methods: We used weighted data from the year 2000 National Health Interview Survey Cancer Control Module to estimate the total number of U.S. women, aged 35-79 years, who were eligible for tamoxifen chemoprevention based on the FDA eligibility criteria. We also estimated the numbers of white and black women who would benefit from tamoxifen chemoprevention on the basis of a positive benefit/risk index developed by Gail et al. Results: Of the 65826074 women aged 35-79 years without reported breast cancer in the United States in 2000, 10232816 women (15.5%, 95% confidence interval [CI] = 14.7% to 16.3%) would be eligible for tamoxifen chemoprevention. The percentage of U.S. women who would be eligible varied dramatically by race, with 18.7% (95% CI = 17.8% to 19.7%) of white women, 5.7% (95% CI = 4.3% to 7.5%) of black women, and 2.9% (95% CI = 2.1% to 3.9%) of Hispanic women being eligible. Of the 50 104829 white U.S. women aged 35-79 years, 2 431 911 (4.9%, 95% CI = 4.3% to 5.4%) would have a positive benefit/risk index for tamoxifen chemoprevention. Of the 7 481 779 black U.S. women aged 35-79 years, only 42 768 (0.6%, 95% CI = 0.2% to 1.3%) would have a positive benefit/risk index. Among white women, 28 492 (95% CI = 24 693 to 32 292) breast cancers would be prevented or deferred if those women who have a positive net benefit index took tamoxifen over the next 5 years. Conclusion: A substantial percentage of U.S. women would be eligible for tamoxifen chemoprevention according to FDA criteria, but a much smaller percentage would have an estimated net benefit. Nevertheless, this latter percentage corresponds to more than two million women.
Keywords: tamoxifen; adult; age; aged; article; breast cancer; tumor invasion; cancer risk; Caucasian; chemoprophylaxis; controlled study; deep vein thrombosis; drug approval; drug indication; drug use; endometrium cancer; female; Food and Drug Administration; frequency analysis; gender; health survey; high risk patient; human; human tissue; lung embolism; major clinical study; Black person; patient selection; priority journal; race difference; risk assessment; risk benefit analysis; treatment outcome; United States

Factors influencing patient survival in a group of men with prostate cancer in Yaoundé, Cameroon - Angwafo III, F.F.; Atanga, P.N.; Minkoulou, E.; Fouda, P.J.; Kim, K.S.; Adams-Campbell, L.; Zoung-Kanyi, J. (UroOncology, 2003)
Purpose: We evaluated the survival time of patients with stage D cancer of the prostate (CaP) in Yaounde, Cameroon, so as to lay the groundwork for evaluating patient management and outcomes in such communities in sub-Saharan Africa. Patients and Materials: A cohort of 200 patients was recruited at diagnosis and followed over a 171 month period. They had a standard work-up and staging protocol except for the absence of bone scan. Treatment was offered after they were staged following the Whitemore ABCD-system. Standard statistical analysis was performed for quantitative variables and graphs developed for continuous variables. Pearson correlation and Chi-square tests were used to evaluate associations between variables. The Kaplan-Meier product-limit method was used to estimate survival functions and log-rank test to compare data from complete survival curves. The statistical significance level was fixed at p values less than or equal to 0.05. Results: The mean age of our patients was 67 years and 41.5% of them were in the 60-69 year-bracket. Survival was worse for those 66 years and older (p = 0.013). Patient survival correlated with tumor differentiation such that a Gleason score of 6 or greater meant diminished survival time (p = 0.014). For the entire group, median overall survival was 40.5 months, 44% at 5 years and 17% at 10 years. Patients who received multi-modal therapy (complete androgen ablation by surgical and medical means, and radiation to the pelvis and metastatic sites) seemed to have the best survival (p < 0.001) although patient stratification into treatment groups was not randomized. A comparison of survival of African-American cohorts and this group showed no statistical significance (p = 0.1). Conclusion: Survival of patients with prostate cancer in Yaounde is just as low as in African-Americans. Survival is worse however, for men older than 66 years in Yaounde. A call for comparative and collaborative clinical trials is made.
Keywords: androgen; adult; age; aged; article; bone scintiscanning; Cameroon; cancer staging; cancer survival; cohort analysis; controlled study; correlation analysis; disease association; human; major clinical study; male; Black person; priority journal; prostate cancer; prostatectomy; race difference; survival time

The national utilization of immediate and early delayed breast reconstruction and the effect of sociodemographic factors - Alderman, A.K.; McMahon Jr., L.; Wilkins, E.G. (Plastic and Reconstructive Surgery, 2003)
The purpose of this study was to identify important sociodemographic factors affecting the utilization of immediate and early delayed postmastectomy breast reconstruction in the United States. Using the Surveillance, Epidemiology, and End Results (SEER) program, all cases of mastectomy-treated breast cancer that were reported to a SEER registry in 1998 were identified. Data were limited to reconstructions within the first 4 months postmastectomy, and logistic regression was used to analyze the effects of sociodemographic variables on reconstruction rates. Of the 10,406 mastectomy-treated breast cancer patients, 1607 (15 percent) underwent reconstruction within the first 4 months postmastectomy. Compared with women 45 to 54 years old, those 35 to 44 years old were significantly more likely to have breast reconstruction (OR = 1.52, p < 0.001), but women 55 to 64, 65 to 74, and 75 years and older were significantly less likely to have reconstruction (OR = 0.42, p < 0.001; OR = 0.16, p < 0.001; OR = 0.04, p < 0.001, respectively). Compared with Caucasian women, African American, Hispanic, and Asian women were significantly less likely to have reconstruction (OR = 0.48, p < 0.001; OR = 0.45, p < 0.001; OR = 0.29, p < 0.001, respectively). In addition, a four-fold difference in reconstruction rates existed in high-use versus low-use regions. With regard to the type of reconstruction, patients younger than 35 and 65 to 74 years old were significantly less likely to receive autogenous tissue reconstruction compared with women 45 to 54 years old (OR = 0.47, p = 0.047; OR = 0.61, p = 0.031, respectively). However, African Americans were significantly more likely to receive autogenous tissue reconstructions compared with Caucasians (OR = 2.03, p = 0.021). According to these data, the utilization of immediate and early delayed breast reconstruction in the United States is low and is significantly influenced by patients' age, race, and geographic location. Further research is needed to evaluate the impact of provider bias, patient preference, and barriers to care on the utilization of breast reconstruction in the United States.
Keywords: adult; age distribution; aged; article; Asian; autograft; breast carcinoma; breast reconstruction; Caucasian; controlled study; ethnic difference; female; geographic distribution; health care utilization; human; logistic regression analysis; major clinical study; mastectomy; Black person; patient selection; postoperative period; priority journal; race difference; self concept; surgical technique; United States

Self-reported reasons men decide not to participate in free prostate cancer screening. - Weinrich, S.P.; Weinrich, M.C.; Priest, J.; Fodi, C. (Oncology nursing forum, 2003)
PURPOSE: To determine the reasons why men fail to participate in a free prostate cancer screening. DESIGN: Survey and secondary analyses using correlational design. SETTING: Community sites in the Southeastern United States. SAMPLE: The sample (N = 241) ranged in age from 40-68 years. Mean age was 50 years (SD = 7.4). Most of the men were African American (79%) and married (70%). Almost half of the subjects (44%) earned between $9,601 and $25,020 per year. METHOD: Telephone survey of men who did not participate in initial prostate cancer screening after educational program. MAIN RESEARCH VARIABLES: Demographics, self-reported reasons men decided not to participate in a free screening following a prostate cancer educational program, and predictors for subsequent participation in screening. FINDINGS: The main self-reported reason for not participating in a free prostate cancer screening opportunity was time problems. A significant relationship between income and physician problems existed among the men who did not participate. Twenty-one percent of the 241 men participated in a second opportunity for free prostate cancer screening. Men who cited "lost packet" as their reason for not participating in the first free screening were more than twice as likely to go for the second opportunity for free screening when offered another packet or voucher for a free screening with their physician of choice. CONCLUSIONS: "Time problems" was the most frequent self-reported reason men gave for failure to participate. Providing a follow-up phone call and vouchers a second time for reimbursement of the cost associated with a screening increased participation. Men often need assistance with locating physicians and nurse practitioners who will file for financial reimbursement. Appointment reminders are critical. IMPLICATIONS FOR NURSING: The findings of this study of the significant relationship between income and "physician problems" for not participating has implications for healthcare providers. Future programs could provide telephone follow-up with men and remail vouchers, as needed. In addition, men could be encouraged to designate one place in their households for health-related papers (for safekeeping).
Keywords: adult; African American; aged; article; attitude to health; Caucasian; health care delivery; health survey; human; male; mass screening; middle aged; nursing; patient attitude; patient participation; prostate tumor; socioeconomics; statistics; United States

An intervention study on screening for breast cancer among single African-American women aged 65 and older - Zhu, K.; Hunter, S.; Bernard, L.J.; Payne-Wilks, K.; Roland, C.L.; Elam, L.C.; Feng, Z.; Levine, R.S. (Preventive Medicine, 2002)
Background. Older African-American women with single marital status are least likely to use screening procedures. This study aimed to evaluate a breast screening intervention program conducted in this population. Methods. Ten public housing complexes were randomly assigned to either the intervention or the control group. African-American women aged 65 and over were recruited into the study if they were widowed, divorced, separated, or never married and did not have a history of breast cancer (n = 325). The intervention program was delivered by lay health educators at the participant's apartment and was designed to increase knowledge about breast screening, reduce psychological problems, and increase support from significant others. Breast-screening-related cognition and behavior were measured at baseline and at 1 and 2 years postintervention. Results. Comparisons of the preintervention and postintervention measurements showed that while the proportion of women who had a clinical breast examination or mammogram in the preceding year was decreased at 1 year postintervention in the control group, it was increased in the intervention group. However, the differences did not reach a significant level. No consistent patterns could be found in changes of breast self-examination and variables in knowledge, attitudes, and beliefs. When analyses were restricted to women whose significant others had provided information or help on breast screening, results were better, but the differences between the intervention and control groups still did not reach statistical significance. Conclusions. These results did not suggest significant effects of an intervention program that used lay health educators to promote breast cancer screening in older single African-American women. © 2002 American Health Foundation and Elsevier Science (USA).
Keywords: aged; article; attitude; behavior; breast cancer; breast examination; cancer screening; clinical trial; cognition; controlled clinical trial; controlled study; human; major clinical study; mammography; measurement; medical information; Black person; priority journal; randomized controlled trial; support group

Lower gastrointestinal hemorrhage in African-American and hispanic elderly patients - Akhtar, A.J. (Ethnicity and Disease, 2002)
Objectives: To investigate the frequency and etiology of lower gastrointestinal hemorrhage (LGIH) in African-American and Hispanic elderly patients and to determine its natural history and the risks and benefits of therapeutic interventions. Setting: Inner-city community teaching hospital serving predominantly African-American and Hispanic populations. Methods: Records of 236 patients, 65 to 103 years of age, with a diagnosis of LGIH were reviewed retrospectively, over a period of 7 years, (9 White and 6 Asian patients were excluded). Results: In 21 patients, the source of bleeding was located in the upper gastrointestinal tract, and these patients were excluded from the study. The source of bleeding remained unidentified in 16 of 200 patients, and they were also excluded. Bleeding was so profuse in 19 patients that satisfactory endoscopy could not be performed and emergency angiography and/or surgery was required. Endoscopic results were available in 165 patients and included: internal hemorrhoids in 60 (active bleeding in 23) patients, diverticular bleeding in 55, angiodysplasia in 50, polyps in 37, cancer in 23, drug-induced (anti-coagulants, non-steroidal anti-inflammatory drugs) lesions in 20, ischemic colitis in 15, ulcerative colitis in 10, solitary rectal ulcer in 9, Crohn's disease in 8, and colonic varices in 6 patients. Forty-eight patients had more than one lesion. Endoscopic therapy was given to 101 patients and was helpful in stopping bleeding and/or delaying surgery in 69 patients. Overall, there were 43 deaths, mostly due to underlying multiple system disease. Mortality rates did not differ by race/ethnicity or gender. Older elderly (76-85 yrs.; P<0.01) and (>85 yrs.; P<0.001) had higher mortality rates. None of the deaths were directly due to endoscopy. Conclusions: Despite the small number of patients, our study suggests that acute LGIH in African-American and Hispanic elderly patients is a common condition, with the potential to become a life-threatening event. All such patients should be offered the benefits of early endoscopy and therapeutic interventions, unless contraindicated by their advanced directives. A patient's advanced age should not be a deterrent to any of the diagnostic or therapeutic interventions.
Keywords: acetylsalicylic acid; alcohol; anticoagulant agent; antiinflammatory agent; nonsteroid antiinflammatory agent; abdominal angiography; age; aged; alcohol abuse; angiodysplasia; article; colon Crohn disease; colon diverticulosis; colon polyp; community hospital; controlled study; death; diagnostic procedure; disease severity; drug induced disease; early diagnosis; elderly care; emergency surgery; endoscopic surgery; ethnology; female; frequency analysis; gastrointestinal endoscopy; gastrointestinal hemorrhage; gender; hemorrhoid; human; human tissue; intestine cancer; intestine injury; ischemic colitis; major clinical study; male; medical record; mortality; patient selection; race difference; rectum ulcer; retrospective study; risk benefit analysis; treatment contraindication; ulcerative colitis; upper gastrointestinal tract; varicosis; aspirin

Comparisons of tailored mammography interventions at two months postintervention - Champion, V.L.; Skinner, C.S.; Menon, U.; Seshadri, R.; Anzalone, D.C.; Rawl, S.M. (Annals of Behavioral Medicine, 2002)
The recent decrease in breast cancer mortality has been linked in part to increased breast cancer screening. Although the percentage of women screened once is rising, rate of continued adherence is poor. The purpose of this article is to assess the effects of tailored mammography interventions implemented prospectively in a factorial design contrasting groups receiving either (a) usual care (no intervention), (b) tailored telephone counseling for mammography, (c) tailored mailed materials promoting mammography, or (d) a combination of tailored mail and telephone counseling. This prospective, randomized study with a 2 × 2 factorial design included women 51 years and older (N = 1,367) who were not adherent with mammography at baseline. The intervention is based on integration of the Transtheoretical and Health Belief Models. Participants were enrolled in one of two health maintenance organizations or seen in a university-related primary care clinic. Baseline data were collected on mammography history and beliefs and knowledge related to mammography. Data were collected via telephone interviews using previously developed scales. The follow-up interviewers were conducted with 976 women. The sample was 41% White, 56% African American, and 3% other. Mean age at baseline was 66.5. Logistic regression indicates that postintervention mammography status in all three intervention groups was significantly better than usual care, with odds ratios ranging from 1.66 (telephone only) to 2.16 (telephone plus mail).
Keywords: adult; aged; article; breast carcinoma; cancer risk; cancer screening; cancer susceptibility; clinical trial; confidence interval; controlled clinical trial; controlled study; family history; female; genetic predisposition; health maintenance organization; human; major clinical study; mammography; marriage; patient compliance; patient counseling; primary medical care; prospective study; randomized controlled trial; risk assessment; screening test; telephone

Outcomes and toxicity in African-American and Caucasians patients in a randomized adjuvant chemotherapy trial for colon cancer - McCollum, A.D.; Catalano, P.J.; Haller, D.G.; Mayer, R.J.; Macdonald, J.S.; Benson III, A.B.; Fuchs, C.S. (Journal of the National Cancer Institute, 2002)
Background: Previous studies have demonstrated that African-Americans with colon cancer have worse overall and stage-specific survival rates than Caucasians. Such differences could reflect variation in access to health care, in tumor biology, or in treatment efficacy. Little is known about potential differences in chemotherapy-related toxicities between African-Americans and Caucasians. In this study, we examined survival and toxic effects among African-American and Caucasian patients enrolled in a large, randomized phase III trial of adjuvant chemotherapy for resected colon cancer. Methods: We analyzed data on 3380 patients (344 African-Americans and 3036 Caucasians) enrolled in a randomized trial of adjuvant 5-fluorouracil-based chemotherapy in patients with stage II (high risk) and stage III colon cancer to evaluate differences in outcomes and toxicity. We compared disease-free survival (DFS) and overall survival (OS) between African-Americans and Caucasians by the Kaplan-Meier method, computed Cox proportional hazards by multivariable analysis, and compared treatment-related toxicity rates by Fisher's exact test. All statistical tests were two-sided. Results: We found no differences in DFS or OS between African-American and Caucasian patients. Five-year DFS was 57% (95% confidence interval [CI] = 52% to 62%) for African-Americans and 58% (95% CI = 56% to 60%) for Caucasians (P = .15), and 5-year OS was 65% (95% CI = 60% to 70%) for African-Americans and 66% (95% CI= 64% to 68%) for Caucasians (P = .38). On multivariable analysis, no statistically significant difference in disease recurrence or death was detected between the racial/ethnic groups (hazard ratios for African-Americans versus Caucasians: disease recurrence = 1.1, 95% CI = 0.9 to 1.3; death = 1.1, 95% CI = 0.9 to 1.3). Treatment-related toxicity differed between the African-American and Caucasian patients, with African-Americans experiencing statistically significantly lower rates of diarrhea (P<.001), nausea (P<.001), vomiting (P = .01), stomatitis (P<.001), and overall toxicity (P = .005). Conclusions: In this study of patients with similar access to health care resources and treatment with adjuvant chemotherapy, we found similar 5-year DFS and OS in African-Americans and Caucasians with stage II and III colon cancer. The two groups derived similar benefits from adjuvant chemotherapy. Moreover, African-Americans appeared to experience less treatment-related toxicity.
Keywords: fluorouracil; folinic acid; levamisole; adult; aged; anemia; article; cancer adjuvant therapy; cancer mortality; cancer recurrence; cancer staging; cancer survival; Caucasian; clinical trial; colon cancer; confidence interval; controlled clinical trial; controlled study; data analysis; diarrhea; ethnic group; female; fever; Fisher exact test; gastrointestinal toxicity; hazard assessment; health care access; high risk patient; human; infection; Kaplan Meier method; leukopenia; major clinical study; male; multivariate analysis; nausea; Black person; phase 3 clinical trial; priority journal; race difference; randomized controlled trial; skin toxicity; statistical analysis; stomatitis; survival rate; thrombocytopenia; treatment outcome; vomiting

Clearance rates of total prostate specific antigen (PSA) after radical prostatectomy in African-Americans and Caucasians - Lotan, Y.; Roehrborn, C.G. (Prostate Cancer and Prostatic Diseases, 2002)
Racial differences in serum prostate specific antigen (PSA) values in men with and without prostate cancer have been observed but have yet to be explained. We aimed to determine if ethnic variations in the rate of metabolism of PSA could explain the different levels of PSA found in African-American and Caucasian men. In a prospective fashion, patients diagnosed with biopsy-proven clinically localized adenocarcinoma of the prostate and scheduled for radical prostatectomy were selected for the study. Eleven patients (six Caucasian, five African-American) were enrolled in the study. All patients demonstrated normal liver and renal function. Sera for total PSA were obtained at the following time intervals: preoperative (within 3 months of operation), time 0 (at time of prostate removal), 1, 4, 8, 24, 48, 72, 168 and 336 h after removal of the prostate. A log - linear regression model was then used to determine the metabolic clearance rate and half-life of serum total PSA. There were no statistically significant differences between Caucasian and African-American patients with regard to age, PSA prior to surgery, prostate weight, Gleason sum and PSA half-life. The metabolic clearance of total PSA followed first order kinetics. When comparing serum PSA levels expressed as a fraction of the baseline PSA, Caucasian and African-American patients demonstrated similar rates of metabolism. This study found similar rates of elimination of serum total PSA between African-Americans and Caucasians. These findings suggest that the rate of metabolism of PSA is similar for these groups. Further studies are needed to explain racial differences of serum PSA in patients with and without prostate cancer.
Keywords: prostate specific antigen; adult; age; aged; article; blood analysis; cancer localization; Caucasian; clinical article; controlled study; ethnic difference; half life time; human; kidney function; kinetics; linear regression analysis; liver function; male; metabolic clearance rate; Black person; organ weight; patient selection; perioperative period; postoperative period; preoperative period; priority journal; prospective study; prostate adenocarcinoma; prostate biopsy; prostatectomy; race difference; statistical model; statistical significance

The study of tamoxifen and raloxifene: Preliminary enrollment data from a randomized breast cancer risk reduction trial - Vogel, V.G.; Costantino, J.P.; Wickerham, D.L.; Cronin, W.M.; Wolmark, N. (Clinical Breast Cancer, 2002)
Tamoxifen reduced the risk of invasive breast cancer by 49% among women at increased risk for breast cancer in the Breast Cancer Prevention Trial P-1, and raloxifene reduced breast cancer incidence by more than 70% in the Multiple Outcomes of Raloxifene Evaluation osteoporosis trial. These findings led the National Surgical Adjuvant Breast and Bowel Project to design and launch the Study of Tamoxifen and Raloxifene. Risk-eligible women are ≥ 35 years of age and postmenopausal; they have either lobular carcinoma in situ (LCIS) or a 5-year risk of invasive breast cancer of at least 1.67% as determined by the Gail model. Participants are randomly assigned to receive either tamoxifen 20 mg or raloxifene 60 mg daily. The trial opened for accrual on July 1, 1999. After 32 months of recruitment at 194 clinical centers in North America, risk assessments have been performed in 107,855 women (83.8% white, 9.4% black, 3.8% Hispanic, 3.1% other race/ethnic groups). Of the eligible patients, 12,637 have been randomized (20.9% of risk-eligible women); the median age is 58 years (mean, 58 years), and the median 5-year risk of breast cancer is 3.3% (mean, 4.0%). LCIS was reported in 8.4% of women prior to randomization. Gail model risk was ≥ 3.0% in 5 years for 59.3% of white women, 45.0% of black women, and 44.5% of Hispanic women. The trial will recruit a total of 22,000 postmenopausal women and is powered to demonstrate superior efficacy of either agent or their equivalence in reducing the incidence of primary breast cancer.
Keywords: placebo; raloxifene; tamoxifen; adult; article; breast cancer; cancer incidence; cancer risk; Caucasian; clinical trial; controlled clinical trial; controlled study; deep vein thrombosis; drug efficacy; drug safety; endometrium cancer; ethnic difference; ethnic group; female; histopathology; human; human tissue; invasive carcinoma; lung carcinoma; lung embolism; Black person; postmenopause; randomized controlled trial; risk assessment; risk benefit analysis; cerebrovascular accident

African-American heredity prostate cancer study: a model for genetic research. - Powell, I.J.; Carpten, J.; Dunston, G.; Kittles, R.; Bennett, J.; Hoke, G.; Pettaway, C.; Weinrich, S.; Vijayakumar, S.; Ahaghotu, C.A.; Boykin, W.; Mason, T.; et al. (Journal of the National Medical Association, 2001)
A genome-wide scan of high-risk prostate cancer families in North America has demonstrated linkage of a particular marker to Chromosome Iq (HPC11. An even greater proportion of African-American families have shown linkage to HPC 1. Therefore, investigators at the National Human Genome Research Institute [NHGRI] in collaboration with Howard University and a predominantly African-American group of urologists established the African-American Hereditary Prostate Cancer (AAHPC) Study Network to confirm the suggested linkage of HPC in African Americans with a gene on Chromosome 1. Blood samples from recruited families were sent to Howard University for extraction of DNA. The DNA was sent to NHGRI at NIH where the genotyping and genetic sequence analysis was conducted. Genotype data are merged with pedigree information so that statistical analysis can be performed to establish potential linkage. From March 1, 1998, to June 1, 1999, a total of 40 African-American families have been recruited who met the study criteria. Preliminary results suggest that racial/ethnicity grouping may affect the incidence and extent of linkage of prostate cancer to specific loci. The importance of these findings lays in the future treatment of genetic-based diseases.
Keywords: article; ethnology; genetics; human; human genome project; male; middle aged; Black person; patient selection; prostate tumor; research; United States

Health related quality of life differences between black and white men with prostate cancer: Data from the cancer of the prostate strategic urologic research endeavor - Lubeck, D.P.; Kim, H.; Grossfeld, G.; Ray, P.; Penson, D.F.; Flanders, S.C.; Carroll, P.R. (Journal of Urology, 2001)
Purpose: Understanding the potential consequences of racial differences in prostate cancer outcomes, from survival rates to quality of life considerations, is important for the clinician and patient. We examined demographic, clinical and health related quality of life data comparing black with white patients just after treatment of prostate cancer and 1 year later. Materials and Methods: We analyzed data on 1,178 patients who were newly diagnosed with prostate cancer in the Cancer of the Prostate Strategic Urologic Research Endeavor, a national observational database of men recruited from 35 community and academic urology practices throughout the United States. Patient demographics, clinical characteristics and validated health related quality of life questionnaires were reviewed. A total of 958 white and 161 black patients with prostate cancer who completed at least 2 surveys were compared. Results: The black patients were younger, and had lower income and education levels than white patients. Controlling for age, education and income differences, black patients generally had worse clinical characteristics at presentation and lower baseline health related quality of life data scores in most generic and disease specific categories at treatment. The most notable exception was sexual function, which was the only score that was higher in black patients at treatment. With time, health related quality of life improved in both groups but black patients had slower rates of improvement for general health, bodily pain, physical function, role function, disease worry and bowel function. They continued to have higher sexual function. Conclusions: Significant differences exist in clinical presentation, sociodemographic characteristics, and health related quality of life between black and white men with prostate cancer. These health related quality of life differences remain after treatment. Physicians should not assume that outcomes in black men would be similar to other patients.
Keywords: adult; aged; anxiety; article; cancer research; Caucasian; data base; demography; human; intestine function; major clinical study; male; Black person; pain; priority journal; prostate cancer; quality of life; questionnaire; race difference; sexual function; United States; urology; validation process

Cues to participation in prostate cancer screening: a theory for practice. - Nivens, A.S.; Herman, J.; Pweinrich, S.; Weinrich, M.C. (Oncology nursing forum, 2001)
PURPOSE/OBJECTIVES: To develop and test the Cues to Participation in Prostate Cancer Screening Theory, which proposes that exposure to information from certain sources cues or triggers screening. DESIGN: Descriptive correlational. SETTING: 11 counties of a southeastern state. SAMPLE: Convenience sample of 1,867 men at risk for prostate cancer (72% African American; 28% Caucasian). METHODS: Recent exposure to prostate cancer information was measured. Men were offered free screening by prostate specific antigen (PSA) and digital rectal exam (DRE). MAIN RESEARCH VARIABLES: Demographic variables (race, age, education, income, and marital status), exposure (electronic media, print media, healthcare provider recommendation, and interpersonal interactions), and screening as measured by PSA and DRE. FINDINGS: Several major propositions of the Cues to Participation Theory were supported. General exposure to prostate cancer information significantly predicted screening participation. Hearing about prostate cancer from a healthcare provider was the best predictor of screening. CONCLUSIONS: Men's demographic characteristics should be considered when providing information about prostate cancer. Hearing about prostate cancer from family and friends was not significantly related to screening behavior. lMPLICATIONS FOR NURSING PRACTICE: The importance of recommendations for prostate cancer screening is underscored.
Keywords: adult; African American; aged; article; attitude to health; ethnology; health behavior; human; male; mass screening; middle aged; nursing; oncology nursing; patient participation; prostate tumor; psychological aspect; United States

Molecular epidemiologic studies within the Selenium and Vitamin E Cancer Prevention Trial (SELECT) - Hoque, A.; Albanes, D.; Lippman, S.M.; Spitz, M.R.; Taylor, P.R.; Klein, E.A.; Thompson, I.M.; Goodman, P.; Stanford, J.L.; Crowley, J.J.; Coltman, C.A.; Santella, R.M. (Cancer Causes and Control, 2001)
Objective: To conduct timely epidemiologic investigations of molecular/genetic markers that may contribute to the development of prostate, lung, colorectal, or other cancers within the Selenium and Vitamin E Cancer Prevention Trial (SELECT), and to evaluate interactions between these markers and the study interventions. Methods: The epidemiologic studies within SELECT will be based on 32,400 men aged 55 years or older (age 50 or older for the African-American men) enrolled into an intergroup, randomized, placebo-controlled, double-blind, phase III prevention trial of supplemental selenium and vitamin E developed and funded by the National Cancer Institute, and coordinated by the Southwest Oncology Group. During the 12-year study period approximately 1500-2000 cases of prostate cancer, 800 lung cancers, and 500 colon cancers are estimated to be diagnosed, based on data from the ongoing Prostate Cancer Prevention Trial of finasteride. A modified fasting blood sample will be processed to collect plasma for analysis of micronutrients, hormones, cytokines, and other proteins. Buffy-coat derived white blood cells collected at baseline will be used for isolation of DNA and establishment of immortalized cell lines. Red blood cells will be stored for analysis of hemoglobin adducts and other components. Results: Specific results anticipated from these molecular studies will provide information on factors hypothesized to contribute to prostate cancer risk and that may modify the efficacy of either trial supplement, including: steroid sex hormones and several polymorphic genes that encode proteins affecting androgenic stimulation of the prostate, including the androgen receptor, steroid 5α-reductase type II, CYP17, and β-hydroxysteroid dehydrogenase; polymorphisms of DNA repair genes and carcinogen metabolism genes, including those involved in the activation of chemical carcinogens to reactive intermediates (e.g., CYP1A1) or the detoxification of reactive intermediates (e.g., glutathione S-transferase M1); DNA and protein adducts; and insulin-like growth factors and leptin. Conclusion: SELECT offers an excellent opportunity to conduct molecular epidemiologic investigations to assess gene-environment interactions and their role in prostate, lung, and colon carcinogenesis.
Keywords: alpha tocopherol; leptin; selenium; sex hormone; somatomedin C; adult; aged; article; cancer prevention; cancer risk; carcinogenesis; colon cancer; controlled study; diet supplementation; DNA adduct; DNA repair; environmental factor; genetic marker; heredity; human; lung cancer; major clinical study; male; priority journal; prostate cancer; risk factor

The effects of message framing and ethnic targeting on mammography use among low-income women - Schneider, T.R.; Salovey, P.; Apanovitch, A.M.; Pizarro, J.; McCarthy, D.; Zullo, J.; Rothman, A.J. (Health Psychology, 2001)
The authors examined the effects that differently framed and targeted health messages have on persuading low-income women to obtain screening mammograms. The authors recruited 752 women over 40 years of age from community health clinics and public housing developments and assigned the women randomly to view videos that were either gain or loss framed and either targeted specifically to their ethnic groups or multicultural. Loss-framed, multicultural messages were most persuasive. The advantage of loss-framed, multicultural messages was especially apparent for Anglo women and Latinas but not for African American women. These effects were stronger after 6 months than after 12 months.
Keywords: adult; article; behavior modification; breast cancer; cancer screening; clinical trial; community care; controlled clinical trial; controlled study; ethnic group; female; health behavior; health center; health promotion; health service; human; lowest income group; major clinical study; mammography; randomized controlled trial; screening test

Comparisons of two breast cancer risk estimates in women with a family history of breast cancer - McTiernan, A.; Kuniyuki, A.; Yasui, Y.; Bowen, D.; Burke, W.; Culver, J.B.; Anderson, R.; Durfy, S. (Cancer Epidemiology Biomarkers and Prevention, 2001)
There is an increasing need for accurate prediction methods of assessing individual risk for breast cancer for both clinical and research purposes. The purpose of this study is to compare the Gail and Claus model risk estimates of breast cancer among women with a family history of breast cancer. This study presents risk estimates from two models of breast cancer risk in 491 women 18 to 74 years of age with a family history of breast cancer who were recruited to risk counseling clinical trials in Seattle, Washington between 1996 and 1997. These trials included women from the general population and additional samples of Ashkenazi Jewish, African-American, and lesbian women. We estimated and compared lifetime (to age 79) and 5-year risk for developing breast cancer using the National Surgical Adjuvant Breast and Bowel Project adaptation of the Gail model and the Claus model. About one-quarter of participants fell into the Gail "high" risk category (≥1.7% risk of developing breast cancer in the next 5 years). The average lifetime risk was estimated at 13.2% by the Gail model and 11.2% by the Claus model. Estimates from the two models were moderately and positively correlated (r = 0.55) with the Gail model yielding a higher estimate than the Claus model for most participants. If women with a family history of breast cancer are being counseled regarding decisions on genetic testing, tamoxifen use, or other preventive measures, presenting both Claus and Gail estimates may be the best option.
Keywords: adult; aged; article; breast cancer; calculation; cancer risk; comparative study; controlled study; family history; female; high risk population; human; major clinical study; mathematical analysis; model; priority journal; risk assessment; scoring system

Randomized trial of black cohosh for the treatment of hot flashes among women with a history of breast cancer - Jacobson, J.S.; Troxel, A.B.; Evans, J.; Klaus, L.; Vahdat, L.; Kinne, D.; Lo, K.M.S.; Moore, A.; Rosenman, P.J.; Kaufman, E.L.; Neugut, A.I.; Grann, V.R. (Journal of Clinical Oncology, 2001)
Purpose: Most breast cancer survivors experience hot flashes; many use complementary or alternative remedies for these symptoms. We undertook a randomized clinical trial of black cohosh, a widely used herbal remedy for menopausal symptoms, among breast cancer patients. Patients and Methods: Patients diagnosed with breast cancer who had completed their primary treatment were randomly assigned to black cohosh or placebo, stratified on tamoxifen use. At enrollment, patients completed a questionnaire about demographic factors and menopausal symptoms. Before starting to take the pills and at 30 and 60 days, they completed a 4-day hot flash diary. At the final visit, they completed another menopausal symptom questionnaire. Follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels were measured in a subset of patients at the first and final visits. Results: Of 85 patients (59 on tamoxifen, 26 not on tamoxifen) enrolled in the study, 42 were assigned to treatment and 43 were assigned to placebo; 69 completed all three hot flash diaries. Both treatment and placebo groups reported declines in number and intensity of hot flashes; the differences between the groups were not statistically significant. Both groups also reported improvements in menopausal symptoms that were, for the most part, not significantly different. Changes in blood levels of FSH and LH also did not differ in the two groups. Conclusion: Black cohosh was not significantly more efficacious than placebo against most menopausal symptoms, including number and intensity of hot flashes. Our study illustrates the feasibility and value of standard clinical trial methodology in assessing the efficacy and safety of herbal agents. © 2001 by American Society of Clinical Oncology.
Keywords: cimifuga racemosa extract; follitropin; herbaceous agent; luteinizing hormone; placebo; plant extract; tamoxifen; unclassified drug; adult; article; breast cancer; cancer survival; Actaea racemosa; clinical trial; constipation; controlled clinical trial; controlled study; double blind procedure; drug efficacy; drug safety; endometrium hyperplasia; female; follitropin blood level; heart arrhythmia; herbal medicine; hot flush; human; indigestion; luteinizing hormone blood level; major clinical study; menopause; muscle cramp; plant root; priority journal; questionnaire; randomized controlled trial; rash; vagina bleeding; body weight gain

The effect of patient reminders on the use of screening mammography in an urban health department primary care setting - Simon, M.S.; Gimotty, P.A.; Moncrease, A.; Dews, P.; Burack, R.C. (Breast Cancer Research and Treatment, 2001)
Mammography screening continues to be under-utilized, especially among women from lower socioeconomic groups. In order to determine whether having direct access to health care services has an effect on mammography use among low income women, we conducted a randomized trial of two alternative letter reminders among 1,717 women who were enrolled at two locations of a multi-site inner city health department in Detroit. All participants were 39 1/2 years of age and older and were due for a screening mammogram at randomization. A physician-directed reminder form was placed in each of the participant's medical records at the beginning of the study. In addition participants were randomized to receive either a letter directing them to visit their primary care physician, a letter directing them to contact the clinic directly to schedule a mammogram, or no letter. Study participants were predominantly African - American, two-thirds of whom were over age 50, and who had minimal health insurance coverage. During the intervention year, mammograms were completed by 179 out of 967 study women at site one (18.5%), and 90 out of 750 study women at site two (12%). A multivariate model controlling for the simultaneous effect of age, insurance type, visit history and past mammography use, showed no significant independent effect of either type of letter reminder on mammography completion during the study year. In conclusion, letters targeted at women due for screening mammograms did not have a beneficial effect on mammography utilization above and beyond that of a physician medical record reminder.
Keywords: adult; aged; article; breast cancer; breast disease; cancer screening; clinical trial; controlled clinical trial; controlled study; female; human; major clinical study; mammography; medicaid; medicare; primary medical care; priority journal; randomized controlled trial; screening test; urban area

Importance of fatalism in understanding mammography screening in rural elderly women. - Mayo, R.M.; Ureda, J.R.; Parker, V.G. (Journal of women & aging, 2001)
This study examined the relationship between demographic factors and other correlates of fatalism, and assessed the impact of fatalistic beliefs on the participation in breast cancer screening in rural women. The subjects were 220 women aged 50 and over recruited from 6 large rural counties in South Carolina. Data were collected using a demographic questionnaire and the revised Powe Fatalism Inventory. Results show significant associations between fatalism and increased age (p = 0.005), race (p = 0.0001), doctor recommendation (p = .0034) and decreased educational level (p = 0.001). Fatalism was associated with noncompliance with mammography screening in univariate analysis among African-American women (OR = .362; 95% CI: 1.11, 11.8). After adjusting for possible confounders (age, education, and doctor recommendation), fatalism was not significantly associated with noncompliance with screening. These results illustrate age, race, and education may be important predictors of fatalism and that fatalism may be one barrier that has previously gone unmeasured and unchallenged in understanding screening behavior in older women.
Keywords: aged; article; breast tumor; elderly care; female; health; human; mammography; mass screening; middle aged; patient participation; psychological aspect; rural population; United States; women's health

A Phase II trial of bryostatin 1 in the treatment of metastatic colorectal cancer - Zonder, J.A.; Shields, A.F.; Zalupski, M.; Chaplen, R.; Heilbrun, L.K.; Arlauskas, P.; Philip, P.A. (Clinical Cancer Research, 2001)
Current chemotherapy for patients with advanced colorectal cancer is relatively ineffective and may be associated with significant toxicity. Bryostatin 1 (bryo 1) influences cell proliferation, intracellular metabolism and signaling, differentiation, and apoptosis in human cancer cell lines via modulation of protein kinase C (PKC) activity. This trial investigates the efficacy and toxicity of bryo 1 as a novel therapeutic agent for patients with advanced colorectal cancer who have had previous 5-fluorouracil therapy. The primary end point was tumor response to bryo 1. Toxicity was also assessed. Twenty-eight patients with advanced colorectal cancer were enrolled. The mean age was 59 years (range, 38-76), with 16 men and 12 women, and good minority representation (11 African-Americans). The first 10 patients initially received 25 μg/m2 of bryo 1 weekly as a 24-h infusion for 3 weeks of every 4-week cycle, with dose escalation to 35 μg/m2 starting with the second cycle. The remaining patients were started at 35 μg/m2 and escalated to 40 μg/m2, if toxicity was minimal. Twenty-five patients were evaluable for objective tumor response, and complete data on toxicity were collected on 26 patients. No partial or complete tumor responses were observed. All 25 patients had disease progression within four cycles. Myalgia was the most common toxicity. Myelosuppression was not seen. bryo 1 as a weekly 24-h continuous infusion lacks single-agent antitumor activity in advanced colorectal cancer. Toxicity differs from that of traditional chemotherapeutic drugs.
Keywords: bryostatin 1; fluorouracil; adult; advanced cancer; aged; article; bone marrow suppression; cancer growth; clinical article; clinical trial; colorectal cancer; dose response; drug efficacy; drug mechanism; female; human; human cell; human tissue; male; myalgia; phase 2 clinical trial; priority journal

The need for comprehensive educational osteoporosis prevention programs for young women: Results from a second osteoporosis prevention survey - Kasper, M.J.; Peterson, M.G.E.; Allegrante, J.P. (Arthritis Care and Research, 2001)
Objective. To assess osteoporosis knowledge, beliefs, and preventive behaviors among young adult women and to identify sources that they would mostly likely utilize to learn more about the disease. Methods. Information was gathered through a cross-sectional survey of 321 women (mean age 21.6 years; 63.5% were white, 29.2% were black) enrolled in a required undergraduate health course at a southeastern state university. Results. Two hundred seventy-seven (86%) of the survey participants had heard about osteoporosis, but only 3.8% of respondents reported getting both adequate exercise and the recommended 1,200 mg of calcium per day. Respondents believed that they were unlikely to develop osteoporosis and that osteoporosis is less serious than other common causes of morbidity and mortality in women, such as heart disease and breast cancer (P < 0.0001). Brochures, magazines, and short counseling sessions were preferred information sources for learning about osteoporosis. Conclusions. The majority of young women studied are at risk for developing premature osteoporosis. They prefer brochures, magazines, and short counseling sessions during medical office visits to learn about osteoporosis. © 2001 by the American College of Rheumatology.
Keywords: calcium; adult; article; clinical trial; education program; female; health survey; human; human experiment; human tissue; morbidity; normal human; osteoporosis; patient counseling; patient information; risk assessment

Phase II study of dolastatin-10 in patients with hormone-refractory metastatic prostate adenocarcinoma - Vaishampayan, U.; Glode, M.; Du, W.; Kraft, A.; Hudes, G.; Wright, J.; Hussain, M. (Clinical Cancer Research, 2000)
Dolastatin-10 is a natural, cytotoxic peptide with microtubule-inhibitory and apoptotic effects. It has demonstrated in vitro and in vivo efficacy in the DU-145 human prostate cancer model. A Phase II clinical trial was designed in patients with hormone-refractory prostate cancer. Dolastatin-10 was administered at a dose of 400 μg/m2 i.v. every 3 weeks. Dose escalation to 450 μg/m2 was permitted. Toxicity evaluation was conducted every 2 weeks, and assessment of response was done at the end of every two cycles. Sixteen patients were enrolled between October 1998 to December 1999. The median age was 71 years (range, 59-79 years). Median prostate-specific antigen value was 108 ng/ml (range, 15.3-1672 ng/ml). Of the 15 eligible patients, 7 were Caucasian and 8 were African-American. Eight patients had bone-only metastases, and seven had measurable disease with or without bone metastases. A total of 56 cycles have been administered. Only 2 patients required dose adjustment because of toxicity, and in 5 patients, dose escalation was feasible to 450 μg/m2. The major toxicities observed were grade 3 and 4 neutropenia in 8 patients and grade 3 neuropathy in 1 patient. All 15 patients are evaluable for response. Three patients demonstrated stable disease; 2 of these had bone disease, and 1 had nodal metastasis. All others had disease progression. Dolastatin-10 is very well tolerated in this elderly, pretreated population but lacks significant clinical activity as a single agent.
Keywords: antineoplastic agent; dolastatin 10; estramustine; etoposide; paclitaxel; prostate specific antigen; vinblastine; adult; aged; article; bone metastasis; cancer chemotherapy; clinical article; clinical trial; drug efficacy; drug induced disease; drug safety; human; male; neutropenia; peripheral neuropathy; phase 2 clinical trial; priority journal; prostate adenocarcinoma; prostate cancer; vp 16

Black participation in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial. - Stallings, F.L.; Ford, M.E.; Simpson, N.K.; Fouad, M.; Jernigan, J.C.; Trauth, J.M.; Miller, D.S. (Controlled clinical trials, 2000)
The primary goal of the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial is to learn whether widespread use of screening tests to detect these cancers will reduce associated mortality. Blacks have the highest age-adjusted cancer incidence and mortality rates of any population group in the United States, but several barriers to their participation in clinical research such as the PLCO trial exist. These barriers involve sociocultural, economic, and individual factors, as well as factors inherent in trial designs. Population diversity in the PLCO trial is necessary to preserve scientific validity and generalizability of trial results. Therefore, the National Cancer Institute and the Centers for Disease Control and Prevention are collaborating to ensure adequate representation of blacks in the PLCO trial. For example, the agencies have funded several new activities designed to better understand and overcome barriers to participation in the trial. These activities include the African American Men Project, a randomized trial designed to evaluate the efficacy of three increasingly intensive recruitment interventions in recruiting black men; the establishment of a minority-focused PLCO trial screening center, a study to identify factors that influenced the decisions of black women recruited to participate in the PLCO trial; and a study to examine the psychosocial factors that influence blacks' decision making to engage in cancer screening and participation in research similar to the PLCO trial. The results of these activities will allow for a more thorough examination of cancer-related issues of importance to blacks and will help shed light on factors that influence their decisions to participate in cancer screening and prevention clinical trials.
Keywords: adult; African American; article; clinical trial; colorectal tumor; controlled clinical trial; female; human; lung tumor; male; mass screening; middle aged; minority group; multicenter study; ovary tumor; patient selection; prostate tumor; randomized controlled trial

Effect of timed incentives on subject participation in a study of long-term breast cancer survivors: are there ethnic differences? - Ashing-Giwa, K.; Ganz, P.A. (Journal of the National Medical Association, 2000)
The recruitment and retention of African Americans into cancer control studies presents a formidable task to the scientific and policy communities as well as patient and advocacy communities. The purpose of this investigation was to assess the role of a timed incentive schedule on response rates in a study of African American and white breast cancer survivors. A mailed quality-of-life survey battery was sent to 583 breast cancer survivors (50% African American, 50% white). Half of the participants received payment in advance, whereas the other half was promised payment. The overall response rate was 54% (n = 278). The timing of incentives did not affect participation rates in either ethnic group. About 51% of the respondents were from the payment-in-advance condition and 49% were from the paid-on-completion condition. Therefore, we conclude that payment on completion may be the more cost-effective approach in studies with higher socioeconomic status patients, such as this sample of breast cancer survivors.
Keywords: adult; African American; aged; article; breast tumor; clinical trial; controlled clinical trial; controlled study; ethnology; female; human; information processing; methodology; middle aged; patient selection; postal mail; psychological aspect; quality of life; randomized controlled trial; reward; time; United States

Recruitment experience in the first phase of the African American Hereditary Prostate Cancer (AAHPC) study. - Royal, C.; Baffoe-Bonnie, A.; Kittles, R.; Powell, I.; Bennett, J.; Hoke, G.; Pettaway, C.; Weinrich, S.; Vijayakumar, S.; Ahaghotu, C.; Mason, T.; Johnson, E.; et al. (Annals of epidemiology, 2000)
The African American Hereditary Prostate Cancer (AAHPC) Study is an ongoing multicenter genetic linkage study organized by Howard University and the National Human Genome Research Institute (NHGRI), with support from the Office for Research on Minority Health and the National Cancer Institute. The goals of the study are to: (i) look for evidence of involvement of chromosome 1q24-25 (HPC1) in African American men with hereditary prostate cancer (HPC) and (ii) conduct a genome-wide search for other loci associated with HPC in African American men. To accomplish these goals, a network has been established including Howard University, the NHGRI, and six Collaborative Recruitment Centers (CRCs). The CRCs are responsible for the identification and enrollment of 100 African American families. To date, 43 families have been enrolled. Recruitment strategies have included mass media campaigns, physician referrals, community health-fairs/prostate cancer screenings, support groups, tumor registries, as well as visits to churches, barber shops, and universities. By far, the most productive recruitment mechanisms have been physician referrals and tumor registries, yielding a total of 35 (81%) families. Approximately 41% (n = 3400) of probands initially contacted by phone or mail expressed interest in participating; the families of 2% of these met the eligibility criteria, and 75% of those families have been enrolled in the study, indicating a 0.5% recruitment yield (ratio of participants to contacts). As the first large-scale genetic linkage study of African Americans, on a common disease, the challenges and successes of the recruitment process for the AAHPC Study should serve to inform future efforts to involve this population in similar studies.
Keywords: African American; article; clinical trial; ethnology; family; genetics; human; male; patient selection; prostate tumor; procedures; United States

Minority recruitment in the prostate cancer prevention trial. - Moinpour, C.M.; Atkinson, J.O.; Thomas, S.M.; Underwood, S.M.; Harvey, C.; Parzuchowski, J.; Lovato, L.C.; Ryan, A.M.; Hill, M.S.; Deantoni, E.; Gritz, E.R.; Thompson Jr., I.M.; et al. (Annals of epidemiology, 2000)
PURPOSE: African American men have a higher prostate cancer risk profile than that of other men in the United States. The purpose of this manuscript is to summarize the challenges associated with enrolling and randomizing African American and other minority participants in the Prostate Cancer Prevention Trial (PCPT). METHODS: The PCPT is a randomized trial of finasteride versus placebo for preventing prostate cancer in healthy men age 55 years and older; it is coordinated by the Southwest Oncology Group. The manuscript describes demographic and lifestyle characteristics of the PCPT randomized sample (18,882 men) by four racial and ethnic groups (Caucasian, African American, Hispanic, and other). African American men comprised 4% of the total randomized sample compared to our goal of 8%. Minority recruitment was emphasized through the Study Manual and training that occurred at trial activation. Supplemental minority recruitment activities were initiated a year after study activation and continued through the end of the accrual period. Minority recruitment was emphasized as follows: minority recruitment presentations at PCPT training seminars (held during twice yearly Southwest Oncology Group meetings); distribution of additional minority recruitment materials; engagement of four consultants for minority recruitment; production of a Minority Recruitment Manual; and a small pilot study involving minority outreach recruiters at five PCPT sites. RESULTS: The consultants were helpful in implementing the pilot project and in suggesting and reviewing materials for minority recruitment. The five-site pilot project did not increase either enrollment or randomization of minorities (with a possible exception at one site). CONCLUSIONS: We suggest that a long-term perspective is required for successful recruitment of minority participants in clinical trials. Likewise, extensive minority recruitment efforts must be ready to implement at trial activation.
Keywords: finasteride; placebo; aged; article; clinical trial; controlled clinical trial; demography; ethnology; human; lifestyle; male; middle aged; minority group; patient selection; pilot study; prostate tumor; race; randomized controlled trial; statistics

Dealing with diversity: recruiting churches and women for a randomized trial of mammography promotion. - Derose, K.P.; Hawes-Dawson, J.; Fox, S.A.; Maldonado, N.; Tatum, A.; Kington, R. (Health education & behavior : the official publication of the Society for Public Health Education, 2000)
There is little documentation about the recruitment process for church-based health education programs. In this study, the authors recruit African American, Latino, and white churches and women members (age 50 to 80) for a randomized church-based trial of mammography promotion in Los Angeles County. Efforts to enhance recruitment began 10 months before churches were invited to participate and included a variety of community-based strategies. Subsequently, 45 churches were recruited over a 5-month period through group pastor breakfast meetings and church-specific follow-up. In close collaboration with the 45 churches, the authors administered church-based surveys over 6 months and identified 1,967 age-eligible women who agreed to be contacted by the program team. It was found that an extended resource intensive period of relationship-building and community-based activities were necessary to conduct church-based programs effectively, particularly among older and ethnically diverse urban populations.
Keywords: aged; article; breast tumor; clinical trial; controlled clinical trial; controlled study; ethnic group; female; health care planning; health education; health promotion; health services research; human; mammography; middle aged; motivation; organization and management; patient selection; public relations; randomized controlled trial; religion; United States; utilization review

Negotiating cultural consensus in a breast cancer self-help group. - Mathews, H.F. (Medical anthropology quarterly, 2000)
This article describes a shared model of the breast cancer experience negotiated by the members of a spontaneously organized breast cancer self-help group in eastern North Carolina. In the course of sharing their personal experience narratives with one another, these women worked to negotiate points of agreement among the varying sources of knowledge and oftentimes conflicting belief systems they held about breast cancer. The synthetic model they created rejected many of the assumptions underlying the dominant biomedical view of cancer "survivorship," particularly its emphasis on the autonomous individual as decision maker and its attendant male-gendered sports and military imagery--assumptions that often implicitly structured the agendas and topics discussed in the formal, medically sanctioned support groups these women found unappealing. The implications for theories about the construction of shared cultural models and for continuing efforts to design support groups to meet the needs of a diverse patient population are explored.
Keywords: African American; article; attitude to health; breast tumor; Caucasian; cognition; cultural anthropology; female; group process; human; interpersonal communication; patient participation; psychological aspect; psychological model; self help; social support; sociology; United States

A four-phase program to recruit African American women into breast cancer promotion programs. - Gibson, L.M. (The ABNF journal : official journal of the Association of Black Nursing Faculty in Higher Education, Inc, 2000)
The author discusses a successful, nurse-coordinated collaborative community-based breast health program that targeted older African American women from the state of South Carolina. Over 16 community organizations and health care partners supported the four-phase program that was funded by the South Carolina Breast and Cervical Risk Reduction Program and the South Carolina Chapter of the American Cancer Society.
Keywords: African American; aged; article; attitude to health; breast tumor; education; ethnology; female; feminism; health education; health promotion; health service; human; mass screening; middle aged; nursing; organization and management; patient selection; poverty; program development; psychological aspect; public relations; United States

Percentage of free PSA in black versus white men for detection and staging of prostate cancer: A prospective multicenter clinical trial - Catalona, W.J.; Partin, A.W.; Slawin, K.M.; Naughton, C.K.; Brawer, M.K.; Flanigan, R.C.; Richie, J.P.; Patel, A.; Walsh, P.C.; Scardino, P.T.; Lange, P.H.; Dekernion, J.B.; et al. (Urology, 2000)
Objectives. In predominately white populations, measurement of the percentage of free prostate-specific antigen (%fPSA) has been shown to enhance the specificity of total PSA testing for prostate cancer while maintaining high sensitivity and to aid in prostate cancer staging. This study evaluated whether the %fPSA cutoff that maintained a 95% sensitivity in a white population yielded the same sensitivity and specificity in a black population and whether %fPSA was useful in predicting postoperative pathologic features in blacks.Methods. We evaluated 647 white and 79 black men, prospectively enrolled at prostate cancer screening and surgical referral centers. Subjects were 50 to 75 years old with digital rectal examination findings that were not suspicious for prostate cancer and total PSA values between 4.0 and 10.0 ng/mL. All had undergone needle biopsy of the prostate. Hybritech's Tandem total and free PSA assays were used.Results. Ninety-five percent sensitivity was attained with a %fPSA cutoff of 25% in both races. Use of this cutoff could have avoided unnecessary biopsies in 20% of white and 17% of black subjects (P = 0.69). In receiver operating characteristic (ROC) curve analysis, the area under the curve (AUC) for %fPSA was significantly higher than for total PSA in both blacks (0.76 versus 0.56, P <0.01) and whites (0.70 versus 0.54, P <0.001). In both races, higher %fPSA values indicated a lower risk of cancer and also predicted favorable pathologic features in radical prostatectomy specimens.Conclusions. A 25% fPSA cutoff detected 95% of cancers and reduced unnecessary biopsies in both races. Higher %fPSA values were associated with favorable postoperative histopathologic findings in both races. Copyright (C) 2000 Elsevier Science Inc.
Keywords: prostate specific antigen; adult; aged; antigen detection; article; cancer staging; Caucasian; clinical trial; controlled clinical trial; controlled study; diagnostic accuracy; ethnic difference; human; human tissue; major clinical study; male; multicenter study; Black person; priority journal; prognosis; prospective study; prostate cancer; statistical analysis; tumor biopsy

The Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial of the National Cancer Institute: history, organization, and status. - Gohagan, J.K.; Prorok, P.C.; Hayes, R.B.; Kramer, B.S. (Controlled clinical trials, 2000)
The Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial is enrolling 148,000 men and women ages 55-74 at ten screening centers nationwide with balanced randomization to intervention and control arms. For prostate cancer, men receive a digital rectal examination and a blood test for prostate-specific antigen. For lung cancer, men and women receive a posteroanterior view chest X-ray. For colorectal cancer, men and women undergo a 60-cm flexible sigmoidoscopy. For ovarian cancer, women receive a blood test for the CA125 tumor marker and transvaginal ultrasound. Members of the control arm continue with their usual care. Follow-up in both groups will continue for at least 13 years from randomization to assess health status and cause of death. The primary endpoint is mortality from the four PLCO cancers, which accounts for about 53% of all cancer deaths in men and 41% of cancer deaths in women in the United States each year. Blood specimens are collected from screened participants, buccal cell DNA from controls, and histology slides from cases; these are maintained in a biorepository. Participants complete a baseline questionnaire (covering health status and risk factors) and a dietary questionnaire. More than 12,000 participants were enrolled in the pilot phase (concluded in September 1994). Changes in the eligibility criteria followed. As of April 2000, enrollment exceeded 144,500. Data are scanned into designated on-site computers for uploading by participant identification number to the coordinating center for quality checks, archival storage, and preparation of analysis datasets for use by the National Cancer Institute (NCI). Scientific direction is provided by NCI scientists, trial investigators, external consultants, and an independent data safety and monitoring board. Performance and data quality are monitored via data edits, site visits, random record audits, and teleconferences. The PLCO trial is formally endorsed by the American Cancer Society and has been ranked by the American Urological Association as one of the most important prostate cancer studies being conducted. Special efforts to enroll black participants are cosponsored by the U.S. Centers for Disease Control and Prevention.
Keywords: aged; article; clinical trial; colorectal tumor; controlled clinical trial; female; human; information processing; international cooperation; lung tumor; male; mass screening; middle aged; multicenter study; ovary tumor; patient selection; prostate tumor; randomized controlled trial

Underrepresentation of patients 65 years of age or older in cancer- treatment trials - Hutchins, L.F.; Unger, J.M.; Crowley, J.J.; Coltman Jr., C.A.; Albain, K.S. (New England Journal of Medicine, 1999)
Background: Studies have documented the underrepresentation of women and blacks in clinical trials, and their recruitment is now federally mandated. However, little is known about the level of participation of elderly patients. We determined the rates of enrollment of patients 65 years of age or older in trials of treatment for cancer. Methods: We analyzed data on 16,396 patients consecutively enrolled in 164 Southwest Oncology Group treatment trials between 1993 and 1996 according to sex, race (black or white), and age under 65 years or 65 or older. These rates were compared with the corresponding rates in the general population of patients with cancer, derived from the 1990 U.S. Census and from the National Cancer Institute's Surveillance, Epidemiology, and End Results Program for the period from 1992 through 1994. Fifteen types of cancer were included in the analysis. Results: The overall proportions of women and blacks enrolled in Southwest Oncology Group trials were similar to or the same as the estimated proportions in the U.S. population of patients with cancer (women, 41 percent and 43 percent; blacks, 10 percent and 10 percent, respectively). In contrast, patients 65 years of age or older were underrepresented overall (25 percent vs. 63 percent, P<0.001) and in trials involving all 15 types of cancer except lymphoma. The underrepresentation was particularly notable in trials of treatment for breast cancer (9 percent vs. 49 percent, P<0.001). The findings were similar when data on patients who were 70 years of age or older were analyzed, when 15 trials that excluded older patients were eliminated from the analysis, and when community-based enrollment was analyzed separately from enrollment at academic centers. Conclusions: There is substantial underrepresentation of patients 65 years of age or older in studies of treatment for cancer. The reasons should be clarified, and policies adopted to correct this underrepresentation.
Keywords: adult; age; aged; article; cancer patient; cancer research; controlled study; female; human; major clinical study; male; methodology; Black person; population research; priority journal; sex difference

Factors associated with weight gain in women after diagnosis of breast cancer - Rock, C.L.; Flatt, S.W.; Newman, V.; Caan, B.J.; Haan, M.N.; Stefanick, M.L.; Faerber, S.; Pierce, J.P. (Journal of the American Dietetic Association, 1999)
Objective: To identify the factors associated with weight gain after diagnosis of breast cancer in a heterogeneous population of women. Design: Descriptive cross-sectional study. Subjects: 1,116 patients who had been diagnosed with stage I, stage II, or stage IIIA primary, operable breast cancer within the previous 4 years. Patients were recruited during enrollment into a diet intervention trial to reduce risk for breast cancer recurrence. Analysis Demographic data, weight history, and physical activity information obtained by questionnaire and medical information obtained by chart review; dietary assessment based on four 24-hour dietary recalls collected by telephone. Associations between weight change after the diagnosis of breast cancer and prediction variables were examined using univariate and multiple linear regression analyses. Results: Overall, 60% of the subjects reported weight gain, 26% reported weight loss, and 14% reported no change in weight after the diagnosis of breast cancer. The overall mean weight change was a gain of 2.7 kg (6 lb). Factors positively and independently associated with weight gain were time since diagnosis of breast cancer, adjuvant chemotherapy, African-American ethnicity, current energy intake, and postmenopausal status at time of study entry. Factors inversely and independently associated with weight gain were prediagnosis body mass index, age at diagnosis, education level, and exercise index score. Applications: Higher energy intake and lower level of physical activity are independently associated with increased risk for weight gain after the diagnosis of breast cancer. Strategies to modify these behaviors are likely to influence the long-term pattern of weight change.
Keywords: cyclophosphamide; doxorubicin; fluorouracil; methotrexate; adjuvant chemotherapy; adult; aged; article; breast cancer; caloric intake; demography; disease association; female; human; major clinical study; nutrition; physical activity; postmenopause; recurrence risk; risk factor; body weight gain

The recruitment of breast cancer survivors into cancer control studies: a focus on African-American women. - Ashing-Giwa, K. (Journal of the National Medical Association, 1999)
The recruitment of African Americans into cancer prevention and control studies has presented a major challenge to scientific investigators. Scientific findings, whether biomedical or behavioral, may not be appropriate and applicable to ethnic minority populations unless they are adequately represented as study participants. Moreover, the need to involve greater numbers of ethnic minorities is quite urgent due to the poor morbidity and mortality outcomes associated with ethnic minority group membership. Such is the case with breast cancer survivorship. The purpose of the study was to test a personalized recruitment strategy on response rate in African-American women. The response rate of 45% (n = 117) African Americans and 64% (n = 161) white subjects indicated only limited success in the recruitment of the African-American breast cancer survivors. The recruitment result suggests that culturally relevant recruitment strategies (e.g., inclusion of African-American investigators, culturally consistent letter of recruitment) may be insufficient in adequately increasing research participation. Therefore, further studies on investigating factors that influence research participation (eg, type of incentives, and schedule of payment as well as type of stationery and stamps used) are needed.
Keywords: African American; article; breast tumor; Caucasian; ethnology; female; human; middle aged; mortality; Black person; patient selection; statistics

Factors associated with attendance in a voluntary nutrition education program - Damron, D.; Langenberg, P.; Anliker, J.; Ballesteros, M.; Feldman, R.; Havas, S. (American Journal of Health Promotion, 1999)
Purpose. This paper examines factors associated with attendance in a National Cancer Institute-funded randomized trial of nutrition education to increase fruit and vegetable consumption among women served by the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). Setting. The study took place at 16 WIC sites in Maryland. Subjects. The participants were 1528 women who were enrolled in WIC or who had children enrolled in WIC, were ≥ 18 years of age, and planned to continue enrollment at that WIC site for at least 6 months (68 % of eligible women approached agreed to participate). Intervention. Women received personal invitations, letters, and telephone reminders from peer educators encouraging their attendance at three bimonthly nutrition sessions. Measures. Demographic data were collected in a baseline survey. Attendance data and telephone and address changes were also collected. The postintervention survey included a question regarding reasons for nonattendance. Focus groups were also held to ascertain reasons for attendance or nonattendance. Chi-square tests of trend and multiple logistic regression, adjusted for within-site correlation, were used in statistical analyses. Results. Fifty-four percent of enrollees attended at least one session. Multiple logistic regression analysis showed increased odds of attending with higher age, breast-feeding, and/or knowledge of the recommendation to eat five or more servings of fruits and vegetables daily. There were decreased odds of attending for pregnant women who already had children. There were nonsignificant trends toward decreased attendance among unmarried women compared with married women and among blacks compared with nonblacks. Reasons given for nonattendance included withdrawal from WIC, moving, conflicting activities, negative feelings about nutrition education, and lack of transportation or child care. Conclusions. The results suggest that numerous barriers hinder participation in nutrition programs aimed at low-income women. These barriers' should be considered by health care professionals when planning intervention programs. Overcoming these barriers presents a major challenge.
Keywords: article; female; health education; human; normal human; nutritional deficiency; nutritional requirement; nutritional value; statistical analysis; United States

Phase II trial of pyrazine diazohydroxide in androgen-independent prostate cancer - Edelman, M.J.; Meyers, F.J.; Grennan, T.; Lauder, J.; Doroshow, J. (Investigational New Drugs, 1998)
No effective therapy has been demonstrated for hormone refractory prostate cancer (HRPC). Pyrazine diazohydroxide (PZDH) is a novel antineoplastic agent with a broad range of activity in preclinical studies and a moderate toxicity profile in Phase I trials. We undertook a Phase II study of PZDH in HRPC utilizing decline in PSA as the primary end point. Fifteen patients were enrolled, median age of 70 (55-86), median pretherapy PSA 206 ng/ml (range 42-10,000). Four patients were African American. Sites of disease: bone only 7, soft tissue only 2, both 6. All were evaluable for toxicity and response. PZDH was administered at 250 mg/m2 IV every three weeks. The median number of cycles administered was two (range 1-6). Toxicity was mild, with only one patient manifesting serious (grade 3-4) toxicity. Unfortunately, activity was minimal with only a single patient demonstrating a > 75% decline in PSA. As this patient's PSA began to rise almost immediately the response was considered transient and not felt to justify pursuing a second stage of the trial. Supporting this conclusion was the disappointing median survival of 220 days. in summary, we conclude that PZDH, while well tolerated at this dose and schedule has only minimal activity in HRPC.
Keywords: antineoplastic agent; prostate specific antigen; pyrazine diazohydroxide; adult; aged; article; cancer survival; clinical article; clinical trial; human; intravenous drug administration; male; neutropenia; phase 2 clinical trial; priority journal; prostate cancer; survival time; thrombocytopenia

Effects of dialogue and therapeutic touch on preoperative and postoperative experiences of breast cancer surgery: an exploratory study. - Samarel, N.; Fawcett, J.; Davis, M.M.; Ryan, F.M. (Oncology nursing forum, 1998)
PURPOSE/OBJECTIVES: To obtain preliminary data and determine the feasibility of a large-scale experimental study to test the efficacy of the Rogerian Science of Unitary Human Beings-based intervention of dialogue and therapeutic touch (TT) on pre- and postoperative anxiety and mood and postoperative pain from breast cancer surgery. DESIGN: Experimental. SETTING: Mid-Atlantic region; ambulatory. SAMPLE: 29 Caucasian and 2 African American English-speaking women with positive breast cancer biopsy (experimental, n = 14; control, n = 17), ranging in age from 31-84 years old (F = 55.6). METHODS: Treatments administered in subjects' homes within seven days prior to surgery and 24 hours after hospital discharge. Experimental treatment consisted of 10 minutes of TT and 20 minutes of dialogue. Control treatment consisted of 10 minutes of quiet time and 20 minutes of dialogue. Data (Spielberger State-Trait Anxiety Inventory. Affects Balance Scale, and Visual Analog Scale-Pain) were collected at the conclusion of each home visit. MAIN RESEARCH VARIABLES: Anxiety, mood, and pain. FINDINGS: The experimental group had lower preoperative state anxiety than the control groups (p = 0.008). No difference was found for preoperative mood. No differences were found for any postoperative measure. CONCLUSIONS: A large-scale study of dialogue and TT would require changes in design and recruitment strategies. IMPLICATIONS FOR NURSING PRACTICE: Nurses may provide more comprehensive care by incorporating dialogue and TT or quiet time into their pre- and postoperative care. Additional research, however, is recommended to determine the differential effects of dialogue, TT, and quiet time on women's experiences with breast cancer prior to incorporating these noninvasive modalities into clinical practice.
Keywords: adult; affect; aged; alternative medicine; anxiety; article; breast tumor; clinical trial; controlled clinical trial; controlled study; female; human; interpersonal communication; middle aged; nurse patient relationship; nursing; nursing methodology research; postoperative care; preoperative care; psychological aspect

Recruiting black men to a clinical trial to evaluate prostate cancer screening--Detroit, Michigan, 1998. (MMWR. Morbidity and mortality weekly report, 1998)
In 1998, an estimated 184,500 cases of prostate cancer will be diagnosed and approximately 39,200 men will die from this disease (1). Black men have higher prostate cancer incidence and mortality rates than white men (2). Representation of blacks in clinical trials that investigate the treatment of cancer is proportional to the burden of this disease in the black population (3). However, blacks have generally been underrepresented in clinical trials of preventive interventions (4). To determine the effect of socioeconomic status (SES) on the enrollment of black men in a trial that includes screening for prostate cancer, the African American Men (AAMEN) project in Detroit, Michigan, analyzed data from local recruitment efforts. This report summarizes preliminary results of this analysis, which indicate that SES was not an important factor in refusal to participate in the screening trial.
Keywords: African American; aged; article; clinical protocol; clinical trial; ethnology; human; male; middle aged; Black person; patient selection; prostate tumor; United States

Prostate cancer education in African American churches. - Weinrich, S.; Holdford, D.; Boyd, M.; Creanga, D.; Cover, K.; Johnson, A.; Frank-Stromborg, M.; Weinrich, M. (Public health nursing (Boston, Mass.), 1998)
The use of churches as recruitment sites of African Americans into health promotion activities is a popular theme in the 1990s literature. This research measured the impact of previous exposure to cancer on participation in an educational program and a free prostate cancer screening. Cues to action from the Health Belief Model provided the conceptual framework. Over 500 men attended a prostate cancer educational program at their church. Men who participated in the educational program and completed the questionnaire were given a voucher that they could take to their doctor of choice for a free prostate cancer examination. Having a member of the congregation who was previously diagnosed with cancer was a significant cue to attendance at the educational program (P = 0.03). Recommendations for future cancer screening in churches are given.
Keywords: African American; article; community health nursing; counseling; ethnology; health care quality; health education; health promotion; human; male; mass screening; middle aged; organization and management; patient selection; prostate tumor; questionnaire; United States

Sociodemographic analysis of patients in Radiation Therapy Oncology Group clinical trials - Chamberlain, R.M.; Winter, K.A.; Vijayakumar, S.; Porter, A.T.; Roach III, M.; Streeter, O.; Cox, J.D.; Bondy, M.L. (International Journal of Radiation Oncology Biology Physics, 1998)
Purpose: To assess the degree to which the sociodemographic characteristics of patients enrolled in Radiation Therapy Oncology Group (RTOG) clinical trails are representative of the general population. Methods and Materials: Sociodemographic data were collected on 4016 patients entered in 33 open RTOG studies between July 1991 and June 1994. The data analyzed included educational attainment, age, gender, and race. For comparison, we obtained similar data from the U.S. Department of Census. We also compared our RTOG data with Surveillance Epidemiology and End Results (SEER) data for patients who received radiation therapy, to determine how RTOG patients compared with cancer patients in general, and with patients with cancers at sites typically treated with radiotherapy. Results: Overall, the sociodemographic characteristics of patients entered in RTOG trials were similar to those of the Census data. We found that, in every age group of African-American men and at nearly every level of educational attainment the proportion of RTOG trial participants mirrored the proportion in the census data. Significant differences were noted only in the youngest category of African-American men, where the RTOG accrues more in the lower educational categories and fewer with college experience. For African-American women, we found a similar pattern in every age group and at each level of educational attainment. As with men, RTOG trials accrued a considerably larger proportion of younger, less educated African-American women than the census reported. Using SEER for comparison, the RTOG enrolled proportionately more African- American men to trials all cancer sites combined, and for prostate and head and neck cancer. In head and neck trials, the RTOG enrolled nearly twice as many African-American men than would be predicted by SEER data. In lung cancer trials, RTOG underrepresented African-American men significantly; however, there was no difference for brain cancer trials. There were no racial differences in RTOG accrual and SEER incidence data for women on trials in brain, lung, and head and neck cancer. However, the RTOG trials accrued nearly twice the proportion of African-American women in cervical cancer trials and in all sites combined, compared to the SEER data. Conclusions. Comparisons with the U.S. Census and SEER show that African- Americans are proportionally well represented in cancer clinical trials conducted by the Radiation Therapy Oncology Group. The comparative analysis indicates that all educational levels in each age group of African-Americans generally mirror the U.S. Census, with one exception. The exception is a significant overrepresentation of less-educated African-Americans in the youngest age category. This exception is counter to the expectation that better-educated patients are more likely to enroll in trials. When compared with SEER data the RTOG trials either parallel or overrepresent African- American men and women, with the only exception being in lung cancer, where men are underrepresented. These results show that, in comparison to the Census and SEER data, the RTOG has fulfilled its commitment to enroll African-American patients in its clinical trials.
Keywords: article; cancer epidemiology; cancer radiotherapy; cancer survival; Caucasian; data analysis; demography; head and neck cancer; human; lung cancer; major clinical study; Black person; patient education; priority journal; race difference; sociology; treatment indication; treatment planning; uterine cervix cancer

Effect of a cancer screening intervention conducted by lay health workers among inner-city women - Sung, J.F.C.; Blumenthal, D.S.; Coates, R.J.; Williams, J.E.; Alema-Mensah, E.; Lill, J.M. (American Journal of Preventive Medicine, 1997)
Introduction: We conducted a randomized controlled trial to determine if an in-home educational intervention conducted by lay health workers (LHWs) could increase adherence among low-income, inner-city, African-American women to breast and cervical cancer screening schedules. Methods: We recruited 321 African-American women from diverse inner-city sources. After baseline interviews, they were randomly assigned to either the intervention (n = 163) or the control (n = 158) group. Those in the intervention group were visited in their homes up to three times by LHWs who provided a culturally sensitive educational program that emphasized the need for screening. Results: Ninety- three (93) women in the intervention group and 102 in the control group completed the postintervention interview. For Pap smears, the increase in screening was similar in both groups. For clinical breast exams (CBEs), however, there was a modest increase in the intervention group. The improvement was greatest for mammography, for which there was a 10% to 12% increase. Among women who were not on recommended schedules at baseline, the improvement was substantial and greater in the intervention group. Conclusions: LHWs' intervention appeared to improve the rate at which inner- city women obtained CBEs and mammograms, but had no effect on Pap smears. A high attrition rate weakened our ability to make conclusive statements about the exact impact of the intervention. Medical Subject Headings (MESH): intervention studies, Papanicolaou smear, mammography, urban health, health services, indigenous community health aides, breast.
Keywords: adult; article; breast cancer; cancer screening; controlled study; early diagnosis; female; health care utilization; human; major clinical study; mammography; Black person; Papanicolaou test; patient compliance; patient education; urban population; uterine cervix cancer

Screening and prevention trials step up minority recruitment. - Reynolds, T. (Journal of the National Cancer Institute, 1996)
Keywords: African American; article; breast tumor; clinical trial; female; Hispanic; human; male; mass screening; minority group; neoplasm; prostate tumor; statistics; United States

The recruitment of African-Americans to cancer prevention and control studies - Paskett, E.D.; DeGraffinreid, C.; Tatum, C.M.; Margitić, S.E. (Preventive Medicine, 1996)
Background. African-Americans have the highest overall age-adjusted cancer incidence and mortality rates of any population group in the United States. Despite this fact, this group remains underrepresented in cancer prevention and control research studies, primarily because most recruitment strategies result in limited access to African-American populations. Methods. As part of three large-scale cancer prevention and control studies, effective strategies for recruiting African-American participants were developed and implemented. Results. Eight strategies have been identified as successful recruitment strategies for involving African-Americans in cancer prevention and control studies. Utilizing these strategies resulted in recruiting a representative number of African-American participants, in relation to the local population, into the three studies. Conclusions. African-Americans can be recruited to participate in cancer control and prevention studies if plans include special strategies targeted to addressing unique barriers, beliefs, and concerns.
Keywords: article; breast cancer; cancer control; cancer incidence; cancer mortality; cancer prevention; cancer screening; clinical trial; colon polyp; double blind procedure; ethnic group; female; human; major clinical study; male; multicenter study; Black person; phase 3 clinical trial; priority journal; prostate cancer

Representation of African-Americans, Hispanics, and whites in National Cancer Institute cancer treatment trials - Tejeda, H.A.; Green, S.B.; Trimble, E.L.; Ford, L.; High, J.L.; Ungerleider, R.S.; Friedman, M.A.; Brawley, O.W. (Journal of the National Cancer Institute, 1996)
Background: The National Cancer Institute (NCI)-sponsored clinical trials cooperative groups place more than 25 000 American patients in treatment trials every year. Equal access and proportional representation of all races/ethnicities is desired. Purpose: Our objectives were to evaluate the inclusion of African-Americans, Hispanics, and non-Hispanic whites in NCI- sponsored treatment trials and to determine if there is proportional racial/ethnic representation. Methods: During the period of January 1, 1991, through June 30, 1994, 99 495 cancer patients were enrolled in clinical trials and declared themselves as non-Hispanic black, non-Hispanic white, or Hispanic (of any race). In the analysis, participants in NCI treatment trials were subdivided into three age groups: birth to 19 years, 20-49 years, and 50 or more years. The racial/ethnic composition of each of these age groups was compared with the racial/ethnic makeup of the American population with cancer. Estimates of the number of incident cancer cases per year were made for each racial/ethnic group within each age group using data from the Surveillance, Epidemiology, and End Results (SEER) Program and the 1990 Census. The percentage of all cancer patients who were in each racial/ethnic group were compared with the population that entered clinical trials. Comparisons are also made separately for patients with leukemia and breast, colorectal, lung, and prostate cancers. Results: Among patients 0-19 years old, 20-49 years old, and 50 years old or older there is relatively proportional representation of non-Hispanic blacks, Hispanics, and non- Hispanic whites in trials. It is noted that more than 70% of cancer patients aged 0-19 years are estimated to enter cooperative group clinical trials compared with 4.0% of cancer patients aged 20-49 years and 1.5% of patients aged 50 years or older. Conclusions: Accrual of American cancer patients to NCI-sponsored treatment trials generally parallels the incident burden of disease among non-Hispanic African-Americans, Hispanics, and non-Hispanic whites. Implications: This study shows that the NCI clinical trials are, as a whole, racially/ethnically representative of the American population and suggests that there is equal access to NCI clinical trials.
Keywords: article; malignant neoplasm; cancer epidemiology; cancer patient; cancer risk; Caucasian; ethnic group; ethnology; human; major clinical study; Black person; race

Attitudes of African-Americans regarding prostate cancer clinical trials - Robinson, S.B.; Ashley, M.; Haynes, M.A. (Journal of Community Health, 1996)
The purpose of this study was to qualitatively assess attitudes associated with the willingness of African-Americans to participate in prostate cancer clinical trials. Fifty-six African-American males, 40 years of age and older, were recruited from South Central Los Angeles. Respondents were divided into lower or middle socio-economic groups based on education and occupation. Focus group discussions were conducted to assess their knowledge about prostate cancer and willingness to participate in prostate cancer clinical trials. In addition, information was obtained to identify their incentives and barriers toward participating in prostate cancer research. Middle socio- economic respondents expressed a greater willingness to participate in prostate cancer clinical trials than did men of lower socio-economic status. Many indicated that they would be more likely to participate if they were encouraged to do so by a physician or researcher who was viewed as being competent and compassionate. Barriers to participation in prostate cancer clinical trials included concerns about drug toxicity, medical experimentation and distrust of the medical establishment. Endeavors aimed at increasing minority representation in prostate cancer clinical studies should address these issues.
Keywords: adult; article; cancer research; clinical trial; controlled clinical trial; controlled study; human; major clinical study; male; Black person; patient attitude; prostate cancer; socioeconomics

Evaluation of race as a prognostic factor in multiple myeloma: An ancillary of Southwest Oncology Group study 8229 - Modiano, M.R.; Villar-Werstler, P.; Crowley, J.; Salmon, S.E. (Journal of Clinical Oncology, 1996)
Purpose: The objective of this investigation was to assess the impact of race (black v white) on the survival of patients with multiple myeloma treated within the context of a large clinical trial. Patients and Methods: A cohort of patients randomized to receive one of two treatment regimens and monitored for at least 10 years was studied to assess the impact of race as a prognostic factor, after adjusting for other known factors such as stage of disease. Patients were recruited from the referral network of the Southwest Oncology Group (SWOG), a national multiinstitutional consortium that includes both academic and community treatment centers. Patients had a diagnosis of multiple myeloma and had not previously been treated for this disease. They were carefully characterized as to demographic and clinical features, and were randomized to receive one of two treatment regimens, which proved to have virtually identical outcomes. The outcome measure was survival, measured from the date of randomization to the date of last contact. Patients still alive at last contact date were treated as censored observations. Results: Survival for black myeloma patients was similar to that for white patients, both overall and adjusted for prognostic factors such as stage. Conclusion: Observed differences in mortality between blacks and whites cannot be attributed to differences in survival after diagnosis, given comparable treatment.
Keywords: adult; aged; article; cancer staging; cancer survival; female; human; major clinical study; male; multiple myeloma; priority journal; prognosis; race; treatment outcome

Frequencies of opportunistic diseases prior to death among HIV-infected persons - Chan, I.S.F.; Neaton, J.D.; Saravolatz, L.D.; Crane, L.R.; Osterberger, J. (AIDS, 1995)
Objectives: To describe the complete history of major opportunistic events experienced by 1883 HIV-infected persons prior to and specifically within 6 months of death, and to determine whether the frequency of specific events varies according to demographic characteristics, risk behaviors or geographic location. Design: Descriptive case series. Methods: Of 6682 HIV-infected individuals enrolled in studies sponsored by the Community Programs for Clinical Research on AIDS between September 1990 and June 1994, 1883 died during follow-up. A complete history of AIDS-defining events was determined for these patients by combining medical history data obtained at the time of enrollment, new events that occurred during follow-up, and causes of death. Results: The most common opportunistic AIDS-defining events these 1883 patients experienced before death were Pneumocystis carinii pneumonia (PCP; 45%), Mycobacterium avium complex (MAC; 25%), wasting syndrome (25%), bacterial pneumonia (24%), cytomegalovirus (CMV) disease (23%) and candidiasis (esophageal or pulmonary; 22%). In addition, 47% of patients experienced two or three AIDS-defining events before death, and 22% experienced four or more events. In the 6 months prior to death, 22% of patients had PCP, 21% had MAC, and 20% had CMV disease. Significant sex and ethnic differences were found: bacterial pneumonia occurred more often before death in women compared with men; fewer blacks and Latinos than whites experienced Kaposi's sarcoma (KS); and fewer blacks than whites had CMV disease before death. The percentage of patients with KS and CMV also varied by risk behavior. The frequency of 10 opportunistic diseases varied by geographic region after adjustment for demographic characteristics and risk behavior. Of note, many more patients in northeastern USA had tuberculosis and fewer had MAC. Conclusion: A large percentage of individuals with HIV infection experienced multiple AIDS-defining opportunistic diseases before death. PCP, MAC, wasting syndrome, bacterial pneumonia, CMV disease, and candidiasis (esophageal or pulmonary) account for a substantial proportion of morbidity associated with HIV infection. More diseases varied by geographic location than by demographic characteristics or risk behavior of patients. Continued research on the etiology and prevention of these diseases and how they relate to one another should be a high priority.
Keywords: article; bacterial pneumonia; behavior; candidiasis; cause of death; clinical research; cytomegalovirus infection; death; demography; ethnic difference; female; follow up; gender; human; Human immunodeficiency virus infection; Kaposi sarcoma; major clinical study; male; medical record; muscle atrophy; Mycobacterium avium complex; opportunistic infection; Pneumocystis pneumonia; priority journal; tuberculosis

Is cost a barrier to screening mammography for low-income women receiving medicare benefits? A randomized trial - Kiefe, C.I.; McKay, S.V.; Halevy, A.; Brody, B.A. (Archives of Internal Medicine, 1994)
Background: In 1991, Medicare began covering screening mammograms subject to copayment and deductible. This study evaluated the effectiveness of Medicare in removing financial barriers to screening mammography among low- income older women. Methods: In an inner-city public hospital's General Medicine Clinic, 119 consecutive, eligible, and consenting Medicare-enrolled women without known risk factors for breast cancer other than age, and no mammogram in the previous 2 years, were entered into a randomized controlled trial with follow-up after 2 months. The mean age was 71 years; 77% were black, 92% had an annual income below $10 000, and 52% had had a previous mammogram. All patients were counseled concerning indications for screening mammograms and Medicare coverage, and all were referred to a low-cost mammography facility. Sixty-one subjects were randomly assigned a voucher for a free screening mammogram at the referral facility. Obtaining a mammogram within 60 days of study entry was the main outcome measure. Results: Of the women given vouchers, 27 (44%) obtained screening mammograms, compared with six (10%) of those without vouchers (P<.001). Adjustment by multiple logistic regression confirmed this association, yielding an adjusted odds ratio of 7.4 (95% confidence interval, 2.5 to 21.4). Knowledge concerning mammography and breast cancer increased significantly overall (and within randomization groups) between initial interview and follow-up; fear did not change. For women without the voucher, the main reason for not obtaining a mammogram was financial; the main reason for women with the voucher was transportation. Conclusion: In a low-income, inner-city population of older women, financial barriers to screening mammography persist despite Medicare coverage.
Keywords: adult; aged; article; breast cancer; cancer screening; female; health behavior; health care cost; health care policy; health insurance; human; lowest income group; major clinical study; mammography; medicare; patient attitude; patient compliance; patient counseling; priority journal; reimbursement

Cancer screening intervention among black women in inner-city Atlanta - Design of a study - Sung, J.F.C.; Coates, R.J.; Williams, J.E.; Liff, J.M.; Greenberg, R.S.; McGrady, G.A.; Avery, B.Y.; Blumenthal, D.S. (Public Health Reports, 1992)
This experimental study attempts to determine if an in-home educational intervention conducted by lay health workers (LHWs) can increase adherence among low-income, inner-city black women to schedules for screening for breast cancer and cervical cancer, as well as increase the women's knowledge and change their attitudes regarding these cancers. This paper is a description of the purposes, hypotheses, design, subject recruitment, intervention, and evaluation of the study conducted by Morehouse School of Medicine. Subjects were recruited from a variety of sources, including patients seen in a community health center, women referred by the National Black Women's Health Project (NBWHP), residents of public and senior citizen housing projects, and persons identified in various community settings. Fewer than half of those asked to participate agreed to do so. The 321 women who were recruited were demographically diverse. Overall, about half of these volunteer subjects self-reported at least one Papanicolaou (Pap) smear and one breast examination within a year before enrollment in the study. There was little variation by source of recruitment in compliance with screening recommendations, except that referrals from NBWHP were more likely (P<0.01) to have had a Pap test and breast self-examination, while residents of public housing projects were somewhat less likely to have done so. About 35 percent of participants ages 35 and older had a mammogram within an appropriate interval. Participants were randomly assigned to intervention and control groups. Women in the intervention group were visited in their homes by LHWs on three occasions; the LHWs provided education on cancer and reproductive health. The groups were comparable in their baseline sociodemographic status and previous screening history.
Keywords: adult; aged; article; attitude; breast cancer; breast examination; cancer screening; cancer survival; clinical trial; controlled study; demography; female; health care personnel; health education; health insurance; human; major clinical study; mammography; marriage; Black person; Papanicolaou test; priority journal; randomized controlled trial; social status; United States; uterine cervix cancer